Alzheimer's disease-related cortical proteins modify the association of brain insulin signaling with cognitive decline. - Tong, Han; Petyuk, Vladislav A; Sendtner, Michael; Sood, Ajay; Bennett, David A; Capuano, Ana W; Arvanitakis, Zoe (J Alzheimers Dis, 2025)
BackgroundBrain insulin signaling has been associated with both Alzheimer's disease (AD) pathology and cognitive decline, but the mechanisms remain unclear.ObjectiveTo examine whether AD-related cortically-expressed proteins modify the association of brain insulin signaling and cognitive decline.MethodsParticipants included 116 autopsied members of the Religious Orders Study (58 with diabetes matched to 58 without, by age at death, sex, and education) who had both postmortem brain (prefrontal cortex) insulin signaling (by ELISA and immunohistochemistry, including RAC-alpha serine/threonine-protein kinase or AKT1) and AD-related cortical protein measurements. Levels of five AD-related proteins including insulin-like growth factor-binding protein-5 (IGFBP-5) and inositol-tetrakisphosphate 1-kinase (ITPK1) were measured using quantitative proteomics. We conducted adjusted linear mixed model analyses to examine associations of insulin signaling measures and AD-related proteins with longitudinally assessed cognitive function.ResultsHigher levels of IGFBP-5 and lower levels of ITPK1 were each associated with higher levels of AKT1 phosphorylation (pTAKT1 /total AKT1). Additionally, higher levels of AKT1 phosphorylation were associated with faster decline in global cognition and most cognitive domains. IGFBP-5 partially mediated the association of AKT1 phosphorylation with the decline rate of global cognition and cognitive domains including perceptual speed and visuospatial abilities. Further, ITPK1 had an interaction with AKT1 phosphorylation on decline of global cognition and domains including episodic memory, perceptual speed, and visuospatial abilities.ConclusionsAD-related proteins IGFBP-5 and ITPK1 are each associated with insulin signaling AKT1 phosphorylation in the postmortem human brain. Moreover, IGFBP-5 mediates, while ITPK1 moderates, the association between AKT1 phosphorylation and late-life cognitive decline.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Cognitive Dysfunction; Female; Humans; Insulin; Insulin-Like Growth Factor Binding Protein 5; Male; Phosphorylation; Proto-Oncogene Proteins c-akt; Signal Transduction

Impact of obesity on neuropsychiatric symptoms in Alzheimer's disease: Insights from the ADNI cohort. - Wang, Shuoshi; Ni, Jingnian; Wei, Mingqing; Li, Ting; Shi, Jing; Tian, Jinzhou (J Alzheimers Dis, 2025)
BackgroundObesity is a major global health issue linked to increased risks of dementia, including Alzheimer's disease (AD). While the association between obesity and neuropsychiatric symptoms (NPS) in AD remains underexplored, identifying these links could aid in weight management in AD patients.ObjectiveThis study investigates the relationship between body mass index (BMI) and NPS in AD dementia patients, focusing on the potential mediating role of systemic inflammation.MethodsWe employed Generalized Additive Models (GAMs) to explore the relationship between BMI and NPS, as measured by the Neuropsychiatric Inventory Questionnaire (NPI-Q). Participants were classified into ideal, overweight, and obese groups based on WHO criteria. Longitudinal analyses assessed the trajectory of NPI-Q scores in different groups over a one-year follow-up.ResultsBMI significantly affects NPI-Q total scores and specific symptoms, including delusions, hallucinations, agitation/aggression, elation/euphoria, disinhibition, irritability/lability, aberrant motor behavior, nighttime disturbances, and appetite/eating disturbances. Obese patients exhibited higher NPI-Q total scores and greater severity in symptoms such as hallucinations, agitation/aggression, elation/euphoria, apathy/indifference, disinhibition, aberrant motor behavior, and nighttime disturbances. Additionally, CRP and complement C3 were identified as mediators in the relationship between obesity and NPS, highlighting the role of systemic inflammation.ConclusionsThis study demonstrates that obesity is associated with a heightened burden of NPS in AD dementia patients. The identification of CRP and complement C3 as mediators suggests inflammation plays a crucial role in the association between obesity and NPS. These findings underscore the importance of addressing obesity and its inflammatory consequences in managing NPS among this vulnerable population.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Body Mass Index; Cohort Studies; Female; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Obesity

African Ancestry Individuals with Higher Educational Attainment Are Resilient to Alzheimer's Disease Measured by pTau181. - Rajabli, Farid; Seixas, Azizi A; Akgun, Bilcag; Adams, Larry D; Inciute, Jovita; Hamilton, Kara L; Whithead, Patrice G; Konidari, Ioanna; Gu, Tianjie; Arvizu, Jamie; Golightly, Charles G; Starks, Takiyah D; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Cognitive and functional abilities in individuals with Alzheimer's disease (AD) pathology (ADP) are highly variable. Factors contributing to this variability are not well understood. Previous research indicates that higher educational attainment (EA) correlates with reduced cognitive impairments among those with ADP. While cognitive and functional impairments are correlated, they are distinguishable in their manifestations. OBJECTIVE: To investigate whether levels of education are associated with functional impairments among those with ADP. METHODS: This research involved 410 African American (AA) individuals (Institutional Review Boards 20070307, 01/27/2023) to ascertain whether EA correlates with functional resilience and if this effect varies between APOE ɛ4 carriers and non-carriers. Utilizing EA as a cognitive reserve proxy, CDR-FUNC as a functional difficulties measure, and blood pTau181 as an ADP proxy, the non-parametric Mann-Whitney U test assessed the relationship between EA and CDR-FUNC in individuals with advanced pTau181 levels. RESULTS: The results showed that EA correlated with functional difficulties in AA individuals with high levels of pTau181, such that individuals with high EA are more likely to have better functional ability compared to those with lower EA (W = 730.5, p = 0.0007). Additionally, we found that the effect of high EA on functional resilience was stronger in ɛ4 non-carriers compared to ɛ4 carriers (W = 555.5, p = 0.022). CONCLUSION: This study extends the role of cognitive reserve and EA to functional performance showing that cognitive reserve influences the association between ADP burden and functional difficulties. Interestingly, this protective effect seems less pronounced in carriers of the strong genetic risk allele ɛ4.
Keywords: Alzheimer Disease; Apolipoprotein E4; Cognitive Dysfunction; Educational Status; Humans; Resilience, Psychological

Alzheimer DataLENS: An Open Data Analytics Portal for Alzheimer's Disease Research. - Noori, Ayush; Jayakumar, Rojashree; Moturi, Vaishnavi; Li, Zhaozhi; Liu, Rongxin; Serrano-Pozo, Alberto; Hyman, Bradley T; Das, Sudeshna (J Alzheimers Dis, 2024)
BACKGROUND: Recent Alzheimer's disease (AD) discoveries are increasingly based on studies from a variety of omics technologies on large cohorts. Currently, there is no easily accessible resource for neuroscientists to browse, query, and visualize these complex datasets in a harmonized manner. OBJECTIVE: Create an online portal of public omics datasets for AD research. METHODS: We developed Alzheimer DataLENS, a web-based portal, using the R Shiny platform to query and visualize publicly available transcriptomics and genetics studies of AD on human cohorts. To ensure consistent representation of AD findings, all datasets were processed through a uniform bioinformatics pipeline. RESULTS: Alzheimer DataLENS currently houses 2 single-nucleus RNA sequencing datasets, over 30 bulk RNA sequencing datasets from 19 brain regions and 3 cohorts, and 2 genome-wide association studies (GWAS). Available visualizations for single-nucleus data include bubble plots, heatmaps, and UMAP plots; for bulk expression data include box plots and heatmaps; for pathways include protein-protein interaction network plots; and for GWAS results include Manhattan plots. Alzheimer DataLENS also links to two other knowledge resources: the AD Progression Atlas and the Astrocyte Atlas. CONCLUSIONS: Alzheimer DataLENS is a valuable resource for investigators to quickly and systematically explore omics datasets and is freely accessible at https://alzdatalens.partners.org.
Keywords: Alzheimer Disease; Brain; Computational Biology; Genome-Wide Association Study; Humans; Internet

Apoptosis, Autophagy, and Mitophagy Genes in the CA3 Area in an Ischemic Model of Alzheimer's Disease with 2-Year Survival. - Pluta, Ryszard; Bogucka-Kocka, Anna; Bogucki, Jacek; Kocki, Janusz; Czuczwar, Stanisław J (J Alzheimers Dis, 2024)
BACKGROUND: Currently, no evidence exists on the expression of apoptosis (CASP3), autophagy (BECN1), and mitophagy (BNIP3) genes in the CA3 area after ischemia with long-term survival. OBJECTIVE: The goal of the paper was to study changes in above genes expression in CA3 area after ischemia in the period of 6-24 months. METHODS: In this study, using quantitative RT-PCR, we present the expression of genes associated with neuronal death in a rat ischemic model of Alzheimer's disease. RESULTS: First time, we demonstrated overexpression of the CASP3 gene in CA3 area after ischemia with survival ranging from 0.5 to 2 years. Overexpression of the CASP3 gene was accompanied by a decrease in the activity level of the BECN1 and BNIP3 genes over a period of 0.5 year. Then, during 1-2 years, BNIP3 gene expression increased significantly and coincided with an increase in CASP3 gene expression. However, BECN1 gene expression was variable, increased significantly at 1 and 2 years and was below control values 1.5 years post-ischemia. CONCLUSIONS: Our observations suggest that ischemia with long-term survival induces neuronal death in CA3 through activation of caspase 3 in cooperation with the pro-apoptotic gene BNIP3. This study also suggests that the BNIP3 gene regulates caspase-independent pyramidal neuronal death post-ischemia. Thus, caspase-dependent and -independent death of neuronal cells occur post-ischemia in the CA3 area. Our data suggest new role of the BNIP3 gene in the regulation of post-ischemic neuronal death in CA3. This suggests the involvement of the BNIP3 together with the CASP3 in the CA3 in neuronal death post-ischemia.
Keywords: Alzheimer Disease; Animals; Apoptosis; Apoptosis Regulatory Proteins; Autophagy; Beclin-1; Brain Ischemia; CA3 Region, Hippocampal; Caspase 3; Disease Models, Animal; Male; Membrane Proteins; Mitochondrial Proteins; Mitophagy; Rats; Rats, Wistar

The Association Between Distinct Delusional Ideations and Depressive Symptoms in Alzheimer's Disease: A Re-Analysis of CATIE-AD. - Nagata, Tomoyuki; Nakajima, Shinichiro; Kito, Shinsuke; Shinagawa, Shunichiro (J Alzheimers Dis, 2024)
BACKGROUND: Delusional ideations, one of neuropsychiatric symptoms (NPSs), are frequently shown in the long-term progression of Alzheimer's disease (AD), and comorbid with other NPSs including depression or agitation. Despite various types of delusional ideations, the comorbidity between each delusional ideation and depressive symptoms has not been discussed. OBJECTIVE: The present cross-sectional study is aimed at testing the hypothetical mechanism of comorbid pattern in AD. METHODS: Among 421 patients with AD, we analyzed the dataset of the Clinical Antipsychotic Trials of Intervention Effectiveness-Alzheimer's Disease to compare age, sex, racial type, Mini-Mental State Examination (MMSE) scores, and Neuropsychiatric Inventory (NPI) depression score of between the presence and absence of each delusional ideation (delusion of persecution, theft, jealousy, abandonment, phantom boarder, Capgras syndrome, misidentification of place, or television sign). Next, with the stratification based on MMSE score of < or > = 15 points, we further explored association between delusional ideation and depressive symptom that was found significances in the primary analysis. RESULTS: Among eight subtypes of delusional ideations, depression score was higher in those with persecution delusion or Capgras syndrome. Moreover, the Capgras syndrome was associated with presence of depression in severer global cognitive impairment status. CONCLUSIONS: As comorbid NPSs of delusional ideation in AD, depressive severity is associated with specific delusional subtype: persecution delusion and Capgras syndrome. Capgras syndrome may be attributable to severe cognitive impairment in addition to depressive symptom. The consideration of pathogenetic differences in the distinct delusional ideations may be helpful for clinicians to select the treatment strategy.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cross-Sectional Studies; Delusions; Depression; Female; Humans; Male; Mental Status and Dementia Tests

Association Between Urinary Glyphosate Exposure and Cognitive Impairment in Older Adults from NHANES 2013-2014. - Ren, Jiawen; Yu, Yongquan; Wang, Yucheng; Dong, Yu; Shen, Xiaobing (J Alzheimers Dis, 2024)
BACKGROUND: Glyphosate is the most commonly used herbicide with potential neurotoxicity. However, limited epidemical evidence is found in the relationship between glyphosate and cognitive impairment, especially in the cognitive-disrupting sensitive elderly populations. OBJECTIVE: This study aimed to examine the association of urinary glyphosate exposure with cognitive impairment in the United State (US) older adults. METHODS: Cognitive impairment was determined by the following four tests: the Consortium to Establish a Registry for Alzheimer's disease (CERAD) Immediate Recall test (IR), the CERAD Delayed Recall tests (DR), the Animal Fluency (AF) test and the Digit Substitution test (DSST). Survey weighted logistic regression and restricted cubic splines were applied to evaluate and visualize the association between glyphosate and cognitive impairment. RESULTS: A total of 465 elderly adults were identified in the National Health and Nutrition Examination Survey (NHANES) 2013-2014 cycle, and among them, 83.87% individuals had detectable urinary levels of glyphosate (0.628 ng/mL in average). After adjusting for the potential covariates, glyphosate was significantly linked to increased DR and AF impairment, and the corresponding ORs were 1.52 (1.01 to 2.30, p = 0.049) and 1.69 (1.11 to 2.59, p = 0.019), respectively. No significant association was identified between glyphosate and IR or DSST impairment. The RCS plot further confirmed the linear and positive relationships between glyphosate and DR and AF impairment. CONCLUSIONS: These findings suggested that exposure to glyphosate might be associated with declined cognitive function in the elderly, and it might be prudent to evaluate cognitive outcomes for aged individuals with glyphosate exposures.
Keywords: Aged; Alzheimer Disease; Cognition; Cognition Disorders; Cognitive Dysfunction; Glyphosate; Humans; Nutrition Surveys

Association of Plastic Exposure with Cognitive Function Among Chinese Older Adults. - Zhu, Yongbin; Wu, Yueping; Shi, Liping; Yang, Yue; Wang, Yanrong; Pan, Degong; He, Shulan; Wang, Liqun; Li, Jiangping (J Alzheimers Dis, 2024)
BACKGROUND: The widespread exposure to plastic products and the increasing number of individuals with cognitive impairments have imposed a heavy burden on society. OBJECTIVE: This study aims to investigate the relationship between plastic product exposure in daily life and cognitive function in older Chinese individuals. METHODS: Data were obtained from the 2023 Ningxia Older Psychological Health Cohort, comprising 4045 participants aged 60 and above. Cognitive function was assessed using the Mini-Mental State Examination scale. A population-based plastic exposure questionnaire was used to calculate plastic exposure scores (PES). Binary logistic regression was employed to analyze the relationship between PES and cognitive function, while restricted cubic splines were used to examine the dose-response relationship between PES and cognitive function. Latent profile analysis (LPA) was employed to explore the potential patterns of plastic exposure, and logistic regression was used to investigate the relationship between different exposure patterns and cognitive function. A linear regression model was utilized to investigate the relationship between PES and different dimensions of cognitive function. RESULTS: Among the 4045 participants, 1915 individuals were assessed with mild cognitive impairment (MCI). After adjusting for all covariates, PES (OR = 1.04, 95% CI 1.02-1.06) was significantly associated with the risk of MCI and exhibited a dose-response relationship. LPA identified two potential categories of plastic exposure, with a higher risk of MCI observed in the group using plastic utensils. CONCLUSIONS: This study indicates a positive correlation between plastic exposure levels and MCI risk, particularly among individuals who frequently use plastic tableware.
Keywords: Aged; Aged, 80 and over; China; Cognition; Cognitive Dysfunction; Cohort Studies; East Asian People; Environmental Exposure; Female; Humans; Male; Mental Status and Dementia Tests; Middle Aged; Plastics; Surveys and Questionnaires

Association of Statin Use with Dementia Risk Among Older Adults in Japan: A Nested Case-Control Study Using the LIFE Study. - Ge, Sanyu; Kitamura, Tetsuhisa; Zha, Ling; Komatsu, Masayo; Komukai, Sho; Murata, Fumiko; Maeda, Megumi; Gon, Yasufumi; Kimura, Yasuyoshi; Kiyohara, Kosuke; Sobue, Tomotaka; Fukuda, Haruhisa (J Alzheimers Dis, 2024)
BACKGROUND: Previous studies have shown a possible association between statin use and a decreased risk of dementia, but the association has not been sufficiently established, especially in the super-aging society of Japan. OBJECTIVE: This study aimed to determine the association between statin use and the risk of dementia among Japanese participants aged> =65 years old. METHODS: Data from the Longevity Improvement and Fair Evidence (LIFE) Study were utilized, including medical and long-term care (LTC) claim data from 17 municipalities between April 2014 and December 2020. A nested case-control study was conducted with one case matched to five controls based on age, sex, municipality, and year of cohort entry. We used a conditional logistic regression model to calculate the odds ratios (ORs) and 95% confidence intervals (95% CIs). RESULTS: This study included 57,302 cases and 283,525 controls, with 59.7% of the participants being woman. After adjusting for potential confounders, statin use was associated with a lower risk of dementia (OR, 0.70; 95% CI: 0.68-0.73) and Alzheimer's disease (OR: 0.66; 95% CI: 0.63-0.69). Compared with non-users, the ORs of dementia were as follows: 1.42 (1.34-1.50) for 1-30 total standardized daily dose (TSDD), 0.91 (0.85-0.98) for 31-90 TSDD, 0.63 (0.58-0.69) for 91-180 TSDD, and 0.33 (0.31-0.36) for >180 TSDD in dose-analysis. CONCLUSIONS: Statin use is associated with a reduced risk of dementia and Alzheimer's disease among older Japanese adults. A low cumulative statin dose is associated with an increased risk of dementia, whereas a high cumulative statin dose is a protective factor against dementia.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Dementia; Female; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Japan; Male; Risk Factors

Association of Vitamin D Levels with Risk of Cognitive Impairment and Dementia: A Systematic Review and Meta-Analysis of Prospective Studies. - Zhang, Xiao-Xue; Wang, He-Ran; Hu, Ya-Zhuo; Sun, Hong-Mei; Feng, Yu-Xin; Jia, Jian-Jun (J Alzheimers Dis, 2024)
BACKGROUND: Emerging evidence suggests the potential relationship between vitamin D deficiency and risk of cognitive impairment or dementia. To what extent the excess risk of dementia conferred by vitamin D deficiency is less clear. OBJECTIVE: We summarized the current evidence from several aspects and further quantified these associations. METHODS: We collected relevant prospective cohort studies by searching PubMed, Embase and Cochrane up to July 2023. The pooled relative risks (RR) were evaluated by random-effects models. Dose-response analyses were conducted by the method of two-stage generalized least squares regression. RESULTS: Of 9,267 identified literatures, 23 were eligible for inclusion in the meta-analyses, among which 9 and 4 literatures were included in the dose-response analyses for the risk of dementia and Alzheimer's disease (AD). Vitamin D deficiency exhibited a 1.42 times risk for dementia (95% confidence interval (CI) = 1.21-1.65) and a 1.57-fold excess risk for AD (95% CI = 1.15-2.14). And vitamin D deficiency was associated with 34% elevated risk with cognitive impairment (95% CI = 1.19-1.52). Additionally, vitamin D was non-linearly related to the risk of dementia (pnonlinearity = 0.0000) and AD (pnonlinearity = 0.0042). The approximate 77.5-100 nmol/L 25-hydroxyvitamin D [25(OH)D] was optimal for reducing dementia risk. And the AD risk seemed to be decreased when the 25(OH)D level >40.1 nmol/L. CONCLUSIONS: Vitamin D deficiency was a risk factor for dementia, AD, and cognitive impairment. The nonlinear relationships may further provide the optimum dose of 25(OH)D for dementia prevention.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Dementia; Humans; Prospective Studies; Risk Factors; Vitamin D; Vitamin D Deficiency

The Associations of Phosphorylated Tau 181 and Tau 231 Levels in Plasma and Cerebrospinal Fluid with Cognitive Function in Alzheimer's Disease: A Systematic Review and Meta-Analysis. - Li, Zhirui; Fan, Zixuan; Zhang, Qian (J Alzheimers Dis, 2024)
BACKGROUND: Cerebrospinal fluid (CSF) or blood biomarkers like phosphorylated tau proteins (p-tau) are used to detect Alzheimer's disease (AD) early. Increasing studies on cognitive function and blood or CSF p-tau levels are controversial. OBJECTIVE: Our study examined the potential of p-tau as a biomarker of cognitive status in normal control (NC), mild cognitive impairment (MCI), and AD patients. METHODS: We searched PubMed, Cochrane, Embase, and Web of Science for relevant material through 12 January 2023. 5,017 participants from 20 studies-1,033 AD, 2,077 MCI, and 1,907 NC-were evaluated. Quantitative analysis provided continuous outcomes as SMDs with 95% CIs. Begg tested publication bias. RESULTS: MCI patients had lower CSF p-tau181 levels than AD patients (SMD =-0.60, 95% CI (-0.85, -0.36)) but higher than healthy controls (SMD = 0.67). AD/MCI patients had greater plasma p-tau181 levels than healthy people (SMD =-0.73, 95% CI (-1.04, -0.43)). MCI patients had significantly lower p-tau231 levels than AD patients in plasma and CSF (SMD =-0.90, 95% CI (-0.82, -0.45)). MCI patients showed greater CSF and plasma p-tau231 than healthy controls (SMD = 1.34, 95% CI (0.89, 1.79) and 0.43, (0.23, 0.64)). Plasma p-tau181/231 levels also distinguished the three categories. MCI patients had higher levels than healthy people, while AD patients had higher levels than MCI patients. CONCLUSIONS: CSF p-tau181 and p-tau231 biomarkers distinguished AD, MCI, and healthy populations. Plasma-based p-tau181 and p-tau231 biomarkers for AD and MCI need further study.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognition; Cognitive Dysfunction; Humans; tau Proteins

Cerebrovascular miRNAs Track Early Development of Alzheimer's Disease and Target Molecular Markers of Angiogenesis and Blood Flow Regulation. - Chum, Phoebe P; Bishara, Mary A; Solis, Summer R; Behringer, Erik J (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is associated with impaired cerebral circulation which underscores diminished delivery of blood oxygen and nutrients to and throughout the brain. In the 3xTg-AD mouse model, we have recently found that > 10 cerebrovascular miRNAs pertaining to vascular permeability, angiogenesis, and inflammation (e.g., let-7d, miR-99a, miR-132, miR-133a, miR-151-5p, and miR-181a) track early development of AD. Further, endothelial-specific miRNAs (miR-126-3p, miR-23a/b, miR-27a) alter with onset of overall AD pathology relative to stability of smooth muscle/pericyte-specific miRNAs (miR-143, miR-145). OBJECTIVE: We tested the hypothesis that cerebrovascular miRNAs indicating AD pathology share mRNA targets that regulate key endothelial cell functions such as angiogenesis, vascular permeability, and blood flow regulation. METHODS: As detected by NanoString nCounter miRNA Expression panel for 3xTg-AD mice, 61 cerebrovascular miRNAs and respective mRNA targets were examined using Ingenuity Pathway Analysis for canonical Cardiovascular (Cardio) and Nervous System (Neuro) Signaling. RESULTS: The number of targets regulated per miRNA were 21±2 and 33±3 for the Cardio and Neuro pathways respectively, whereby 14±2 targets overlap among pathways. Endothelial miRNAs primarily target members of the PDE, PDGF, SMAD, and VEGF families. Individual candidates regulated by≥4 miRNAs that best mark AD pathology presence in 3xTg-AD mice include CFL2, GRIN2B, PDGFB, SLC6A1, SMAD3, SYT3, and TNFRSF11B. CONCLUSION: miRNAs selective for regulation of endothelial function and respective downstream mRNA targets support a molecular basis for dysregulated cerebral blood flow regulation coupled with enhanced cell growth, proliferation, and inflammation.
Keywords: Alzheimer Disease; Angiogenesis; Animals; Biomarkers; Brain; Cerebrovascular Circulation; Disease Models, Animal; Endothelial Cells; Humans; Mice; Mice, Transgenic; MicroRNAs; Neovascularization, Pathologic

Characterizing Gut Microbiota in Older Chinese Adults with Cognitive Impairment: A Cross-Sectional Study. - Wang, Jing; Zhang, Gong; Lai, Hao; Li, Zengbin; Shen, Mingwang; Li, Chao; Kwan, Patrick; O'Brien, Terence J; Wu, Ting; Yang, Siyu; Zhang, Xueli; Zhang, Lei (J Alzheimers Dis, 2024)
BACKGROUND: Cognitive impairment is a clinical manifestation that occurs in the course of dementia like Alzheimer's disease. The association between cognitive impairment and gut microbiota is unclear. OBJECTIVE: We aimed to identify gut microbiota characteristics and key gut microbiota biomarkers associated with cognitive impairment in a relatively large cohort of older adults in China. METHODS: A total of 229 adults aged ≥60 years from Shenzhen, China were recruited into this cross-sectional study. Participants were divided into cognitive impairment (CI) and no cognitive impairment (NCI) groups according to the results of the Mini-Mental State Examination. Diversity analysis and network analysis were used to characterize the gut microbiota between the two groups. The linear discriminant analysis effect size method and machine learning approaches were sequentially performed to identify gut microbiota biomarkers. The relationship between biomarkers and lifestyle factors was explored using Transformation-based redundancy analysis (tb-RDA). RESULTS: A total of 74 CI participants and 131 NCI participants were included in the analysis. The CI group demonstrated lower α-diversity compared to the NCI group (Shannon: 2.798 versus 3.152, p < 0.001). The density of the gut microbiota interaction network was lower in the CI group (0.074) compared to the NCI group (0.081). Megamonas, Blautia, Pseudomonas, Stenotrophomonas, and Veillonella were key biomarkers for CI. The tb-RDA revealed that increased fruit intake and exercise contribute to a higher abundance of Megamonas, Blautia, and Veillonella. CONCLUSIONS: We identified a significantly reduced abundance of certain beneficial gut microbiota in older Chinese adults with cognitive impairment.
Keywords: Aged; Aged, 80 and over; Biomarkers; China; Cognitive Dysfunction; Cross-Sectional Studies; East Asian People; Female; Gastrointestinal Microbiome; Humans; Machine Learning; Male; Middle Aged

Circulating adipokines and MRI markers of brain aging in middle-aged adults from the community. - Satizabal, Claudia L; Himali, Jayandra Jung; Conner, Sarah C; Beiser, Alexa S; Maillard, Pauline; Vasan, Ramachandran S; DeCarli, Charles; Seshadri, Sudha (J Alzheimers Dis, 2024)
BACKGROUND: Midlife obesity is related to late-onset dementia. Studying adipose tissue-secreted adipokines in the context of brain aging may help us understand this association. OBJECTIVE: To investigate associations between adipokines and brain MRI markers in middle-aged adults from the Third-Generation cohort of the Framingham Heart Study. METHODS: Serum adiponectin, retinol-binding protein 4 (RBP4), fetuin-A, and Fatty Acid-Binding Protein 4 (FABP4) concentrations were measured by enzymatic immunoassays. MRI measures included total brain, cortical gray matter, hippocampal (total and anterior), lateral ventricular, and white matter hyperintensity volumes. We used linear regression models to separately relate adipokine concentrations to MRI measures, adjusting for potential confounders. RESULTS: We included 1882 participants (mean age of 48 ± 8 years, 54% women). Higher RBP4 concentrations were related to markers of brain atrophy, including smaller total (Beta ± standard error, -0.05 ± 0.02; p = 0.014) and cortical gray brain volumes (-0.06 ± 0.02; p = 0.004), and larger lateral ventricular volumes (0.06 ± 0.02; p = 0.006). Additionally, higher RBP4 (-0.06 ± 0.03; p = 0.042), Fetuin-A (-0.06 ± 0.03; p = 0.039), and FABP4 (-0.09 ± 0.03; p = 0.008) concentrations were associated with smaller anterior hippocampal volumes. Most associations remained after additional adjustment for vascular risk factors. In exploratory analyses, higher FABP4 was related to larger total brain in non-obese participants, and to smaller anterior hippocampal volumes in obese participants. Finally, higher adiponectin concentrations were related to smaller cortical gray, only in non-obese participants. CONCLUSIONS: Our results suggest that adipokines are associated with markers of brain atrophy during midlife. Further studies are needed to replicate these findings and elucidate any potential mechanisms contributing to abnormal brain aging.
Keywords: Adipokines; Adiponectin; Adult; Aging; alpha-2-HS-Glycoprotein; Atrophy; Biomarkers; Brain; Cohort Studies; Fatty Acid-Binding Proteins; Female; Gray Matter; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Retinol-Binding Proteins, Plasma

On the Clinimetrics of the Montreal Cognitive Assessment: Cutoff Analysis in Patients with Mild Cognitive Impairment due to Alzheimer's Disease. - Ilardi, Ciro Rosario; Menichelli, Alina; Michelutti, Marco; Cattaruzza, Tatiana; Federico, Giovanni; Salvatore, Marco; Iavarone, Alessandro; Manganotti, Paolo (J Alzheimers Dis, 2024)
BACKGROUND: In the era of disease-modifying therapies, empowering the clinical neuropsychologist's toolkit for timely identification of mild cognitive impairment (MCI) is crucial. OBJECTIVE: Here we examine the clinimetric properties of the Montreal Cognitive Assessment (MoCA) for the early diagnosis of MCI due to Alzheimer's disease (MCI-AD). METHODS: Data from 48 patients with MCI-AD and 47 healthy controls were retrospectively analyzed. Raw MoCA scores were corrected according to the conventional Nasreddine's 1-point correction and demographic adjustments derived from three normative studies. Optimal cutoffs were determined while previously established cutoffs were diagnostically reevaluated. RESULTS: The original Nasreddine's cutoff of 26 and normative cutoffs (non-parametric outer tolerance limit on the 5th percentile of demographically-adjusted score distributions) were overly imbalanced in terms of Sensitivity (Se) and Specificity (Sp). The optimal cutoff for Nasreddine's adjustment showed adequate clinimetric properties (≤23.50, Se = 0.75, Sp = 0.70). However, the optimal cutoff for Santangelo's adjustment (≤22.85, Se = 0.65, Sp = 0.87) proved to be the most effective for both screening and diagnostic purposes according to Larner's metrics. The results of post-probability analyses revealed that an individual testing positive using Santangelo's adjustment combined with a cutoff of 22.85 would have 84% post-test probability of receiving a diagnosis of MCI-AD (LR+ = 5.06). CONCLUSIONS: We found a common (mal)practice of bypassing the applicability of normative cutoffs in diagnosis-oriented clinical practice. In this study, we identified optimal cutoffs for MoCA to be allocated in secondary care settings for supporting MCI-AD diagnosis. Methodological and psychometric issues are discussed.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Female; Humans; Male; Mental Status and Dementia Tests; Middle Aged; Neuropsychological Tests; Retrospective Studies; Sensitivity and Specificity

Comparative accuracy of Mini-Linguistic State Examination, Addenbrooke's Cognitive Examination, and Depistage Cognitif de Quebec for the diagnosis of primary progressive aphasia. - Fernández-Romero, Lucía; Morello-García, Florentina; Laforce, Robert; Delgado-Alonso, Cristina; Delgado-Álvarez, Alfonso; Gil-Moreno, María José; Lavoie, Monica; Matías-Guiu, Jorge; Cuetos, Fernando; Matías-Guiu, Jordi A (J Alzheimers Dis, 2024)
BACKGROUND: Clinical diagnosis in primary progressive aphasia (PPA) is challenging. Recently, emphasis has been placed on the importance of screening evaluation. Three different screening tests that use different strategies based on the assessment of language (Mini-Linguistic State Examination, MLSE) or different cognitive domains (Addenbrooke's Cognitive Examination, ACE-III and Dépistage Cognitif de Québec, DCQ) have been proposed and independently validated. These tests aim to detect PPA and classify into the three main variants (non-fluent (nfvPPA), semantic (svPPA) and logopenic (lvPPA)). OBJECTIVE: This study aims to evaluate and compare the diagnostic capacity of these three instruments in PPA. METHODS: A cross-sectional study including 43 patients with PPA (nfvPPA ( = 19), svPPA ( = 8), and lvPPA ( = 16)) and 21 cognitively unimpaired controls was conducted. Clinical diagnoses were established based on an extensive multidisciplinary assessment including neuropsychological assessment, fluorodeoxyglucose-positron emission tomography, MRI, and cerebrospinal fluid biomarkers. Both PPA patients and controls completed the three tests (MLSE, ACE-III, and DCQ). RESULTS: Internal consistency was excellent for the three tests. The area under the curve for the diagnosis of PPA was 0.950 for MLSE, 0.953 for ACE-III, and 0.933 for DCQ. Correlations between the three tests were high. The MLSE, ACE-III, and DCQ tests obtained adequate levels of discrimination between the variants of PPA, with accuracies between 76-79%. CONCLUSIONS: This study confirms the validity of ACE-III, MLSE, and DCQ for the diagnosis of PPA and its variants. This suggests that detailed assessment of linguistic characteristics (MLSE) and non-linguistic features (DCQ, ACE-III) are relevant for the diagnosis and classification of PPA.
Keywords: Aged; Aphasia, Primary Progressive; Cross-Sectional Studies; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography; Reproducibility of Results

Comparative Efficacy, Tolerability, and Acceptability of Donanemab, Lecanemab, Aducanumab, Melatonin, and Aerobic Exercise for a Short Time on Cognitive Function in Mild Cognitive Impairment and Mild Alzheimer's Disease - Terao, Itsuki; Kodama, Wakako (J Alzheimers Dis, 2024)
BACKGROUND: The Food and Drug Administration (FDA) has approved lecanemab and aducanumab and is reviewing donanemab, but they have questionable efficacy, serious side effects and are costly, whereas melatonin administration and aerobic exercise for a short time may overcome these problems. OBJECTIVE: We aim to compare the efficacy on cognitive function, tolerability and acceptability of melatonin administration and aerobic exercise for a short time with donanemab, lecanemab, and aducanumab in people with mild AD and MCI. METHODS: We systematically reviewed relevant randomized placebo-controlled trials (RCTs) in PubMed, the Cochrane Library, CINHAL, and ClinicalTrials.gov and performed network meta-analyses. RESULTS: The analysis included 10 randomized placebo-controlled trials with 4,599 patients. Although melatonin and aerobic exercise for a short time were significantly more effective than donanemab, lecanemab, aducanumab and placebo in the primary analysis, there was significant heterogeneity. In the sensitivity analysis excluding exercise, melatonin was significantly more effective than donanemab, lecanemab, aducanumab and placebo, with no significant heterogeneity. Aerobic exercise for a short time was significantly less acceptable than donanemab, aducanumab and placebo. Donanemab, lecanemab, and aducanumab were significantly less tolerable than placebo and donanemab and lecanemab were significantly less acceptable than placebo. CONCLUSIONS: Melatonin may be a better potential disease-modifying treatment for cognitive decline in mild AD and MCI. Aerobic exercise for a short time might also be better than donanemab, lecanemab and aducanumab if continued, as it is well tolerated and more effective, although less valid due to heterogeneity. Another limitation is the small number of participants.
Keywords: Alzheimer Disease; Antibodies, Monoclonal, Humanized; Cognition; Cognitive Dysfunction; Exercise Therapy; Humans; Melatonin; Network Meta-Analysis; Randomized Controlled Trials as Topic; Treatment Outcome

Computational Evaluation of the Potential Pharmacological Activity of Salen-Type Ligands in Alzheimer's Disease. - Puentes-Díaz, Nicolás; Chaparro, Diego; Reyes-Marquez, Viviana; Morales-Morales, David; Flores-Gaspar, Areli; Alí-Torres, Jorge (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is the most common form of dementia representing from 60% to 70% of the cases globally. It is a multifactorial disease that, among its many pathological characteristics, has been found to provoke the metal ion dysregulation in the brain, along with an increase in the oxidative stress. There is proof that metallic complexes formed by the amyloid-β peptide (Aβ) and extraneuronal copper can catalyze the production of reactive oxygen species, leading to an increase in oxidative stress, promoting neuronal death. Due to this interaction, bioavailable copper has become an important redox active target to consider within the search protocols of multifunctional agents for AD's treatment. OBJECTIVE: In this study, we examined by using bioinformatics and electronic structure calculations the potential application of 44 salen-type copper chelating ligands and 12 further proposed molecules as possible multifunctional agents in the context of AD. METHODS: The candidates were evaluated by combining bioinformatic tools and electronic structure calculations, which allowed us to classify the molecules as potential antioxidants, redistributor-like compounds, and the newly proposed suppressor mechanism. RESULTS: This evaluation demonstrate that salen-type ligands exhibit properties suitable for interfering in the chain of copper-induced oxidative stress reactions present in AD and potential redistributor and suppressor activity for copper ions. Finally, a novel set of plausible candidates is proposed and evaluated. CONCLUSION: According to the evaluated criteria, a subset of 13 salen-type candidates was found to exhibit promissory pharmacological properties in the AD framework and were classified according to three plausible action mechanisms.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Antioxidants; Chelating Agents; Computational Biology; Copper; Humans; Ligands; Oxidative Stress

A Continuous Extension of Gene Set Enrichment Analysis Using the Likelihood Ratio Test Statistics Identifies Vascular Endothelial Growth Factor as a Candidate Pathway for Alzheimer's Disease via ITGA5. - Mahzarnia, Ali; Lutz, Michael W; Badea, Alexandra (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) involves brain neuropathologies such as amyloid plaque and hyperphosphorylated tau tangles and is accompanied by cognitive decline. Identifying the biological mechanisms underlying disease onset and progression based on quantifiable phenotypes will help understand disease etiology and devise therapies. OBJECTIVE: Our objective was to identify molecular pathways associated with hallmark AD biomarkers and cognitive status, accounting for variables such as age, sex, education, and APOE genotype. METHODS: We introduce a pathway-based statistical approach, extending the gene set likelihood ratio test to continuous phenotypes. We first analyzed independently each of the three phenotypes (amyloid-β, tau, cognition) using continuous gene set likelihood ratio tests to account for covariates, including age, sex, education, and APOE genotype. The analysis involved 634 subjects with data available for all three phenotypes, allowing for the identification of common pathways. RESULTS: We identified 14 pathways significantly associated with amyloid-β; 5 associated with tau; and 174 associated with cognition, which showed a larger number of pathways compared to biomarkers. A single pathway, vascular endothelial growth factor receptor binding (VEGF-RB), exhibited associations with all three phenotypes. Mediation analysis showed that among the VEGF-RB family genes, ITGA5 mediates the relationship between cognitive scores and pathological biomarkers. CONCLUSIONS: We presented a new statistical approach linking continuous phenotypes, gene expression across pathways, and covariates like sex, age, and education. Our results reinforced VEGF RB2's role in AD cognition and demonstrated ITGA5's significant role in mediating the AD pathology-cognition connection.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Biomarkers; Cognitive Dysfunction; Humans; Likelihood Functions; tau Proteins; Vascular Endothelial Growth Factor A

Effect of Metformin on Plasma and Cerebrospinal Fluid Biomarkers in Non-Diabetic Older Adults with Mild Cognitive Impairment Related to Alzheimer's Disease. - Weinberg, Marc S; He, Yingnan; Kivisäkk, Pia; Arnold, Steven E; Das, Sudeshna (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is a complicated condition involving multiple metabolic and immunologic pathophysiological processes that can occur with the hallmark pathologies of amyloid-β, tau, and neurodegeneration. Metformin, an anti-diabetes drug, targets several of these disease processes in in vitro and animal studies. However, the effects of metformin on human cerebrospinal fluid (CSF) and plasma proteins as potential biomarkers of treatment remain unexplored. OBJECTIVE: Using proteomics data from a metformin clinical trial, identify the impact of metformin on plasma and CSF proteins. METHODS: We analyzed plasma and CSF proteomics data collected previously (ClinicalTrials.gov identifier: NCT01965756, conducted between 2013 and 2015), and conduced bioinformatics analyses to compare the plasma and CSF protein levels after 8 weeks of metformin or placebo use to their baseline levels in 20 non-diabetic patients with mild cognitive impairment (MCI) and positive AD biomarkers participants. RESULTS: 50 proteins were significantly (unadjusted p < 0.05) altered in plasma and 26 in CSF after 8 weeks of metformin use, with 7 proteins in common (AZU1, CASP-3, CCL11, CCL20, IL32, PRTN3, and REG1A). The correlation between changes in plasma and CSF levels of these 7 proteins after metformin use relative to baseline levels was high (r = 0.98). The proteins also demonstrated temporal stability. CONCLUSIONS: Our pilot study is the first to investigate the effect of metformin on plasma and CSF proteins in non-diabetic patients with MCI and positive AD biomarkers and identifies several candidate plasma biomarkers for future clinical trials after confirmatory studies.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Cognitive Dysfunction; Double-Blind Method; Female; Humans; Hypoglycemic Agents; Male; Metformin; Middle Aged; Proteomics

The Effects of Pomegranate Seed Oil on Mild Cognitive Impairment. - Chatzikostopoulos, Thanos; Gialaouzidis, Moses; Koutoupa, Anna; Tsolaki, Magda (J Alzheimers Dis, 2024)
BACKGROUND: In recent years, there has been a growing interest, supported by many experimental and clinical studies, about the benefits of pomegranate in preventing various pathologic conditions, including brain neurodegeneration. The pomegranate seed oil (PSO) contains high levels of fatty acids that have antioxidant and anti-inflammatory properties. OBJECTIVE: Due to the lack of clinical trials, the aim of the present study was to investigate the effects of PSO on cognition of people with mild cognitive impairment (MCI). METHODS: Eighty people with the diagnosis of MCI were randomized forty to take 5 drops of PSO and follow the Mediterranean Diet (MeDi) and forty just followed MeDi. All were examined with an extensive neuropsychological assessment before and after one year of treatment. RESULTS: The results showed that the participants who took the PSO had statistically significantly better global cognition (p = 0.004), verbal episodic memory (p = 0.009), and processing and executive functions (p < 0.001) in contrast with the participants who did not take it. CONCLUSIONS: In conclusion, the PSO can be beneficial for people with MCI as it is helpful for some important cognitive domains. As PSO is a natural product that does not burden the human body, it can be used by people with MCI and be a significant and promising part of holistic approaches for the prevention of dementia.
Keywords: Biological Products; Cognition; Cognitive Dysfunction; Humans; Neuropsychological Tests; Plant Oils; Pomegranate

Elevated Risk of Dementia Diagnosis in Older Adults with Low Frequencies and Durations of Social Conversation. - Shimada, Hiroyuki; Doi, Takehiko; Tsutsumimoto, Kota; Makino, Keitaro; Harada, Kenji; Tomida, Kouki; Arai, Hidenori (J Alzheimers Dis, 2024)
BACKGROUND: Social networks and social participation have protective effects on cognitive function maintenance and Alzheimer's disease and general dementia development. OBJECTIVE: We aimed to investigate the association between conversations and dementia incidence in older adults. METHODS: This longitudinal prospective cohort study used population data from the National Center for Geriatric and Gerontology-Study of Geriatric Syndromes (NCGG-SGS) from September 2015 to February 2017. The database included 4,167 individuals in Japan aged ≥60 years who were generally healthy and without major cognitive impairment. Participants were classified into two groups according to six daily conversation measures at baseline. The conversation index was calculated as a composite score for these measures. Participants were tracked monthly over 60 months for new-onset dementia. RESULTS: Data from 2,531 participants were analyzed (72.7±6.7 years; range: 60-96 years). Dementia incidence per 1,000 person-years was 15.7 (95% confidence interval, 13.6-18.1). The Youden index determined the cut-off point for dementia incidence, with a conversation index of 16/17 points. The low conversation group included more participants with new-onset dementia. Cox proportional hazards regression crude models showed remarkable relationships between dementia onset and specific conversation measurements, including conversation index. According to the Cox regression adjusted model, the cut-off point of the conversation index showed only a remarkable relationship with dementia onset. CONCLUSIONS: Dementia risk was extensively associated with low daily conversation statuses. The assessment of conversational factors may be useful as a risk indicator for the development of Alzheimer's disease and general dementia.
Keywords: Aged; Alzheimer Disease; Cognitive Dysfunction; Dementia; Geriatrics; Humans; Prospective Studies

The Etiology of Rapidly Progressive Dementia: A 3-Year Retrospective Study in a Tertiary Hospital in China. - Shi, Qin; Liu, Wei-Shi; Liu, Fang; Zeng, Yi-Xuan; Chen, Shu-Fen; Chen, Ke-Liang; Yu, Jin-Tai; Huang, Yu-Yuan (J Alzheimers Dis, 2024)
BACKGROUND: Rapidly progressive dementia (RPD), characterized by a rapid cognitive decline leading to dementia, comprises a diverse range of disorders. Despite advancements in diagnosis and treatment, research on RPD primarily focuses on Western populations. OBJECTIVE: This study aims to explore the etiology and demographics of RPD in Chinese patients. METHODS: We retrospectively analyzed 323 RPD inpatients at Huashan Hospital from May 2019 to March 2023. Data on sociodemographic factors, epidemiology, clinical presentation, and etiology were collected and analyzed. RESULTS: The median onset age of RPD patients was 60.7 years. Two-thirds received a diagnosis within 6 months of symptom onset. Memory impairment was the most common initial symptom, followed by behavioral changes. Neurodegenerative diseases accounted for 47.4% of cases, with central nervous system inflammatory diseases at 30.96%. Autoimmune encephalitis was the leading cause (16.7%), followed by Alzheimer's disease (16.1%), neurosyphilis (11.8%), and Creutzfeldt-Jakob disease (9.0%). Alzheimer's disease, Creutzfeldt-Jakob disease, and frontotemporal dementia were the primary neurodegenerative causes, while autoimmune encephalitis, neurosyphilis, and vascular cognitive impairment were the main non-neurodegenerative causes. CONCLUSIONS: The etiology of RPD in Chinese patients is complex, with neurodegenerative and non-neurodegenerative diseases equally prevalent. Recognizing treatable conditions like autoimmune encephalitis and neurosyphilis requires careful consideration and differentiation.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; China; Cognitive Dysfunction; Creutzfeldt-Jakob Syndrome; Dementia; Disease Progression; Encephalitis; Female; Frontotemporal Dementia; Humans; Male; Middle Aged; Neurodegenerative Diseases; Neurosyphilis; Retrospective Studies; Tertiary Care Centers

First Biodistribution Study of [68Ga]Ga-NOTA-Insulin Following Intranasal Administration in Adult Vervet Monkeys. - Solingapuram Sai, Kiran Kumar; Erichsen, Jennifer M; Gollapelli, Krishna K; Krizan, Ivan; Miller, Mack; Bansode, Avinash; Jorgensen, Mathew J; Register, Thomas; Cazzola, Charles; Gandhi, Reenal; Suman, Julie; Craft, Suzanne (J Alzheimers Dis, 2024)
BACKGROUND: Intranasal insulin (INI) is being explored as a treatment for Alzheimer's disease (AD). Improved memory, functional ability, and cerebrospinal fluid (CSF) AD biomarker profiles have been observed following INI administration. However, the method of intranasal delivery may significantly affect outcomes. OBJECTIVE: To show reliable delivery of insulin to the brain using the Aptar Cartridge Pump System (CPS) intranasal delivery system. METHODS: To visualize INI biodistribution, we developed a novel PET radiotracer, Gallium 68-radiolabeled (NOTA-conjugated) insulin, [68Ga]Ga-NOTA-insulin. We used the Aptar CPS to administer [68Ga]Ga-NOTA-insulin to anesthetized healthy adult vervet monkeys and measured brain regional activity and whole-body dosimetry following PET/CT scans. RESULTS: We observed brain penetration of [68Ga]Ga-NOTA-insulin following intranasal administration with the Aptar CPS. Radioactive uptake was seen in multiple regions, including the amygdala, putamen, hypothalamus, hippocampus, and choroid plexus. A safety profile and whole-body dosimetry were also established in a second cohort of vervets. Safety was confirmed: vitals remained stable, blood glucose levels were unchanged, and no organ was exposed to more than 2.5 mSv of radioactivity. Extrapolations from vervet organ distribution allowed for estimation of the [68Ga]Ga-NOTA-insulin absorbed dose in humans, and the maximum dose of [68Ga]Ga-NOTA-insulin that can be safely administered to humans was determined to be 185 MBq. CONCLUSIONS: The use of [68Ga]Ga-NOTA-insulin as a PET radiotracer is safe and effective for observing brain uptake in vervet monkeys. Further, the Aptar CPS successfully targets [68Ga]Ga-NOTA-insulin to the brain. The data will be essential in guiding future studies of intranasal [68Ga]Ga-NOTA-insulin administration in humans.
Keywords: Administration, Intranasal; Animals; Brain; Chlorocebus aethiops; Female; Gallium Radioisotopes; Heterocyclic Compounds; Heterocyclic Compounds, 1-Ring; Insulin; Male; Positron Emission Tomography Computed Tomography; Positron-Emission Tomography; Radiopharmaceuticals; Tissue Distribution

The funnel effect of reserves prompted by leisure activities across the Alzheimer's disease continuum. - Serra, Laura; Bonarota, Sabrina; Di Domenico, Carlotta; Caruso, Giulia; Giulietti, Giovanni; Rizzuti, Martina; Assogna, Martina; Rodini, Marta; Mencarelli, Lucia; Di Lorenzo, Francesco; Koch, Giacomo; Fadda, Lucia; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Reserves' mechanisms explain inconsistencies between accumulation of neuropathological damage and clinical manifestations. Leisure activities are believed to promote reserves. OBJECTIVE: This study evaluates whether cognitive, social, and physical leisure activities performed over life-span predict current cognitive functioning in normal aging and Alzheimer's disease (AD) continuum. METHODS: 35 AD, 24 amnestic-Mild Cognitive Impairment (a-MCI) patients, 21 individuals with subjective cognitive complaint (SCD), and 25 controls underwent a questionnaire developed to quantify leisure activities in different life periods, the Addenbrooke's Cognitive Examination-Revised (ACE-R), and T1-weighted 3T-MRI scans for brain volumetrics and cortical thickness quantification. Partial/total leisure activities' scores and demographic and brain variables were entered as predictors, while ACE-R scores as dependent variables in linear regression analyses. RESULTS: Current level of cognition was predicted by (i) social and physical activities performed in middle age and current cognitive activity in AD; (ii) cognitive and social activities performed in middle age, current age and cortical thickness in a-MCI; (iii) recreational activities the set of lifetime, current age, and brain features in SCD; (iv) education and the set of lifetime leisure activities over lifespan in controls. CONCLUSIONS: This study shows a funnel effect due to gradual reduction of stimulatory activities in the transition from healthy aging to AD. Reserve indices taking into account different types of stimulatory activities allow to capture even smallest residual effects of reserves accumulated over lifespan, until their complete depletion at advanced AD stages. These results may help target tailored interventions during normal and pathological aging.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Brain; Cognition; Cognitive Dysfunction; Cognitive Reserve; Female; Humans; Leisure Activities; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Surveys and Questionnaires

The Inflammation-Induced Dysregulation of Reelin Homeostasis Hypothesis of Alzheimer's Disease. - Reive, Brady S; Lau, Victor; Sánchez-Lafuente, Carla L; Henri-Bhargava, Alexandre; Kalynchuk, Lisa E; Tremblay, Marie-Ève; Caruncho, Hector J (J Alzheimers Dis, 2024)
Alzheimer's disease (AD) accounts for most dementia cases, but we lack a complete understanding of the mechanisms responsible for the core pathology associated with the disease (e.g., amyloid plaque and neurofibrillary tangles). Inflammation has been identified as a key contributor of AD pathology, with recent evidence pointing towards Reelin dysregulation as being associated with inflammation. Here we describe Reelin signaling and outline existing research involving Reelin signaling in AD and inflammation. Research is described pertaining to the inflammatory and immunological functions of Reelin before we propose a mechanism through which inflammation renders Reelin susceptible to dysregulation resulting in the induction and exacerbation of AD pathology. Based on this hypothesis, it is predicted that disorders of both inflammation (including peripheral inflammation and neuroinflammation) and Reelin dysregulation (including disorders associated with upregulated Reelin expression and disorders of Reelin downregulation) have elevated risk of developing AD. We conclude with a description of AD risk in various disorders involving Reelin dysregulation and inflammation.
Keywords: Alzheimer Disease; Animals; Cell Adhesion Molecules, Neuronal; Extracellular Matrix Proteins; Homeostasis; Humans; Inflammation; Nerve Tissue Proteins; Reelin Protein; Serine Endopeptidases; Signal Transduction

Influence of genotype on PCSK9-lipids association in cerebrospinal fluid and serum of patients in the Alzheimer's disease continuum. - Papotti, Bianca; Palumbo, Marcella; Adorni, Maria Pia; Elviri, Lisa; Chiari, Annalisa; Tondelli, Manuela; Bedin, Roberta; Baldelli, Enrica; Lancellotti, Giulia; Lupo, Maria Giovanna; Ferri, Nicola; Bertolotti, Marco; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Alterations in factors involved in cholesterol homeostasis are critical in Alzheimer's disease (AD), but the stage of occurrence, their specific association, and a possible relationship with the genotype are not clarified. OBJECTIVE: We aimed to quantify and correlate specific lipid factors in patients with different degrees of cognitive decline, namely patients with AD and patients with mild cognitive impairment due to AD (MCI-AD), carriers or non-carriers of the genotype. METHODS: We evaluated Proprotein Convertase Subtilisin/Kexin type 9 (PCSK9), cholesterol and the oxidative metabolites 24-, 25-, 27-hydroxycholesterol (HC) in the cerebrospinal fluid (CSF) and serum of AD (n = 28) and MCI-AD (n = 27) patients. RESULTS: CSF and serum PCSK9 and lipids were similar, except for higher serum PCSK9 and triglycerides in MCI-AD compared to AD. In CSF, AD carriers showed higher PCSK9 and 24-HC (+61.3%,  = 0.027 and +32.7%,  = 0.037), compared to non-carriers. There was a negative association between CSF PCSK9 and 27-HC in AD (r = -0.444,  = 0.049) and, exclusively among AD carriers, a negative association between CSF PCSK9 and 24-HC (r = -0.786,  = 0.028). A positive correlation was observed between CSF and serum PCSK9 in AD (r = 0.520,  = 0.004), driven by carriers (r = 0.544,  = 0.038), suggesting PCSK9 exchange between brain and periphery. A positive correlation was detected between serum and CSF 27-HC (r = 0.465,  = 0.039) in AD. None of these results were found in MCI-AD patients. CONCLUSIONS: PCSK9 and 24-HC might be specific markers of ApoE4-associated lipid alterations in AD, possibly contributing to clinical progression in the AD continuum.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Biomarkers; Cholesterol; Cognitive Dysfunction; Female; Genotype; Humans; Lipids; Male; Middle Aged; Proprotein Convertase 9

An Insertion Within SIRPβ1 Shows a Dual Effect Over Alzheimer's Disease Cognitive Decline Altering the Microglial Response. - García-Alberca, José María; de Rojas, Itziar; Sanchez-Mejias, Elisabeth; Garrido-Martín, Diego; Gonzalez-Palma, Laura; Jimenez, Sebastian; Pino-Angeles, Almudena; Cruz-Gamero, Jose Manuel; Mendoza, Silvia; Alarcón-Martín, Emilio; Muñoz-Castro, Clara; Real, Luis Miguel; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Microglial dysfunction plays a causative role in Alzheimer's disease (AD) pathogenesis. Here we focus on a germline insertion/deletion variant mapping SIRPβ1, a surface receptor that triggers amyloid-β(Aβ) phagocytosis via TYROBP. OBJECTIVE: To analyze the impact of this copy-number variant in SIRPβ1 expression and how it affects AD molecular etiology. METHODS: Copy-number variant proxy rs2209313 was evaluated in GERALD and GR@ACE longitudinal series. Hippocampal specimens of genotyped AD patients were also examined. SIRPβ1 isoform-specific phagocytosis assays were performed in HEK393T cells. RESULTS: The insertion alters the SIRPβ1 protein isoform landscape compromising its ability to bind oligomeric Aβ and its affinity for TYROBP. SIRPβ1 Dup/Dup patients with mild cognitive impairment show an increased cerebrospinal fluid t-Tau/Aβ ratio (p = 0.018) and a higher risk to develop AD (OR = 1.678, p = 0.018). MRIs showed that Dup/Dup patients exhibited a worse initial response to AD. At the moment of diagnosis, all patients showed equivalent Mini-Mental State Examination scores. However, AD patients with the duplication had less hippocampal degeneration (p < 0.001) and fewer white matter hyperintensities. In contrast, longitudinal studies indicate that patients bearing the duplication allele show a slower cognitive decline (p = 0.013). Transcriptional analysis also shows that the SIRPβ1 duplication allele correlates with higher TREM2 expression and an increased microglial activation. CONCLUSIONS: The SIRPβ1 internal duplication has opposite effects over MCI-to-Dementia conversion risk and AD progression, affecting microglial response to Aβ. Given the pharmacological approaches focused on the TREM2-TYROBP axis, we believe that SIRPβ1 structural variant might be considered as a potential modulator of this causative pathway.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Humans; Microglia; Phagocytosis; Receptors, Cell Surface

Interaction Between Arteriosclerosis and Amyloid-β on Cognitive Function. - Frentz, Ingeborg; van Arendonk, Joyce; Leeuwis, Anna E; Vernooij, Meike W; van der Flier, Wiesje M; Bos, Daniel; De Deyn, Peter Paul; Wolters, Frank J; Ikram, M Arfan (J Alzheimers Dis, 2024)
BACKGROUND: Dementia is a multifactorial disease, with Alzheimer's disease (AD) and vascular pathology often co-occurring in many individuals with dementia. Yet, the interplay between AD and vascular pathology in cognitive decline is largely undetermined. OBJECTIVE: The aim of the present study was to examine the joint effect of arteriosclerosis and AD pathology on cognition in the general population without dementia. METHODS: We determined the interaction between blood-based AD biomarkers and CT-defined arteriosclerosis on cognition in 2,229 dementia-free participants of the population-based Rotterdam Study (mean age: 68.9 years, 52% women) cross-sectionally. RESULTS: Amyloid-β (Aβ)42 and arterial calcification were associated with cognitive performance. After further adjustment for confounders in a model that combined all biomarkers, only arterial calcification remained independently associated with cognition. There was a significant interaction between arterial calcification and Aβ42 and between arterial calcification and the ratio of Aβ42/40. Yet, estimates attenuated, and interactions were no longer statistically significant after adjustment for cardio metabolic risk factors. CONCLUSIONS: Arteriosclerosis and AD display additive interaction-effects on cognition in the general population, that are due in part to cardio metabolic risk factors. These findings suggest that joint assessment of arteriosclerosis and AD pathology is important for understanding of disease etiology in individuals with cognitive impairment.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Arteriosclerosis; Biomarkers; Cognition; Cognitive Dysfunction; Female; Humans; Male; tau Proteins

Lucidity in the Deeply Forgetful: A Scoping Review. - Ross, John Paul; Post, Stephen G; Scheinfeld, Laurel (J Alzheimers Dis, 2024)
BACKGROUND: Even in severe states of Alzheimer's disease and related dementias (ADRD), accounts of an unexpected or paradoxical return of awareness and lucidity have been reported in some patients, documented formally, and studied. OBJECTIVE: A scoping review was undertaken to survey the literature on the topic. METHODS: Five databases were searched using pertinent search terms. Results were deduplicated and subsequently screened by title and abstract for relevance. Remaining reports were read and included or excluded using specific inclusion criteria. 30 results consisted of a mix of perspective papers, case reports, qualitative surveys of caregivers, law journal comments, and mechanistic speculation. RESULTS: An equal mix of primary and secondary research was identified. CONCLUSIONS: The papers collected in this review provide a valuable methodological outline for researching the topic of lucid episodes in ADRD. The verified legitimacy and simultaneous inexplicability of these events promote philosophical discussion, mechanistic investigations, and sorely needed research in the field of ADRD.
Keywords: Alzheimer Disease; Caregivers; Cognition; Humans

Memory consolidation, temporal and parietal atrophy, and metabolism in amyloid-β positive and negative mild cognitive impairment. - Keith, Cierra M; Haut, Marc W; Vieira Ligo Teixeira, Camila; Mehta, Rashi I; Phelps, Holly; Ward, Melanie; Miller, Mark; Navia, R Osvaldo; Coleman, Michelle M; Marano, Gary; Wang, Xiaofei; Pockl, Stephanie; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is classically characterized by alterations in memory consolidation. With the advent of diagnostic biomarkers, some patients clinically diagnosed with AD display biomarkers inconsistent with the diagnosis. OBJECTIVE: We aimed to explore differences in memory consolidation and neurodegeneration of the temporal and parietal lobes as a function of amyloid-β status in amnestic mild cognitive impairment (aMCI). METHODS: We examined differences in memory consolidation and neurodegeneration between patients diagnosed with amyloid-β positive aMCI (Aβ+ N = 78), amyloid-β negative aMCI (Aβ- N = 48), and healthy participants (HP; N = 41), within a well-characterized clinical cohort. RESULTS: Aβ+ exhibited more pronounced consolidation impairments compared to Aβ-, while Aβ- faced more consolidation challenges than HP. Both Aβ+ and Aβ- were similar in hippocampal volume and entorhinal thickness, but Aβ+ had thinner inferior parietal cortex than Aβ-. Using F-fluoro-deoxyglucose-positron emission tomography, metabolism in both temporal and parietal regions was lower in Aβ+ relative to Aβ-. CONCLUSIONS: These findings suggest pathologies other than AD likely contribute to memory consolidation difficulties in aMCI, and neurodegeneration of the parietal cortex in combination with hypometabolism may contribute to more pronounced consolidation problems in Aβ+.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Atrophy; Cognitive Dysfunction; Female; Fluorodeoxyglucose F18; Humans; Magnetic Resonance Imaging; Male; Memory Consolidation; Middle Aged; Neuropsychological Tests; Parietal Lobe; Positron-Emission Tomography; Temporal Lobe

A Metabolomics Analysis of a Novel Phenotype of Older Adults at Higher Risk of Dementia. - Sultana, Munira; Camicioli, Richard; Dixon, Roger A; Whitehead, Shawn; Pieruccini-Faria, Frederico; Petrotchenko, Evgeniy; Speechley, Mark; Borchers, Christoph H; Montero-Odasso, Manuel (J Alzheimers Dis, 2024)
BACKGROUND: Older adults presenting with dual-decline in cognition and walking speed face a 6-fold higher risk for dementia compared with those showing no decline. We hypothesized that the metabolomics profile of dual-decliners would be unique even before they show signs of decline in cognition and gait speed. OBJECTIVE: The objective of this study was to determine if plasma metabolomics signatures can discriminate dual-decliners from no decliners, purely cognitive decliners, and purely motor decliners prior to decline. METHODS: A retrospective cross-sectional study using baseline plasma for untargeted metabolomics analyses to investigate early signals of later dual-decline status in study participants (n = 76) with convenient sampling. Dual-decline was operationalized as decline in gait speed (>10 cm/s) and cognition (>2 points decline in Montreal Cognitive Assessment score) on at least two consecutive 6-monthly assessments. The participants' decliner status was evaluated 3 years after the blood sample was collected. Pair-wise comparison of detected compounds was completed using principal components and hierarchical clustering analyses. RESULTS: Analyses did not detect any cluster separation in untargeted metabolomes across baseline groups. However, follow-up analyses of specific molecules detected 4 compounds (17-Hydroxy-12-(hydroxymethyl)-10-oxo-8 oxapentacyclomethyl hexopyranoside, Fleroxacin, Oleic acid, and 5xi-11,12-Dihydroxyabieta-8(14),9(11),12-trien-20-oic acid) were at significantly higher concentration among the dual-decliners compared to non-decliners. The pure cognitive decliner group had significantly lower concentration of six compounds (1,3-nonanediol acetate, 4-(2-carboxyethyl)-2-methoxyphenyl beta-D-glucopyranosiduronic acid, oleic acid, 2E-3-[4-(sulfo-oxy)phenyl] acrylic acid, palmitelaidic acid, and myristoleic acid) compared to the non-decliner group. CONCLUSIONS: The unique metabolomics profile of dual-decliners warrants follow-up metabolomics analysis. Results may point to modifiable pathways.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Cross-Sectional Studies; Dementia; Female; Humans; Male; Metabolomics; Phenotype; Retrospective Studies

Mitochondria-Related Candidate Genes and Diagnostic Model to Predict Late-Onset Alzheimer's Disease and Mild Cognitive Impairment. - Yan, Ran; Wang, Wenjing; Yang, Wen; Huang, Masha; Xu, Wei (J Alzheimers Dis, 2024)
BACKGROUND: Late-onset Alzheimer's disease (LOAD) is the most common type of dementia, but its pathogenesis remains unclear, and there is a lack of simple and convenient early diagnostic markers to predict the occurrence. OBJECTIVE: Our study aimed to identify diagnostic candidate genes to predict LOAD by machine learning methods. METHODS: Three publicly available datasets from the Gene Expression Omnibus (GEO) database containing peripheral blood gene expression data for LOAD, mild cognitive impairment (MCI), and controls (CN) were downloaded. Differential expression analysis, the least absolute shrinkage and selection operator (LASSO), and support vector machine recursive feature elimination (SVM-RFE) were used to identify LOAD diagnostic candidate genes. These candidate genes were then validated in the validation group and clinical samples, and a LOAD prediction model was established. RESULTS: LASSO and SVM-RFE analyses identified 3 mitochondria-related genes (MRGs) as candidate genes, including NDUFA1, NDUFS5, and NDUFB3. In the verification of 3 MRGs, the AUC values showed that NDUFA1, NDUFS5 had better predictability. We also verified the candidate MRGs in MCI groups, the AUC values showed good performance. We then used NDUFA1, NDUFS5 and age to build a LOAD diagnostic model and AUC was 0.723. Results of qRT-PCR experiments with clinical blood samples showed that the three candidate genes were expressed significantly lower in the LOAD and MCI groups when compared to CN. CONCLUSION: Two mitochondrial-related candidate genes, NDUFA1 and NDUFS5, were identified as diagnostic markers for LOAD and MCI. Combining these two candidate genes with age, a LOAD diagnostic prediction model was successfully constructed.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Female; Humans; Male; Mitochondria; Support Vector Machine

Neural Computation-Based Methods for the Early Diagnosis and Prognosis of Alzheimer's Disease Not Using Neuroimaging Biomarkers: A Systematic Review. - Cabrera-León, Ylermi; Báez, Patricio García; Fernández-López, Pablo; Suárez-Araujo, Carmen Paz (J Alzheimers Dis, 2024)
BACKGROUND: The growing number of older adults in recent decades has led to more prevalent geriatric diseases, such as strokes and dementia. Therefore, Alzheimer's disease (AD), as the most common type of dementia, has become more frequent too. BACKGROUND: Objective: The goals of this work are to present state-of-the-art studies focused on the automatic diagnosis and prognosis of AD and its early stages, mainly mild cognitive impairment, and predicting how the research on this topic may change in the future. METHODS: Articles found in the existing literature needed to fulfill several selection criteria. Among others, their classification methods were based on artificial neural networks (ANNs), including deep learning, and data not from brain signals or neuroimaging techniques were used. Considering our selection criteria, 42 articles published in the last decade were finally selected. RESULTS: The most medically significant results are shown. Similar quantities of articles based on shallow and deep ANNs were found. Recurrent neural networks and transformers were common with speech or in longitudinal studies. Convolutional neural networks (CNNs) were popular with gait or combined with others in modular approaches. Above one third of the cross-sectional studies utilized multimodal data. Non-public datasets were frequently used in cross-sectional studies, whereas the opposite in longitudinal ones. The most popular databases were indicated, which will be helpful for future researchers in this field. CONCLUSIONS: The introduction of CNNs in the last decade and their superb results with neuroimaging data did not negatively affect the usage of other modalities. In fact, new ones emerged.
Keywords: Alzheimer Disease; Biomarkers; Cognitive Dysfunction; Deep Learning; Early Diagnosis; Humans; Neural Networks, Computer; Neuroimaging; Prognosis

The Neuro-Inflammatory Microenvironment: An Important Regulator of Stem Cell Survival in Alzheimer's Disease. - Shen, Zhiwei; Yang, Xinyi; Lan, Yulong; Chen, Gao (J Alzheimers Dis, 2024)
Alzheimer's disease (AD) is the most common neurodegenerative disease, characterized by progressive memory loss and cognitive impairment due to excessive accumulation of extracellular amyloid-β plaques and intracellular neurofibrillary tangles. Although decades of research efforts have been put into developing disease-modifying therapies for AD, no "curative" drug has been identified. As a central player in neuro-inflammation, microglia play a key role inbrain homeostasis by phagocytosing debris and regulating the balance between neurotoxic and neuroprotective events. Typically, the neurotoxic phenotype of activated microglia is predominant in the impaired microenvironment of AD. Accordingly, transitioning the activity state of microglia from pro-inflammatory to anti-inflammatory can restore the disrupted homeostatic microenvironment. Recently, stem cell therapy holds great promise as a treatment for AD; however, the diminished survival of transplanted stem cells has resulted in a disappointing long-term outcome for this treatment. This article reviews the functional changes of microglia through the course of AD-associated homeostatic deterioration. We summarize the possible microglia-associated therapeutic targets including TREM2, IL-3Rα, CD22, C5aR1, CX3CR1, P2X7R, CD33, Nrf2, PPAR-γ, CSF1R, and NLRP3, each of which has been discussed in detail. The goal of this review is to put forth the notion that microglia could be targeted by either small molecules or biologics to make the brain microenvironment more amenable to stem cell implantation and propose a novel treatment strategy for future stem cell interventions in AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Cell Survival; Humans; Inflammation; Microglia; Neurodegenerative Diseases

Odor Identification Across Time in Mutation Carriers and Non-Carriers in Autosomal-Dominant Alzheimer's Disease. - Almkvist, Ove; Larsson, Maria; Graff, Caroline (J Alzheimers Dis, 2024)
BACKGROUND: Impaired odor identification is a characteristic of sporadic Alzheimer'sdisease(AD), but its presence in autosomal-dominantAD (adAD) remains uncertain. OBJECTIVE: To investigate odor identification ability in mutation carriers (MC) and non-carriers (NC) of adAD in relation to years to estimated clinical onset clinical onset (YECO) of disease. METHODS: Participants from six families with autosomal-dominant mutations (APP Swedish, APP Arctic, and PSEN1 mutations) included 20 MC and 20 NC. The groups were comparable in age, gender, education, number of APOE ɛ4 alleles, and YECO, but differed in global cognition (Mini-Mental State Examination). The MC group included individuals in asymptomatic, symptomatic cognitively unimpaired, mild cognitive impairment, and dementia stages of disease, spanning approximately 40 years of the AD continuum. All NC were asymptomatic. Olfactory function was assessed by means of free and cued identification of common odors summarized as total identification. RESULTS: MC performed poorer than NC in free and total identification. Four MC and none of the NC were anosmic. Olfactory functions in MC and NC were significantly and inversely related to time course (YECO) for both free and total identification. The decline in free identification began approximately 10 years prior to the estimated clinical onset of AD in MC. Odor identification proficiency was associated with episodic memory and executive function in MC and NC. CONCLUSIONS: Impaired odor identification is present well before the clinical diagnosis of AD in MC and is associated with disease progression. Odor identification ability may be a useful early biomarker for adAD.
Keywords: Alzheimer Disease; Cognition; Cognitive Dysfunction; Humans; Mutation; Odorants; Presenilin-1

Optimizing the Implementation of a Lifestyle Dementia Prevention Intervention for Older Patients in an Academic Healthcare System. - Mace, Ryan A; Lyons, Christopher; Cohen, Joshua E; Ritchie, Christine; Bartels, Stephen; Okereke, Olivia I; Hoeppner, Bettina B; Brewer, Judson A; Vranceanu, Ana-Maria (J Alzheimers Dis, 2024)
BACKGROUND: Interventions that promote healthy lifestyles are critical for the prevention of Alzheimer's disease and Alzheimer's disease related dementias (AD/ADRD). However, knowledge of the best practices for implementing AD/ADRD prevention in healthcare settings remains limited. OBJECTIVE: We aimed to qualitatively identify barriers and facilitators to implementing a clinical trial of a novel lifestyle intervention (My Healthy Brain) in our medical center for older patients with subjective cognitive decline who are at-risk for AD/ADRD. METHODS: We conducted focus groups with 26 healthcare professionals (e.g., physicians, psychology, nursing) from 5 clinics that treat older patients (e.g., memory care, psychiatry). Our qualitative analysis integrated two implementation frameworks to systematically capture barriers and facilitators to AD/ADRD prevention (Consolidated Framework for Implementation Science Research) that impact implementation outcomes of acceptability, appropriateness, and feasibility (Proctor's framework). RESULTS: We found widespread support for an RCT of My Healthy Brain and AD/ADRD prevention. Participants identified barriers related to patients (stigma, technological skills), providers (dismissiveness of "worried well," doubting capacity for behavior change), clinics (limited time and resources), and the larger healthcare system (underemphasis on prevention). Implementation strategies guided by Expert Recommendations for Implementing Change (ERIC) included: developing tailored materials, training staff, obtaining buy-in from leadership, addressing stigmatized language and practices, identifying "champions," and integrating with workflows and resources. CONCLUSIONS: The results will inform our recruitment, enrollment, and retention procedures to implement the first randomized clinical trial of My Healthy Brain. Our study provides a blueprint for addressing multi-level barriers to the implementation of AD/ADRD prevention for older patients in medical settings.
Keywords: Academic Medical Centers; Aged; Alzheimer Disease; Cognitive Dysfunction; Dementia; Female; Focus Groups; Health Personnel; Humans; Life Style; Male

Palliative Care in Nursing Home Residents with Young-Onset Dementia: Professional and Family Caregiver Perspectives. - Maters, Jasper; van der Steen, Jenny T; de Vugt, Marjolein E; Bakker, Christian; Koopmans, Raymond T C M (J Alzheimers Dis, 2024)
BACKGROUND: The evidence underpinning palliative care in dementia is mostly based on research in older populations. Little is known about the palliative care needs of people with young-onset dementia (YOD). OBJECTIVE: To describe palliative care practices including advance care planning (ACP) in people with YOD residing in Dutch nursing homes. METHODS: The study presents baseline questionnaire data from an observational cohort study. Physicians, family caregivers, and nursing staff completed questionnaires about 185 residents with YOD. The questionnaires included items on sociodemographics, quality of life measured with the quality of life in late-stage dementia (QUALID) scale, dementia-related somatic health problems, symptoms, pain medication, psychotropic drugs, and ACP. RESULTS: The mean age was 63.9 (SD 5.8) years. Half (50.3%) of them were female. Alzheimer's disease dementia (42.2%) was the most prevalent subtype. The mean QUALID score was 24.0 (SD 7.9) as assessed by family caregivers, and 25.3 (SD 8.6) as assessed by the nursing staff. Swallowing problems were the most prevalent dementia-related health problem (11.4%). Agitation was often reported by physicians (42.0%) and nursing staff (40.5%). Psychotropics were prescribed frequently (72.3%). A minority had written advance directives (5.4%) or documentation on treatment preferences by the former general practitioner (27.2%). Global care goals most often focused on comfort (73.9%). Proportions of do-not-treat orders were higher than do-treat orders for all interventions except for hospitalization and antibiotics. CONCLUSIONS: ACP must be initiated earlier, before nursing home admission. A palliative approach seems appropriate even though residents are relatively young and experience few dementia-related health problems.
Keywords: Aged; Alzheimer Disease; Caregivers; Dementia; Female; Humans; Male; Nursing Homes; Palliative Care; Quality of Life

Plasma BDNF/Irisin Ratio Associates with Cognitive Function in Older People. - Huang, Xiuxiu; Wang, Jiaxin; Zhang, Shifang; Zhao, Xiaoyan; An, Ran; Lan, Yue; Yi, Ming; Wan, Qiaoqin (J Alzheimers Dis, 2024)
BACKGROUND: Reliable blood biomarkers are crucial for early detection and treatment evaluation of cognitive impairment, including Alzheimer's disease and other dementias. OBJECTIVE: To examine whether plasma biomarkers and their combination are different between older people with mild cognitive impairment (MCI) and cognitively normal individuals, and to explore their relations with cognitive performance. METHODS: This cross-sectional study included 250 older adults, including 124 participants with MCI, and 126 cognitively normal participants. Plasma brain-derived neurotrophic factor (BDNF), irisin and clusterin were measured, and BDNF/irisin ratio was calculated. Global cognition was evaluated by the Montreal Cognitive Assessment. RESULTS: Plasma irisin levels, but not BDNF, were significantly different between MCI group and cognitively normal group. Higher irisin concentration was associated with an increased probability for MCI both before and after controlling covariates. By contrast, plasma BDNF concentration, but not irisin, was linearly correlated with cognitive performance after adjusting for covariates. Higher BDNF/irisin ratios were not only correlated with better cognitive performance, but also associated with lower risks of MCI, no matter whether we adjusted for covariates. Plasma BDNF and irisin concentrations increased with aging, whereas BDNF/irisin ratios remained stable. No significant results of clusterin were observed. CONCLUSIONS: Plasma BDNF/irisin ratio may be a reliable indicator which not only reflects the odds of the presence of MCI but also directly associates with cognitive performance.
Keywords: Aged; Aged, 80 and over; Aging; Biomarkers; Brain-Derived Neurotrophic Factor; Clusterin; Cognition; Cognitive Dysfunction; Cross-Sectional Studies; Female; Fibronectins; Humans; Male; Mental Status and Dementia Tests; Neuropsychological Tests

Potential Impact of Slowing Disease Progression in Early Symptomatic Alzheimer's Disease on Patient Quality of Life, Caregiver Time, and Total Societal Costs: Estimates Based on Findings from GERAS-US Study. - Chandler, Julie M; Ye, Wenyu; Mi, Xiaojuan; Doty, Erin G; Johnston, Joseph A (J Alzheimers Dis, 2024)
BACKGROUND: Impact of Alzheimer's disease (AD) progression on patient health-related quality of life (HRQoL), caregiver time, and societal costs is not well characterized in early AD. OBJECTIVE: To assess the association of change in cognition with HRQoL, caregiver time, and societal costs over 36 months, and estimate the impact of slowing disease progression on these outcomes. METHODS: This post-hoc analysis included patients with amyloid-positive mild cognitive impairment (MCI) and mild AD dementia (MILD AD) from the 36-month GERAS-US study. Disease progression was assessed using the Mini-Mental State Examination score. Change in outcomes associated with slowing AD progression was estimated using coefficients from generalized linear models. RESULTS: At baseline, 300 patients had MCI and 317 had MILD AD. Observed natural progression over 36 months was associated with: 5.1 point decline in the Bath Assessment of Subjective Quality of Life in Dementia (BASQID) score (for HRQoL), increase in 1,050 hours of total caregiver time, and $8,504 total societal costs for MCI; 6.6 point decline in the BASQID score, increase in 1,929 hours of total caregiver time, and $12,795 total societal costs for MILD AD per person. Slowing AD progression by 30% could result in per person savings in HRQoL decline, total caregiver time, and total societal costs: for MCI: 1.5 points, 315 hours, and $2,638; for MILD AD: 2.0 points, 579 hours, and $3,974. CONCLUSIONS: Slowing AD progression over 36 months could slow decline in HRQoL and save caregiver time and societal cost in patients with MCI and MILD AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Caregivers; Cognitive Dysfunction; Cost of Illness; Disease Progression; Female; Humans; Male; Mental Status and Dementia Tests; Quality of Life; United States

Pre-existing dementia is associated with 2-3 folds risk for in-hospital mortality and complications after intracerebral hemorrhage stroke. - Zuo, Lijun; Hu, Yang; Dong, YanHong; Seet, Raymond Cs; Li, Zixiao; Wang, Yongjun; Zhao, Xingquan (J Alzheimers Dis, 2024)
BACKGROUND: Pre-existing dementia was related to poor functional outcome after intracerebral hemorrhage (ICH), and its commonly underlying pathologies were considered as cerebral amyloid angiopathy. But the impact of pre-existing dementia on in-hospital mortality in Chinese ICH patients has not been well characterized. OBJECTIVE: To investigate the association between pre-existing dementia and in-hospital mortality after ICH. METHODS: Data were extracted from the China Stroke Center Alliance database. Information about the existence of prior to stroke dementia was obtained from next of kin informants and registered in clinical charts. Patients' characteristics, in-hospital mortality, home discharge and complications were compared between ICH patients with and without pre-existing dementia. RESULTS: Out of the 72,318 ICH patients, we identified 328 patients with pre-existing dementia. Patients with pre-existing dementia were more likely to experience greater stroke severity as measured by the National Institute of Health Stroke Scale and Glasgow Coma Scale. In the adjusted models, the presence of pre-existing dementia was associated with an increased risk of in-hospital mortality (OR 2.31, 95% CI 1.12-4.77), more frequent in-hospital complications of pulmonary embolism (OR 5.41, 95% CI 1.16-25.14), pneumonia (OR 1.58, 95% CI 1.08-2.33), urinary tract infection (OR 2.37, 95% CI 1.21-4.64), gastrointestinal bleeding (OR 2.39, 95% CI 1.27-4.49) and lower home discharge (OR 0.59, 95% CI 0.38∼0.93). CONCLUSIONS: ICH patients with pre-existing dementia are more likely to suffer from greater stroke severity, poorer outcomes and lower home discharge. Future studies should evaluate the value of intensive risk factor control among individuals with pre-existing dementia for stroke prevention.
Keywords: Aged; Aged, 80 and over; Cerebral Hemorrhage; China; Dementia; Female; Hemorrhagic Stroke; Hospital Mortality; Humans; Male; Middle Aged; Risk Factors; Stroke

Primary cortical cell tri-culture to study effects of amyloid-β on microglia function and neuroinflammatory response. - Kim, Hyehyun; Le, Bryan; Goshi, Noah; Zhu, Kan; Grodzki, Ana Cristina; Lein, Pamela J; Zhao, Min; Seker, Erkin (J Alzheimers Dis, 2024)
BACKGROUND: Microglia play a critical role in neurodegenerative disorders, such as Alzheimer's disease, where alterations in microglial function may result in pathogenic amyloid-β (Aβ) accumulation, chronic neuroinflammation, and deleterious effects on neuronal function. However, studying these complex factors in vivo, where numerous confounding processes exist, is challenging, and until recently, in vitro models have not allowed sustained culture of critical cell types in the same culture. OBJECTIVE: We employed a rat primary tri-culture (neurons, astrocytes, and microglia) model and compared it to co-culture (neurons and astrocytes) and mono-culture (microglia) to study microglial function (i.e., motility and Aβ clearance) and proteomic response to exogenous Aβ. METHODS: The cultures were exposed to fluorescently-labeled Aβ (FITC-Aβ) particles for varying durations. Epifluorescence microscopy images were analyzed to quantify the number of FITC-Aβ particles and assess cytomorphological features. Cytokine profiles from conditioned media were obtained. Live-cell imaging was employed to extract microglia motility parameters. RESULTS: FITC-Aβ particles were more effectively cleared in the tri-culture compared to the co-culture. This was attributed to microglia engulfing FITC-Aβ particles, as confirmed via epifluorescence and confocal microscopy. FITC-Aβ treatment significantly increased microglia size, but had no significant effect on neuronal surface coverage or astrocyte size. Upon FITC-Aβ treatment, there was a significant increase in proinflammatory cytokines in tri-culture, but not in co-culture. Aβ treatment altered microglia motility evident as a swarming-like motion. CONCLUSIONS: The results suggest that neuron-astrocyte-microglia interactions influence microglia function and highlight the utility of the tri-culture model for studies of neuroinflammation, neurodegeneration, and cell-cell communication.
Keywords: Amyloid beta-Peptides; Animals; Astrocytes; Cells, Cultured; Cerebral Cortex; Coculture Techniques; Cytokines; Microglia; Neuroinflammatory Diseases; Neurons; Rats; Rats, Sprague-Dawley

Regional differences in glucose metabolic decline and tau deposition in the Alzheimer's continuum brain. - Ishii, Kazunari; Yamada, Takahiro; Hanaoka, Kohei; Kaida, Hayato; Kojita, Yasuyuki; Kono, Atsushi; Hanada, Kazushi; Saigoh, Kazumasa; Sakuta, Shizuka; Hashimoto, Mamoru; Kato, Takashi; Nakamura, Akinori (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is characterized by the accumulation of amyloid-β and tau proteins, leading to neurofibrillary tangles. A biomarker-based diagnostic method called the ATN system categorizes AD pathology into amyloid-β (A), tau (T), and neurodegeneration (N). The relationship between regional tau deposition and reduced glucose metabolism in the preclinical AD stage is not well understood. OBJECTIVE: We presented voxel-by-voxel metabolic/tau deposition ratio (MTR) images to investigate the effects of tau deposition on metabolism in AD brains on a stage-by-stage basis. METHODS: We selected 174 subjects who underwent 3D-MRI, FDG-PET, amyloid PET, and tau PET scans. MTR images were created by normalizing FDG-PET toMK6240 PET images. Voxel-wise comparisons among 63 cognitively normal amyloid-negative (CNA) subjects, 49 subjects with AD dementia (ADD), 23 subjects with mild cognitive impairment due to AD (MCA), and 39 preclinical AD (PRC) subjects were conducted. RESULTS: There was reduced glucose metabolism in ADD and MCA groups compared to CNA, predominantly in parietotemporal areas. Tau deposition was observed in wider areas in ADD and restricted to the medial temporal lobes in MCA. MTR exhibited significant reductions in broader regions in ADD and MCA, indicating simultaneous glucose metabolism decrease and tau deposition. At the MCA and PRC stages, glucose metabolism impairment and tau deposition were shown in separate regions by FDG PET and tau PET, respectively, while MTR images showed impairment in both regions. CONCLUSIONS: Our findings suggest that MTR imaging provides insights into AD pathophysiology by simultaneously assessing glucose metabolism and tau deposition. In the early stage of the AD continuum (MCA and PRC), metabolic decline and tau deposition occur independently in different brain regions.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Brain; Cognitive Dysfunction; Female; Fluorodeoxyglucose F18; Glucose; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Positron-Emission Tomography; tau Proteins

Research Participants' Perspectives on Precision Diagnostics for Alzheimer's Disease. - Smith, Hadley Stevens; Robinson, Jill O; Levchenko, Ariel; Pereira, Stacey; Pascual, Belen; Bradbury, Kathleen; Arbones, Victoria; Fong, Jamie; Shulman, Joshua M; McGuire, Amy L; Masdeu, Joseph (J Alzheimers Dis, 2024)
BACKGROUND: Understanding research participants' responses to learning Alzheimer's disease (AD) risk information is important to inform clinical implementation of precision diagnostics given rapid advances in disease modifying therapies. OBJECTIVE: We assessed participants' perspectives on the meaning of their amyloid positron emission tomography (PET) imaging results for their health, self-efficacy to understand their results, psychological impact of learning their results, experience receiving their results from the clinical team, and interest in genetic testing for AD risk. METHODS: We surveyed individuals who were being clinically evaluated for AD and received PET imaging six weeks after the return of results. We analyzed responses to close-ended survey items by PET result using Fisher's exact test and qualitatively coded open-ended responses. RESULTS: A total of 88 participants completed surveys, most of whom had mild cognitive impairment due to AD (38.6%), AD (28.4%), or were cognitively unimpaired (21.6%). Participants subjectively understood their results (25.3% strongly agreed, 41.8% agreed), which could help them plan (16.5% strongly agreed, 49.4% agreed). Participants with a negative PET result (n = 25) reported feelings of relief (Fisher's exact p < 0.001) and happiness (p < 0.001) more frequently than those with a positive result. Most participants felt that they were treated respectfully and were comfortable voicing concerns during the disclosure process. Genetic testing was anticipated to be useful for medical care decisions (48.2%) and to inform family members about AD risk (42.9%). CONCLUSIONS: Participants had high subjective understanding and self-efficacy around their PET results and did not experience negative psychological effects. Interest in genetic testing was high.
Keywords: Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Cognitive Dysfunction; Emotions; Humans; Positron-Emission Tomography

The RESIST Study: Examining Cognitive Change in Rheumatoid Arthritis Patients with Mild Cognitive Impairment Being Treated with a TNF-Inhibitor Compared to a Conventional Synthetic Disease-Modifying Anti-Rheumatic Drug. - Marr, Calum; McDowell, Bethany; Holmes, Clive; Edwards, Christopher J; Cardwell, Christopher; McHenry, Michelle; Meenagh, Gary; Teeling, Jessica L; McGuinness, Bernadette (J Alzheimers Dis, 2024)
BACKGROUND: Evidence suggests that TNF inhibitors (TNFi) used to treat rheumatoid arthritis (RA) may protect against Alzheimer's disease progression by reducing inflammation. OBJECTIVE: To investigate whether RA patients with mild cognitive impairment (MCI) being treated with a TNFi show slower cognitive decline than those being treated with a conventional synthetic disease-modifying anti-rheumatic drug (csDMARD). METHODS: 251 participants with RA and MCI taking either a csDMARD (N = 157) or a TNFi (N = 94) completed cognitive assessments at baseline and 6-month intervals for 18 months. It was hypothesized that those taking TNFis would show less decline on the primary outcome of Free and Cued Selective Reminding Test with Immediate Recall (FCSRT-IR) and the secondary outcome of Montreal Cognitive Assessment (MoCA). RESULTS: No significant changes in FCSRT-IR scores were observed in either treatment group. There was no significant difference in FCSRT-IR between treatment groups at 18 months after adjusting for baseline (mean difference = 0.5, 95% CI = -1.3, 2.3). There was also no difference in MoCA score (mean difference = 0.4, 95% CI = -0.4, 1.3). CONCLUSIONS: There was no cognitive decline in participants with MCI being treated with TNFis and csDMARDs, raising the possibility both classes of drug may be protective. Future studies should consider whether controlling inflammatory diseases using any approach is more important than a specific therapeutic intervention.
Keywords: Aged; Antirheumatic Agents; Arthritis, Rheumatoid; Cognitive Dysfunction; Female; Humans; Male; Mental Status and Dementia Tests; Middle Aged; Neuropsychological Tests; Tumor Necrosis Factor Inhibitors; Tumor Necrosis Factor-alpha

Senescence Targeting Methods Impact Alzheimer's Disease Features in 3xTg Mice. - Ng, Pei Y; Zhang, Cheng; Li, Hu; Baker, Darren J (J Alzheimers Dis, 2024)
BACKGROUND: Cellular senescence has been associated with neurodegenerative disease and clearance of senescent cells using genetic or pharmaceutical strategies (senolytics) has demonstrated beneficial effects in mouse models investigating individual disease etiologies of Alzheimer's disease (AD). However, it has remained unclear if senescent cell clearance in a mouse model exhibiting both plaque and tau pathologies modifies the disease state (3xTg). OBJECTIVE: To investigate the effects of senescent cell clearance in the 3xTg mouse model. METHODS: 3xTg mice were treated with senolytics (ABT263 (navitoclax; NAVI), a combination of dasatinib and quercetin (D+Q)), or subjected to transgene-mediated removal of p16-expressing cells (via INK-ATTAC). RESULTS: Senolytic treatments consistently reduced microgliosis and ameliorated both amyloid and tau pathology in 3xTg mice. Using RNA sequencing, we found evidence that synaptic dysfunction and neuroinflammation were attenuated with treatment. These beneficial effects were not observed with short-term senolytic treatment in mice with more advanced disease. CONCLUSIONS: Overall, our results further corroborate the beneficial effects senescent cell clearance could have on AD and highlight the importance of early intervention for the treatment of this debilitating disease.
Keywords: Alzheimer Disease; Animals; Cellular Senescence; Disease Models, Animal; Mice; Mice, Transgenic; Neurodegenerative Diseases; Senotherapeutics; tau Proteins

Sex and Sleep Disruption as Contributing Factors in Alzheimer's Disease. - Johnson, Carrie E; Duncan, Marilyn J; Murphy, M Paul (J Alzheimers Dis, 2024)
Alzheimer's disease (AD) affects more women than men, with women throughout the menopausal transition potentially being the most under researched and at-risk group. Sleep disruptions, which are an established risk factor for AD, increase in prevalence with normal aging and are exacerbated in women during menopause. Sex differences showing more disrupted sleep patterns and increased AD pathology in women and female animal models have been established in literature, with much emphasis placed on loss of circulating gonadal hormones with age. Interestingly, increases in gonadotropins such as follicle stimulating hormone are emerging to be a major contributor to AD pathogenesis and may also play a role in sleep disruption, perhaps in combination with other lesser studied hormones. Several sleep influencing regions of the brain appear to be affected early in AD progression and some may exhibit sexual dimorphisms that may contribute to increased sleep disruptions in women with age. Additionally, some of the most common sleep disorders, as well as multiple health conditions that impair sleep quality, are more prevalent and more severe in women. These conditions are often comorbid with AD and have bi-directional relationships that contribute synergistically to cognitive decline and neuropathology. The association during aging of increased sleep disruption and sleep disorders, dramatic hormonal changes during and after menopause, and increased AD pathology may be interacting and contributing factors that lead to the increased number of women living with AD.
Keywords: Alzheimer Disease; Animals; Cross-Sectional Studies; Female; Humans; Male; Multimorbidity; Sex Factors; Sleep; Sleep Wake Disorders

Short-Term Practice Effects on Cognitive Tests Across the Late Life Cognitive Spectrum and How They Compare to Biomarkers of Alzheimer's Disease. - Duff, Kevin; Hammers, Dustin B; Koppelmans, Vincent; King, Jace B; Hoffman, John M (J Alzheimers Dis, 2024)
BACKGROUND: Practice effects on cognitive testing in mild cognitive impairment (MCI) and Alzheimer's disease (AD) remain understudied, especially with how they compare to biomarkers of AD. OBJECTIVE: The current study sought to add to this growing literature. METHODS: Cognitively intact older adults (n = 68), those with amnestic MCI (n = 52), and those with mild AD (n = 45) completed a brief battery of cognitive tests at baseline and again after one week, and they also completed a baseline amyloid PET scan, a baseline MRI, and a baseline blood draw to obtain APOE ɛ4 status. RESULTS: The intact participants showed significantly larger baseline cognitive scores and practice effects than the other two groups on overall composite measures. Those with MCI showed significantly larger baseline scores and practice effects than AD participants on the composite. For amyloid deposition, the intact participants had significantly less tracer uptake, whereas MCI and AD participants were comparable. For total hippocampal volumes, all three groups were significantly different in the expected direction (intact > MCI > AD). For APOE ɛ4, the intact had significantly fewer copies of ɛ4 than MCI and AD. The effect sizes of the baseline cognitive scores and practice effects were comparable, and they were significantly larger than effect sizes of biomarkers in 7 of the 9 comparisons. CONCLUSION: Baseline cognition and short-term practice effects appear to be sensitive markers in late life cognitive disorders, as they separated groups better than commonly-used biomarkers in AD. Further development of baseline cognition and short-term practice effects as tools for clinical diagnosis, prognostic indication, and enrichment of clinical trials seems warranted.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Biomarkers; Cognition; Cognitive Dysfunction; Female; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Positron-Emission Tomography; Practice, Psychological

Sleep Biomarkers for Predicting Cognitive Decline and Alzheimer's Disease: A Systematic Review of Longitudinal Studies. - Carpi, Matteo; Fernandes, Mariana; Mercuri, Nicola Biagio; Liguori, Claudio (J Alzheimers Dis, 2024)
BACKGROUND: Sleep disturbances are considered a hallmark of dementia, and strong evidence supports the association between alterations in sleep parameters and cognitive decline in patients with mild cognitive impairment and Alzheimer's disease (AD). OBJECTIVE: This systematic review aims to summarize the existing evidence on the longitudinal association between sleep parameters and cognitive decline, with the goal of identifying potential sleep biomarkers of AD-related neurodegeneration. METHODS: Literature search was conducted in PubMed, Web of Science, and Scopus databases from inception to 28 March 2023. Longitudinal studies investigating the association between baseline objectively-measured sleep parameters and cognitive decline were assessed for eligibility. RESULTS: Seventeen studies were included in the qualitative synthesis. Sleep fragmentation, reduced sleep efficiency, reduced REM sleep, increased light sleep, and sleep-disordered breathing were identified as predictors of cognitive decline. Sleep duration exhibited a U-shaped relation with subsequent neurodegeneration. Additionally, several sleep microstructural parameters were associated with cognitive decline, although inconsistencies were observed across studies. CONCLUSIONS: These findings suggest that sleep alterations hold promise as early biomarker of cognitive decline, but the current evidence is limited due to substantial methodological heterogeneity among studies. Further research is necessary to identify the most reliable sleep parameters for predicting cognitive impairment and AD, and to investigate interventions targeting sleep that can assist clinicians in the early recognition and treatment of cognitive decline. Standardized procedures for longitudinal studies evaluating sleep and cognition should be developed and the use of continuous sleep monitoring techniques, such as actigraphy or EEG headband, might be encouraged.
Keywords: Alzheimer Disease; Biomarkers; Cognition; Cognitive Dysfunction; Humans; Longitudinal Studies; Sleep

The Standardized Extract of Centella asiatica and Its Fractions Exert Antioxidative and Anti-Neuroinflammatory Effects on Microglial Cells and Regulate the Nrf2/HO-1 Signaling Pathway. - Hambali, Aqilah; Jusril, Nor Atiqah; Md Hashim, Nur Fariesha; Abd Manan, Nizar; Adam, Siti Khadijah; Mehat, Muhammad Zulfadli; Adenan, Mohd Ilham; Stanslas, Johnson; Abdul Hamid, Hafizah (J Alzheimers Dis, 2024)
BACKGROUND: Neuroinflammation and oxidative stress can aggravate the progression of Alzheimer's disease (AD). Centella asiatica has been traditionally consumed for memory and cognition. The triterpenes (asiaticoside, madecassoside, asiatic acid, madecassic acid) have been standardized in the ethanolic extract of Centella asiatica (SECA). The bioactivity of the triterpenes in different solvent polarities of SECA is still unknown. OBJECTIVE: In this study, the antioxidative and anti-neuroinflammatory effects of SECA and its fractions were explored on lipopolysaccharides (LPS)-induced microglial cells. METHODS: HPLC measured the four triterpenes in SECA and its fractions. SECA and its fractions were tested for cytotoxicity on microglial cells using MTT assay. NO, pro-inflammatory cytokines (TNF-α, IL-6, IL-1β), ROS, and MDA (lipid peroxidation) produced by LPS-induced microglial cells were measured by colorimetric assays and ELISA. Nrf2 and HO-1 protein expressions were measured using western blotting. RESULTS: The SECA and its fractions were non-toxic to BV2 microglial cells at tested concentrations. The levels of NO, TNF-α, IL-6, ROS, and lipid peroxidation in LPS-induced BV2 microglial cells were significantly reduced (p < 0.001) by SECA and its fractions. SECA and some of its fractions can activate the Nrf2/HO-1 signaling pathway by significantly enhancing (p < 0.05) the Nrf2 and HO-1 protein expressions. CONCLUSIONS: This study suggests that the inhibitory activity of SECA and its fractions on pro-inflammatory and oxidative stress events may be the result of the activation of antioxidant defense systems. The potential of SECA and its fractions in reducing neuroinflammation and oxidative stress can be further studied as a potential therapeutic strategy for AD.
Keywords: Animals; Anti-Inflammatory Agents; Antioxidants; Cell Line; Centella; Heme Oxygenase-1; Lipopolysaccharides; Membrane Proteins; Mice; Microglia; Neuroinflammatory Diseases; NF-E2-Related Factor 2; Oxidative Stress; Plant Extracts; Signal Transduction; Triterpenes

Targeting Caspases 3/6 and Cathepsins L/B May Decrease Laminopathy-Induced Apoptosis in Alzheimer's Disease. - Rustamzadeh, Auob; Tafakhori, Abbas; Ariaei, Armin; Heydari, Mahdi; Shah-Abadi, Mehran Ebrahimi; Seif, Farhad (J Alzheimers Dis, 2024)
BACKGROUND: Laminopathy is a pathological manifestation observed in Alzheimer's disease (AD), leading to neuronal apoptosis. OBJECTIVE: Our objective was to assess inhibitors of enzymes involved in laminopathy. METHODS: The mRNA expression of the cathepsins L and B, caspases 3 and 6, lamins b1 and b2, granzymes A and B, and lamins A and C were extracted and analyzed from GSE5281 and GSE28146 datasets. A total of 145 ligands were selected for molecular docking. Subsequently, 10 ns and 100 ns atomistic molecular dynamics (MD) and Martini 3 were performed with NAMD for two selected ligands (PubChem id: 608841 and ChEMBL id: 550872). RESULTS: The mRNA expression level highlighted caspase 6 and lamin A/C upregulation in the hippocampus of the AD samples, in contrast to cathepsin B, lamin b2, and caspase 3. Moreover, there was a strong correlation between the expression level of cathepsin B, lamin A/C, and caspase 6 in the AD group. The MD results suggested molecule with ChEMBL id of 550872 had higher free binding energy, while in longer simulation the molecule with PubChem id of 608841 was suggested to be more stable in complex with the receptor. CONCLUSIONS: Our findings suggest that lamins A/C, cathepsins B/L, caspase 6, and lamin B2 are associated with laminopathy as potential factors contributing to apoptosis in AD. We propose that simultaneous inhibition of caspases 6 and cathepsins L may decrease the rate of apoptosis triggered by lamin degradation. Nevertheless, further studies are required to confirm these observations due to the lack of in vivo findings.
Keywords: Alzheimer Disease; Apoptosis; Caspase 3; Caspase 6; Cathepsin B; Cathepsin L; Hippocampus; Humans; Lamin Type A; Laminopathies; Male; Molecular Docking Simulation

Tau Immunotherapies for Alzheimer's Disease and Related Tauopathies: Status of Trials and Insights from Preclinical Studies. - Sigurdsson, Einar M (J Alzheimers Dis, 2024)
The tau protein undergoes pathological changes in Alzheimer's disease and other tauopathies that eventually lead to functional impairments. Over the years, several therapeutic approaches have been examined to slow or halt the progression of tau pathology but have yet to lead to an approved disease-modifying treatment. Of the drugs in clinical trials that directly target tau, immunotherapies are the largest category and mostly consist of antibodies in different stages of development. There is a reasonable optimism that at least some of these compounds will have a clinically meaningful efficacy. This view is based on the significant although modest efficacy of some antibodies targeting amyloid-β in Alzheimer's disease and the fact that tau pathology correlates much better with the degree of dementia than amyloid-β lesions. In Alzheimer's disease, clearing pathological tau may therefore improve function later in the disease process than when removing amyloid-β. This review provides a brief update on the active and passive clinical tau immunization trials with insight from preclinical studies. Various epitopes are being targeted and some of the antibodies are said to target extracellular tau but because almost all of pathological tau is found intracellularly, the most efficacious antibodies should be able to enter the cell.
Keywords: Alzheimer Disease; Animals; Clinical Trials as Topic; Humans; Immunotherapy; tau Proteins; Tauopathies

Transcriptomic Profiling Reveals Neuroinflammation in the Corpus Callosum of a Transgenic Mouse Model of Alzheimer's Disease. - Takase, Hajime; Hamanaka, Gen; Hoshino, Tomonori; Ohtomo, Ryo; Guo, Shuzhen; Mandeville, Emiri T; Lo, Eng H; Arai, Ken (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is a widespread neurodegenerative disorder characterized by progressive cognitive decline, affecting a significant portion of the aging population. While the cerebral cortex and hippocampus have been the primary focus of AD research, accumulating evidence suggests that white matter lesions in the brain, particularly in the corpus callosum, play an important role in the pathogenesis of the disease. OBJECTIVE: This study aims to investigate the gene expression changes in the corpus callosum of 5xFAD transgenic mice, a widely used AD mouse model. METHODS: We conducted behavioral tests for spatial learning and memory in 5xFAD transgenic mice and performed RNA sequencing analyses on the corpus callosum to examine transcriptomic changes. RESULTS: Our results show cognitive decline and demyelination in the corpus callosum of 5xFAD transgenic mice. Transcriptomic analysis reveals a predominance of upregulated genes in AD mice, particularly those associated with immune cells, including microglia. Conversely, downregulation of genes related to chaperone function and clock genes such as Per1, Per2, and Cry1 is also observed. CONCLUSIONS: This study suggests that activation of neuroinflammation, disruption of chaperone function, and circadian dysfunction are involved in the pathogenesis of white matter lesions in AD. The findings provide insights into potential therapeutic targets and highlight the importance of addressing white matter pathology and circadian dysfunction in AD treatment strategies.
Keywords: Alzheimer Disease; Animals; Corpus Callosum; Disease Models, Animal; Gene Expression Profiling; Mice; Mice, Transgenic; Neuroinflammatory Diseases

Voluntary wheel running decreases amyloidogenic pathway and rescues cognition and mitochondrial energy metabolism in middle-aged female 3xTg-AD mouse model of Alzheimer's disease. - Dos Santos, Jonathas Rodrigo; Catalão, Carlos Henrique Rocha; Vulczak, Anderson; Azzolini, Ana Elisa Caleiro Seixas; Alberici, Luciane Carla (J Alzheimers Dis, 2024)
BACKGROUND: Evidence supports the neuroprotective effects of physical activity, either in experimental animal models or humans. However, the biological mechanisms by which physical exercise modulates dementia and Alzheimer's disease (AD) progression are still unclear. OBJECTIVE: This study investigated whether long-term (6 months) of voluntary wheel running induces neuroprotective effects in the pathogenesis of AD in middle-aged (8 months) female mice, focusing on energy metabolism. METHODS: A genetic mice model of AD (3xTg-AD) that performed wheel running presented changes in body metabolism and muscle oxidative profile, as well as restored discriminative and non-associative retention memories, evaluated by novel object recognition and open field tasks, respectively. RESULTS: In the hippocampus, these mice exhibited reduced levels of amyloidogenic AβPPβ fragment, phospho-Tau protein and phospho-Akt (activated form), without changes in phospho-AMPK (activated form). In addition, hippocampal mitochondria presented a restored respiratory function, characterized by lower coupling degree and weak contribution from complex I found in 3xTg-AD mice. CONCLUSIONS: The results demonstrated that voluntary exercise improves cognitive parameters and biochemical hallmarks of AD, modulates Akt activation and enhances mitochondrial energy metabolism in hippocampus of middle-aged 3xTg-AD female mice, thereby reinforcing the neuroprotective role of physical exercise and the involvement of mitochondria in the etiology of the AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Cognition; Disease Models, Animal; Energy Metabolism; Female; Hippocampus; Mice; Mice, Transgenic; Mitochondria; Physical Conditioning, Animal; tau Proteins

Advanced Alzheimer's Disease Patients Show Safe, Significant, and Persistent Benefit in 6-Month Bryostatin Trial. - Alkon, Daniel L; Sun, Miao-Kun; Tuchman, Alan J; Thompson, Richard E (J Alzheimers Dis, 2023)
BACKGROUND: In pre-clinical studies, Bryostatin, MW (molecular weight) 904, has demonstrated synaptogenic, anti-apoptotic, anti-amyloid, and anti-tau tangle efficacies. OBJECTIVE: To identify AD patients who show significant cognitive benefit versus placebo when treated in a trial with chronic Bryostatin dosing. METHODS: In this 6-month 122 AD patient Bryostatin trial, there were two cohorts: the Moderate Cohort (MMSE, Mini-Mental Status Exam: 15-18) and the Moderately Severe Cohort (MMSE 10-14) as pre-specified secondary endpoints. Patient randomization was stratified by baseline SIB to insure balance in baseline cognitive ability between treatment arms. RESULTS: With no safety events noted by the data safety and monitoring board, the Moderately Severe (MMSE 10-14) Bryostatin-treated patients were significantly improved above the placebo patients for Weeks #13 through Week #42. After two cycles of 7 x i.v. Bryostatin doses over a 26-week period, the 10-14 Cohort Severe Impairment Battery (SIB), measured every 2 weeks, showed significant benefit using a Mixed Model Repeated Measures model (MMRM, 2-tailed, p < 0.05) for Weeks #13 through #42, even 16 weeks after dosing completion by Week #26. Placebo 10-14 patients showed no benefit, declining to negative 12.8 points by Week #42. Trend analyses confirmed the MMRM data for this Cohort, with a significant downward slope (equivalent to Cognitive Decline) for the placebo group, p < 0.001, 2-tailed, but no significant decline for the Bryostatin-treated group (p = 0.409, NS), treatment versus placebo p < 0.007. The Moderate Cohort patients showed no significant benefit. CONCLUSIONS: The Bryostatin-treated MMSE 10-14 patients showed no significant cognitive decline throughout the 10-month trial, versus placebo patients' decline of -12.8 SIB points.
Keywords: Alzheimer Disease; Bryostatins; Cognition Disorders; Double-Blind Method; Humans; Treatment Outcome

Age-Related Association Between APOE ɛ4 and Cognitive Progression in de novo Parkinson's Disease. - Liu, Jia-Yao; Ma, Ling-Zhi; Wang, Jun; Cui, Xin-Jing; Sheng, Ze-Hu; Fu, Yan; Li, Meng; Ou, Ya-Nan; Yu, Jin-Tai; Tan, Lan; Lian, Yan (J Alzheimers Dis, 2023)
BACKGROUND: APOE ɛ4 genotype was correlated with exacerbation of pathology and higher risk of dementia in Parkinson's disease (PD). Meanwhile, the differential influence of APOE ɛ4 on cognition in young and old individuals interpreted as antagonistic pleiotropy. OBJECTIVE: To examine whether the effect of APOE ɛ4 on cognitive progression in de novo PD is age dependent. METHODS: In this study, 613 de novo PD patients were recruited from Parkinson's Progression Markers Initiative (PPMI). To examine the age-dependent relationship between APOE ɛ4 and cognitive changes, we added 3-way interaction of APOE ɛ4*baseline age*time to the linear mixed-effect (LME) models and evaluated the specific roles of APOE ɛ4 in the middle age group and elderly group separately. Cox regression was utilized to examine the progression of cognition in age-stratified PD participants. RESULTS: Age significantly modified relationship between APOE ɛ4 and cognitive changes in most cognitive domains (pinteraction <0.05). In the elderly group, APOE ɛ4 carriers showed steeper decline in global cognition (p = 0.001) as well as in most cognitive domains, and they had a greater risk of cognitive progression (adjusted HR 1.625, 95% CI 1.143-2.310, p = 0.007), compared with non-carriers. However, in the middle age group, no significant relationships between APOE ɛ4 and cognitive decline can be detected. CONCLUSION: Our results indicated that the APOE ɛ4 allele has an age-dependent effect on cognitive decline in PD patients. The underlying mechanisms need to be investigated in the future.
Keywords: Aged; Apolipoprotein E4; Cognition; Cognitive Dysfunction; Disease Progression; Genotype; Heterozygote; Humans; Parkinson Disease

Association Between Oral Bacteria and Alzheimer's Disease: A Systematic Review and Meta-Analysis. - Liu, Sixin; Dashper, Stuart G; Zhao, Rui (J Alzheimers Dis, 2023)
BACKGROUND: Pre-clinical evidence implicates oral bacteria in the pathogenesis of Alzheimer's disease (AD), while clinical studies show diverse results. OBJECTIVE: To comprehensively assess the association between oral bacteria and AD with clinical evidence. METHODS: Studies investigating the association between oral bacteria and AD were identified through a systematic search of six databases PubMed, Embase, Cochrane Central Library, Scopus, ScienceDirect, and Web of Science. Methodological quality ratings of the included studies were performed. A best evidence synthesis was employed to integrate the results. When applicable, a meta-analysis was conducted using a random-effect model. RESULTS: Of the 16 studies included, ten investigated periodontal pathobionts and six were microbiome-wide association studies. Samples from the brain, serum, and oral cavity were tested. We found over a ten-fold and six-fold increased risk of AD when there were oral bacteria (OR = 10.68 95% CI: 4.48-25.43; p < 0.00001, I2 = 0%) and Porphyromonas gingivalis (OR = 6.84 95% CI: 2.70-17.31; p < 0.0001, I2 = 0%) respectively in the brain. While AD patients exhibited lower alpha diversity of oral microbiota than healthy controls, the findings of bacterial communities were inconsistent among studies. The best evidence synthesis suggested a moderate level of evidence for an overall association between oral bacteria and AD and for oral bacteria being a risk factor for AD. CONCLUSION: Current evidence moderately supports the association between oral bacteria and AD, while the association was strong when oral bacteria were detectable in the brain. Further evidence is needed to clarify the interrelationship between both individual species and bacterial communities and the development of AD.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Humans; Microbiota; Porphyromonas gingivalis; Risk Factors

Association of Influenza Vaccination and Dementia Risk: A Meta-Analysis of Cohort Studies. - Sun, Huimin; Liu, Min; Liu, Jue (J Alzheimers Dis, 2023)
BACKGROUND: Dementia is a critical global public health problem. Previous cohort studies have found that influenza vaccination can decrease the risk of dementia. OBJECTIVE: This meta-analysis aimed to systematically examine the relationship between influenza vaccination and dementia risk. METHODS: We searched PubMed, Embase, Web of Science, ScienceDirect, medRxiv, and bioRxiv for studies investigating dementia risk based on influenza vaccination status, up to September 14, 2022. Relative risks (RRs) and 95% confidence intervals (95% CIs) were pooled in the meta-analysis. Subgroup analyses and sensitivity analyses were conducted as well. RESULTS: Of the 4,087 articles initially reviewed, 6 cohort studies were included in the final meta-analysis, and all eligible studies were at low risk of bias. There were 2,087,195 participants without dementia at baseline (mean age: 61.8-75.5 years, 57.05% males), and 149,804 (7.18%) cases of dementia occurred during 4.00-13.00 years of follow-up. Pooled analysis of adjusted RRs found that influenza vaccination could reduce dementia risk by 31% (RR = 0.69, 95% CI: 0.57-0.83). Subgroup analyses showed that in the study with a mean age of 75-80 years or 75%-100% males, the association was generally weakened compared with studies with a mean age of 60-75 years or 25%-50% males. The results were stable in the sensitivity analyses, and no publication bias was observed. CONCLUSION: Influenza vaccination in older adults was markedly associated with a decreased risk of dementia. More mechanistic studies and epidemiological studies are needed to clarify the association between influenza vaccination and decreased dementia risk.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Dementia; Humans; Influenza, Human; Vaccination

Association of Interleukin-6 and Interleukin-8 with Cognitive Decline in an Asian Memory Clinic Population. - Teoh, Nicole Shu Ning; Gyanwali, Bibek; Lai, Mitchell K P; Chai, Yuek Ling; Chong, Joyce R; Chong, Eddie Jun Yi; Chen, Christopher; Tan, Chuen Seng; Hilal, Saima (J Alzheimers Dis, 2023)
BACKGROUND: Neuroinflammation has been postulated to play an important role in cognitive impairment, cognitive decline, and dementia. Inflammatory biomarkers such as interleukin-6 (IL-6) and IL-8 are found to be associated with the neuro-inflammatory process and worse cognitive function. However, it is unknown whether these interleukins are associated with long-term cognitive function. OBJECTIVE: To investigate the association of baseline IL-6 and IL-8 with cognitive function at baseline as well as its association with cognitive decline over five-year follow-up. METHODS: 387 patients were recruited from an ongoing memory clinic-based study who underwent comprehensive physical, medical, neuropsychological and blood assessments together with brain MRI. IL-6 and IL-8 were measured using LUMINEX assays. The National Institute of Neurological Disorders and Stroke-Canadian Stroke Network neuropsychological battery was used to assess cognitive decline across multiple domains. RESULTS: Among the 387 (mean age = 72.9 years and 53.7% males) participants, 322 had at least two follow-up assessments and were included in the longitudinal analysis. Negative linear trend associations were found between tertiles of IL-8 with baseline global cognition (p-trend< 0.001), attention (p-trend = 0.005), executive function (p-trend< 0.001), and visuospatial function (p-trend = 0.002) domains. No association was found between baseline IL-8 and cognitive decline. IL-6 was not associated with both baseline and follow-up cognition. CONCLUSION: IL-8 was associated with worse cognition especially in attention, executive function, and visuospatial function, suggesting the role of neuroinflammation in cognitive impairment. Hence, blood inflammatory biomarkers may be useful indicators in identifying patients at risk of cognitive impairment and warrant consideration for inclusion in treatment trials.
Keywords: Aged; Biomarkers; Canada; Cognition; Cognitive Dysfunction; Female; Humans; Interleukin-6; Interleukin-8; Male; Neuroinflammatory Diseases; Neuropsychological Tests

Associations of the Harvard Automated Phone Task and Alzheimer's Disease Pathology in Cognitively Normal Older Adults: Preliminary Findings. - Gonzalez, Christopher; Mimmack, Kayden J; Amariglio, Rebecca E; Becker, J Alex; Chhatwal, Jasmeer P; Fitzpatrick, Colleen D; Gatchel, Jennifer R; Johnson, Keith A; Katz, Zoe S; Kuppe, Madeline K; Locascio, Joseph J; Udeogu, Onyinye J; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Detecting clinically meaningful changes in instrumental activities of daily living (IADL) at the earliest stages of Alzheimer's disease (AD) is critical. OBJECTIVE: The objective of this exploratory study was to examine the cross-sectional relationship between a performance-based IADL test, the Harvard Automated Phone Task (APT), and cerebral tau and amyloid burden in cognitively normal (CN) older adults. METHODS: Seventy-seven CN participants underwent flortaucipir tau and Pittsburgh Compound B amyloid PET. IADL were assessed using the three Harvard APT tasks: prescription refill (APT-Script), health insurance company call (APT-PCP), and bank transaction (APT-Bank). Linear regression models were used to determine associations between each APT task and entorhinal cortex, inferior temporal, or precuneus tau with or without an interaction with amyloid. RESULTS: Significant associations were found between APT-Bank task rate and interaction between amyloid and entorhinal cortex tau, and APT-PCP task and interactions between amyloid and inferior temporal and precuneus tau. No significant associations were found between the APT tasks and tau or amyloid alone. CONCLUSION: Our preliminary findings suggest an association between a simulated real-life IADL test and interactions of amyloid and several regions of early tau accumulation in CN older adults. However, some analyses were underpowered due to the small number of participants with elevated amyloid, and findings should be interpreted with caution. Future studies will further explore these associations cross-sectionally and longitudinally in order to determine whether the Harvard APT can serve as a reliable IADL outcome measure for preclinical AD prevention trials and ultimately in the clinic setting.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Amyloidogenic Proteins; Cognitive Dysfunction; Entorhinal Cortex; Humans; Positron-Emission Tomography; tau Proteins

Best Medicine for Dementia: The Life-Long Defense of the Brain. - Andersson, Marcus J; Stone, Jonathan (J Alzheimers Dis, 2023)
This review deals with an unwelcome reality about several forms of dementia, including Alzheimer's disease- that these dementias are caused, in part or whole, by the aging of the vasculature. Since the vasculature ages in us all, dementia is our fate, sealed by the realit!ies of the circulation; it is not a disease with a cure pending. Empirically, cognitive impairment before our 7th decade is uncommon and considered early, while a diagnosis in our 11th decade is late but common in that cohort (>40%). Projections from earlier ages suggest that the prevalence of dementia in people surviving into their 12th decade exceeds 80%. We address the question why so few of many interventions known to delay dementia are recognized as therapy; and we try to resolve this few-and-many paradox, identifying opportunities for better treatment, especially pre-diagnosis. The idea of dementia as a fate is resisted, we argue, because it negates the hope of a cure. But the price of that hope is lost opportunity. An approach more in line with the evidence, and more likely to limit suffering, is to understand the damage that accumulates with age in the cerebral vasculature and therefore in the brain, and which eventually gives rise to cognitive symptoms in late life, too often leading to dementia. We argue that hope should be redirected to delaying that damage and with it the onset of cognitive loss; and, for each individual, it should be redirected to a life-long defense of their brain.
Keywords: Aging; Alzheimer Disease; Brain; Cognitive Dysfunction; Dementia; Humans

Can Traditional Board Games Prevent or Slow Down Cognitive Impairment? A Systematic Review and Meta-Analysis. - Pozzi, Federico Emanuele; Appollonio, Ildebrando; Ferrarese, Carlo; Tremolizzo, Lucio (J Alzheimers Dis, 2023)
BACKGROUND: Traditional board games can entail significant skills encompassing several cognitive functions across different domains. Therefore, they may potentially represent effective cognitive interventions in the aging population with or without Alzheimer's disease or other types of dementia. OBJECTIVE: We aimed at verifying the hypothesis that traditional board games can prevent or slow down cognitive decline, through a systematic review on traditional board games and dementia. METHODS: We searched five databases with tailored search strings. We included studies assessing the impact of board games on elderly subjects at risk of or suffering from cognitive impairment, or subjects with cognitive impairment irrespective of age. Studies where the effect of board games was not separated by cards or other games were excluded. A meta-analysis was performed for specific cognitive and non-cognitive outcomes. RESULTS: Board games improved mental function, as measured by Montreal Cognitive Assessment (p = 0.003) and Mini-Mental State Examination (p = 0.02). Ska and Go improved Trail Making Test -A, while Mahjong improved executive functions. There was no consistent effect across different games on Digit Span or Categorical Fluency. Chess improved quality of life measured with the WHO-QoL-OLD scale (p < 0.00001). Mahjong temporarily improved depressive symptoms. Go increased BDNF levels and left middle temporal gyrus and bilateral putamen metabolism. CONCLUSIONS: Traditional board games may slow global cognitive decline and improve the quality of life in elderly subjects. Different games have varying impacts on specific cognitive domains, possibly mediated by functional and biological factors.
Keywords: Aged; Alzheimer Disease; Cognition; Cognitive Dysfunction; Executive Function; Humans; Quality of Life

CERAD (Consortium to Establish a Registry for Alzheimer's Disease) Neuropsychology Assessment Battery: 35 Years and Counting. - Fillenbaum, Gerda G; Mohs, Richard (J Alzheimers Dis, 2023)
BACKGROUND: In 1986, the Consortium to Establish a Registry for Alzheimer's Disease (CERAD) was mandated to develop a brief neuropsychological assessment battery (CERAD-NAB) for AD, for uniform neuropsychological assessment, and information aggregation. Initially used across the National Institutes of Aging-funded Alzheimer's Disease Research Centers, it has become widely adopted wherever information is desired on cognitive status and change therein, particularly in older populations. OBJECTIVE: Our purpose is to provide information on the multiple uses of the CERAD-NAB since its inception, and possible further developments. METHODS: Since searching on "CERAD neuropsychological assessment battery" or similar terms missed important information, "CERAD" alone was entered into PubMed and SCOPUS, and CERAD-NAB use identified from the resulting studies. Use was sorted into major categories, e.g., psychometric information, norms, dementia/differential dementia diagnosis, epidemiology, intervention evaluation, genetics, etc., also translations, country of use, and alternative data gathering approaches. RESULTS: CERAD-NAB is available in ∼20 languages. In addition to its initial purpose assessing AD severity, CERAD-NAB can identify mild cognitive impairment, facilitate differential dementia diagnosis, determine cognitive effects of naturally occurring and experimental interventions (e.g., air pollution, selenium in soil, exercise), has helped to clarify cognition/brain physiology-neuroanatomy, and assess cognitive status in dementia-risk conditions. Surveys of primary and tertiary care patients, and of population-based samples in multiple countries have provided information on prevalent and incident dementia, and cross-sectional and longitudinal norms for ages 35-100 years. CONCLUSION: CERAD-NAB has fulfilled its original mandate, while its uses have expanded, keeping up with advances in the area of dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cross-Sectional Studies; Humans; Neuropsychological Tests; Neuropsychology; Psychometrics; Registries

Characterizing Performance Gaps of a Code-Based Dementia Algorithm in a Population-Based Cohort of Cognitive Aging. - Vassilaki, Maria; Fu, Sunyang; Christenson, Luke R; Garg, Muskan; Petersen, Ronald C; St Sauver, Jennifer; Sohn, Sunghwan (J Alzheimers Dis, 2023)
BACKGROUND: Multiple algorithms with variable performance have been developed to identify dementia using combinations of billing codes and medication data that are widely available from electronic health records (EHR). If the characteristics of misclassified patients are clearly identified, modifying existing algorithms to improve performance may be possible. OBJECTIVE: To examine the performance of a code-based algorithm to identify dementia cases in the population-based Mayo Clinic Study of Aging (MCSA) where dementia diagnosis (i.e., reference standard) is actively assessed through routine follow-up and describe the characteristics of persons incorrectly categorized. METHODS: There were 5,316 participants (age at baseline (mean (SD)): 73.3 (9.68) years; 50.7% male) without dementia at baseline and available EHR data. ICD-9/10 codes and prescription medications for dementia were extracted between baseline and one year after an MCSA dementia diagnosis or last follow-up. Fisher's exact or Kruskal-Wallis tests were used to compare characteristics between groups. RESULTS: Algorithm sensitivity and specificity were 0.70 (95% CI: 0.67, 0.74) and 0.95 (95% CI: 0.95, 0.96). False positives (i.e., participants falsely diagnosed with dementia by the algorithm) were older, with higher Charlson comorbidity index, more likely to have mild cognitive impairment (MCI), and longer follow-up (versus true negatives). False negatives (versus true positives) were older, more likely to have MCI, or have more functional limitations. CONCLUSIONS: We observed a moderate-high performance of the code-based diagnosis method against the population-based MCSA reference standard dementia diagnosis. Older participants and those with MCI at baseline were more likely to be misclassified.
Keywords: Alzheimer Disease; Cognitive Aging; Cognitive Dysfunction; Dementia; Disease Progression; Female; Humans; Male

Circulating Omega-3 and Omega-6 Fatty Acids, Cognitive Decline, and Dementia in Older Adults. - de Oliveira Otto, Marcia C; Wu, Jason H Y; Thacker, Evan L; Lai, Heidi Tsz Mung; Lemaitre, Rozenn N; Padhye, Nikhil; Song, Xiaoling; King, Irena B; Lopez, Oscar; Siscovick, David S; Mozaffarian, Dariush (J Alzheimers Dis, 2023)
BACKGROUND: Comprising nearly 35% of brain lipids, polyunsaturated fatty acids (PUFA) are essential for optimal brain function. However, the role of PUFA on cognitive health outcomes later in life is largely unknown. OBJECTIVE: We investigated prospective associations of plasma phospholipid omega-3 (ALA [18 : 3], EPA [20 : 5], DPA [22 : 5], DHA [22 : 6]) and omega-6 (LA [18 : 2], AA [20 : 4]) PUFA with cognitive decline, risk of cognitive impairment and dementia among adults aged≥65 years in the Cardiovascular Health Study. METHODS: Circulating fatty acid concentrations were measured serially at baseline (1992/1993), 6 years, and 13 years later. Cognitive decline and impairment were assessed using the 100-point Modified Mini-Mental State Examination (3MSE) up to 7 times. Clinical dementia was identified using adjudicated neuropsychological tests, and ICD-9 codes. RESULTS: Among 3,564 older adults free of stroke and dementia at baseline, cognitive function declined annually by approximately -0.5 3MSE points; 507 participants developed cognitive impairment and 499 dementia over up to 23 years of follow-up. In multivariable models, higher circulating arachidonic acid (AA) concentrations were associated with slower cognitive decline and lower dementia risk, with associations growing stronger with greater length of follow-up (hazard ratio [HR,95% CI] of dementia per interquintile range, 0.74 [0.56-0.97] at 5 years, and 0.53 [0.37-0.77] at 15 years). Circulating docosapentaenoic (DPA) concentrations were associated with slower cognitive decline and lower risk of cognitive impairment (extreme-quintile HR, 0.72 [95% CI: 0.55, 0.95]). Findings were generally null or inconsistent for other omega-3 or omega-6 PUFA. CONCLUSION: Circulating AA and DPA, but not other PUFA, are associated with slower rate of cognitive decline and lower risk of dementia or cognitive impairment later in life.
Keywords: Aged; Arachidonic Acid; Cognitive Dysfunction; Dementia; Fatty Acids; Fatty Acids, Omega-3; Fatty Acids, Omega-6; Fatty Acids, Unsaturated; Humans

Cleveland Clinic Cognitive Battery (C3B): Normative, Reliability, and Validation Studies of a Self-Administered Computerized Tool for Screening Cognitive Dysfunction in Primary Care. - Rao, Stephen M; Galioto, Rachel; Sokolowski, Megan; Pierce, Madelyn; Penn, Lisa; Sturtevant, Anna; Skugor, Blazenka; Anstead, Brent; Leverenz, James B; Schindler, David; Blum, David; Alberts, Jay L; et al. (J Alzheimers Dis, 2023)
BACKGROUND: The self-administered iPad-based Cleveland Clinic Cognitive Battery (C3B) was designed specifically for the efficient screening of cognitive functioning of older adults in a primary care setting. OBJECTIVE: 1) Generate regression-based norms from healthy participants to enable demographic corrections to facilitate clinical interpretation; 2) estimate test-retest reliability and practice effects; 3) examine ability to discriminate mild cognitive impairment (MCI) from healthy aging; 4) d etermine validity of screening in a distracting clinical environment; and 5) determine completion rates and patient satisfaction in a primary care setting. METHODS: Study 1 (S1) recruited a stratified sample of 428 healthy adults, ages 18-89, to generate regression-based equations. S2 assessed 2-week test-retest reliability and practice effects in 30 healthy elders. S3 recruited 30 MCI patients and 30 demographically-matched healthy controls. In S4, 30 healthy elders self-administered the C3B in a distracting environment and in a quiet private room in counterbalanced order. In a demonstration project, 470 consecutive primary care patients were administered the C3B as part of routine clinical care (S5). RESULTS: C3B performance was primarily influenced by age, education, and race (S1), had acceptably high test-retest reliability and minimal practice effects (S2), discriminated MCI from healthy controls (S3), was not negatively impacted by a distracting clinical environment (S4), had high completion rates (>92%) and positive ratings from primary care patients (S5). CONCLUSION: The C3B is a computerized cognitive screening tool that is reliable, validated, self-administered, and is conducive to integration into a busy primary care clinical workflow for detecting MCI, early Alzheimer's disease, and other related dementias.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Cognition; Cognitive Dysfunction; Humans; Middle Aged; Neuropsychological Tests; Primary Health Care; Reproducibility of Results; Young Adult

Coexistence of Amyotrophic Lateral Sclerosis and Alzheimer's Disease: Case Report and Review of the Literature. - Verde, Federico; Aiello, Edoardo Nicolò; Adobbati, Laura; Poletti, Barbara; Solca, Federica; Tiloca, Cinzia; Sangalli, Davide; Maranzano, Alessio; Muscio, Cristina; Ratti, Antonia; Zago, Stefano; Ticozzi, Nicola; et al. (J Alzheimers Dis, 2023)
We describe a case of amyotrophic lateral sclerosis (ALS) associated with Alzheimer's disease (AD) and review the literature about the coexistence of the two entities, highlighting the following: mean age at onset is 63.8 years, with slight female predominance; ALS tends to manifest after cognitive impairment and often begins in the bulbar region; average disease duration is 3 years; cognitive phenotype is mostly amnestic; the pattern of brain involvement is, in most cases, consistent with AD. Our case and the reviewed ones suggest that patients with ALS and dementia lacking unequivocal features of FTD should undergo additional examinations in order to recognize AD.
Keywords: Alzheimer Disease; Amyotrophic Lateral Sclerosis; Brain; Cognitive Dysfunction; Female; Frontotemporal Dementia; Humans; Male

Cognitive and Neuropsychological Profiles in Alzheimer's Disease and Primary Age-Related Tauopathy and the Influence of Comorbid Neuropathologies. - Walker, Jamie M; Gonzales, Mitzi M; Goette, William; Farrell, Kurt; White Iii, Charles L; Crary, John F; Richardson, Timothy E (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease neuropathologic change (ADNC) is defined by the progression of both hyperphosphorylated-tau (p-tau) and amyloid-β (Aβ) and is the most common underlying cause of dementia worldwide. Primary age-related tauopathy (PART), an Aβ-negative tauopathy largely confined to the medial temporal lobe, is increasingly being recognized as an entity separate from ADNC with diverging clinical, genetic, neuroanatomic, and radiologic profiles. OBJECTIVE: The specific clinical correlates of PART are largely unknown; we aimed to identify cognitive and neuropsychological differences between PART, ADNC, and subjects with no tauopathy (NT). METHODS: We compared 2,884 subjects with autopsy-confirmed intermediate-high stage ADNC to 208 subjects with definite PART (Braak stage I-IV, Thal phase 0, CERAD NP score "absent") and 178 NT subjects from the National Alzheimer's Coordinating Center dataset. RESULTS: PART subjects were older than either ADNC or NT patients. The ADNC cohort had more frequent neuropathological comorbidities as well as APOE ɛ4 alleles than the PART or NT cohort, and less frequent APOE ɛ2 alleles than either group. Clinically, ADNC patients performed significantly worse than NT or PART subjects across cognitive measures, but PART subjects had selective deficits in measures of processing speed, executive function, and visuospatial function, although additional cognitive measures were further impaired in the presence of neuropathologic comorbidities. In isolated cases of PART with Braak stage III-IV, there are additional deficits in measures of language. CONCLUSION: Overall, these findings demonstrate underlying cognitive features specifically associated with PART, and reinforce the concept that PART is a distinct entity from ADNC.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Cognition; Executive Function; Humans; Tauopathies

Costs of Dementia in Low- And Middle-Income Countries: A Systematic Review. - Kenne Malaha, Angeladine; Thébaut, Clémence; Achille, Dayna; Preux, Pierre-Marie; Guerchet, Maëlenn (J Alzheimers Dis, 2023)
BACKGROUND: The proportion of people living with dementia in low- and middle-income countries (LMICs) is expected to reach 71% by 2050. Appraising the economic burden of the disease may contribute to strategic policy planning. OBJECTIVE: To review studies conducted on the costs of dementia in LMICs, describe their methodology and summarize available costs estimates. METHODS: Systematic review, including a search of health, economics, and social science bibliographic databases. No date or language restrictions were applied. All studies with a direct measure of the costs of dementia care were included. RESULTS: Of the 6,843 publications reviewed, 17 studies from 11 LMICs were included. Costs of dementia tended to increase with the severity of the disease. Medical costs were greater in the mild stage, while social and informal care costs were highest in the moderate and severe stages. Annual cost estimates per patient ranged from PPP$131.0 to PPP$31,188.8 for medical costs; from PPP$16.1 to PPP$10,581.7 for social care services and from PPP$140.0 to PPP$25,798 for informal care. Overall, dementia care can cost from PPP$479.0 to PPP$66,143.6 per year for a single patient. CONCLUSION: Few studies have been conducted on the costs of dementia in LMICs, and none so far in Africa. There seems to be a need to provide accurate data on the burden of disease in these countries to guide public health policies in the coming decades.
Keywords: Cost of Illness; Dementia; Developing Countries; Health Care Costs; Health Expenditures; Humans

COVID-19 as a Risk Factor for Alzheimer's Disease. - Golzari-Sorkheh, Mahdieh; Weaver, Donald F; Reed, Mark A (J Alzheimers Dis, 2023)
Severe acute respiratory disease coronavirus 2 (SARS-CoV-2) is responsible for the coronavirus disease 2019 (COVID-19) pandemic. Although a primarily respiratory disease, recent reports indicate that it also affects the central nervous system (CNS). Over 25% of COVID-19 patients report neurological symptoms such as memory loss, anosmia, hyposmia, confusion, and headaches. The neurological outcomes may be a result of viral entry into the CNS and/or resulting neuroinflammation, both of which underlie an elevated risk for Alzheimer's disease (AD). Herein, we ask: Is COVID-19 a risk factor for AD? To answer, we identify the literature and review mechanisms by which COVID-19-mediated neuroinflammation can contribute to the development of AD, evaluate the effects of acute versus chronic phases of infection, and lastly, discuss potential therapeutics to address the rising rates of COVID-19 neurological sequelae.
Keywords: Alzheimer Disease; COVID-19; Humans; Nervous System Diseases; Neuroinflammatory Diseases; Risk Factors; SARS-CoV-2

Is Dementia Associated with COVID-19 Mortality? A Multicenter Retrospective Cohort Study Conducted in 50 Hospitals in Germany. - Kostev, Karel; Gessler, Nele; Wohlmuth, Peter; Arnold, Dirk; Bein, Berthold; Bohlken, Jens; Herrlinger, Klaus; Jacob, Louis; Koyanagi, Ai; Nowak, Lorenz; Smith, Lee; Wesseler, Claas; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Dementia has been identified as a major predictor of mortality associated with COVID-19. OBJECTIVE: The objective of this study was to investigate the association between dementia and mortality in COVID-19 inpatients in Germany across a longer interval during the pandemic. METHODS: This retrospective study was based on anonymized data from 50 hospitals in Germany and included patients with a confirmed COVID-19 diagnosis hospitalized between March 11, 2020 and July, 20, 2022. The main outcome of the study was the association of mortality during inpatient stays with dementia diagnosis, which was studied using multivariable logistic regression adjusted for age, sex, and comorbidities as well as univariate logistic regression for matched pairs. RESULTS: Of 28,311 patients diagnosed with COVID-19, 11.3% had a diagnosis of dementia. Prior to matching, 26.5% of dementia patients and 11.5% of non-dementia patients died; the difference decreased to 26.5% of dementia versus 21.7% of non-dementia patients within the matched pairs (n = 3,317). This corresponded to an increase in the risk of death associated with dementia (OR = 1.33; 95% CI: 1.16-1.46) in the univariate regression conducted for matched pairs. CONCLUSION: Although dementia was associated with COVID-19 mortality, the association was weaker than in previously published studies. Further studies are needed to better understand whether and how pre-existing neuropsychiatric conditions such as dementia may impact the course and outcome of COVID-19.
Keywords: COVID-19; COVID-19 Testing; Dementia; Germany; Hospitalization; Hospitals; Humans; Mortality; Retrospective Studies

Detecting Anosognosia from the Prodromal Stage of Alzheimer's Disease. - Guieysse, Thomas; Lamothe, Roxane; Houot, Marion; Razafimahatratra, Solofo; Medani, Takfarinas; Lejeune, François-Xavier; Dreyfus, Gérard; Klarsfeld, André; Pantazis, Dimitrios; Koechlin, Etienne; Andrade, Katia (J Alzheimers Dis, 2023)
BACKGROUND: Though not originally developed for this purpose, the Healthy Aging Brain Care Monitor (HABC-M) seems a valuable instrument for assessing anosognosia in Alzheimer's disease (AD). OBJECTIVES: Our study aimed at 1) investigating the validity of the HABC-M (31 items), and its cognitive, psychological, and functional subscales, in discriminating AD patients from controls; 2) exploring whether the HABC-M discrepancy scores between the self-reports of patients/controls in these different domains and the respective ratings provided by their caregivers/informants correlate with an online measure of self-awareness; 3) determining whether the caregiver burden level, also derived from the HABC-M, could add additional support for detecting anosognosia. METHODS: The HABC-M was administered to 30 AD patients and 30 healthy controls, and to their caregivers/informants. A measure of online awareness was established from subjects' estimation of their performances in a computerized experiment. RESULTS: The HABC-M discrepancy scores distinguished AD patients from controls. The cognitive subscale discriminated the two groups from the prodromal AD stage, with an AUC of 0.88 [95% CI: 0.78;0.97]. Adding the caregiver burden level raised it to 0.94 [0.86;0.99]. Significant correlations between the HABC-M and online discrepancy scores were observed in the patients group, providing convergent validity of these methods. CONCLUSIONS: The cognitive HABC-M (six items) can detect anosognosia across the AD spectrum. The caregiver burden (four items) may corroborate the suspicion of anosognosia. The short-hybrid scale, built from these 10 items instead of the usual 31, showed the highest sensitivity for detecting anosognosia from the prodromal AD stage, which may further help with timely diagnosis.
Keywords: Agnosia; Alzheimer Disease; Brain; Caregivers; Humans; Neuropsychological Tests; Prodromal Symptoms

Diet's Role in Modifying Risk of Alzheimer's Disease: History and Present Understanding. - Grant, William B; Blake, Steven M (J Alzheimers Dis, 2023)
Diet is an important nonpharmacological risk-modifying factor for Alzheimer's disease (AD). The approaches used here to assess diet's role in the risk of AD include multi-country ecological studies, prospective and cross-sectional observational studies, and laboratory studies. Ecological studies have identified fat, meat, and obesity from high-energy diets as important risk factors for AD and reported that AD rates peak about 15-20 years after national dietary changes. Observational studies have compared the Western dietary pattern with those of the Dietary Approaches to Stop Hypertension (DASH), Mediterranean (MedDi), and Mediterranean-DASH Intervention for Neurodegenerative Delay (MIND) diets. Those studies identified AD risk factors including higher consumption of saturated and total fats, meat, and ultraprocessed foods and a lower risk of AD with higher consumption of fruits, legumes, nuts, omega-3 fatty acids, vegetables, and whole grains. Diet-induced factors associated with a significant risk of AD include inflammation, insulin resistance, oxidative stress, elevated homocysteine, dietary advanced glycation end products, and trimethylamine N-oxide. The molecular mechanisms by which dietary bioactive components and specific foods affect risk of AD are discussed. Given most countries' entrenched food supply systems, the upward trends of AD rates would be hard to reverse. However, for people willing and able, a low-animal product diet with plenty of anti-inflammatory, low-glycemic load foods may be helpful.
Keywords: Alzheimer Disease; Cross-Sectional Studies; Diet; Humans; Prospective Studies; Risk Factors

Early Life Stress Enhances Cognitive Decline and Alters Synapse Function and Interneuron Numbers in Young Male APP/PS1 Mice. - Brosens, Niek; Samouil, Dimitris; Stolker, Sabine; Katsika, Efthymia Vasilina; Weggen, Sascha; Lucassen, Paul J; Krugers, Harm J (J Alzheimers Dis, 2023)
BACKGROUND: Exposure to stress early in life increases the susceptibility to Alzheimer's disease (AD) pathology in aged AD mouse models. So far, the underlying mechanisms have remained elusive. OBJECTIVE: To investigate 1) effects of early life stress (ELS) on early functional signs that precede the advanced neuropathological changes, and 2) correlate synaptosomal protein content with cognition to identify neural correlates of AD. METHODS: APPswe/PS1dE9 mice and littermates were subjected to ELS by housing dams and pups with limited bedding and nesting material from postnatal days 2-9. At 3 months of age, an age where no cognitive loss or amyloid-β (Aβ) pathology is typically reported in this model, we assessed hippocampal Aβ pathology, synaptic strength and synapse composition and interneuron populations. Moreover, cognitive flexibility was assessed and correlated with synaptosomal protein content. RESULTS: While ELS did not affect Aβ pathology, it increased synaptic strength and decreased the number of calretinin+ interneurons in the hippocampal dentate gyrus. Both genotype and condition further affected the level of postsynaptic glutamatergic protein content. Finally, APP/PS1 mice were significantly impaired in cognitive flexibility at 3 months of age, and ELS exacerbated this impairment, but only at relatively high learning criteria. CONCLUSIONS: ELS reduced cognitive flexibility in young APP/PS1 mice and altered markers for synapse and network function. These findings at an early disease stage provide novel insights in AD etiology and in how ELS could increase AD susceptibility.
Keywords: Adverse Childhood Experiences; Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Cognitive Dysfunction; Disease Models, Animal; Interneurons; Male; Mice; Mice, Transgenic; Plaque, Amyloid; Presenilin-1; Synapses

Effects of a Physical Activity Program that Incorporates Exercises Targeting Balance, Strength, and Proprioception on Cognitive Functions and Physical Performance in Old Adults with Mild Cognitive Impairment. - Boulares, Ayoub; Fabre, Claudine; Cherni, Ala; Jdidi, Hela; Gaied Chortane, Sabri; Trompetto, Carlo; Puce, Luca; Bragazzi, Nicola Luigi (J Alzheimers Dis, 2023)
BACKGROUND: Aging often leads to cognitive function decline, sensory structure deterioration, and musculoskeletal system weakening. This impacts postural control during static and dynamic activities like walking, increasing the fall risk among the elderly. Older adults with mild cognitive impairment (MCI) face an elevated fall risk and cognitive decline, magnifying the public health concern. OBJECTIVE: This study aimed to explore solutions by investigating the effects of a multi-component physical activity program on cognitive and motor functions in MCI patients. METHODS: Twenty-three participants were enrolled in the study and assigned into two groups: an intervention group (n = 13; age = 85.7±5.5 years) and a control group (n = 9; age = 85±6.7 years). The study spanned two months, with participants engaging in three 60-minute weekly physical exercise sessions. The intervention focused on improving proprioception, muscle strength, and balance. RESULTS: Results demonstrated significant enhancements in physical performance, fall risk reduction, and balance (p < 0.05). Various tests, including the timed up and go test, Unipedal Stance test, Tinetti test, Short Physical Performance Battery, and 6-minute walking test, indicated these improvements. Cognitive function was evaluated with the Mini-Mental State Examination, revealing non-significant progress (p > 0.05). Predictive models for outcomes were developed using linear regression analysis during the follow-up stage. CONCLUSIONS: This study underscores the effectiveness of a multi-component physical activity program encompassing balance, proprioception, and muscle-strengthening exercises as a non-pharmaceutical approach in improving balance skills and playing a key role in mitigating the risk of falls among old adults with MCI.
Keywords: Accidental Falls; Aged; Aged, 80 and over; Cognition; Cognitive Dysfunction; Exercise; Exercise Therapy; Humans; Physical Functional Performance; Postural Balance; Proprioception; Time and Motion Studies

Effects of Remote Expressive Arts Program in Older Adults with Mild Cognitive Impairment: A Randomized Controlled Trial. - Luo, Yuting; Lin, Rong; Yan, Yuanjiao; Su, Jiawei; Lin, Shengmei; Ma, Mingping; Li, Hong (J Alzheimers Dis, 2023)
BACKGROUND: Mild cognitive impairment (MCI) is a stage of cognitive ability loss with intact activities of daily living and an increased risk for the development of dementia. OBJECTIVE: This study evaluated the intervention effect of remote expressive arts program (rEAP) on cognitive function in older adults with MCI and investigated the underlying neurobiological mechanisms. METHODS: We assigned 73 older MCI patients to receive rEAP or health education (HE), who underwent neuropsychological evaluation and resting-state functional magnetic resonance imaging before and after treatment. Neuropsychological scores were analyzed using SPSS software, and regional homogeneity (ReHo) values and seed-based functional connectivity (FC) were analyzed using Matlab software. RESULTS: The rEAP group showed more significant improvements in cognitive function than the HE group. rEAP affected spontaneous brain activity and brain networks. The ReHo values in the right anterior cingulate/paracingulate cortex and the left dorsolateral superior frontal gyrus significantly increased and decreased, respectively, in the rEAP and HE groups. Further, ReHo value changes were significantly associated with the corresponding neuropsychological test score changes in the rEAP group. Moreover, the rEAP group showed decreased FC between the posterior cingulate cortex and the right middle temporal gyrus and increased FC between the ventromedial prefrontal cortex and left angular gyrus. CONCLUSION: The 12-week rEAP improved cognitive function in MCI patients. Additionally, the alterations of spontaneous brain network connections and activity helped improve and maintain cognitive function in MCI patients.
Keywords: Activities of Daily Living; Aged; Brain; Cognition; Cognitive Dysfunction; Humans; Magnetic Resonance Imaging

The Efficacy and Safety of Physiotherapy in People with Dementia: A Systematic Review. - Saúde, Alexandra; Bouça-Machado, Raquel; Leitão, Mariana; Benedetti, Andrea; Ferreira, Joaquim J (J Alzheimers Dis, 2023)
BACKGROUND: Physiotherapy has become increasingly relevant as a new therapeutic intervention for dementia. However, it is unclear which interventions are the most suitable. OBJECTIVE: This study sought to summarize and critically appraise the evidence on physiotherapy interventions in dementia. METHODS: A systematic review conducted using CENTRAL, MEDLINE, and PEDro databases, from their inception to July 2022, identified all experimental studies of dementia that included physiotherapy interventions. RESULTS: Of 194 articles included, the most frequently used interventions were aerobic training (n = 82, 42%), strength training (n = 79, 41%), balance training (n = 48, 25%), and stretching (n = 22, 11%). These were associated with a positive effect on several motor and cognitive outcomes. A total number of 1,119 adverse events were reported. CONCLUSION: Physiotherapy has several motor and cognitive benefits in dementia. Future research should focus on establishing a physiotherapy prescription protocol for people with mild cognitive impairment and for each stage of dementia.
Keywords: Cognitive Dysfunction; Dementia; Humans; Physical Therapy Modalities; Resistance Training

Emotional Dysregulation in Mild Behavioral Impairment Is Associated with Reduced Cortical Thickness in the Right Supramarginal Gyrus. - Imai, Ayu; Matsuoka, Teruyuki; Narumoto, Jin (J Alzheimers Dis, 2023)
BACKGROUND: Mild behavioral impairment (MBI) has attracted attention as a possible precursor symptom of dementia, but its neural basis has not been fully investigated. OBJECTIVE: We aimed to investigate the relationship between MBI and surface area, cortical thickness, and volume in the temporal and parietal lobes, which are strongly associated with dementia and emotional disorders. METHODS: This retrospective study evaluated 123 participants: 90 with mild cognitive impairment (MCI), 13 with subjective cognitive decline (SCD), and 20 cognitively healthy (CH). Using analysis of covariance (ANCOVA) with sex, age, and MMSE score as covariates, cortical thickness, surface area, and volume in 10 regions were compared between groups with and without MBI. Groups with MBI emotional dysregulation were also compared with groups without MBI. RESULTS: ANCOVA revealed significantly smaller cortical thickness in the MBI group's right parahippocampal (p = 0.01) and supramarginal gyri (p = 0.002). After multiple comparison correction, only the right supramarginal gyrus was significantly smaller (p = 0.02). When considering only MBI emotional dysregulation, the right parahippocampal and supramarginal gyrus' cortical thicknesses were significantly smaller in this MBI group (p = 0.03, 0.01). However, multiple comparison correction identified no significant differences (p = 0.14, 0.11). CONCLUSION: Overall MBI and the emotional dysregulation domains were associated with reduced cortical thickness in the right parahippocampal and supramarginal gyri. Since neurodegeneration in the medial temporal and parietal lobe precedes early Alzheimer's disease (AD), MBI, particularly emotion dysregulation, may predict early AD below the diagnostic threshold.
Keywords: Alzheimer Disease; Attention; Cognitive Dysfunction; Dementia; Humans; Neuropsychological Tests; Parietal Lobe; Retrospective Studies

Etiology and Clinical Significance of Network Hyperexcitability in Alzheimer's Disease: Unanswered Questions and Next Steps. - Samudra, Niyatee; Ranasinghe, Kamalini; Kirsch, Heidi; Rankin, Katherine; Miller, Bruce (J Alzheimers Dis, 2023)
Cortical network hyperexcitability related to synaptic dysfunction in Alzheimer's disease (AD) is a potential target for therapeutic intervention. In recent years, there has been increased interest in the prevalence of silent seizures and interictal epileptiform discharges (IEDs, or seizure tendency), with both entities collectively termed "subclinical epileptiform activity" (SEA), on neurophysiologic studies in AD patients. SEA has been demonstrated to be common in AD, with prevalence estimates ranging between 22-54%. Converging lines of basic and clinical evidence imply that modifying a hyperexcitable state results in an improvement in cognition. In particular, though these results require further confirmation, post-hoc findings from a recent phase II clinical trial suggest a therapeutic effect with levetiracetam administration in patients with AD and IEDs. Here, we review key unanswered questions as well as potential clinical trial avenues. Specifically, we discuss postulated mechanisms and treatment of hyperexcitability in patients with AD, which are of interest in designing future disease-modifying therapies. Criteria to prompt screening and optimal screening methodology for hyperexcitability have yet to be defined, as does timing and personalization of therapeutic intervention.
Keywords: Alzheimer Disease; Causality; Clinical Relevance; Electroencephalography; Humans; Levetiracetam; Seizures

Evaluation of Blood-Based Plasma Biomarkers as Potential Markers of Amyloid Burden in Preclinical Alzheimer's Disease. - Winston, Charisse N; Langford, Oliver; Levin, Natalie; Raman, Rema; Yarasheski, Kevin; West, Tim; Abdel-Latif, Sara; Donohue, Michael; Nakamura, Akinori; Toba, Kenji; Masters, Colin L; Doecke, James; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Participant eligibility for the A4 Study was determined by amyloid PET imaging. Given the disadvantages of amyloid PET imaging in accessibility and cost, blood-based biomarkers may serve as a sufficient biomarker and more cost-effective screening tool for patient enrollment into preclinical AD trials. OBJECTIVE: To determine if a blood-based screening test can adequately identify amyloid burden in participants screened into a preclinical AD trial. METHODS: In this cross-sectional study, 224 participants from the A4 Study received an amyloid PET scan (18Florbetapir) within 90 days of blood sample collection. Blood samples from all study participants were processed within 2 h after phlebotomy. Plasma amyloid measures were quantified by Shimazdu and C2 N Diagnostics using mass spectrometry-based platforms. A corresponding subset of blood samples (n = 100) was processed within 24 h after phlebotomy and analyzed by C2 N. RESULTS: Plasma Aβ42/Aβ40 demonstrated the highest association for Aβ accumulation in the brain with an AUC 0.76 (95%CI = 0.69, 0.82) at C2 N and 0.80 (95%CI = 0.75, 0.86) at Shimadzu. Blood samples processed to plasma within 2 h after phlebotomy provided a better prediction of amyloid PET status than blood samples processed within 24 h (AUC 0.80 versus 0.64; p < 0.001). Age, sex, and APOE ɛ4 carrier status did not the diagnostic performance of plasma Aβ42/Aβ40 to predict amyloid PET positivity in A4 Study participants. CONCLUSION: Plasma Aβ42/Aβ40 may serve as a potential biomarker for predicting elevated amyloid in the brain. Utilizing blood testing over PET imaging may improve screening efficiency into clinical trials.
Keywords: Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Amyloidogenic Proteins; Biomarkers; Cross-Sectional Studies; Humans; Peptide Fragments; Positron-Emission Tomography

Exploring Reasons for Differential Vulnerability and Alzheimer's Disease Risk in Racial and Ethnic Minorities. - Daniel, E Valerie; Kleiman, Michael J; Galvin, James E (J Alzheimers Dis, 2023)
BACKGROUND: African American and Hispanic older adults are reported to have up to a 2-fold higher risk of Alzheimer's disease and related disorders (ADRD), but the reasons for this increased vulnerability have not been fully explored. The Vulnerability Index (VI) was designed to identify individuals who are at risk of developing cognitive impairment in the future, capturing 12 sociodemographic variables and modifiable medical comorbidities associated with higher ADRD risk. However, a prior limitation of the VI was that the original study cohort had limited diversity. We examined the association of the VI within and between non-Hispanic White, African American, and Hispanic older adults with and without cognitive impairment and different socioeconomic strata enrolled in a community-based dementia screening study. OBJECTIVE: To explore reasons for reported higher ADRD vulnerability in African Americans and Hispanics. METHODS: In a cross-sectional study of 300 non-Hispanic White, African American, and Hispanic older adults with and without cognitive impairment, we studied the association between cognitive status, the VI, and socioeconomic status (SES). RESULTS: When considering race/ethnicity, the presence of more vascular comorbidities drove greater vulnerability. When considering SES, vascular comorbidities played a less prominent role suggesting resources and access to care drives risk. The VI had differential effects on cognitive performance with the greatest effect in the earlier stages of impairment. CONCLUSION: Findings from this study provide a deeper understanding of the differential risk of ADRD in multicultural older adults captured by the VI and how barriers to healthcare access may increase vulnerability in racial/ethnic minorities.
Keywords: Aged; Alzheimer Disease; Cross-Sectional Studies; Ethnic and Racial Minorities; Ethnicity; Humans; White People

Exposure to World Trade Center Dust Exacerbates Cognitive Impairment and Evokes a Central and Peripheral Pro-Inflammatory Transcriptional Profile in an Animal Model of Alzheimer's Disease. - Iban-Arias, Ruth; Trageser, Kyle J; Yang, Eun-Jeong; Griggs, Elizabeth; Radu, Aurelian; Naughton, Sean; Al Rahim, Md; Tatsunori, Oguchi; Raval, Urdhva; Palmieri, Joshua; Huang, Zerlina; Chen, Lung-Chi; et al. (J Alzheimers Dis, 2023)
BACKGROUND: The terrorist attacks on September 11, 2001, on the World Trade Center (WTC) led to intense fires and a massive dense cloud of toxic gases and suspended pulverized debris. In the subsequent years, following the attack and cleanup efforts, a cluster of chronic health conditions emerged among First Responders (FR) who were at Ground Zero for prolonged periods and were repeatedly exposed to high levels of WTC particulate matter (WTCPM). Among those are neurological complications which may increase the risk for the development of Alzheimer's disease (AD) later in life. OBJECTIVE: We hypothesize that WTCPM dust exposure affects the immune cross-talking between the periphery and central nervous systems that may induce brain permeability ultimately promoting AD-type phenotype. METHODS: 5XFAD and wild-type mice were intranasally administered with WTCPM dust collected at Ground Zero within 72 h after the attacks. Y-maze assay and novel object recognition behavioral tests were performed for working memory deficits and learning and recognition memory, respectively. Transcriptomic analysis in the blood and hippocampus was performed and confirmed by RT qPCR. RESULTS: Mice exposed to WTCPM dust exhibited a significant impairment in spatial and recognition short and long-term memory. Furthermore, the transcriptomic analysis in the hippocampal formation and blood revealed significant changes in genes related to immune-inflammatory responses, and blood-brain barrier disruption. CONCLUSION: These studies suggest a putative peripheral-brain immune inflammatory cross-talking that may potentiate cognitive decline, identifying for the first time key steps which may be therapeutically targetable in future studies in WTC FR.
Keywords: Alzheimer Disease; Animals; Cognitive Dysfunction; Dust; Mice; Models, Animal; September 11 Terrorist Attacks

Impact of Computerized Cognitive Training on Default Mode Network Connectivity in Subjects at Risk for Alzheimer's Disease: A 78-week Randomized Controlled Trial. - Petrella, Jeffrey R; Michael, Andrew M; Qian, Min; Nwosu, Adaora; Sneed, Joel; Goldberg, Terry E; Devanand, Davangere P; Doraiswamy, P Murali (J Alzheimers Dis, 2023)
BACKGROUND: Mild cognitive impairment (MCI) represents a high risk group for Alzheimer's disease (AD). Computerized Cognitive Games Training (CCT) is an investigational strategy to improve targeted functions in MCI through the modulation of cognitive networks. OBJECTIVE: The goal of this study was to examine the effect of CCT versus a non-targeted active brain exercise on functional cognitive networks. METHODS: 107 patients with MCI were randomized to CCT or web-based crossword puzzles. Resting-state functional MRI (fMRI) was obtained at baseline and 18 months to evaluate differences in fMRI measured within- and between-network functional connectivity (FC) of the default mode network (DMN) and other large-scale brain networks: the executive control, salience, and sensorimotor networks. RESULTS: There were no differences between crosswords and games in the primary outcome, within-network DMN FC across all subjects. However, secondary analyses suggest differential effects on between-network connectivity involving the DMN and SLN, and within-network connectivity of the DMN in subjects with late MCI. Paradoxically, in both cases, there was a decrease in FC for games and an increase for the crosswords control (p < 0.05), accompanied by lesser cognitive decline in the crosswords group. CONCLUSION: Results do not support a differential impact on within-network DMN FC between games and crossword puzzle interventions. However, crossword puzzles might result in cognitively beneficial remodeling between the DMN and other networks in more severely impaired MCI subjects, parallel to the observed clinical benefits.
Keywords: Alzheimer Disease; Brain; Cognitive Dysfunction; Cognitive Training; Default Mode Network; Humans; Magnetic Resonance Imaging; Nerve Net

Impact of Hearing Aids on Progression of Cognitive Decline, Depression, and Quality of Life Among People with Cognitive Impairment and Dementia. - Atef, Roaa Zayed; Michalowsky, Bernhard; Raedke, Anika; Platen, Moritz; Mohr, Wiebke; Mühlichen, Franka; Thyrian, Jochen René; Hoffmann, Wolfgang (J Alzheimers Dis, 2023)
BACKGROUND: Hearing loss is common in people with dementia (PwD) and a modifiable risk factor for cognitive decline. Recent studies revealed that hearing loss could cause social isolation and depression, which is associated with health-related quality of life (HRQoL). However, there is a lack of knowledge about the impact of the utilization of hearing aids on these outcomes. OBJECTIVE: To assess whether hearing aids use might be positively associated with the progression of cognitive function, depression, and HRQoL among PwD. METHODS: We analyzed two-year follow-up data from 258 PwD (≥70 years, living at home). Cognitive decline was measured with Mini-Mental Status Examination (MMSE), depression using Geriatric Depression Scale (GDS), and HRQoL with Quality of Life in Alzheimer's Disease Scale (QoL-AD). The impact of hearing aid utilization on the progression of outcomes was assessed using multivariate regression models. RESULTS: 123 patients had hearing loss (47.7%), from which n = 54 (43.9%) used hearing aids. Patients with hearing loss were older and had a lower HRQoL than those without hearing loss. Use of hearing aids in patients with hearing loss was associated with a lower increase in depressive symptoms (b = -0.74, CI95 -1.48 --0.01, p = 0.047) over time as compared to those not using hearing aids. There was no effect on PwD's cognition, and the association with higher HRQoL was significant after one, but not consistently over two years. CONCLUSION: Early detection and intervention of presbycusis using hearing aids might improve mental health and HRQoL in dementia.
Keywords: Aged; Cognitive Dysfunction; Deafness; Dementia; Depression; Hearing Aids; Humans; Presbycusis; Quality of Life

Impact of the MIND Diet on Cognition in Individuals with Dementia. - Healy, Elizabeth (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) plagues 6.5 million Americans 65+, yet treatments are lacking. The Mediterranean-DASH Intervention for Neurodegenerative Delay (MIND) diet has been developed to address the expansive impact of dementias on the general public. This systematic review evaluated the impact of the MIND diet on cognition in those with pathologies across the dementia spectrum. OBJECTIVE: To evaluate the application of the MIND diet for prevention and/or treatment of dementia. METHODS: PubMed was used to conduct a search using the MIND diet and terms related to cognition. Articles were excluded if they were published prior to 2018, studied a population without dementia or significant risk factors, or did not include those 65 + . The overall quality of each source was analyzed based on the cognitive test(s) used, the selection of subjects, and the sample size. RESULTS: The search generated 33 papers, which yielded 11 articles after screening. Of these studies, one was conducted on those with mild cognitive impairment, one with AD, two with general dementia, and seven with at-risk individuals. All the studies found a positive correlation between adherence and some form of cognitive functioning, but results were mixed for specific cognitive domains. CONCLUSIONS: These findings suggest that the MIND diet may be a useful long-term treatment option for those with various dementia pathologies. However, more research is needed on subjects with onset dementias. Additionally, there is a need for more research into the mechanisms behind the common comorbidities.
Keywords: Alzheimer Disease; Cognition; Cognition Disorders; Cognitive Dysfunction; Diet, Mediterranean; Humans

The Lipid Invasion Model: Growing Evidence for This New Explanation of Alzheimer's Disease. - Rudge, Jonathan D'Arcy (J Alzheimers Dis, 2023)
The Lipid Invasion Model (LIM) is a new hypothesis for Alzheimer's disease (AD) which argues that AD is a result of external lipid invasion to the brain, following damage to the blood-brain barrier (BBB). The LIM provides a comprehensive explanation of the observed neuropathologies associated with the disease, including the lipid irregularities first described by Alois Alzheimer himself, and accounts for the wide range of risk factors now identified with AD, all of which are also associated with damage to the BBB. This article summarizes the main arguments of the LIM, and new evidence and arguments in support of it. The LIM incorporates and extends the amyloid hypothesis, the current main explanation of the disease, but argues that the greatest cause of late-onset AD is not amyloid-β (Aβ) but bad cholesterol and free fatty acids, let into the brain by a damaged BBB. It suggests that the focus on Aβ is the reason why we have made so little progress in treating the disease in the last 30 years. As well as offering new perspectives for further research into the diagnosis, prevention, and treatment of AD, based on protecting and repairing the BBB, the LIM provides potential new insights into other neurodegenerative diseases such as Parkinson's disease and amyotrophic lateral sclerosis/motor neuron disease.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Blood-Brain Barrier; Brain; Cholesterol; Humans

Lithium Provides Broad Therapeutic Benefits in an Alzheimer's Disease Mouse Model. - Wiseman, Alyssa L; Briggs, Clark A; Peritt, Ariel; Kapecki, Nicolas; Peterson, Daniel A; Shim, Seong S; Stutzmann, Grace E (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) is a chronic neurodegenerative disorder with a progressive loss of cognitive function. Currently, no effective treatment regimen is available. Lithium, a mood stabilizer for bipolar disorder, exerts broad neuroprotective and neurotrophic actions and improves cognitive function. OBJECTIVE: The study investigated if lithium stabilizes Ca2+ signaling abnormalities in hippocampal neurons and subsequently normalize downstream effects on AD neuropathology and synaptic plasticity in young AD mice. METHODS: Four-month-old 3xTg-AD mice were treated with a LiCl diet chow for 30 days. At the end of the lithium treatment, a combination of two-photon Ca2+ imaging, electrophysiology, and immunohistochemistry assays were used to assess the effects of the LiCl treatment on inositol trisphosphate receptor (IP3R)-dependent endoplasmic reticulum (ER) Ca2+ and voltage-gated Ca2+ channel (VGCC)-mediated Ca2+ signaling in CA1 neurons, neuronal nitric oxide synthase (nNOS) and hyperphosphorylated tau (p-tau) levels and synaptic plasticity in the hippocampus and overlying cortex from 3xTg-ADmice. RESULTS: Thirty-day LiCl treatment reduced aberrant IP3R-dependent ER Ca2+ and VGCC-mediated Ca2+ signaling in CA1 pyramidal neurons from 3xTg-AD mice and restored neuronal nitric oxide synthase (nNOS) and hyperphosphorylated tau (p-tau) levels to control levels in the hippocampal subfields and overlying cortex. The LiCl treatment enhanced post-tetanic potentiation (PTP), a form of short-term plasticity in the hippocampus. CONCLUSION: The study found that lithium exerts therapeutic effects across several AD-associated early neuronal signaling abnormalities including aberrant Ca2+ signaling, nNOS, and p-tau formation and enhances short-term synaptic plasticity. Lithium could serve as an effective treatment or co-therapeutic for AD.
Keywords: Alzheimer Disease; Animals; Calcium; Disease Models, Animal; Hippocampus; Lithium; Mice; Mice, Transgenic; Nitric Oxide Synthase Type I; tau Proteins

Longitudinal White and Gray Matter Response to Precision Medicine-Guided Intervention for Alzheimer's Disease. - Chwa, Won Jong; Raji, Cyrus A; Toups, Kat; Hathaway, Ann; Gordon, Deborah; Chung, Henrianna; Boyd, Alan; Hill, Benjamin D; Hausman-Cohen, Sharon; Attarha, Mouna; Jarrett, Michael; Bredesen, Dale E (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) is a debilitating condition that is widely known to adversely affect gray matter (GM) and white matter (WM) tracts within the brain. Recently, precision medicine has shown promise in alleviating the clinical and gross morphological trajectories of patients with AD. However, regional morphological changes have not yet been adequately characterized. OBJECTIVE: Investigate regional morphological responses to a precision medicine-guided intervention with regards to white and gray matter in AD and mild cognitive impairment (MCI). METHODS: Clinical and neuroimaging data were compiled over a 9-month period from 25 individuals who were diagnosed with AD or MCI receiving individualized treatment plans. Structural T1-weighted MRI scans underwent segmentation and volumetric quantifications via Neuroreader. Longitudinal changes were calculated via annualized percent change of WM or GM ratios. RESULTS: Montreal Cognitive Assessment scores (p < 0.001) and various domains of the Computerized Neurocognitive Screening Vital Signs significantly improved from baseline to 9-month follow-up. There was regional variability in WM and GM atrophy or hypertrophy, but none of these observed changes were statistically significant after correction for multiple comparisons.
Keywords: Alzheimer Disease; Atrophy; Brain; Cognitive Dysfunction; Gray Matter; Humans; Magnetic Resonance Imaging; Precision Medicine; White Matter

Medial Temporal Lobe Atrophy in Predementia Alzheimer's Disease: A Longitudinal Multi-Site Study Comparing Staging and A/T/N in a Clinical Research Cohort. - Jarholm, Jonas Alexander; Bjørnerud, Atle; Dalaker, Turi Olene; Akhavi, Mehdi Sadat; Kirsebom, Bjørn Eivind; Pålhaugen, Lene; Nordengen, Kaja; Grøntvedt, Gøril Rolfseng; Nakling, Arne; Kalheim, Lisa F; Almdahl, Ina S; Tecelao, Sandra; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Atrophy of the medial temporal lobe (MTL) is a biological characteristic of Alzheimer's disease (AD) and can be measured by segmentation of magnetic resonance images (MRI). OBJECTIVE: To assess the clinical utility of automated volumetry in a cognitively well-defined and biomarker-classified multi-center longitudinal predementia cohort. METHODS: We used Automatic Segmentation of Hippocampal Subfields (ASHS) to determine MTL morphometry from MRI. We harmonized scanner effects using the recently developed longitudinal ComBat. Subjects were classified according to the A/T/N system, and as normal controls (NC), subjective cognitive decline (SCD), or mild cognitive impairment (MCI). Positive or negative values of A, T, and N were determined by cerebrospinal fluid measurements of the Aβ42/40 ratio, phosphorylated and total tau. From 406 included subjects, longitudinal data was available for 206 subjects by stage, and 212 subjects by A/T/N. RESULTS: Compared to A-/T-/N- at baseline, the entorhinal cortex, anterior and posterior hippocampus were smaller in A+/T+orN+. Compared to NC A- at baseline, these subregions were also smaller in MCI A+. Longitudinally, SCD A+ and MCI A+, and A+/T-/N- and A+/T+orN+, had significantly greater atrophy compared to controls in both anterior and posterior hippocampus. In the entorhinal and parahippocampal cortices, longitudinal atrophy was observed only in MCI A+ compared to NC A-, and in A+/T-/N- and A+/T+orN+ compared to A-/T-/N-. CONCLUSION: We found MTL neurodegeneration largely consistent with existing models, suggesting that harmonized MRI volumetry may be used under conditions that are common in clinical multi-center cohorts.
Keywords: Alzheimer Disease; Atrophy; Cognitive Dysfunction; Entorhinal Cortex; Hippocampus; Humans; Magnetic Resonance Imaging; Temporal Lobe

Mediation Effect of Brain Volume on the Relationship Between Peripheral Inflammation and Cognitive Decline. - Zhuo, Bingting; Zheng, Dashan; Cai, Miao; Wang, Chongjian; Zhang, Shiyu; Zhang, Zilong; Tian, Fei; Wang, Xiaojie; Lin, Hualiang (J Alzheimers Dis, 2023)
BACKGROUND: Studies have reported the associations between inflammation, brain volume, and cognition separately. It is reasonable to assume peripheral inflammation may contribute to cognitive decline through brain volume atrophy. OBJECTIVE: To examine the associations between peripheral inflammation, brain volume, and cognition among adults, and to investigate whether brain volume atrophy mediates the inflammation-cognition relationshipMethods:We retrieved 20,381 participants with available data on peripheral inflammation, brain volume, and cognition from the UK Biobank cohort. Cognitive function was assessed by performance on cognitive tasks probing various cognitive domains. Brain volumes were measured by magnetic resonance imaging (MRI). Multivariable linear models were used to investigate the associations between three peripheral inflammatory indexes (C-reactive protein, systemic immune-inflammatory index, neutrophil-to-lymphocyte ratio), brain volume, and cognition. Mediation analyses were conducted to assess the potential mediating effect of brain volume atrophy. All results were corrected for multiple comparisons using the false-discovery rate (FDR). RESULTS: Peripheral inflammation was inversely associated with grey matter volume (GMV), white matter volume (WMV), and cognition after adjusting for potential covariates. For instance, CRP was associated with the GMV of left parahippocampal gyrus (β= -0.05, 95% confidence interval [CI]: -0.06 to -0.04, pFDR =1.07×10-16) and general cognitive factor (β= -0.03, 95% CI: -0. -0.04 to -0.01, pFDR = 0.001). Brain volume atrophy mediated the inflammation-cognitive decline relationship, accounting for 15-29% of the overall impact. CONCLUSION: In this cohort study, peripheral inflammation was associated with brain volume atrophy and cognitive decline. Brain atrophy may mediate the inflammation-cognitive decline relationship.
Keywords: Atrophy; Brain; Cognition; Cognitive Dysfunction; Cohort Studies; Encephalitis; Humans; Inflammation; Magnetic Resonance Imaging

Microglia-Astrocyte Communication in Alzheimer's Disease. - Wu, Yingying; Eisel, Ulrich L M (J Alzheimers Dis, 2023)
Microglia and astrocytes are regarded as active participants in the central nervous system under various neuropathological conditions, including Alzheimer's disease (AD). Both microglia and astrocyte activation have been reported to occur with a spatially and temporarily distinct pattern. Acting as a double-edged sword, glia-mediated neuroinflammation may be both detrimental and beneficial to the brain. In a variety of neuropathologies, microglia are activated before astrocytes, which facilitates astrocyte activation. Yet reactive astrocytes can also prevent the activation of adjacent microglia in addition to helping them become activated. Studies describe changes in the genetic profile as well as cellular and molecular responses of these two types of glial cells that contribute to dysfunctional immune crosstalk in AD. In this paper, we construct current knowledge of microglia-astrocyte communication, highlighting the multifaceted functions of microglia and astrocytes and their role in AD. A thorough comprehension of microglia-astrocyte communication could hasten the creation of novel AD treatment approaches.
Keywords: Alzheimer Disease; Astrocytes; Central Nervous System; Communication; Humans; Microglia

Mild Cognitive Impairment is Associated with Poorer Everyday Decision Making. - Fenton, Laura; Han, S Duke; DiGuiseppi, Carolyn G; Fowler, Nicole R; Hill, Linda; Johnson, Rachel L; Peterson, Ryan A; Knoepke, Christopher E; Matlock, Daniel D; Moran, Ryan; Karlawish, Jason; Betz, Marian E (J Alzheimers Dis, 2023)
BACKGROUND: Older adults are faced with many unique and highly consequential decisions such as those related to finances, healthcare, and everyday functioning (e.g., driving cessation). Given the significant impact of these decisions on independence, wellbeing, and safety, an understanding of how cognitive impairment may impact decision making in older age is important. OBJECTIVE: To examine the impact of mild cognitive impairment (MCI) on responses to a modified version of the Short Portable Assessment of Capacity for Everyday Decision making (SPACED). METHODS: Participants were community-dwelling, actively driving older adults (N = 301; M age = 77.1 years, SD = 5.1; 69.4% with a college degree or higher; 51.2% female; 95.3% White) enrolled in the Advancing Understanding of Transportation Options (AUTO) study. A generalized linear model adjusted for age, education, sex, randomization group, cognitive assessment method, and study site was used to examine the relationship between MCI status and decision making. RESULTS: MCI status was associated with poorer decision making; participants with MCI missed an average of 2.17 times more points on the SPACED than those without MCI (adjusted mean ratio: 2.17, 95% CI: 1.02, 4.61, p = 0.044). CONCLUSION: This finding supports the idea that older adults with MCI exhibit poorer decision-making abilities than cognitively normal older adults. It also suggests that older adults with MCI may exhibit poorer decision making across a wide range of decision contexts.
Keywords: Aged; Cognitive Dysfunction; Decision Making; Delivery of Health Care; Educational Status; Female; Humans; Independent Living; Male

Mitochondria Profoundly Influence Apolipoprotein E Biology. - Gabrielli, Alexander P; Weidling, Ian; Ranjan, Amol; Wang, Xiaowan; Novikova, Lesya; Chowdhury, Subir Roy; Menta, Blaise; Berkowicz, Alexandra; Wilkins, Heather M; Peterson, Kenneth R; Swerdlow, Russell H (J Alzheimers Dis, 2023)
BACKGROUND: Mitochondria can trigger Alzheimer's disease (AD)-associated molecular phenomena, but how mitochondria impact apolipoprotein E (APOE; apoE) is not well known. OBJECTIVE: Consider whether and how mitochondrial biology influences APOE and apoE biology. METHODS: We measured APOE expression in human SH-SY5Y neuronal cells with different forms of mitochondrial dysfunction including total, chronic mitochondrial DNA (mtDNA) depletion (ρ0 cells); acute, partial mtDNA depletion; and toxin-induced mitochondrial dysfunction. We further assessed intracellular and secreted apoE protein levels in the ρ0 cells and interrogated the impact of transcription factors and stress signaling pathways known to influence APOE expression. RESULTS: SH-SY5Y ρ0 cells exhibited a 65-fold increase in APOE mRNA, an 8-fold increase in secreted apoE protein, and increased intracellular apoE protein. Other models of primary mitochondrial dysfunction including partial mtDNA-depletion, toxin-induced respiratory chain inhibition, and chemical-induced manipulations of the mitochondrial membrane potential similarly increased SH-SY5Y cell APOE mRNA. We explored potential mediators and found in the ρ0 cells knock-down of the C/EBPα and NFE2L2 (Nrf2) transcription factors reduced APOE mRNA. The activity of two mitogen-activated protein kinases, JNK and ERK, also strongly influenced ρ0 cell APOE mRNA levels. CONCLUSION: Primary mitochondrial dysfunction either directly or indirectly activates APOE expression in a neuronal cell model by altering transcription factors and stress signaling pathways. These studies demonstrate mitochondrial biology can influence the biology of the APOE gene and apoE protein, which are implicated in AD.
Keywords: Alzheimer Disease; Apolipoproteins E; Biology; Cell Line, Tumor; DNA, Mitochondrial; Humans; Mitochondria; Neuroblastoma; RNA, Messenger; Transcription Factors

Mortality Risks and Causes of Death by Dementia Types in a Japanese Cohort with Dementia: NCGG-STORIES. - Ono, Rei; Sakurai, Takashi; Sugimoto, Taiki; Uchida, Kazuaki; Nakagawa, Takeshi; Noguchi, Taiji; Komatsu, Ayane; Arai, Hidenori; Saito, Tami (J Alzheimers Dis, 2023)
BACKGROUND: Prognosis-related information regarding dementia needs to be updated, as changes in medical and long-term care environments for patients with dementia in recent decades may be improving the prognosis of the disease. OBJECTIVE: We aimed to investigate the mortality, cause of death, and prognostic factors by types of dementia in a Japanese clinic-based cohort. METHODS: The National Center for Geriatrics and Gerontology-Life Stories of People with Dementia consists of clinical records and prognostic data of patients who visited the Memory Clinic in Japan. Patients who attended the clinic between July 2010 and September 2018, or their close relatives, were asked about death information via a postal survey. A cohort of 3,229 patients (mean age, 76.9; female, 1,953) was classified into six groups: normal cognition (NC), mild cognitive impairment (MCI), Alzheimer's disease (AD), vascular dementia, dementia with Lewy bodies (DLB), and frontotemporal lobar degeneration. A Cox proportional hazards model was employed to compare the mortality of each type of dementia, MCI, and NC. RESULTS: Patients with all types of dementia and MCI had higher mortality rates than those with NC (hazard risks: 2.61-5.20). The most common cause of death was pneumonia, followed by cancer. In the MCI, AD, and DLB groups, older age, male sex, and low cognitive function were common prognostic factors but not presence of apolipoprotein E ɛ4 allele. CONCLUSION: Our findings suggest important differences in the mortality risk and cause of death among patients with dementia, which will be useful in advanced care planning and policymaking.
Keywords: Aged; Alzheimer Disease; Cause of Death; Cognitive Dysfunction; Dementia; East Asian People; Female; Humans; Lewy Body Disease; Male

Neural Stem Cells in the Treatment of Alzheimer's Disease: Current Status, Challenges, and Future Prospects. - Chen, Xiaokun; Jiang, Shenzhong; Wang, Renzhi; Bao, Xinjie; Li, Yongning (J Alzheimers Dis, 2023)
Alzheimer's disease (AD), a progressive dementia, is one of the world's most dangerous and debilitating diseases. Clinical trial results of amyloid-β (Aβ) and tau regulators based on the pretext of straightforward amyloid and tau immunotherapy were disappointing. There are currently no effective strategies for slowing the progression of AD. Further understanding of the mechanisms underlying AD and the development of novel therapeutic options are critical. Neurogenesis is impaired in AD, which contributes to memory deficits. Transplanted neural stem cells (NSCs) can regenerate degraded cholinergic neurons, and new neurons derived from NSCs can form synaptic connections with neighboring neurons. In theory, employing NSCs to replace and restore damaged cholinergic neurons and brain connections may offer new treatment options for AD. However there remain barriers to surmount before NSC-based therapy can be used clinically. The objective of this article is to describe recent advances in the treatment of AD models and clinical trials involving NSCs. In addition, we discuss the challenges and prospects associated with cell transplant therapy for AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Cholinergic Neurons; Disease Models, Animal; Humans; Neural Stem Cells

Non-Pharmacological Interventions for Feeding and Eating Disorders in Persons with Dementia: Systematic Review and Evidence Summary. - Chen, Hong-Li; Li, Cheng; Wang, Jing; Fei, Yang; Min, Min; Zhao, Yue; Shan, En-Fang; Yin, Yue-Heng; Liu, Chong-Yuan; Li, Xian-Wen (J Alzheimers Dis, 2023)
BACKGROUND: Feeding and eating disorders related to cognitive and psycho-behavioral symptoms are strongly associated with health status in persons with dementia (PWD). Non-pharmacological interventions have been the priority selection to address this significant issue. However, the direct targets of non-pharmacological interventions are unclear and there is no consistent evidence of recommendations on the intervention of different dementia stages and the settings of intervention practice. OBJECTIVE: To provide caregivers with a set of self-help non-pharmacological interventions for feeding and eating disorders in PWD. METHODS: Based on the process of evidence summary, a systematic literature search was performed on dementia websites and seven databases. Two researchers screened the studies independently and appraise the quality. The evidence was graded by Joanna Briggs Institute Grades of Recommendation. RESULTS: Twenty-eight articles were included. Twenty-three non-pharmacological intervention recommendations were categorized into six themes containing oral nutritional supplementation, assistance with eating and drinking, person-centered mealtime care, environmental modification, education or training, and multi-component intervention. These interventions corresponded to three direct targets including improving engagement, making up for loss ability, and increasing food intake directly. They were applied to different stages of dementia and most interventions were targeted at PWD in long-term care institutions. CONCLUSION: This article summarized the direct targets and the specific implementation of recommendations at different stages of dementia to provide caregivers with self-help non-pharmacological interventions. The practice of recommendations was more applicable to institutionalized PWD. When applied to PWD at home, caregivers need to identify the specific feeding and eating conditions at different stages and adopted the interventions in conjunction with the wishes of the PWD and professional advice.
Keywords: Caregivers; Dementia; Feeding and Eating Disorders; Health Status; Humans; Nutritional Status

Observed Improvement in Cognition During a Personalized Lifestyle Intervention in People with Cognitive Decline. - Sandison, Heather; Callan, Nini G L; Rao, Rammohan V; Phipps, John; Bradley, Ryan (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) is a chronic condition marked by progressive objective cognitive impairment (OCI). No monotherapy has substantially altered disease progression, suggesting the disease is multifactorial and may require a multimodal therapeutic approach. OBJECTIVE: We sought to determine if cognitive function in a sample with OCI would change in response to a multimodal, individualized care plan based on potential contributors to cognitive decline (e.g., nutritional status, infection, etc.). METHODS: Participants (n = 34) were recruited from the San Diego, CA area. The multimodal intervention included lifestyle changes (i.e., movement, diet, and stress management), nutraceutical support, and medications. It was delivered pragmatically over four clinical visits, and outcome measures were gathered at four study visits, occurring at baseline, one, three, and six months (primary endpoint). Study participants received weekly phone calls for nutrition support throughout study participation. Outcome measures included the Cambridge Brain Sciences (CBS) battery, and the Montreal Cognitive Assessment (MoCA). RESULTS: At 6 months, mean MoCA scores improved from 19.6±3.1 to 21.7±6.2 (p = 0.013). Significant improvement was observed in mean scores of the CBS memory domain [25.2 (SD 23.3) to 35.8 (SD 26.9); p < 0.01] and CBS overall composite cognition score [24.5 (SD 16.1) to 29.7 (SD 20.5); p = 0.02]. All CBS domains improved. CONCLUSION: Multiple measures of cognitive function improved after six months of intervention. Our results support the feasibility and impact of a multimodal, individualized treatment approach to OCI, warranting further research.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; California; Cognition; Cognitive Dysfunction; Diet, Healthy; Dietary Supplements; Disease Progression; Exercise; Feasibility Studies; Female; Healthy Lifestyle; Humans; Infections; Male; Memory; Middle Aged; Nutritional Status; Pragmatic Clinical Trials as Topic; Reproducibility of Results; Stress, Psychological; Time Factors; Treatment Outcome; Verbal Behavior

Odor Discrimination as a Marker of Early Alzheimer's Disease. - Audronyte, Egle; Pakulaite-Kazliene, Gyte; Sutnikiene, Vaiva; Kaubrys, Gintaras (J Alzheimers Dis, 2023)
BACKGROUND: Olfactory dysfunction is an early symptom of Alzheimer's disease (AD). However, olfactory tests are rarely performed in clinical practice because their diagnostic efficacy in detecting early AD is unclear. OBJECTIVE: To investigate odor discrimination in patients with early AD and the efficacy of olfactory discrimination tests in differentiating these patients from subjects with normal cognition (CN). METHODS: Thirty patients each with mild dementia due to AD (MD-AD) and mild cognitive impairment due to AD (MCI-AD) and 30 older subjects with CN were enrolled. All participants underwent cognitive examinations (CDR, MMSE, ADAS-Cog 13, and verbal fluency) and odor discrimination tests (Sniffin' Sticks test, Burghart®, Germany). RESULTS: The MD-AD group achieved significantly worse scores on the olfactory discrimination test than the MCI-AD group, and the MCI-AD group achieved significantly worse results than the CN group (p < 0.05). A cut-off score of≤10 had a diagnostic accuracy of 94.44% (95% CI, 87.51-98.17%) in differentiating patients with MCI-AD/MD-AD from subjects with CN and of 91.67% (95% CI, 81.61-97.24%) in differentiating those with MCI-AD from subjects with CN. Our multinomial logistic regression model with demographic data and ADAS-Cog 13 scores as predictor variables correctly classified 82.2% of the cases (CN, 93.3%; MC-AD, 70%; MD-AD, 83.3%); on adding the olfactory discrimination score to the model, the percentage increased to 92.2% (CN, 96.7%; MCI-AD, 86.7%; MD-AD, 93.3%). CONCLUSION: Odor discrimination is impaired in cases of early AD and continues to deteriorate as the disease progresses. The olfactory discrimination test showed good diagnostic efficacy in detecting early AD.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Humans; Neuropsychological Tests; Odorants; Olfaction Disorders; Smell

The PI3K/AKT Signaling Pathway and Caspase-3 in Alzheimer's Disease: Which One Is the Beginner? - Khezri, Mohammad Rafi; Ghasemnejad-Berenji, Morteza; Moloodsouri, Donya (J Alzheimers Dis, 2023)
One of the main players in apoptosis during Alzheimer's disease progression are different members of caspase family of proteases. The most well-known member of this family is caspase-3, in which alterations of its levels have been detected in samples from Alzheimer's disease patients. There are numerous intracellular factors involved in regulation of cellular apoptosis through regulation of caspase-3 activity, the most important of which is the PI3K/AKT signaling pathway. This commentary tries to highlight the probable relations between PI3K/AKT signaling pathway and caspase-3 in Alzheimer's disease.
Keywords: Alzheimer Disease; Apoptosis; Caspase 3; Humans; Phosphatidylinositol 3-Kinases; Proto-Oncogene Proteins c-akt; Signal Transduction

Plasma Glial Fibrillary Acidic Protein Is Associated with 18F-SMBT-1 PET: Two Putative Astrocyte Reactivity Biomarkers for Alzheimer's Disease. - Chatterjee, Pratishtha; Doré, Vincent; Pedrini, Steve; Krishnadas, Natasha; Thota, Rohith; Bourgeat, Pierrick; Ikonomovic, Milos D; Rainey-Smith, Stephanie R; Burnham, Samantha C; Fowler, Christopher; Taddei, Kevin; Mulligan, Rachel; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Astrocyte reactivity is an early event along the Alzheimer's disease (AD) continuum. Plasma glial fibrillary acidic protein (GFAP), posited to reflect astrocyte reactivity, is elevated across the AD continuum from preclinical to dementia stages. Monoamine oxidase-B (MAO-B) is also elevated in reactive astrocytes observed using 18F-SMBT-1 PET in AD. OBJECTIVE: The objective of this study was to evaluate the association between the abovementioned astrocyte reactivity biomarkers. METHODS: Plasma GFAP and Aβ were measured using the Simoa® platform in participants who underwent brain 18F-SMBT-1 and Aβ-PET imaging, comprising 54 healthy control (13 Aβ-PET+ and 41 Aβ-PET-), 11 mild cognitively impaired (3 Aβ-PET+ and 8 Aβ-PET-) and 6 probable AD (5 Aβ-PET+ and 1 Aβ-PET-) individuals. Linear regressions were used to assess associations of interest. RESULTS: Plasma GFAP was associated with 18F-SMBT-1 signal in brain regions prone to early Aβ deposition in AD, such as the supramarginal gyrus (SG), posterior cingulate (PC), lateral temporal (LT) and lateral occipital cortex (LO). After adjusting for age, sex, APOE ɛ4 genotype, and soluble Aβ (plasma Aβ42/40 ratio), plasma GFAP was associated with 18F-SMBT-1 signal in the SG, PC, LT, LO, and superior parietal cortex (SP). On adjusting for age, sex, APOE ɛ4 genotype and insoluble Aβ (Aβ-PET), plasma GFAP was associated with 18F-SMBT-1 signal in the SG. CONCLUSION: There is an association between plasma GFAP and regional 18F-SMBT-1 PET, and this association appears to be dependent on brain Aβ load.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Astrocytes; Biomarkers; Brain; Cognitive Dysfunction; Glial Fibrillary Acidic Protein; Humans; Positron-Emission Tomography; tau Proteins

Plasma Soluble ST2 Levels Are Higher in Neurodegenerative Disorders and Associated with Poorer Cognition. - Tan, Yi Jayne; Siow, Isabel; Saffari, Seyed Ehsan; Ting, Simon K S; Li, Zeng; Kandiah, Nagaendran; Tan, Louis C S; Tan, Eng King; Ng, Adeline S L (J Alzheimers Dis, 2023)
BACKGROUND: Suppressor of tumorgenicity 2 (ST2) is highly expressed in brain tissue and is a receptor for interleukin 33 (IL-33). ST2 exists in two forms, a transmembrane receptor (ST2L) and a soluble decoy receptor (sST2). IL-33 binds to ST2L, triggering downstream signaling pathways involved in amyloid plaque clearance. Conversely, sST2 binds competitively to IL-33, attenuating its neuroprotective effects. High sST2 levels have been reported in mild cognitive impairment (MCI) and Alzheimer's disease (AD), suggesting that the IL-33/ST2 signaling pathway may be implicated in neurodegenerative diseases. OBJECTIVE: To investigate plasma sST2 levels in controls and patients with MCI, AD, frontotemporal dementia (FTD), and Parkinson's disease (PD). METHODS: Plasma sST2 levels were measured using ELISA in 397 subjects (91 HC, 46 MCI, 38 AD, 28 FTD, and 194 PD). Cerebrospinal fluid (CSF) levels of sST2 were measured in 22 subjects. Relationship between sST2 and clinical outcomes were analyzed. RESULTS: Plasma sST2 levels were increased across all disease groups compared to controls, with highest levels seen in FTD followed by AD and PD. Dementia patients with higher sST2 had lower cross-sectional cognitive scores in Frontal Assessment Battery and Digit Span Backward. At baseline, PD-MCI patients had higher sST2, associated with worse attention. In the longitudinal PD cohort, higher sST2 significantly associated with decline in global cognition and visuospatial domains. Plasma sST2 levels correlated with CSF sST2 levels. CONCLUSION: Plasma sST2 is raised across neurodegenerative diseases and is associated with poorer cognition. Higher baseline sST2 is a potential biomarker of disease severity in neurodegeneration.
Keywords: Alzheimer Disease; Biomarkers; Cognition; Cross-Sectional Studies; Frontotemporal Dementia; Humans; Interleukin-1 Receptor-Like 1 Protein; Interleukin-33; Parkinson Disease

Playing Russian Roulette with Alzheimer's Disease Patients: Do the Cognitive Benefits of Lecanemab Outweigh the Risk of Edema, Stroke and Encephalitis? - Atwood, Craig S; Perry, George (J Alzheimers Dis, 2023)
The questionable approval of aducanumab and the recent approval of lecanemab (Leqembi; Eisai and Biogen) by the FDA has raised the issue of safety (stroke, meningitis, and encephalitis) over efficacy (slowing of cognitive decline). This communication recounts the important physiological functions of amyloid-β as a barrier protein with unique sealant and anti-pathogenic activities important for maintaining vascular integrity coupled with innate immune functions that prevent encephalitis and meningitis. The approval of a drug that obviates both of these purposive functions increases the risk of hemorrhage, edema and downstream pathogenic outcomes and should be clearly outlined to patients.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Cognition; Edema; Encephalitis; Humans; Russia; Stroke

PM2.5 and Dementia in a Low Exposure Setting: The Influence of Odor Identification Ability and APOE. - Andersson, John; Sundström, Anna; Nordin, Maria; Segersson, David; Forsberg, Bertil; Adolfsson, Rolf; Oudin, Anna (J Alzheimers Dis, 2023)
BACKGROUND: Growing evidence show that long term exposure to air pollution increases the risk of dementia. OBJECTIVE: The aim of this study was to investigate associations between PM2.5 exposure and dementia in a low exposure area, and to investigate the role of olfaction and the APOE ɛ4 allele in these associations. METHODS: Data were drawn from the Betula project, a longitudinal study on aging, memory, and dementia in Sweden. Odor identification ability was assessed using the Scandinavian Odor Identification Test (SOIT). Annual mean PM2.5 concentrations were obtained from a dispersion-model and matched at the participants' residential address. Proportional hazard regression was used to calculate hazard ratios. RESULTS: Of 1,846 participants, 348 developed dementia during the 21-year follow-up period. The average annual mean PM2.5 exposure at baseline was 6.77μg/m3, which is 1.77μg/m3 above the WHO definition of clean air. In a fully adjusted model (adjusted for age, sex, APOE, SOIT, cardiovascular diseases and risk factors, and education) each 1μg/m3 difference in annual mean PM2.5-concentration was associated with a hazard ratio of 1.23 for dementia (95% CI: 1.01-1.50). Analyses stratified by APOE status (ɛ4 carriers versus non-carriers), and odor identification ability (high versus low), showed associations only for ɛ4 carriers, and for low performance on odor identification ability. CONCLUSION: PM2.5 was associated with an increased risk of dementia in this low pollution setting. The associations between PM2.5 and dementia seemed stronger in APOE carriers and those with below average odor identification ability.
Keywords: Air Pollutants; Air Pollution; Apolipoproteins E; Cohort Studies; Dementia; Environmental Exposure; Humans; Longitudinal Studies; Odorants; Particulate Matter

Poor Oral Health as a Risk Factor for Dementia in a Swedish Population: A Cohort Study with 40 Years of Follow-Up. - He, Fei; Luo, Huizi; Yin, Li; Roosaar, Ann; Axéll, Tony; Zhao, Hongwei; Ye, Weimin (J Alzheimers Dis, 2023)
BACKGROUND: Whether poor oral health is associated with dementia risk remains unclear. OBJECTIVE: We conducted a cohort study of 14,439 participants who were followed up for up to 40 years in Uppsala County, central Sweden, aiming to explore the association between poor oral health, namely the number of tooth loss, dental plaque status, and oral mucosal lesions, and the risk of dementia. METHODS: We used Cox proportional hazards regression model to derive cause-specific hazard ratios (HR) and corresponding 95% confidence intervals (CI), while adjusting for baseline potential confounders as well as a time-varying covariate, Charlson's Comorbidity Index score. RESULTS: Dementia risk was substantially higher among those with a higher number of tooth loss; compared to the group with tooth loss 0-10, the HRs were 1.21 (95% CI: 1.02, 1.42), 1.17 (95% CI: 0.97, 1.40), and 1.30 (95% CI: 1.09, 1.54) respectively for groups with increasing number of tooth loss. There was some evidence of dose-risk association in this study, with a HR of 1.10 (1.04, 1.18) comparing adjacent groups (ptrend = 0.001). In a stratified analysis by attained age, tooth loss was more pronouncedly associated with the risk of dementia onset before age 80 (those with 21-32 versus 0-10 lost teeth, HR = 1.82, (95% CI: 1.32, 2.51); HR = 1.22 (95% CI: 1.10, 1.35) comparing adjacent groups, ptrend < 0.001). CONCLUSION: In summary, there are some indications that poor oral health, as indicated by more tooth loss, is positively associated with an increased risk of dementia, especially for dementia onset before age 80.
Keywords: Aged, 80 and over; Cohort Studies; Dementia; Follow-Up Studies; Humans; Oral Health; Risk Factors; Sweden; Tooth Loss

Precision Medicine Approach to Alzheimer's Disease: Rationale and Implications. - Bredesen, Dale E; Toups, Kat; Hathaway, Ann; Gordon, Deborah; Chung, Henrianna; Raji, Cyrus; Boyd, Alan; Hill, Benjamin D; Hausman-Cohen, Sharon; Attarha, Mouna; Chwa, Won Jong; Kurakin, Alexei; et al. (J Alzheimers Dis, 2023)
The neurodegenerative disease field has enjoyed extremely limited success in the development of effective therapeutics. One potential reason is the lack of disease models that yield accurate predictions and optimal therapeutic targets. Standard clinical trials have pre-determined a single treatment modality, which may be unrelated to the primary drivers of neurodegeneration. Recent proof-of-concept clinical trials using a precision medicine approach suggest a new model of Alzheimer's disease (AD) as a chronic innate encephalitis that creates a network insufficiency. Identifying and addressing the multiple potential contributors to cognitive decline for each patient may represent a more effective strategy. Here we review the rationale for a precision medicine approach in prevention and treatment of cognitive decline associated with AD. Results and implications from recent proof-of-concept clinical trials are presented. Randomized controlled trials, with much larger patient numbers, are likely to be significant to establishing precision medicine protocols as a standard of care for prevention and treatment of cognitive decline. Furthermore, combining this approach with the pharmaceutical approach offers the potential for enhanced outcomes. However, incorporating precision medicine approaches into everyday evaluation and care, as well as future clinical trials, would require fundamental changes in trial design, IRB considerations, funding considerations, laboratory evaluation, personalized treatment plans, treatment teams, and ultimately in reimbursement guidelines. Nonetheless, precision medicine approaches to AD, based on a novel model of AD pathophysiology, offer promise that has not been realized to date with monotherapeutic approaches.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Humans; Neurodegenerative Diseases; Precision Medicine

Preventing Neurocognitive Decline in Adults Aging with HIV: Implications for Practice and Research. - Cody, Shameka L; Miller, Gabe H; Fazeli, Pariya L; Wang, Ge; Li, Wei; Goodin, Burel R; Vance, David E (J Alzheimers Dis, 2023)
Mild to moderate forms of neurocognitive impairment persist among people living with HIV (PLWH), despite being virally suppressed on antiretroviral therapy. PLWH are disproportionally impacted by physiological and psychosocial comorbidities compared to those without HIV. As adults live longer with HIV, the neurocognitive burden of physiological and psychosocial stressors can impair everyday functioning and may contribute to the development of neurodegenerative diseases such as Alzheimer's disease. This article outlines neurocognitive consequences of everyday stressors in PLWH. While some lifestyle factors can exacerbate inflammatory processes and promote negative neurocognitive health, novel interventions including the use of cannabinoids may be neuroprotective for aging PLWH who are at risk for elevated levels of inflammation from comorbidities. Studies of integrated neurocognitive rehabilitation strategies targeting lifestyle factors are promising for improving neurocognitive health, and may over time, reduce the risk of Alzheimer's disease in PLWH.
Keywords: Aging; Alzheimer Disease; Comorbidity; HIV Infections; Humans

The Role of Interferon-α in Neurodegenerative Diseases: A Systematic Review. - Hui, Brendan Su Mee; Zhi, Lee Rui; Retinasamy, Thaarvena; Arulsamy, Alina; Law, Christine Shing Wei; Shaikh, Mohd Farooq; Yeong, Keng Yoon (J Alzheimers Dis, 2023)
BACKGROUND: Neurodegenerative diseases (NDs) impose significant financial and healthcare burden on populations all over the world. The prevalence and incidence of NDs have been observed to increase dramatically with age. Hence, the number of reported cases is projected to increase in the future, as life spans continues to rise. Despite this, there is limited effective treatment against most NDs. Interferons (IFNs), a family of cytokines, have been suggested as a promising therapeutic target for NDs, particularly IFN-α, which governs various pathological pathways in different NDs. OBJECTIVE: This systematic review aimed to critically appraise the currently available literature on the pathological role of IFN-α in neurodegeneration/NDs. METHODS: Three databases, Scopus, PubMed, and Ovid Medline, were utilized for the literature search. RESULTS: A total of 77 journal articles were selected for critical evaluation, based on the inclusion and exclusion criteria. The studies selected and elucidated in this current systematic review have showed that IFN-α may play a deleterious role in neurodegenerative diseases through its strong association with the inflammatory processes resulting in mainly neurocognitive impairments. IFN-α may be displaying its neurotoxic function via various mechanisms such as abnormal calcium mineralization, activation of STAT1-dependent mechanisms, and increased quinolinic acid production. CONCLUSION: The exact role IFN-α in these neurodegenerative diseases have yet to be determine due to a lack in more recent evidence, thereby creating a variability in the role of IFN-α. Future investigations should thus be conducted, so that the role played by IFN-α in neurodegenerative diseases could be delineated.
Keywords: Cytokines; Databases, Factual; Humans; Interferon-alpha; Neurodegenerative Diseases

Safety, Feasibility, and Potential Clinical Efficacy of 40 Hz Invisible Spectral Flicker versus Placebo in Patients with Mild-to-Moderate Alzheimer's Disease: A Randomized, Placebo-Controlled, Double-Blinded, Pilot Study. - Agger, Mikkel Pejstrup; Danielsen, Else Rubæk; Carstensen, Marcus Schultz; Nguyen, N Mai; Horning, Maibritt; Henney, Mark Alexander; Jensen, Christopher Boe Ravn; Baandrup, Anders Ohlhues; Kjær, Troels Wesenberg; Madsen, Kristoffer Hougaard; Miskowiak, Kamilla; Petersen, Paul Michael; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Recent studies suggested induction of 40 Hz neural activity as a potential treatment for Alzheimer's disease (AD). However, prolonged exposure to flickering light raises adherence and safety concerns, encouraging investigation of tolerable light stimulation protocols. OBJECTIVE: To investigate the safety, feasibility, and exploratory measures of efficacy. METHODS: This two-stage randomized placebo-controlled double-blinded clinical trial, recruited first cognitive healthy participants (n = 3/2 active/placebo), and subsequently patients with mild-to-moderate AD (n = 5/6, active/placebo). Participants were randomized 1:1 to receive either active intervention with 40 Hz Invisible Spectral Flicker (ISF) or placebo intervention with color and intensity matched non-flickering white light. RESULTS: Few and mild adverse events were observed. Adherence was above 86.1% of intended treatment days, with participants remaining in front of the device for >51.3 min (60 max) and directed gaze >34.9 min. Secondary outcomes of cognition indicate a tendency towards improvement in the active group compared to placebo (mean: -2.6/1.5, SD: 6.58/6.53, active/placebo) at week 6. Changes in hippocampal and ventricular volume also showed no tendency of improvement in the active group at week 6 compared to placebo. At week 12, a potential delayed effect of the intervention was seen on the volume of the hippocampus in the active group compared to placebo (mean: 0.34/-2.03, SD: 3.26/1.18, active/placebo), and the ventricular volume active group (mean: -0.36/2.50, SD: 1.89/2.05, active/placebo), compared to placebo. CONCLUSION: Treatment with 40 Hz ISF offers no significant safety or adherence concerns. Potential impact on secondary outcomes must be tested in larger scale clinical trials.
Keywords: Alzheimer Disease; Cognition; Double-Blind Method; Feasibility Studies; Humans; Pilot Projects; Treatment Outcome

Serotonin Degeneration and Amyloid-β Deposition in Mild Cognitive Impairment: Relationship to Cognitive Deficits. - Smith, Gwenn S; Kuwabara, Hiroto; Yan, Haijuan; Nassery, Najlla; Yoon, Mark; Kamath, Vidya; Kraut, Michael; Gould, Neda F; Savonenko, Alena; Coughlin, Jennifer M; Lodge, Martin; Pomper, Martin G; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Neuropathological and neuroimaging studies have demonstrated degeneration of the serotonin system in Alzheimer's disease (AD). Neuroimaging studies have extended these observations to the preclinical stages of AD, mild cognitive impairment (MCI). Serotonin degeneration has been observed also in transgenic amyloid mouse models, prior to widespread cortical distribution of amyloid-β (Aβ). OBJECTIVE: The present study evaluated the regional distribution of the serotonin transporter (5-HTT) and of Aβ in individuals with MCI and healthy older controls, as well as the contribution of 5-HTT and Aβ to cognitive deficits. METHODS: Forty-nine MCI participants and 45 healthy older controls underwent positron emission tomography (PET) imaging of 5-HTT and Aβ, structural magnetic resonance imaging and neuropsychological assessments. RESULTS: Lower cortical, striatal, and limbic 5-HTT and higher cortical Aβ was observed in MCIs relative to healthy controls. Lower 5-HTT, mainly in limbic regions, was correlated with greater deficits in auditory-verbal and visual-spatial memory and semantic, not phonemic fluency. Higher cortical A β was associated with greater deficits in auditory-verbal and visual-spatial memory and in semantic, not phonemic fluency. When modeling the association between cognition, gray matter volumes and Aβ, inclusion of 5-HTT in limbic and in select cortical regions significantly improved model fit for auditory-verbal and visual-spatial memory and semantic, but not phonemic fluency. CONCLUSIONS: These results support the role of serotonin degeneration in the memory and semantic fluency deficits observed in MCI.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Cognition; Cognition Disorders; Cognitive Dysfunction; Humans; Mice; Positron-Emission Tomography; Serotonin

Soluble TREM2, Alzheimer's Disease Pathology, and Risk for Progression of Cerebral Small Vessel Disease: A Longitudinal Study. - Wu, Chao; Ma, Ya-Hui; Hu, Hao; Zhao, Bing; Tan, Lan (J Alzheimers Dis, 2023)
BackgroundUntil recently, studies on associations between neuroinflammation in vivo and cerebral small vessel disease (CSVD) are scarce. Cerebrospinal fluid (CSF) levels of soluble triggering receptor expressed on myeloid cells 2 (sTREM2), a candidate biomarker of microglial activation and neuroinflammation, were found elevated in Alzheimer's disease (AD), but they have not been fully explored in CSVD.ObjectiveTo determine whether CSF sTREM2 levels are associated with the increased risk of CSVD progression.MethodsA total of 426 individuals from the Alzheimer's Disease Neuroimaging Initiative (ADNI) database were included in this study. All participants underwent measurements of CSF sTREM2 and AD pathology (Aβ1-42, P-tau181P). The progression of CSVD burden and imaging markers, including cerebral microbleeds (CMBs), white matter hyperintensities and lacunes, were estimated based on neuroimaging changes. Logistic regression and moderation effect models were applied to explore associations of sTREM2 with CSVD progression and AD pathology.Results Higher CSF sTREM2 levels at baseline were associated with increased CSVD burden (OR = 1.28 [95% CI, 1.01-1.62]) and CMBs counts (OR = 1.32 [95% CI, 1.03-1.68]). Similarly, increased change rates of CSF sTREM2 might predict elevated CMBs counts (OR = 1.44 [95% CI, 1.05-1.98]). Participants with AD pathology (Aβ1-42 and P-tau181P) showed a stronger association between CSF sTREM2 and CSVD progression.ConclusionThis longitudinal study found a positive association between CSF sTREM2 and CSVD progression, suggesting that neuroinflammation might promote CSVD. Furthermore, neuroinflammation could be a shared pathogenesis of CSVD and AD at the early stage. Targeting neuroinflammation to intervene the progression of CSVD and AD warrants further investigation.
Keywords: Alzheimer Disease; Biomarkers; Cerebral Small Vessel Diseases; Humans; Longitudinal Studies; Membrane Glycoproteins; Myeloid Cells; Neuroinflammatory Diseases; Receptors, Immunologic

Vacuolar Protein-Sorting Proteins Are Reduced Even Before Cognitive Decline in a Mouse Model of Alzheimer's Disease. - Shinagawa, Hijiri; Ohuchi, Kazuki; Goto, Yuya; Hashimoto, Kohei; Kijima, Hideki; Maekawa, Shogo; Kurita, Hisaka; Inden, Masatoshi (J Alzheimers Dis, 2023)
Currently, interventions from the preclinical stage are considered necessary for the treatment of Alzheimer's disease (AD). Previous studies have reported that vacuolar protein-sorting protein (VPS), a retromer construct, is involved in the pathogenic mechanisms of AD and Parkinson's disease. This study evaluated VPS26, VPS29, and VPS35 before and after the onset of cognitive decline in an App knock-in mouse model of AD that more closely resembles the human pathology than previous AD models. The results showed that the expression of VPS26 and VPS35 decreased before the onset of cognitive decline, suggesting the possibility of anti-amyloid-β disease-modifying treatment targeting these proteins.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Cognitive Dysfunction; Humans; Mice; Protein Transport; Vesicular Transport Proteins

5-Hydroxymethylcytosine Signatures in Circulating Cell-Free DNA as Diagnostic Biomarkers for Late-Onset Alzheimer's Disease. - Chen, Lei; Shen, Qianqian; Xu, Shunliang; Yu, Hongzhuan; Pei, Shengjie; Zhang, Yangting; He, Xin; Wang, QiuZhen; Li, Duo (J Alzheimers Dis, 2022)
BACKGROUND: 5-Hydroxymethylcytosine (5hmC) is an epigenetic DNA modification that is highly abundant in central nervous system. It has been reported that DNA 5hmC dysregulation play a critical role in Alzheimer's disease (AD) pathology. Changes in 5hmC signatures can be detected in circulating cell-free DNA (cfDNA), which has shown potential as a non-invasive liquid biopsy material. OBJECTIVE: However, the genome-wide profiling of 5hmC in cfDNA and its potential for the diagnosis of AD has not been reported to date. METHODS: We carried out a case-control study and used a genome-wide chemical capture followed by high-throughput sequencing to detect the genome-wide profiles of 5hmC in human cfDNA and identified differentially hydroxymethylated regions (DhMRs) in late-onset AD patients and the control. RESULTS: We discovered significant differences of 5hmC enrichment in gene bodies which were linked to multiple AD pathogenesis-associated signaling pathways in AD patients compared with cognitively normal controls, indicating they can be well distinguished from normal controls by DhMRs in cfDNA. Specially, we identified 7 distinct genes (RABEP1, CPNE4, DNAJC15, REEP3, ROR1, CAMK1D, and RBFOX1) with predicting diagnostic potential based on their significant correlations with MMSE and MoCA scores of subjects. CONCLUSION: The present results suggest that 5hmC markers derived from plasma cfDNA can served as an effective, minimally invasive biomarkers for clinical auxiliary diagnosis of late-onset AD.
Keywords: 5-Methylcytosine; Aged; Alzheimer Disease; Biomarkers; Case-Control Studies; Cell-Free Nucleic Acids; DNA Methylation; DNA, Neoplasm; Epigenesis, Genetic; Female; High-Throughput Nucleotide Sequencing; Humans; Male; Middle Aged

Alteration of Gut Microbiota in Alzheimer's Disease and Their Relation to the Cognitive Impairment. - Khedr, Eman M; Omeran, Nehad; Karam-Allah Ramadan, Haidi; Ahmed, Gellan K; Abdelwarith, Ahmed M (J Alzheimers Dis, 2022)
BACKGROUND: Dysbiosis of gut microbiota has been reported to be enrolled in the pathogenesis of Alzheimer's disease (AD). However, there is a lack of relevant studies on this topic in Egyptian patients with AD. OBJECTIVE: To investigate different species of gut microbiota in Egyptian patients with AD and correlate microbiota bacterial abundance with clinical data. METHODS: The study included 25 patients with AD and 25 healthy volunteers as age and sex-matched controls. Clinical data was taken for each patient, including medical history and examination; Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) were assessed for each participant. Bacterial DNA was extracted from stool, and abundance quantified via qPCR using 16S rRNA group-specific primers. RESULTS: Akkermansia, Enterobacteria, Bacteroidetes, Bacillus cereus, Prevotella, and Clostridium cluster IV were more abundant in the AD group than in the control group, although there was significantly less abundance of Bifidobacterium spp., Firmicutes, and Actinobacteria in patients with AD than in controls, whereas no such significance was found for lactic acid bacteria between both groups. Lactic acid bacteria and Prevotella abundance was negatively correlated with cognitive impairment (p = 0.03 with MMSE, and p = 0.03 with MoCA). Prevotella abundance was positively correlated with age of onset and duration of illness and negatively correlated with smoking and coronary heart disease (p = 0.007, p = 0.03, p = 0.035, and p = 0.047, respectively). CONCLUSION: The current work highlighted a significant relationship between AD and gut microbiota dysbiosis. A higher abundance of Prevotella species and lactic acid bacteria was correlated with cognition.
Keywords: Alzheimer Disease; Bacteria; Cognitive Dysfunction; Dysbiosis; Gastrointestinal Microbiome; Humans; RNA, Ribosomal, 16S

Analysis and Identification Genetic Effect of SARS-CoV-2 Infections to Alzheimer's Disease Patients by Integrated Bioinformatics. - Wang, Fang; Xu, Jia; Xu, Shu-Jun; Guo, Jie-Jie; Wang, Feiming; Wang, Qin-Wen (J Alzheimers Dis, 2022)
BACKGROUND: COVID-19 pandemic is a global crisis which results in millions of deaths and causes long-term neurological sequelae, such as Alzheimer's disease (AD). OBJECTIVE: We aimed to explore the interaction between COVID-19 and AD by integrating bioinformatics to find the biomarkers which lead to AD occurrence and development with COVID-19 and provide early intervention. METHODS: The differential expressed genes (DEGs) were found by GSE147507 and GSE132903, respectively. The common genes between COVID-19 and AD were identified. Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and protein-protein interactions (PPI) network analysis were carried out. Hub genes were found by cytoscape. A multivariate logistic regression model was constructed. NetworkAnalyst was used for the analysis of TF-gene interactions, TF-miRNA coregulatory network, and Protein-chemical Interactions. RESULTS: Forty common DEGs for AD and COVID-19 were found. GO and KEGG analysis indicated that the DEGs were enriched in the calcium signal pathway and other pathways. A PPI network was constructed, and 5 hub genes were identified (ITPR1, ITPR3, ITPKB, RAPGEF3, MFGE8). Four hub genes (ITPR1, ITPR3, ITPKB, RAPGEF3) which were considered as important factors in the development of AD that were affected by COVID-19 were shown by nomogram. Utilizing NetworkAnalyst, the interaction network of 4 hub genes and TF, miRNA, common AD risk genes, and known compounds is displayed, respectively. CONCLUSION: COVID-19 patients are at high risk of developing AD. Vaccination is required. Four hub genes can be considered as biomarkers for prediction and treatment of AD development caused by COVID-19. Compounds with neuroprotective effects can be used as adjuvant therapy for COVID-19 patients.
Keywords: Alzheimer Disease; Computational Biology; COVID-19; Databases, Genetic; Gene Expression Profiling; Humans; Protein Interaction Maps; SARS-CoV-2

Antihypertensive Medication Class and the Risk of Dementia and Cognitive Decline in Older Adults: A Secondary Analysis of the Prospective HELIAD Cohort. - Liampas, Ioannis; Hatzimanolis, Alex; Siokas, Vasileios; Yannakoulia, Mary; Kosmidis, Mary H; Sakka, Paraskevi; Hadjigeorgiou, Georgios M; Scarmeas, Nikolaos; Dardiotis, Efthimios (J Alzheimers Dis, 2022)
BACKGROUND: It is unclear whether the main antihypertensive medication classes (diuretics, calcium channel blockers, beta-blockers, angiotensin converting enzyme inhibitors, and angiotensin receptor blockers (ARBs)) are associated with different risks of cognitive decline. Published evidence is conflicting and stems mainly from observational studies. OBJECTIVE: To investigate the differential effects of antihypertensives on the risks of developing dementia and cognitive decline, with a specific focus on the vascular component of the mechanisms underlying these interactions. METHODS: Older adults with a history of hypertension and without dementia were drawn from the population-based HELIAD cohort. Age-, gender-, education-, and antihypertensive medication- (five dichotomous exposures) adjusted Cox proportional-hazards models and generalized estimating equations were performed to appraise the associations of baseline antihypertensive therapy with dementia incidence and cognitive decline (quantified using a comprehensive neuropsychological battery). Analyses were subsequently adjusted for clinical vascular risk (dyslipidemia, diabetes mellitus, smoking, cardiovascular, and cerebrovascular history) and genetic susceptibility to stroke (using polygenic risk scores generated according to the MEGASTROKE consortium GWAS findings). RESULTS: A total of 776 predominantly female participants (73.61±4.94 years) with hypertension and a mean follow-up of 3.02±0.82 years were analyzed. Baseline treatment was not associated with the risk of incident dementia. ARB users experienced a slower yearly global cognitive [2.5% of a SD, 95% CI = (0.1, 4.9)] and language [4.4% of a SD, 95% CI = (1.4, 7.4)] decline compared to non-users. The fully adjusted model reproduced similar associations for both global cognitive [β= 0.027, 95% CI =  (-0.003, 0.057)], and language decline [β= 0.063, 95% CI = (0.023, 0.104)]. CONCLUSION: ARBs may be superior to other antihypertensive agents in the preservation of cognition, an association probably mediated by vascular-independent mechanisms.
Keywords: Aged; Angiotensin Receptor Antagonists; Angiotensin-Converting Enzyme Inhibitors; Antihypertensive Agents; Calcium Channel Blockers; Cognitive Dysfunction; Dementia; Diuretics; Female; Humans; Hypertension; Male; Prospective Studies

Anti-Inflammatory Gene Therapy Improves Spatial Memory Performance in a Mouse Model of Alzheimer's Disease. - Yoo, Tai June (J Alzheimers Dis, 2022)
The immune system plays a critical role in neurodegenerative processes involved in Alzheimer's disease (AD). In this study, a gene-based immunotherapeutic method examined the effects of anti-inflammatory cellular immune response elements (CIREs) in the amyloid-β protein precursor (AβPP) mouse model. Bi-monthly intramuscular administration, beginning at either 4 or 6 months, and examined at 7.5 through 16 months, with plasmids encoding Interleukin (IL)-10, IL-4, TGF-β polynucleotides, or a combination thereof, into AβPP mice improved spatial memory performance. This work demonstrates an efficient gene therapy strategy to downregulate neuroinflammation, and possibly prevent or delay cognitive decline in AD.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Anti-Inflammatory Agents; Cognition; Disease Models, Animal; Female; Genetic Therapy; Immunity, Cellular; Immunotherapy; Injections, Intramuscular; Interleukin-10; Interleukin-4; Male; Mice; Mice, Transgenic; Spatial Memory

Association Between Serum Vitamins and the Risk of Alzheimer's Disease in Chinese Population. - Liu, Xi-Xi; Wu, Peng-Fei; Liu, Ying-Zi; Jiang, Ya-Ling; Wan, Mei-Dan; Xiao, Xue-Wen; Yang, Qi-Jie; Jiao, Bin; Liao, Xin-Xin; Wang, Jun-Ling; Liu, Shao-Hui; Zhang, Xuewei; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Alzheimer's disease (AD) is a chronic and fatal neurodegenerative disease; accumulating evidence suggests that vitamin deficiency is associated with the risk of AD. However, studies attempting to elucidate the relationship between vitamins and AD varied widely. OBJECTIVE: This study aimed to investigate the relationship between serum vitamin levels and AD in a cohort of the Chinese population. METHODS: A total of 368 AD patients and 574 healthy controls were recruited in this study; serum vitamin A, B1, B6, B9, B12, C, D, and E were measured in all participants. RESULTS: Compared with the controls, vitamin B2, B9, B12, D, and E were significantly reduced in AD patients. Lower levels of vitamin B2, B9, B12, D, and E were associated with the risk of AD. After adjusting for age and gender, low levels of vitamin B2, B9, and B12 were still related to the risk of AD. In addition, a negative correlation was determined between vitamin E concentration and Activity of Daily Living Scale score while no significant association was found between serum vitamins and age at onset, disease duration, Mini-Mental State Examination, and Neuropsychiatric Inventory Questionnaire score. CONCLUSION: We conclude that lower vitamin B2, B9, B12, D, and E might be associated with the risk of AD, especially vitamin B2, B9, and B12. And lower vitamin E might be related to severe ability impairment of daily activities.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Case-Control Studies; China; Female; Folic Acid; Humans; Logistic Models; Male; Mental Status and Dementia Tests; Middle Aged; Riboflavin; Risk; Vitamin B 12; Vitamin D; Vitamin E

Association of Alzheimer's Disease with COVID-19 Susceptibility and Severe Complications: A Nationwide Cohort Study. - Chung, Seok Jong; Chang, Yoonkyung; Jeon, Jimin; Shin, Jae Il; Song, Tae-Jin; Kim, Jinkwon (J Alzheimers Dis, 2022)
BACKGROUND: Identification of patients at high susceptibility and high risk of developing serious complications related to coronavirus disease 2019 (COVID-19) infection is clinically important in the face of the COVID-19 pandemic. OBJECTIVE: To investigate whether patients with Alzheimer's disease (AD) are more susceptible to COVID-19 infection and whether they have a higher risk of developing serious complications. METHODS: We retrospectively reviewed the Korean nationwide population-based COVID-19 dataset for participants who underwent real-time reverse transcription polymerase chain reaction assays for COVID-19 between January 1 and June 4, 2020. A 1 : 3 ratio propensity score matching and binary logistic regression analysis were performed to investigate the association between AD and the susceptibility or severe complications (i.e., mechanical ventilation, intensive care unit admission, or death) of COVID-19. RESULTS: Among 195,643 study participants, 5,725 participants had AD and 7,334 participants were diagnosed with COVID-19. The prevalence of participants testing positive for COVID-19 did not differ according to the presence of AD (p = 0.234). Meanwhile, AD was associated with an increased risk of severe COVID-19 complications (OR 2.25 [95% CI 1.54-3.28]). Secondary outcome analyses showed that AD patients had an increased risk for mortality (OR 3.09 [95% CI 2.00-4.78]) but were less likely to receive mechanical ventilation (OR 0.42 [95% CI 0.20-0.87]). CONCLUSION: AD was not associated with increased susceptibility to COVID-19 infection, but was associated with severe COVID-19 complications, especially with mortality. Early diagnosis and active intervention are necessary for patients with AD suspected COVID-19 infection.
Keywords: Alzheimer Disease; Cohort Studies; COVID-19; Humans; Pandemics; Retrospective Studies; SARS-CoV-2

Association of Cholinergic Basal Forebrain Volume and Functional Connectivity with Markers of Inflammatory Response in the Alzheimer's Disease Spectrum. - Teipel, Stefan J; Dyrba, Martin; Ballarini, Tommaso; Brosseron, Frederic; Bruno, Davide; Buerger, Katharina; Cosma, Nicoleta-Carmen; Dechent, Peter; Dobisch, Laura; Düzel, Emrah; Ewers, Michael; Fliessbach, Klaus; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Inflammation has been described as a key pathogenic event in Alzheimer's disease (AD), downstream of amyloid and tau pathology. Preclinical and clinical data suggest that the cholinergic basal forebrain may moderate inflammatory response to different pathologies. OBJECTIVE: To study the association of cholinergic basal forebrain volume and functional connectivity with measures of neuroinflammation in people from the AD spectrum. METHODS: We studied 261 cases from the DELCODE cohort, including people with subjective cognitive decline, mild cognitive impairment, AD dementia, first degree relatives, and healthy controls. Using Bayesian ANCOVA, we tested associations of MRI indices of cholinergic basal forebrain volume and functional connectivity with cerebrospinal fluid (CSF) levels of sTREM2 as a marker of microglia activation, and serum levels of complement C3. Using Bayesian elastic net regression, we determined associations between basal forebrain measures and a large inflammation marker panel from CSF and serum. RESULTS: We found anecdotal to moderate evidence in favor of the absence of an effect of basal forebrain volume and functional connectivity on CSF sTREM2 and serum C3 levels both in Aβ42/ptau-positive and negative cases. Bayesian elastic net regression identified several CSF and serum markers of inflammation that were associated with basal forebrain volume and functional connectivity. The effect sizes were moderate to small. CONCLUSION: Our data-driven analyses generate the hypothesis that cholinergic basal forebrain may be involved in the neuroinflammation response to Aβ42 and phospho-tau pathology in people from the AD spectrum. This hypothesis needs to be tested in independent samples.
Keywords: Aged; Alzheimer Disease; Basal Forebrain; Biomarkers; Cholinergic Agents; Cognitive Dysfunction; Cohort Studies; Female; Humans; Inflammation; Magnetic Resonance Imaging; Male

Association of COVID-19 with New-Onset Alzheimer's Disease. - Wang, Lindsey; Davis, Pamela B; Volkow, Nora D; Berger, Nathan A; Kaelber, David C; Xu, Rong (J Alzheimers Dis, 2022)
An infectious etiology of Alzheimer's disease has been postulated for decades. It remains unknown whether SARS-CoV-2 viral infection is associated with increased risk for Alzheimer's disease. In this retrospective cohort study of 6,245,282 older adults (age ≥65 years) who had medical encounters between 2/2020-5/2021, we show that people with COVID-19 were at significantly increased risk for new diagnosis of Alzheimer's disease within 360 days after the initial COVID-19 diagnosis (hazard ratio or HR:1.69, 95% CI: 1.53-1.72), especially in people age ≥85 years and in women. Our findings call for research to understand the underlying mechanisms and for continuous surveillance of long-term impacts of COVID-19 on Alzheimer's disease.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; COVID-19; COVID-19 Testing; Female; Humans; Retrospective Studies; SARS-CoV-2

Barriers to Effective Memory Assessments for Alzheimer's Disease. - Parra, Mario A (J Alzheimers Dis, 2022)
Recently, Alzheimer's Disease International (ADI) stressed that around 75% of people living with dementia globally are still not receiving a diagnosis. In this commentary, I reflect on how efforts towards better cognitive assessments, particularly of memory, can be aligned and harmonized to contribute to such needs. I highlight some barriers that ongoing collaborations and trials are facing and their potential drivers. I suggest some strategies that can help overcome them and in so doing, integrate research agendas. We need to ignite the debate towards strategies that can help level the playfield to tackle Alzheimer's disease with true global solutions.
Keywords: Alzheimer Disease; Cognition; Cognition Disorders; Humans; Longitudinal Studies

Better Subjective Sleep Quality Partly Explains the Association Between Self-Reported Physical Activity and Better Cognitive Function. - Cheval, Boris; Maltagliati, Silvio; Sieber, Stefan; Cullati, Stéphane; Zou, Liye; Ihle, Andreas; Kramer, Arthur F; Yu, Qian; Sander, David; Boisgontier, Matthieu P (J Alzheimers Dis, 2022)
BACKGROUND: Physical activity has been associated with better cognitive function and better sleep quality. Yet, whether the beneficial effect of physical activity on cognitive function can be explained by an indirect pathway involving better sleep quality is unclear. OBJECTIVE: To investigate whether sleep quality mediates the association between physical activity and cognitive function in adults 50 years of age or older. METHODS: 86,541 community-dwelling European adults were included in the study. Physical activity and sleep quality were self-reported. Indicators of cognitive function (immediate recall, delayed recall, verbal fluency) were assessed using objective tests. All measures were collected six times between 2004 and 2017. The mediation was tested using multilevel mediation analyses. RESULTS: Results showed that self-reported physical activity was associated with better self-reported sleep quality, which was associated with better performance in all three indicators of cognitive function, demonstrating an indirect effect of physical activity on cognitive function through sleep quality. The mediating effect of sleep quality accounted for 0.41%, 1.46%, and 8.88% of the total association of physical activity with verbal fluency, immediate recall, and delayed recall, respectively. CONCLUSION: These findings suggest that self-reported sleep quality partly mediates the association between self-reported physical activity and cognitive function. These results need to be confirmed by device-based data of physical activity and sleep quality.
Keywords: Cognition; Exercise; Humans; Self Report; Sleep; Sleep Quality

A Blood Test for Alzheimer's Disease: It's about Time or Not Ready for Prime Time? - Galasko, Douglas R; Grill, Joshua D; Lingler, Jennifer H; Heidebrink, Judith L (J Alzheimers Dis, 2022)
A blood test for Alzheimer's disease is now available for clinical use in persons with cognitive impairment. This is an extraordinary milestone, though the amyloid-based PrecivityAD™ test is not without limitations. Pre and post-test counseling are essential. Phosphorylated tau blood tests are likely to follow soon. When used in conjunction with an appropriate clinical evaluation, blood tests provide the opportunity for an early, accurate, and accessible diagnosis of Alzheimer's disease. Standalone use, however, carries a significant risk of misinterpretation and is strongly discouraged. Now is the time to develop appropriate use criteria to guide the use of these promising assays.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Hematologic Tests; Humans; tau Proteins

Burden of Insomnia and Sleep Disturbances and the Impact of Sleep Treatments in Patients with Probable or Possible Alzheimer's Disease: A Structured Literature Review. - Benca, Ruth; Herring, W Joseph; Khandker, Rezaul; Qureshi, Zaina P (J Alzheimers Dis, 2022)
BACKGROUND: Sleep disturbances are frequent in Alzheimer's disease (AD). OBJECTIVE: To summarize the impact of sleep disturbances on AD patients and their caregivers and the effects of currently available sleep therapies. METHODS: Published studies (January 1985-March 2020) assessing the burden associated with insomnia/sleep disturbances in the AD population and insomnia treatment effects were identified by searching PubMed, Embase, and Cochrane Library and screened against inclusion criteria. RESULTS: 58 studies assessing patient and caregiver burden, institutionalization, and insomnia treatments in AD patients with sleep disturbances were identified. Sleep disturbances were associated with worse cognition, functional ability, and behavioral and neuropsychological functioning. Health status and quality of life of both patients and caregivers were reduced in the presence of sleep disturbances. Sleep disturbances were also associated with institutionalization. Although significant associations between sleep problems and clinical outcomes were apparent, there was generally no control for other influencing factors (e.g., cognitive status). Bright light and behavioral therapies as well as drugs showed some promise in AD patients, but studies were primarily small and limited data were available, particularly in regard to the effect on associated clinical burden. CONCLUSION: Sleep disturbances are a significant problem for AD patients and caregivers, associated with behavioral and psychological problems and cognitive decline. However, they remain poorly characterized and under-researched. As the global population is aging and AD is on thes rise, data from larger, prospective trials are required to fully understand the clinical correlates of sleep disturbances and the impact insomnia treatments can have.
Keywords: Alzheimer Disease; Caregivers; Humans; Prospective Studies; Quality of Life; Sleep; Sleep Initiation and Maintenance Disorders; Sleep Wake Disorders

"Captive by the Uncertainty"-Experiences with Anticipatory Guidance for People Living with Dementia and Their Caregivers at a Specialty Dementia Clinic. - Shafir, Adi; Ritchie, Christine S; Garrett, Sarah B; Bernstein Sideman, Alissa; Naasan, Georges; Merrilees, Jennifer; Widera, Eric; Flint, Lynn; Harrison, Krista L (J Alzheimers Dis, 2022)
BACKGROUND: After a diagnosis of Alzheimer's disease and related disorders, people living with dementia (PWD) and caregivers wonder what disease trajectory to expect and how to plan for functional and cognitive decline. This qualitative study aimed to identify patient and caregiver experiences receiving anticipatory guidance about dementia from a specialty dementia clinic. OBJECTIVE: To examine PWD and caregiver perspectives on receiving anticipatory guidance from a specialty dementia clinic. METHODS: We conducted semi-structured interviews with PWD, and active and bereaved family caregivers, recruited from a specialty dementia clinic. Interviews were recorded, transcribed, and systematically summarized. Thematic analysis identified anticipatory guidance received from clinical or non-clinical sources and areas where respondents wanted additional guidance. RESULTS: Of 40 participants, 9 were PWD, 16 were active caregivers, and 15 were bereaved caregivers. PWD had a mean age of 75 and were primarily male (n = 6/9); caregivers had a mean age of 67 and were primarily female (n = 21/31). Participants felt they received incomplete or "hesitant" guidance on prognosis and expected disease course via their clinicians and filled the gap with information they found via the internet, books, and support groups. They appreciated guidance on behavioral, safety, and communication issues from clinicians, but found more timely and advance guidance from other non-clinical sources. Guidance on legal and financial planning was primarily identified through non-clinical sources. CONCLUSION: PWD and caregivers want more information about expected disease course, prognosis, and help planning after diagnosis. Clinicians have an opportunity to improve anticipatory guidance communication and subsequent care provision.
Keywords: Aged; Alzheimer Disease; Caregivers; Dementia; Female; Humans; Male; Qualitative Research; Uncertainty

Caregiver Tele-Assistance for Reduction of Emotional Distress During the COVID-19 Pandemic. Psychological Support to Caregivers of People with Dementia: The Italian Experience. - Rotondo, Emanuela; Galimberti, Daniela; Mercurio, Matteo; Giardinieri, Giulia; Forti, Sara; Vimercati, Roberto; Borracci, Vittoria; Fumagalli, Giorgio G; Pietroboni, Anna M; Carandini, Tiziana; Nobili, Alessandro; Scarpini, Elio; et al. (J Alzheimers Dis, 2022)
BACKGROUND: COVID-19 pandemic worsened vulnerability of patients with dementia (PWD). This new reality associated with government restriction and isolation worsened stress burden and psychological frailties in PWD caregivers. OBJECTIVE: To give tele-psychological support to caregivers and evaluate the effect of this intervention by quantifying stress burden and quality of life during the first COVID-19 lockdown. METHODS: 50 caregivers were divided into two groups: "Caregiver-focused group" (Cg) and "Patient-focused group" (Pg). Both groups received telephone contact every 2 weeks over a 28-week period, but the content of the call was different: in Cg, caregivers answered questions about the state of the PWD but also explored their own emotional state, stress burden, and quality of life. In Pg instead, telephone contacts were focused only on the PWD, and no evaluation regarding the caregiver mood or state of stress was made. Psychometric scales were administered to evaluate COVID-19 impact, stress burden, and quality of life. RESULTS: Considering the time of intervention, from baseline (W0) to W28, Zarit Burden Interview and Quality of Life-caregiver questionnaires remained unchanged in Cg as compared with baseline (p > 0.05), whereas they worsened significantly in Pg (p < 0.01), showing increased stress over time and decreased quality of life in this group. Moreover, Impact on Event Scale values improved over the weeks in Cg (p = 0.015), while they remained unchanged in Pg (p = 0.483). CONCLUSION: Caregivers who received telephone support about their mood and stress burden did not worsen their psychological state during the time of intervention, as did instead those who did not get such support.
Keywords: Aged; Aged, 80 and over; Caregiver Burden; Caregivers; COVID-19; Dementia; Female; Humans; Italy; Male; Middle Aged; Psychological Distress; Psychosocial Support Systems; Quality of Life; Surveys and Questionnaires; Telephone

Cerebral Volumetric Correlates of Apathy in Alzheimer's Disease and Cognitively Normal Older Adults: Meta-Analysis, Label-Based Review, and Study of an Independent Cohort. - Chaudhary, Shefali; Zhornitsky, Simon; Chao, Herta H; van Dyck, Christopher H; Li, Chiang-Shan R (J Alzheimers Dis, 2022)
BACKGROUND: Affecting nearly half of the patients with Alzheimer's disease (AD), apathy is associated with higher morbidity and reduced quality of life. Basal ganglia and cortical atrophy have been implicated in apathy. However, the findings have varied across studies and left unclear whether subdomains of apathy may involve distinct neuroanatomical correlates. OBJECTIVE: To identify neuroanatomical correlates of AD-associated apathy. METHODS: We performed a meta-analysis and label-based review of the literature. Further, following published routines of voxel-based morphometry, we aimed to confirm the findings in an independent cohort of 19 patients with AD/mild cognitive impairment and 25 healthy controls assessed with the Apathy Evaluation Scale. RESULTS: Meta-analysis of 167 AD and 56 healthy controls showed convergence toward smaller basal ganglia gray matter volume (GMV) in apathy. Label-based review showed anterior cingulate, putamen, insula, inferior frontal gyrus (IFG) and middle temporal gyrus (MTG) atrophy in AD apathy. In the independent cohort, with small-volume-correction, right putamen and MTG showed GMVs in negative correlation with Apathy Evaluation Scale total, behavioral, and emotional scores, and right IFG with emotional score (p < 0.05 family-wise error (FWE)-corrected), controlling for age, education, intracranial volume, and depression. With the Mini-Mental State Examination scores included as an additional covariate, the correlation of right putamen GMV with behavioral and emotional score, right MTG GMV with total and emotional score, and right IFG GMV with emotional score were significant. CONCLUSION: The findings implicate putamen, MTG and IFG atrophy in AD associated apathy, potentially independent of cognitive impairment and depression, and suggest potentially distinct volumetric correlates of apathy.
Keywords: Aged; Alzheimer Disease; Apathy; Atrophy; Basal Ganglia; Brain; Cognitive Dysfunction; Cohort Studies; Gray Matter; Gyrus Cinguli; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Prefrontal Cortex

Chronic Renin-Angiotensin System Activation Induced Neuroinflammation: Common Mechanisms Underlying Hypertension and Dementia? - Tran, Shirley; Kuruppu, Sanjaya; Rajapakse, Niwanthi W (J Alzheimers Dis, 2022)
Hypertension is a major risk factor for the pathogenesis of vascular dementia and Alzheimer's disease. Chronic activation of the renin-angiotensin system (RAS) contributes substantially to neuroinflammation. We propose that neuroinflammation arising from chronic RAS activation can initiate and potentiate the onset of hypertension and related dementia. Neuroinflammation induced by chronic activation of the RAS plays a key role in the pathogenesis of dementia. Increased levels of pro-inflammatory cytokines tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and transforming growth factor (TGF)-β have been reported in brain tissue of vascular dementia patients and animal models of vascular dementia induced by either angiotensin II infusion or transverse aortic coarctation. It is proposed that neuronal cell death and synaptic dysfunction induced by neuroinflammation lead to cognitive impairment in dementia. The neuroprotective RAS pathway, regulated by angiotensin-converting enzyme 2 (ACE2) which converts angiotensin II into angiotensin-(1-7), can attenuate hypertension and dementia. Furthermore, the use of anti-hypertensive medications in preventing dementia or cognitive decline in hypertensive patients and animal models of dementia have mostly been beneficial. Current evidence suggests a strong link between RAS induced neuroinflammation and the onset of hypertension and dementia, which warrants further investigation. Strategies to counteract an overactive RAS and enhance the neuroprotective arm of the RAS may help prevent or improve cognitive impairment associated with hypertension.
Keywords: Angiotensin I; Angiotensin II; Animals; Antihypertensive Agents; Brain; Cytokines; Dementia, Vascular; Humans; Hypertension; Inflammation; Peptide Fragments; Renin-Angiotensin System

Clinical and Imaging Determinants of Neurocognitive Disorders in Post-Acute COVID-19 Patients with Cognitive Complaints. - Andriuta, Daniela; Si-Ahmed, Cherifa; Roussel, Martine; Constans, Jean-Marc; Makki, Malek; Aarabi, Ardalan; Basille, Damien; Andrejak, Claire; Godefroy, Olivier (J Alzheimers Dis, 2022)
BACKGROUND: Neurocognitive disorders (NCDs) are a part of the post-acute coronavirus disease (COVID-19) syndrome. No study has specifically evaluated NCDs in post-acute COVID-19 patients with cognitive complaints or their MRI determinants. OBJECTIVE: To characterize NCDs in post-acute COVID-19 patients with cognitive complaints. The secondary objectives were to assess their clinical and MRI determinants. METHODS: We included 46 patients with a post-acute COVID-19 cognitive complaint referred to the Amiens University Hospital Memory Center. They underwent a neuropsychological assessment and 36 had cerebral MRI. The G3 overall summary score was the sum of the mean z scores for the executive function, language, and action speed domains. Neuropsychological profiles were compared in a general linear model. Clinical determinants were analyzed by stepwise linear regression. White matter hyperintensities (WMH) masks were analyzed using parcel-based WMH symptom mapping to identify the locations of WMHs associated with cognitive performance. RESULTS: Repeated ANOVA showed a group effect (p = 0.0001) due to overall lower performance for patients and a domain effect (p = 0.0001) due to a lower (p = 0.007) action speed score. The G3 overall summary score was significantly associated with solely the requirement for oxygen (R2 = 0.319, p = 0.031). WHMs were associated with the G3 overall summary score in the following structures, all right-sided (p < 0.01): superior frontal region, postcentral region, cingulum, cortico-spinal tract, inferior longitudinal fasciculus, internal capsule, and posterior segment of the arcuate fasciculus. CONCLUSION: Post-acute COVID-19 patients with cognitive complaints had NCD, with prominent action slowing, significantly associated with the acute phase oxygen requirement and a right-sided WMH structure pattern.
Keywords: Cognition; COVID-19; Humans; Leukoaraiosis; Magnetic Resonance Imaging; Neurocognitive Disorders; Neuropsychological Tests; Oxygen; White Matter

Cognitive Decline Risk Stratification in People with Late-Onset Epilepsy of Unknown Etiology: An Electroencephalographic Connectivity and Graph Theory Pilot Study. - Costa, Cinzia; Vecchio, Fabrizio; Romoli, Michele; Miraglia, Francesca; Nardi Cesarini, Elena; Alù, Francesca; Calabresi, Paolo; Rossini, Paolo Maria (J Alzheimers Dis, 2022)
BACKGROUND: Although people with late onset epilepsy of unknown etiology (LOEU) are at higher risk of cognitive decline compared to the general population, we still lack affordable tools to predict and stratify their risk of dementia. OBJECTIVE: This pilot-study investigates the potential application of electroencephalography (EEG) network small-world (SW) properties in predicting cognitive decline among patients with LOEU. METHODS: People diagnosed with LOEU and normal cognitive examination at the time of epilepsy diagnosis were included. Cerebrospinal fluid biomarkers, brain imaging, and neuropsychological assessment were performed at the time of epilepsy diagnosis. Baseline EEG was analyzed for SW properties. Patients were followed-up over time with neuropsychological testing to define the trajectory of cognitive decline. RESULTS: Over 5.1 years of follow-up, among 24 patients diagnosed with LOEU, 62.5% were female, mean age was 65.3 years, thirteen developed mild cognitive impairment (MCI), and four developed dementia. Patients with LOEU developing MCI had lower values of SW coefficients in the delta (p = 0.03) band and higher SW values in the alpha frequency bands (p = 0.02) compared to patients having normal cognition at last follow-up. The two separate ANOVAs, for low and alpha bands, confirmed an interaction between SW and cognitive decline at follow-up. A similar gradient was confirmed for patients developing dementia compared to those with normal cognitive function as well as to those developing MCI. CONCLUSION: Baseline EEG analysis through SW is worth investigating as an affordable, widely available tool to stratify LOEU patients for their risk of cognitive decline.
Keywords: Aged; Cognitive Dysfunction; Dementia; Electroencephalography; Epilepsy; Female; Humans; Male; Neuropsychological Tests; Pilot Projects; Risk Assessment

Cognitive Function Associated with Gut Microbial Abundance in Sucrose and S-Adenosyl-L-Methionine (SAMe) Metabolic Pathways. - Jeong, Sohyun; Huang, Li-Kai; Tsai, Ming-Ju; Liao, Yi-Tyng; Lin, Yow-Sien; Hu, Chaur-Jong; Hsu, Yi-Hsiang (J Alzheimers Dis, 2022)
BACKGROUND: Differential abundance of gut microbiota has found to be associated with Alzheimer's disease (AD). However, the relative abundance of gut microbiota between dementia and mild cognitive impairment (MCI) in AD is not well studied. OBJECTIVE: We attempted to identify differentially enriched gut microbes and their metabolic pathways in AD patients with dementia comparing to AD patients with MCI. METHODS: Fecal samples were collected at Shuang Ho Hospital, Taipei Medical University, Taiwan and analyzed by whole metagenomic sequencing technique. For normal controls without AD (NC), 16S rRNA sequencing was obtained from the Taiwan Microbiome Database. A total of 48 AD (38 dementia and 10 MCI defined by cognitive function scores) and 50 NC were included. Microbiome alpha and beta diversities were estimated. Differentially enriched microbes were identified with HAllA, MaAsLin, DESeq2, and LEfSe statistical modeling approaches. RESULTS: We found significantly increased abundance of Firmicutes but decreased abundance of Bacteroidetes at phylum level in AD compared to NC. In AD patients, cognitive function scores were negatively associated with abundance of Blautia hydrogenotrophica (Firmicutes), Anaerotruncus colihominis (Firmicutes), and Gordonibacter pamelaeae (Actinobacteria). In addition, microbial abundance in the sucrose and S-Adenosyl-L-methionine (SAMe) metabolic pathways was more enriched in AD with MCI than AD with dementia and significantly associated with higher cognitive function scores. CONCLUSION: Gut microbe community diversity was similar in AD patients regardless of MCI or dementia status. However, differential analyses probed in lower-level taxa and metabolic pathways suggested that specific gut microbes in Firmicutes and Actinobacteria might involve in cognitive decline.
Keywords: Alzheimer Disease; Cognition; Cognitive Dysfunction; Gastrointestinal Microbiome; Humans; Metabolic Networks and Pathways; RNA, Ribosomal, 16S; S-Adenosylmethionine; Sucrose

Cognitive, Functional, and Emotional Changes During the COVID-19 Pandemic in Greek Patients with Neurocognitive Disorders. - Tsiakiri, Anna; Vlotinou, Pinelopi; Terzoudi, Aikaterini; Heliopoulos, Ioannis; Vadikolias, Konstantinos (J Alzheimers Dis, 2022)
BACKGROUND: Prolonged periods of social deprivation, such as COVID-19-related lockdowns, are associated with deleterious effects on cognitive functions. OBJECTIVE: The aim of this study was to gauge the effect of prolonged social isolation on the cognitive function of older adults with neurocognitive disorders. METHODS: We recruited 125 older adults with minor or major neurocognitive disorders divided into two groups. The control group was tested at the first period of the study (October 2018-May 2019), whereas the experimental group was evaluated at the second chronological period of the study (October 2020-May 2021) during the second wave of COVID-19. Neuropsychological tests were performed at baseline and six months after baseline. RESULTS: In the control group, significant changes in the scores from the Montreal Cognitive Assessment (MoCA; p = 0.049) and the Functional Rating Scale for Symptoms of Dementia (FRSSD; p = 0.005) were found between baseline and follow-up assessments, whereas no changes were identified in Mini-Mental State Examination (MMSE; p = 0.229) and Geriatric Depression Scale (GDS; p = 0.619) scores. In the experimental group, the scores from all neuropsychological tests (MoCA, MMSE, GDS, and FRSSD; p < 0.001 for all) were significantly different at follow-up when compared with those at baseline measurements. Moreover, significant deterioration of specific functions assessed in MMSE and FRSSD was detected, especially in the experimental group. CONCLUSION: This study highlights cognitive functions directly affected by social deprivation of individuals with neurocognitive disorders. The findings can be used in the rehabilitation from confinement and its negative consequences.
Keywords: Aged; Cognition; Cognitive Dysfunction; Communicable Disease Control; COVID-19; Greece; Humans; Neurocognitive Disorders; Neuropsychological Tests; Pandemics

Comparison of Steady-State Pharmacokinetics of Donepezil Transdermal Delivery System with Oral Donepezil. - Tariot, Pierre N; Braeckman, Rene; Oh, Charles (J Alzheimers Dis, 2022)
BACKGROUND: Donepezil is approved for treatment of dementia of the Alzheimer type and is currently available only in tablet forms in the United States. OBJECTIVE: To compare steady-state pharmacokinetics of once-weekly 10-mg/d and 5-mg/d Corplex™ donepezil transdermal delivery systems (TDS) with once-daily 10-mg oral donepezil. METHODS: Open-label, randomized, crossover study (NCT04617782) enrolled healthy participants aged 18-55 years. All participants received 5-mg/d donepezil TDS during the 5-week Period 1, followed by 10-mg/d TDS or 10-mg/d oral donepezil in the 5-week Period 2; treatments were switched in Period 3. Bioequivalence was assessed at steady state on Week 5. RESULTS: All 60 enrolled participants received 5-mg/d TDS, 55 received 10-mg/d TDS, and 56 received oral donepezil. Adjusted geometric mean ratio (% [90% CI]) for maximum plasma concentration and area under the plasma concentration versus time curve (0-168 h) were 88.7 (81.7-96.2) and 108.6 (100.5-117.4) for 10-mg/d and 86.1 (79.8-92.9) and 105.3 (97.6-113.6) for dose-normalized 5-mg/d TDS and were generally within the 80% -125% range for establishing bioequivalence with oral donepezil. Skin adhesion was similar for both TDSs (>80% of patches remaining ≥75% adhered throughout the wear period). Overall incidence of adverse events (AEs) was similar across treatments. Compared with 10-mg/d TDS, oral donepezil was associated with higher incidence of gastrointestinal and nervous system AEs (14.5% versus 53.6% and 14.5% versus 30.4%, respectively). CONCLUSION: Donepezil TDSs are bioequivalent to oral donepezil at steady state and have a safety profile that supports their use in treating dementia of the Alzheimer type.
Keywords: Adolescent; Adult; Alzheimer Disease; Cross-Over Studies; Donepezil; Humans; Middle Aged; Young Adult

A Comparison of Well-Being of Carers of People with Dementia and Their Ability to Manage Before and During the COVID-19 Pandemic: Findings from the IDEAL Study. - Gamble, Laura D; Parker, Sophie; Quinn, Catherine; Bennett, Holly Q; Martyr, Anthony; Sabatini, Serena; Pentecost, Claire; Collins, Rachel; Dawson, Eleanor; Hunt, Anna; Allan, Louise; Burns, Alistair; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Social restriction measures imposed to curb the spread of COVID-19 in the United Kingdom impacted on carers of people with dementia, limiting access to support services and increasing perceived burden of caring. Few studies have compared data collected both during and before the pandemic to examine the effect of these changes. OBJECTIVE: To explore whether the COVID-19 pandemic affected the well-being of carers of people with dementia living in the community, and their ability to cope with their caring responsibilities. METHODS: Analysis was conducted on two groups of carers who were enrolled in the IDEAL programme; the 'pre-pandemic group' (n = 312), assessed at two time points prior to the pandemic, and the 'pandemic group', assessed prior to and several months into the pandemic (n = 156). For the pre-pandemic group, carers were matched 2:1 to carers in the pandemic group on certain characteristics. Differences in change over time between the two groups on self-reported well-being, quality of life, coping, perceived competence, and role captivity, were investigated using mixed effect modelling. RESULTS: Compared to the pre-pandemic group, those in the pandemic group appeared to cope better and had more stable self-rated competency and role captivity. They did not differ in terms of well-being or quality of life. CONCLUSIONS: Despite reports of negative impacts on carers early in the pandemic, the findings suggest the pandemic had little negative longer-term impact on carers of people with dementia, and in fact they appeared to have a more positive attitude towards coping several months into the pandemic.
Keywords: Adaptation, Psychological; Caregivers; COVID-19; Dementia; Humans; Pandemics; Quality of Life

The Correlation of Tau Levels with Blood Monocyte Count in Patients with Alzheimer's Disease. - Sun, Hao-Lun; Zhou, Fa-Ying; Chen, Dong-Wan; Tan, Cheng-Rong; Zeng, Gui-Hua; Liu, Yu-Hui; Wang, Jun; Bu, Xian-Le; Wang, Yan-Jiang; Li, Hui-Yun; Jin, Wang-Sheng (J Alzheimers Dis, 2022)
BACKGROUND: Recent studies have shown that monocytes can phagocytize the tau protein, which may ameliorate tau-type pathology in Alzheimer's disease (AD). However, there are few clinical studies on the relationship between monocytes and tau-type pathology in AD patients. OBJECTIVE: We aimed to explore changes in peripheral monocytes and their association with tau protein in AD patients. METHODS: A total of 127 clinically diagnosed AD patients and 100 age- and sex-matched cognitively normal controls were recruited for analysis of the correlation of plasma tau levels with the blood monocyte count. Cerebrospinal fluid (CSF) samples from 46 AD patients and 88 controls were further collected to analyze the correlation of CSF tau and amyloid-β (Aβ) levels with the blood monocyte count. 105 clinically diagnosed mild cognitive impairment (MCI) patients and 149 age- and sex-matched cognitively normal controls were recruited from another cohort for verification. RESULTS: Compared to normal controls, AD patients showed a significant reduction in the blood monocyte count. In addition, the monocyte count of AD patients was negatively correlated with CSF t-tau and p-tau levels but not with plasma tau levels. In normal people, monocyte count lack correlation with tau levels both in plasma and CSF. Monocyte count were not correlated with CSF Aβ levels in either group but were negatively correlated with CSF tau/Aβ42 levels in the AD group. We had further verified the correlations of monocyte count with CSF tau levels in another cohort. CONCLUSION: This study suggests that monocytes may play an important role in the clearance of tau protein in the brain.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Brain; Cognitive Dysfunction; Cohort Studies; Female; Humans; Male; Monocytes; tau Proteins

COVID-19 and Neurodegenerative Diseases: Prion-Like Spread and Long-Term Consequences. - Baazaoui, Narjes; Iqbal, Khalid (J Alzheimers Dis, 2022)
COVID-19 emerged as a global pandemic starting from Wuhan in China and spread at a lightning speed to the rest of the world. One of the potential long-term outcomes that we speculate is the development of neurodegenerative diseases as a long-term consequence of SARS-CoV-2 especially in people that have developed severe neurological symptoms. Severe inflammatory reactions and aging are two very strong common links between neurodegenerative diseases and COVID-19. Thus, patients that have very high viral load may be at high risk of developing long-term adverse neurological consequences such as dementia. We hypothesize that people with neurodegenerative diseases such as Alzheimer's disease, Parkinson's disease, and aged people are at higher risk of getting the COVID-19 than normal adults. The basis of this hypothesis is the fact that SARS-CoV-2 uses as a receptor angiotensin-converting enzyme 2 to enter the host cell and that this interaction is calcium-dependent. This could then suggest a direct relationship between neurodegenerative diseases, ACE-2 expression, and the susceptibility to COVID-19. The analysis of the available literature showed that COVID-19 virus is neurotropic and was found in the brains of patients infected with this virus. Furthermore, that the risk of having the infection increases with dementia and that infected people with severe symptoms could develop dementia as a long-term consequence. Dementia could be developed following the acceleration of the spread of prion-like proteins. In the present review we discuss current reports concerning the prevalence of COVID-19 in dementia patients, the individuals that are at high risk of suffering from dementia and the potential acceleration of prion-like proteins spread following SARS-CoV-2 infection.
Keywords: Aged; COVID-19; Dementia; Humans; Neurodegenerative Diseases; Prions; SARS-CoV-2

Demonstration of Clinical Meaningfulness of the Integrated Alzheimer's Disease Rating Scale (iADRS): Association Between Change in iADRS Scores and Patient and Caregiver Health Outcomes. - Wessels, Alette M; Belger, Mark; Johnston, Joseph A; Yu, Youying; Rentz, Dorene M; Dowsett, Sherie A; Chandler, Julie (J Alzheimers Dis, 2022)
BACKGROUND: The integrated Alzheimer's Disease Rating Scale (iADRS) is a validated cognitive/functional composite that effectively captures cognitive and functional decline over a broad spectrum of disease. The clinical meaningfulness of change on iADRS can be supported by establishing an association with changes on important health outcome measures. OBJECTIVE: To evaluate the relationship between change on the iADRS and changes in health outcomes in individuals with mild cognitive impairment (MCI) due to Alzheimer's disease (AD), or mild or moderate AD dementia using placebo data from four AD clinical trials and data from one AD observational study. METHODS: Analysis of covariate (ANCOVA) models were used to estimate the relationship between 18-month change on the iADRS and changes on health outcome measures (related to cost, quality of life, and caregiver burden). The regression coefficients for the iADRS were used to compute impact of natural disease progression and disease-modifying treatment on health outcomes. Additional ANCOVAs were conducted to understand whether cognition and/or function was the underlying explanation of any association between iADRS and health outcome change. RESULTS: Across datasets and disease stages, a worsening on the iADRS was significantly associated with increased societal costs, caregiver burden (time and distress) and worsening in measures of patient quality of life. CONCLUSION: Decline on the iADRS was associated with worsening in health outcome measures. These findings suggest that the iADRS can be used in clinical trials as a proxy measure of clinically meaningful outcomes of AD progression.
Keywords: Alzheimer Disease; Caregivers; Clinical Trials as Topic; Cognitive Dysfunction; Humans; Observational Studies as Topic; Outcome Assessment, Health Care; Quality of Life

Detecting Alzheimer's Disease Using Natural Language Processing of Referential Communication Task Transcripts. - Liu, Ziming; Paek, Eun Jin; Yoon, Si On; Casenhiser, Devin; Zhou, Wenjun; Zhao, Xiaopeng (J Alzheimers Dis, 2022)
BACKGROUND: People with Alzheimer's disease (AD) often demonstrate difficulties in discourse production. Referential communication tasks (RCTs) are used to examine a speaker's capability to select and verbally code the characteristics of an object in interactive conversation. OBJECTIVE: In this study, we used contextualized word representations from Natural language processing (NLP) to evaluate how well RCTs are able to distinguish between people with AD and cognitively healthy older adults. METHODS: We adapted machine learning techniques to analyze manually transcribed speech transcripts in an RCT from 28 older adults, including 12 with AD and 16 cognitively healthy older adults. Two approaches were applied to classify these speech transcript samples: 1) using clinically relevant linguistic features, 2) using machine learned representations derived by a state-of-art pretrained NLP transfer learning model, Bidirectional Encoder Representation from Transformer (BERT) based classification model. RESULTS: The results demonstrated the superior performance of AD detection using a designed transfer learning NLP algorithm. Moreover, the analysis showed that transcripts of a single image yielded high accuracies in AD detection. CONCLUSION: The results indicated that RCT may be useful as a diagnostic tool for AD, and that the task can be simplified to a subset of images without significant sacrifice to diagnostic accuracy, which can make RCT an easier and more practical tool for AD diagnosis. The results also demonstrate the potential of RCT as a tool to better understand cognitive deficits from the perspective of discourse production in people with AD.
Keywords: Aged; Alzheimer Disease; Cognitive Dysfunction; Communication; Humans; Natural Language Processing; Speech

Diabetic Retinopathy Predicts Risk of Alzheimer's Disease: A Danish Registry-Based Nationwide Cohort Study. - Pedersen, Frederik Nørregaard; Stokholm, Lonny; Pouwer, Frans; Hass Rubin, Katrine; Peto, Tunde; Frydkjær-Olsen, Ulrik; Thykjær, Anne Suhr; Andersen, Nis; Andresen, Jens; Bek, Toke; La Cour, Morten; Heegaard, Steffen; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Retinal neurodegeneration is evident in early diabetic retinopathy (DR) which may be associated with other neurodegenerative diseases like Alzheimer's disease (AD). OBJECTIVE: To investigate diabetes and DR as a risk marker of present and incident AD. METHODS: A register-based cohort study was performed. We included 134,327 persons with diabetes above 60 years of age, who had attended DR screening, and 651,936 age- and gender-matched persons without diabetes. RESULTS: At baseline, the prevalence of AD was 0.7% and 1.3% among patients with and without diabetes, respectively. In a multivariable regression model, patients with diabetes were less likely to have AD at baseline (adjusted OR 0.63, 95% CI 0.59-0.68). During follow-up, incident AD was registered for 1473 (0.35%) and 6,899 (0.34%) persons with and without diabetes, respectively. Compared to persons without diabetes, persons with diabetes and no DR had a lower risk to develop AD (adjusted HR 0.87, 95% CI 0.81-0.93), while persons with diabetes and DR had higher risk of AD (adjusted HR 1.24, 95% CI 1.08-1.43). When persons with diabetes and no DR were used as references, a higher risk of incident AD was observed in persons with DR (adjusted HR 1.34, 95% CI 1.18-1.53). CONCLUSION: Individuals with diabetes without DR were less likely to develop AD compared to persons without diabetes. However, individuals with DR had a 34% higher risk of incident AD, which raise the question whether screening for cognitive impairment should be done among individuals with DR.
Keywords: Alzheimer Disease; Cohort Studies; Denmark; Diabetes Mellitus; Diabetic Retinopathy; Humans; Registries; Risk Factors

Dimethyl Fumarate is a Potential Therapeutic Option for Alzheimer's Disease. - Sun, Xiaodi; Suo, Xinjun; Xia, Xianyou; Yu, Chunshui; Dou, Yan (J Alzheimers Dis, 2022)
BACKGROUND: Dimethyl fumarate (DMF) has been approved for clinical treatment of multiple sclerosis based on its antioxidant and anti-inflammatory effects by activating the Nrf2 pathway. Since both oxidative stress and inflammation are involved in Alzheimer's disease (AD), DMF is a potential therapeutic option for AD. OBJECTIVE: This study aims to test the therapeutic effects of DMF on AD model mice and to reveal its underlying molecular mechanisms. METHODS: Cell viability assay and in vitro immunofluorescence imaging were used to evaluate the antioxidant effect of DMF on embryonic mouse hippocampal neurons. Behavioral test and brain magnetic resonance imaging were used to assess the therapeutic effects of DMF on spatial learning and memory as well as hippocampal volume in AD model mice with and without Nrf2 knockdown. Western blotting was used to analyze the expression of antioxidant enzymes and molecules associated with AD-related pathological pathways. RESULTS: DMF inhibits reactive oxygen species overproduction and protects neurons without Nrf2 knockdown from death. DMF reduces amyloid-β induced memory impairment and hippocampal atrophy in AD model mice rather than in Nrf2 knockdown AD mice. DMF delays the progression of AD by activating the Nrf2 pathway to enhance the expression of downstream antioxidant enzymes and inhibits lipid peroxidation, apoptosis, inflammation, mitochondrial dysfunction and amyloid-β deposition. CONCLUSION: These results indicate that DMF is a potential therapeutic option for AD through its antioxidant, anti-inflammatory, anti-apoptotic, and other anti-AD effects by activating the Nrf2 pathway.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Antioxidants; Cell Survival; Dimethyl Fumarate; Disease Models, Animal; Hippocampus; Inflammation; Male; Memory Disorders; Mice; Mice, Inbred C57BL; Neurons; NF-E2-Related Factor 2; NF-kappa B; Oxidative Stress; Protective Agents; Reactive Oxygen Species

Effect of Probiotic Bifidobacterium breve in Improving Cognitive Function and Preventing Brain Atrophy in Older Patients with Suspected Mild Cognitive Impairment: Results of a 24-Week Randomized, Double-Blind, Placebo-Controlled Trial. - Asaoka, Daisuke; Xiao, Jinzhong; Takeda, Tsutomu; Yanagisawa, Naotake; Yamazaki, Takahiro; Matsubara, Yoichiro; Sugiyama, Hideki; Endo, Noemi; Higa, Motoyuki; Kasanuki, Koji; Ichimiya, Yosuke; Koido, Shigeo; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Probiotics have been reported to ameliorate cognitive impairment. OBJECTIVE: We investigated the effect of the probiotic strain Bifidobacterium breve MCC1274 (A1) in enhancing cognition and preventing brain atrophy of older patients with mild cognitive impairment (MCI). METHODS: In this RCT, 130 patients aged from 65 to 88 years old with suspected MCI received once daily either probiotic (B. breve MCC1274, 2×1010 CFU) or placebo for 24 weeks. Cognitive functions were assessed by ADAS-Jcog and MMSE tests. Participants underwent MRI to determine brain atrophy changes using Voxel-based Specific Regional Analysis System for Alzheimer's disease (VSRAD). Fecal samples were collected for the analysis of gut microbiota composition. RESULTS: Analysis was performed on 115 participants as the full analysis set (probiotic 55, placebo 60). ADAS-Jcog subscale "orientation" was significantly improved compared to placebo at 24 weeks. MMSE subscales "orientation in time" and "writing" were significantly improved compared to placebo in the lower baseline MMSE (< 25) subgroup at 24 weeks. VSRAD scores worsened in the placebo group; probiotic supplementation tended to suppress the progression, in particular among those subjects with progressed brain atrophy (VOI Z-score ≥1.0). There were no marked changes in the overall composition of the gut microbiota by the probiotic supplementation. CONCLUSION: Improvement of cognitive function was observed on some subscales scores only likely due to the lower sensitiveness of these tests for MCI subjects. Probiotics consumption for 24 weeks suppressed brain atrophy progression, suggesting that B. breve MCC1274 helps prevent cognitive impairment of MCI subjects.
Keywords: Aged; Aged, 80 and over; Atrophy; Bifidobacterium breve; Brain; Cognition; Cognitive Dysfunction; Double-Blind Method; Humans; Probiotics

The Efficacy and Safety of Alzheimer's Disease Therapies: An Updated Umbrella Review. - Fan, Fangcheng; Liu, Hua; Shi, Xiaojie; Ai, Yangwen; Liu, Qingshan; Cheng, Yong (J Alzheimers Dis, 2022)
BACKGROUND: Evidence summaries for efficacy and safety of frequently employed treatments of Alzheimer's disease (AD) are sparse. OBJECTIVE: We aimed to perform an updated umbrella review to identify an efficacious and safe treatment for AD patients. METHODS: We conducted a search for meta-analyses and systematic reviews on the Embase, PubMed, The Cochrane Library, and Web of Science to address this knowledge gap. We examined the cognitive functions, behavioral symptoms, global clinical assessment, and Activities of Daily Living as efficacy endpoints, and the incidence of adverse events as safety profiles. RESULTS: Sixteen eligible papers including 149 studies were included in the umbrella review. The results showed that AChE inhibitors (donepezil, galantamine, rivastigmine, Huperzine A), Ginkgo biloba, and cerebrolysin appear to be beneficial for cognitive, global performances, and activities of daily living in patients with AD. Furthermore, anti-Aβ agents are unlikely to have an important effect on slowing cognitive or functional impairment in mild to moderate AD. CONCLUSION: Our study demonstrated that AChE inhibitors, Ginkgo biloba, and cerebrolysin are the optimum cognitive and activities of daily living medication for patients with AD.
Keywords: Activities of Daily Living; Alzheimer Disease; Amino Acids; Cholinesterase Inhibitors; Cognition; Donepezil; Galantamine; Ginkgo biloba; Humans; Nootropic Agents; Patient Safety; Plant Extracts; Rivastigmine

Environmental Enrichment Effects on the Brain-Derived Neurotrophic Factor Expression in Healthy Condition, Alzheimer's Disease, and Other Neurodegenerative Disorders. - Cutuli, Debora; Landolfo, Eugenia; Petrosini, Laura; Gelfo, Francesca (J Alzheimers Dis, 2022)
Brain-derived neurotrophic factor (BDNF), a protein belonging to the neurotrophin family, is known to be heavily involved in synaptic plasticity processes that support brain development, post-lesion regeneration, and cognitive performances, such as learning and memory. Evidence indicates that BDNF expression can be epigenetically regulated by environmental stimuli and thus can mediate the experience-dependent brain plasticity. Environmental enrichment (EE), an experimental paradigm based on the exposure to complex stimulations, constitutes an efficient means to investigate the effects of high-level experience on behavior, cognitive processes, and neurobiological correlates, as the BDNF expression. In fact, BDNF exerts a key role in mediating and promoting EE-induced plastic changes and functional improvements in healthy and pathological conditions. This review is specifically aimed at providing an updated framework of the available evidence on the EE effects on brain and serum BDNF levels, by taking into account both changes in protein expression and regulation of gene expression. A further purpose of the present review is analyzing the potential of BDNF regulation in coping with neurodegenerative processes characterizing Alzheimer's disease (AD), given BDNF expression alterations are described in AD patients. Moreover, attention is also paid to EE effects on BDNF expression in other neurodegenerative disease. To investigate such a topic, evidence provided by experimental studies is considered. A deeper understanding of environmental ability in modulating BDNF expression in the brain may be fundamental in designing more tuned and effective applications of complex environmental stimulations as managing approaches to AD.
Keywords: Alzheimer Disease; Animals; Brain; Brain-Derived Neurotrophic Factor; Cognition; Disease Models, Animal; Environment; Humans; Neurodegenerative Diseases; Neuronal Plasticity

Evaluation of the Accuracy of Cognitive Screening Tests in Detecting Dementia Associated with Alzheimer's Disease: A Hierarchical Bayesian Latent Class Meta-Analysis. - Wang, Xiaonan; Li, Fengjie; Gao, Qi; Jiang, Zhen; Abudusaimaiti, Xiayidanmu; Yao, Jiangyue; Zhu, Huiping (J Alzheimers Dis, 2022)
BACKGROUND: Montreal Cognitive Assessment (MoCA) and Mini-Mental State Examination (MMSE) are neuropsychological tests commonly used by physicians for screening cognitive dysfunction of Alzheimer's disease (AD). Due to different imperfect reference standards, the performance of MoCA and MMSE do not reach consensus. It is necessary to evaluate the consistence and differentiation of MoCA and MMSE in the absence of a gold standard for AD. OBJECTIVE: We aimed to assess the accuracy of MoCA and MMSE in screening AD without a gold standard reference test. METHODS: Studies were identified from PubMed, Web of Science, CNKI, Chinese Wanfang Database, China Science and Technology Journal Database, and Cochrane Library. Our search was limited to studies published in English and Chinese before August 2021. A hierarchical Bayesian latent class model was performed in meta-analysis when the gold standard was absent. RESULTS: A total of 67 studies comprising 5,554 individuals evaluated for MoCA and 76,862 for MMSE were included in this meta-analysis. The pooled sensitivity was 0.934 (95% CI 0.905 to 0.954) for MoCA and 0.883 (95% CI 0.859 to 0.903) for MMSE, while the pooled specificity was 0.899 (95% CI 0.859 to 0.928) for MoCA and 0.903 (95% CI 0.879 to 0.923) for MMSE. MoCA was useful to rule out dementia associated with AD with lower negative likelihood ratio (LR-) (0.074, 95% CI 0.051 to 0.108). MoCA showed better performance with higher diagnostic odds ratio (DOR) (124.903, 95% CI 67.459 to 231.260). CONCLUSION: MoCA had better performance than MMSE in screening dementia associated with AD from patients with mild cognitive impairment or healthy controls.
Keywords: Alzheimer Disease; Bayes Theorem; Cognition; Cognitive Dysfunction; Humans; Mental Status and Dementia Tests; Neuropsychological Tests

Impact of COVID-19 on 'Living Well' with Mild-to-Moderate Dementia in the Community: Findings from the IDEAL Cohort. - Clare, Linda; Martyr, Anthony; Gamble, Laura D; Pentecost, Claire; Collins, Rachel; Dawson, Eleanor; Hunt, Anna; Parker, Sophie; Allan, Louise; Burns, Alistair; Hillman, Alexandra; Litherland, Rachael; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Negative impacts of the COVID-19 pandemic on people with dementia have been widely-documented, but most studies have relied on carer reports and few have compared responses to information collected before the pandemic. OBJECTIVE: We aimed to explore the impact of the pandemic on community-dwelling individuals with mild-to-moderate dementia and compare responses with pre-pandemic data. METHODS: During the second wave of the pandemic, we conducted structured telephone interviews with 173 people with dementia and 242 carers acting as informants, all of whom had previously participated in the IDEAL cohort. Where possible, we benchmarked responses against pre-pandemic data. RESULTS: Significant perceived negative impacts were identified in cognitive and functional skills and ability to engage in self-care and manage everyday activities, along with increased levels of loneliness and discontinuity in sense of self and a decline in perceived capability to 'live well'. Compared to pre-pandemic data, there were lower levels of pain, depression, and anxiety, higher levels of optimism, and better satisfaction with family support. There was little impact on physical health, mood, social connections and relationships, or perceptions of neighborhood characteristics. CONCLUSION: Efforts to mitigate negative impacts of pandemic-related restrictions and restore quality of life could focus on reablement to address the effects on participation in everyday activities, creating opportunities for social contact to reduce loneliness, and personalized planning to reconnect people with their pre-COVID selves. Such efforts may build on the resilience demonstrated by people with dementia and carers in coping with the pandemic.
Keywords: Activities of Daily Living; Adult; Aged; Aged, 80 and over; Caregivers; COVID-19; Dementia; Female; Humans; Male; Middle Aged; Neighborhood Characteristics; Quality of Life; SARS-CoV-2

Informal Caregivers' Attitude Toward Dementia: The Impact of Dementia Knowledge, Confidence in Dementia Care, and the Behavioral and Psychological Symptoms of the Person with Dementia. A Cross-Sectional Study. - Teichmann, Birgit; Gkioka, Mara; Kruse, Andreas; Tsolaki, Magda (J Alzheimers Dis, 2022)
BACKGROUND: Dementia is rapidly increasing worldwide due to demographic aging. More than two-thirds of patients are cared by family members. The quality of care depends on the caregivers' attitude toward dementia influencing patient care decisions. OBJECTIVE: The aim of this study is to examine the factors that influence the caregivers' attitude and whether there is an association between participation in a psycho-educational program and attitude. METHODS: We performed a cross-sectional study using a structured closed-ended questionnaire to retrieve socio-demographic information from caregivers and the persons with dementia (N = 86). The study included validated scales such as the Dementia Attitude Scale, the Dementia Knowledge Assessment Tool 2, the Positive Aspects of Caregiving, the Zarit Burden Interview, the Confidence in Dementia Scale, and Spielberger's State-Trait Anxiety Inventory, as well as a neuropsychological battery to assess the condition of people with dementia. RESULTS: Our final model explains 55.6% of the total variance and shows a significant correlation of five factors with attitude toward dementia: confidence, behavioral and psychological symptoms of dementia, anxiety as a trait, positive aspects of caregiving, and dementia knowledge. The caregivers who participated in a psycho-educational program showed a significantly more positive attitude toward dementia, better dementia knowledge, higher confidence in dementia care, and lower anxiety as a state. CONCLUSION: The strong correlation of attitude and knowledge, as well as confidence in dementia care, supports the tripartite model of attitude, which hypothesizes the interrelation of affect, cognition, and behavior.
Keywords: Attitude; Caregivers; Cross-Sectional Studies; Dementia; Humans; Surveys and Questionnaires

Investigating Causal Relations Between Circulating Metabolites and Alzheimer's Disease: A Mendelian Randomization Study. - Huang, Shu-Yi; Yang, Yu-Xiang; Zhang, Ya-Ru; Kuo, Kevin; Li, Hong-Qi; Shen, Xue-Ning; Chen, Shi-Dong; Chen, Ke-Liang; Dong, Qiang; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2022)
BACKGROUND: Metabolomics is a promising approach that can be used to understand pathophysiological pathways of Alzheimer's disease (AD). However, the causal relationships between metabolism and AD are poorly understood. OBJECTIVE: We aimed to investigate the causal association between circulating metabolites and risk of AD through two-sample Mendelian randomization (MR) approach. METHODS: Genetic associations with 123 circulating metabolic traits were utilized as exposures. Summary statistics data from International Genomics of Alzheimer's Project was used in primary analysis, including 21,982 AD cases and 41,944 controls. Validation was performed using family history of AD data from UK Biobank (27,696 cases of maternal AD, 14,338 cases of paternal AD, and 272,244 controls). We utilized inverse-variance weighted method as primary method. RESULTS: We found significantly increased risks of developing AD per standard deviation increase in the levels of circulating ApoB (odd ratio[OR] = 3.18; 95% confidence interval[CI]: 1.52-6.66, p = 0.0022), glycoprotein acetyls (OR = 1.21; 95% CI: 1.05-1.39, p = 0.0093), total cholesterol (OR = 2.73; 95% CI: 1.41-5.30, p = 0.0030), and low-density lipoprotein (LDL) cholesterol (OR = 2.34; 95% CI: 1.53-3.57, p = 0.0001). Whereas glutamine (OR = 0.81; 95% CI: 0.71-0.92, p = 0.0011) were significantly associated with lower risk of AD. We also detected causal effects of several different composition of LDL fractions on increased AD risk, which has been verified in validation. However, we found no association between circulating high-density lipoprotein cholesterol and AD. CONCLUSION: Our findings suggest causal effects of circulating glycoprotein acetyls, ApoB, LDL cholesterol, and serum total cholesterol on higher risk of AD, whereas glutamine showed the protective effect.
Keywords: Alzheimer Disease; Apolipoproteins B; Cholesterol; Genome-Wide Association Study; Glutamine; Humans; Mendelian Randomization Analysis; Polymorphism, Single Nucleotide; Risk Factors

Oral Health Status in Subjects with Amnestic Mild Cognitive Impairment and Alzheimer's Disease: Data from the Zabút Aging Project. - Panzarella, Vera; Mauceri, Rodolfo; Baschi, Roberta; Maniscalco, Laura; Campisi, Giuseppina; Monastero, Roberto (J Alzheimers Dis, 2022)
BACKGROUND: The relationship between Alzheimer's disease (AD) and periodontitis has been recently investigated with heterogenous results. OBJECTIVE: This study aims to evaluate the oral health status and its relationship with cognitive impairment of participants, enrolled in the Zabút Aging Project, a community-based cohort study performed in a rural community in Sicily, Italy. METHODS: A case-control study (20 subjects with AD, 20 with amnestic mild cognitive impairment [aMCI], and 20 controls) was conducted. The protocol included a comprehensive medical and cognitive-behavioral examination. Full-mouth evaluation, microbial analysis of subgingival plaque samples (by RT-PCR analysis), and oral health-related quality of life (OHR-QoL) were evaluated. RESULTS: The decayed, missing, and filled teeth (DMFT) total score of AD subjects was significantly higher than aMCI (p = 0.009) and controls (p = 0.001). Furthermore, the "M" component of DMFT (i.e., the number of missing teeth) was significantly higher in AD than in aMCI (p < 0.001) and controls (p < 0.001). A Poisson regression model revealed that age (p < 0.001), male gender (p = 0.001), and AD (p = 0.001) were positively correlated with DMFT. Concerning oral microbial load, the presence of Fusobacterium nucleatum was significantly higher in AD than in controls (p = 0.02), and a higher load of Treponema denticola was found in aMCI than with AD (p = 0.004). OHR-QoL scores did not differ among the groups. CONCLUSION: The current research suggests that AD is associated with chronic periodontitis, which is capable of determining tooth loss due to the pathogenicity of Fusobacterium nucleatum. These data remain to be confirmed in larger population-based cohorts.
Keywords: Aging; Alzheimer Disease; Case-Control Studies; Cognitive Dysfunction; Cohort Studies; Humans; Male; Neuropsychological Tests; Oral Health; Quality of Life

Peptidylarginine Deiminase and Alzheimer's Disease. - Wang, Lai; Chen, Hongyang; Tang, Jing; Guo, Zhengwei; Wang, Yanming (J Alzheimers Dis, 2022)
Peptidylarginine deiminases (PADs) are indispensable enzymes for post-translational modification of proteins, which can convert Arg residues on the surface of proteins to citrulline residues. The PAD family has five isozymes, PAD1, 2, 3, 4, and 6, which have been found in multiple tissues and organs. PAD2 and PAD4 were detected in cerebral cortex and hippocampus from human and rodent brain. In the central nervous system, abnormal expression and activation of PADs are involved in the pathological changes and pathogenesis of Alzheimer's disease (AD). This article reviews the classification, distribution, and function of PADs, with an emphasis on the relationship between the abnormal activation of PADs and AD pathogenesis, diagnosis, and the therapeutic potential of PADs as drug targets for AD.
Keywords: Alzheimer Disease; Animals; Cerebral Cortex; Citrulline; Hippocampus; Humans; Isoenzymes; Protein Processing, Post-Translational; Protein-Arginine Deiminases

Post-Stroke Cognitive Impairment: Epidemiology, Risk Factors, and Management. - Huang, Yu-Yuan; Chen, Shi-Dong; Leng, Xin-Yi; Kuo, Kevin; Wang, Zuo-Teng; Cui, Mei; Tan, Lan; Wang, Kai; Dong, Qiang; Yu, Jin-Tai (J Alzheimers Dis, 2022)
Stroke, characterized as a neurological deficit of cerebrovascular cause, is very common in older adults. Increasing evidence suggests stroke contributes to the risk and severity of cognitive impairment. People with cognitive impairment following stroke often face with quality-of-life issues and require ongoing support, which have a profound effect on caregivers and society. The high morbidity of post-stroke cognitive impairment (PSCI) demands effective management strategies, in which preventive strategies are more appealing, especially those targeting towards modifiable risk factors. In this review article, we attempt to summarize existing evidence and knowledge gaps on PSCI: elaborating on the heterogeneity in current definitions, reporting the inconsistent findings in PSCI prevalence in the literature, exploring established or less established predictors, outlining prevention and treatment strategies potentially effective or currently being tested, and proposing promising directions for future research.
Keywords: Aged; Cognitive Dysfunction; Humans; Prevalence; Risk Factors; Stroke

Psychosis as a Treatment Target in Dementia: A Roadmap for Designing Interventions. - Agüera-Ortiz, Luis; Babulal, Ganesh M; Bruneau, Marie-Andrée; Creese, Byron; D'Antonio, Fabrizia; Fischer, Corinne E; Gatchel, Jennifer R; Ismail, Zahinoor; Kumar, Sanjeev; McGeown, William J; Mortby, Moyra E; Nuñez, Nicolas A; et al. (J Alzheimers Dis, 2022)
Psychotic phenomena are among the most severe and disruptive symptoms of dementias and appear in 30% to 50% of patients. They are associated with a worse evolution and great suffering to patients and caregivers. Their current treatments obtain limited results and are not free of adverse effects, which are sometimes serious. It is therefore crucial to develop new treatments that can improve this situation. We review available data that could enlighten the future design of clinical trials with psychosis in dementia as main target. Along with an explanation of its prevalence in the common diseases that cause dementia, we present proposals aimed at improving the definition of symptoms and what should be included and excluded in clinical trials. A review of the available information regarding the neurobiological basis of symptoms, in terms of pathology, neuroimaging, and genomics, is provided as a guide towards new therapeutic targets. The correct evaluation of symptoms is transcendental in any therapeutic trial and these aspects are extensively addressed. Finally, a critical overview of existing pharmacological and non-pharmacological treatments is made, revealing the unmet needs, in terms of efficacy and safety. Our work emphasizes the need for better definition and measurement of psychotic symptoms in dementias in order to highlight their differences with symptoms that appear in non-dementing diseases such as schizophrenia. Advances in neurobiology should illuminate the development of new, more effective and safer molecules for which this review can serve as a roadmap in the design of future clinical trials.
Keywords: Caregivers; Dementia; Hallucinations; Humans; Psychotic Disorders; Schizophrenia

Relationship Between the Gut Microbiota and Alzheimer's Disease: A Systematic Review. - González Cordero, Elisa Marina; Cuevas-Budhart, Miguel Angel; Pérez Morán, Diana; Trejo Villeda, Miguel Angel; Gomez-Del-Pulgar Gª-Madrid, Mercedes (J Alzheimers Dis, 2022)
BACKGROUND: In recent years, scientific research on the gut microbiota and their relationship with some diseases, including neurological ones, has notably increased. As a result of these investigations, the so-called gut-brain axis arises. Despite its influence on the evolution and development of cognitive impairment, the gut-brain axis is little defined and demonstrated. OBJECTIVE: To provide the best scientific evidence available on the relationship between the gut microbiota and Alzheimer's disease. METHOD: Systematic and narrative review of the information generated in the last 5 years in national and international databases, in English and Spanish. RESULTS: Eight observational studies were selected, carried out in humans and, therefore, suitable for inclusion in this review. CONCLUSION: The results of these studies support the hypothesis that there is a relationship between the gut microbiota and cognitive disorders through the gut-brain axis. However, today, there is a substantial lack of human studies, especially clinical trials, which makes it difficult to formulate clinical recommendations on this topic.
Keywords: Alzheimer Disease; Brain; Brain-Gut Axis; Cognitive Dysfunction; Gastrointestinal Microbiome; Humans

Rheumatoid Arthritis, Cognitive Impairment, and Neuroimaging Biomarkers: Results from the Mayo Clinic Study of Aging. - Vassilaki, Maria; Crowson, Cynthia S; Davis Iii, John M; Duong, Stephanie Q; Jones, David T; Nguyen, Aivi; Mielke, Michelle M; Vemuri, Prashanthi; Myasoedova, Elena (J Alzheimers Dis, 2022)
BACKGROUND: Observational studies suggested that dementia risk in patients with rheumatoid arthritis (RA) is higher than in the general population. OBJECTIVE: To examine the associations of RA with cognitive decline and dementia, and neuroimaging biomarkers of aging, Alzheimer's disease, and vascular pathology in adult participants in the Mayo Clinic Study of Aging (MCSA). METHODS: Participants with RA were matched 1:3 on age, sex, education, and baseline cognitive diagnosis to participants without RA. RA cases with MRI were also matched with non-cases with available MRI. All available imaging studies (i.e., amyloid and FDG PET, sMRI, and FLAIR) were included. The study included 104 participants with RA and 312 without RA (mean age (standard deviation, SD) 75.0 (10.4) years, 33% male and average follow-up (SD) 4.2 (3.8) years). RESULTS: Groups were similar in cognitive decline and risk of incident dementia. Among participants with neuroimaging, participants with RA (n = 33) and without RA (n = 98) had similar amyloid burden and neurodegeneration measures, including regions sensitive to aging and dementia, but greater mean white matter hyperintensity volume relative to the total intracranial volume (mean (SD)% : 1.12 (0.57)% versus 0.76 (0.69)% of TIV, p = 0.01), and had higher mean (SD) number of cortical infarctions (0.24 (0.44) versus 0.05 (0.33), p = 0.02). CONCLUSION: Although cognitive decline and dementia risk were similar in participants with and without RA, participants with RA had more abnormal cerebrovascular pathology on neuroimaging. Future studies should examine the mechanisms underlying these changes and potential implications for prognostication and prevention of cognitive decline in RA.
Keywords: Aged; Aging; Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Amyloidosis; Arthritis, Rheumatoid; Biomarkers; Brain; Cognitive Dysfunction; Female; Fluorodeoxyglucose F18; Humans; Magnetic Resonance Imaging; Male; Neuroimaging; Positron-Emission Tomography

Risk of Alzheimer's Disease Following Influenza Vaccination: A Claims-Based Cohort Study Using Propensity Score Matching. - Bukhbinder, Avram S; Ling, Yaobin; Hasan, Omar; Jiang, Xiaoqian; Kim, Yejin; Phelps, Kamal N; Schmandt, Rosemarie E; Amran, Albert; Coburn, Ryan; Ramesh, Srivathsan; Xiao, Qian; Schulz, Paul E (J Alzheimers Dis, 2022)
BACKGROUND: Prior studies have found a reduced risk of dementia of any etiology following influenza vaccination in selected populations, including veterans and patients with serious chronic health conditions. However, the effect of influenza vaccination on Alzheimer's disease (AD) risk in a general cohort of older US adults has not been characterized. OBJECTIVE: To compare the risk of incident AD between patients with and without prior influenza vaccination in a large US claims database. METHODS: Deidentified claims data spanning September 1, 2009 through August 31, 2019 were used. Eligible patients were free of dementia during the 6-year look-back period and≥65 years old by the start of follow-up. Propensity-score matching (PSM) was used to create flu-vaccinated and flu-unvaccinated cohorts with similar baseline demographics, medication usage, and comorbidities. Relative risk (RR) and absolute risk reduction (ARR) were estimated to assess the effect of influenza vaccination on AD risk during the 4-year follow-up. RESULTS: From the unmatched sample of eligible patients (n = 2,356,479), PSM produced a sample of 935,887 flu-vaccinated-unvaccinated matched pairs. The matched sample was 73.7 (SD, 8.7) years of age and 56.9% female, with median follow-up of 46 (IQR, 29-48) months; 5.1% (n = 47,889) of the flu-vaccinated patients and 8.5% (n = 79,630) of the flu-unvaccinated patients developed AD during follow-up. The RR was 0.60 (95% CI, 0.59-0.61) and ARR was 0.034 (95% CI, 0.033-0.035), corresponding to a number needed to treat of 29.4. CONCLUSION: This study demonstrates that influenza vaccination is associated with reduced AD risk in a nationwide sample of US adults aged 65 and older.
Keywords: Adult; Aged; Alzheimer Disease; Chronic Disease; Cohort Studies; Female; Humans; Influenza, Human; Male; Middle Aged; Propensity Score; Vaccination

Safety and Efficacy of Monoclonal Antibodies for Alzheimer's Disease: A Systematic Review and Meta-Analysis of Published and Unpublished Clinical Trials. - Lacorte, Eleonora; Ancidoni, Antonio; Zaccaria, Valerio; Remoli, Giulia; Tariciotti, Leonardo; Bellomo, Guido; Sciancalepore, Francesco; Corbo, Massimo; Lombardo, Flavia L; Bacigalupo, Ilaria; Canevelli, Marco; Piscopo, Paola; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Monoclonal antibodies (mAbs) are currently among the most investigated targets for potential disease-modifying therapies in Alzheimer's disease (AD). OBJECTIVE: Our objectives were to identify all registered trials investigating mAbs in MCI due to AD or AD at any stage, retrieve available published and unpublished data from all registered trials, and analyze data on safety and efficacy outcomes. METHODS: A systematic search of all registered trials on ClinicalTrials.gov and EUCT was performed. Available results were searched on both platforms and on PubMed, ISI Web of Knowledge, and The Cochrane Library. RESULTS: Overall, 101 studies were identified on 27 mAbs. Results were available for 50 trials investigating 12 mAbs. For 18 trials, data were available from both published and unpublished sources, for 21 trials only from published sources, and for 11 trials only from unpublished sources. Meta-analyses of amyloid-related imaging abnormalities (ARIA) events showed overall risk ratios of 10.65 for ARIA-E and of 1.75 for ARIA-H. The meta-analysis of PET-SUVR showed an overall significant effect of mAbs in reducing amyloid (SMD -0.88), but when considering clinical efficacy, data on CDR-SB showed that treated patients had a statistically significant but clinically non-relevant lower worsening (MD -0.15). CONCLUSION: Our results suggest that the risk-benefit profile of mAbs remains unclear. Research should focus on clarifying the effect of amyloid on cognitive decline, providing data on treatment response rate, and accounting for minimal clinically important difference. Research on mAbs should also investigate the possible long-term impact of ARIA events, including potential factors predicting their onset.
Keywords: Alzheimer Disease; Amyloid; Amyloidogenic Proteins; Amyloidosis; Antibodies, Monoclonal; Cognitive Dysfunction; Humans

Shortening of Saccades as a Possible Easy-to-Use Biomarker to Detect Risk of Alzheimer's Disease. - Hannonen, Sanna; Andberg, Sami; Kärkkäinen, Virve; Rusanen, Minna; Lehtola, Juha-Matti; Saari, Toni; Korhonen, Ville; Hokkanen, Laura; Hallikainen, Merja; Hänninen, Tuomo; Leinonen, Ville; Kaarniranta, Kai; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Wide-ranging functional defects in eye movements have been reported in Alzheimer's disease (AD) dementia. The detection of abnormal eye movements and reading problems may identify persons at risk of AD when clear clinical symptoms are lacking. OBJECTIVE: To examine whether computer-based eye-tracking (ET) analysis of King-Devick (KD) test results differentiates cognitively healthy persons from persons with minor problems in cognitive testing or diagnosed mild AD. METHODS: We recruited 78 participants (57 non-demented, 21 with mild AD) who underwent neurological examination, the Consortium to Establish a Registry for Alzheimer's Disease neuropsychological test battery (CERAD-NB), and a Clinical Dementia Rating (CDR) interview. The non-demented participants were further divided into control (normal CERAD subtests, mean MMSE = 28) and objective mild cognitive impairment (MCI; decline in at least one CERAD memory score, mean MMSE = 27) groups. The KD reading test was performed using computer-based ET. The total time used for the reading test, errors made, fixation and saccade durations, and saccade amplitudes were analyzed. RESULTS: We found significant differences between the control, objective MCI, and AD groups in regard to the mean saccade amplitude (3.58, 3.33, and 3.21 ms, respectively, p < 0.03) and duration (27.1, 25.3, and 24.8 ms, respectively, p < 0.05). The KD error scores in the AD group differed significantly (p < 0.01) from the other groups. CONCLUSION: Computed ET analysis of the KD test may help detect persons with objective MCI early when clear clinical symptoms are lacking. The portable device for ET is easy to use in primary health care memory clinics.
Keywords: Alzheimer Disease; Biomarkers; Cognitive Dysfunction; Humans; Neuropsychological Tests; Saccades

A Tale of Two Diseases: Exploring Mechanisms Linking Diabetes Mellitus with Alzheimer's Disease. - Lynn, Jessica; Park, Mingi; Ogunwale, Christiana; Acquaah-Mensah, George K (J Alzheimers Dis, 2022)
Dementias, including the type associated with Alzheimer's disease (AD), are on the rise worldwide. Similarly, type 2 diabetes mellitus (T2DM) is one of the most prevalent chronic diseases globally. Although mechanisms and treatments are well-established for T2DM, there remains much to be discovered. Recent research efforts have further investigated factors involved in the etiology of AD. Previously perceived to be unrelated diseases, commonalities between T2DM and AD have more recently been observed. As a result, AD has been labeled as "type 3 diabetes". In this review, we detail the shared processes that contribute to these two diseases. Insulin resistance, the main component of the pathogenesis of T2DM, is also present in AD, causing impaired brain glucose metabolism, neurodegeneration, and cognitive impairment. Dysregulation of insulin receptors and components of the insulin signaling pathway, including protein kinase B, glycogen synthase kinase 3β, and mammalian target of rapamycin are reported in both diseases. T2DM and AD also show evidence of inflammation, oxidative stress, mitochondrial dysfunction, advanced glycation end products, and amyloid deposition. The impact that changes in neurovascular structure and genetics have on the development of these conditions is also being examined. With the discovery of factors contributing to AD, innovative treatment approaches are being explored. Investigators are evaluating the efficacy of various T2DM medications for possible use in AD, including but not limited to glucagon-like peptide-1 receptor agonists and peroxisome proliferator-activated receptor-gamma agonists. Furthermore, there are 136 active trials involving 121 therapeutic agents targeting novel AD biomarkers. With these efforts, we are one step closer to alleviating the ravaging impact of AD on our communities.
Keywords: Alzheimer Disease; Animals; Biomarkers; Brain Chemistry; Cognitive Dysfunction; Diabetes Mellitus, Type 2; Glucose; Glycation End Products, Advanced; Humans; Inflammation; Insulin Resistance; Oxidative Stress; Randomized Controlled Trials as Topic

α-Lipoic Acid Has the Potential to Normalize Copper Metabolism, Which Is Dysregulated in Alzheimer's Disease. - Metsla, Kristel; Kirss, Sigrid; Laks, Katrina; Sildnik, Gertrud; Palgi, Mari; Palumaa, Teele; Tõugu, Vello; Palumaa, Peep (J Alzheimers Dis, 2022)
BACKGROUND: Alzheimer's disease (AD) is an age-dependent progressive neurodegenerative disorder and the most common cause of dementia. The treatment and prevention of AD present immense yet unmet needs. One of the hallmarks of AD is the formation of extracellular amyloid plaques in the brain, composed of amyloid-β (Aβ) peptides. Besides major amyloid-targeting approach there is the necessity to focus also on alternative therapeutic strategies. One factor contributing to the development of AD is dysregulated copper metabolism, reflected in the intracellular copper deficit and excess of extracellular copper. OBJECTIVE: In the current study, we follow the widely accepted hypothesis that the normalization of copper metabolism leads to the prevention or slowing of the disease and search for new copper-regulating ligands. METHODS: We used cell culture, ICP MS, and Drosophila melanogaster models of AD. RESULTS: We demonstrate that the natural intracellular copper chelator, α-lipoic acid (LA) translocates copper from extracellular to intracellular space in an SH-SY5Y-based neuronal cell model and is thus suitable to alleviate the intracellular copper deficit characteristic of AD neurons. Furthermore, we show that supplementation with LA protects the Drosophila melanogaster models of AD from developing AD phenotype by improving locomotor activity of fruit fly with overexpression of human Aβ with Iowa mutation in the fly brain. In addition, LA slightly weakens copper-induced smooth eye phenotype when amyloid-β protein precursor (AβPP) and beta-site AβPP cleaving enzyme 1 (BACE1) are overexpressed in eye photoreceptor cells. CONCLUSION: Collectively, these results provide evidence that LA has the potential to normalize copper metabolism in AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Aspartic Acid Endopeptidases; Brain; Cell Line; Copper; Disease Models, Animal; Drosophila melanogaster; Humans; Neurons; Thioctic Acid

Alzheimer's Disease and Face Masks in Times of COVID-19. - Gil, Roger; Arroyo-Anlló, Eva M (J Alzheimers Dis, 2021)
Generalized lockdown caused by COVID-19, necessary yesterday, can no longer be that of tomorrow. It will no longer be possible to cram the humblest into cramped areas, but priority must be given to prevention (certainly with physical barriers, hydro-alcoholic gel, face masks), biological diagnosis, isolation, and also the care of any infected person. COVID-19 has hit the most vulnerable first in terms of biological inequality, such as Alzheimer's disease (AD) patients. Those with AD can have sensorial deficits and perception troubles, including visual difficulties and the inability to recognize faces and emotions. Face masks and physical distancing can disrupt facial familiarity and make it more difficult to recognize emotional facial expressions. It can provoke distress, which the visitor can perceive and feel obligated to take off the face mask. This gesture should not be considered as an act of indiscipline, but an act of empathy. Transparent face masks could improve the suffering of AD patients, distraught in the presence of their loved ones whose masks hide their faces. Wearing a mask should not be due to fear of punishment, but as an understanding of the responsibility of each individual in the control of the current pandemic. It may be necessary to convince more citizens of this civic duty, using clear and attractive messaging in order to standardize the wearing of face masks for the general public and to adapt them to the needs of patients.
Keywords: Alzheimer Disease; Communicable Disease Control; COVID-19; Emotions; Facial Expression; Humans; Masks

ANMerge: A Comprehensive and Accessible Alzheimer's Disease Patient-Level Dataset. - Birkenbihl, Colin; Westwood, Sarah; Shi, Liu; Nevado-Holgado, Alejo; Westman, Eric; Lovestone, Simon; Hofmann-Apitius, Martin (J Alzheimers Dis, 2021)
BACKGROUND: Accessible datasets are of fundamental importance to the advancement of Alzheimer's disease (AD) research. The AddNeuroMed consortium conducted a longitudinal observational cohort study with the aim to discover AD biomarkers. During this study, a broad selection of data modalities was measured including clinical assessments, magnetic resonance imaging, genotyping, transcriptomic profiling, and blood plasma proteomics. Some of the collected data were shared with third-party researchers. However, this data was incomplete, erroneous, and lacking in interoperability. OBJECTIVE: To provide the research community with an accessible, multimodal, patient-level AD cohort dataset. METHODS: We systematically addressed several limitations of the originally shared resources and provided additional unreleased data to enhance the dataset. RESULTS: In this work, we publish and describe ANMerge, a new version of the AddNeuroMed dataset. ANMerge includes multimodal data from 1,702 study participants and is accessible to the research community via a centralized portal. CONCLUSION: ANMerge is an information rich patient-level data resource that can serve as a discovery and validation cohort for data-driven AD research, such as, for example, machine learning and artificial intelligence approaches.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cohort Studies; Datasets as Topic; Female; Gene Expression Profiling; Genotype; Humans; Magnetic Resonance Imaging; Male; Proteomics

Anti-Aβ Antibody Aducanumab Regulates the Proteome of Senile Plaques and Closely Surrounding Tissue in a Transgenic Mouse Model of Alzheimer's Disease. - Bastrup, Joakim; Hansen, Kathrine H; Poulsen, Thomas B G; Kastaniegaard, Kenneth; Asuni, Ayodeji A; Christensen, Søren; Belling, Dorthe; Helboe, Lone; Stensballe, Allan; Volbracht, Christiane (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease (AD) is characterized by accumulation of amyloid-β (Aβ) species and deposition of senile plaques (SPs). Clinical trials with the anti-Aβ antibody aducanumab have been completed recently. OBJECTIVE: To characterize the proteomic profile of SPs and surrounding tissue in a mouse model of AD in 10-month-old tgAPPPS1-21 mice after chronic treatment with aducanumab for four months with weekly dosing (10 mg/kg). METHODS: After observing significant reduction of SP numbers in hippocampi of aducanumab-treated mice, we applied a localized proteomic analysis by combining laser microdissection and liquid chromatography-tandem mass spectrometry (LC-MS/MS) of the remaining SPs in hippocampi. We microdissected three subregions, containing SPs, SP penumbra level 1, and an additional penumbra level 2 to follow the proteomic profile as gradient. RESULTS: In the aducanumab-treated mice, we identified 17 significantly regulated proteins that were associated with 1) mitochondria and metabolism (ACAT2, ATP5J, ETFA, EXOG, HK1, NDUFA4, NDUFS7, PLCB1, PPP2R4), 2) cytoskeleton and axons (ADD1, CAPZB, DPYSL3, MAG), 3) stress response (HIST1H1C/HIST1H1D, HSPA12A), and 4) AβPP trafficking/processing (CD81, GDI2). These pathways and some of the identified proteins are implicated in AD pathogenesis. Proteins associated with mitochondria and metabolism were mainly upregulated while proteins associated with AβPP trafficking/processing and stress response pathways were mainly downregulated, suggesting that aducanumab could lead to a beneficial proteomic profile around SPs in tgAPPPS1-21 mice. CONCLUSION: We identified novel proteomic patterns of SPs and surrounding tissue indicating that chronic treatment with aducanumab could inhibit Aβ toxicity and increase phagocytosis and cell viability.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Antibodies, Monoclonal, Humanized; Brain; Chromatography, Liquid; Cytoskeletal Proteins; Disease Models, Animal; Humans; Mice; Mice, Transgenic; Mitochondrial Proteins; Plaque, Amyloid; Presenilin-1; Protein Transport; Proteome; Proteomics; Stress, Physiological; Tandem Mass Spectrometry

APOE4 Copy Number-Dependent Proteomic Changes in the Cerebrospinal Fluid. - Berger, Miles; Cooter, Mary; Roesler, Alexander S; Chung, Stacey; Park, John; Modliszewski, Jennifer L; VanDusen, Keith W; Thompson, J Will; Moseley, Arthur; Devinney, Michael J; Smani, Shayan; Hall, Ashley; et al. (J Alzheimers Dis, 2021)
BACKGROUND: APOE4 has been hypothesized to increase Alzheimer's disease risk by increasing neuroinflammation, though the specific neuroinflammatory pathways involved are unclear. OBJECTIVE: Characterize cerebrospinal fluid (CSF) proteomic changes related to APOE4 copy number. METHODS: We analyzed targeted proteomic data from ADNI CSF samples using a linear regression model adjusting for age, sex, and APOE4 copy number, and additional linear models also adjusting for AD clinical status or for CSF Aβ, tau, or p-tau levels. False discovery rate was used to correct for multiple comparisons correction. RESULTS: Increasing APOE4 copy number was associated with a significant decrease in a CRP peptide level across all five models (q < 0.05 for each), and with significant increases in ALDOA, CH3L1 (YKL-40), and FABPH peptide levels (q < 0.05 for each) except when controlling for AD clinical status or neurodegeneration biomarkers (i.e., CSF tau or p-tau). In all models except the one controlling for CSF Aβ levels, though not statistically significant, there was a consistent inverse direction of association between APOE4 copy number and the levels of all 24 peptides from all 8 different complement proteins measured. The odds of this happening by chance for 24 unrelated peptides would be less than 1 in 16 million. CONCLUSION: Increasing APOE4 copy number was associated with decreased CSF CRP levels across all models, and increased CSF ALDOA, CH3L1, and FABH levels when controlling for CSF Aβ levels. Increased APOE4 copy number may also be associated with decreased CSF complement pathway protein levels, a hypothesis for investigation in future studies.
Keywords: Aged; Alzheimer Disease; Apolipoprotein E4; Biomarkers; Chitinase-3-Like Protein 1; DNA Copy Number Variations; Female; Fructose-Bisphosphate Aldolase; Humans; Male; Proteomics; Receptors, Immunologic

Assessing the Progression of Alzheimer's Disease in Real-World Settings in Three European Countries. - Lladó, Albert; Froelich, Lutz; Khandker, Rezaul K; Roset, Montserrat; Black, Christopher M; Lara, Nuria; Chekani, Farid; Ambegaonkar, Baishali M (J Alzheimers Dis, 2021)
BACKGROUND: There exists considerable variation in disease progression rates among patients with Alzheimer's disease (AD). OBJECTIVE: The primary objective of this observational study is to assess the progression of AD by characterizing cognitive, functional, and behavioral changes during the follow-up period between 6 and 24 months. METHODS: A longitudinal prospective study with community-dwelling patients with an established clinical diagnosis of AD of mild to moderate severity was conducted in Germany, Spain and the UK. A sample of 616 patients from 69 sites was included. RESULTS: Patients had a mean of 1.9 years (SD = 1.9) since AD diagnosis at study inclusion. Cognitive symptoms were reported to have first occurred a mean of 1.1 years (SD = 1.7) prior to AD diagnosis and 1.4 (SD = 1.8) years prior to AD treatment. Patients initially diagnosed with mild and moderate AD spent a median (95%CI) of 3.7 (2.8; 4.4) and 11.1 (6.1, 'not reached') years until progression to moderate and severe AD, respectively, according to the Mini-Mental State Examination (MMSE) scores. A mixed model developed for cognitive, functional, and neuropsychiatric scores, obtained from study patients at baseline and during follow-up period, showed progressive deterioration of AD patients over time. CONCLUSION: The study showed a deterioration of cognitive, functional, and neuropsychiatric functions during the follow-up period. Cognitive deterioration was slightly faster in patients with moderate AD compared to mild AD. The duration of moderate AD can be overestimated due to the use of retrospective data, lack of availability of MMSE scores in clinical charts and exclusion of patients at time of institutionalization.
Keywords: Alzheimer Disease; Cholinesterase Inhibitors; Cognition Disorders; Disease Progression; Europe; Germany; Humans; Institutionalization; Neuropsychological Tests; Spain

Broader Insights into Understanding Tumor Necrosis Factor and Neurodegenerative Disease Pathogenesis Infer New Therapeutic Approaches. - Clark, I A; Vissel, B (J Alzheimers Dis, 2021)
Proinflammatory cytokines such as tumor necrosis factor (TNF), with its now appreciated key roles in neurophysiology as well as neuropathophysiology, are sufficiently well-documented to be useful tools for enquiry into the natural history of neurodegenerative diseases. We review the broader literature on TNF to rationalize why abruptly-acquired neurodegenerative states do not exhibit the remorseless clinical progression seen in those states with gradual onsets. We propose that the three typically non-worsening neurodegenerative syndromes, post-stroke, post-traumatic brain injury (TBI), and post cardiac arrest, usually become and remain static because of excess cerebral TNF induced by the initial dramatic peak keeping microglia chronically activated through an autocrine loop of microglial activation through excess cerebral TNF. The existence of this autocrine loop rationalizes post-damage repair with perispinal etanercept and proposes a treatment for cerebral aspects of COVID-19 chronicity. Another insufficiently considered aspect of cerebral proinflammatory cytokines is the fitness of the endogenous cerebral anti-TNF system provided by norepinephrine (NE), generated and distributed throughout the brain from the locus coeruleus (LC). We propose that an intact LC, and therefore an intact NE-mediated endogenous anti-cerebral TNF system, plus the DAMP (damage or danger-associated molecular pattern) input having diminished, is what allows post-stroke, post-TBI, and post cardiac arrest patients a strong long-term survival advantage over Alzheimer's disease and Parkinson's disease sufferers. In contrast, Alzheimer's disease and Parkinson's disease patients remorselessly worsen, being handicapped by sustained, accumulating, DAMP and PAMP (pathogen-associated molecular patterns) input, as well as loss of the LC-origin, NE-mediated, endogenous anti-cerebral TNF system. Adrenergic receptor agonists may counter this.
Keywords: Alzheimer Disease; Anti-Inflammatory Agents, Non-Steroidal; Brain; Brain Injuries; COVID-19; Disease Progression; Etanercept; Heart Arrest; Humans; Locus Coeruleus; Neurodegenerative Diseases; Norepinephrine; Parkinson Disease; Risk Factors; SARS-CoV-2; Stroke; Survivors; Tumor Necrosis Factor-alpha

Cannabidiol Ameliorates Cognitive Function via Regulation of IL-33 and TREM2 Upregulation in a Murine Model of Alzheimer's Disease. - Khodadadi, Hesam; Salles, Évila Lopes; Jarrahi, Abbas; Costigliola, Vincenzo; Khan, M B; Yu, Jack C; Morgan, John C; Hess, David C; Vaibhav, Kumar; Dhandapani, Krishnan M; Baban, Babak (J Alzheimers Dis, 2021)
There is a dire need for due innovative therapeutic modalities to improve outcomes of AD patients. In this study, we tested whether cannabidiol (CBD) improves outcomes in a translational model of familial AD and to investigate if CBD regulates interleukin (IL)-33 and triggering receptor expressed on myeloid cells 2 (TREM2), which are associated with improved cognitive function. CBD was administered to 5xFAD mice, which recapitulate early onset, familial AD. Behavioral tests and immunoassays were used to evaluate cognitive and motor outcomes. Our findings suggest that CBD treatment enhanced IL-33 and TREM2 expression, ameliorated the symptoms of AD, and retarded cognitive decline.
Keywords: Alzheimer Disease; Animals; Cannabidiol; Cognition; Disease Models, Animal; Humans; Interleukin-33; Male; Membrane Glycoproteins; Mice; Mice, Transgenic; Receptors, Immunologic; Up-Regulation

Clinical Approach of Low-Dose Whole-Brain Ionizing Radiation Treatment in Alzheimer's Disease Dementia Patients. - Chung, Mijoo; Rhee, Hak Young; Chung, Weon Kuu (J Alzheimers Dis, 2021)
Our research team recently published two relevant papers. In one study, we have seen the acute effect of low-dose ionizing irradiation (LDIR) did not reduce the amyloid-β (Aβ) protein concentration in brain tissue, yet significantly improved synaptic degeneration and neuronal loss in the hippocampus and cerebral cortex. Surprisingly, in another study, we could see late effect that the LDIR-treated mice showed significantly improved learning and memory skills compared with those in the sham group. In addition, Aβ concentrations were significantly decreased in brain tissue. Furthermore, the pro-inflammatory cytokine tumor necrosis factor-α was decreased and the anti-inflammatory cytokine transforming growth factor-β was increased in the brain tissue of 5xFAD mice treated with LDIR. Definitive clinical results for the safety and efficacy of LDIR have not yet been published and, despite the promising outcomes reported during preclinical studies, LDIR can only be applied to patients with Alzheimer's disease dementia when clinical results are made available. In addition, in the case of LDIR, additional large-scale clinical studies are necessary to determine the severity of Alzheimer's disease dementia, indications for LDIR, the total dose to be irradiated, fraction size, and intervals of LDIR treatment. The purpose of this review is to summarize the mechanism of LDIR based on existing preclinical results in a way that is useful for conducting subsequent clinical research.
Keywords: Alzheimer Disease; Animals; Brain; Cranial Irradiation; Humans

Cognition at Each Stage of Lewy Body Disease with Co-occurring Alzheimer's Disease Pathology. - Ryman, Sephira G; Yutsis, Maya; Tian, Lu; Henderson, Victor W; Montine, Thomas J; Salmon, David P; Galasko, Douglas; Poston, Kathleen L (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease neuropathologic change (ADNC) may contribute to dementia in patients with Lewy body disease (LBD) pathology. OBJECTIVE: To examine how co-occurring ADNC impacts domain specific cognitive impairments at each pathologic stage (brainstem, limbic, cerebral cortical) of LBD. METHODS: 2,433 participants with antemortem longitudinal neuropsychological assessment and postmortem neuropathological assessment from the National Alzheimer's Coordinating Center's Uniform Data Set were characterized based on the evaluation of ADNC and LBD. Longitudinal mixed-models were used to derive measures of cumulative cognitive deficit for each cognitive domain at each pathologic stage of LBD (brainstem, limbic, and cerebral cortical). RESULTS: 111 participants with a pathologic diagnosis of LBD, 741 participants with combined LBD and ADNC, 1,357 participants with ADNC only, and 224 with no pathology (healthy controls) were included in the analyses. In the executive/visuospatial domain, combined LBD and ADNC showed worse deficits than LBD only when Lewy bodies were confined to the brainstem, but no difference when Lewy bodies extended to the limbic or cerebral cortical regions. The cerebral cortical LBD only group exhibited greater executive/visuospatial deficits than the ADNC only group. By contrast, the ADNC only group and the combined pathology group both demonstrated significantly greater cumulative memory deficits relative to Lewy body disease only, regardless of stage. CONCLUSION: The impact of co-occurring ADNC on antemortem cumulative cognitive deficits varies not only by domain but also on the pathological stage of Lewy bodies. Our findings stress the cognitive impact of different patterns of neuropathological progression in Lewy body diseases.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Cognitive Dysfunction; Female; Humans; Lewy Body Disease; Male

Cognitive Effects of the BET Protein Inhibitor Apabetalone: A Prespecified Montreal Cognitive Assessment Analysis Nested in the BETonMACE Randomized Controlled Trial. - Cummings, Jeffrey; Schwartz, Gregory G; Nicholls, Stephen J; Khan, Aziz; Halliday, Chris; Toth, Peter P; Sweeney, Michael; Johansson, Jan O; Wong, Norman C W; Kulikowski, Ewelina; Kalantar-Zadeh, Kamyar; Lebioda, Kenneth; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Epigenetic changes may contribute importantly to cognitive decline in late life including Alzheimer's disease (AD) and vascular dementia (VaD). Bromodomain and extra-terminal (BET) proteins are epigenetic "readers" that may distort normal gene expression and contribute to chronic disorders. OBJECTIVE: To assess the effects of apabetalone, a small molecule BET protein inhibitor, on cognitive performance of patients 70 years or older participating in a randomized trial of patients at high risk for major cardiovascular events (MACE). METHODS: The Montreal Cognitive Assessment (MoCA) was performed on all patients 70 years or older at the time of randomization. 464 participants were randomized to apabetalone or placebo in the cognition sub-study. In a prespecified analysis, participants were assigned to one of three groups: MoCA score≥26 (normal performance), MoCA score 25-22 (mild cognitive impairment), and MoCA score≤21 (dementia). Exposure to apabetalone was equivalent in the treatment groups in each MoCA-defined group. RESULTS: Apabetalone was associated with an increased total MoCA score in participants with baseline MoCA score of≤21 (p = 0.02). There was no significant difference in change from baseline in the treatment groups with higher MoCA scores. In the cognition study, more patients randomized to apabetalone discontinued study drug for adverse effects (11.3% versus 7.9%). CONCLUSION: In this randomized controlled study, apabetalone was associated with improved cognition as measured by MoCA scores in those with baseline scores of 21 or less. BET protein inhibitors warrant further investigation for late life cognitive disorders.
Keywords: Aged; Cardiovascular Diseases; Cognitive Dysfunction; Epigenesis, Genetic; Female; Humans; Male; Mental Status and Dementia Tests; Middle Aged; Quinazolinones

Combining Multimodal Behavioral Data of Gait, Speech, and Drawing for Classification of Alzheimer's Disease and Mild Cognitive Impairment. - Yamada, Yasunori; Shinkawa, Kaoru; Kobayashi, Masatomo; Caggiano, Vittorio; Nemoto, Miyuki; Nemoto, Kiyotaka; Arai, Tetsuaki (J Alzheimers Dis, 2021)
BACKGROUND: Gait, speech, and drawing behaviors have been shown to be sensitive to the diagnosis of Alzheimer's disease (AD) and mild cognitive impairment (MCI). However, previous studies focused on only analyzing individual behavioral modalities, although these studies suggested that each of these modalities may capture different profiles of cognitive impairments associated with AD. OBJECTIVE: We aimed to investigate if combining behavioral data of gait, speech, and drawing can improve classification performance compared with the use of individual modality and if each of these behavioral data can be associated with different cognitive and clinical measures for the diagnosis of AD and MCI. METHODS: Behavioral data of gait, speech, and drawing were acquired from 118 AD, MCI, and cognitively normal (CN) participants. RESULTS: Combining all three behavioral modalities achieved 93.0% accuracy for classifying AD, MCI, and CN, and only 81.9% when using the best individual behavioral modality. Each of these behavioral modalities was statistically significantly associated with different cognitive and clinical measures for diagnosing AD and MCI. CONCLUSION: Our findings indicate that these behaviors provide different and complementary information about cognitive impairments such that classification of AD and MCI is superior to using either in isolation.
Keywords: Aged; Alzheimer Disease; Cognitive Dysfunction; Female; Gait; Humans; Male; Neuropsychological Tests; Speech

Could Altered Evoked Pain Responsiveness Be a Phenotypic Biomarker for Alzheimer's Disease Risk? A Cross-Sectional Analysis of Cognitively Healthy Individuals. - Romano, Raymond R; Carter, Michael A; Dietrich, Mary S; Cowan, Ronald L; Bruehl, Stephen P; Monroe, Todd B (J Alzheimers Dis, 2021)
BACKGROUND: This study evaluated whether the apolipoprotein ɛ4 (APOE4) allele, a genetic marker associated with increased risk of developing late-onset Alzheimer's disease (AD), was associated with differences in evoked pain responsiveness in cognitively healthy subjects. OBJECTIVE: The aim was to determine whether individuals at increased risk of late-onset AD based on APOE allele genotype differ phenotypically in their response to experimentally-induced painful stimuli compared to those who do not have at least one copy of the ɛ4 allele. METHODS: Forty-nine cognitively healthy subjects aged 30-89 years old with the APOE4 allele (n = 12) and without (n = 37) were assessed for group differences in pain thresholds and affective (unpleasantness) responses to experimentally-induced thermal pain stimuli. RESULTS: Statistically significant main effects of APOE4 status were observed for both the temperature at which three different pain intensity percepts were reached (p = 0.040) and the level of unpleasantness associated with each (p = 0.014). APOE4 positive participants displayed lower overall pain sensitivity than those who were APOE4 negative and also greater overall levels of pain unpleasantness regardless of intensity level. CONCLUSION: Cognitively healthy APOE4 carriers at increased risk of late-onset AD demonstrated reduced thermal pain sensitivity but greater unpleasantness to thermal pain stimuli relative to individuals at lower risk of late-onset AD. These results suggest that altered evoked pain perception could potentially be used as a phenotypic biomarker of late-onset AD risk prior to disease onset. Additional studies of this issue may be warranted.
Keywords: Adult; Aged; Aged, 80 and over; Alleles; Alzheimer Disease; Apolipoprotein E4; Biomarkers; Cross-Sectional Studies; Female; Genetic Association Studies; Hot Temperature; Humans; Male; Middle Aged; Pain Perception; Phenotype; Risk Factors

COVID-19: Association Between Increase of Behavioral and Psychological Symptoms of Dementia During Lockdown and Caregivers' Poor Mental Health. - Pongan, Elodie; Dorey, Jean-Michel; Borg, Céline; Getenet, Jean Claude; Bachelet, Romain; Lourioux, Charles; Laurent, Bernard; Rey, Romain; Rouch, Isabelle (J Alzheimers Dis, 2021)
BACKGROUND: From March 2020, the support and care systems for caregivers and people with dementia (PWD) were suspended or dramatically changed due to the lockdown during the world pandemic of COVID-19. Thus, these changes in living conditions have had deleterious consequences on the behavior of PWD and subsequently on their caregivers' mental health, the two being linked. OBJECTIVE: Our study aimed to examine changes in behavior among PWD and to look for associations between the evolution of behavioral and psychological symptoms of dementia (BPSD) and caregivers' mental health in the context of COVID-19. METHODS: The study was conducted among caregivers of PWD living at home in France. Caregivers were interviewed via an anonymous cross-sectional online survey during the first lockdown between April 15 and June 15, 2020. RESULTS: Three hundred and eighty-nine caregivers accompanying a relative living at home participated in the study; 43.3%of the PWD presented a worsening of BPSD during the lockdown. With multivariate logistic regressions, a significant association was observed between "more BPSD" and burden, anxiety and depression, between "BPSD equivalent" and anxiety and depression, and between "emerging BPSD" and only depression. CONCLUSION: The lockdown seems to have an impact on behavioral disorders in PWD and these disorders are associated with poorer mental health of caregivers. Our findings suggest attention should be given to caregivers of PWD who have BPSD before lockdown and the need for continued consultations and professional help in case of new lockdowns.
Keywords: Aged; Aged, 80 and over; Caregivers; Communicable Disease Control; COVID-19; Cross-Sectional Studies; Dementia; Female; France; Humans; Male; Mental Disorders; Mental Health; Middle Aged; Surveys and Questionnaires

COVID-19 Crisis Effects on Caregiver Distress in Neurocognitive Disorder. - Alexopoulos, Panagiotis; Soldatos, Rigas; Kontogianni, Evangelia; Frouda, Maria; Loanna Aligianni, Souzana; Skondra, Maria; Passa, Maria; Konstantopoulou, Georgia; Stamouli, Evangelia; Katirtzoglou, Evgenia; Politis, Anastasios; Economou, Polychronis; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The outbreak of the COVID-19 pandemic seems to have mental health implications for both people with neurocognitive disorder and their caregivers. OBJECTIVE: The study aimed to shed light on relations between caregiver mental reaction to the pandemic and caregiver distress related to neuropsychiatric symptoms, memory impairment progression, and functional impairment of people with neurocognitive disorder during the period of confinement in Greece. METHODS: The study included caregivers of patients with mild (N = 13) and major (N = 54) neurocognitive disorder. The caregiver-based telephone interview was based on items of the neuropsychiatric inventory questionnaire, the AD8 Dementia Screening Instrument, and the Bristol Activities of Daily Living Scale. Regarding the mental impact of the COVID-19 crisis on caregivers, four single questions referring to their worries in the last seven days were posed, in addition to the scales Generalized Anxiety Disorder 7-Item (GAD-7) and the 22-item Impact of Event Scale-revised (IES-R). A stepwise linear regression model was employed for studying the relationship between caregiver distress and demographic and clinical data and caregiver mental reaction to COVID-19 pandemic outbreak. RESULTS: Caregiver distress severity during the confinement period was influenced not only by memory deficits (p = 0.009) and neuropsychiatric symptoms (p < 0.001) of patients, but also by caregiver hyperarousal (p = 0.003) and avoidance symptoms (p = 0.033) and worries directly linked to the COVID-19 crisis (p = 0.022). CONCLUSION: These observations provide further evidence for the urgent need for support of caregivers of patients with neurocognitive disorder during the COVID-19 pandemic.
Keywords: Aged; Aged, 80 and over; Caregivers; COVID-19; Female; Greece; Humans; Male; Middle Aged; Neurocognitive Disorders; Quarantine

Current and Future Prevalence Estimates of Mild Cognitive Impairment, Dementia, and Its Subtypes in a Population-Based Sample of People 70 Years and Older in Norway: The HUNT Study. - GjØra, Linda; Strand, Bjørn Heine; Bergh, Sverre; Borza, Tom; Brækhus, Anne; Engedal, Knut; Johannessen, Aud; Kvello-Alme, Marte; Krokstad, Steinar; Livingston, Gill; Matthews, Fiona E; Myrstad, Christian; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Having accurate, up-to-date information on the epidemiology of mild cognitive impairment (MCI) and dementia is imperative. OBJECTIVE: To determine the prevalence of MCI and dementia in Norway using data from a large population-based study. METHODS: All people 70 + years of age, n = 19,403, in the fourth wave of the Trøndelag Health Study (HUNT4) were invited to participate in the study HUNT4 70 + . Trained health personnel assessed participants using cognitive tests at a field station, at homes, or at their nursing home. Interviewers also completed a structured carer questionnaire in regard to participants suspected of having dementia. Clinical experts made diagnoses according to DSM-5 criteria. We calculated prevalence weighing the data to ensure population representativeness. RESULTS: A total of 9,930 (51.2%) of the possible 19,403 people participated, and 9,663 of these had sufficient information for analysis. Standardized prevalence of dementia and MCI was 14.6% (95% confidence interval (CI) 13.9-15.4) and 35.3% (95% CI 34.3-36.4), respectively. Dementia was more prevalent in women and MCI more prevalent in men. The most prevalent dementia subtype was Alzheimer's disease (57%). By adding data collected from a study of persons < 70 years in the same region, we estimate that there are 101,118 persons with dementia in Norway in 2020, and this is projected to increase to 236,789 and 380,134 in 2050 and 2100, respectively. CONCLUSION: We found a higher prevalence of dementia and MCI than most previous studies. The present prevalence and future projections are vital for preparing for future challenges to the healthcare system and the entire society.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Dementia; Female; Forecasting; Humans; Male; Mental Status and Dementia Tests; Neuropsychological Tests; Norway; Prevalence; Sex Factors; Surveys and Questionnaires

Dementia and COVID-19, a Bidirectional Liaison: Risk Factors, Biomarkers, and Optimal Health Care. - Toniolo, Sofia; Scarioni, Marta; Di Lorenzo, Francesco; Hort, Jakub; Georges, Jean; Tomic, Svetlana; Nobili, Flavio; Frederiksen, Kristian Steen (J Alzheimers Dis, 2021)
Cognitive impairment following SARS-CoV-2 infection is being increasingly recognized as an acute and possibly also long-term sequela of the disease. Direct viral entry as well as systemic mechanisms such as cytokine storm are thought to contribute to neuroinflammation in these patients. Biomarkers of COVID-19-induced cognitive impairment are currently lacking, but there is some limited evidence that SARS-CoV-2 could preferentially target the frontal lobes, as suggested by behavioral and dysexecutive symptoms, fronto-temporal hypoperfusion on MRI, EEG slowing in frontal regions, and frontal hypometabolism on 18F-FDG-PET. Possible confounders include cognitive impairment due to hypoxia and mechanical ventilation and post-traumatic stress disorder. Conversely, patients already suffering from dementia, as well as their caregivers, have been greatly impacted by the disruption of their care caused by COVID-19. Patients with dementia have experienced worsening of cognitive, behavioral, and psychological symptoms, and the rate of COVID-19-related deaths is disproportionately high among cognitively impaired people. Multiple factors, such as difficulties in remembering and executing safeguarding procedures, age, comorbidities, residing in care homes, and poorer access to hospital standard of care play a role in the increased morbidity and mortality. Non-pharmacological interventions and new technologies have shown a potential for the management of patients with dementia, and for the support of their caregivers.
Keywords: Alzheimer Disease; Biomarkers; Brain; Cognitive Dysfunction; Comorbidity; COVID-19; Humans; Neuroimaging; Neuroimmunomodulation; Patient Care; SARS-CoV-2

Dementia-Friendly "Design": Impact on COVID-19 Death Rates in Long-Term Care Facilities Around the World. - Olson, Nancy L; Albensi, Benedict C (J Alzheimers Dis, 2021)
Persons with dementia (PWD) make up a large portion of the long-term care (LTC) population the world over. Before a global pandemic swept the world, governments and healthcare providers struggled with how to best care for this unique population. One of the greatest challenges is a PWD's tendency to "walk with purpose" and exhibit unsafe wayfinding and elopement, which places them at risk of falls and injury. Past solutions included increased use of restraints and pharmacological interventions, but these have fallen out of favor over the years and are not optimal. These challenges put enormous strain on staff and caregivers, who are often poorly trained in dementia care, underpaid, overworked, and overstressed. PWD are impacted by these stresses, and unmet needs in LTC places an even greater stress on them and increases their risks of morbidity and mortality. The physical design of their environments contributes to the problem. Old, institutionalized buildings have poor lighting, poor ventilation, long dead-end hallways, poor visual cues, lack of home-like décor, shared bedrooms and bathrooms, and are often dense and overcrowded. These design elements contribute to the four 'A's' of dementia: apathy, anxiety, agitation, and aggression, and they also contributed to the rapid spread of COVID-19 in these facilities the world over. In this review, we present current "dementia friendly" design models in the home, community, and LTC, and argue how they could have saved lives during the pandemic and reduced the stresses on both the dementia resident and the caregiver/staff.
Keywords: COVID-19; Dementia; Environment Design; Health Services Needs and Demand; Humans; Long-Term Care; Pandemics; Quality of Life

Different Inflammatory Signatures in Alzheimer's Disease and Frontotemporal Dementia Cerebrospinal Fluid. - Boström, Gustaf; Freyhult, Eva; Virhammar, Johan; Alcolea, Daniel; Tumani, Hayrettin; Otto, Markus; Brundin, Rose-Marie; Kilander, Lena; Löwenmark, Malin; Giedraitis, Vilmantas; Lleo, Alberto; von Arnim, Christine A F; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Neuroinflammatory processes are common in neurodegenerative diseases such as Alzheimer's disease (AD) and frontotemporal dementia (FTD), but current knowledge is limited as to whether cerebrospinal fluid (CSF) levels of neuroinflammatory proteins are altered in these diseases. OBJECTIVE: To identify and characterize neuroinflammatory signatures in CSF from patients with AD, mild cognitive impairment (MCI), and FTD. METHODS: We used proximity extension assay and ANOVA to measure and compare levels of 92 inflammatory proteins in CSF from 42 patients with AD, 29 with MCI due to AD (MCI/AD), 22 with stable MCI, 42 with FTD, and 49 control subjects, correcting for age, gender, collection unit, and multiple testing. RESULTS: Levels of matrix metalloproteinase-10 (MMP-10) were increased in AD, MCI/AD, and FTD compared with controls (AD: fold change [FC] = 1.32, 95% confidence interval [CI] 1.14-1.53, q = 0.018; MCI/AD: FC = 1.53, 95% CI 1.20-1.94, q = 0.045; and FTD: FC = 1.42, 95% CI 1.10-1.83, q = 0.020). MMP-10 and eleven additional proteins were increased in MCI/AD, compared with MCI (q < 0.05). In FTD, 36 proteins were decreased, while none was decreased in AD or MCI/AD, compared with controls (q < 0.05). CONCLUSION: In this cross-sectional multi-center study, we found distinct patterns of CSF inflammatory marker levels in FTD and in both early and established AD, suggesting differing neuroinflammatory processes in the two disorders.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Cross-Sectional Studies; Female; Frontotemporal Dementia; Humans; Inflammation; Male; Middle Aged; Peptide Fragments; tau Proteins

Economic Burden of Alzheimer's Disease Dementia in Japan. - Ikeda, Shunya; Mimura, Masaru; Ikeda, Manabu; Wada-Isoe, Kenji; Azuma, Mie; Inoue, Sachie; Tomita, Kiyoyuki (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease dementia (ADD) is the leading cause of long-term care in Japan. OBJECTIVE: This study estimates the annual healthcare and long-term care costs in fiscal year 2018 for adults over 65 years of age with ADD in Japan and the informal care costs and productivity loss for their families. METHODS: Healthcare and long-term care costs for ADD were estimated according to the disease severity classified by the clinical dementia rating (CDR) score, using reports from a literature review. For the costs of time spent on caregiving activities, productivity loss for ADD family caregivers aged 20-69 and informal care costs for all ADD family caregivers were estimated. RESULTS: The total healthcare cost of ADD was JPY 1,073 billion, of which 86% (JPY 923 billion) was attributed to healthcare costs other than ADD drug costs (JPY 151 billion). The healthcare costs other than ADD drug costs by severity were less than JPY 200 billion for CDR 0.5, CDR 1, and CDR 2, respectively, but increased to JPY 447 billion (48%) for CDR 3. The public long-term care costs were estimated to be JPY 4,783 billion, which increased according to the severity. Total productivity loss for ADD family caregivers aged 20-69 was JPY 1,547 billion and the informal care cost for all ADD family caregivers was JPY 6,772 billion. CONCLUSION: ADD costs have a significant impact on public-funded healthcare, long-term care systems, and families in Japan. To minimize the economic burden of ADD, prolonging healthy life expectancy is the key factor to address.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Caregivers; Female; Health Care Costs; Humans; Japan; Long-Term Care; Male

Effects of COVID-19 Home Confinement on Mental Health in Individuals with Increased Risk of Alzheimer's Disease. - Soldevila-Domenech, Natalia; Forcano, Laura; Boronat, Anna; Lorenzo, Thais; Piera, Iris; Puig-Pijoan, Albert; Mateus, Julian; González de Echevarri Gómez, José María; Knezevic, Iva; Soteras, Anna; Fauria, Karine; Pizarro, Nieves; et al. (J Alzheimers Dis, 2021)
We explored the impact of the Spanish COVID-19 strict home confinement on mental health and cognition in non-infected subjects (N = 16, 60-80 years) diagnosed with subjective cognitive decline and APOEɛ3/ɛ4 carriers. Mental health was monitored for 2 months on a daily, weekly, or monthly basis, and compared to pre-confinement values. Emotional distress, anxiety, and depression scores increased to pathological threshold values during and after confinement. Those with lower mood during confinement experienced a decline in their mood after confinement. Cognition did not change. These preliminary results suggest that mental health consequences of corona measures in preclinical stages of Alzheimer's disease should be further evaluated.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Anxiety Disorders; Apolipoprotein E3; Apolipoprotein E4; Cognition Disorders; Cognitive Dysfunction; COVID-19; Depressive Disorder; Female; Humans; Male; Mental Health; Middle Aged; Psychological Distress; Quarantine; Risk; Spain

Egocentric and Allocentric Spatial Memory in Mild Cognitive Impairment with Real-World and Virtual Navigation Tasks: A Systematic Review. - Tuena, Cosimo; Mancuso, Valentina; Stramba-Badiale, Chiara; Pedroli, Elisa; Stramba-Badiale, Marco; Riva, Giuseppe; Repetto, Claudia (J Alzheimers Dis, 2021)
BACKGROUND: Spatial navigation is the ability to estimate one's position on the basis of environmental and self-motion cues. Spatial memory is the cognitive substrate underlying navigation and relies on two different reference frames: egocentric and allocentric. These spatial frames are prone to decline with aging and impairment is even more pronounced in Alzheimer's disease (AD) or in mild cognitive impairment (MCI). OBJECTIVE: To conduct a systematic review of experimental studies investigating which MCI population and tasks are used to evaluate spatial memory and how allocentric and egocentric deficits are impaired in MCI after navigation. METHODS: PRISMA and PICO guidelines were applied to carry out the systematic search. Down and Black checklist was used to assess methodological quality. RESULTS: Our results showed that amnestic MCI and AD pathology are the most investigated typologies; both egocentric and allocentric memory are impaired in MCI individuals, and MCI due to AD biomarkers has specific encoding and retrieval impairments; secondly, spatial navigation is principally investigated with the hidden goal task (virtual and real-world version), and among studies involving virtual reality, the privileged setting consists of non-immersive technology; thirdly, despite subtle differences, real-world and virtual versions showed good overlap for the assessment of MCI spatial memory. CONCLUSION: Considering that MCI is a subclinical entity with potential risk for conversion to dementia, investigating spatial memory deficits with navigation tasks might be crucial to make accurate diagnosis and rehabilitation.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Humans; Spatial Memory; Spatial Navigation

Elevated Norepinephrine Metabolism Gauges Alzheimer's Disease-Related Pathology and Memory Decline. - Riphagen, Joost M; van Egroo, Maxime; Jacobs, Heidi I L (J Alzheimers Dis, 2021)
The noradrenergic (NE) locus coeruleus (LC) is vulnerable to hyperphosphorylated tau, and dysregulated NE-metabolism is linked to greater tau and disease progression. We investigated whether elevated NE-metabolism alone predicts memory decline or whether concomitant presence of tau and amyloid-β is required. Among 114 memory clinic participants, time trends (max. six years) showed dose-response declines in learning across groups with elevated NE-metabolite 3-methoxy-4-hydroxyphenylethyleneglycol (MHPG) with no, one, or two Alzheimer's disease biomarkers; and no decline in the low MHPG group. Elevated MHPG is required and sufficient to detect learning declines, supporting a pathophysiologic model including the LC-NE system contributing to initial Alzheimer's disease-related processes.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Cohort Studies; Disease Progression; Female; Humans; Learning; Locus Coeruleus; Male; Memory Disorders; Methoxyhydroxyphenylglycol; Middle Aged; Neuropsychological Tests; Norepinephrine; Predictive Value of Tests; tau Proteins

Is the Frontal Lobe the Primary Target of SARS-CoV-2? - Toniolo, Sofia; Di Lorenzo, Francesco; Scarioni, Marta; Frederiksen, Kristian Steen; Nobili, Flavio (J Alzheimers Dis, 2021)
Acute delirium and other neuropsychiatric symptoms have frequently been reported in COVID-19 patients and are variably referred to as acute encephalopathy, COVID-19 encephalopathy, SARS-CoV-2 encephalitis, or steroid-responsive encephalitis. COVID-19 specific biomarkers of cognitive impairment are currently lacking, but there is some evidence that SARS-CoV-2 could preferentially and directly target the frontal lobes, as suggested by behavioral and dysexecutive symptoms, fronto-temporal hypoperfusion on MRI, EEG slowing in frontal regions, and frontal hypometabolism on 18F-FDG-PET imaging. We suggest that an inflammatory parainfectious process targeting preferentially the frontal lobes (and/or frontal networks) could be the underlying cause of these shared clinical, neurophysiological, and imaging findings in COVID-19 patients. We explore the biological mechanisms and the clinical biomarkers that might underlie such disruption of frontal circuits and highlight the need of standardized diagnostic procedures to be applied when investigating patients with these clinical findings. We also suggest the use of a unique label, to increase comparability across studies.
Keywords: Acute Febrile Encephalopathy; Biomarkers; COVID-19; Delirium; Electroencephalography; Frontal Lobe; Humans; Magnetic Resonance Imaging; Nerve Net; SARS-CoV-2; Virulence

Gut Microbiome Features of Chinese Patients Newly Diagnosed with Alzheimer's Disease or Mild Cognitive Impairment. - Guo, Mingyan; Peng, Jun; Huang, Xiaoyan; Xiao, Lingjun; Huang, Fenyan; Zuo, Zhiyi (J Alzheimers Dis, 2021)
BACKGROUND: Patients with Alzheimer's disease (AD) have gut microbiome alterations compared with healthy controls. However, previous studies often assess AD patients who have been on medications or other interventions for the disease. Also, simultaneous determination of gut microbiome in patients with mild cognitive impairment (MCI) or AD in a study is rare. OBJECTIVE: To determine whether there was a gut microbiome alteration in patients newly diagnosed with AD or MCI and whether the degree of gut microbiome alteration was more severe in patients with AD than patients with MCI. METHODS: Fecal samples of 18 patients with AD, 20 patients with MCI, and 18 age-matched healthy controls were collected in the morning for 16S ribosomal RNA sequencing. No patient had medications or interventions for AD or MCI before the samples were collected. RESULTS: Although there was no difference in the microbial α-diversity among the three groups, patients with AD or MCI had increased β-diversity compared with healthy controls. Patients with AD had decreased Bacteroides, Lachnospira, and Ruminiclostridium_9 and increased Prevotella at the genus level compared with healthy controls. The changing direction of these genera in patients with MCI was the same as patients with AD. However, Lachnospira was the only genus whose abundance in patients with MCI was statistically significantly lower than healthy controls. Bacteroides, Lachnospira, and Ruminiclostridium_9 were positively associated with better cognitive functions whereas Prevotella was on the contrary when subjects of all three groups were considered. The negative correlation of Prevotella with cognitive functions remained among patients with MCI. CONCLUSION: Patients newly diagnosed with AD or MCI have gut dysbiosis that includes the decrease of potentially protective microbiome, such as Bacteroides, and the increase of microbiome that can promote inflammation, such as Prevotella. Our results support a novel idea that the degree of gut dysbiosis is worsened with the disease stage from MCI to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Asians; Biodiversity; China; Cognition; Cognitive Dysfunction; Disease Progression; Feces; Female; Gastrointestinal Microbiome; Humans; Male; Middle Aged; RNA, Ribosomal, 16S

Gut Microbiota Alterations and Cognitive Impairment Are Sexually Dissociated in a Transgenic Mice Model of Alzheimer's Disease. - Cuervo-Zanatta, Daniel; Garcia-Mena, Jaime; Perez-Cruz, Claudia (J Alzheimers Dis, 2021)
BACKGROUND: Normal aging is accompanied by cognitive deficiencies, affecting women and men equally. Aging is the main risk factor for Alzheimer's disease (AD), with women having a higher risk. The higher prevalence of AD in women is associated with the abrupt hormonal decline seen after menopause. However, other factors may be involved in this sex-related cognitive decline. Alterations in gut microbiota (GM) and its bioproducts have been reported in AD subjects and transgenic (Tg) mice, having a direct impact on brain amyloid-β pathology in male (M), but not in female (F) mice. OBJECTIVE: The aim of this work was to determine GM composition and cognitive dysfunction in M and F wildtype (WT) and Tg mice, in a sex/genotype segregation design. METHODS: Anxiety, short term working-memory, spatial learning, and long-term spatial memory were evaluated in 6-month-old WT and Tg male mice. Fecal short chain fatty acids were determined by chromatography, and DNA sequencing and bioinformatic analyses were used to determine GM differences. RESULTS: We observed sex-dependent differences in cognitive skills in WT mice, favoring F mice. However, the cognitive advantage of females was lost in Tg mice. GM composition showed few sex-related differences in WT mice. Contrary, Tg-M mice presented a more severe dysbiosis than Tg-F mice. A decreased abundance of Ruminococcaceae was associated with cognitive deficits in Tg-F mice, while butyrate levels were positively associated with better working- and object recognition-memory in WT-F mice. CONCLUSION: This report describes a sex-dependent association between GM alterations and cognitive impairment in a mice model of AD.
Keywords: Alzheimer Disease; Animals; Cognitive Dysfunction; Female; Gastrointestinal Microbiome; Humans; Male; Mice; Mice, Transgenic; Sex Characteristics; Spatial Memory

How Do Persons with Young and Late Onset Dementia Die? - Roβmeier, Carola; Hartmann, Julia; Riedl, Lina; Dorn, Bianca; Fischer, Julia; Hartmann, Florentine; Egert-Schwender, Silvia; Kehl, Victoria; Schneider-Schelte, Helga; Jox, Ralf J; Dinkel, Andreas; Diehl-Schmid, Janine (J Alzheimers Dis, 2021)
BACKGROUND: End of life symptoms and symptom management as well as the quality of dying (QoD) of persons with advanced dementia (PWAD) have not yet been systematically studied in Germany. OBJECTIVE: 1) To investigate symptoms, treatment and care at the end of life, advance care planning, and circumstances of death of recently deceased PWAD; 2) To determine whether there are differences between young and late onset dementia (YOD and LOD). METHODS: The study was performed in the context of the project EPYLOGE (IssuEs in Palliative care for persons in advanced and terminal stages of Young-onset and Late-Onset dementia in Germany). Closest relatives of recently deceased patients with advanced YOD (N = 46) and LOD (N = 54) living at home or in long term care were interviewed. RESULTS: Circumstances of death, symptoms, and treatment appeared to be similar between YOD and LOD, except that persons with LOD had significantly more somatic comorbidities and were admitted to hospital in the last three months of life more often than persons with LOD. At end of life, 60% of PWAD appeared to be "at peace". Difficulty swallowing, gurgling, shortness of breath, and discomfort were observed most frequently. Large interindividual differences in suffering and QoD were present. Determinants of QoD were not identified. CONCLUSION: Our findings suggest that low QoD was caused by inadequate recognition and/or insufficient treatment of burdensome physical and emotional symptoms. PWADs' needs should be assessed regularly, and strategies focusing on treatment and implementing support for both the patient and caregiver must be established.
Keywords: Advance Care Planning; Age of Onset; Aged; Aged, 80 and over; Caregivers; Dementia; Female; Humans; Long-Term Care; Male; Palliative Care; Quality of Life

The Impact of a Global Pandemic on People Living with Dementia and Their Care Partners: Analysis of 417 Lived Experience Reports. - Tam, Mallorie T; Dosso, Jill A; Robillard, Julie M (J Alzheimers Dis, 2021)
BACKGROUND: The COVID-19 pandemic is impacting the physical and emotional health of older adults living with dementia and their care partners. OBJECTIVE: Using a patient-centered approach, we explored the experiences and needs of people living with dementia and their care partners during the COVID-19 pandemic as part of an ongoing evaluation of dementia support services in British Columbia, Canada. METHODS: A survey instrument was developed around the priorities identified in the context of the COVID-19 and Dementia Task Force convened by the Alzheimer Society of Canada. RESULTS: A total of 417 surveys were analyzed. Overall, respondents were able to access information that was helpful for maintaining their own health and managing a period of social distancing. Care partners reported a number of serious concerns, including the inability to visit the person that they care for in long-term or palliative care. Participants also reported that the pandemic increased their levels of stress overall and that they felt lonelier and more isolated than they did before the pandemic. The use of technology was reported as a way to connect socially with their loved ones, with the majority of participants connecting with others at least twice per week. CONCLUSION: Looking at the complex effects of a global pandemic through the experiences of people living with dementia and their care partners is vital to inform healthcare priorities to restore their quality of life and health and better prepare for the future.
Keywords: Adaptation, Psychological; Aged; Alzheimer Disease; British Columbia; Caregivers; COVID-19; Disabled Persons; Female; Humans; Loneliness; Male; Needs Assessment; Psychosocial Support Systems; Social Isolation; Social Support; Stress, Psychological; Surveys and Questionnaires

Impact of Social Isolation on People with Dementia and Their Family Caregivers. - Azevedo, Lílian Viana Dos Santos; Calandri, Ismael Luis; Slachevsky, Andrea; Graviotto, Héctor Gastón; Vieira, Maria Carolina Santos; Andrade, Caíssa Bezerra de; Rossetti, Adriana Peredo; Generoso, Alana Barroso; Carmona, Karoline Carvalho; Pinto, Ludmilla Aparecida Cardoso; Sorbara, Marcos; Pinto, Alejandra; et al. (J Alzheimers Dis, 2021)
BACKGROUND: People with dementia and their family caregivers may face a great burden through social isolation due to the COVID-19 pandemic, which can be manifested as various behavioral and clinical symptoms. OBJECTIVE: To investigate the impacts of social isolation due to the COVID-19 pandemic on individuals with dementia and their family caregivers. METHODS: Two semi-structured questionnaires were applied via telephone to family caregivers of people diagnosed with dementia in three cities in Argentina, Brazil, and Chile, in order to assess clinical and behavioral changes in people with dementia and in their caregivers. RESULTS: In general, 321 interviews were conducted. A significant decline in memory function has been reported among 53.0%of people with dementia. In addition, 31.2%of individuals with dementia felt sadder and 37.4%had increased anxiety symptoms. These symptoms of anxiety were greater in individuals with mild to moderate dementia, while symptoms of agitation were greater in individuals with severe dementia. Moreover, compulsive-obsessive behavior, hallucinations, increased forgetfulness, altered appetite, and increased difficulty in activities of daily living were reported more frequently among individuals with moderate to severe dementia. Caregivers reported feeling more tired and overwhelmed during this period and these symptoms were also influenced by the severity of dementia. CONCLUSION: Social isolation during the COVID-19 pandemic triggered a series of negative behavioral repercussions, both for people with dementia and for their family caregivers in these three South American countries.
Keywords: Activities of Daily Living; Adult; Aged; Aged, 80 and over; Argentina; Brazil; Caregivers; Chile; COVID-19; Dementia; Female; Humans; Male; Middle Aged; Pandemics; Physical Distancing; Social Isolation; Surveys and Questionnaires

Implementing Delirium Prevention in the Era of COVID-19. - Radhakrishnan, Nila S; Mufti, Mariam; Ortiz, Daniel; Maye, Suzanne T; Melara, Jennifer; Lim, Duke; Rosenberg, Eric I; Price, Catherine C (J Alzheimers Dis, 2021)
Patients admitted with COVID-19 can develop delirium due to predisposing factors, isolation, and the illness itself. Standard delirium prevention methods focus on interaction and stimulation. It can be challenging to deliver these methods of care in COVID settings where it is necessary to increase patient isolation. This paper presents a typical clinical vignette of representative patients in a tertiary care hospital and how a medical team modified an evidence-based delirium prevention model to deliver high-quality care to COVID-19 patients. The implemented model focuses on four areas of delirium-prevention: Mobility, Sleep, Cognitive Stimulation, and Nutrition. Future studies will be needed to track quantitative outcome measures.
Keywords: Aged; Alzheimer Disease; COVID-19; Delirium; Humans; Male

Improving the Diagnosis of the Frontal Variant of Alzheimer's Disease with the DAPHNE Scale. - Lehingue, Elsa; Gueniat, Julien; Jourdaa, Sandra; Hardouin, Jean BenoÎt; Pallardy, Amandine; Courtemanche, Hélène; Rocher, Laetitia; Etcharry-Bouyx, Frédérique; Auriacombe, Sophie; Mollion, Hélène; Formaglio, Maıté; Rouaud, Olivier; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The frontal variant of Alzheimer's disease (fAD) is poorly understood and poorly defined. The diagnosis remains challenging. The main differential diagnosis is the behavioral variant of frontotemporal degeneration (bvFTD). For fAD, there is some dissociation between the clinical frontal presentation and imaging and neuropathological studies, which do not always find a specific involvement of the frontal lobes. DAPHNE is a behavioral scale, which demonstrated excellent performance to distinguish between bvFTD and AD. OBJECTIVE: The aim of the present study was to assess the reliability of this new tool to improve the clinical diagnosis of fAD. METHODS: Twenty fAD patients and their caregivers were prospectively included and were compared with 36 bvFTD and 22 AD patients. RESULTS: The three main behavioral disorders in the fAD patients were apathy, loss of empathy, and disinhibition. Three disorders were discriminant because they were less frequent and less severe in the fAD patients than in the bvFTD patients, namely hyperorality, neglect, and perseverations. This specific pattern of behavioral disorders was corroborated by SPECT or 18FDG PET-CT scan that showed that patients with fAD could have a medial frontal hypoperfusion, whereas in bvFTD patients the orbitofrontal cortex was the main involved region, with more diffuse hypoperfusion. CONCLUSION: We demonstrated that DAPHNE had good sensitivity and good specificity to discriminate between the three groups and in particular between fAD and bvFTD patients. DAPHNE is a quick tool that could help clinicians in memory clinics not only to differentiate bvFTD from typical AD but also from fAD.
Keywords: Aged; Alzheimer Disease; Cohort Studies; Diagnosis, Differential; Female; Frontal Lobe; Frontotemporal Dementia; Humans; Male; Middle Aged; Neuropsychological Tests

Incremental Healthcare Utilization and Cost Burden of Comorbid Insomnia in Alzheimer's Disease Patients. - Qureshi, Zaina P; Thiel, Ellen; Nelson, James; Khandker, Rezaul (J Alzheimers Dis, 2021)
BACKGROUND: Insomnia is associated with worsened clinical outcomes among Alzheimer's disease dementia (AD) patients, increased caregiver burden, and healthcare utilization. OBJECTIVE: This study aimed to characterize the incremental healthcare burden of insomnia in AD using real-world data. METHODS: A retrospective observational study was conducted on AD patients selected from the IBM® MarketScan Commercial and Medicare Supplemental Databases. AD patients with claims-based evidence of insomnia were direct matched to a non-insomnia cohort based on demographic factors. Healthcare utilization and associated costs were assessed for a 12-month follow-up period. RESULTS: A total of 3,500 insomnia AD patients and 9,884 non-insomnia AD patients were analyzed. The insomnia cohort had a higher comorbidity burden at baseline (mean score on Charlson Comorbidity Index 2.5 versus 2.2, p < 0.001) and higher proportions of patients with baseline diagnoses for other conditions including depression: 40%, insomnia cohort versus 25%, non-insomnia (p < 0.001). AD patients with insomnia were more likely to have a claim for inpatient hospitalizations (39.8%versus 32.3%), emergency room services (56.4%versus 48.0%), and skilled-nursing services (42.6%versus 31.9%) (all p < 0.05). Mean total annual healthcare costs during the 12-month follow-up period were significantly higher among AD patients with insomnia as compared to those without. (Mean costs: $37,356 versus $27,990, p < 0.001). CONCLUSION: AD patients with comorbid insomnia are more likely to use higher-cost healthcare services such as inpatient hospitalization, and skilled nursing, and have higher total healthcare costs. This real-world analysis provides evidence that AD disease management should consider proper treatment of comorbid insomnia due to the incremental burden and cost implications.
Keywords: Aged, 80 and over; Alzheimer Disease; Comorbidity; Databases, Factual; Female; Health Care Costs; Humans; Male; Medicare; Patient Acceptance of Health Care; Retrospective Studies; Sleep Initiation and Maintenance Disorders; United States

Life Course Air Pollution Exposure and Cognitive Decline: Modelled Historical Air Pollution Data and the Lothian Birth Cohort 1936. - Russ, Tom C; Cherrie, Mark P C; Dibben, Chris; Tomlinson, Sam; Reis, Stefan; Dragosits, Ulrike; Vieno, Massimo; Beck, Rachel; Carnell, Ed; Shortt, Niamh K; Muniz-Terrera, Graciela; Redmond, Paul; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Air pollution has been consistently linked with dementia and cognitive decline. However, it is unclear whether risk is accumulated through long-term exposure or whether there are sensitive/critical periods. A key barrier to clarifying this relationship is the dearth of historical air pollution data. OBJECTIVE: To demonstrate the feasibility of modelling historical air pollution data and using them in epidemiologicalmodels. METHODS: Using the EMEP4UK atmospheric chemistry transport model, we modelled historical fine particulate matter (PM2.5) concentrations for the years 1935, 1950, 1970, 1980, and 1990 and combined these with contemporary modelled data from 2001 to estimate life course exposure in 572 participants in the Lothian Birth Cohort 1936 with lifetime residential history recorded. Linear regression and latent growth models were constructed using cognitive ability (IQ) measured by the Moray House Test at the ages of 11, 70, 76, and 79 years to explore the effects of historical air pollution exposure. Covariates included sex, IQ at age 11 years, social class, and smoking. RESULTS: Higher air pollution modelled for 1935 (when participants would have been in utero) was associated with worse change in IQ from age 11-70 years (β = -0.006, SE = 0.002, p = 0.03) but not cognitive trajectories from age 70-79 years (p > 0.05). There was no support for other critical/sensitive periods of exposure or an accumulation of risk (all p > 0.05). CONCLUSION: The life course paradigm is essential in understanding cognitive decline and this is the first study to examine life course air pollution exposure in relation to cognitive health.
Keywords: Adolescent; Adult; Aged; Air Pollution; Child; Cognitive Dysfunction; Environmental Exposure; Female; History, 20th Century; Humans; Linear Models; Male; Middle Aged; Particulate Matter; Scotland; Young Adult

Low Doses of Ionizing Radiation as a Treatment for Alzheimer's Disease: A Pilot Study. - Cuttler, Jerry M; Abdellah, Eslam; Goldberg, Yael; Al-Shamaa, Sarmad; Symons, Sean P; Black, Sandra E; Freedman, Morris (J Alzheimers Dis, 2021)
BACKGROUND: In 2015, a patient in hospice with Alzheimer's disease (AD) was treated with ionizing radiation to her brain using repeated CT scans. Improvement in cognition, speech, movement, and appetite was observed. These improvements were so momentous that she was discharged from the hospice to a long-term care home. Based on this case, we conducted a pilot clinical trial to examine the effect of low-dose ionizing radiation (LDIR) in severe AD. OBJECTIVE: To determine whether the previously reported benefits of LDIR in a single case with AD could be observed again in other cases with AD when the same treatments are given. METHODS: In this single-arm study, four patients were treated with three consecutive treatments of LDIR, each spaced two weeks apart. Qualitative changes in communication and behavior with close relatives were observed and recorded. Quantitative measures of cognition and behavior were administered pre and post LDIR treatments. RESULTS: Minor improvements on quantitative measures were noted in three of the four patients following treatment. However, the qualitative observations of cognition and behavior suggested remarkable improvements within days post-treatment, including greater overall alertness. One patient showed no change. CONCLUSION: LDIR may be a promising, albeit controversial therapy for AD. Trials of patients with less severe AD, double-blind and placebo-controlled, should be carried out to determine the benefits of LDIR. Quantitative measures are needed that are sensitive to the remarkable changes induced by LDIR, such as biological markers of oxidative stress that are associated with AD.
Keywords: Aged, 80 and over; Alzheimer Disease; Cranial Irradiation; Female; Humans; Male; Pilot Projects; Radiation, Ionizing

Memory-Related Frontal Brainwaves Predict Transition to Mild Cognitive Impairment in Healthy Older Individuals Five Years Before Diagnosis. - Jiang, Yang; Li, Juan; Schmitt, Frederick A; Jicha, Gregory A; Munro, Nancy B; Zhao, Xiaopeng; Smith, Charles D; Kryscio, Richard J; Abner, Erin L (J Alzheimers Dis, 2021)
BACKGROUND: Early prognosis of high-risk older adults for amnestic mild cognitive impairment (aMCI), using noninvasive and sensitive neuromarkers, is key for early prevention of Alzheimer's disease. We have developed individualized measures in electrophysiological brain signals during working memory that distinguish patients with aMCI from age-matched cognitively intact older individuals. OBJECTIVE: Here we test longitudinally the prognosis of the baseline neuromarkers for aMCI risk. We hypothesized that the older individuals diagnosed with incident aMCI already have aMCI-like brain signatures years before diagnosis. METHODS: Electroencephalogram (EEG) and memory performance were recorded during a working memory task at baseline. The individualized baseline neuromarkers, annual cognitive status, and longitudinal changes in memory recall scores up to 10 years were analyzed. RESULTS: Seven of the 19 cognitively normal older adults were diagnosed with incident aMCI for a median 5.2 years later. The seven converters' frontal brainwaves were statistically identical to those patients with diagnosed aMCI (n = 14) at baseline. Importantly, the converters' baseline memory-related brainwaves (reduced mean frontal responses to memory targets) were significantly different from those who remained normal. Furthermore, differentiation pattern of left frontal memory-related responses (targets versus nontargets) was associated with an increased risk hazard of aMCI (HR = 1.47, 95% CI 1.03, 2.08). CONCLUSION: The memory-related neuromarkers detect MCI-like brain signatures about five years before diagnosis. The individualized frontal neuromarkers index increased MCI risk at baseline. These noninvasive neuromarkers during our Bluegrass memory task have great potential to be used repeatedly for individualized prognosis of MCI risk and progression before clinical diagnosis.
Keywords: Aged; Brain Waves; Cognition; Cognitive Dysfunction; Electroencephalography; Female; Humans; Longitudinal Studies; Male; Memory, Short-Term; Neuropsychological Tests; Prodromal Symptoms

Mild Behavioral Impairment and Subjective Cognitive Decline Predict Cognitive and Functional Decline. - Ismail, Zahinoor; McGirr, Alexander; Gill, Sascha; Hu, Sophie; Forkert, Nils D; Smith, Eric E (J Alzheimers Dis, 2021)
BACKGROUND: Mild behavioral impairment (MBI) and subjective cognitive decline (SCD) are dementia risk states, and potentially represent neurobehavioral and neurocognitive manifestations, respectively, of early stage neurodegeneration. Both MBI and SCD predict incident cognitive decline and dementia, are associated with known dementia biomarkers, and are both represented in the NIA-AA research framework for AD in Stage 2 (preclinical disease). OBJECTIVE: To assess the associations of MBI and SCD, alone and in combination, with incident cognitive and functional decline in a population of older adults. We tested the hypothesis that MBI and SCD confer additive risk for decline. METHODS: Cognitively normal participants were followed up annually at Alzheimer's Disease Centers. Logistic regression assessed the relationship between baseline classification (MBI-SCD-, MBI-SCD+, MBI+SCD-, or MBI+SCD+) and 3-year outcome. RESULTS: Of 2,769 participants (mean age=76), 1,536 were MBI-SCD-, 254 MBI-SCD+, 743 MBI+SCD-, and 236 MBI+SCD+. At 3 years, 349 (12.6%) declined to CDR >0, including 23.1% of the MBI+group, 23.5% of the SCD+group, and 30.9% of the intersection group of both MBI+and SCD+participants. Compared to SCD-MBI-, we observed an ordinal progression in risk (ORs [95% CI]): 3.61 [2.42-5.38] for MBI-SCD+ (16.5% progression), 4.76 [3.57-6.34] for MBI+SCD- (20.7%), and 8.15 [5.71-11.64] for MBI+SCD+(30.9%). CONCLUSION: MBI and SCD together were associated with the greatest risk of decline. These complementary dementia risk syndromes can be used as simple and scalable methods to identify high-risk patients for workup or for clinical trial enrichment.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Disease Progression; Executive Function; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Odds Ratio; Risk Assessment

MIND Diet, Common Brain Pathologies, and Cognition in Community-Dwelling Older Adults. - Dhana, Klodian; James, Bryan D; Agarwal, Puja; Aggarwal, Neelum T; Cherian, Laurel J; Leurgans, Sue E; Barnes, Lisa L; Bennett, David A; Schneider, Julie A (J Alzheimers Dis, 2021)
BACKGROUND: MIND diet, a hybrid of the Mediterranean diet and the Dietary Approaches to Stop Hypertension diet, is associated with a slower cognitive decline and lower risk of Alzheimer's disease (AD) dementia in older adults. OBJECTIVE: We aim to examine whether the association of the MIND diet with cognition is independent of common brain pathologies. METHODS: Utilizing data from the Rush Memory and Aging Project (MAP), a longitudinal clinical-pathologic study, we studied 569 decedents with valid dietary data, cognitive testing proximate to death, and complete autopsy data at the time of these analyses. A series of regression analyses were used to examine associations of the MIND diet, dementia-related brain pathologies, and global cognition proximate to death adjusting for age, sex, education, APOEɛ4, late-life cognitive activities, and total energy intake. RESULTS: A higher MIND diet score was associated with better global cognitive functioning proximate to death (β= 0.119, SE = 0.040, p = 0.003), and neither the strength nor the significance of association changed substantially when AD pathology and other brain pathologies were included in the model. The β-estimate after controlling for global AD pathology was 0.111 (SE = 0.037, p = 0.003). The MIND diet-cognition relationship remained significant when we restricted our analysis to individuals without mild cognitive impairment at the baseline (β= 0.121, SE = 0.042, p = 0.005) or in people diagnosed with postmortem diagnosis of AD based on NIA-Reagan consensus recommendations (β= 0.114, SE = 0.050, p = 0.023). CONCLUSION: MIND diet is associated with better cognitive functioning independently of common brain pathology, suggesting that the MIND diet may contribute to cognitive resilience in the elderly.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Amyloid; Autopsy; Brain; Chicago; Cognition; Diet, Mediterranean; Female; Humans; Independent Living; Longitudinal Studies; Male; Neuropsychological Tests; Surveys and Questionnaires

Modifiable Barriers for Recruitment and Retention of Older Adults Participants from Underrepresented Minorities in Alzheimer's Disease Research. - Indorewalla, Khushnoo K; O'Connor, Maureen K; Budson, Andrew E; Guess DiTerlizzi, Christina; Jackson, Jonathan (J Alzheimers Dis, 2021)
Clinical Alzheimer's disease (AD) trials currently face a critical shortfall of thousands of eligible participants, which inflates the duration and cost of the clinical study as well as threatens the scientific merit of promising clinical interventions. This recruitment crisis is further compounded by the fact that underrepresented and marginalized populations-particularly those identifying as a racial or ethnic minority, those with low socioeconomic status, or living in rural areas-have been historically underrepresented in ongoing AD clinical trials despite overwhelming evidence that such populations are at increased risk for developing dementia. As a result of various recruitment barriers, current AD clinical studies frequently reflect a decreasingly representative segment of the US population, which threatens the overall generalizability of these findings. The current narrative review provides an updated examination and critique of common recruitment barriers and potential solutions, as well as a discussion of theoretical approaches that may address barriers disproportionately experienced by underrepresented communities. AD clinical researchers are encouraged to take purposive action aimed at increasing diversity of enrolled AD clinical trial cohorts by actively identifying and quantifying barriers to research participation-especially recruitment barriers and health disparities that disproportionately prevent underrepresented and marginalized populations from participating in research. Furthermore, researchers are encouraged to closely track which individuals who express interest in AD research ultimately enroll in research studies to examine whether AD research participation is appropriately representative of the intended population for whom these new and novel AD interventions are being designed.
Keywords: Alzheimer Disease; Clinical Trials as Topic; Humans; Minority Groups; Patient Selection

Mortality After Ischemic Stroke in Patients with Alzheimer's Disease Dementia and Other Dementia Disorders. - Zupanic, Eva; von Euler, Mia; Winblad, Bengt; Xu, Hong; Secnik, Juraj; Kramberger, Milica Gregoric; Religa, Dorota; Norrving, Bo; Garcia-Ptacek, Sara (J Alzheimers Dis, 2021)
BACKGROUND: Stroke and dementia are interrelated diseases and risk for both increases with age. Even though stroke incidence and age-standardized death rates have decreased due to prevention of stroke risk factors, increased utilization of reperfusion therapies, and other changes in healthcare, the absolute numbers are increasing due to population growth and aging. OBJECTIVE: To analyze predictors of death after stroke in patients with dementia and investigate possible time and treatment trends. METHODS: A national longitudinal cohort study 2007-2017 using Swedish national registries. We compared 12,629 ischemic stroke events in patients with dementia with matched 57,954 stroke events in non-dementia controls in different aspects of patient care and mortality. Relationship between dementia status and dementia type (Alzheimer's disease and mixed dementia, vascular dementia, other dementias) and death was analyzed using Cox regressions. RESULTS: Differences in receiving intravenous thrombolysis between patients with and without dementia disappeared after the year 2015 (administered to 11.1% dementia versus 12.3% non-dementia patients, p = 0.117). One year after stroke, nearly 50% dementia and 30% non-dementia patients had died. After adjustment for demographics, mobility, nursing home placement, and comorbidity index, dementia was an independent predictor of death compared with non-dementia patients (HR 1.26 [1.23-1.29]). CONCLUSION: Dementia before ischemic stroke is an independent predictor of death. Over time, early and delayed mortality in patients with dementia remained increased, regardless of dementia type. Patients with≤80 years with prior Alzheimer's disease or mixed dementia had higher mortality rates after stroke compared to patients with prior vascular dementia.
Keywords: Aged; Aged, 80 and over; Comorbidity; Dementia; Female; Fibrinolytic Agents; Humans; Incidence; Ischemic Stroke; Male; Registries; Survival Rate; Sweden; Thrombolytic Therapy

Needs of Dementia Family Caregivers in Spain During the COVID-19 Pandemic. - Carcavilla, Nuria; Pozo, Ana Sofía; González, Belén; Moral-Cuesta, Débora; Roldán, José Joaquín; Erice, Victoria; Remírez, Ana de Ganuza (J Alzheimers Dis, 2021)
We explored the experience from caregivers of people with dementia (PwD) during mandatory confinement due to the COVID-19 pandemic in Spain. An online survey, which studied the perceptions of the main problems and consequences experienced during confinement, was answered by 106 family caregivers of PwD. Results showed that family caregivers of PwD experienced psychological problems, like anxiety, mood, sleep, or eating disorders during confinement and felt less supported when they had to handle challenging behaviors or offer meaningful activities. An innovative multi-tiered supportive approach is needed which considers a post-pandemic reality and ensures the continuity of quality care for PwD and their family careers.
Keywords: Adaptation, Psychological; Aged; Aged, 80 and over; Alzheimer Disease; Anxiety Disorders; Caregivers; COVID-19; Feeding and Eating Disorders; Female; Humans; Male; Middle Aged; Mood Disorders; Needs Assessment; Sleep Wake Disorders; Social Isolation; Social Support; Spain

Neuropsychiatric Symptoms in Patients with Dementia Associated with Increased Psychological Distress in Caregivers During the COVID-19 Pandemic. - Borelli, Wyllians Vendramini; Augustin, Marina Coutinho; de Oliveira, Paola Bell Felix; Reggiani, Lorenzo Casagrande; Bandeira-de-Mello, Renato Gorga; Schumacher-Schuh, Artur Francisco; Chaves, Marcia Lorena Fagundes; Castilhos, Raphael Machado (J Alzheimers Dis, 2021)
BACKGROUND: The social isolation imposed by COVID-19 pandemic can have a major impact on the mental health of dementia patients and their caregivers. OBJECTIVE: We aim to evaluate the neurological decline of patients with dementia and the caregivers' burden during the pandemic. METHODS: We performed a cross-sectional study. Caregivers of dementia patients following in the outpatient clinic were included. A structured telephone interview composed of the Neuropsychiatric Inventory Questionnaire (NPI-Q), Zarit Burden Interview (ZBI), Beck Depression (BDI) and Anxiety (BAI) Inventories to address cognitive, behavioral, and functional changes associated with social distancing during the Sars-Cov-2 outbreak. Patients were divided in two groups according to caregivers' report: with perceived Altered Cognition (AC) and Stable Cognition (SC). RESULTS: A total of 58 patients (median age: 57 years [21-87], 58.6%females) and caregivers (median age: 76.5 years [55-89], 79.3%females) were included. Cognitive decline was shown by most patients (53.4%), as well as behavioral symptoms (48.3%), especially apathy/depression (24.1%), and functional decline (34.5%). The AC group (n = 31) presented increased behavioral (67.7%versus 25.9%, p = 0.002) and functional (61.3%versus 3.7%, p < 0.001) changes when compared to the SC group. In the AC group, ZBI, BDI, NPI-Q caregiver distress, and NPI-Q patient's severity of symptoms scores were worse than the SC group (p < 0.005 for all). CONCLUSION: Patients' neuropsychiatric worsening and caregiver burden were frequent during the pandemic. Worsening of cognition was associated with increased caregivers' psychological distress.
Keywords: Adult; Aged; Aged, 80 and over; Brazil; Caregivers; COVID-19; Cross-Sectional Studies; Dementia; Female; Humans; Male; Mental Disorders; Middle Aged; Outpatient Clinics, Hospital; Pandemics; Psychological Distress; Social Isolation; Young Adult

One-Year Aerobic Exercise Reduced Carotid Arterial Stiffness and Increased Cerebral Blood Flow in Amnestic Mild Cognitive Impairment. - Tomoto, Tsubasa; Liu, Jie; Tseng, Benjamin Y; Pasha, Evan P; Cardim, Danilo; Tarumi, Takashi; Hynan, Linda S; Munro Cullum, C; Zhang, Rong (J Alzheimers Dis, 2021)
BACKGROUND: Central arterial stiffness and brain hypoperfusion are emerging risk factors of Alzheimer's disease (AD). Aerobic exercise training (AET) may improve central arterial stiffness and brain perfusion. OBJECTIVE: To investigate the effects of AET on central arterial stiffness and cerebral blood flow (CBF) in patients with amnestic mild cognitive impairment (MCI), a prodromal stage of AD. METHODS: This is a proof-of-concept, randomized controlled trial that assigned 70 amnestic MCI patients into a 12-month program of moderate-to-vigorous AET or stretching-and-toning (SAT) intervention. Carotid β-stiffness index and CBF were measured by color-coded duplex ultrasonography and applanation tonometry. Total CBF was measured as the sum of CBF from both the internal carotid and vertebral arteries, and divided by total brain tissue mass assessed with MRI to obtain normalized CBF (nCBF). Episodic memory and executive function were assessed using standard neuropsychological tests (CVLT-II and D-KEFS). Changes in cardiorespiratory fitness were measured by peak oxygen uptake (VO2peak). RESULTS: Total 48 patients (29 in SAT and 19 in AET) were completed one-year training. AET improved VO2peak, decreased carotid β-stiffness index and CBF pulsatility, and increased nCBF. Changes in VO2peak were associated positively with changes in nCBF (r = 0.388, p = 0.034) and negatively with carotid β-stiffness index (r = -0.418, p = 0.007) and CBF pulsatility (r = -0.400, p = 0.014). Decreases in carotid β-stiffness were associated with increases in cerebral perfusion (r = -0.494, p = 0.003). AET effects on cognitive performance were minimal compared with SAT. CONCLUSION: AET reduced central arterial stiffness and increased CBF which may precede its effects on neurocognitive function in patients with MCI.
Keywords: Aged; Brain; Cardiorespiratory Fitness; Carotid Arteries; Cerebrovascular Circulation; Cognitive Dysfunction; Exercise; Humans; Magnetic Resonance Imaging; Neuropsychological Tests; Vascular Stiffness

Plasma Biomarkers of Alzheimer's Disease in African Americans. - Deniz, Kaancan; Ho, Charlotte C G; Malphrus, Kimberly G; Reddy, Joseph S; Nguyen, Thuy; Carnwath, Troy P; Crook, Julia E; Lucas, John A; Graff-Radford, Neill R; Carrasquillo, Minerva M; Ertekin-Taner, Nilufer (J Alzheimers Dis, 2021)
BACKGROUND/OBJECTIVE: The aim of this study was to determine if plasma concentrations of 5 surrogate markers of Alzheimer's disease (AD) pathology and neuroinflammation are associated with disease status in African Americans. METHODS: We evaluated 321 African Americans (159 AD, 162 controls) from the Florida Consortium for African-American Alzheimer's Disease Studies (FCA3DS). Five plasma proteins reflecting AD neuropathology or inflammation (Aβ42, tau, IL6, IL10, TNFα) were tested for associations with AD, age, sex, APOE and MAPT genotypes, and for pairwise correlations. RESULTS: Plasma tau levels were higher in AD when adjusted for biological and technical covariates. APOEɛ4 was associated with lower plasma Aβ42 and tau levels. Older age was associated with higher plasma Aβ42, tau, and TNFα. Females had lower IL10 levels. Inflammatory proteins had strong pairwise correlations amongst themselves and with Aβ42. CONCLUSION: We identified effects of demographic and genetic variants on five potential plasma biomarkers in African Americans. Plasma inflammatory biomarkers and Aβ42 may reflect correlated pathologies and elevated plasma tau may be a biomarker of AD in this population.
Keywords: African Americans; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Case-Control Studies; Female; Humans; Interleukin-10; Interleukin-6; Male; Middle Aged; Peptide Fragments; tau Proteins; Tumor Necrosis Factor-alpha

Polyphenols as Potential Metal Chelation Compounds Against Alzheimer's Disease. - Lakey-Beitia, Johant; Burillo, Andrea M; La Penna, Giovanni; Hegde, Muralidhar L; Rao, K S (J Alzheimers Dis, 2021)
Alzheimer's disease (AD) is the most common neurodegenerative disease affecting more than 50 million people worldwide. The pathology of this multifactorial disease is primarily characterized by the formation of amyloid-β (Aβ) aggregates; however, other etiological factors including metal dyshomeostasis, specifically copper (Cu), zinc (Zn), and iron (Fe), play critical role in disease progression. Because these transition metal ions are important for cellular function, their imbalance can cause oxidative stress that leads to cellular death and eventual cognitive decay. Importantly, these transition metal ions can interact with the amyloid-β protein precursor (AβPP) and Aβ42 peptide, affecting Aβ aggregation and increasing its neurotoxicity. Considering how metal dyshomeostasis may substantially contribute to AD, this review discusses polyphenols and the underlying chemical principles that may enable them to act as natural chelators. Furthermore, polyphenols have various therapeutic effects, including antioxidant activity, metal chelation, mitochondrial function, and anti-amyloidogenic activity. These combined therapeutic effects of polyphenols make them strong candidates for a moderate chelation-based therapy for AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Antioxidants; Chelating Agents; Copper; Humans; Oxidative Stress; Polyphenols; Zinc

Porphyromonas gingivalis Outer Membrane Vesicles as the Major Driver of and Explanation for Neuropathogenesis, the Cholinergic Hypothesis, Iron Dyshomeostasis, and Salivary Lactoferrin in Alzheimer's Disease. - Nara, Peter L; Sindelar, Daniel; Penn, Marc S; Potempa, Jan; Griffin, W Sue T (J Alzheimers Dis, 2021)
Porphyromonas gingivalis (Pg) is a primary oral pathogen in the widespread biofilm-induced "chronic" multi-systems inflammatory disease(s) including Alzheimer's disease (AD). It is possibly the only second identified unique example of a biological extremophile in the human body. Having a better understanding of the key microbiological and genetic mechanisms of its pathogenesis and disease induction are central to its future diagnosis, treatment, and possible prevention. The published literature around the role of Pg in AD highlights the bacteria's direct role within the brain to cause disease. The available evidence, although somewhat adopted, does not fully support this as the major process. There are alternative pathogenic/virulence features associated with Pg that have been overlooked and may better explain the pathogenic processes found in the "infection hypothesis" of AD. A better explanation is offered here for the discrepancy in the relatively low amounts of "Pg bacteria" residing in the brain compared to the rather florid amounts and broad distribution of one or more of its major bacterial protein toxins. Related to this, the "Gingipains Hypothesis", AD-related iron dyshomeostasis, and the early reduced salivary lactoferrin, along with the resurrection of the Cholinergic Hypothesis may now be integrated into one working model. The current paper suggests the highly evolved and developed Type IX secretory cargo system of Pg producing outer membrane vesicles may better explain the observed diseases. Thus it is hoped this paper can provide a unifying model for the sporadic form of AD and guide the direction of research, treatment, and possible prevention.
Keywords: Alzheimer Disease; Anti-Infective Agents; Bacterial Outer Membrane Proteins; Bacteroidaceae Infections; Brain; Cholinergic Agents; Extremophiles; Humans; Iron; Lactoferrin; Porphyromonas gingivalis; Saliva

Promoting Successful Cognitive Aging: A Ten-Year Update. - Krivanek, Taylor J; Gale, Seth A; McFeeley, Brittany M; Nicastri, Casey M; Daffner, Kirk R (J Alzheimers Dis, 2021)
A decade has passed since we published a comprehensive review in this journal addressing the topic of promoting successful cognitive aging, making this a good time to take stock of the field. Because there have been limited large-scale, randomized controlled trials, especially following individuals from middle age to late life, some experts have questioned whether recommendations can be legitimately offered about reducing the risk of cognitive decline and dementia. Despite uncertainties, clinicians often need to at least make provisional recommendations to patients based on the highest quality data available. Converging lines of evidence from epidemiological/cohort studies, animal/basic science studies, human proof-of-concept studies, and human intervention studies can provide guidance, highlighting strategies for enhancing cognitive reserve and preventing loss of cognitive capacity. Many of the suggestions made in 2010 have been supported by additional research. Importantly, there is a growing consensus among major health organizations about recommendations to mitigate cognitive decline and promote healthy cognitive aging. Regular physical activity and treatment of cardiovascular risk factors have been supported by all of these organizations. Most organizations have also embraced cognitively stimulating activities, a heart-healthy diet, smoking cessation, and countering metabolic syndrome. Other behaviors like regular social engagement, limiting alcohol use, stress management, getting adequate sleep, avoiding anticholinergic medications, addressing sensory deficits, and protecting the brain against physical and toxic damage also have been endorsed, although less consistently. In this update, we review the evidence for each of these recommendations and offer practical advice about behavior-change techniques to help patients adopt brain-healthy behaviors.
Keywords: Cognition; Cognitive Aging; Diet, Healthy; Exercise; Healthy Aging; Healthy Lifestyle; Humans

Quality of Life in Advanced Dementia with Late Onset, Young Onset, and Very Young Onset. - Hartmann, Julia; Roßmeier, Carola; Riedl, Lina; Dorn, Bianca; Fischer, Julia; Slawik, Till; Fleischhaker, Mareike; Hartmann, Florentine; Egert-Schwender, Silvia; Kehl, Victoria; Haller, Bernhard; Schneider-Schelte, Helga; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Advanced stages of dementia are characterized by severe cognitive and physical impairment. It has not yet been investigated whether persons with young onset dementia (YOD) and late onset dementia (LOD) differ in advanced disease stages. OBJECTIVES: To compare quality of life (QoL) between persons with advanced YOD and LOD; to explore the determinants of QoL; to investigate whether YOD and LOD differ with regard to symptoms and care. METHODS: The study was performed in the context of EPYLOGE (IssuEs in Palliative care for persons in advanced and terminal stages of YOD and LOD in Germany). Persons with advanced dementia (PWAD) were assessed and caregivers were interviewed. QoL was measured with the proxy rating Quality of Life in Late Stage Dementia (QUALID) scale. RESULTS: 93 persons with YOD and 98 with LOD were included. No significant differences in QoL were detected. Determinants of QoL were similar in YOD and LOD. Behavioral and psychological symptoms of dementia (BPSD), suffering and other distressing symptoms were associated with a lower QoL. In YOD but not in LOD antipsychotic treatment was associated with low QoL. The group of persons who were younger than 65 years at the time of the study visit experienced significantly more distressing symptoms than older PWAD. CONCLUSION: Overall, persons with advanced YOD do not appear to be disadvantaged compared to old and oldest PWAD. Special attention, however, must be paid to the group of the very young persons who seem to be particularly vulnerable.
Keywords: Adult; Age of Onset; Aged; Aged, 80 and over; Antipsychotic Agents; Behavioral Symptoms; Caregivers; Dementia; Disease Progression; Female; Germany; Home Care Services; Humans; Individuality; Male; Middle Aged; Pain; Palliative Care; Psychotropic Drugs; Quality of Life

Race/Ethnic Disparities in Mild Cognitive Impairment and Dementia: The Northern Manhattan Study. - Wright, Clinton B; DeRosa, Janet T; Moon, Michelle P; Strobino, Kevin; DeCarli, Charles; Cheung, Ying Kuen; Assuras, Stephanie; Levin, Bonnie; Stern, Yaakov; Sun, Xiaoyan; Rundek, Tatjana; Elkind, Mitchell S V; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Variability in dementia rates across racial and ethnic groups has been estimated at 60%. Studies suggest disparities in Caribbean Hispanic and Black populations, but community-based data are limited. OBJECTIVE: Estimate the prevalence of mild cognitive impairment (MCI) and dementia in the racially and ethnically diverse community-based Northern Manhattan Study cohort and examine sociodemographic, vascular risk factor, and brain imaging correlates. METHODS: Cases of MCI and dementia were adjudicated by a team of neuropsychologists and neurologists and prevalence was estimated across race/ethnic groups. Ordinal proportional odds models were used to estimate race/ethnic differences in the prevalence of MCI or dementia adjusting for sociodemographic variables (model 1), model 1 plus potentially modifiable vascular risk factors (model 2), and model 1 plus structural imaging markers of brain integrity (model 3). RESULTS: There were 989 participants with cognitive outcome determinations (mean age 69±9 years; 68% Hispanic, 16% Black, 14% White; 62% women; mean (±SD) follow-up five (±0.6) years). Hispanic and Black participants had greater likelihood of MCI (20%) and dementia (5%) than White participants accounting for age and education differences. Hispanic participants had greater odds of MCI or dementia than both White and Black participants adjusting for sociodemographic variables, vascular risk factors, and brain imaging factors. White matter hyperintensity burden was significantly associated with greater odds of MCI or dementia (OR = 1.3, 1.1 to 1.6), but there was no significant interaction by race/ethnicity. CONCLUSION: In this diverse community-based cohort, cross-sectional data revealed significant race/ethnic disparities in the prevalence of MCI and dementia. Longer follow-up and incidence data are needed to further clarify these relationships.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Cohort Studies; Cross-Sectional Studies; Dementia; Ethnicity; Female; Humans; Male; Middle Aged; New York City; Prevalence

Reliability of Telephone and Videoconference Methods of Cognitive Assessment in Older Adults with and without Dementia. - Hunter, Matthew B; Jenkins, Natalie; Dolan, Clare; Pullen, Hannah; Ritchie, Craig; Muniz-Terrera, Graciela (J Alzheimers Dis, 2021)
BACKGROUND: Telephone and videoconference administration of cognitive tests introduce additional sources of variance compared to in-person testing. Reviews of test-retest reliability have included mixed neurocognitive and psychiatric populations with limited consideration of methodological and statistical contributions. OBJECTIVE: We reviewed reliability estimates from comparison studies of older adults with and without dementia, considering test-retest analyses and study methods. METHODS: Medline, Embase, PsycINFO, and Web of Science were systematically searched from 1 January 2000 to 9 June 2020 for original articles comparing telephone or videoconference administered cognitive instruments to in-person administration in older adults with and without dementia or mild cognitive impairment. RESULTS: Of 4,125 articles, 23 were included: 11 telephone (N = 2 dementia cohorts) and 12 videoconference (N = 4 dementia cohorts). Telephone administered subtest scores trended in the same direction as in-person with comparable means. Person-level data were scarce. Data on dementia was only available for MMSE, with resulting subtle modality bias. MMSE, SMMSE, Letter Fluency, and HVLT-R in healthy to mild-moderate Alzheimer's disease were particularly reliable for videoconference administration. Other tests show promise but require more observations and comprehensive analyses. Most studies used high-speed stable videoconferencing hardware resulting in a lack of ecological validity for home administration. CONCLUSION: Remote administration is often consistent with in-person administration but variable and limited at the person/test level. Improved statistical design and inclusion of dementia related cohorts in telephone studies is recommended. Reliability evidence is stronger for videoconferencing but with limited applicability to home administration and severe dementia. Improved reporting of administrative procedures is recommended.
Keywords: Aged; Aged, 80 and over; Cognition; Cognitive Dysfunction; Dementia; Geriatric Assessment; Humans; Neuropsychological Tests; Remote Consultation; Reproducibility of Results; Telephone; Videoconferencing

The Retinal Vessel Density Can Reflect Cognitive Function in Patients with Alzheimer's Disease: Evidence from Optical Coherence Tomography Angiography. - Yan, Yibing; Wu, Xingqi; Wang, Xiaojing; Geng, Zhi; Wang, Lu; Xiao, Guixian; Wu, Yue; Zhou, Shanshan; Liao, Rongfeng; Wei, Ling; Tian, Yanghua; Wang, Kai (J Alzheimers Dis, 2021)
BACKGROUND: There is increasing evidence that Alzheimer's disease (AD) patients may present decreased cerebral blood perfusion before pathological brain changes. Using the retina as a window to the brain, we can study disorders of the central nervous system through the eyes. OBJECTIVE: This study aimed to investigate differences in retinal structure and vessel density (VD) between patients with mild AD and healthy controls (HCs). Furthermore, we explored the relationship between retinal VD and cognitive function. METHODS: We enrolled 37 patients with AD and 29 age-matched HCs who underwent standard ophthalmic optical coherence tomography angiography (OCTA) for evaluation of the retinal layer thickness and VD parameters. Cognitive function was evaluated using a battery of neuropsychological assessments. Finally, the correlations among retinal layer thickness, VD parameters, and cognitive function were evaluated. RESULTS: The retinal fiber layer thickness and retinal VD of patients with AD were significantly reduced compared with HCs. The retinal VD was significantly correlated with overall cognition, memory, executive, and visual-spatial perception functions. However, there was no significant between-group difference in the macular thickness. CONCLUSION: Our findings indicate a positive correlation between retinal VD and some, but not all, cognitive function domains. Most importantly, we demonstrated the role of OCTA in detecting early capillary changes, which could be a noninvasive biomarker for early AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cognition; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Retinal Vessels; Tomography, Optical Coherence

A Super-Resolved View of the Alzheimer's Disease-Related Amyloidogenic Pathway in Hippocampal Neurons. - Yu, Yang; Gao, Yang; Winblad, Bengt; Tjernberg, Lars O; Schedin-Weiss, Sophia (J Alzheimers Dis, 2021)
BACKGROUND: Processing of the amyloid-β protein precursor (AβPP) is neurophysiologically important due to the resulting fragments that regulate synapse biology, as well as potentially harmful due to generation of the 42 amino acid long amyloid β-peptide (Aβ42), which is a key player in Alzheimer's disease. OBJECTIVE: Our aim was to clarify the subcellular locations of the fragments involved in the amyloidogenic pathway in primary neurons with a focus on Aβ42 and its immediate substrate AβPP C-terminal fragment (APP-CTF). To overcome the difficulties of resolving these compartments due to their small size, we used super-resolution microscopy. METHODS: Mouse primary hippocampal neurons were immunolabelled and imaged by stimulated emission depletion (STED) microscopy, including three-dimensional three-channel imaging, and quantitative image analyses. RESULTS: The first (β-secretase) and second (γ-secretase) cleavages of AβPP were localized to functionally and distally distinct compartments. The β-secretase cleavage was observed in early endosomes in soma, where we were able to show that the liberated N- and C-terminal fragments were sorted into distinct vesicles budding from the early endosomes. Lack of colocalization of Aβ42 and APP-CTF in soma suggested that γ-secretase cleavage occurs in neurites. Indeed, APP-CTF was, in line with Aβ42 in our previous study, enriched in the presynapse but absent from the postsynapse. In contrast, full-length AβPP was not detected in either the pre- or the postsynaptic side of the synapse. Furthermore, we observed that endogenously produced and endocytosed Aβ42 were localized in different compartments. CONCLUSION: These findings provide critical super-resolved insight into amyloidogenic AβPP processing in primary neurons.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Amyloidogenic Proteins; Animals; Cells, Cultured; Hippocampus; Humans; Mice; Mice, Inbred C57BL; Microscopy; Neurons; Peptide Fragments; Protein Transport

tRNA-Derived Fragments in Alzheimer's Disease: Implications for New Disease Biomarkers and Neuropathological Mechanisms. - Wu, Wenzhe; Lee, Inhan; Spratt, Heidi; Fang, Xiang; Bao, Xiaoyong (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease (AD) is the most common type of dementia caused by irreversible neurodegeneration, with the onset mechanisms elusive. tRNA-derived RNA fragments (tRFs), a recently discovered family of small non-coding RNAs (sncRNAs), have been found to associate with many human diseases, including infectious, metabolic, and neurological diseases. However, whether tRFs play a role in human AD development is not known. OBJECTIVE: This study aimed to explore whether tRFs are involved in human AD. METHODS: Thirty-four postmortem human hippocampus samples were used. The expression of Drosha, Dicer, and angiogenin (ANG), three ribonucleases responsible for the biogenesis of sncRNAs, was determined by qRT-PCR and western blot. The tRFs in the hippocampus was detected by qRT-PCR or northern blot. We also used qRT-PCR to quantify NOP2/Sun RNA methyltransferase 2 (NSun2) and polyadenylation factor I subunit 1 (CLP1), two tRNA modification enzymes. RESULTS: tRFs derived from a subset of tRNAs are significantly altered in the hippocampus of AD patients. The expression change of some tRFs showed age- and disease stage-dependent. ANG is significantly enhanced in AD, suggesting its role in inducing tRFs in AD. The expression of NSun2 in AD patients younger than 65 was significantly decreased. According to a previous report supporting NSun2-mediated tRNA methylation modification making tRNA less susceptible to ANG-mediated cleavage, our results suggested that the decrease in NSun2 may make tRNAs less methylated and subsequently enhanced tRF production from ANG-mediated tRNA cleavage. CONCLUSION: Our studies demonstrated for the first time the involvement of tRFs in human AD.
Keywords: Aged; Alzheimer Disease; Biomarkers; Blotting, Northern; Case-Control Studies; Hippocampus; Humans; Polymerase Chain Reaction; RNA, Small Untranslated; RNA, Transfer

Upregulation of Cortical A2A Adenosine Receptors Is Reflected in Platelets of Patients with Alzheimer's Disease. - Merighi, Stefania; Battistello, Enrica; Casetta, Ilaria; Gragnaniello, Daniela; Poloni, Tino Emanuele; Medici, Valentina; Cirrincione, Alice; Varani, Katia; Vincenzi, Fabrizio; Borea, Pier Andrea; Gessi, Stefania (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease (AD) is a neurodegenerative pathology covering about 70%of all cases of dementia. Adenosine, a ubiquitous nucleoside, plays a key role in neurodegeneration, through interaction with four receptor subtypes. The A2A receptor is upregulated in peripheral blood cells of patients affected by Parkinson's and Huntington's diseases, reflecting the same alteration found in brain tissues. However, whether these changes are also present in AD pathology has not been determined. OBJECTIVE: In this study we verified any significant difference between AD cases and controls in both brain and platelets and we evaluated whether peripheral A2A receptors may reflect the status of neuronal A2A receptors. METHODS: We evaluated the expression of A2A receptors in frontal white matter, frontal gray matter, and hippocampus/entorhinal cortex, in postmortem AD patients and control subjects, through [3H]ZM 241385 binding experiments. The same analysis was performed in peripheral platelets from AD patients versus controls. RESULTS: The expression of A2A receptors in frontal white matter, frontal gray matter, and hippocampus/entorhinal cortex, revealed a density (Bmax) of 174±29, 219±33, and 358±84 fmol/mg of proteins, respectively, in postmortem AD patients in comparison to 104±16, 103±19, and 121±20 fmol/mg of proteins in controls (p < 0.01). The same trend was observed in peripheral platelets from AD patients versus controls (Bmax of 214±17 versus 95±4 fmol/mg of proteins, respectively, p < 0.01). CONCLUSION: AD subjects show significantly higher A2A receptor density than controls. Values on platelets seem to correlate with those in the brain supporting a role for A2A receptor as a possible marker of AD pathology and drug target for novel therapies able to modify the progression of dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Blood Platelets; Cerebral Cortex; Female; Humans; Male; Receptor, Adenosine A2A; Up-Regulation

White Matter Connectivity in Incident Mild Cognitive Impairment: A Diffusion Spectrum Imaging Study of World Trade Center Responders at Midlife. - Huang, Chuan; Kritikos, Minos; Clouston, Sean A P; Deri, Yael; Serrano-Sosa, Mario; Bangiyev, Lev; Santiago-Michels, Stephanie; Gandy, Sam; Sano, Mary; Bromet, Evelyn J; Luft, Benjamin J (J Alzheimers Dis, 2021)
BACKGROUND: Individuals who participated in response efforts at the World Trade Center (WTC) following 9/11/2001 are experiencing elevated incidence of mild cognitive impairment (MCI) at midlife. OBJECTIVE: We hypothesized that white matter connectivity measured using diffusion spectrum imaging (DSI) would be restructured in WTC responders with MCI versus cognitively unimpaired responders. METHODS: Twenty responders (mean age 56; 10 MCI/10 unimpaired) recruited from an epidemiological study were characterized using NIA-AA criteria alongside controls matched on demographics (age/sex/occupation/race/education). Axial DSI was acquired on a 3T Siemen's Biograph mMR scanner (12-channel head coil) using a multi-band diffusion sequence. Connectometry examined whole-brain tract-level differences in white matter integrity. Fractional anisotropy (FA), mean diffusivity (MD), and quantified anisotropy were extracted for region of interest (ROI) analyses using the Desikan-Killiany atlas. RESULTS: Connectometry identified both increased and decreased connectivity within regions of the brains of responders with MCI identified in the corticothalamic pathway and cortico-striatal pathway that survived adjustment for multiple comparisons. MCI was also associated with higher FA values in five ROIs including in the rostral anterior cingulate; lower MD values in four ROIs including the left rostral anterior cingulate; and higher MD values in the right inferior circular insula. Analyses by cognitive domain revealed nominal associations in domains of response speed, verbal learning, verbal retention, and visuospatial learning. CONCLUSIONS: WTC responders with MCI at midlife showed early signs of neurodegeneration characterized by both increased and decreased white matter diffusivity in regions commonly affected by early-onset Alzheimer's disease.
Keywords: Brain; Cognitive Dysfunction; Diffusion Tensor Imaging; Emergency Responders; Female; Humans; Incidence; Male; Middle Aged; September 11 Terrorist Attacks; White Matter

Awareness of the COVID-19 Outbreak and Resultant Depressive Tendencies in Patients with Severe Alzheimer's Disease. - Tsugawa, Akito; Sakurai, Shu; Inagawa, Yuta; Hirose, Daisuke; Kaneko, Yoshitsugu; Ogawa, Yusuke; Serisawa, Shuntaro; Takenoshita, Naoto; Sakurai, Hirofumi; Kanetaka, Hidekazu; Hirao, Kentaro; Shimizu, Soichiro (J Alzheimers Dis, 2020)
The ongoing coronavirus disease 2019 (COVID-19) pandemic has substantially affected patients with dementia and their caregivers. However, we found not all Alzheimer's disease (AD) patients were afraid of COVID-19 infection. Therefore, we investigated the association between rate of awareness of COVID-19 and depressive tendency in AD. 126 consecutive outpatients with AD were enrolled in this study from May 25, on the day when the declaration of emergency was lifted in Japan, through June 30, 2020. In addition to routine psychological tests, the participants were asked the following two questions: "Do you know COVID-19?" and "Why are you wearing a face mask?". Moderate to severe AD patients were found to have a low COVID-19 recognition rate and did not fully understand why they were wearing face masks. In addition, because they did not understand the seriousness of the COVID-19 outbreak, their Geriatric Depression Scale scores were also substantially lower. These results may appear to simply indicate that people with severe dementia are unaware of current events. However, these results provide insights into how to care for patients with dementia and how to allocate the time and support of our limited staff during the COVID-19 outbreak.
Keywords: Aged; Alzheimer Disease; Awareness; Betacoronavirus; Caregivers; Communicable Disease Control; Coronavirus Infections; COVID-19; Female; Humans; Japan; Male; Mental Competency; Pandemics; Patient Care; Pneumonia, Viral; Psychosocial Support Systems; SARS-CoV-2; Severity of Illness Index

Circulating Vitamin D Levels and Alzheimer's Disease: A Mendelian Randomization Study in the IGAP and UK Biobank. - Wang, Longcai; Qiao, Yanchun; Zhang, Haihua; Zhang, Yan; Hua, Jiao; Jin, Shuilin; Liu, Guiyou (J Alzheimers Dis, 2020)
Observational studies strongly supported the association of low levels of circulating 25-hydroxyvitamin D (25OHD) and cognitive impairment or dementia in aging populations. However, randomized controlled trials have not shown clear evidence that vitamin D supplementation could improve cognitive outcomes. In fact, some studies reported the association between vitamin D and cognitive impairment based on individuals aged 60 years and over. However, it is still unclear that whether vitamin D levels are causally associated with Alzheimer's disease (AD) risk in individuals aged 60 years and over. Here, we performed a Mendelian randomization (MR) study to investigate the causal association between vitamin D levels and AD using a large-scale vitamin D genome-wide association study (GWAS) dataset and two large-scale AD GWAS datasets from the IGAP and UK Biobank with individuals aged 60 years and over. Our results showed that genetically increased 25OHD levels were significantly associated with reduced AD risk in individuals aged 60 years and over. Hence, our findings in combination with previous literature indicate that maintaining adequate vitamin D status in older people especially aged 60 years and over, may contribute to slow down cognitive decline and forestall AD. Long-term randomized controlled trials are required to test whether vitamin D supplementation may prevent AD in older people especially those aged 60 years and may be recommended as preventive agents.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biological Specimen Banks; Cognition Disorders; Databases, Factual; Female; Genome-Wide Association Study; Humans; Hydroxycholecalciferols; Male; Mendelian Randomization Analysis; Middle Aged; Nutritional Status; United Kingdom; Vitamin D; Vitamin D Deficiency

Cognitive Impairment Is a Common Comorbidity in Deceased COVID-19 Patients: A Hospital-Based Retrospective Cohort Study. - Martín-Jiménez, Paloma; Muñoz-García, Mariana I; Seoane, David; Roca-Rodríguez, Lucas; García-Reyne, Ana; Lalueza, Antonio; Maestro, Guillermo; Folgueira, Dolores; Blanco-Palmero, Víctor A; Herrero-San Martín, Alejandro; Llamas-Velasco, Sara; Pérez-Martínez, David A; et al. (J Alzheimers Dis, 2020)
We analyzed the frequency of cognitive impairment (CI) in deceased COVID-19 patients at a tertiary hospital in Spain. Among the 477 adult cases who died after admission from March 1 to March 31, 2020, 281 had confirmed COVID-19. CI (21.1% dementia and 8.9% mild cognitive impairment) was a common comorbidity. Subjects with CI were older, tended to live in nursing homes, had shorter time from symptom onset to death, and were rarely admitted to the ICU, receiving palliative care more often. CI is a frequent comorbidity in deceased COVID-19 subjects and is associated with differences in care.
Keywords: Adolescent; Adult; Age Factors; Aged; Aged, 80 and over; Cognitive Dysfunction; Comorbidity; COVID-19; Female; Hospital Mortality; Hospitals; Humans; Male; Middle Aged; Palliative Care; Patient Admission; Retrospective Studies; Spain; Young Adult

Comparative Cognitive Effects of Choreographed Exercise and Multimodal Physical Therapy in Older Adults with Amnestic Mild Cognitive Impairment: Randomized Clinical Trial. - Bisbe, Marta; Fuente-Vidal, Andrea; López, Elisabet; Moreno, Marta; Naya, Marian; de Benetti, Claudio; Milà, Raimon; Bruna, Olga; Boada, Merce; Alegret, Montserrat (J Alzheimers Dis, 2020)
BACKGROUND: Recent research on mild cognitive impairment (MCI) has primarily focused on searching for measures to prevent or delay the progression of MCI to dementia. Physical exercise has shown to be effective in the prevention of age-related cognitive decline in elderly adults with MCI. However, the most effective type and dose of exercise for the improvement of cognition are yet to be determined. OBJECTIVE: To compare the cognitive effects of choreographed exercise (Choreography group) with a multimodal physical therapy program (Physical Therapy group) in elderly adults with amnestic MCI, a population with an increased risk of developing dementia. METHODS: We conducted a randomized clinical trial with two parallel groups under allocation concealment and assessor blinding. Participants were allocated into Choreography or Physical Therapy group and performed exercises twice per week in 60-minute sessions during 12 weeks. RESULTS: Thirty-six participants with amnestic MCI, ages 65 to 85, were assessed at baseline and after 12 weeks of intervention, by comprehensive validated neuropsychological and physical assessments. A Repeated measures General Lineal Model showed statistically significant differences in cognitive and physical outcomes. Both groups significantly improved in visual delayed recall. The Choreography group exhibited significantly more benefits on verbal recognition memory than the Physical Therapy group. CONCLUSION: Greater cognitive benefits were achieved in the choreographic intervention than in the multimodal physical therapy, mainly in those functions more related to the risk of conversion to dementia. Additional studies are needed to confirm whether the observed effects are related to delayed onset of Alzheimer's disease in elderly adults with amnestic MCI.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Combined Modality Therapy; Dance Therapy; Exercise Therapy; Female; Humans; Linear Models; Male; Neuropsychological Tests; Physical Therapy Modalities; Single-Blind Method

COVID-19: Review of a 21st Century Pandemic from Etiology to Neuro-psychiatric Implications. - Yamamoto, Vicky; Bolanos, Joe F; Fiallos, John; Strand, Susanne E; Morris, Kevin; Shahrokhinia, Sanam; Cushing, Tim R; Hopp, Lawrence; Tiwari, Ambooj; Hariri, Robert; Sokolov, Rick; Wheeler, Christopher; et al. (J Alzheimers Dis, 2020)
COVID-19 is a severe infectious disease that has claimed >150,000 lives and infected millions in the United States thus far, especially the elderly population. Emerging evidence has shown the virus to cause hemorrhagic and immunologic responses, which impact all organs, including lungs, kidneys, and the brain, as well as extremities. SARS-CoV-2 also affects patients', families', and society's mental health at large. There is growing evidence of re-infection in some patients. The goal of this paper is to provide a comprehensive review of SARS-CoV-2-induced disease, its mechanism of infection, diagnostics, therapeutics, and treatment strategies, while also focusing on less attended aspects by previous studies, including nutritional support, psychological, and rehabilitation of the pandemic and its management. We performed a systematic review of >1,000 articles and included 425 references from online databases, including, PubMed, Google Scholar, and California Baptist University's library. COVID-19 patients go through acute respiratory distress syndrome, cytokine storm, acute hypercoagulable state, and autonomic dysfunction, which must be managed by a multidisciplinary team including nursing, nutrition, and rehabilitation. The elderly population and those who are suffering from Alzheimer's disease and dementia related illnesses seem to be at the higher risk. There are 28 vaccines under development, and new treatment strategies/protocols are being investigated. The future management for COVID-19 should include B-cell and T-cell immunotherapy in combination with emerging prophylaxis. The mental health and illness aspect of COVID-19 are among the most important side effects of this pandemic which requires a national plan for prevention, diagnosis and treatment.
Keywords: Coronavirus Infections; COVID-19; Humans; Immunotherapy; Mental Health; Nutritional Support; Pandemics; Pneumonia, Viral

Death Rate Due to COVID-19 in Alzheimer's Disease and Frontotemporal Dementia. - Matías-Guiu, Jordi A; Pytel, Vanesa; Matías-Guiu, Jorge (J Alzheimers Dis, 2020)
We aimed to evaluate the frequency and mortality of COVID-19 in patients with Alzheimer's disease (AD) and frontotemporal dementia (FTD). We conducted an observational case series. We enrolled 204 patients, 15.2% of whom were diagnosed with COVID-19, and 41.9% of patients with the infection died. Patients with AD were older than patients with FTD (80.36±8.77 versus 72.00±8.35 years old) and had a higher prevalence of arterial hypertension (55.8% versus 26.3%). COVID-19 occurred in 7.3% of patients living at home, but 72.0% of those living at care homes. Living in care facilities and diagnosis of AD were independently associated with a higher probability of death. We found that living in care homes is the most relevant factor for an increased risk of COVID-19 infection and death, with AD patients exhibiting a higher risk than those with FTD.
Keywords: Age Factors; Aged; Aged, 80 and over; Alzheimer Disease; Coronavirus Infections; COVID-19; Female; Frontotemporal Dementia; Humans; Hypertension; Independent Living; Male; Nursing Homes; Pandemics; Pneumonia, Viral; Prevalence; Risk Factors

Dementia Care in the Time of COVID-19 Pandemic. - Tousi, Babak (J Alzheimers Dis, 2020)
Patients with dementia are particularly vulnerable during the COVID-19 pandemic. The initial response to COVID-19 promoted behavioral changes in both society and healthcare, while a long-term solution is sought by prioritizing societal values. In addition, there has been disruption to clinical care and clinical research. This pandemic might have significantly changed the care for our patients with dementia toward increased acceptance of telemedicine by the patients and providers, and its utilization in both clinical care and research.
Keywords: Betacoronavirus; Coronavirus Infections; Dementia; Health Services Accessibility; Humans; Pandemics; Pneumonia, Viral; Telemedicine

Dementia Care in Times of COVID-19: Experience at Fundació ACE in Barcelona, Spain. - Benaque, Alba; Gurruchaga, Miren Jone; Abdelnour, Carla; Hernandez, Isabel; Cañabate, Pilar; Alegret, Montserrat; Rodríguez, Isabel; Rosende-Roca, Maitee; Tartari, Juan Pablo; Esteban, Ester; López, Rogelio; Gil, Silvia; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Fundació ACE is a non-profit organization providing care based on a holistic model to persons with cognitive disorders and their families for 25 years in Barcelona, Spain. Delivering care to this vulnerable population amidst the COVID-19 pandemic has represented a major challenge to our institution. OBJECTIVE: To share our experience in adapting our model of care to the new situation to ensure continuity of care. METHODS: We detail the sequence of events and the actions taken within Fundació ACE to swiftly adapt our face-to-face model of care to one based on telemedicine consultations. We characterize individuals under follow-up by the Memory Unit from 2017 to 2019 and compare the number of weekly visits in 2020 performed before and after the lockdown was imposed. RESULTS: The total number of individuals being actively followed by Fundació ACE Memory Unit grew from 6,928 in 2017 to 8,147 in 2019. Among those newly diagnosed in 2019, most patients had mild cognitive impairment or mild dementia (42% and 25%, respectively). Weekly visits dropped by 60% following the suspension of face-to-face activity. However, by April 24 we were able to perform 78% of the visits we averaged in the weeks before confinement began. DISCUSSION: We have shown that Fundació ACE model of care has been able to successfully adapt to a health and social critical situation as COVID-19 pandemic. Overall, we were able to guarantee the continuity of care while preserving the safety of patients, families, and professionals. We also seized the opportunity to improve our model of care.
Keywords: Aged; Aged, 80 and over; Betacoronavirus; Coronavirus Infections; COVID-19; Dementia; Female; Follow-Up Studies; Holistic Health; Humans; Male; Pandemics; Patient-Centered Care; Pneumonia, Viral; SARS-CoV-2; Spain; Telemedicine

Dementia in the COVID-19 Period. - Korczyn, Amos D (J Alzheimers Dis, 2020)
Keywords: Betacoronavirus; Coronavirus; Coronavirus Infections; COVID-19; Dementia; Humans; Nervous System Diseases; Pandemics; Pneumonia, Viral; SARS-CoV-2; Telemedicine

The Effects of Confinement on Neuropsychiatric Symptoms in Alzheimer's Disease During the COVID-19 Crisis. - Boutoleau-Bretonnière, Claire; Pouclet-Courtemanche, Hélene; Gillet, Aurelie; Bernard, Amelie; Deruet, Anne Laure; Gouraud, Ines; Mazoue, Aurelien; Lamy, Estelle; Rocher, Laetitia; Kapogiannis, Dimitrios; El Haj, Mohamad (J Alzheimers Dis, 2020)
BACKGROUND: Neuropsychiatric symptoms, such as depression, anxiety, apathy, agitation, and hallucinations, are frequent in Alzheimer's disease (AD) and their prevalence tends to increase with external stressors. OBJECTIVE: We offer the first investigation of the effects of confinement during the COVID-19 crisis on neuropsychiatric symptoms in patients with AD. METHODS: We contacted caregivers of 38 patients with AD who were confined to their homes for nearly two months and asked them to report whether patients experienced any change in neuropsychiatric symptoms during, compared to before, the confinement and rate its severity and impact on themselves using the Neuropsychiatric Inventory-Questionnaire. RESULTS: Among the 38 patients, only 10 demonstrated neuropsychiatric changes during the confinement. Cognitive function of these 10 patients, assessed with the Mini-Mental State Examination, was worse than that of patients who did not demonstrate neuropsychiatric changes. Interestingly, among the 10 patients with neuropsychiatric changes, the duration of confinement significantly correlated with the severity of symptoms as well as with their caregivers' distress. DISCUSSION: The confinement seems to impact neuropsychiatric symptomatology in AD patients with low baseline cognitive function.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Betacoronavirus; Cohort Studies; Coronavirus Infections; COVID-19; Female; Humans; Male; Mental Disorders; Mental Status and Dementia Tests; Middle Aged; Pandemics; Pneumonia, Viral; Quarantine; SARS-CoV-2

Environmental Nanoparticles, SARS-CoV-2 Brain Involvement, and Potential Acceleration of Alzheimer's and Parkinson's Diseases in Young Urbanites Exposed to Air Pollution. - Calderón-Garcidueñas, Lilian; Torres-Jardón, Ricardo; Franco-Lira, Maricela; Kulesza, Randy; González-Maciel, Angelica; Reynoso-Robles, Rafael; Brito-Aguilar, Rafael; García-Arreola, Berenice; Revueltas-Ficachi, Paula; Barrera-Velázquez, Juana Adriana; García-Alonso, Griselda; García-Rojas, Edgar; et al. (J Alzheimers Dis, 2020)
Alzheimer's and Parkinson's diseases (AD, PD) have a pediatric and young adult onset in Metropolitan Mexico City (MMC). The SARS-CoV-2 neurotropic RNA virus is triggering neurological complications and deep concern regarding acceleration of neuroinflammatory and neurodegenerative processes already in progress. This review, based on our MMC experience, will discuss two major issues: 1) why residents chronically exposed to air pollution are likely to be more susceptible to SARS-CoV-2 systemic and brain effects and 2) why young people with AD and PD already in progress will accelerate neurodegenerative processes. Secondary mental consequences of social distancing and isolation, fear, financial insecurity, violence, poor health support, and lack of understanding of the complex crisis are expected in MMC residents infected or free of SARS-CoV-2. MMC residents with pre-SARS-CoV-2 accumulation of misfolded proteins diagnostic of AD and PD and metal-rich, magnetic nanoparticles damaging key neural organelles are an ideal host for neurotropic SARS-CoV-2 RNA virus invading the body through the same portals damaged by nanoparticles: nasal olfactory epithelium, the gastrointestinal tract, and the alveolar-capillary portal. We urgently need MMC multicenter retrospective-prospective neurological and psychiatric population follow-up and intervention strategies in place in case of acceleration of neurodegenerative processes, increased risk of suicide, and mental disease worsening. Identification of vulnerable populations and continuous effort to lower air pollution ought to be critical steps.
Keywords: Adult; Air Pollution; Alzheimer Disease; Brain Diseases; Coronavirus Infections; COVID-19; Disease Progression; Environmental Pollutants; Humans; Middle Aged; Nanoparticles; Pandemics; Parkinson Disease; Pneumonia, Viral; Suicide; Urban Population

Neurobiology of COVID-19. - Fotuhi, Majid; Mian, Ali; Meysami, Somayeh; Raji, Cyrus A (J Alzheimers Dis, 2020)
Anosmia, stroke, paralysis, cranial nerve deficits, encephalopathy, delirium, meningitis, and seizures are some of the neurological complications in patients with coronavirus disease-19 (COVID-19) which is caused by acute respiratory syndrome coronavirus 2 (SARS-Cov2). There remains a challenge to determine the extent to which neurological abnormalities in COVID-19 are caused by SARS-Cov2 itself, the exaggerated cytokine response it triggers, and/or the resulting hypercoagulapathy and formation of blood clots in blood vessels throughout the body and the brain. In this article, we review the reports that address neurological manifestations in patients with COVID-19 who may present with acute neurological symptoms (e.g., stroke), even without typical respiratory symptoms such as fever, cough, or shortness of breath. Next, we discuss the different neurobiological processes and mechanisms that may underlie the link between SARS-Cov2 and COVID-19 in the brain, cranial nerves, peripheral nerves, and muscles. Finally, we propose a basic "NeuroCovid" classification scheme that integrates these concepts and highlights some of the short-term challenges for the practice of neurology today and the long-term sequalae of COVID-19 such as depression, OCD, insomnia, cognitive decline, accelerated aging, Parkinson's disease, or Alzheimer's disease in the future. In doing so, we intend to provide a basis from which to build on future hypotheses and investigations regarding SARS-Cov2 and the nervous system.
Keywords: Betacoronavirus; Brain; Coronavirus Infections; COVID-19; Humans; Inflammation Mediators; Nervous System Diseases; Pandemics; Pneumonia, Viral; SARS-CoV-2

Potential Novel Role of COVID-19 in Alzheimer's Disease and Preventative Mitigation Strategies. - Naughton, Sean X; Raval, Urdhva; Pasinetti, Giulio M (J Alzheimers Dis, 2020)
There are a number of potential implications for the field of Alzheimer's disease (AD) stemming from the global spread of SARS-CoV-2. Neuroinflammation is known to be a prominent feature of neurodegeneration and plays a major role in AD pathology. Immune response and excessive inflammation in COVID-19 may also accelerate the progression of brain inflammatory neurodegeneration, and elderly individuals are more susceptible to severe outcomes after SARS-CoV-2 infection. Individuals with type 2 diabetes (T2D) are at an increased risk for AD as well as severe outcomes after SARS-CoV-2 infection. Genetic and socioeconomic factors influencing the rates of T2D, AD, and COVID-19 severity may create an exceptionally high-risk profile for certain demographics such as African Americans and Hispanic Americans. Type I interferon response plays an important role in both host response to viral infection, as well as AD pathology and may be a sensible therapeutic target in both AD and COVID-19.
Keywords: Aged; Alzheimer Disease; Betacoronavirus; Coronavirus Infections; COVID-19; Diabetes Mellitus, Type 2; Humans; Interferon Type I; Pandemics; Pneumonia, Viral; SARS-CoV-2; Synapses

Resilience of Alzheimer's Disease to COVID-19. - Li, Jingwen; Long, Xi; Huang, Heqing; Tang, Jine; Zhu, Chunli; Hu, Shaoping; Wu, Jing; Li, Jinghong; Lin, Zhicheng; Xiong, Nian (J Alzheimers Dis, 2020)
BACKGROUND: Facing the novel coronavirus disease 2019 (COVID-19), most vulnerable individuals are seniors, especially those with comorbidities. More attention needs to been paid to the COVID-19 patients with Alzheimer's disease (AD), which is the top age-related neurodegenerative disease. OBJECTIVE: Since it is unclear whether AD patients are prone to COVID-19 infection and progression to severe stages, we report for the first time a retrospective analysis of the clinical characteristics of AD patients with COVID-19 pneumonia. METHODS: We conducted a retrospective cohort study of the clinical data of 19 AD patients with COVID-19 pneumonia, compared with 23 non-AD COVID-19 patients admitted at the same time to our hospital. Demographic, clinical, laboratory, radiological, and treatment data were collected and analyzed. RESULTS: Between AD patients and non-AD patients with COVID-19 pneumonia, the pneumonia severity was not significantly different. AD patients had a higher clustering onset than non-AD patients. The median duration from symptom onset to hospitalization were shorter in AD patients than non-AD patients, indicating the former were sent to the hospital by their family or from nursing home earlier than the later. The median duration from hospitalization to discharge seemed shorter in AD patients than non-AD patients. Dementia patients seemed less likely to report fatigue. It is noticed that more AD patients might have pericardial effusion than the non-AD patients. CONCLUSION: AD patients with COVID-19 were in milder conditions with a better prognosis than non-AD patients. AD patients who had adequate access to healthcare showed resilience to COVID-19 with shorter hospital stays.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cluster Analysis; Cohort Studies; Coronavirus Infections; COVID-19; Disease Progression; Fatigue; Female; Humans; Length of Stay; Male; Middle Aged; Pandemics; Patient Discharge; Pleural Effusion; Pneumonia; Pneumonia, Viral; Prognosis; Resilience, Psychological

Telemedicine for Delivery of Care in Frontotemporal Lobar Degeneration During COVID-19 Pandemic: Results from Southern Italy. - Capozzo, Rosa; Zoccolella, Stefano; Frisullo, Maria Elisa; Barone, Roberta; Dell'Abate, Maria Teresa; Barulli, Maria Rosaria; Musio, Marco; Accogli, Miriam; Logroscino, Giancarlo (J Alzheimers Dis, 2020)
BACKGROUND: The COVID-19 pandemic is changing clinical practice in neurology, after the governments decided the introduction of social distancing and interruption of medical non-emergency services in many countries. Teleneurology is an effective tool for the remote evaluation of patients but its adoption for frontotemporal lobar dementia (FTD) is in a preliminary stage. OBJECTIVE: We evaluated multidisciplinary assessment of patients with FTD using telehealth during the COVID-19 pandemic. METHODS: All patients received a diagnosis of FTD during 2018-2019 according to international criteria. A structured questionnaire and Clinical Dementia Rating Scale (CDR)-FTD were used by the neurologist with patients and/or caregivers. Index symptoms of COVID-19 infection were searched. RESULTS: Twenty-eight clinical interviews were completed with caregivers and four with both patients/caregivers. Most patients and caregivers were satisfied with the neurological interview and expressed their willingness to continue to be included in remote evaluation programs (90%). Fifty percent of patients experienced significant worsening of clinical picture and quality of life since the start of social distancing. The CDR-FTD scale revealed a significant worsening of behavior (p = 0.01) and language functions (p = 0.009), compared to the last in-person evaluation at the center. One patient presented index symptoms of COVID-19 infection and was confirmed to be positive for COVID-19 with pharyngeal swab. CONCLUSION: The study was conducted in Italy, one of the countries hit particularly hard by the COVID-19 pandemic, with interruption of all non-emergency medical services. Our study indicates that telemedicine is a valid tool to triage patients with FTD to increase practice outreach and efficiency.
Keywords: Aged; Aged, 80 and over; Behavior; Coronavirus Infections; COVID-19; Delivery of Health Care; Disease Progression; Female; Frontotemporal Lobar Degeneration; Humans; Italy; Language; Male; Mental Status and Dementia Tests; Middle Aged; Pandemics; Pneumonia, Viral; Quality of Life; Quarantine; Surveys and Questionnaires; Telemedicine; Triage

11C-CFT-PET in Presymptomatic FTDP-17: A Potential Biomarker Predicting Onset. - Wu, Liyong; Liu, Jia; Feng, Xueyan; Dong, Jing; Qin, Wei; Liu, Yang; Wang, Jingjuan; Lu, Jie; Chen, Kewei; Wang, Yuping; Jia, Jianping (J Alzheimers Dis, 2018)
Frontotemporal dementia with parkinsonism-linked to chromosome 17 (FTDP-17) is a rare autosomal dominant neurodegenerative disorder. Most patients with FTDP-17 carry the mutation in the microtubule-associated protein tau (MAPT) gene. Striatum is predominantly and early affected in FTDP-17. Five family members (two symptomatic patients and three presymptomatic mutation carriers) from a Chinese pedigree of FTDP-17 with N279K mutation in MAPT were enrolled. Parkinsonism was the initial symptom for symptomatic patients. 2b-carbomethoxy-3b-(4-trimethylstannylphenyl) tropane (11C-CFT) uptake was obviously affected in the putamen of two presymptomatic mutation carriers. Presymptomatic case 3, whose 11C-CFT uptake in the right putamen was normal at baseline, was still free of parkinsonism during follow-up. In conclusion, 11C-CFT-positron emission tomography could be a potential biomarker for the presymptomatic stage of FTDP-17 to predict the disease onset.
Keywords: Adult; Biomarkers; Brain; Carbon Radioisotopes; Female; Frontotemporal Dementia; Heterozygote; Humans; Male; Middle Aged; Mutation; Parkinsonian Disorders; Pedigree; Positron-Emission Tomography; tau Proteins

Albuminuria and Microalbuminuria as Predictors of Cognitive Performance in a General Population: An 11-Year Follow-Up Study. - Ekblad, Laura L; Toppala, Sini; Johansson, Jouni K; Koskinen, Seppo; Sundvall, Jouko; Rinne, Juha O; Puukka, Pauli; Viitanen, Matti; Jula, Antti (J Alzheimers Dis, 2018)
Microalbuminuria, defined as urine albumin-to-creatinine ratio (UACR)>3.0 mg/mmol and ≤ 30 mg/mmol, is an early marker of endothelial damage of the renal glomeruli. Recent research suggests an association among microalbuminuria, albuminuria (UACR > 3.0 mg/mmol), and cognitive impairment. Previous studies on microalbuminuria, albuminuria, and cognition in the middle-aged have not provided repeated cognitive testing at different time-points. We hypothesized that albuminuria (micro- plus macroalbuminuria) and microalbuminuria would predict cognitive decline independently of previously reported risk factors for cognitive decline, including cardiovascular risk factors. In addition, we hypothesized that UACR levels even below the cut-off for microalbuminuria might be associated with cognitive functioning. These hypotheses were tested in the Finnish nationwide, population-based Health 2000 Survey (n = 5,921, mean age 52.6, 55.0% women), and its follow-up, Health 2011 (n = 3,687, mean age at baseline 49.3, 55.6% women). Linear regression analysis was used to determine the associations between measures of albuminuria and cognitive performance. Cognitive functions were assessed with verbal fluency, word-list learning, word-list delayed recall (at baseline and at follow-up), and with simple and visual choice reaction time tests (at baseline only). Here, we show that micro- plus macroalbuminuria associated with poorer word-list learning and a slower reaction time at baseline, with poorer word-list learning at follow-up, and with a steeper decline in word-list learning during 11 years after multivariate adjustments. Also, higher continuous UACR consistently associated with poorer verbal fluency at levels below microalbuminuria. These results suggest that UACR might have value in evaluating the risk for cognitive decline.
Keywords: Adult; Aged; Albuminuria; Cognition; Cognitive Dysfunction; Creatinine; Cross-Sectional Studies; Female; Finland; Follow-Up Studies; Humans; Kidney; Linear Models; Male; Middle Aged; Multivariate Analysis; Neuropsychological Tests; Risk Factors

Alterations in Acrolein Metabolism Contribute to Alzheimer's Disease. - Tsou, Han-Hsing; Hsu, Wen-Chin; Fuh, Jong-Ling; Chen, Shih-Pin; Liu, Tsung-Yun; Wang, Hsiang-Tsui (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a detrimental neurodegenerative disease, and early diagnosis appears to be the key to successful treatment. Acrolein, a byproduct of lipid peroxidation, has been shown to contribute to the pathological process of AD. This study recruited 118 elderly subjects consisting of 58 non-demented control subjects and 62 AD patients. We analyzed the acrolein-related metabolites in the plasma, cerebrospinal fluid (CSF), and urine of all subjects. We found that the levels of acrolein-conjugated protein (Acr-PC) in the plasma (p = 0.00012) and CSF (p = 0.00161) of AD patients were significantly higher than those of control subjects, whereas the levels of a urinary acrolein metabolite, 3-hydroxypropyl mercapturic acid (3-HPMA), were markedly decreased (p = 0.00882) in AD patients. These data suggest that deregulated acrolein metabolism may be correlated with neuronal damage in AD patients, which might provide further insights into the disease progression and early diagnosis of AD.
Keywords: Acetylcysteine; Acrolein; Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Case-Control Studies; Creatinine; Disease Progression; Early Diagnosis; Female; Humans; Male; Middle Aged

Altered Expression of Circulating Cdc42 in Frontotemporal Lobar Degeneration. - Saraceno, Claudia; Catania, Marcella; Paterlini, Anna; Fostinelli, Silvia; Ciani, Miriam; Zanardini, Roberta; Binetti, Giuliano; Di Fede, Giuseppe; Caroppo, Paola; Benussi, Luisa; Ghidoni, Roberta; Bolognin, Silvia (J Alzheimers Dis, 2018)
The term frontotemporal lobar degeneration (FTLD) defines a group of heterogeneous conditions histologically characterized by neuronal degeneration, inclusions of various proteins, and synaptic loss. However, the molecular mechanisms contributing to these alterations are still unknown. As the Rho-GTPase family member Cell division cycle 42 (Cdc42) plays a key role in the regulation of actin cytoskeleton dynamics and spine formation, we investigated whether Cdc42 protein levels were altered in the disease. Cdc42 was increased in the frontal cortex of FTLD patients compared to age-matched controls, but also in Alzheimer's disease (AD) patients included in the data-set. On the other hand, the pool of circulating Cdc42 in the plasma was altered in FTLD but not in AD patients. Interestingly, the stratification of the FTLD patients according to the different clinical variants showed a specific decrease of Cdc42 expression in the behavioral subgroup. This data support a role of Cdc42 in FTLD and specifically in the behavioral variant.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Case-Control Studies; cdc42 GTP-Binding Protein; Female; Frontotemporal Lobar Degeneration; Humans; Male; Middle Aged

Alzheimer's Disease Progression: Factors Influencing Cognitive Decline. - Ferrari, Camilla; Lombardi, Gemma; Polito, Cristina; Lucidi, Giulia; Bagnoli, Silvia; Piaceri, Irene; Nacmias, Benedetta; Berti, Valentina; Rizzuto, Debora; Fratiglioni, Laura; Sorbi, Sandro (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) patients present high variability in the rate of cognitive decline. Despite the wide knowledge on factors influencing dementia risk, little is known on what accounts for AD progression. Previous studies on this topic have mainly analyzed each factor separately without taking into account the interaction between genetic and non-genetic factors. OBJECTIVE: The aim of the present study is to evaluate the role of demographic, clinical, therapeutic, and genetic factors and their interaction on cognitive decline among newly diagnosed AD patients. METHODS: We retrospectively selected 160 AD patients diagnosed at the Neurology Unit of Careggi University Hospital of Florence. We evaluated the occurrence of rapid cognitive changes defined as the worsening of more than four points at the Mini-Mental State Examination after 2-year follow up period. RESULTS: Among the 160 AD patients, 50% presented rapid disease progression. Extrapyramidal signs at disease onset were predictors of worse outcome (OR 2.2), especially among Apolipoprotein E (APOE) ɛ4 allele carriers, while the presence of family history for dementia decreased the risk of rapid progression by about 50%. Higher educated ɛ4-carriers showed a slower AD progression. We identified the chronic use of aspirin as potential secondary preventative strategy for the non ɛ4-carriers. CONCLUSION: At dementia onset, some clinical and demographic data can be predictors of future progression. The outcomes of the present study support the already hypothesized interaction between genetic and non-genetic factors during disease course and suggest genetic-based approaches.
Keywords: Aged; Aged, 80 and over; Alleles; Alzheimer Disease; Apolipoprotein E4; Aspirin; Cognitive Dysfunction; Disease Progression; Female; Heterozygote; Humans; Italy; Male; Middle Aged; Neuropsychological Tests; Retrospective Studies; Secondary Prevention

Alzheimer's Disease: Recent Concepts on the Relation of Mitochondrial Disturbances, Excitotoxicity, Neuroinflammation, and Kynurenines. - Zádori, Dénes; Veres, Gábor; Szalárdy, Levente; Klivenyi, Peter; Vecsei, Laszlo (J Alzheimers Dis, 2018)
The pathomechanism of Alzheimer's disease (AD) certainly involves mitochondrial disturbances, glutamate excitotoxicity, and neuroinflammation. The three main aspects of mitochondrial dysfunction in AD, i.e., the defects in dynamics, altered bioenergetics, and the deficient transport, act synergistically. In addition, glutamatergic neurotransmission is affected in several ways. The balance between synaptic and extrasynaptic glutamatergic transmission is shifted toward the extrasynaptic site contributing to glutamate excitotoxicity, a phenomenon augmented by increased glutamate release and decreased glutamate uptake. Neuroinflammation in AD is predominantly linked to central players of the innate immune system, with central nervous system (CNS)-resident microglia, astroglia, and perivascular macrophages having been implicated at the cellular level. Several abnormalities have been described regarding the activation of certain steps of the kynurenine (KYN) pathway of tryptophan metabolism in AD. First of all, the activation of indolamine 2,3-dioxygenase, the first and rate-limiting step of the pathway, is well-demonstrated. 3-Hydroxy-L-KYN and its metabolite, 3-hydroxy-anthranilic acid have pro-oxidant, antioxidant, and potent immunomodulatory features, giving relevance to their alterations in AD. Another metabolite, quinolinic acid, has been demonstrated to be neurotoxic, promoting glutamate excitotoxicity, reactive oxygen species production, lipid peroxidation, and microglial neuroinflammation, and its abundant presence in AD pathologies has been demonstrated. Finally, the neuroprotective metabolite, kynurenic acid, has been associated with antagonistic effects at glutamate receptors, free radical scavenging, and immunomodulation, giving rise to potential therapeutic implications. This review presents the multiple connections of KYN pathway-related alterations to three main domains of AD pathomechanism, such as mitochondrial dysfunction, excitotoxicity, and neuroinflammation, implicating possible therapeutic options.
Keywords: Alzheimer Disease; Animals; Central Nervous System; Disease Models, Animal; Energy Metabolism; Glutamic Acid; Humans; Immunity, Innate; Inflammation; Kynurenine; Mitochondria; Quinolinic Acid; Reactive Oxygen Species; Receptors, Glutamate; Signal Transduction

Alzheimer's Disease rs11767557 Variant Regulates EPHA1 Gene Expression Specifically in Human Whole Blood. - Liu, Guiyou; Zhang, Yan; Wang, Longcai; Xu, Jianyong; Chen, Xiaoyun; Bao, Yunjuan; Hu, Yang; Jin, Shuilin; Tian, Rui; Bai, Weiyang; Zhou, Wenyang; Wang, Tao; et al. (J Alzheimers Dis, 2018)
Large-scale genome-wide association studies have reported EPHA1 rs11767557 variant to be associated with Alzheimer's disease (AD) risk in the European population. However, it is still unclear how this variant functionally contributes to the underlying disease pathogenesis. The rs11767557 variant is located approximately 3 kb upstream of EPHA1 gene. We think that rs11767557 may modify the expression of nearby genes such as EPHA1 and further cause AD risk. Until now, the potential association between rs11767557 and the expression of nearby genes has not been reported in previous studies. Here, we evaluate the potential expression association between rs11767557 and EPHA1 using multiple large-scale eQTLs datasets in human brain tissues and the whole blood. The results show that rs11767557 variant could significantly regulate EPHA1 gene expression specifically in human whole blood. These findings may further provide important supplementary information about the regulating mechanisms of rs11767557 variant in AD risk.
Keywords: Alzheimer Disease; Case-Control Studies; China; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Polymorphism, Single Nucleotide; Receptor, EphA1; Risk Assessment

Aphasia in Progressive Supranuclear Palsy: As Severe as Progressive Non-Fluent Aphasia. - Burrell, James R; Ballard, Kirrie J; Halliday, Glenda M; Hodges, John R (J Alzheimers Dis, 2018)
BACKGROUND: Adynamic speech is characteristic of progressive supranuclear palsy (PSP), but higher language deficits have been reported inconsistently, in the context of clinical and pathological overlaps with progressive non-fluent aphasia (PNFA). OBJECTIVE: The present study tested two hypotheses: 1) PSP and PNFA display impaired single word repetition, object naming, semantic knowledge, and syntactic comprehension; and 2) PSP have reduced speed on timed cognitive tasks. METHODS: Structured clinical and neuropsychological assessments of language were performed on patients with clinically defined PSP and PNFA. Language was tested using the Sydney Language Battery (SYDBAT) and the Test of Reception of Grammar (TROG). RESULTS: In total, 144 participants were studied (PSP 22, PNFA 29, and Control 93). PSP patients had prominent eye movement abnormalities, parkinsonism, and falls. All 4 PSP patients who underwent postmortem examination had 4-Repeat tauopathy, with PSP pathology in 3. The frequency and severity of impairment on the SYDBAT (naming, word comprehension, semantic association), and TROG (syntactic comprehension) did not differ between PSP and PNFA, but PSP were significantly slower on timed non-language cognitive tests. CONCLUSION: Tested formally, aphasia may be seen in PSP, with a severity similar to that seen in PNFA.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Cognition; Female; Humans; Language Tests; Male; Middle Aged; Primary Progressive Nonfluent Aphasia; Semantics; Speech; Supranuclear Palsy, Progressive

Apparent Cognitive Decline as Revealed by an Executive Function Test within a Cohort of Elderly Individuals Self-Reporting Normal Cognitive Performance. - Shea, Thomas B; Remington, Ruth (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) can be preceded by subtle memory decline that can last a decade or more before progressing to what would be diagnosed as the mild cognitive impairment stage. During this early stage of decline, individuals and even their caregivers can fail to perceive any serious difficulty or need to consult a physician. Herein, we present evidence in support of these concerns, and demonstrate how this can interfere not only with clinical trials of AD but also those involving cognitive performance of elderly individuals without intentional reference to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognition; Cognitive Dysfunction; Cohort Studies; Executive Function; Female; Humans; Male; Memory; Neuropsychological Tests; Self Report

An Aspartyl Cathepsin Targeted PET Agent: Application in an Alzheimer's Disease Mouse Model. - Snir, Jonatan A; Suchy, Mojmir; Bindseil, Geron A; Kovacs, Michael; Chronik, Blaine A; Hudson, Robert H E; Pasternak, Stephen H; Bartha, Robert (J Alzheimers Dis, 2018)
BACKGROUND: Early detection of Alzheimer's disease (AD) pathology is a serious challenge for both diagnosis and clinical trials. The aspartyl protease, Cathepsin D (CatD), is overexpressed in AD and could be a biomarker of disease. We have previously designed a unique contrast agent (CA) for dual-optical and magnetic resonance imaging of the activity of the CatD class of enzymes. OBJECTIVE: To compare the uptake and retention of a novel, more sensitive, and clinically-translatable 68Ga PET tracer targeting CatD activity in 5XFAD mice and non-Tg littermates. METHODS: The targeted CA consisted of an HIV-1 Tat cell penetrating peptide (CPP) conjugated to a specialized cleavage sequence targeting aspartyl cathepsins and a DOTA conjugate chelating 68Ga. PET images were acquired using a Siemens Inveon preclinical microPET in female Tg AD mice and non-Tg age matched female littermates (n = 5-8) following intravenous CA administration at 2, 6, and 9 months of age. Additionally, 18F fluorodeoxyglucose (FDG) PET imaging was performed at 10 months to measure glucose uptake. RESULTS: The Tg mice showed significantly higher relative uptake rate of the targeting CA in the forebrain relative to hindbrain at all ages compared to controls, consistent with histology. In contrast, no differences were seen in CA uptake in other organs. Additionally, the Tg mice did not show any differences in relative uptake of FDG at 10 months of age in the forebrain relative to the hindbrain compared to age matched non-Tg controls. CONCLUSIONS: Elevated aspartryl cathepsin activity was detected in vivo in the 5XFAD mouse model of AD using a novel targeted PET contrast agent.
Keywords: Alzheimer Disease; Animals; Brain; Cathepsin D; Contrast Media; Disease Models, Animal; Female; Fluorodeoxyglucose F18; Glucose; Mice; Mice, Transgenic; Positron-Emission Tomography

Assay of Plasma Phosphorylated Tau Protein (Threonine 181) and Total Tau Protein in Early-Stage Alzheimer's Disease. - Yang, Che-Chuan; Chiu, Ming-Jang; Chen, Ta-Fu; Chang, Hui-Ling; Liu, Bing-Hsien; Yang, Shieh-Yueh (J Alzheimers Dis, 2018)
The feasibility of assaying plasma phosphorylated tau protein (threonine 181), denoted p-tau181, using immunomagnetic reduction (IMR) is explored. The reagent for assaying p-tau181 with IMR was synthesized, and its analytic performances were characterized. Seventy-three subjects were recruited. Each participant was examined with neuropsychological tests, magnetic resonance imaging, and IMR assay for plasma p-tau181. Using commercially available IMR kits, the plasma total tau protein (T-tau) of each subject was assayed. The dynamic range for assaying p-tau181 using IMR was 1.96×10-2 pg/ml to 104 pg/ml. There was no significant interference from total tau protein in the assay of p-tau181. The measured concentrations of plasma p-tau181 were 2.46±1.09 pg/ml for healthy controls, 4.41±1.85 pg/ml for MCI due to AD, and 6.14±1.59 pg/ml for very mild AD. Meanwhile, the measured concentrations of plasma T-tau were 18.85±10.16 pg/ml for healthy controls, 32.98±10.18 pg/ml for MCI due to AD, and 37.54±12.29 pg/ml for very mild AD. A significant difference in plasma p-tau181 was observed between healthy controls and MCI due to AD (p < 0.001) and between MCI due to AD and very mild AD (p < 0.001). However, for the plasma T-tau concentration, a significant difference existed only between healthy controls and MCI due to AD (p < 0.001). This implies that the plasma p-tau181 level is correlated more to AD severity than plasma T-tau is. Additionally, p-tau181 was observed as approximately 14% of T-tau in human plasma.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Case-Control Studies; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Phosphorylation; tau Proteins

Assessing Working Memory in Mild Cognitive Impairment with Serial Order Recall. - Emrani, Sheina; Libon, David J; Lamar, Melissa; Price, Catherine C; Jefferson, Angela L; Gifford, Katherine A; Hohman, Timothy J; Nation, Daniel A; Delano-Wood, Lisa; Jak, Amy; Bangen, Katherine J; Bondi, Mark W; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Working memory (WM) is often assessed with serial order tests such as repeating digits backward. In prior dementia research using the Backward Digit Span Test (BDT), only aggregate test performance was examined. OBJECTIVE: The current research tallied primacy/recency effects, out-of-sequence transposition errors, perseverations, and omissions to assess WM deficits in patients with mild cognitive impairment (MCI). METHODS: Memory clinic patients (n = 66) were classified into three groups: single domain amnestic MCI (aMCI), combined mixed domain/dysexecutive MCI (mixed/dys MCI), and non-MCI where patients did not meet criteria for MCI. Serial order/WM ability was assessed by asking participants to repeat 7 trials of five digits backwards. Serial order position accuracy, transposition errors, perseverations, and omission errors were tallied. RESULTS: A 3 (group)×5 (serial position) repeated measures ANOVA yielded a significant group×trial interaction. Follow-up analyses found attenuation of the recency effect for mixed/dys MCI patients. Mixed/dys MCI patients scored lower than non-MCI patients for serial position 3 (p < 0.003) serial position 4 (p < 0.002); and lower than both group for serial position 5 (recency; p < 0.002). Mixed/dys MCI patients also produced more transposition errors than both groups (p < 0.010); and more omissions (p < 0.020), and perseverations errors (p < 0.018) than non-MCI patients. CONCLUSIONS: The attenuation of a recency effect using serial order parameters obtained from the BDT may provide a useful operational definition as well as additional diagnostic information regarding working memory deficits in MCI.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Executive Function; Female; Humans; Male; Memory Disorders; Memory, Short-Term; Mental Recall; Neuropsychological Tests; Regression Analysis; Serial Learning

Association between α-Klotho and Deep White Matter Lesions in the Brain: A Pilot Case Control Study Using Brain MRI. - Kuriyama, Nagato; Ozaki, Etsuko; Mizuno, Toshiki; Ihara, Masafumi; Mizuno, Shigeto; Koyama, Teruhide; Matsui, Daisuke; Watanabe, Isao; Akazawa, Kentaro; Takeda, Kazuo; Takada, Akihiro; Inaba, Masaaki; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The anti-aging protein, α-Klotho, may be involved in cognitive decline and has potential as a surrogate marker that reflects dementia. However, the role of α-Klotho in the brain has not been sufficiently investigated. OBJECTIVE: Here, we investigated the association between α-Klotho and cognitive decline that is associated with cerebral deep white matter lesions (DWMLs). METHODS: Two hundred-eighty participants (187 males and 93 females, mean age: 70.8 years old) were evaluated for DWMLs, and the Fazekas scale (Grade) was assessed following brain magnetic resonance imaging. A questionnaire concerning lifestyle and neuropsychological tests was administered, and their associations with the blood α-Klotho level were retrospectively investigated. RESULTS: The α-Klotho level was 685.1 pg/mL in Grade 0 (68 subjects), 634.1 in G1 (134), 596.0 in G2 (62), and 571.6 in G3 (16), showing that the level significantly decreased with advanced grades. Significant correlations were noted between the α-Klotho level and higher brain function tests including the Mini-Mental State Examination and word fluency tests (p < 0.05). When a 90th percentile value of the level in the G0 group (400 pg/mL) or lower was defined as a low α-Klotho level, the odds ratio of the high-grade G3 group was 2.9 (95% confidence interval: 1.4-7.8) (after correction for age, sex, hypertension, and chronic kidney disease), which was significant. CONCLUSION: A reduced blood α-Klotho level was correlated with grading of cerebral DWMLs and was accompanied by cognitive decline as an independent risk factor. The α-Klotho level may serve as a useful clinical index of vascular cognitive impairment.
Keywords: Aged; Aged, 80 and over; Apolipoprotein E4; Brain; C-Reactive Protein; Case-Control Studies; Cognition Disorders; Female; Glucuronidase; Humans; Image Processing, Computer-Assisted; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Pilot Projects; Severity of Illness Index

Association of Cerebrospinal Fluid (CSF) Insulin with Cognitive Performance and CSF Biomarkers of Alzheimer's Disease. - Geijselaers, Stefan L C; Aalten, Pauline; Ramakers, Inez H G B; De Deyn, Peter Paul; Heijboer, Annemieke C; Koek, Huiberdina L; OldeRikkert, Marcel G M; Papma, Janne M; Reesink, Fransje E; Smits, Lieke L; Stehouwer, Coen D A; Teunissen, Charlotte E; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Abnormal insulin signaling in the brain has been linked to Alzheimer's disease (AD). OBJECTIVE: To evaluate whether cerebrospinal fluid (CSF) insulin levels are associated with cognitive performance and CSF amyloid-β and Tau. Additionally, we explore whether any such association differs by sex or APOE ɛ4 genotype. METHODS: From 258 individuals participating in the Parelsnoer Institute Neurodegenerative Diseases, a nationwide multicenter memory clinic population, we selected 138 individuals (mean age 66±9 years, 65.2% male) diagnosed with subjective cognitive impairment (n = 45), amnestic mild cognitive impairment (n = 44), or AD (n = 49), who completed a neuropsychological assessment, including tests of global cognition and memory performance, and who underwent lumbar puncture. We measured CSF levels of insulin, amyloid-β1-42, total (t-)Tau, and phosphorylated (p-)Tau. RESULTS: CSF insulin levels did not differ between the diagnostic groups (p = 0.136). Across the whole study population, CSF insulin was unrelated to cognitive performance and CSF biomarkers of AD, after adjustment for age, sex, body mass index, diabetes status, and clinic site (all p≥0.131). Importantly, however, we observed effect modification by sex and APOE ɛ4 genotype. Specifically, among women, higher insulin levels in the CSF were associated with worse global cognition (standardized regression coefficient -0.483; p = 0.008) and higher p-Tau levels (0.353; p = 0.040). Among non-carriers of the APOE ɛ4 allele, higher CSF insulin was associated with higher t-Tau (0.287; p = 0.008) and p-Tau (0.246; p = 0.029). CONCLUSION: Our findings provide further evidence for a relationship between brain insulin signaling and AD pathology. It also highlights the need to consider sex and APOE ɛ4 genotype when assessing the role of insulin.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Brain; Cognition Disorders; Female; Humans; Insulin; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptide Fragments; Signal Transduction; tau Proteins

Association of Low-Level Ozone with Cognitive Decline in Older Adults. - Cleary, Ekaterina Galkina; Cifuentes, Manuel; Grinstein, Georges; Brugge, Doug; Shea, Thomas B (J Alzheimers Dis, 2018)
Increasing evidence points to an association of airborne pollutant exposure with respiratory, cardiovascular, and neurological pathology. We examined whether or not ground-level ozone or fine particulate matter ≤ 2.5 μm in diameter (PM2.5) was associated with accelerated cognitive decline. Using repeated measures mixed regression modeling, we analyzed cognitive performance of a geographically diverse sampling of individuals from the National Alzheimer's Coordinating Center between 2004-2008. Ambient air concentrations of ozone and PM2.5 were established using a space-time Hierarchical Bayesian Model that statistically merged air monitor data and modeled air quality estimates. We then compared the ambient regional concentrations of ozone and PM2.5 with the rate of cognitive decline in residents within those regions. Increased levels of ozone correlated with an increased rate of cognitive decline, following adjustment for key individual and community-level risk factors. Furthermore, individuals harboring one or more APOE4 alleles exhibited a faster rate of cognitive decline. The deleterious association of ozone was confined to individuals with normal cognition who eventually became cognitively impaired as opposed to those who entered the study with baseline impairment. In contrast to ozone, we did not observe any correlation between ambient PM2.5 and cognitive decline at regulatory limits set by the Environmental Protection Agency. Our findings suggest that prolonged exposure to ground-level ozone may accelerate cognitive decline during the initial stages of dementia development.
Keywords: Age Distribution; Aged; Aged, 80 and over; Aging; Air Pollutants; Cognitive Dysfunction; Female; Humans; Male; Mental Status and Dementia Tests; Middle Aged; Ozone; Regression Analysis; Retrospective Studies; United States

Association of the New Variant Tyr424Asp at TBK1 Gene with Amyotrophic Lateral Sclerosis and Cognitive Decline. - Piaceri, Irene; Bessi, Valentina; Matà, Sabrina; Polito, Cristina; Tedde, Andrea; Berti, Valentina; Bagnoli, Silvia; Braccia, Arianna; Del Mastio, Monica; Pignone, Alberto Moggi; Pupi, Alberto; Sorbi, Sandro; et al. (J Alzheimers Dis, 2018)
A new risk gene associated with amyotrophic lateral sclerosis (ALS) has recently been identified: the Tank-binding kinase 1 (TBK1) gene. Up to now, 90 TBK1 variants have been described in ALS patients with or without frontotemporal dementia (FTD), thus making TBK1 the third or fourth most frequent genetic cause of ALS and FTD. A point mutation analysis in a cohort of 69 Italian ALS patients was performed in order to analyze the frequency of TBK1 mutations and the correlation with clinical phenotypes. The analysis identified the novel variant p.Tyr424Asp in a patient with a rapid progression of the disease. Our data supports the implication of TBK1 in ALS pathogenesis in Italy.
Keywords: Aged; Amyotrophic Lateral Sclerosis; Aspartic Acid; C9orf72 Protein; Cognitive Dysfunction; DNA Mutational Analysis; Female; Fluorodeoxyglucose F18; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Italy; Male; Mental Status and Dementia Tests; Middle Aged; Mutation; Neuropsychological Tests; Positron-Emission Tomography; Protein-Serine-Threonine Kinases; Tyrosine

Associations between Use of Specific Analgesics and Concentrations of Amyloid-β 42 or Phospho-Tau in Regions of Human Cerebral Cortex. - Flanagan, Margaret E; Larson, Eric B; Walker, Rod L; Keene, C Dirk; Postupna, Nadia; Cholerton, Brenna; Sonnen, Joshua A; Dublin, Sascha; Crane, Paul K; Montine, Thomas J (J Alzheimers Dis, 2018)
Analgesics are commonly used by older adults, raising the question of whether their use might contribute to dementia risk and neuropathologic changes of Alzheimer's disease (AD). The Adult Changes in Thought (ACT) study is a population-based study of brain aging and incident dementia among people 65 years or older who are community dwelling and not demented at entry. Amyloid-β (Aβ)42 and phospho-tau were quantified using Histelide in regions of cerebral cortex from 420 brain autopsies. Total standard daily doses of prescription opioid and non-aspirin nonsteroidal anti-inflammatory drug (NSAID) exposure during a defined 10-year exposure window were identified using automated pharmacy dispensing data and used to classify people as having no/low, intermediate, or high exposure. People with high NSAID exposure had significantly greater Aβ42 concentration in middle frontal gyrus and superior and middle temporal gyri, but not inferior parietal lobule; no Aβ42 regional concentration was associated with prescription opioid usage. People with high opioid usage had significantly greater concentration of phospho-tau in middle frontal gyrus than people with little-to-no opioid usage. Consistent with our previous studies, findings suggest that high levels of NSAID use in older individuals may promote Aβ42 accumulation in cerebral cortex.
Keywords: Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Analgesics; Analgesics, Opioid; Anti-Inflammatory Agents, Non-Steroidal; Autopsy; Cerebral Cortex; Female; Humans; Logistic Models; Male; Peptide Fragments; Prospective Studies; tau Proteins

Associations of Dietary Protein and Fiber Intake with Brain and Blood Amyloid-β. - Fernando, W M A D Binosha; Rainey-Smith, Stephanie R; Gardener, Samantha L; Villemagne, Victor L; Burnham, Samantha C; Macaulay, S Lance; Brown, Belinda M; Gupta, Veer Bala; Sohrabi, Hamid R; Weinborn, Michael; Taddei, Kevin; Laws, Simon M; et al. (J Alzheimers Dis, 2018)
Accumulating evidence suggests a diet high in protein and fiber may confer some protection against Alzheimer's disease (AD). However, no human studies to-date have assessed the relationship between protein and fiber intake, and plasma and brain amyloid-β (Aβ). Consequently, this cross-sectional study, investigated the association of self-reported dietary intakes of protein and fiber, with plasma and brain Aβ burden (n = 541, and n = 162 respectively), in a well-characterized cohort of cognitively normal older adults, drawn from the larger Australian Imaging, Biomarkers and Lifestyle (AIBL) study of aging. We observed 12.59 and 8.43 higher odds of 'high' brain Aβ burden (PiB PET SUVR≥1.5) if protein intake fell in the lowest and middle tertile, respectively, compared to the highest tertile (p = 0.008; p = 0.013). Thus, in this cohort, the more protein consumed, the less likelihood of 'high' Aβ burden in the brain. No other significant associations were observed. The results of this study highlight the potentially protective impact of high dietary protein intake on brain Aβ burden in older adults, before objective memory decline is apparent. While longitudinal validation is required, these findings may assist in the development of dietary approaches aimed at preventing or delaying AD onset.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Australia; Biomarkers; Brain; Cognition; Cohort Studies; Cross-Sectional Studies; Dietary Fiber; Dietary Proteins; Female; Humans; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography

Biallelic Loss of Function of SORL1 in an Early Onset Alzheimer's Disease Patient. - Le Guennec, Kilan; Tubeuf, Hélène; Hannequin, Didier; Wallon, David; Quenez, Olivier; Rousseau, Stéphane; Richard, Anne-Claire; Deleuze, Jean-François; Boland, Anne; Frebourg, Thierry; Gaildrat, Pascaline; Campion, Dominique; et al. (J Alzheimers Dis, 2018)
Heterozygous SORL1 protein truncating variants (PTV) are a strong risk factor for early-onset Alzheimer's disease (EOAD). In case control studies performed at the genome-wide level, PTV definition is usually straightforward. Regarding splice site variants, only those affecting canonical sites are typically included. Some other variants, not annotated as PTV, could, however, affect splicing and hence result in a loss of SORL1 function. We took advantage of the whole exome sequencing data from the 9/484 patients with a previously reported SORL1 PTV in the French EOAD series and searched for a second variant which may affect splicing and eventually result in more than 50% loss of function overall. We found that one patient, known to carry a variant predicted to disrupt the canonical 5' splice site of exon 8, also carried a second novel intronic variant predicted to affect SORL1 splicing of exon 29. Segregation analysis showed that the second variant was located in trans from the known PTV. We performed ex vivo minigene splicing assays and showed that both variants led to the generation of transcripts containing a premature stop codon. This is therefore the first evidence of a human carrying biallelic SORL1 PTV. This patient had a family history of dementia in both maternal and paternal lineages with later ages of onset than the proband himself. However, his 55 years age at onset was in the same ranges as previously published SORL1 heterozygous PTV carriers. This suggests that biallelic loss of SORL1 function is an extremely rare event that was not associated with a dramatically earlier age at onset than heterozygous SORL1 loss-of-function variant carriers, in this single patient.
Keywords: Alzheimer Disease; Case-Control Studies; Female; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Humans; LDL-Receptor Related Proteins; Male; Membrane Transport Proteins; Middle Aged; Risk Factors

Biological Factors Contributing to the Response to Cognitive Training in Mild Cognitive Impairment. - Peter, Jessica; Schumacher, Lena V; Landerer, Verena; Abdulkadir, Ahmed; Kaller, Christoph P; Lahr, Jacob; Klöppel, Stefan (J Alzheimers Dis, 2018)
In mild cognitive impairment (MCI), small benefits from cognitive training were observed for memory functions but there appears to be great variability in the response to treatment. Our study aimed to improve the characterization and selection of those participants who will benefit from cognitive intervention. We evaluated the predictive value of disease-specific biological factors for the outcome after cognitive training in MCI (n = 25) and also considered motivation of the participants. We compared the results of the cognitive intervention group with two independent control groups of MCI patients (local memory clinic, n = 20; ADNI cohort, n = 302). The primary outcome measure was episodic memory as measured by verbal delayed recall of a 10-word list. Episodic memory remained stable after treatment and slightly increased 6 months after the intervention. In contrast, in MCI patients who did not receive an intervention, episodic memory significantly decreased during the same time interval. A larger left entorhinal cortex predicted more improvement in episodic memory after treatment and so did higher levels of motivation. Adding disease-specific biological factors significantly improved the prediction of training-related change compared to a model based simply on age and baseline performance. Bootstrapping with resampling (n = 1000) verified the stability of our finding. Cognitive training might be particularly helpful in individuals with a bigger left entorhinal cortex as individuals who did not benefit from intervention showed 17% less volume in this area. When extended to alternative treatment options, stratification based on disease-specific biological factors is a useful step towards individualized medicine.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Apolipoproteins E; Biological Factors; Cognitive Behavioral Therapy; Cognitive Dysfunction; Entorhinal Cortex; Female; Follow-Up Studies; Functional Laterality; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Mental Recall; Middle Aged; Neuropsychological Tests; Reaction Time; Spatial Navigation; Treatment Outcome

Cardiorespiratory Fitness and White Matter Neuronal Fiber Integrity in Mild Cognitive Impairment. - Ding, Kan; Tarumi, Takashi; Zhu, David C; Tseng, Benjamin Y; Thomas, Binu P; Turner, Marcel; Repshas, Justin; Kerwin, Diana R; Womack, Kyle B; Lu, Hanzhang; Cullum, C Munro; Zhang, Rong (J Alzheimers Dis, 2018)
BACKGROUND: Mounting evidence showed the self-reported levels of physical activity are positively associated with white matter (WM) integrity and cognitive performance in normal adults and patients with mild cognitive impairment (MCI). However, the objective measure of cardiorespiratory fitness (CRF) was not used in these studies. OBJECTIVE: To determine the associations of CRF measured by maximal oxygen uptake (VO2max) with WM fiber integrity and neurocognitive performance in older adults with MCI. METHODS: Eighty-one participants (age = 65±7 years, 43 women), including 26 cognitively normal older adults and 55 amnestic MCI patients, underwent VO2max test to measure CRF, diffusion tensor imaging (DTI) to assess WM fiber integrity, and neurocognitive assessment focused on memory and executive function. DTI data were analyzed by the tract-based spatial statistics and region-of-interest approach. RESULTS: Cognitively normal older adults and MCI patients were not different in global WM fiber integrity and VO2max. VO2max was associated positively with DTI metrics of fractional anisotropy in ∼54% WM fiber tracts, and negatively with mean and radial diffusivities in ∼46% and ∼56% of the WM fiber tracts. The associations of VO2max with DTI metrics remained statistically significant after adjustment of age, sex, body mass index, WM lesion burden, and MCI status. The DTI metrics obtained from the area that correlated to VO2max were associated with executive function performance in MCI patients. CONCLUSIONS: Higher levels of CRF are associated with better WM fiber integrity, which in turn is correlated with better executive function performance in MCI patients.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Anisotropy; Cardiorespiratory Fitness; Case-Control Studies; Cognition; Cognitive Dysfunction; Diffusion Tensor Imaging; Executive Function; Female; Humans; Linear Models; Male; Memory; Middle Aged; Nerve Fibers, Myelinated; Neuropsychological Tests; Texas; White Matter

Cerebrospinal Fluid C-C Motif Chemokine Ligand 2 Correlates with Brain Atrophy and Cognitive Impairment in Alzheimer's Disease. - Kimura, Akio; Yoshikura, Nobuaki; Hayashi, Yuichi; Inuzuka, Takashi (J Alzheimers Dis, 2018)
BACKGROUND: Chronic neuroinflammation has been implicated in Alzheimer's disease (AD) pathology. OBJECTIVE: To investigate the association between cytokine and anti-amyloid-β (Aβ) autoantibody levels and the degree of brain atrophy and cognitive impairment in AD patients. METHODS: Cerebrospinal fluid (CSF) levels of C-C motif chemokine ligand 2 (CCL2), C-X-C motif chemokine ligand 8, C-X-C motif chemokine ligand 10, interleukin 6, and anti-Aβ autoantibody were evaluated in 69 AD patients. Serum levels of CCL2 and anti-Aβ autoantibody were also examined. The degree of brain atrophy was assessed using the voxel-based specific regional analysis system for AD, which targets the volumes of interest (VOI) in medial temporal structures. Cognitive function was evaluated by neuropsychological testing, including the Mini-Mental State Examination (MMSE) and Frontal Assessment Battery (FAB). RESULTS: CSF CCL2 levels correlated significantly with the severity (p = 0.023) and the extent (p = 0.022) of VOI atrophy, and with the extent of gray matter atrophy (p = 0.039) in AD patients. CSF anti-Aβ autoantibody levels were inversely correlated with the severity of VOI atrophy (p = 0.020), the extent of VOI atrophy (p = 0.015), and the ratio of VOI/GM atrophy (r = -0.358, p = 0.004). CSF CCL2 levels were also inversely correlated with MMSE (p = 0.0497) and FAB scores (p = 0.016). CONCLUSIONS: CSF CCL2 levels are associated with the degree of medial temporal lobe and gray matter atrophy, and cognitive decline in AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Atrophy; Biomarkers; Chemokine CCL2; Cognitive Dysfunction; Disease Progression; Female; Gray Matter; Humans; Linear Models; Magnetic Resonance Imaging; Male; Neuropsychological Tests; tau Proteins; Temporal Lobe

Cerebrospinal Fluid, MRI, and Florbetaben-PET in Cerebral Amyloid Angiopathy-Related Inflammation. - Renard, Dimitri; Collombier, Laurent; Demattei, Christophe; Wacongne, Anne; Charif, Mahmoud; Ayrignac, Xavier; Azakri, Souhayla; Gaillard, Nicolas; Boudousq, Vincent; Lehmann, Sylvain; Menjot de Champfleur, Nicolas; Thouvenot, Eric (J Alzheimers Dis, 2018)
BACKGROUND: Cerebral amyloid angiopathy-related inflammation (CAA-ri) is associated with a cerebrospinal fluid (CSF) biomarker profile similar to that observed in CAA. Few CAA-ri patients have been studied by fibrillar amyloid-β (Aβ) imaging (using 11C-Pittsburgh compound B and 18F-florbetapir, but not 18F-florbetaben). OBJECTIVE: To describe CSF biomarkers, magnetic resonance imaging (MRI), and 18F-florbetaben (FBB)-positron emission tomography (PET) changes in CAA-ri patients. METHODS: CSF levels of total tau, phosphorylated tau, Aβ1-42, and Aβ1-40, MRI (cerebral microbleeds count on susceptibility-weighted imaging and semi-quantitative analysis of fluid-attenuation inversion recovery white matter hyperintensities), and FBB-PET (using both cerebellar cortex and pons to calculate standardized uptake value ratios) were analyzed in nine consecutive CAA-ri patients. RESULTS: A median number of 769 cerebral microbleeds/patient were counted on MRI. When using the pons as reference region, amyloid load on FBB-PET was very strongly correlated to CSF Aβ1-40 levels (rho = -0.83, p = 0.008) and moderately correlated to cerebral microbleed numbers in the occipital lobes (rho = 0.59, p = 0.001), while comparisons with other CSF biomarkers were not statistically significant (total tau, rho = -0.63, p = 0.076; phosphorylated tau, rho = -0.68, p = 0.05; Aβ1-42, rho = -0.59, p = 0.09). All correlations were weaker, and not statistically significant, when using the cerebellum as reference region. A non-significant correlation (rho = -0.50, p = 0.18) was observed between CSF Aβ1-40 levels and cerebral microbleed numbers. CONCLUSION: In CAA-ri, CSF Aβ1-40 levels correlated well with amyloid load assessed by FBB-PET when the pons was used as reference, and to a lesser degree with cerebral microbleeds count on MRI. This confirms earlier data on CSF Aβ1-40 as an in vivo marker for CAA and CAA-ri.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Aniline Compounds; Biomarkers; Brain; Cerebral Amyloid Angiopathy; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Multivariate Analysis; Positron-Emission Tomography; Prospective Studies; Stilbenes; tau Proteins; Vasculitis, Central Nervous System

Characteristics of Cognitively Normal Mexican-Americans with Cognitive Complaints. - Hall, James R; Wiechmann, April; Johnson, Leigh A; Edwards, Melissa; O'Bryant, Sid E (J Alzheimers Dis, 2018)
BACKGROUND: Subjective cognitive complaints in cognitively normal adults have been linked to later cognitive decline and dementia. Research on the characteristics of this group has been conducted on a variety of clinical and community-based populations. The current study focuses on the rapidly expanding population of Mexican-American elders. OBJECTIVE: The objective of the study is the determination of characteristics of cognitively normal Mexican-Americans with cognitive complaints. METHODS: Data on 319 cognitively normal participants in a large-scale community-based study of elderly Mexican-Americans (HABLE) were analyzed comparing those with cognitive complaints with those without on clinical characteristics, affective status, neuropsychological functioning, and proteomic markers. RESULTS: Those expressing concern about cognitive decline scored lower on the MMSE, were more likely to have significantly more affective symptoms, higher levels of diabetic markers, poorer performance on attention and executive functioning, and a different pattern of inflammatory markers. CONCLUSION: Although longitudinal research is needed to determine the impact of these differences on later cognition, possible targets for early intervention with Mexican-Americans were identified.
Keywords: Aged; Biomarkers; Cognition; Cognitive Dysfunction; Executive Function; Female; Humans; Male; Mexican Americans; Middle Aged; Neuropsychological Tests; Risk Factors; Texas

Circulating Progenitor Cells Correlate with Memory, Posterior Cortical Thickness, and Hippocampal Perfusion. - Nation, Daniel A; Tan, Alick; Dutt, Shubir; McIntosh, Elissa C; Yew, Belinda; Ho, Jean K; Blanken, Anna E; Jang, Jung Yun; Rodgers, Kathleen E; Gaubert, Aimée (J Alzheimers Dis, 2018)
BACKGROUND: Bone marrow-derived progenitor cells survey the vasculature and home to sites of tissue injury where they can promote repair and regeneration. It has been hypothesized that these cells may play a protective role neurodegenerative and vascular cognitive impairment. OBJECTIVE: To evaluate progenitor cell levels in older adults with and without mild cognitive impairment (MCI), and to relate circulating levels to memory, brain volume, white matter lesion volume, and cerebral perfusion. METHOD: Thirty-two older adults, free of stroke and cardiovascular disease, were recruited from the community and evaluated for diagnosis of MCI versus cognitively normal (CN). Participants underwent brain MRI and blood samples were taken to quantify progenitor reserve using flow cytometry (CD34+, CD34+CD133+, and CD34+CD133+CD309+ cells). RESULTS: Participants with MCI (n = 10) exhibited depletion of all CPC markers relative to those who were CN (n = 22), after controlling for age, sex, and education. Post-hoc age, sex, and education matched comparisons (n = 10 MCI, n = 10 CN) also revealed the same pattern of results. Depletion of CD34+ cells correlated with memory performance, left posterior cortical thickness, and bilateral hippocampal perfusion. Participants exhibited low levels of vascular risk and white matter lesion burden that did not correlate with progenitor levels. CONCLUSIONS: Circulating progenitor cells are associated with cognitive impairment, memory, cortical atrophy, and hippocampal perfusion. We hypothesize that progenitor depletion contributes to, or is triggered by, cognitive decline and cortical atrophy. Further study of progenitor cell depletion in older adults may benefit efforts to prevent or delay dementia.
Keywords: Aged; Aged, 80 and over; Antigens, CD; Apolipoproteins E; Cerebral Cortex; Cognitive Dysfunction; Female; Flow Cytometry; Hippocampus; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Perfusion; Stem Cells; White Matter

Clinical Trials for Disease-Modifying Therapies in Alzheimer's Disease: A Primer, Lessons Learned, and a Blueprint for the Future. - Cummings, Jeffrey; Ritter, Aaron; Zhong, Kate (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) has no currently approved disease-modifying therapies (DMTs), and treatments to prevent, delay the onset, or slow the progression are urgently needed. A delay of 5 years if available by 2025 would decrease the total number of patients with AD by 50% in 2050. To meet the definition of DMT, an agent must produce an enduring change in the course of AD; clinical trials of DMTs have the goal of demonstrating this effect. AD drug discovery entails target identification followed by high throughput screening and lead optimization of drug-like compounds. Once an optimized agent is available and has been assessed for efficacy and toxicity in animals, it progresses through Phase I testing with healthy volunteers, Phase II learning trials to establish proof-of-mechanism and dose, and Phase III confirmatory trials to demonstrate efficacy and safety in larger populations. Phase III is followed by Food and Drug Administration review and, if appropriate, market access. Trial populations include cognitively normal at-risk participants in prevention trials, mildly impaired participants with biomarker evidence of AD in prodromal AD trials, and subjects with cognitive and functional impairment in AD dementia trials. Biomarkers are critical in trials of DMTs, assisting in participant characterization and diagnosis, target engagement and proof-of-pharmacology, demonstration of disease-modification, and monitoring side effects. Clinical trial designs include randomized, parallel group; delayed start; staggered withdrawal; and adaptive. Lessons learned from completed trials inform future trials and increase the likelihood of success.
Keywords: Alzheimer Disease; Animals; Clinical Trials as Topic; Humans

A Clinically-Translatable Machine Learning Algorithm for the Prediction of Alzheimer's Disease Conversion in Individuals with Mild and Premild Cognitive Impairment. - Grassi, Massimiliano; Perna, Giampaolo; Caldirola, Daniela; Schruers, Koen; Duara, Ranjan; Loewenstein, David A (J Alzheimers Dis, 2018)
BACKGROUND: Available therapies for Alzheimer's disease (AD) can only alleviate and delay the advance of symptoms, with the greatest impact eventually achieved when provided at an early stage. Thus, early identification of which subjects at high risk, e.g., with MCI, will later develop AD is of key importance. Currently available machine learning algorithms achieve only limited predictive accuracy or they are based on expensive and hard-to-collect information. OBJECTIVE: The current study aims to develop an algorithm for a 3-year prediction of conversion to AD in MCI and PreMCI subjects based only on non-invasively and effectively collectable predictors. METHODS: A dataset of 123 MCI/PreMCI subjects was used to train different machine learning techniques. Baseline information regarding sociodemographic characteristics, clinical and neuropsychological test scores, cardiovascular risk indexes, and a visual rating scale for brain atrophy was used to extract 36 predictors. Leave-pair-out-cross-validation was employed as validation strategy and a recursive feature elimination procedure was applied to identify a relevant subset of predictors. RESULTS: 16 predictors were selected from all domains excluding sociodemographic information. The best model resulted a support vector machine with radial-basis function kernel (whole sample: AUC = 0.962, best balanced accuracy = 0.913; MCI sub-group alone: AUC = 0.914, best balanced accuracy = 0.874). CONCLUSIONS: Our algorithm shows very high cross-validated performances that outperform the vast majority of the currently available algorithms, and all those which use only non-invasive and effectively assessable predictors. Further testing and optimization in independent samples will warrant its application in both clinical practice and clinical trials.
Keywords: Aged; Aged, 80 and over; Algorithms; Alzheimer Disease; Area Under Curve; Atrophy; Brain; Cognitive Dysfunction; Disease Progression; Female; Humans; Logistic Models; Machine Learning; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Predictive Value of Tests; Prognosis; Regression Analysis; Sensitivity and Specificity; Support Vector Machine

Clinic-Based Validation of Cerebrospinal Fluid Biomarkers with Florbetapir PET for Diagnosis of Dementia. - Álvarez, Ignacio; Aguilar, Miquel; González, Jose Manuel; Ysamat, Montse; Lorenzo-Bosquet, Carles; Alonso, Alvaro; Tartari, Juan Pablo; Romero, Silvia; Diez-Fairen, Monica; Carcel, Maria; Pujalte, Francisco; Pastor, Pau (J Alzheimers Dis, 2018)
BACKGROUND: Cerebrospinal fluid (CSF) biomarker studies have shown variable accuracy for diagnosis of Alzheimer's disease (AD); therefore, internal validation is recommended. OBJECTIVE: To investigate the correlation between CSF biomarkers and cerebral 18-Florbetapir positron emission tomography (Amyloid-PET) and calculate their sensitivity and specificity to obtain the optimal clinical cut-off points to diagnose the etiology of cognitive impairment. METHODS: We performed Amyloid-PET scans and CSF biomarker levels analyses in 68 subjects (50 with mild cognitive impairment, 11 with AD dementia, and 7 with non-AD dementia). Visual examination of Amyloid-PET scans was performed. CSF analyses were performed using standard sandwich ELISA. RESULTS: Amyloid-PET was positive in 36 subjects, negative in 26, and inconclusive in 6. Optimal clinical cut-off points for CSF markers were the following: amyloid-β 1-42 (Aβ42) = 629 pg/ml, total tau (t-tau) = 532 pg/ml, phosphorylated tau (p-tau) = 88 pg/ml, and t-tau/Aβ42 ratio = 0.58. T-tau/Aβ42 ratio showed the best sensitivity and specificity (92 and 84%, respectively). T-tau and p-tau CSF levels (r2 = 0.867) followed by the t-tau and t-tau/Aβ42 CSF ratio (r2 = 0.666) showed the strongest inter-marker correlation. Interestingly, subjects with inconclusive Amyloid-PET showed intermediate values for all CSF markers between negative and positive Amyloid-PET groups. CONCLUSIONS: CSF t-tau/Aβ42 ratio appears to be the most accurate AD CSF marker. The presence of intermediate values for CSF markers among the subjects with inconclusive Amyloid-PET suggests the presence of other dementias associated with AD pathology or intermediate phenotypes.
Keywords: Aged; Amyloid beta-Peptides; Analysis of Variance; Aniline Compounds; Apolipoproteins E; Biomarkers; Cognition Disorders; Dementia; Ethylene Glycols; Female; Humans; Male; Middle Aged; Peptide Fragments; Positron-Emission Tomography; tau Proteins

Co-Expression of Glia Maturation Factor and Apolipoprotein E4 in Alzheimer's Disease Brain. - Thangavel, Ramasamy; Bhagavan, Sachin M; Ramaswamy, Swathi Beladakere; Surpur, Spurthi; Govindarajan, Raghav; Kempuraj, Duraisamy; Zaheer, Smita; Raikwar, Sudhanshu; Ahmed, Mohammad E; Selvakumar, Govindhasamy Pushpavathi; Iyer, Shankar S; Zaheer, Asgar (J Alzheimers Dis, 2018)
Apolipoprotein E4 (ApoE4) is a major genetic risk factor for Alzheimer's disease (AD). The E4 allele of ApoE plays a crucial role in the inflammatory and neurodegenerative processes associated with AD. This is evident from the multiple effects of the ApoE isoforms in amyloid-β (Aβ) aggregation. Glia maturation factor (GMF) is a brain-specific neuroinflammatory protein that we have previously demonstrated to be significantly upregulated in various regions of AD brains compared to non-AD control brains and that it induces neurodegeneration. We have previously reported that GMF is predominantly expressed in the reactive astrocytes surrounding amyloid plaques (APs) in AD brain. In the present study, using immunohistochemical and dual immunofluorescence staining, we show the expression and colocalization of GMF and ApoE4 in AD brains. Our results show that ApoE4 is present within the APs of AD brain. Further, we found that GMF and ApoE4 were strongly expressed and co-associated in APs and in the reactive astrocytes surrounding APs in AD. An increased expression of GMF in APs and neurofibrillary tangles in the AD brain, and the co-localization of GMF and ApoE4 in APs suggest that GMF and ApoE4 together should be contributing to the neuropathological changes associated with AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Brain; Case-Control Studies; Fluorescent Antibody Technique; Glia Maturation Factor; Humans; Neurofibrillary Tangles; Plaque, Amyloid

Cognitive Decline in Preclinical Alzheimer's Disease: Amyloid-Beta versus Tauopathy. - Huber, Colin M; Yee, Connor; May, Taylor; Dhanala, Apoorva; Mitchell, Cassie S (J Alzheimers Dis, 2018)
We perform a large-scale meta-analysis of 51 peer-reviewed 3xTg-AD mouse publications to compare Alzheimer's disease (AD) quantitative clinical outcome measures, including amyloid-β (Aβ), total tau, and phosphorylated tau (pTau), with cognitive performance in Morris water maze (MWM) and Novel Object Recognition (NOR). "High" levels of Aβ (Aβ40, Aβ42) showed significant but weak trends with cognitive decline (MWM: slope = 0.336, R2 = 0.149, n = 259, p < 0.001; NOR: slope = 0.156, R2 = 0.064, n = 116, p < 0.05); only soluble Aβ or directly measured Aβ meaningfully contribute. Tau expression in 3xTg-AD mice was within 10-20% of wild type and not associated with cognitive decline. In contrast, increased pTau is directly and significantly correlated with cognitive decline in MWM (slope = 0.408, R2 = 0.275, n = 371, p < < 0.01) and NOR (slope = 0.319, R2 = 0.176, n = 113, p < 0.05). While a variety of pTau epitopes (AT8, AT270, AT180, PHF-1) were examined, AT8 correlated most strongly with cognition (slope = 0.586, R2 = 0.521, n = 185, p < < 0.001). Multiple linear regression confirmed pTau is a stronger predictor of MWM performance than Aβ. Despite pTau's lower physical concentration than Aβ, pTau levels more directly and quantitatively correlate with 3xTg-AD cognitive decline. pTau's contribution to neurofibrillary tangles well after Aβ levels plateau makes pTau a viable treatment target even in late-stage clinical AD. Principal component analysis, which included hyperphosphorylation induced by kinases (pGSK3β, GSK3β, CDK5), identified phosphorylated ser9 GSK3β as the primary contributor to MWM variance. In summary, meta-analysis of cognitive decline in preclinical AD finds tauopathy more impactful than Aβ. Nonetheless, complex AD interactions dictate successful therapeutics harness synergy between Aβ and pTau, possibly through the GSK3 pathway.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Cognitive Dysfunction; Disease Models, Animal; Maze Learning; Mice; Reaction Time; Recognition (Psychology); tau Proteins

Cognitive Variability Predicts Incident Alzheimer's Disease and Mild Cognitive Impairment Comparable to a Cerebrospinal Fluid Biomarker. - Gleason, Carey E; Norton, Derek; Anderson, Eric D; Wahoske, Michelle; Washington, Danielle T; Umucu, Emre; Koscik, Rebecca L; Dowling, N Maritza; Johnson, Sterling C; Carlsson, Cynthia M; Asthana, Sanjay (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) biomarkers are emerging as critically important for disease detection and monitoring. Most biomarkers are obtained through invasive, resource-intense procedures. A cognitive marker, intra-individual cognitive variability (IICV) may provide an alternative or adjunct marker of disease risk for individuals unable or disinclined to undergo lumbar puncture. OBJECTIVE: To contrast risk of incident AD and mild cognitive impairment (MCI) associated with IICV to risk associated with well-established biomarkers: cerebrospinal fluid (CSF) phosphorylated tau protein (p-tau181) and amyloid-β 42 (Aβ42) peptide. METHODS: Dispersion in cognitive performance, IICV, was estimated with a published algorithm, and included Trail Making Test A and B, Rey Auditory Verbal Learning Test (RAVLT), and the American National Adult Reading Test (ANART). CSF biomarkers were expressed as a ratio: p-tau181/Aβ42, wherein high values signified pathognomonic profiles. Logistic regression models included longitudinal data from 349 Alzheimer's Disease Neuroimaging Initiative (ADNI) participants who completed lumbar puncture. All subjects were cognitively healthy (n = 105) or diagnosed with MCI (n = 244) at baseline. We examined odds of conversion associated with baseline elevations in IICV and/or ratio of CSF p-tau181/Aβ42. RESULTS: When included in models alone or in combination with CSF p-tau181/Aβ42, one standard IICV unit higher was associated with an estimated odds ratio for incident AD or MCI of 2.81 (95% CI: 1.83-4.33) in the most inclusive sample, and an odds ratio of 3.41 (95% CI: 2.03-5.73) when restricted to participants with MCI. Iterative analyses suggested that IICV independently improved model fit even when individual index components were included in comparative models. CONCLUSIONS: These analyses provide preliminary support for IICV as a marker of incident AD and MCI. This easily-disseminated, non-invasive marker compared favorably to well-established CSF biomarkers.
Keywords: Aged; Aged, 80 and over; Algorithms; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Cross-Sectional Studies; Female; Humans; Incidence; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Peptide Fragments; Statistics, Nonparametric; tau Proteins

Combined Socio-Behavioral Evaluation Improves the Differential Diagnosis Between the Behavioral Variant of Frontotemporal Dementia and Alzheimer's Disease: In Search of Neuropsychological Markers. - Dodich, Alessandra; Cerami, Chiara; Cappa, Stefano F; Marcone, Alessandra; Golzi, Valeria; Zamboni, Michele; Giusti, Maria Cristina; Iannaccone, Sandro (J Alzheimers Dis, 2018)
BACKGROUND: Current diagnostic criteria for behavioral variant of frontotemporal dementia (bvFTD) and typical Alzheimer's disease (AD) include a differential pattern of neuropsychological impairments (episodic memory deficit in typical AD and dysexecutive syndrome in bvFTD). There is, however, large evidence of a frequent overlap in neuropsychological features, making the differential diagnosis extremely difficult. OBJECTIVES: In this retrospective study, we evaluated the diagnostic value of different cognitive and neurobehavioral markers in bvFTD and AD patient groups. METHODS: We included 95 dementia patients with a clinical and biomarker evidence of bvFTD (n = 48) or typical AD (n = 47) pathology. A clinical 2-year follow-up confirmed clinical classification. Performances at basic cognitive tasks (memory, executive functions, visuo-spatial, language) as well as social cognition skills and neurobehavioral profiles have been recorded. A stepwise logistic regression model compared the neuropsychological profiles between groups and assessed the accuracy of cognitive and neurobehavioral markers in discriminating bvFTD from AD. RESULTS: Statistical comparison between patient groups proved social cognition and episodic memory impairments as main cognitive signatures of bvFTD and AD neuropsychological profiles, respectively. Only half of bvFTD patients showed attentive/executive deficits, questioning their role as cognitive marker of bvFTD. Notably, the large majority of bvFTD sample (i.e., 70%) poorly performed at delayed recall tasks. Logistic regression analysis identified social cognition performances, Frontal Behavioral Inventory and Mini-Mental State Examination scores as the best combination in distinguishing bvFTD from AD. CONCLUSION: Social cognition tasks and socio-behavioral questionnaires are recommended in clinical settings to improve the accuracy of early diagnosis of bvFTD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Cognition; Diagnosis, Differential; Female; Frontotemporal Dementia; Humans; Logistic Models; Male; Memory, Episodic; Mental Recall; Middle Aged; Neuropsychological Tests; Retrospective Studies; Social Skills

Comparison between FCSRT and LASSI-L to Detect Early Stage Alzheimer's Disease. - Matías-Guiu, Jordi A; Cabrera-Martín, María Nieves; Curiel, Rosie E; Valles-Salgado, María; Rognoni, Teresa; Moreno-Ramos, Teresa; Carreras, José Luis; Loewenstein, David A; Matías-Guiu, Jorge (J Alzheimers Dis, 2018)
BACKGROUND: The Free and Cued Selective Reminding Test (FCSRT) is the most accurate test for the diagnosis of prodromal Alzheimer's disease (AD). Recently, a novel cognitive test, the Loewenstein-Acevedo Scale for Semantic Interference and Learning (LASSI-L), has been developed in order to provide an early diagnosis. OBJECTIVE: To compare the diagnostic accuracy of the FCSRT and the LASSI-L for the diagnosis of AD in its preclinical and prodromal stages using 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) as a reference. METHODS: Fifty patients consulting for subjective memory complaints without functional impairment and at risk for AD were enrolled and evaluated using FCSRT, LASSI-L, and FDG-PET. Participants were evaluated using a comprehensive neurological and neuropsychological protocol and were assessed with the FCSRT and LASSI-L. FDG-PET was acquired concomitantly and used for classification of patients as AD or non-AD according to brain metabolism using both visual and semi-quantitative methods. RESULTS: LASSI-L scores allowed a better classification of patients as AD/non-AD in comparison to FCSRT. Logistic regression analysis showed delayed recall and failure to recovery from proactive semantic interference from LASSI-L as independent statistically significant predictors, obtaining an area under the curve of 0.894. This area under the curve provided a better discrimination than the best FCSRT score (total delayed recall, area under the curve 0.708, p = 0.029). CONCLUSIONS: The LASSI-L, a cognitive stress test, was superior to FCSRT in the prediction of AD features on FDG-PET. This emphasizes the possibility to advance toward an earlier diagnosis of AD from a clinical perspective.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cues; Female; Fluorodeoxyglucose F18; Humans; Male; Memory Disorders; Mental Recall; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography; Psychiatric Status Rating Scales; ROC Curve; Semantics

Concordance Between Cerebrospinal Fluid Biomarkers with Alzheimer's Disease Pathology Between Three Independent Assay Platforms. - Doecke, James D; Rembach, Alan; Villemagne, Victor L; Varghese, Shiji; Rainey-Smith, Stephanie; Sarros, Shannon; Evered, Lisbeth A; Fowler, Christopher J; Pertile, Kelly K; Rumble, Rebecca L; Trounson, Brett; Taddei, Kevin; et al. (J Alzheimers Dis, 2018)
BACKGROUND: To enhance the accuracy of clinical diagnosis for Alzheimer's disease (AD), pre-mortem biomarkers have become increasingly important for diagnosis and for participant recruitment in disease-specific treatment trials. Cerebrospinal fluid (CSF) biomarkers provide a low-cost alternative to positron emission tomography (PET) imaging for in vivo quantification of different AD pathological hallmarks in the brains of affected subjects; however, consensus around the best platform, most informative biomarker and correlations across different methodologies are controversial. OBJECTIVE: Assessing levels of Aβ-amyloid and tau species determined using three different versions of immunoassays, the current study explored the ability of CSF biomarkers to predict PET Aβ-amyloid (32 Aβ-amyloid-and 45 Aβ-amyloid+), as well as concordance between CSF biomarker levels and PET Aβ-amyloid imaging. METHODS: Prediction and concordance analyses were performed using a sub-cohort of 77 individuals (48 healthy controls, 15 with mild cognitive impairment, and 14 with AD) from the Australian Imaging Biomarker and Lifestyle study of aging. RESULTS: Across all three platforms, the T-tau/Aβ42 ratio biomarker had modestly higher correlation with SUVR/BeCKeT (ρ= 0.69-0.8) as compared with Aβ42 alone (ρ= 0.66-0.75). Differences in CSF biomarker levels between the PET Aβ-amyloid-and Aβ-amyloid+ groups were strongest for the Aβ42/Aβ40 and T-tau/Aβ42 ratios (p < 0.0001); however, comparison of predictive models for PET Aβ-amyloid showed no difference between Aβ42 alone and the T-tau/Aβ42 ratio. CONCLUSION: This study confirms strong concordance between CSF biomarkers and PET Aβ-amyloid status is independent of immunoassay platform, supporting their utility as biomarkers in clinical practice for the diagnosis of AD and for participant enrichment in clinical trials.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognition Disorders; Female; Humans; Male; Mental Status Schedule; Peptide Fragments; Positron-Emission Tomography; ROC Curve; tau Proteins

Delirium Severity Post-Surgery and its Relationship with Long-Term Cognitive Decline in a Cohort of Patients without Dementia. - Vasunilashorn, Sarinnapha M; Fong, Tamara G; Albuquerque, Asha; Marcantonio, Edward R; Schmitt, Eva M; Tommet, Douglas; Gou, Yun; Travison, Thomas G; Jones, Richard N; Inouye, Sharon K (J Alzheimers Dis, 2018)
BACKGROUND: Delirium has been associated with more rapid cognitive decline. However, it is unknown whether increased delirium severity is associated with a higher rate of long-term cognitive decline. OBJECTIVE: To evaluate delirium severity and the presence and rate of cognitive decline over 36 months following surgery. METHODS: We examined patients from the Successful Aging after Elective Surgery Study, who were age ≥70 years undergoing major elective surgery (N = 560). Delirium severity was determined by the peak Confusion Assessment Method-Severity (CAM-S) score for each patient's hospitalization and grouped based on the sample distribution: scores of 0-2, 3-7, and 8-19. A neuropsychological composite, General Cognitive Performance (GCP), and proxy-reported Informant Questionnaire for Cognitive Decline (IQCODE) were used to examine cognitive outcomes following surgery at 0, 1, and 2 months, and then every 6 months for up to 3 years. RESULTS: No significant cognitive decline was observed for patients with peak CAM-S scores 0-2 (-0.17 GCP units/year, 95% confidence interval [CI] -0.35, 0.01). GCP scores decreased significantly in the group with peak CAM-S scores 3-7 (-0.30 GCP units/year, 95% CI -0.51, -0.09), and decreased almost three times faster in the highest delirium severity group (peak CAM-S scores 8-19; -0.82 GCP units/year, 95% CI -1.28, -0.37). A similar association was found for delirium severity and the proportion of patients who developed IQCODE impairment over time. CONCLUSION: Patients with the highest delirium severity experienced the greatest rate of cognitive decline, which exceeds the rate previously observed for patients with dementia, on serial neuropsychological testing administered over 3 years, with a dose-response relationship between delirium severity and long-term cognitive decline.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Cohort Studies; Delirium; Elective Surgical Procedures; Female; Humans; Male; Neuropsychological Tests; Postoperative Complications; Severity of Illness Index

Designing an Internet-Based Multidomain Intervention for the Prevention of Cardiovascular Disease and Cognitive Impairment in Older Adults: The HATICE Trial. - Barbera, Mariagnese; Mangialasche, Francesca; Jongstra, Susan; Guillemont, Juliette; Ngandu, Tiia; Beishuizen, Cathrien; Coley, Nicola; Brayne, Carol; Andrieu, Sandrine; Richard, Edo; Soininen, Hilkka; Kivipelto, Miia (J Alzheimers Dis, 2018)
BACKGROUND: Many dementia and cardiovascular disease (CVD) cases in older adults are attributable to modifiable vascular and lifestyle-related risk factors, providing opportunities for prevention. In the Healthy Aging Through Internet Counselling in the Elderly (HATICE) randomized controlled trial, an internet-based multidomain intervention is being tested to improve the cardiovascular risk (CVR) profile of older adults. OBJECTIVE: To design a multidomain intervention to improve CVR, based on the guidelines for CVR management, and administered through a coach-supported, interactive, platform to over 2500 community-dwellers aged 65+ in three European countries. METHODS: A comparative analysis of national and European guidelines for primary and secondary CVD prevention was performed. Results were used to define the content of the intervention. RESULTS: The intervention design focused on promoting awareness and self-management of hypertension, dyslipidemia, diabetes mellitus, and overweight, and supporting smoking cessation, physical activity, and healthy diet. Overall, available guidelines lacked specific recommendations for CVR management in older adults. The comparative analysis of the guidelines showed general consistency for lifestyle-related recommendations. Key differences, identified mostly in methods used to assess the overall CVR, did not hamper the intervention design. Minor country-specific adaptations were implemented to maximize the intervention feasibility in each country. CONCLUSION: Despite differences in CVR management within the countries considered, it was possible to design and implement the HATICE multidomain intervention. The study can help define preventative strategies for dementia and CVD that are applicable internationally.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cognitive Dysfunction; Counseling; Europe; Exercise; Female; Healthy Aging; Humans; Internet; Life Style; Male; Practice Guidelines as Topic; Risk Factors; Telemedicine

Detection of Dementia Cases in Two Swedish Health Registers: A Validation Study. - Rizzuto, Debora; Feldman, Adina L; Karlsson, Ida K; Dahl Aslan, Anna K; Gatz, Margaret; Pedersen, Nancy L (J Alzheimers Dis, 2018)
BACKGROUND: Population-based health registers are potential assets in epidemiological research; however, the quality of case ascertainment is crucial. OBJECTIVE: To compare the case ascertainment of dementia, from the National Patient Register (NPR) and the Cause of Death Register (CDR) with dementia diagnoses from six Swedish population based studies. METHODS: Sensitivity, specificity, and positive predictive value (PPV) of dementia identification in NPR and CDR were estimated by individual record linkage with six Swedish population based studies (n = 19,035). Time to detection in NPR was estimated using data on dementia incidence from longitudinal studies with more than two decades of follow-up. RESULTS: Barely half of the dementia cases were ever detected by NPR or CDR. Using data from longitudinal studies we estimated that a record with a dementia diagnosis appears in the NPR on average 5.5 years after first diagnosis. Although the ability of the registers to detect dementia cases was moderate, the ability to detect non-dementia cases was almost perfect (99%). When registers indicate that there is a dementia diagnosis, there are very few instances in which the clinicians determined the person was not demented. Indeed, PPVs were close to 90%. However, misclassification between dementia subtype diagnoses is quite common, especially in NPR. CONCLUSIONS: Although the overall sensitivity is low, the specificity and the positive predictive value are very high. This suggests that hospital and death registers can be used to identify dementia cases in the community, but at the cost of missing a large proportion of the cases.
Keywords: Aged; Aged, 80 and over; Cause of Death; Dementia; Female; Humans; Incidence; Longitudinal Studies; Male; Middle Aged; Registries; Sensitivity and Specificity; Sweden; Twin Studies as Topic

Development of a High-Sensitivity Method for the Measurement of Human Nasal Aβ42, Tau, and Phosphorylated Tau. - Liu, Ziyi; Kameshima, Naoko; Nanjo, Toshifumi; Shiino, Akihiko; Kato, Tomoko; Shimizu, Shino; Shimizu, Takeshi; Tanaka, Sachiko; Miura, Katsuyuki; Tooyama, Ikuo (J Alzheimers Dis, 2018)
Cost-effective and feasible methods for early diagnosis of Alzheimer's disease (AD) are needed. We present two methods to measure AD-related biomarkers simultaneously from one nasal smear for the purpose of diagnosing AD. Japanese men and women aged 63-85 years old were recruited in 2015-2016 for this case-control study. A total of 25 AD cases and 25 controls (22 men and 28 women) participated in this research. Nasal smears were collected from the common nasal meatus, inferior concha, middle nasal meatus, and olfactory cleft, and the proteins in the samples were analyzed by two methods, which we named PGD (Pre-treatment with guanidine- n-Dodecyl-beta-D-maltoside solution) method 1 (PGD-I) and 2 (PGD-II). The PGD-I method measured total tau and amyloid-β (Aβ)42, but no differences in median levels of total tau and Aβ42 between AD cases and controls were found in any of the nasal locations. The PGD-II method measured Aβ42, total tau, and phosphorylated tau, but levels of Aβ40 in all nasal locations of both groups were near zero. Median levels of phosphorylated tau to total tau (p-tau/t-tau) ratios in the middle nasal meatus and in the olfactory cleft were significantly higher in AD cases than in controls, and could significantly predict AD. To assess diagnostic reliability, areas under the ROC curve were 0.74 (95% CL = 0.52-0.95, p = 0.030) for the middle nasal meatus and 0.72 (95% CL = 0.52-0.92, p = 0.029) for the olfactory cleft. Thus, PGD-I and PGD-II can detect AD-related biomarkers in nasal smears and PGD-II may be a useful tool for diagnosing AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Case-Control Studies; Female; Humans; Male; Middle Aged; Nasal Mucosa; Peptide Fragments; Phosphorylation; Reproducibility of Results; ROC Curve; tau Proteins

The Diagnostic and Prognostic Value of a Dual-Tasking Paradigm in a Memory Clinic. - Nielsen, Malene Schjnning; Simonsen, Anja Hviid; Siersma, Volkert; Hasselbalch, Steen Gregers; Hoegh, Peter (J Alzheimers Dis, 2018)
BACKGROUND: Daily living requires the ability to perform dual-tasking. As cognitive skills decrease in dementia, performing a cognitive and motor task simultaneously become increasingly challenging and subtle gait abnormalities may even be present in pre-dementia stages. Therefore, a dual-tasking paradigm, such as the Timed Up and Go-Dual Task (TUG-DT), may be useful in the diagnostic assessment of mild cognitive impairment (MCI). OBJECTIVE: To investigate the diagnostic and prognostic ability of a dual-tasking paradigm in patients with MCI or mild Alzheimer's disease (AD) and to evaluate the association between the dual-tasking paradigm and cerebrospinal fluid (CSF) AD biomarkers. METHODS: The study is a prospective cohort study conducted in a clinical setting in two memory clinics. Eighty-six patients were included (28 MCI, 17 AD, 41 healthy controls (HC)). The ability to perform dual-tasking was evaluated by the TUG-DT. Patients underwent a standardized diagnostic assessment and were evaluated to determine progression yearly. RESULTS: ROC curve analysis illustrated a high discriminative ability of the dual-tasking paradigm in separating MCI patients from HC (AUC: 0.78, AUC: 0.82) and a moderate discriminative ability in separating MCI from AD (AUC: 0.73, AUC: 0.55). Performance discriminated clearly between all groups (p < 0.01). Logistic regression analyses revealed a low prognostic value of the dual-tasking paradigm for progression and rate of cognitive decline. A moderately strong correlation between the dual-tasking paradigm and CSF AD biomarkers was observed. CONCLUSION: In our study, we found that patients with MCI and mild AD have increasing difficulties in dual-tasking compared to healthy elderly. Hence, the dual-tasking paradigm may be a potential complement in the diagnostic assessment in a typical clinical setting.
Keywords: Aged; Alzheimer Disease; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Disease Progression; Female; Humans; Logistic Models; Male; Memory; Middle Aged; Neuropsychological Tests; Prognosis; Prospective Studies; ROC Curve

Dilated Perivascular Spaces in the Centrum Semiovale Begin to Develop in Middle Age. - Ishikawa, Masatsune; Yamada, Shigeki; Yamamoto, Kazuo (J Alzheimers Dis, 2018)
BACKGROUND: Dilated perivascular spaces in the centrum semiovale (CSO-PVS) are closely related to small vessel disease. However, recent studies have revealed that cerebral amyloid angiopathy can cause dilation of the CSO-PVS and obstruction of interstitial fluid flow along the intramural periarterial drainage. OBJECTIVE: To examine the severity and age-related prevalence of CSO-PVS through magnetic resonance imaging (MRI) and investigate their clinically relevant factors. METHODS: This study included 1,060 subjects who participated in our brain program. The subjects ranged from 23 to 83 years in age and were active in society. The frequencies of the MRI abnormalities of small vessel diseases, including CSO-PVS, were examined. The CSO-PVS severity was classified into three grades: G0, G1, G2, according to the visual rating. The subjects were divided into five age groups and their age-related frequencies were also studied. Using the clinico-laboratory data of 712 subjects, the clinically relevant factors of CSO-PVS were investigated using logistic regression analysis. RESULTS: The frequencies of all G0 ("normal") MRI abnormalities significantly decreased with age. A high prevalence of G2 CSO-PVS was observed (24%) in the youngest group aged≤39 years, whereas other MRI abnormalities in this group were not or rarely observed. In multivariable logistic regression analyses, G2 CSO-PVS was found to be closely associated with age, hypertension, and the estimated glomerular filtration ratio. CONCLUSIONS: This study reveals that CSO-PVS begin to develop in subjects aged less than 39 years. Age-related changes are involved. Further studies are necessary to elucidate the pathophysiological role of the CSO-PVS.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Cerebral Amyloid Angiopathy; Corpus Callosum; Cross-Sectional Studies; Female; Humans; Japan; Logistic Models; Magnetic Resonance Imaging; Male; Middle Aged; Multivariate Analysis; Prospective Studies; Young Adult

Does Fatty Acid Composition in Subcutaneous Adipose Tissue Differ between Patients with Alzheimer's Disease and Cohabiting Proxies? - Faxen-Irving, Gerd; Falahati, Farshad; Basun, Hans; Eriksdotter, Maria; Vedin, Inger; Wahlund, Lars-Olof; Schultzberg, Marianne; Hjorth, Erik; Palmblad, Jan; Cederholm, Tommy; Freund-Levi, Yvonne (J Alzheimers Dis, 2018)
Low tissue levels of the major marine ω3 fatty acids (FAs) DHA and EPA are found in Alzheimer's disease (AD). We investigated if healthy proxies to AD patients have higher levels of these ω3 FAs. We observed lower levels of EPA and DHA in subcutaneous adipose tissue biopsies from 64 AD patients compared with 16 cognitively healthy proxies. No significant difference was observed when pairwise comparisons were made between a subset of 16 AD patients and their co-habiting proxies. Larger studies are needed to replicate these findings and to determine if they could depend on FA intake or differences in metabolism.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Dietary Supplements; Fatty Acids, Omega-3; Female; Humans; Male; Regression Analysis; Subcutaneous Fat

Drugs for Dementia and Excess of Hospitalization: A Longitudinal French Study. - François, Mathilde; Sicsic, Jonathan; Pelletier Fleury, Nathalie (J Alzheimers Dis, 2018)
BACKGROUND: The impact of adverse effects of drugs for dementia on the risk of hospitalization has not been much studied despite the impact of hospitalizations on cognitive decline. OBJECTIVE: To determine if the main adverse effects of cholinesterase inhibitors and memantine may be associated with excess of hospitalization and to quantify the subsequent impact on healthcare expenditures. METHODS: A representative sample of the French national health insurance beneficiaries aged 65 and older and suffering from dementia were included and followed from 2007 to 2014. Binary logit models for longitudinal data (GEE estimation technique) were used to estimate the excess of hospitalization events related to the adverse effects of anti-dementia drugs and then to derive the additional costs of hospitalizations for the public health insurance fund. RESULTS: In total, 7,668 patients were followed, generating 111,133 individual observations over the 8-year period. Treated patients were hospitalized significantly more than non-treated patients (adjusted Odd Ratio (OR) = 1.08, 95% confidence interval (95% CI) = [1.02 to 1.13], p = 0.004), mainly with cholinesterase inhibitors for cardiac (OR = 1.21, 95% CI = [1.01 to 1.46], p = 0.034) and gastrointestinal events (OR = 1.43, 95% CI = [1.01-2.05], p = 0.045), especially with rivastigmine. When extrapolated to the entire population, this corresponded to an annual additional cost of € 55,000. CONCLUSION: Prescription of antidementia drugs, more specifically rivastigmine, increases the risk of hospitalizations via their cardiac and gastrointestinal adverse effects and lead to additional health care expenditures. Even though these results must be confirmed, they may encourage cautious consideration of the balance between benefits and harms before a prescription is given.
Keywords: Aged; Aged, 80 and over; Cholinesterase Inhibitors; Dementia; Female; France; Health Expenditures; Hospitalization; Humans; Longitudinal Studies; Male; Rivastigmine

Dysregulation and Dislocation of SFPQ Disturbed DNA Organization in Alzheimer's Disease and Frontotemporal Dementia. - Lu, Jing; Shu, Runzhe; Zhu, Yan (J Alzheimers Dis, 2018)
SFPQ (Splicing factor proline- and glutamine-rich) is a DNA and RNA binding protein involved in transcription, pre-mRNA splicing, and DNA damage repair. SFPQ was found dysregulated in a few tauopathies such as Alzheimer's disease (AD) and frontotemporal dementia (FTD). In addition, knock-down of SFPQ induced FTD-like behavior in mouse. To confirm the role of SFPQ in AD and FTD, we analyzed the brain sections from the AD and FTD brain samples with SFPQ upregulation and dislocation. Specifically, we observed SFPQ dislocated to the cytoplasm and nuclear envelopes, and DNA structures and organizations were associated with these dislocation phenotypes in AD and FTD brains. Consistently, we also found decreased DAPI intensities and smaller chromocenters associated with SFPQ dislocation in nerural-2a (N2a) cells. As the upregulation and hyperphosphorylation of tau protein is a hallmark of AD and FTD, our study sought to investigate potential interactions between tau and SFPQ by co-transfection and co-immunoprecipitation assays in N2a cells. SFPQ dislocation was found enhanced with tau co-transfection and tau co-transfection further resulted in extended DNA disorganization in N2a cells. Overall, our results indicate that dysregulation and dislocation of SFPQ and subsequent DNA disorganization might be a novel pathway in the progression of AD and FTD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Animals; Brain; Cell Line, Tumor; DNA Damage; Female; Frontotemporal Dementia; Gene Expression Regulation; Humans; Male; Mice; PTB-Associated Splicing Factor; tau Proteins; Translocation, Genetic

Early Stage Alterations in CA1 Extracellular Region Proteins Indicate Dysregulation of IL6 and Iron Homeostasis in the 5XFAD Alzheimer's Disease Mouse Model. - Gurel, Busra; Cansev, Mehmet; Sevinc, Cansu; Kelestemur, Seda; Ocalan, Busra; Cakir, Aysen; Aydin, Sami; Kahveci, Nevzat; Ozansoy, Mehmet; Taskapilioglu, Ozlem; Ulus, Ismail Hakki; Başar, Merve Karayel; et al. (J Alzheimers Dis, 2018)
In recent years, an increasing number of research papers revealed that the compositional and volumetric alterations in the extracellular matrix are the consequences of aging and may be related to Alzheimer's disease (AD). In this study, we aimed to demonstrate the alterations in hippocampal extracellular fluid proteins in vivo using the 5XFAD mouse model. Samples were obtained from hippocampi of 5XFAD mice (n = 6) and their non-transgenic littermates by intracerebral push-pull perfusion technique at 3 months of age, representing the pre-pathological stage of the AD. Proteins in the hippocampal perfusates were analyzed by Ultra Performance Liquid Chromatography-Electrospray Ionization Quadrupole Time-of-Flight Mass Spectrometry (UPLC-ESI-qTOF-MS/MS). 178 proteins were identified and 19 proteins of them were found to be statistically significantly altered (p≤0.05, fold change ≥40%, unique peptide count ≥3) in the hippocampal CA1 extracellular fluid of the 5XFAD mouse model. Ingenuity pathway analysis of the protein expression results identified IL6 as an upstream regulator. The upregulation of IL6 was validated by immunohistochemical staining of the hippocampus and cortex of the 5XFAD mice prior to Aβ plaque formation. Furthermore, the iron level in the hippocampus was measured by inductively coupled plasma-mass spectrometry as IL6 is mentioned in several studies to take part in iron homeostasis and inflammation and found to be increased in 5XFAD mice hippocampus. Alterations in extracellular matrix proteins in addition to increasing amount of hippocampal IL6 and iron in the early stages of AD may reveal inflammation-mediated iron dyshomeostasis in the early stages of neurodegeneration.
Keywords: Alzheimer Disease; Animals; CA1 Region, Hippocampal; Chromatography, Liquid; Disease Models, Animal; Female; Homeostasis; Interleukin-6; Iron; Mice; Mice, Transgenic; Proteomics; Tandem Mass Spectrometry

Economic Burden, Mortality, and Institutionalization in Patients Newly Diagnosed with Alzheimer's Disease. - Black, Christopher M; Fillit, Howard; Xie, Lin; Hu, Xiaohan; Kariburyo, M Furaha; Ambegaonkar, Baishali M; Baser, Onur; Yuce, Huseyin; Khandker, Rezaul K (J Alzheimers Dis, 2018)
BACKGROUND: Current information is scarce regarding comorbid conditions, treatment, survival, institutionalization, and health care utilization for Alzheimer's disease (AD) patients. OBJECTIVES: Compare all-cause mortality, rate of institutionalization, and economic burden between treated and untreated newly-diagnosed AD patients. METHODS: Patients aged 65-100 years with ≥1 primary or ≥2 secondary AD diagnoses (ICD-9-CM:331.0] with continuous medical and pharmacy benefits for ≥12 months pre-index and ≥6 months post-index date (first AD diagnosis date) were identified from Medicare fee-for-service claims 01JAN2011-30JUN2014. Patients with AD treatment claims or AD/AD-related dementia diagnosis during the pre-index period were excluded. Patients were assigned to treated and untreated cohorts based on AD treatment received post-index date. Total 8,995 newly-diagnosed AD patients were identified; 4,037 (44.8%) were assigned to the treated cohort. Time-to-death and institutionalization were assessed using Cox regression. To compare health care costs and utilizations, 1 : 1 propensity score matching (PSM) was used. RESULTS: Untreated patients were older (83.85 versus 81.44 years; p < 0.0001), with more severe comorbidities (mean Charlson comorbidity index: 3.54 versus 3.22; p < 0.0001). After covariate adjustment, treated patients were less likely to die (hazard ratio[HR] = 0.69; p < 0.0001) and were associated with 20% lower risk of institutionalization (HR = 0.801; p = 0.0003). After PSM, treated AD patients were less likely to have hospice visits (3.25% versus 9.45%; p < 0.0001), and incurred lower annual all-cause costs ($25,828 versus $30,110; p = 0.0162). CONCLUSION: After controlling for comorbidities, treated AD patients have better survival, lower institutionalization, and sometimes fewer resource utilizations, suggesting that treatment and improved care management could be beneficial for newly-diagnosed AD patients from economic and clinical perspectives.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cohort Studies; Comorbidity; Cost of Illness; Female; Humans; Institutionalization; Male; Neuropsychological Tests

The Effects and Meanings of Receiving a Diagnosis of Mild Cognitive Impairment or Alzheimer's Disease When One Lives Alone. - Portacolone, Elena; Johnson, Julene K; Covinsky, Kenneth E; Halpern, Jodi; Rubinstein, Robert L (J Alzheimers Dis, 2018)
BACKGROUND: One third of older adults with cognitive impairment live alone and are at high risk for poor health outcomes. Little is known about how older adults who live alone experience the process of receiving a diagnosis of mild cognitive impairment (MCI) or Alzheimer's disease (AD). OBJECTIVE: The aim of this study was to understand the effects and meanings of receiving a diagnosis of MCI or AD on the lived experience of older adults living alone. METHODS: This is a qualitative study of adults age 65 and over living alone with cognitive impairment. Participants' lived experiences were elicited through ethnographic interviews and participant observation in their homes. Using a qualitative content analysis approach, interview transcripts and fieldnotes were analyzed to identify codes and themes. RESULTS: Twenty-nine older adults and 6 members of their social circles completed 114 ethnographic interviews. Core themes included: relief, distress, ambiguous recollections, and not knowing what to do. Participants sometimes felt uplifted and relieved by the diagnostic process. Some participants did not mention having received a diagnosis or had only partial recollections about it. Participants reported that, as time passed, they did not know what to do with regard to the treatment of their condition. Sometimes they also did not know how to prepare for a likely worsening of their condition, which they would experience while living alone. CONCLUSION: Findings suggest the need for more tailored care and follow-up as soon as MCI or AD is diagnosed in persons living alone.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Emotions; Female; Health Services; Humans; Interviews as Topic; Male; Residence Characteristics; Single Person

Epigenetic Drug Repositioning for Alzheimer's Disease Based on Epigenetic Targets in Human Interactome. - Chatterjee, Paulami; Roy, Debjani; Rathi, Nitin (J Alzheimers Dis, 2018)
BACKGROUND: Epigenetics has emerged as an important field in drug discovery. Alzheimer's disease (AD), the leading neurodegenerative disorder throughout the world, is shown to have an epigenetic basis. Currently, there are very few effective epigenetic drugs available for AD. OBJECTIVE: In this work, for the first time we have proposed 14 AD repositioning epigenetic drugs and identified their targets from extensive human interactome. METHODS: Interacting partners of the AD epigenetic proteins were identified from the extensive human interactome to construct Epigenetic Protein-Protein Interaction Network (EP-PPIN). Epigenetic Drug-Target Network (EP-DTN) was constructed with the drugs associated with the proteins of EP-PPIN. Regulation of non-coding RNAs associated with the target proteins of these drugs was also studied. AD related target proteins, epigenetic targets, enriched pathways, and functional categories of the proposed repositioning drugs were also studied. RESULTS: The proposed 14 AD epigenetic repositioning drugs have overlapping targets and miRs with known AD epigenetic targets and miRs. Furthermore, several shared functional categories and enriched pathways were obtained for these drugs with FDA approved epigenetic drugs and known AD drugs. CONCLUSIONS: The findings of our work might provide insight into future AD epigenetic-therapeutics.
Keywords: Alzheimer Disease; Antipsychotic Agents; Computational Biology; Drug Repositioning; Epigenesis, Genetic; Epigenomics; Humans; MicroRNAs; Protein Interaction Maps; PubMed

Erythromyeloid-Derived TREM2: A Major Determinant of Alzheimer's Disease Pathology in Down Syndrome. - Raha-Chowdhury, Ruma; Henderson, James W; Raha, Animesh Alexander; Stott, Simon R W; Vuono, Romina; Foscarin, Simona; Wilson, Liam; Annus, Tiina; Fincham, Robert; Allinson, Kieren; Devalia, Vinod; Friedland, Robert P; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Down syndrome (DS; trisomy 21) individuals have a spectrum of hematopoietic and neuronal dysfunctions and by the time they reach the age of 40 years, almost all develop Alzheimer's disease (AD) neuropathology which includes senile plaques and neurofibrillary tangles. Inflammation and innate immunity are key players in AD and DS. Triggering receptor expressed in myeloid cells-2 (TREM2) variants have been identified as risk factors for AD and other neurodegenerative diseases. OBJECTIVE: To investigate the effects of TREM2 and the AD-associated R47H mutation on brain pathology and hematopoietic state in AD and DS. METHODS: We analyzed peripheral blood, bone marrow, and brain tissue from DS, AD, and age-matched control subjects by immunohistochemistry and western blotting. TREM2-related phagocytosis was investigated using a human myeloid cell line. RESULTS: TREM2 protein levels in brain and sera declined with age and disease progression in DS. We observed soluble TREM2 in brain parenchyma that may be carried by a subset of microglia, macrophages, or exosomes. Two DS cases had the AD-associated TREM2-R47H mutation, which manifested a morphologically extreme phenotype of megakaryocytes and erythrocytes in addition to impaired trafficking of TREM2 to the erythroid membrane. TREM2 was shown to be involved in phagocytosis of red blood cells. TREM2 was seen in early and late endosomes. Silencing TREM2 using siRNA in THP1 cells resulted in significant cell death. CONCLUSION: We provide evidence that peripheral TREM2 originating from erythromyeloid cells significantly determines AD neuropathology in DS subjects. Understanding the molecular signaling pathways mediated by TREM2 may reveal novel therapeutic targets.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Cell Line; Disease Progression; Down Syndrome; Exosomes; Female; Humans; Immunity, Innate; Macrophages; Male; Membrane Glycoproteins; Microglia; Middle Aged; Phagocytosis; Polymorphism, Single Nucleotide; Receptors, Immunologic

Establishing a New Screening System for Mild Cognitive Impairment and Alzheimer's Disease with Mental Rotation Tasks that Evaluate Visuospatial Function. - Suzuki, Ayuko; Shinozaki, Jun; Yazawa, Shogo; Ueki, Yoshino; Matsukawa, Noriyuki; Shimohama, Shun; Nagamine, Takashi (J Alzheimers Dis, 2018)
BACKGROUND: The mental rotation task is well-known for the assessment of visuospatial function; however, it has not been used for screening of dementia patients. OBJECTIVE: The aim of this study was to create a simple screening test for patients with mild cognitive impairment (MCI) and Alzheimer's disease (AD) by focusing on non-amnestic symptoms. METHODS: Age-matched healthy controls (age 75.3±6.8), patients with MCI (76.5±5.5), and AD (78.2±5.0) participated in this study. They carried out mental rotation tasks targeting geometric graphics or alphabetical characters with three rotating angles (0°, 90°, and 180°) and indicated the correct answer. Response accuracy and reaction time were recorded along with their eye movements using an eye tracker. To quantify their visual processing strategy, the run count ratio (RC ratio) was calculated by dividing the mean number of fixations in incorrect answers by that in correct answers. RESULTS: AD patients showed lower accuracy and longer reaction time than controls. They also showed a significantly greater number of fixation and smaller saccade amplitude than controls, while fixation duration did not differ significantly. The RC ratio was higher for AD, followed by MCI and control groups. By setting the cut-off value to 0.47 in the 180° rotating angle task, we could differentiate MCI patients from controls with a probability of 80.0%. CONCLUSIONS: We established a new screening system for dementia patients by evaluating visuospatial function. The RC ratio during a mental rotation task is useful for discriminating MCI patients from controls.
Keywords: Aged; Aged, 80 and over; Agnosia; Alzheimer Disease; Case-Control Studies; Cognition; Cognitive Dysfunction; Disease Progression; Early Diagnosis; Eye Movements; Female; Humans; Male; Mental Status Schedule; Reaction Time; ROC Curve

Executive and Language Subjective Cognitive Decline Complaints Discriminate Preclinical Alzheimer's Disease from Normal Aging. - Valech, Natalia; Tort-Merino, Adrià; Coll-Padrós, Nina; Olives, Jaume; León, María; Rami, Lorena; Molinuevo, José Luis (J Alzheimers Dis, 2018)
BACKGROUND: There is a need to specify the profile of subjective cognitive decline in preclinical Alzheimer's disease (preAD). OBJECTIVES: To explore specific items of the Subjective Cognitive Decline Questionnaire (SCD-Q) that discriminate preAD from normal aging. METHODS: 68 cognitively normal older adults were classified as controls (n = 52) or preAD (n = 16) according to amyloid-β (Aβ) levels. An exploratory factor analysis and item analysis of the SCD-Q were performed. Informant reports of the SCD-Q were used to corroborate the findings of self-reports. One-year neuropsychological follow-up was available. RESULTS: Four SCD-Q factors were extracted: EM-factor (episodic memory), A-factor (attention), O-factor (organization), and L-factor (language). PreAD reported a significantly higher decline in L-factor (F(1) = 6.49; p = 0.014) and A-factor (F(1) = 4.04; p = 0.049) compared to controls, and showed a higher frequency of perceived decline in SCD-Q items related with language and executive tasks (Sig-items.) Significant discriminative powers for Aβ-positivity were found for L-factor (AUC = 0.75; p = 0.003) and A-factor (AUC = 0.74; p = 0.004). Informants in the preAD group confirmed significantly higher scores in L-factor and Sig-items. A significant time×group interaction was found in the Semantic Fluency and Stroop tests, with the preAD group showing a decrease in performance at one-year. CONCLUSIONS: Our results suggest that SCD-Q items related with language and executive decline may help in prediction algorithms to detect preAD. Validation in an independent population is needed.
Keywords: Aged; Aging; Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Executive Function; Factor Analysis, Statistical; Female; Humans; Language; Male; Middle Aged; Neuropsychological Tests; Self Report

Executive Dysfunction Detected with the Frontal Assessment Battery in Alzheimer's Disease Versus Vascular Dementia. - D'Onofrio, Grazia; Panza, Francesco; Sancarlo, Daniele; Addante, Filomena; Solfrizzi, Vincenzo; Cantarini, Chiara; Mangiacotti, Antonio; Lauriola, Michele; Cascavilla, Leandro; Paris, Francesco; Lozupone, Madia; Daniele, Antonio; et al. (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) and vascular dementia (VaD) lead to progressive decline in executive function. We estimated the prevalence of executive dysfunction in AD and VaD patients, investigating cognitive, functional, and clinical correlates and also using a multidimensional approach based on a standardized comprehensive geriatric assessment (CGA). We included 215 patients (115 AD patients and 100 VaD patients) consecutively evaluated with a complete cognitive and affective assessment, a CGA, and the Frontal Assessment Battery (FAB) with six subtests investigating conceptualization, mental flexibility, motor programming, sensitivity to interference, inhibitory control, and environmental autonomy. The prevalence of dysexecutive syndrome screened with a FAB score <12 points was high in both AD (97 patients) and VaD (77 patients) (84.3% versus 77.0%, p = 0.171). AD patients were significantly younger, with higher grade of cognitive impairment and less severe comorbidity and polypharmacy than VaD patients. AD patients showed a significantly higher impairment in FAB total score and five FAB subtests (conceptualization, motor programming, sensitivity to interference, inhibitory control, and environmental autonomy) than VaD patients. These findings were largely confirmed in a sub-analysis conducted subdividing the sample in mild and moderate-to-severe demented patients and suggesting that in moderate-to-severe AD there was higher impairment in FAB total score and four FAB subtests (conceptualization, sensitivity to interference, inhibitory control, and environmental autonomy). Executive dysfunction could be greater in AD patients with moderate-to-severe dementia compared to VaD patients, although our groups were also not matched for age, comorbidity or polypharmacy, which could also exert an effect.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Comorbidity; Dementia, Vascular; Executive Function; Female; Frontal Lobe; Geriatric Assessment; Humans; Logistic Models; Male; Polypharmacy; Severity of Illness Index

The First Historically Reported Italian Family with FTD/ALS Teaches a Lesson on C9orf72 RE: Clinical Heterogeneity and Oligogenic Inheritance. - Giannoccaro, Maria Pia; Bartoletti-Stella, Anna; Piras, Silvia; Casalena, Alfonsina; Oppi, Federico; Ambrosetto, Giovanni; Montagna, Pasquale; Liguori, Rocco; Parchi, Piero; Capellari, Sabina (J Alzheimers Dis, 2018)
BACKGROUND: In 1969, Dazzi and Finizio reported the second observation of frontotemporal dementia (FTD) - amyotrophic lateral sclerosis (ALS) association in a large Italian kindred affected by an autosomal dominant form of ALS with high penetrance, frequent bulbar onset, and frequent cognitive decline. OBJECTIVE: To expand the original characterization of this family and report the link with the C9orf72 repeat expansion (RE). METHODS: We followed or reviewed the medical records of thirteen patients belonging to the original family and performed genetic analyses in four individuals. RESULTS: Eight patients presented with ALS, four with FTD, and one with schizophrenia. The C9orf72 RE was found in three patients but not in the healthy survivor. Additionally, we found a novel possible pathogenic variant in the ITM2B gene in one patient with a complex phenotype, associating movement disorders, psychiatric and cognitive features, deafness, and optic atrophy. The neuropathological examination of this patient did not show the classical features of ITM2B mutation related dementias suggesting that the putative pathogenic mechanism does not involve cellular mislocalization of the protein or the formation of amyloid plaques. CONCLUSION: We showed that the original Italian pedigree described with FTD/ALS carries the C9orf72 RE. Moreover, the finding of an additional mutation in another dementia causing gene in a patient with a more complex phenotype suggests a possible role of genetic modifiers in the disease. Together with other reports showing the coexistence of mutations in multiple ALS/FTD causative genes in the same family, our study supports an oligogenic etiology of ALS/FTD.
Keywords: Adult; Amyotrophic Lateral Sclerosis; C9orf72 Protein; Cerebral Cortex; DNA Repeat Expansion; Female; Frontotemporal Dementia; Genetic Testing; Humans; Male; Membrane Glycoproteins; Middle Aged; Multifactorial Inheritance; Mutation; Pedigree

Frequency of Cardiovascular Genetic Risk Factors in a Calabrian Population and Their Effects on Dementia. - Maletta, Raffaele; Smirne, Nicoletta; Bernardi, Livia; Anfossi, Maria; Gallo, Maura; Conidi, Maria Elena; Colao, Rosanna; Puccio, Gianfranco; Curcio, Sabrina A M; Laganà, Valentina; Frangipane, Francesca; Cupidi, Chiara; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Several genetic variants playing a key role in cholesterol levels, blood pressure, and vascular dysfunction influence the risk of Alzheimer's disease (AD) and vascular dementia (VaD). The many meta-analysis studies carried out on large numbers of samples in different populations have not provided clear results to date, because a trans-ethnic shift of risk genotypes in different populations is often observed. OBJECTIVES: To determine genotypes allele frequencies of the polymorphisms most frequently identified to be correlated with cardio-cerebrovascular disease and AD in a Southern Italy population and to investigate their possible association with dementia. METHODS: The genotype and allele frequencies of 13 cardio-cerebrovascular risk polymorphisms were assessed and their possible association with dementia was investigated in a case-control study, including 221 consecutive unrelated subjects diagnosed with dementia (120 subjects affected by AD, 55 by frontotemporal dementia, and 33 by vascular dementia) and 218 matched controls of Calabrian origin. RESULTS: Carriers of at least one APOEɛ4 allele resulted to be at higher risk of AD [OR(95% CI) = 2.721(1.477-5.011)] and VaD [OR(95% CI) = 6.205(2.356-16.342)] compared to non-carriers. Individuals with the IV genotype of the CETP polymorphism were more likely to have AD [OR(95% CI) = 2.427(1.364-4.319)] and VaD [OR(95% CI) = 3.649(1.455-9.152)] compared to subjects with the II-VV genotypes. CONCLUSION: CETP I405V polymorphism is likely a risk factor for AD and VaD in our cohort, independent of APOEɛ4 status. Unmodifiable genetic risk factors should be taken into account to promote a healthy lifestyle to prevent dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Case-Control Studies; Cholesterol Ester Transfer Proteins; Cohort Studies; Dementia, Vascular; Female; Frontotemporal Dementia; Gene Frequency; Humans; Italy; Male; Middle Aged; Polymorphism, Genetic; Risk Factors

GDF11 Rejuvenates Cerebrovascular Structure and Function in an Animal Model of Alzheimer's Disease. - Zhang, Wei; Guo, Yi; Li, Bo; Zhang, Qi; Liu, Jian-Hui; Gu, Guo-Jun; Wang, Jin-Hong; Bao, Rui-Kang; Chen, Yu-Jie; Xu, Jian-Rong (J Alzheimers Dis, 2018)
Cerebral amyloid angiopathy (CAA) is present in up to 90% of patients with Alzheimer's disease (AD), and may interact with classical neuropathology to exacerbate cognitive decline. Since growth differentiation factor 11 (GDF11) can activate vascular remodeling, we tested its effects on cognitive function and neuroinflammatory changes of AD model mice. We intravenously administered GDF11 or vehicle daily to 12-month-old transgenic mice overexpressing the amyloid-β protein precursor (AβPP)/PS1). Cognitive function was monitored using the Morris water maze, and after conclusion of the treatment, we assessed the morphology and presence of inflammatory markers in the cerebral vasculature. Subchronic treatment of adult AβPP/PS1 mice with GDF11 rescued cognitive function and ameliorated cerebrovascular function. In particular, the de novo genesis of small blood vessels and the expression of vascular-related proteins were significantly higher than in the vehicle-treated AβPP/PS1 mice, whereas the expressions of the inflammatory markers Iba-1 and GFAP significantly decreased in proportion to the lower ratio of two forms of amyloid-β (Aβ40/42). Daily intravenous treatment with GDF11-injection can rejuvenate respects of cognition and cerebrovascular changes in AD mice.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Behavior, Animal; Cerebral Amyloid Angiopathy; Disease Models, Animal; Growth Differentiation Factors; Maze Learning; Mice; Mice, Transgenic; Prefrontal Cortex; Presenilin-1

Gradual Cerebral Hypoperfusion Impairs Fear Conditioning and Object Recognition Learning and Memory in Mice: Potential Roles of Neurodegeneration and Cholinergic Dysfunction. - Mehla, Jogender; Lacoursiere, Sean; Stuart, Emily; McDonald, Robert J; Mohajerani, Majid H (J Alzheimers Dis, 2018)
In the present study, male C57BL/6J mice were subjected to gradual cerebral hypoperfusion by implanting an ameroid constrictor (AC) on the left common carotid artery (CCA) and a stenosis on the right CCA. In the sham group, all surgical procedures were kept the same except no AC was implanted and stenosis was not performed. One month following the surgical procedures, fear conditioning and object recognition tests were conducted to evaluate learning and memory functions and motor functions were assessed using a balance beam test. At the experimental endpoint, mice were perfused and brains were collected for immunostaining and histology. Learning and memory as well as motor functions were significantly impaired in the hypoperfusion group. The immunoreactivity to choline acetyltransferase was decreased in dorsal striatum and basal forebrain of the hypoperfusion group indicating that cholinergic tone in these brain regions was compromised. In addition, an increased number of Fluoro-Jade positive neurons was also found in cerebral cortex, dorsal striatum and hippocampus indicating neurodegeneration in these brain regions. Based on this pattern of data, we argued that this mouse model would be a useful tool to investigate the therapeutic interventions for the treatment of vascular dementia. Additionally, this model could be employed to exploit the effect of microvascular occlusions on cognitive impairment in the absence and presence of Alzheimer's disease pathology.
Keywords: Animals; Brain; Carotid Stenosis; Cerebrovascular Circulation; Choline O-Acetyltransferase; Conditioning (Psychology); Disease Models, Animal; Fear; Fluoresceins; Learning Disorders; Male; Mice; Mice, Inbred C57BL; Phosphopyruvate Hydratase; Postural Balance; Recognition (Psychology)

Healthy versus Entorhinal Cortical Atrophy Identification in Asymptomatic APOE4 Carriers at Risk for Alzheimer's Disease. - Konishi, Kyoko; Joober, Ridha; Poirier, Judes; MacDonald, Kathleen; Chakravarty, Mallar; Patel, Raihaan; Breitner, John; Bohbot, Véronique D (J Alzheimers Dis, 2018)
Early detection of Alzheimer's disease (AD) has been challenging as current biomarkers are invasive and costly. Strong predictors of future AD diagnosis include lower volume of the hippocampus and entorhinal cortex, as well as the ɛ4 allele of the Apolipoprotein E gene (APOE) gene. Therefore, studying functions that are critically mediated by the hippocampus and entorhinal cortex, such as spatial memory, in APOE ɛ4 allele carriers, may be key to the identification of individuals at risk of AD, prior to the manifestation of cognitive impairments. Using a virtual navigation task developed in-house, specifically designed to assess spatial versus non-spatial strategies, the current study is the first to differentiate functional and structural differences within APOE ɛ4 allele carriers. APOE ɛ4 allele carriers that predominantly use non-spatial strategies have decreased fMRI activity in the hippocampus and increased atrophy in the hippocampus, entorhinal cortex, and fimbria compared to APOE ɛ4 allele carriers who use spatial strategies. In contrast, APOE ɛ4 allele carriers who use spatial strategies have grey matter levels comparable to non-APOE ɛ4 allele carriers. Furthermore, in a leave-one-out analysis, grey matter in the entorhinal cortex could predict navigational strategy with 92% accuracy.
Keywords: Aged; Alleles; Alzheimer Disease; Apolipoprotein E4; Atrophy; Case-Control Studies; Entorhinal Cortex; Female; Heterozygote; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Risk Factors; Spatial Memory

Hedonic Assessment of Odors: A Comparison of Two Sensory Scales for Use with Alzheimer's Disease Patients and Elderly Individuals. - Atanasova, Boriana; Mondon, Karl; Dreyfuss, Lise; Beaufils, Emilie; Desmidt, Thomas; Hommet, Caroline; El-Hage, Wissam; Belzung, Catherine (J Alzheimers Dis, 2018)
BACKGROUND: Several clinical studies concerning the olfactory function of patients with cognitive impairment have used sensory scales to investigate hedonic perception. However, no study has focused on the choice of the most appropriate sensory hedonic scale for the individuals with neurodegenerative disorders or other psychiatric diseases involving cognitive deficits. OBJECTIVE: The aim of this study was to investigate the ability of patients with Alzheimer's disease (AD) to use two hedonic scales (category scale and linear scale) and compare their discriminatory capacity, repeatability, and ease of use. This should allow us to identify the most appropriate hedonic scale for patients with AD. METHODS: We recruited 18 patients with mild to moderate AD, and 20 healthy volunteers matched for gender, age, smoking status, and educational level. The participants underwent a clinical assessment and hedonic evaluation of three odorants (pleasant, unpleasant, and neutral), using a five-point category scale and a 10-cm linear scale with a marked mid-point. RESULTS: AD patients were able to use hedonic scales as well as paired healthy elderly subjects. The linear scale performed slightly better in terms of ease of use for both patients and healthy controls and discriminatory capacity for AD patients. The results for AD patients and controls with both scales were repeatable. CONCLUSION: The linear scale may be more appropriate for AD patients pending further studies involving a larger population of patients, using several odorants.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cognitive Dysfunction; Female; Humans; Linear Models; Male; Olfaction Disorders; Olfactory Perception; Severity of Illness Index; Smell

The Heritability of Frontotemporal Lobar Degeneration: Validation of Pedigree Classification Criteria in a Northern Italy Cohort. - Fostinelli, Silvia; Ciani, Miriam; Zanardini, Roberta; Zanetti, Orazio; Binetti, Giuliano; Ghidoni, Roberta; Benussi, Luisa (J Alzheimers Dis, 2018)
A large portion of frontotemporal lobar degeneration (FTLD) patients has a family history of disease and the presence of a pathogenic mutation confirms the clinical diagnosis. Recently, standardized criteria to evaluate FTLD pedigree, based on first- and second-degree affected relatives, their age at onset, and clinical phenotype, were proposed and validated in an American cohort. Herein we applied these criteria to 402 Italian FTLD pedigrees and assessed mutation frequencies in GRN, C9orf72, and MAPT genes with the aim of validating these criteria. Moreover, we evaluated whether genetic counseling requests reflect the estimated family risk. 12.4% of pedigrees had high family history, 6.5% medium, 15.4% low; 39% were apparent sporadic cases and 26.6% had family history of unknown significance. Mutations frequencies were in line with the categorization proposed: the highest rate was found in the most at-risk families (74%) and decreased in other categories (medium: 15.4%; low: 9.7%; sporadic: 1.3%). Mutation carriers with unknown family history (5.6%) were mostly early-onset patients. Detected mutation frequency was comparable with the US-cohort (13.7%), but mutations distribution among genes was different, with higher frequency of GRN mutations (9.4%) in our cohort. An elevated proportion of FTLD patients belonging to "high risk" pedigrees asked for genetic counseling (42%); requests decreased according to the estimated family risk (medium: 26.9%; low: 17.7%; sporadic: 5.1%). In conclusion, the proposed pedigree classification criteria, herein further validated, should be incorporated in the FTLD diagnostic work-up. Moreover, our data suggest to extend genetic screening to early-onset patients with unknown family history.
Keywords: Age of Onset; Aged; C9orf72 Protein; Cohort Studies; Female; Frontotemporal Lobar Degeneration; Genetic Counseling; Genetic Testing; Humans; Italy; Male; Middle Aged; Mutation; Pedigree; Progranulins; tau Proteins

High Caregiver Burden in Young Onset Dementia: What Factors Need Attention? - Lim, Linda; Zhang, Angeline; Lim, Levinia; Choong, Tanya-Marie; Silva, Eveline; Ng, Adeline; Kandiah, Nagaendran (J Alzheimers Dis, 2018)
BACKGROUND: There is an increase in prevalence of young onset dementia (YOD). The specific problems among YOD patients and levels of caregiver burden (CB) in this group warrants further evaluation. OBJECTIVE: To evaluate and compare level of CB in YOD and late onset dementia (LOD). Also, we sought to understand the specific factors, such as neuropsychiatric symptoms, that may affect the levels of caregiver burden in the YOD group. METHODS: Patient-caregiver dyads with YOD and LOD were recruited from a tertiary neurology center. Levels of CB between YOD and LOD were compared among 183 patient-caregiver dyads. CB was quantified using the Zarit Burden Inventory (ZBI). Neuropsychological evaluations as well as the Neuropsychiatric Inventory were performed. Factors that influenced level of CB in YOD group was investigated with regression analyses. RESULTS: There were 57 YOD and 126 LOD dyads. Caregivers of YOD subjects reported significantly higher levels of burden compared to caregivers of LOD subjects (ZBI: 17.3 versus 13.94; p = 0.015). 52.6% of YOD caregivers reported a high caregiver burden. When compared to caregivers of LOD, the odds of a caregiver of YOD reporting high caregiver burden was 2.34 (95% CI: 1.22-4.49: p = 0.010). YOD dyads with a high caregiver burden had significantly higher neuropsychiatric inventory scores. Risk factors for high caregiver burden in YOD included family history of dementia and behavioral symptoms including disinhibited behavior, delusions, and apathy. CONCLUSION: Targeted support for caregivers of patients with YOD is needed to address the higher CB in this group.
Keywords: Adaptation, Psychological; Age of Onset; Aged; Aged, 80 and over; Behavioral Symptoms; Caregivers; Cost of Illness; Cross-Sectional Studies; Dementia; Female; Humans; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Stress, Psychological; Surveys and Questionnaires

Hippocampal Stratum Radiatum, Lacunosum, and Moleculare Sparing in Mild Cognitive Impairment. - Su, Li; Hayes, Lawrence; Soteriades, Soteris; Williams, Guy; Brain, Susannah A E; Firbank, Michael J; Longoni, Giulia; Arnold, Robert J; Rowe, James B; O'Brien, John T (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is associated with atrophy in entorhinal cortex (ERC), the hippocampus, and its subfields Cornu Ammonis 1 (CA1) and subiculum, which predict conversion from mild cognitive impairment (MCI) to clinical AD. The stratum radiatum, lacunosum, and moleculare (SRLM) are also important gateways involving ERC and CA1, which are affected by early AD pathology. OBJECTIVE: To assess whether the SRLM is affected in MCI and AD. METHODS: In this proof-of-concept study, 27 controls, 13 subjects with AD, and 22 with MCI underwent 3T MRI. T1 maps were used for whole-hippocampal volumetry, T2 maps were segmented for hippocampal subfield areas, entorhinal cortex and subiculum thickness, and evaluated for SRLM integrity. RESULTS: Significant CA1 atrophy and subiculum thinning were found in both AD and MCI compared to similarly aged controls. However, SRLM integrity was only significantly reduced in AD but not in MCI compared to controls. There were no significant differences in other hippocampal subfields (CA2, CA3/dentate gyrus) or ERC thickness between the groups. Finally, CA1 and CA3/DG areas and SRLM clarity were correlated with clinical and cognitive measurements of disease severity. CONCLUSION: Although this study was cross sectional, it suggests a progression of specific subfield changes from MCI to established AD that is associated with the reduced integrity of SRLM, which may reflect more widespread hippocampal involvement as the disease progresses and the relative preservation of SRLM in MCI. These results provide new MRI biomarkers for disease staging and understanding of the neurobiology in AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Atrophy; Cognitive Dysfunction; Disease Progression; Entorhinal Cortex; Female; Hippocampus; Humans; Imaging, Three-Dimensional; Magnetic Resonance Imaging; Male; Middle Aged; Reproducibility of Results

Homocysteine and Dementia: An International Consensus Statement. - Smith, A David; Refsum, Helga; Bottiglieri, Teodoro; Fenech, Michael; Hooshmand, Babak; McCaddon, Andrew; Miller, Joshua W; Rosenberg, Irwin H; Obeid, Rima (J Alzheimers Dis, 2018)
Identification of modifiable risk factors provides a crucial approach to the prevention of dementia. Nutritional or nutrient-dependent risk factors are especially important because dietary modifications or use of dietary supplements may lower the risk factor level. One such risk factor is a raised concentration of the biomarker plasma total homocysteine, which reflects the functional status of three B vitamins (folate, vitamins B12, B6). A group of experts reviewed literature evidence from the last 20 years. We here present a Consensus Statement, based on the Bradford Hill criteria, and conclude that elevated plasma total homocysteine is a modifiable risk factor for development of cognitive decline, dementia, and Alzheimer's disease in older persons. In a variety of clinical studies, the relative risk of dementia in elderly people for moderately raised homocysteine (within the normal range) ranges from 1.15 to 2.5, and the Population Attributable risk ranges from 4.3 to 31%. Intervention trials in elderly with cognitive impairment show that homocysteine-lowering treatment with B vitamins markedly slows the rate of whole and regional brain atrophy and also slows cognitive decline. The findings are consistent with moderately raised plasma total homocysteine (>11 μmol/L), which is common in the elderly, being one of the causes of age-related cognitive decline and dementia. Thus, the public health significance of raised tHcy in the elderly should not be underestimated, since it is easy, inexpensive, and safe to treat with B vitamins. Further trials are needed to see whether B vitamin treatment will slow, or prevent, conversion to dementia in people at risk of cognitive decline or dementia.
Keywords: Cognition; Cognitive Dysfunction; Consensus; Dementia; Dietary Supplements; Homocysteine; Humans; Meta-Analysis as Topic; Review Literature as Topic; Risk Factors; Vitamin B Complex

Impact of a Virtual Dementia Experience on Medical and Pharmacy Students' Knowledge and Attitudes Toward People with Dementia: A Controlled Study. - Gilmartin-Thomas, Julia F-M; McNeil, John; Powell, Anne; Malone, Daniel T; Wolfe, Rory; Larson, Ian C; O'Reilly, Claire L; Kirkpatrick, Carl M; Kipen, Eva; Petrovich, Tanya; Bell, J Simon (J Alzheimers Dis, 2018)
BACKGROUND: Clinical practice guidelines for dementia highlight the importance of providing patient-centered care. This can be achieved by improving health professionals' attitudes and knowledge toward people with dementia. OBJECTIVE: Quantitatively evaluate the impact of a virtual dementia experience on medical and pharmacy students' knowledge and attitudes toward people with dementia. METHODS: A non-randomized controlled study from September-October 2016. The intervention group received a 1.5-hour multisensory, virtual simulation of light, sound, color, and visual content to experience the cognitive and perceptual difficulties faced by people with dementia. Controls participated in the standard curriculum only. All students were invited to complete the 20-item Dementia Attitudes Scale (DAS) pre- and post-intervention. RESULTS: A total of 278 students (n = 64 medical, n = 214 pharmacy) were analyzed (n = 80 intervention, n = 198 control). The majority of students were female (n = 184, 66.2%), with an average age of 22.5 years. The intervention improved the DAS total score and subdomains of comfort and knowledge (p < 0.001). CONCLUSION: The intervention had a positive impact on medical and pharmacy students' knowledge and attitudes toward people with dementia.
Keywords: Australia; Curriculum; Dementia; Female; Health Knowledge, Attitudes, Practice; Humans; Male; Students, Medical; Students, Pharmacy; Virtual Reality; Young Adult

The Impact of APOE ɛ4 in Alzheimer's Disease Differs According to Age. - Kim, Jaeho; Park, Seongbeom; Yoo, Heejin; Jang, Hyemin; Kim, Yeshin; Kim, Ko Woon; Jang, Young Kyoung; Lee, Jin San; Kim, Sung Tae; Kim, Seonwoo; Lee, Jong Min; Ki, Chang-Seok; et al. (J Alzheimers Dis, 2018)
We evaluated how the impact of apolipoprotein E4 (APOE4) differs according to age in Alzheimer's disease (AD) patients. We recruited 846 AD patients and 815 cognitively normal controls and categorized into three groups with respect to their age (<65, 65-74, and ≥75 years). We evaluated the risk of AD in APOE4 carriers and compared cortical thickness and cognitive function according to APOE4 status in each age group. At the point of this study, in young (<65 years) AD, APOE4 noncarriers had the most severe frontal and perisylvian atrophy, while in old (≥75 years) AD, APOE4 carriers had the most severe medial temporal atrophy. In AD under 75 years, APOE4 noncarriers and heterozygotes showed worse performance in language, visuospatial, and frontal function compared to homozygotes, while, in old (≥75 years) AD, APOE4 homozygotes showed worse performance in memory compared to noncarriers. As the detrimental effects of APOE4 seen in older AD patients were not found in younger AD patients, we suggest that some unrevealed factors are associated with cortical atrophy and non-amnestic cognitive dysfunction in young AD with APOE4 noncarriers.
Keywords: Age Factors; Aged; Alzheimer Disease; Apolipoprotein E4; Atrophy; Brain; Case-Control Studies; Cognition; Female; Heterozygote; Humans; Magnetic Resonance Imaging; Male; Memory; Middle Aged; Republic of Korea

The Impact of Music on the Self in Dementia. - Baird, Amee; Thompson, William Forde (J Alzheimers Dis, 2018)
In this review, we consider how the onset and progression of dementia can disrupt one's sense of self, and propose that music is an ideal tool for alleviating this distressing symptom. Various aspects of the self can be impaired in people with dementia, depending on how the self is defined. There are anecdotal reports that music can 'bring people back to themselves' in the face of dementia, but there have been scarce empirical investigations of this topic. Motivated by a consideration of the existing literature, we outline a novel theoretical framework that accounts for the relationship between music and the self in people with dementia. We propose that music has a number of 'design features' that make it uniquely equipped to engage multiple aspects of the self. We suggest that each design feature interacts with different aspects of the self to varying degrees, promoting overall wellbeing. We discuss how existing research on music and dementia fits within this framework, and describe two case studies in which music was an ideal stimulus for reaffirming their sense of self. Our framework may be useful for the diagnosis and treatment of impairments of self in people with dementia, and highlights how music, given its ability to engage all aspects of the self simultaneously, can result in an overall enhanced sense of self.
Keywords: Consciousness; Dementia; Humans; Music; Music Therapy; Personality

In vivo Depiction of α7 Nicotinic Receptor Loss for Cognitive Decline in Alzheimer's Disease. - Nakaizumi, Kyoko; Ouchi, Yasuomi; Terada, Tatsuhiro; Yoshikawa, Etsuji; Kakimoto, Akihiro; Isobe, Takashi; Bunai, Tomoyasu; Yokokura, Masamichi; Suzuki, Katsuaki; Magata, Yasuhiro (J Alzheimers Dis, 2018)
BACKGROUND: The α7 subtype of the nicotinic acetylcholine receptor (nAChR) is considered important in higher cognitive functions, and cholinergic loss underpins the pathophysiology of Alzheimer's disease (AD). However, the relationships between α7 nAChR function and clinical functions or amyloid-β (Aβ) deposition remain to be explored in the living AD brain. OBJECTIVE: We aimed to elucidate the relationship between α7 nAChR availability in the specific cholinergic region and cognitive decline in the Aβ-confirmed AD brain. METHODS: Twenty AD patients and ten age-matched healthy subjects were examined. The α7-nAChR availability and Aβ deposition were evaluated using positron emission tomography with an α7 nAChR radiotracer 11C-(R)-MeQAA and 11C-Pittsburg compound B (11C-PiB), respectively. Semi-quantified values of tracer binding were estimated with a simplified reference tissue method for BPND of 11C-(R)-MeQAA and a tissue ratio method for SUVR of 11C-PiB. These parameters and clinical scores were compared voxel-wise using a statistical parametric mapping method. RESULTS: The levels of 11C-(R)-MeQAA BPND in the temporal and prefrontal cholinergic projection regions were significantly lower in AD, and negative correlations were found between 11C-PiB SUVR and 11C-(R)-MeQAA BPND in the region of the nucleus basalis magnocellularis and medial prefrontal cortex. Levels of 11C-(R)-MeQAA BPND were significantly correlated with memory and frontal function scores in AD. CONCLUSION: The association between Aβ burden and α7-nAChR reduction in the basal forebrain cholinergic system was highlighted in relation to cognitive decline in AD. This suggests that Aβ-linked α7-nAChR reduction is clinico-pathophyisologically important for considering a good therapeutic target in AD.
Keywords: Adult; Aged; alpha7 Nicotinic Acetylcholine Receptor; Alzheimer Disease; Brain; Case-Control Studies; Cognitive Dysfunction; Female; Humans; Male; Middle Aged; Positron-Emission Tomography; Young Adult

Increased Serum Acylated Ghrelin Levels in Patients with Mild Cognitive Impairment. - Cao, Xi; Zhu, Min; He, Yan; Chu, Wenzheng; Du, Yifeng; Du, Heng (J Alzheimers Dis, 2018)
Ghrelin is a stomach-derived circulating hormone. In addition to its function as an orexigenic stimulant, the role of ghrelin in the consolidation of learning and memory has been implicated in recent years. However, the status of circulating acylated ghrelin (AG, that is, the functional form of ghrelin) in the symptomatic predementia stage of Alzheimer's disease (AD) has rarely been investigated. In the current study, we examined the serum levels of acylated and total ghrelin in 22 patients with mild cognitive impairment (MCI) and 30 cognitively normal controls. We have found that patients with MCI had significantly increased serum AG levels, which were inversely associated with defected short- and long-term memory as well as language skills. Of note, the levels of total circulating ghrelin were similar between the two groups. Intriguingly, serum AG but not total ghrelin was associated with AD risk factors including the age, hypertension, and hyperlipidemia. Therefore, circulating AG may serve as a potential early systemic biomarker for AD-related cognitive impairments. Nevertheless, the simplest interpretation of the results is that the levels of circulating AG are associated with cognitive impairments in patients with MCI, thereby forming the groundwork for our future studies on the systemic mechanisms of AD pertaining to the ghrelin system.
Keywords: Aged; Alzheimer Disease; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Female; Ghrelin; Humans; Male; Middle Aged; Risk Factors

Influence of Butyrylcholinesterase in Progression of Mild Cognitive Impairment to Alzheimer's Disease. - Gabriel, António José; Almeida, Maria Rosário; Ribeiro, Maria Helena; Carneiro, Diogo; Valério, Daniela; Pinheiro, Ana Cristina; Pascoal, Rui; Santana, Isabel; Baldeiras, Ines (J Alzheimers Dis, 2018)
BACKGROUND: Several demographic and genetic prognostic factors of conversion from mild cognitive impairment (MCI) to Alzheimer's disease (AD) have been recognized so far. The most frequent polymorphism of butyrylcholinesterase (BuChE), the K-variant, has been proposed as a risk factor for AD, but data regarding its influence on early disease progression is still limited. OBJECTIVE: To investigate the influence of the BuChE-K variant in MCI progression to AD. METHODS: 96 MCI patients were included in the study and were genotyped for BuChE-K variant and Apolipoprotein E (ApoE). Cerebrospinal fluid (CSF) BuChE activity, as well as the levels of AD biomarkers amyloid-β 42 (Aβ42), total and hyperphosphorylated tau (t-tau and p-tau) were also determined. RESULTS: No significant differences were found in either BuChE-K variant or BuChE activity between MCI patients that progressed to AD (MCI-AD) and patients that remained stable during clinical follow-up (MCI-St). As expected, baseline CSF levels of Aβ42 were significantly lower and t-Tau, p-Tau, and ApoE ɛ4 allele frequency were significantly higher in MCI-AD patients. An association between the ApoE ɛ4 allele and the BuChE-K variant in MCI-AD, but not in MCI-St patients, was found with patients carrying both alleles presenting the highest incidence of progression and the lowest estimated time of progression to AD. CONCLUSION: Although BuChE-K alone does not seem to play a major role in progression to AD in MCI patients, a synergistic effect with the ApoE ɛ4 allele was found, highlighting the importance of assessing these combined genotypes for evaluating risk progression in MCI patients.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Biomarkers; Butyrylcholinesterase; Cognitive Dysfunction; Disease Progression; Female; Genetic Predisposition to Disease; Humans; Kaplan-Meier Estimate; Male; Middle Aged; Risk Factors; tau Proteins

Interaction between Cytomegalovirus and Herpes Simplex Virus Type 1 Associated with the Risk of Alzheimer's Disease Development. - Lövheim, Hugo; Olsson, Jan; Weidung, Bodil; Johansson, Anders; Eriksson, Sture; Hallmans, Göran; Elgh, Fredrik (J Alzheimers Dis, 2018)
BACKGROUND: Several environmental factors, including infectious agents, have been suggested to cause Alzheimer's disease (AD). Cytomegalovirus (CMV) has been associated with AD in several recent studies. OBJECTIVE: To investigate whether carriage of CMV, alone or in combination with Herpes simplex virus (HSV), increased the risk of developing AD. METHODS: Plasma samples from 360 AD cases (75.3% women, mean age 61.2 years), taken an average of 9.6 years before AD diagnosis, and 360 age-, sex-, cohort-, and sampling date matched dementia-free controls were analyzed to detect anti-CMV (immunoglobulin [Ig] G and IgM), group-specific anti-HSV (IgG and IgM), and specific anti-HSV1 and HSV2 IgG antibodies by enzyme-linked immunosorbent assays. AD cases and dementia-free controls were compared using conditional logistic regression analyses. RESULTS: The presence of anti-CMV IgG antibodies did not increase the risk of AD (odds ratio [OR], 0.857; p = 0.497). Among AD cases, an association between CMV and HSV1 carriage was detected (OR 7.145, p < 0.001); in a conditional logistic regression model, the interaction between CMV and HSV1 was associated with AD development (OR 5.662; p = 0.007). CONCLUSION: The present findings do not support a direct relationship between CMV infection and the development of AD; however, an interaction between CMV and HSV1 was found to be associated significantly with AD development. These findings suggest that CMV infection facilitates the development of HSV1-associated AD, possibly via its effects on the immune system.
Keywords: Aged; Alzheimer Disease; Antibodies, Viral; Case-Control Studies; Cytomegalovirus; Cytomegalovirus Infections; Enzyme-Linked Immunosorbent Assay; Female; Herpes Simplex; Herpesvirus 1, Human; Humans; Immunoglobulin G; Immunoglobulin M; Logistic Models; Male; Middle Aged

Interactions between Atrial Fibrillation, Cardiovascular Risk Factors, and ApoE Genotype in Promoting Cognitive Decline in Patients with Alzheimer's Disease: A Prospective Cohort Study. - Falsetti, Lorenzo; Viticchi, Giovanna; Buratti, Laura; Grigioni, Francesco; Capucci, Alessandro; Silvestrini, Mauro (J Alzheimers Dis, 2018)
BACKGROUND: An association between non-valvular atrial fibrillation (NVAF) and cognitive impairment has been hypothesized. OBJECTIVE: We sought to evaluate whether and how permanent NVAF (pNVAF) is associated with progression of cognitive impairment in patients with Alzheimer's disease (AD) in the presence of vascular or genetic risk factors. METHODS: 310 consecutive patients affected by mild-moderate AD were included and followed for a 24-month period. At the end of the follow-up, based on the results of the neuropsychological evaluation patients were classified as stable or deteriorated to severe AD. Clinical history, therapy, time in therapeutic range for anticoagulation, Framingham cardiovascular risk profile (FCRP), CHA2DS2-VASc score, Mini-Mental State Examination (MMSE), ApoE genotype, brain CT-scan, carotid ultrasound, and ECG were collected. Binary logistic and path analysis were adopted to assess relationships between pNVAF, ApoE, and cognitive outcome. RESULTS: Despite anticoagulant therapy, pNVAF was associated with lower entry MMSE, higher mean intima-media thickness (mIMT) and higher FCRP. Among patients carrying ApoE ɛ4 allele and affected by pNVAF, the lowest MMSE (14.90±7.62) and the highest mIMT (1.16±0.17 mm) and FCRP (26.24±3.96) values were detected. In this group, the risk of cognitive deterioration reached the highest probability. pNVAF was associated with an increased cognitive deterioration in subjects with high FCRP, CHA2DS2-VASc, or mIMT. CONCLUSIONS: pNVAF seems to identify AD patients with a significant atherosclerotic burden and reduced cognitive performances. The interaction between pNVAF and ApoE ɛ4 genotype, especially with aggregated risk factors and an advanced stage of vascular damage is associated with higher risk of fast cognitive deterioration.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Atherosclerosis; Atrial Fibrillation; Carotid Intima-Media Thickness; Cognitive Dysfunction; Disease Progression; Female; Humans; Logistic Models; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Prospective Studies; Risk Factors; Tomography, X-Ray Computed

A Link between Subjective Perceptions of Memory and Physical Function: Implications for Subjective Cognitive Decline. - Cosentino, Stephanie; Devanand, Davangere; Gurland, Barry (J Alzheimers Dis, 2018)
Subjective impairment in memory is a frequently defining feature of subjective cognitive decline (SCD), a state hypothesized to precede objectively apparent cognitive symptoms of Alzheimer's disease (AD) and to hold promise as a non-invasive, inexpensive, preclinical indicator of AD. However, a full model of the factors that contribute to subjective memory (SM), and therefore to SCD, has yet to be articulated. While SM impairment is widely known to be associated with negative affect, the extent to which SM functioning may also reflect other factors, particularly subjective beliefs or perceptions about one's health, is not known. To examine the extent to which SM is associated with subjective perceptions of health more broadly, the current study investigated the link between SM and subjective physical functioning (independent of depressive affect, and objective cognitive and physical function) in an ethnically diverse sample of 471 older adults enrolled in the population-based Northern Manhattan Aging Project. 199 (42%) participants endorsed no difficulty on a 5-point SM index while 272 (58%) endorsed some degree of difficulty. As hypothesized, SM correlated with both depression and subjective physical function, but not with age, education, global cognition, or objective physical function. When objective and subjective physical function were entered in two separate, adjusted linear regressions predicting SM, only subjective physical function and depressive affect independently predicted SM. Subjective perceptions of memory appear to reflect individuals' broader health perceptions in part. Articulating the various correlates of SM will improve identification of SCD specific to preclinical AD.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Executive Function; Female; Humans; Linear Models; Male; Memory; Neuropsychological Tests; New York City; Perception

Lipid Metabolism and Survival Across the Frontotemporal Dementia-Amyotrophic Lateral Sclerosis Spectrum: Relationships to Eating Behavior and Cognition. - Ahmed, Rebekah M; Highton-Williamson, Elizabeth; Caga, Jashelle; Thornton, Nicolette; Ramsey, Eleanor; Zoing, Margaret; Kim, Woojin Scott; Halliday, Glenda M; Piguet, Olivier; Hodges, John R; Farooqi, I Sadaf; Kiernan, Matthew C (J Alzheimers Dis, 2018)
BACKGROUND: Patients with frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS) exhibit changes in eating behavior that could potentially affect lipid levels. OBJECTIVE: This study aimed to document changes in lipid metabolism across the ALS-FTD spectrum to identify potential relationships to eating behavior (including fat intake), cognitive change, body mass index (BMI), and effect on survival. METHODS: One hundred and twenty-eight participants were recruited: 37 ALS patients, 15 ALS patients with cognitive and behavioral change (ALS-Plus), 13 ALS-FTD, 31 behavioral variant FTD, and 32 healthy controls. Fasting total cholesterol, low density lipoprotein cholesterol (LDL), high density lipoprotein cholesterol (HDL) and triglyceride levels were measured and correlated to eating behavior (caloric, fat intake), cognitive change, and BMI; effect on survival was examined using cox regression analyses. RESULTS: There was a spectrum of lipid changes from ALS to FTD with increased triglyceride (p < 0.001), total cholesterol/HDL ratio (p < 0.001), and lower HDL levels (p = 0.001) in all patient groups compared to controls. While there was no increase in total cholesterol levels, a higher cholesterol level was found to correlate with 3.25 times improved survival (p = 0.008). Triglyceride and HDL cholesterol levels correlated to fat intake, BMI, and measures of cognition and disease duration. CONCLUSION: A spectrum of changes in lipid metabolism has been identified in ALS-FTD, with total cholesterol levels found to potentially impact on survival. These changes were mediated by changes in fat intake, and BMI, and may also be mediated by the neurodegenerative process, offering the potential to modify these factors to slow disease progression and improve survival.
Keywords: Adult; Aged; Amyotrophic Lateral Sclerosis; Australia; Body Mass Index; Case-Control Studies; Cholesterol; Cholesterol, HDL; Cognition; Energy Intake; Feeding Behavior; Female; Frontotemporal Dementia; Humans; Lipid Metabolism; Male; Middle Aged; Neuropsychological Tests; Survival Analysis

A Longitudinal Study of Total and Phosphorylated α-Synuclein with Other Biomarkers in Cerebrospinal Fluid of Alzheimer's Disease and Mild Cognitive Impairment. - Wang, Hua; Stewart, Tessandra; Toledo, Jon B; Ginghina, Carmen; Tang, Lu; Atik, Anzari; Aro, Patrick; Shaw, Leslie M; Trojanowski, John Q; Galasko, Douglas R; Edland, Steven; Jensen, Poul H; et al. (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) features a dynamic sequence of amyloid deposition, neurodegeneration, and cognitive impairment. A significant fraction of AD brains also displays Lewy body pathology, suggesting that addition of classically Parkinson's disease-related proteins to the AD biomarker panel may be of value. To determine whether addition of cerebrospinal fluid (CSF) total α-synuclein and its form phosphorylated at S129 (pS129) to the AD biomarker panel [Amyloid-β1-42 (Aβ42), tau, and phosphorylated tau (p-tau181)] improves its performance, we examined CSF samples collected longitudinally up to 7 years as part of the Alzheimer's Disease Neuroimaging Initiative. From 87 AD, 177 mild cognitive impairment (MCI), and 104 age-matched healthy controls, 792 baseline and longitudinal CSF samples were tested for total α-synuclein, pS129, Aβ42, tau, and p-tau181. pS129, but not total α-synuclein, was weakly associated with diagnosis at baseline when t-tau/Aβ42 was included in the statistical model (β= 0.0026, p = 0.041, 95% CI [(0.0001)-(0.005)]). CSF α-synuclein predicted Alzheimer's Disease Assessment Scale-Cognitive (β= -0.59, p = 0.0015, 95% CI [(-0.96)-(-0.23)]), memory (β= 0.4, p = 0.00025, 95% CI [(0.16)-(0.59)]), and executive (0.62,<0.0001, 95% CI [(0.31)-(0.93)]) function composite scores, and progression from MCI to AD (β= 0.019, p = 0.0011, 95% CI [(0.002)-(0.20)]). pS129 was associated with executive function (β= -2.55, p = 0.0085, 95% CI [(-4.45)-(-0.66)]). Lower values in the mismatch between α-synuclein and p-tau181 predicted faster cognitive decline (β= 0.64, p = 0.0012, 95% CI [(0.48)-(0.84)]). Longitudinal biomarker changes did not differ between groups, and may not reflect AD progression. The α-synuclein-p-tau181-Mismatch could better predict longitudinal cognitive changes than classical AD markers alone, and its pathological correlates should be investigated further.
Keywords: Aged; Aged, 80 and over; alpha-Synuclein; Alzheimer Disease; Biomarkers; Cognitive Dysfunction; Cross-Sectional Studies; Disease Progression; Executive Function; Female; Humans; Linear Models; Longitudinal Studies; Male; Memory Disorders; Multivariate Analysis; Neuropsychological Tests; Phosphorylation; tau Proteins

Low Prevalence of Cancer in Patients with Frontotemporal Lobar Degeneration. - Katisko, Kasper; Haapasalo, Annakaisa; Koivisto, Anne; Krüger, Johanna; Hartikainen, Päivi; Korhonen, Ville; Helisalmi, Seppo; Herukka, Sanna-Kaisa; Remes, Anne M; Solje, Eino (J Alzheimers Dis, 2018)
Several studies have reported reduced risk of cancer in patients with Alzheimer's disease (AD) or Parkinson's disease. The relationship between cancer and frontotemporal lobar degeneration (FTLD) has not been previously reported. Here, our aim was to evaluate the occurrence of cancer in Finnish FTLD patients with a high proportion of C9ORF72 repeat expansion carriers in comparison to age- and sex-matched group of AD patients and control subjects classified as not cognitively impaired (NCI). The prevalence of cancer was 9.7% in FTLD, 18.7% in AD, and 17.4% in NCI (FTLD versus AD p = 0.012, FTLD versus NCI p = 0.029) groups. No differences were observed between C9ORF72 repeat expansion carriers and non-carriers inside the FTLD group. To our knowledge, this is the first study showing significantly lower prevalence of cancer in FTLD patients compared to patients with AD or NCI subjects. Our data suggest an inverse association between neurodegeneration and cancer and that FTLD-specific mechanisms may underlie the especially strong inverse association observed in this study.
Keywords: Aged; Alzheimer Disease; C9orf72 Protein; DNA Repeat Expansion; Female; Finland; Frontotemporal Lobar Degeneration; Heterozygote; Humans; Male; Middle Aged; Neoplasms; Prevalence

Mental States in Moving Shapes: Distinct Cortical and Subcortical Contributions to Theory of Mind Impairments in Dementia. - Synn, Artemis; Mothakunnel, Annu; Kumfor, Fiona; Chen, Yu; Piguet, Olivier; Hodges, John R; Irish, Muireann (J Alzheimers Dis, 2018)
Impaired capacity for Theory of Mind (ToM) represents one of the hallmark features of the behavioral variant of frontotemporal dementia (bvFTD) and is suggested to underpin an array of socioemotional disturbances characteristic of this disorder. In contrast, while social processing typically remains intact in Alzheimer's disease (AD), the cognitive loading of socioemotional tasks may adversely impact mentalizing performance in AD. Here, we employed the Frith-Happé animations as a dynamic on-line assessment of mentalizing capacity with reduced incidental task demands in 18 bvFTD, 18 AD, and 25 age-matched Controls. Participants viewed silent animations in which geometric shapes interact in Random, Goal-Directed, and ToM conditions. An exclusive deficit in ToM classification was observed in bvFTD relative to Controls, while AD patients were impaired in the accurate classification of both Random and ToM trials. Correlation analyses revealed robust associations between ToM deficits and carer ratings of affective empathy disruption in bvFTD, and with episodic memory dysfunction in AD. Voxel-based morphometry analyses further identified dissociable neural correlates contingent on patient group. A distributed network of medial prefrontal, frontoinsular, striatal, lateral temporal, and parietal regions were implicated in the bvFTD group, whereas the right hippocampus correlated with task performance in AD. Notably, subregions of the cerebellum, including lobules I-IV and V, bilaterally were implicated in task performance irrespective of patient group. Our findings reveal new insights into the mechanisms potentially mediating ToM disruption in dementia syndromes, and suggest that the cerebellum may play a more prominent role in social cognition than previously appreciated.
Keywords: Aged; Alzheimer Disease; Brain; Case-Control Studies; Female; Frontotemporal Dementia; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Memory, Episodic; Mentalization; Middle Aged; Neuropsychological Tests; Task Performance and Analysis; Theory of Mind

Mesenchymal Stem Cell-Derived Extracellular Vesicles Suppresses iNOS Expression and Ameliorates Neural Impairment in Alzheimer's Disease Mice. - Wang, Shan-Shan; Jia, Jianjun; Wang, Zhenfu (J Alzheimers Dis, 2018)
BACKGROUND: Mesenchymal stem cells (MSCs)-derived extracellular vesicles (EVs) have been reported to exhibit therapeutic effects in various animal models of neurological diseases, such as stroke and hypoxic-ischemic brain injury. OBJECTIVE: The present study investigated the potential beneficial effect of MSC-derived EVs in an animal model of Alzheimer's disease (AD). METHODS: APP/PS1 mice and their non-transgenic littermates (WT) received intracerebroventricle injection of MSC-derived EVs once per two days for two weeks. Then novel object recognition and water maze tasks were carried out to measure the cognitive behaviors. Electrophysiological tests were carried out to measure hippocampal synaptic plasticity. Inducible nitric oxide synthase (iNOS) mRNA and protein levels were measured by qRT-PCR and western blotting in primary cultured neurons treated with amyloid-β peptide (Aβ) or prepared from APP/PS1 mice. RESULTS: Treatment with MSC-derived EVs alleviates exogenous Aβ-induced iNOS mRNA and protein expression. In cultured primary neurons prepared from APP/PS1 pups, iNOS mRNA and protein levels were significantly reduced when treated with MSC-derived EVs. MSC-derived EVs improved cognitive behavior, rescued impairment of CA1 synaptic transmission, and long-term potentiation in APP/PS1 mice. CONCLUSION: MSC-derived EVs possessed beneficial effects in a mouse model of AD, probably by suppressing Aβ induced iNOS expression.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Cells, Cultured; Disease Models, Animal; Extracellular Vesicles; Humans; Male; Mesenchymal Stem Cells; Mice; Mice, Transgenic; Neuronal Plasticity; Neurons; Nitric Oxide Synthase Type II; Synaptic Transmission

Meta-Analysis of Personality Traits in Alzheimer's Disease: A Comparison with Healthy Subjects. - D'Iorio, Alfonsina; Garramone, Federica; Piscopo, Fausta; Baiano, Chiara; Raimo, Simona; Santangelo, Gabriella (J Alzheimers Dis, 2018)
BACKGROUND: The role of specific personality traits as factor risks of Alzheimer's disease (AD) has been consistently found, whereas personality traits specifically related to AD (after the diagnosis) have not been outlined yet. OBJECTIVE: A meta-analysis of published studies was performed to determine whether AD patients have a distinctive personality trait profile compared to healthy subjects (HC), similar to or different from a premorbid personality profile consistently reported in previous studies. METHODS: A systematic literature search was performed using PsycInfo (PROQUEST), PubMed, and Scopus. The meta-analysis pooled results from primary studies using Hedges' g unbiased approach. RESULTS: The meta-analysis included 10 primary studies and revealed that, when the personality was evaluated by informant-rated measures, AD patients had significantly higher levels of Neuroticism, lower levels of Openness, Agreeableness, Conscientiousness, and Extraversion than HCs. When the personality was evaluated by self-rated measures, the results obtained from informants were confirmed for Neuroticism, Openness, and Extraversion but not for Agreeableness and Conscientiousness where AD patients and HCs achieved similar scores. CONCLUSIONS: The meta-analysis revealed that high Neuroticism and low Openness and Extraversion are distinctive personality traits significantly associated with a diagnosis of AD when evaluated both self-rated and informant-rated measures. This personality trait profile is similar to premorbid one, which contributes to development of AD over time. Therefore, our findings indirectly support the idea of specific premorbid personality traits as harbingers of AD.
Keywords: Alzheimer Disease; Case-Control Studies; Humans; Personality; Personality Inventory

microRNA 221 Targets ADAM10 mRNA and is Downregulated in Alzheimer's Disease. - Manzine, Patricia R; Pelucchi, Silvia; Horst, Maria A; Vale, Francisco A C; Pavarini, Sofia C I; Audano, Matteo; Mitro, Nico; Di Luca, Monica; Marcello, Elena; Cominetti, Márcia R (J Alzheimers Dis, 2018)
ADAM10 is the α-secretase that cleaves amyloid-β protein precursor in the non-amyloidogenic pathway in Alzheimer's disease (AD) and is known to be regulated by different microRNAs (miRNAs), which are post-transcriptional regulators related to several biological and pathological processes, including AD. Here we proposed to explore and validate miRNAs that have direct or indirect relations to the AD pathophysiology and ADAM10 gene. Approximately 700 miRNAs were analyzed and 21 differentially expressed miRNAs were validated in a sample of 21 AD subjects and 17 cognitively healthy matched controls. SH-SY5Y cells were transfected with miR-144-5p, miR-221, and miR-374 mimics and inhibitors, and ADAM10 protein levels were evaluated. miR-144-5p, miR-221, and miR-374 were downregulated in AD. The overexpression of miR-221 in SH-SY5Y cells resulted in ADAM10 reduction and its inhibition in ADAM10 increased. These findings show that miR-221 can be a new potential therapeutic target for increasing ADAM10 levels in AD. In addition, these results can contribute to the better understanding of ADAM10 post-transcriptional regulation.
Keywords: ADAM10 Protein; Aged; Aged, 80 and over; Alzheimer Disease; Cell Line, Tumor; Cohort Studies; Down-Regulation; Female; Humans; Male; MicroRNAs; Middle Aged; Neuroblastoma; Psychiatric Status Rating Scales; RNA, Messenger; ROC Curve; Transfection

Mutation Screening of the CHCHD2 Gene for Alzheimer's Disease and Frontotemporal Dementia in Chinese Mainland Population. - Che, Xiang-Qian; Zhao, Qian-Hua; Huang, Yue; Li, Xia; Ren, Ru-Jing; Chen, Sheng-Di; Guo, Qi-Hao; Wang, Gang (J Alzheimers Dis, 2018)
As an important multifunctional protein involved in regulation of mitochondrial metabolism, CHCHD2 was identified as a causative gene for Parkinson's disease (PD), yet the relationship between CHCHD2 and neurodegenerative dementia is not well understood. We directly sequenced the entire coding region of CHCHD2 gene in 150 AD patients, 84 FTD patients, and 417 controls. Four rare putative pathogenic variants of CHCHD2, including rs142444896 (c.5C>T, p.P2L), rs752705344 (c.15C>G, p.S5R), rs145190179 (c.94G>A, p.A32T), and rs182992574 (c.255T>A, p.S85R) were identified from a cohort composed of 150 AD and 84 FTD patients. These results suggest that CH CHD2 gene play an important role in other neurodegenerative disorders from our dementia study in China.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Asian Continental Ancestry Group; Case-Control Studies; China; Female; Frontotemporal Dementia; Genetic Association Studies; Humans; Male; Middle Aged; Mitochondrial Proteins; Mutation; Transcription Factors

A Natural Benzofuran from the Patagonic Aleurodiscus vitellinus Fungus has Potent Neuroprotective Properties on a Cellular Model of Amyloid-β Peptide Toxicity. - González-Ramírez, Mariela; Gavilán, Javiera; Silva-Grecchi, Tiare; Cajas-Madriaga, Daniel; Triviño, Sergio; Becerra, José; Saez-Orellana, Francisco; Pérez, Claudia; Fuentealba, Jorge (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is characterized by amyloid plaques that form due to an increase in amyloid-β peptide (Aβ) aggregation. One strategy in the search of new treatments for AD focuses on compounds that decrease Aβ accumulation. Compounds containing a benzofuran ring have been described to play an important role in decreasing Aβ-induced toxicity; however, only synthetic benzofurans have been tested thus far. The aim of the present study was to examine the in vitro neuroprotective properties of fomannoxin (Fx), a natural benzofuran isolated from cultures of the Andean-Patagonian fungi Aleurodiscus vitellinus, and evaluate its effect on Aβ peptide. We tested the effect of Fx at a wide concentration range (10-11-10-4 M) in PC-12 cells, and found the compound did not alter cellular viability. Fx also showed a concentration-dependent effect on the Aβ-induced toxicity in PC12 cells, showing viability above 100% at 10-6 M. We then measured the effect of Fx (10-7-10-5 M) on the frequency of cytosolic Ca2+ transients in rat hippocampal neurons at both acute and chronic (24 h) times. Acute incubation with Fx increased the frequency of cytosolic Ca2+ transients to values around 200%, whereas chronic incubation with Fx increased the frequency of Ca2+ transients. Finally, the Aβ-induced decrease in intracellular Ca2+ transients was prevented when Fx (10-6 M) was co-incubated with Aβ (5×10-6 M). The results suggest a potent neuroprotective effect of this naturally occurring benzofuran against Aβ peptide toxicity that could be mediated by an interference with it binding to plasma membrane, and lead Fx as new chemical entity to develop pharmacological tools against Aβ peptide neurotoxicity.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Basidiomycota; Benzofurans; Cell Survival; Hippocampus; Neurons; Neuroprotective Agents; PC12 Cells; Plaque, Amyloid; Rats

The Need to Separate Chronic Traumatic Encephalopathy Neuropathology from Clinical Features. - Iverson, Grant L; Keene, C Dirk; Perry, George; Castellani, Rudolph J (J Alzheimers Dis, 2018)
There is tremendous recent interest in chronic traumatic encephalopathy (CTE) in former collision sport athletes, civilians, and military veterans. This critical review places important recent research results into a historical context. In 2015, preliminary consensus criteria were developed for defining the neuropathology of CTE, which substantially narrowed the pathology previously reported to be characteristic. There are no agreed upon clinical criteria for diagnosis, although sets of criteria have been proposed for research purposes. A prevailing theory is that CTE is an inexorably progressive neurodegenerative disease within the molecular classification of the tauopathies. However, historical and recent evidence suggests that CTE, as it is presented in the literature, might not be pathologically or clinically progressive in a substantial percentage of people. At present, it is not known whether the emergence, course, or severity of clinical symptoms can be predicted by specific combinations of neuropathologies, thresholds for accumulation of pathology, or regional distributions of pathologies. More research is needed to determine the extent to which the neuropathology ascribed to long-term effects of neurotrauma is static, progressive, or both. Disambiguating the pathology from the broad array of clinical features that have been reported in recent studies might facilitate and accelerate research- and improve understanding of CTE.
Keywords: Chronic Traumatic Encephalopathy; Cognition Disorders; Disease Progression; Gait Disorders, Neurologic; Humans; Neurodegenerative Diseases; Neuropathology; Tremor

Negative Prospective Memory in Alzheimer's Disease: "Do Not Perform That Action". - El Haj, Mohamad; Coello, Yann; Kapogiannis, Dimitrios; Gallouj, Karim; Antoine, Pascal (J Alzheimers Dis, 2018)
Relatively to "standard" prospective memory, i.e., remembering to perform a future action, little is known about negative prospective memory, i.e., remembering not to perform a future action. This study investigated the latter ability in Alzheimer's disease (AD). AD participants and healthy older adults were asked to click on the keyboard or not to click on it when a cue word was encountered. Results showed more omissions (i.e., forgetting to click the keyboard when the instruction was to do so) in AD participants than in healthy older adults, suggesting a prospective memory deficit. Interestingly, more commissions (i.e., clicking the keyboard when the instruction was not to do so) were also observed in AD participants than in healthy older adults. Similar levels of commissions and omissions were observed in AD participants and in healthy older adults. Also, commissions and omissions were correlated with performance on an inhibition assessment task. Our findings reveal that AD is characterized by not only difficulty in the retrieval of recent information, but also difficulty to inhibit no-longer appropriate stimulus-response associations previously learned, suggesting a specific deficit of negative prospective memory in AD.
Keywords: Aged; Alzheimer Disease; Case-Control Studies; Female; Humans; Inhibition (Psychology); Male; Memory Disorders; Memory, Episodic; Mental Recall; Neuropsychological Tests

A Network of Genetic Effects on Non-Demented Cognitive Aging: Alzheimer's Genetic Risk (CLU + CR1 + PICALM) Intensifies Cognitive Aging Genetic Risk (COMT + BDNF) Selectively for APOEɛ4 Carriers. - Sapkota, Shraddha; Dixon, Roger A (J Alzheimers Dis, 2018)
BACKGROUND: Trajectories of complex neurocognitive phenotypes in preclinical aging may be produced differentially through selective and interactive combinations of genetic risk. OBJECTIVE: We organize three possible combinations into a "network" of genetic risk indices derived from polymorphisms associated with normal and impaired cognitive aging, as well as Alzheimer's disease (AD). Specifically, we assemble and examine three genetic clusters relevant to non-demented cognitive trajectories: 1) Apolipoprotein E (APOE), 2) a Cognitive Aging Genetic Risk Score (CA-GRS; Catechol-O-methyltransferase + Brain-derived neurotrophic factor), and 3) an AD-Genetic Risk Score (AD-GRS; Clusterin + Complement receptor 1 + Phosphatidylinositol-binding clathrin assembly protein). METHOD: We use an accelerated longitudinal design (n = 634; age range = 55-95 years) to test whether AD-GRS (low versus high) moderates the effect of increasing CA-GRS risk on executive function (EF) performance and change as stratified by APOE status (ɛ4+ versus ɛ4-). RESULTS: APOEɛ4 carriers with high AD-GRS had poorer EF performance at the centering age (75 years) and steeper 9-year decline with increasing CA-GRS but this association was not present in APOEɛ4 carriers with low AD-GRS. CONCLUSIONS: APOEɛ4 carriers with high AD-GRS are at elevated risk of cognitive decline when they also possess higher CA-GRS risk. Genetic risk from both common cognitive aging and AD-related indices may interact in intensification networks to differentially predict (1) level and trajectories of EF decline and (2) potential selective vulnerability for transitions into impairment and dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Brain-Derived Neurotrophic Factor; Canada; Catechol O-Methyltransferase; Clusterin; Cognitive Aging; Cognitive Dysfunction; Executive Function; Female; Genetic Predisposition to Disease; Heterozygote; Humans; Longitudinal Studies; Male; Middle Aged; Monomeric Clathrin Assembly Proteins; Neuropsychological Tests; Receptors, Complement 3b

Neuroanatomical Comparison of the "Word" and "Picture" Versions of the Free and Cued Selective Reminding Test in Alzheimer's Disease. - Slachevsky, Andrea; Barraza, Paulo; Hornberger, Michael; Muñoz-Neira, Carlos; Flanagan, Emma; Henriquez, Fernando; Bravo, Eduardo; Farías, Mauricio; Delgado, Carolina (J Alzheimers Dis, 2018)
Episodic memory tests with cued recall, such as the Free and Cued Selective Reminding Test (FCSRT), allow for the delineation of hippocampal and prefrontal atrophy contributions to memory performance in Alzheimer's disease (AD). Both Word and Picture versions of the test exist but show different profiles, with the Picture version usually scoring higher across different cohorts. One possible explanation for this divergent performance between the different modality versions of the test might be that they rely on different sets of neural correlates. The current study explores this by contrasting the neural correlates of the Word and Picture versions of the FCSRT with voxel-based morphometry (VBM) in AD and healthy subjects. We predicted that the Picture version would be associated with different cortical regions than the Word version, which might be more hippocampal-centric. When comparing 35 AD patients and 34 controls, AD patients exhibited impairments on both versions of the FCSRT and both groups performed higher in the Picture version. A region of interest analysis based on prior work revealed significant correlations between free recall of either version with atrophy of the temporal pole and hippocampal regions. Thus, contrary to expectations, performance on both the Word and the Picture version of the FCSRT is associated with largely overlapping networks. Free recall is associated with hippocampal volume and might be properly considered as an indicator of hippocampal structural integrity.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Case-Control Studies; Cues; Female; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Memory, Episodic; Mental Recall; Middle Aged; Neuropsychological Tests; Photic Stimulation

Neuropsychiatric and Cognitive Subtypes among Community-Dwelling Older Persons and the Association with DSM-5 Mild Neurocognitive Disorder: Latent Class Analysis. - Liew, Tau Ming; Yu, Junhong; Mahendran, Rathi; Ng, Tze-Pin; Kua, Ee-Heok; Feng, Lei (J Alzheimers Dis, 2018)
BACKGROUND: Neuropsychiatric symptoms (NPS) have been shown to increase the risk of neurocognitive disorders (NCD), leading to the recently-published criteria of mild behavioral impairment (MBI) to identify pre-dementia using NPS alone. However, MBI drew concerns about over-diagnosing subclinical psychiatric disorders. OBJECTIVE: We hypothesized that the specificity of NPS in predicting NCD may be improved by considering NPS together with various domains of cognitive deficits. We tested this hypothesis by identifying subtypes based on the combination of NPS and cognitive deficits among community-dwelling older persons, and evaluating how the identified subtypes were associated with mild NCD. METHODS: Our participants were from a community-based cohort study. They completed assessments such as Geriatric Depression Scale (GDS), Geriatric Anxiety Inventory (GAI), and Montreal Cognitive Assessment (MoCA). Those with possible cognitive impairment underwent further evaluations for mild NCD. Latent class analysis was conducted using GDS, GAI, and MoCA domains. Logistic regression was performed to investigate the association between the latent-classes and mild NCD. RESULTS: We included 825 participants, and identified four distinct subtypes: Subtype 1 (no NPS or cognitive deficits), Subtype 2 (NPS alone), Subtype 3 (cognitive deficits alone), and Subtype 4 (both NPS and cognitive deficits). Subtype 1 and 2 had low risk of prevalent mild NCD (OR 0.92- 1.00), while Subtype 3 conferred a moderate risk (OR 4.47- 4.85) and Subtype 4 had the highest risk (OR 7.95- 8.63). CONCLUSION: We demonstrated the benefits of combining NPS and cognitive deficits to predict those at highest risk of prevalent mild NCD. Our findings highlighted the relevance of subclinical psychiatric symptoms in predicting NCD, and indirectly supported the need for longer durations of NPS to improve its specificity.
Keywords: Aged; Cognition; Cognitive Dysfunction; Diagnostic and Statistical Manual of Mental Disorders; Female; Humans; Latent Class Analysis; Logistic Models; Longitudinal Studies; Male; Middle Aged; Neuropsychological Tests; Sensitivity and Specificity

Nutrition: Review on the Possible Treatment for Alzheimer's Disease. - Botchway, Benson O A; Moore, Masania K; Akinleye, Faith O; Iyer, Ishwari C; Fang, Marong (J Alzheimers Dis, 2018)
Since its discovery some hundred years ago, Alzheimer's disease (AD), a neurodegenerative disease and an eminent cause of most dementia, continues to pose problems for affected families and society, especially in developed countries. With the approved medications by the Food and Drugs Administration in the United States, effectual treatment of AD apropos to the complete eradication of the disease continues to be elusive due to complexities relating to the pathophysiology of the disease. Nutrition has and continues to play a salient role in the survival of living organisms with no exception for human beings. Herein, we report the connection between nutrition and AD with particular attention to vitamins, curcumin, and the Mediterranean diet.
Keywords: Alzheimer Disease; Curcumin; Diet, Mediterranean; Dietary Supplements; Humans; Nutritional Status; Risk Factors; Vitamins

An Objective Method to Accurately Measure Cardiorespiratory Fitness in Older Adults Who Cannot Satisfy Widely Used Oxygen Consumption Criteria. - Dougherty, Ryan J; Lindheimer, Jacob B; Stegner, Aaron J; Van Riper, Stephanie; Okonkwo, Ozioma C; Cook, Dane B (J Alzheimers Dis, 2018)
Cardiorespiratory fitness (CRF) is routinely investigated in older adults; however, the most appropriate CRF measure to use for this population has received inadequate attention. This study aimed to 1) evaluate the reliability and validity of the oxygen uptake efficiency slope (OUES) as a sub-maximal measurement of CRF; 2) examine demographic, risk-factor, and exercise testing differences in older adults who satisfied standardized criteria for a peak oxygen consumption (V̇O2peak) test compared to those who did not; and 3) determine the difference between directly measured V̇O2peak values and OUES-predicted V̇O2peak values. One hundred ten enrollees from the Wisconsin Registry for Alzheimer's Prevention participated in this study. Participants performed a graded maximal exercise test and wore an accelerometer for 7 days. For each participant, the OUES was calculated at 75%, 90%, and 100% of exercise duration. V̇O2peak was recorded at peak effort, and one week of physical activity behavior was measured. OUES values calculated at separate relative exercise durations displayed excellent reliability (ICC = 0.995; p < 0.001), and were strongly correlated with V̇O2peak (rrange = 0.801-0.909; p < 0.001). As hypothesized, participants who did not satisfy V̇O2peak criteria were significantly older than those who satisfied criteria (p = 0.049) and attained a directly measured V̇O2peak that was 2.31 mL·kg·min-1 less than the value that was predicted by OUES V̇O2peak (p = 0.003). Older adults are less likely to satisfy V̇O2peak criteria, which results in an underestimation of their CRF. Without adhering to standardized criteria, V̇O2peak measurement error may lead to misinterpretation of CRF and age-related associations. Here, we conclude that OUES is a reliable, valid measurement of CRF which does not require achievement of standardized criteria.
Keywords: Aged; Cardiorespiratory Fitness; Exercise Test; Female; Humans; Male; Middle Aged; Oxygen Consumption; Reproducibility of Results; Wisconsin

Ozone Atmospheric Pollution and Alzheimer's Disease: From Epidemiological Facts to Molecular Mechanisms. - Croze, Marine L; Zimmer, Luc (J Alzheimers Dis, 2018)
Atmospheric pollution is a well-known environmental hazard, especially in developing countries where millions of people are exposed to airborne pollutant levels above safety standards. Accordingly, several epidemiological and animal studies confirmed its role in respiratory and cardiovascular pathologies and identified a strong link between ambient air pollution exposure and adverse health outcomes such as hospitalization and mortality. More recently, the potential deleterious effect of air pollution inhalation on the central nervous system was also investigated and mounting evidence supports a link between air pollution exposure and neurodegenerative pathologies, especially Alzheimer's disease (AD). The focus of this review is to highlight the possible link between ozone air pollution exposure and AD incidence. This review's approach will go from observational and epidemiological facts to the proposal of molecular mechanisms. First, epidemiological and postmortem human study data concerning residents of ozone-severely polluted megacities will be presented and discussed. Then, the more particular role of ozone air pollution in AD pathology will be described and evidenced by toxicological studies in rat or mouse with ozone pollution exposure only. The experimental paradigms used to reproduce in rodent the human exposure to ozone air pollution will be described. Finally, current insights into the molecular mechanisms through which ozone inhalation can affect the brain and play a role in AD development or progression will be recapitulated.
Keywords: Air Pollution; Alzheimer Disease; Animals; Central Nervous System; Humans; Incidence; Inhalation Exposure; Ozone; Particulate Matter

Palmitoylethanolamide Blunts Amyloid-β42-Induced Astrocyte Activation and Improves Neuronal Survival in Primary Mouse Cortical Astrocyte-Neuron Co-Cultures. - Beggiato, Sarah; Borelli, Andrea Celeste; Ferraro, Luca; Tanganelli, Sergio; Antonelli, Tiziana; Tomasini, Maria Cristina (J Alzheimers Dis, 2018)
BACKGROUND: Based on the pivotal role of astrocytes in brain homeostasis and the strong metabolic cooperation existing between neurons and astrocytes, it has been suggested that astrocytic dysfunctions might cause and/or contribute to neuroinflammation and neurodegenerative processes. Therapeutic approaches aimed at both neuroprotection and neuroinflammation reduction may prove particularly effective in slowing the progression of these diseases. The endogenous lipid mediator palmitoylethanolamide (PEA) displayed neuroprotective and anti(neuro)inflammatory properties, and demonstrated interesting potential as a novel treatment for Alzheimer's disease. OBJECTIVE AND METHODS: We firstly evaluated whether astrocytes could participate in regulating the Aβ42-induced neuronal damage, by using primary mouse astrocytes cell cultures and mixed astrocytes-neurons cultures. Furthermore, the possible protective effects of PEA against Aβ42-induced neuronal toxicity have also been investigated by evaluating neuronal viability, apoptosis, and morphometric parameters. RESULTS: The presence of astrocytes pre-exposed to Aβ42 (0.5μM; 24 h) induced a reduction of neuronal viability in primary mouse astrocytes-neurons co-cultures. Furthermore, under these experimental conditions, an increase in the number of neuronal apoptotic nuclei and a decrease in the number of MAP-2 positive neurons were observed. Finally, astrocytic Aβ42 pre-exposure induced an increase in the number of neurite aggregations/100μm as compared to control (i.e., untreated) astrocytes-neurons co-cultures. These effects were not observed in neurons cultured in the presence of astrocytes pre-exposed to PEA (0.1μM), applied 1 h before and maintained during Aβ42 treatment. CONCLUSION: Astrocytes contribute to Aβ42-induced neurotoxicity and PEA, by blunting Aβ42-induced astrocyte activation, improved neuronal survival in mouse astrocyte-neuron co-cultures.
Keywords: Amyloid beta-Peptides; Analysis of Variance; Animals; Animals, Newborn; Anti-Inflammatory Agents, Non-Steroidal; Astrocytes; Cell Survival; Cells, Cultured; Cerebral Cortex; Coculture Techniques; Ethanolamines; Mice; Mice, Inbred C57BL; Microtubule-Associated Proteins; Neurons; Palmitic Acids; Peptide Fragments; Time Factors

Patient Characteristics and Outcomes Associated with Receiving an Earlier Versus Later Diagnosis of Probable Alzheimer's Disease. - Kirson, Noam Y; Scott Andrews, J; Desai, Urvi; King, Sarah B; Schonfeld, Sophie; Birnbaum, Howard G; Ball, Daniel E; Kahle-Wrobleski, Kristin (J Alzheimers Dis, 2018)
BACKGROUND: Effectiveness of Alzheimer's disease (AD) treatments may depend critically on the timeliness of intervention. OBJECTIVE: To compare characteristics and outcomes of patients diagnosed with probable AD (prAD) based on time elapsed from first onset of cognitive decline. METHODS: Patients with ≥1 prAD diagnosis and ≥1 follow-up visit were selected from the National Alzheimer's Coordinating Center (NACC) Uniform Data Set (UDS; 9/2005-6/2015) and stratified based on the time between the perceived onset of cognitive decline at baseline and first prAD diagnosis (i.e., earlier versus later diagnosis). Characteristics at baseline and prAD diagnosis, clinically meaningful progression, and medication use following prAD diagnosis were compared. RESULTS: Median time from perceived onset of cognitive decline to prAD diagnosis was 4.5 years (earlier diagnosis: ≤3.46; later diagnosis: >5.71). Earlier-diagnosed patients (n = 1,476) were younger at baseline (74.3 versus 76.3 years) and had better cognitive and functional scores than later-diagnosed patients (n = 1,474). At first prAD diagnosis, earlier-diagnosed patients had lower mean global Clinical Dementia Rating (CDR) score (0.8 versus 1.1), higher mean Mini-Mental State Examination (MMSE) (22.6 versus 20.0), and lower mean Functional Activities Questionnaire (11.6 versus 17.3). Earlier- and later-diagnosed patients experienced similar time to a decrease of ≥3 points in MMSE (median 23.2 versus 23.1 months, p = 0.83), but earlier-diagnosed patients had longer time to a CDR score of ≥2 points, and longer times to initiation of AD medication and antipsychotic agents (all p < 0.01). CONCLUSION: Earlier prAD diagnosis in NACC data is associated with higher cognitive function and lower functional impairment at diagnosis.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Cognition Disorders; Cohort Studies; Datasets as Topic; Disease Progression; Female; Humans; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Statistics, Nonparametric; Time Factors

Perspectives on Communicating Biomarker-Based Assessments of Alzheimer's Disease to Cognitively Healthy Individuals. - Milne, Richard; Bunnik, Eline; Diaz, Ana; Richard, Edo; Badger, Shirlene; Gove, Dianne; Georges, Jean; Fauria, Karine; Molinuevo, Jose-Luis; Wells, Katie; Ritchie, Craig; Brayne, Carol (J Alzheimers Dis, 2018)
In clinical trials which target pathophysiological mechanisms associated with Alzheimer's disease, research participants who are recruited based on biomarker test results should be informed about their increased risk of developing Alzheimer's dementia. This paper presents the results of a qualitative focus group study of attitudes and concerns toward learning information about biomarker-based risk status among healthy research participants in the United Kingdom and Spain and people with dementia and their supporters/caregivers from countries represented in the European Working Group of People with Dementia of Alzheimer Europe. The study identified expectations related to learning risk status and preferences related to the content, quality, and follow-up of the disclosure process. The latter emphasize distinctions between risk and diagnoses, the importance of clear information about risk, and suggestions for risk reduction, as well as expectations for follow up and support. The implications of these preferences for practice are discussed. Providing details of research participants' experience and views may serve as a guide for the development of processes for the responsible disclosure of Alzheimer's disease biomarkers.
Keywords: Adult; Aged; Alzheimer Disease; Biomarkers; Caregivers; Disclosure; Female; Focus Groups; Humans; Male; Middle Aged; Qualitative Research; Risk Factors; Spain; United Kingdom

Physical Activity and Hippocampal Sub-Region Structure in Older Adults with Memory Complaints. - Siddarth, Prabha; Rahi, Berna; Emerson, Natacha D; Burggren, Alison C; Miller, Karen J; Bookheimer, Susan; Lavretsky, Helen; Dobkin, Bruce; Small, Gary; Merrill, David A (J Alzheimers Dis, 2018)
BACKGROUND: Physical activity (PA) plays a major role in maintaining cognition in older adults. PA has been shown to be correlated with total hippocampal volume, a memory-critical region within the medial temporal lobe (MTL). However, research on associations between PA and MTL sub-region integrity is limited. OBJECTIVE: To examine the relationship between PA, MTL thickness, and its sub-regions, and cognitive function in non-demented older adults with memory complaints. METHODS: Twenty-nine subjects aged ≥60 years, with memory complaints were recruited for this cross-sectional study. PA was tracked for 7 days using accelerometers, and average number of steps/day determined. Subjects were categorized into two groups: those who walked ≤4000 steps/day (lower PA) and those with >4000 steps/day (higher PA). Subjects received neuropsychological testing and 3T MRI scans. Nonparametric ANCOVAs controlling for age examined differences between the two groups. RESULTS: Twenty-six subjects aged 72.7(8.1) years completed the study. The higher PA group (n = 13) had thicker fusiform gyrus (median difference = 0.11 mm, effect size (ES) = 1.43, p = 0.001) and parahippocampal cortex (median difference = 0.12 mm, ES = 0.93, p = 0.04) compared to the lower PA group. The higher PA group also exhibited superior performance in attention and information-processing speed (median difference = 0.90, ES = 1.61, p = 0.003) and executive functioning (median difference = 0.97, ES = 1.24, p = 0.05). Memory recall was not significantly different between the two groups. CONCLUSION: Older non-demented individuals complaining of memory loss who walked >4000 steps each day had thicker MTL sub-regions and better cognitive functioning than those who walked ≤4000 steps. Future studies should include longitudinal analyses and explore mechanisms mediating hippocampal related atrophy.
Keywords: Aged; Aged, 80 and over; Cognition; Cross-Sectional Studies; Executive Function; Exercise; Female; Geriatric Assessment; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Memory; Memory Disorders; Middle Aged; Neuropsychological Tests

Potential of Low Dose Leuco-Methylthioninium Bis(Hydromethanesulphonate) (LMTM) Monotherapy for Treatment of Mild Alzheimer's Disease: Cohort Analysis as Modified Primary Outcome in a Phase III Clinical Trial. - Wilcock, Gordon K; Gauthier, Serge; Frisoni, Giovanni B; Jia, Jianping; Hardlund, Jiri H; Moebius, Hans J; Bentham, Peter; Kook, Karin A; Schelter, Bjoern O; Wischik, Damon J; Davis, Charles S; Staff, Roger T; et al. (J Alzheimers Dis, 2018)
BACKGROUND: LMTM is being developed as a treatment for AD based on inhibition of tau aggregation. OBJECTIVES: To examine the efficacy of LMTM as monotherapy in non-randomized cohort analyses as modified primary outcomes in an 18-month Phase III trial in mild AD. METHODS: Mild AD patients (n = 800) were randomly assigned to 100 mg twice a day or 4 mg twice a day. Prior to unblinding, the Statistical Analysis Plan was revised to compare the 100 mg twice a day as monotherapy subgroup (n = 79) versus 4 mg twice a day as randomized (n = 396), and 4 mg twice a day as monotherapy (n = 76) versus 4 mg twice a day as add-on therapy (n = 297), with strong control of family-wise type I error. RESULTS: The revised analyses were statistically significant at the required threshold of p < 0.025 in both comparisons for change in ADAS-cog, ADCS-ADL, MRI atrophy, and glucose uptake. The brain atrophy rate was initially typical of mild AD in both add-on and monotherapy groups, but after 9 months of treatment, the rate in monotherapy patients declined significantly to that reported for normal elderly controls. Differences in severity or diagnosis at baseline between monotherapy and add-on patients did not account for significant differences in favor of monotherapy. CONCLUSIONS: The results are consistent with earlier studies in supporting the hypothesis that LMTM might be effective as monotherapy and that 4 mg twice a day may serve as well as higher doses. A further suitably randomized trial is required to test this hypothesis.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Antipsychotic Agents; Cohort Studies; Double-Blind Method; Female; Humans; International Cooperation; Male; Mental Status and Dementia Tests; Methylene Blue; Middle Aged; Treatment Outcome

Pramlintide: The Effects of a Single Drug Injection on Blood Phosphatidylcholine Profile for Alzheimer's Disease. - Tao, Qiushan; Zhu, Haihao; Chen, Xi; Stern, Robert A; Kowall, Neil; Au, Rhoda; Blusztajn, Jan Krzysztof; Qiu, Wei Qiao (J Alzheimers Dis, 2018)
Studies suggest that a single injection of pramlintide, an amylin analog, induces changes in Alzheimer's disease (AD) biomarkers in the blood of AD mouse models and AD patients. The aim of this study was to examine whether a pramlintide challenge combined with a phosphatidylcholine (PC) profile diagnoses of AD and mild cognitive impairment (MCI) better than PC alone. Non-diabetic subjects with cognitive status were administered a single subcutaneous injection of 60 mcg of pramlintide under fasting condition. A total of 71 PCs, amyloid-β peptide (Aβ), and total tau (t-tau) in plasma at different time points were measured and treated as individual variables. A single injection of pramlintide altered the levels of 7 PCs in the blood, while a pramlintide injection plus food modulated the levels of 10 PCs in the blood (p < 0.05). The levels of 2 PCs in MCI and 12 PCs in AD in the pramlintide challenge were significantly lower than the ones in controls. We found that while some PCs were associated with only Aβ levels, other PCs were associated with both Aβ and t-tau levels. A receiver operating characteristic analysis of the PCs was combined with the Aβ and t-tau data to produce an area under the curve predictive value of 0.9799 between MCI subjects and controls, 0.9794 between AD subjects and controls, and 0.9490 between AD and MCI subjects. A combination of AD biomarkers and a group of PCs post a pramlintide challenge may provide a valuable diagnostic and prognostic test for AD and MCI.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Female; Humans; Islet Amyloid Polypeptide; Logistic Models; Male; Middle Aged; Phosphatidylcholines; ROC Curve; tau Proteins

Prediction of Alzheimer's Dementia in Patients with Amnestic Mild Cognitive Impairment in Clinical Routine: Incremental Value of Biomarkers of Neurodegeneration and Brain Amyloidosis Added Stepwise to Cognitive Status. - Lange, Catharina; Suppa, Per; Pietrzyk, Uwe; Makowski, Marcus R; Spies, Lothar; Peters, Oliver; Buchert, Ralph (J Alzheimers Dis, 2018)
The aim of this study was to evaluate the incremental benefit of biomarkers for prediction of Alzheimer's disease dementia (ADD) in patients with mild cognitive impairment (MCI) when added stepwise in the order of their collection in clinical routine. The model started with cognitive status characterized by the ADAS-13 score. Hippocampus volume (HV), cerebrospinal fluid (CSF) phospho-tau (pTau), and the FDG t-sum score in an AD meta-region-of-interest were compared as neurodegeneration markers. CSF-Aβ1-42 was used as amyloidosis marker. The incremental prognostic benefit from these markers was assessed by stepwise Kaplan-Meier survival analysis in 402 ADNI MCI subjects. Predefined cutoffs were used to dichotomize patients as 'negative' or 'positive' for AD characteristic alteration with respect to each marker. Among the neurodegeneration markers, CSF-pTau provided the best incremental risk stratification when added to ADAS-13. FDG PET outperformed HV only in MCI subjects with relatively preserved cognition. Adding CSF-Aβ provided further risk stratification in pTau-positive subjects, independent of their cognitive status. Stepwise integration of biomarkers allows stepwise refinement of risk estimates for MCI-to-ADD progression. Incremental benefit strongly depends on the patient's status according to the preceding diagnostic steps. The stepwise Kaplan-Meier curves might be useful to optimize diagnostic workflow in individual patients.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloidosis; Brain; Cognitive Dysfunction; Female; Fluorodeoxyglucose F18; Humans; Imaging, Three-Dimensional; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography; Survival Analysis; tau Proteins

Prevalence of Delirium in a Population of Elderly Outpatients with Dementia: A Retrospective Study. - Addesi, Desirée; Maio, Raffaele; Smirne, Nicoletta; Laganà, Valentina; Altomari, Natalia; Puccio, Gianfranco; Colao, Rosanna; Cupidi, Chiara; Perticone, Francesco; Bruni, Amalia Cecilia (J Alzheimers Dis, 2018)
BACKGROUND: Delirium is a multifactorial geriatric syndrome and often occurs in patients with cognitive impairment. It also remains under-recognized, specifically in elderly outpatients, because signs of delirium might overlap with symptoms of dementia. OBJECTIVE: The aim of the present study is to retrospectively apply the chart-based delirium instrument on a cohort of elderly outpatients with dementia, to assess prevalence and features of delirium in this population. METHODS: We randomly selected 650 medical records of outpatients referred to the "Neurogenetic Regional Centre" (CRN) of Lamezia Terme. Each evaluation included demographics, medical history, drugs, type and severity of dementia, and cognitive and functional status. Delirium was identified by the application of the chart-based delirium instrument. RESULTS: The prevalence of delirium was 13.3%. The study population was divided, according to the presence of delirium, into two subgroups. Compared to the no delirium group, the delirium group was significantly older and had greater cognitive impairment with lower MMSE scores both at baseline and at the end of the follow up. They also had a significant lower score on the ADL and IADL. In this group, a higher intake of antihypertensive and antipsychotic drugs, together with a lower intake of cholinesterase inhibitors and memantine, was observed. CONCLUSIONS: In this study, the chart-based delirium instrument was applied to an outpatient population affected by dementia and followed for a long time. Our data confirm the importance that age and frailty play on the genesis of delirium and suggest attention should be paid to the pharmacological treatment of these patients.
Keywords: Aged; Aged, 80 and over; Antipsychotic Agents; Cohort Studies; Delirium; Dementia; Female; Geriatric Assessment; Humans; Male; Outpatients; Prevalence; Severity of Illness Index

Prevalence of Potentially Inappropriate Medication Use in Older Inpatients with and without Cognitive Impairment: A Systematic Review. - Redston, Mitchell R; Hilmer, Sarah N; McLachlan, Andrew J; Clough, Alexander J; Gnjidic, Danijela (J Alzheimers Dis, 2018)
BACKGROUND: Older people with cognitive impairment, including dementia and delirium, are high users of acute care services internationally. Potentially inappropriate medication (PIM) use may be associated with adverse outcomes, including hospital re-admission, functional disability, and mortality. OBJECTIVE: This systematic review aimed to quantify and compare the prevalence of PIMs in older inpatients with and without cognitive impairment. METHODS: A systematic search of observational studies was performed independently assessed by two reviewers in Embase, Medline, PsycINFO, International Pharmaceutical Abstracts, Scopus, and Informit. Articles published in English during the period January 2007-June 2017 that reported PIM prevalence in hospital inpatients ≥ 65 years were included. PIMs were defined as the presence of polypharmacy (multiple medication use) and using implicit or explicit tools, such as the Beers criteria, and 'Screening Tool of Older Person's Prescriptions' (STOPP). RESULTS: 47 articles were included. In studies measuring polypharmacy (n = 15), the prevalence of PIMs ranged from 53.2% to 89.8% and 30.4% to 97.1% for inpatients with and without cognitive impairment, respectively, and 24.0% to 80.0% when cognitive status was unreported. In studies employing explicit and implicit tools (n = 35), the prevalence of PIMs when cognitive impairment was reported ranged from 20.6% to 80.5% using the Beers criteria, and 39.3% to 88.5% using STOPP. When cognitive status was unreported, the prevalence of PIMs ranged from 7.0% to 79.2% using the Beers criteria, and 20.0% to 63.4% using STOPP. CONCLUSION: Our findings suggest a high prevalence of PIMs in older inpatients with and without cognitive impairment. Future studies should investigate the impact of PIM use on patient-centered outcomes, such as functional status and quality of life, to inform enhanced acute care services.
Keywords: Aged; Cognitive Dysfunction; Dementia; Humans; Inpatients; Polypharmacy; Potentially Inappropriate Medication List; Prevalence; Quality of Life

Profiling of Specific Gene Expression Pathways in Peripheral Cells from Prodromal Alzheimer's Disease Patients. - Serpente, Maria; Fenoglio, Chiara; Cioffi, Sara Maria Giulia; Oldoni, Emanuela; Arcaro, Marina; Arighi, Andrea; Fumagalli, Giorgio Giulio; Ghezzi, Laura; Scarpini, Elio; Galimberti, Daniela (J Alzheimers Dis, 2018)
Herein, we performed a gene expression profiling in a cohort of 10 mild cognitive impairment (MCI), subdivided, according to the analysis of cerebrospinal fluid biomarkers, in prodromal Alzheimer's disease (AD) and non-AD MCI, as compared with 27 AD patients and 24 controls, in order to detect early gene expression alterations. We observed a significant upregulation of insulin (INS) and INS Receptor (INSR) expression levels in AD both prodromal and fully symptomatic, as compared with controls, but not in MCI subjects. Our results suggest an early dysregulation of INS and INSR in AD pathogenesis and pave the way to a possible utility of these transcripts as peripheral biomarkers.
Keywords: Aged; Alzheimer Disease; Antigens, CD; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Female; Gene Expression Profiling; Humans; Insulin; Male; Middle Aged; Receptor, Insulin

Progression of Alzheimer's Disease-Related Pathology and Cell Counts in a Patient with Idiopathic Normal Pressure Hydrocephalus. - Libard, Sylwia; Laurell, Katarina; Cesarini, Kristina Giuliana; Alafuzoff, Irina (J Alzheimers Dis, 2018)
We had an opportunity to assess the change observed in the brain regarding Alzheimer's disease (AD)-related alterations, cell count, and inflammation that took place during a period of 21 months in a subject with a definite diagnosis of AD and idiopathic Normal Pressure Hydrocephalus (iNPH). Four neuronal markers, i.e., synaptophysin, microtubule associated protein 2, non-phosphorylated neurofilament H (SMI32), and embryonic lethal abnormal visual system proteins 3/4 HuC/HuD (HuC/HuD); three microglial markers CD68, Human Leucocytic Antigen DR, ionized calcium-binding adaptor molecule 1, glial fibrillary acidic protein (GFAP); and AD-related markers, hyperphosphorylated τ (HPτ) and amyloid-β (Aβ, Aβ40, Aβ42) were assessed. Morphometrically assessed immunoreactivity of all neuronal and all microglial markers and Aβ42 decreased parallel with an increase in the HPτ in the frontal cortex. The expression of GFAP was stable with time. The first sample was obtained during the therapeutic shunting procedure for iNPH, and the second sample was obtained postmortem. Negligible reactive changes were observed surrounding the shunt channel. In conclusion, in the late stage of AD with time, a neuronal loss, increase in the HPτ, and decrease in Aβ42 and microglia was observed, whereas the expression of GFAP was rather stable. The observations described here suggest that when a brain biopsy has been obtained from an adult subject with iNPH, the assessment of postmortem brain is of major significance.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Biopsy; Brain; Cell Count; Disease Progression; Female; Glial Fibrillary Acidic Protein; Humans; Hydrocephalus, Normal Pressure; Microglia; tau Proteins

The Progression of Neuropsychiatric Symptoms in Alzheimer's Disease During a Five-Year Follow-Up: Kuopio ALSOVA Study. - Hallikainen, Ilona; Hongisto, Kristiina; Välimäki, Tarja; Hänninen, Tuomo; Martikainen, Janne; Koivisto, Anne M (J Alzheimers Dis, 2018)
BACKGROUND: An improved understanding of the role of neuropsychiatric symptoms (NPS) in the course of Alzheimer's disease (AD) has recently emerged. NPS lead to hospitalization and caregiver stress, but are more variable during the course of the disease than other symptoms. Knowledge about the role of specific NPS in disease progression and prognosis is especially limited. OBJECTIVES: To examine the relationship between specific NPS and AD severity during a 5-year follow-up period, and to determine which baseline NPS predict AD progression. METHODS: 236 persons with very mild (CDR 0.5) or mild (CDR 1) AD at baseline and their caregivers were followed up for five years as part of the ALSOVA study. The Neuropsychiatric Inventory was used to assess NPS, and AD severity progression was measured with the Clinical Dementia Rating Sum of Boxes. Data was analyzed with Generalized Estimated Equations and Linear Mixed Models. RESULTS: The baseline NPS that best predicted AD progression were delusions, agitation, and aberrant motor behavior, while AD severity during follow-up was associated with hallucinations, delusions, agitation, apathy, aberrant motor behavior, and sleep and appetite disturbances. CONCLUSIONS: Persons with mild AD presenting delusions, agitation, and aberrant motor behavior at the time of diagnosis could have a more rapidly progressing disease, and some NPS are associated with AD severity. These results highlight the importance of evaluating NPS at the time of AD diagnosis, and the need to offer additional support to persons presenting delusions, agitation and aberrant motor behavior, and their caregivers.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Anxiety; Caregivers; Delusions; Disease Progression; Female; Finland; Hallucinations; Humans; Linear Models; Male; Motor Activity; Multivariate Analysis; Neuropsychological Tests; Severity of Illness Index

Protective Effects of Indian Spice Curcumin Against Amyloid-β in Alzheimer's Disease. - Reddy, P Hemachandra; Manczak, Maria; Yin, XiangLing; Grady, Mary Catherine; Mitchell, Andrew; Tonk, Sahil; Kuruva, Chandra Sekhar; Bhatti, Jasvinder Singh; Kandimalla, Ramesh; Vijayan, Murali; Kumar, Subodh; Wang, Rui; et al. (J Alzheimers Dis, 2018)
The purpose of our article is to assess the current understanding of Indian spice, curcumin, against amyloid-β (Aβ)-induced toxicity in Alzheimer's disease (AD) pathogenesis. Natural products, such as ginger, curcumin, and gingko biloba have been used as diets and dietary supplements to treat human diseases, including cancer, cardiovascular, respiratory, infectious, diabetes, obesity, metabolic syndromes, and neurological disorders. Products derived from plants are known to have protective effects, including anti-inflammatory, antioxidant, anti-arthritis, pro-healing, and boosting memory cognitive functions. In the last decade, several groups have designed and synthesized curcumin and its derivatives and extensively tested using cell and mouse models of AD. Recent research on Aβ and curcumin has revealed that curcumin prevents Aβ aggregation and crosses the blood-brain barrier, reach brain cells, and protect neurons from various toxic insults of aging and Aβ in humans. Recent research has also reported that curcumin ameliorates cognitive decline and improves synaptic functions in mouse models of AD. Further, recent groups have initiated studies on elderly individuals and patients with AD and the outcome of these studies is currently being assessed. This article highlights the beneficial effects of curcumin on AD. This article also critically assesses the current limitations of curcumin's bioavailability and urgent need for new formulations to increase its brain levels to treat patients with AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Blood-Brain Barrier; Curcumin; Disease Models, Animal; Humans; Mice; Neuroprotective Agents; Randomized Controlled Trials as Topic; Spices

Putative Dementia Cases Fluctuate as a Function of Mini-Mental State Examination Cut-Off Points. - Rosa, Ilka M; Henriques, Ana G; Wiltfang, Jens; da Cruz E Silva, Odete A B (J Alzheimers Dis, 2018)
As the population ages, there is a growing need to quickly and accurately identify putative dementia cases. Many cognitive tests are available; among those commonly used are the Cognitive Dementia Rating (CDR) and the Mini-Mental Status Examination (MMSE). The aim of this work was to compare the validity and reliability of these cognitive tests in a primary care based cohort (pcb-Cohort). The MMSE and the CDR were applied to 568 volunteers in the pcb-Cohort. Distinct cut-off points for the MMSE were considered, namely MMSE 27, MMSE 24, and MMSE PT (adapted for the Portuguese population). The MMSE 27 identified the greatest number of putative dementia cases, and, as determined by the ROC curve, it was the most sensitive and specific of the MMSE cut-offs considered. Putative predictive or risk factors identified included age, literacy, depression, and diabetes mellitus (DM). DM has previously been indicated as a risk factor for dementia and Alzheimer's disease. Comparatively, the MMSE 27 cut-off has the greatest sensibility (94.9%) and specificity (66.3%) when compared to MMSE PT and MMSE 24. Upon comparing MMSE and CDR scores, the latter identified a further 146 putative dementia cases, thus permitting one to propose that in an ideal situation, both tests should be employed. This increases the likelihood of identifying putative dementia cases for subsequent follow up work, thus these cognitive tests represent important tools in patient care. Further, this is a significant study for Portuguese populations, where few of these studies have been carried out.
Keywords: Age Factors; Aged; Aged, 80 and over; Cohort Studies; Community Health Planning; Cross-Sectional Studies; Dementia; Female; Humans; Male; Mental Status and Dementia Tests; Middle Aged; Neuropsychological Tests; ROC Curve

Rationale and Design of the Mechanistic Potential of Antihypertensives in Preclinical Alzheimer's (HEART) Trial. - Wharton, Whitney; Goldstein, Felicia C; Tansey, Malú G; Brown, Alexandra L; Tharwani, Sonum D; Verble, Danielle D; Cintron, Amarallys; Kehoe, Patrick G (J Alzheimers Dis, 2018)
Research indicates that certain antihypertensive medications alter Alzheimer's disease (AD) biomarkers in Caucasians. The renin angiotensin system (RAS) regulates blood pressure (BP) in the body and the brain and may directly influence AD biomarkers, including amyloid-β (Aβ) neuropathology, cerebral blood flow (CBF), and inflammatory markers. This hypothesis is supported by studies, including ours, showing that antihypertensives targeting the RAS reduce the risk and slow the progression of AD in Caucasians. While mounting evidence supports a protective role of RAS medications in Caucasians, this mechanism has not been explored in African Americans. To assess the mechanism by which RAS medications modify the brain RAS, cerebrospinal fluid (CSF) Aβ, CBF, and inflammatory markers in African Americans, we are conducting an eight month, Phase Ib randomized, placebo controlled trial, enrolling 60 middle-aged (45-70 years), non-demented individuals, at risk for AD by virtue of a parental history. Participants include normotensive and treated hypertensives that have never been exposed to a RAS medication. Participants are randomized (1 : 1:1) by gender and BP medication use (yes/no) to one of three groups: placebo, or 20 mg, or 40 mg telmisartan (Micardis), to determine the dose required to penetrate the CNS. Our overarching hypothesis is that, compared to placebo, both doses of telmisartan will penetrate the CNS and produce salutary, dose dependent effects on the brain RAS as well as CSF Aβ, CBF, and CSF inflammatory markers in African Americans, over eight months. This manuscript describes the trial rationale and design.
Keywords: African Americans; Aged; Alzheimer Disease; Amyloid beta-Peptides; Antihypertensive Agents; Biomarkers; Blood Pressure; Brain; Clinical Trials, Phase I as Topic; Female; Georgia; Humans; Linear Models; Male; Middle Aged; Randomized Controlled Trials as Topic; Renin-Angiotensin System; Telmisartan

The Rationale and Design of the Reducing Pathology in Alzheimer's Disease through Angiotensin TaRgeting (RADAR) Trial. - Kehoe, Patrick G; Blair, Peter S; Howden, Beth; Thomas, David L; Malone, Ian B; Horwood, Jeremy; Clement, Clare; Selman, Lucy E; Baber, Hannah; Lane, Athene; Coulthard, Elizabeth; Passmore, Anthony Peter; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Anti-hypertensives that modify the renin angiotensin system may reduce Alzheimer's disease (AD) pathology and reduce the rate of disease progression. OBJECTIVE: To conduct a phase II, two arm, double-blind, placebo-controlled, randomized trial of losartan to test the efficacy of Reducing pathology in Alzheimer's Disease through Angiotensin TaRgeting (RADAR). METHODS: Men and women aged at least 55 years with mild-to-moderate AD will be randomly allocated 100 mg encapsulated generic losartan or placebo once daily for 12 months after successful completion of a 2-week open-label phase and 2-week placebo washout to establish drug tolerability. 228 participants will provide at least 182 subjects with final assessments to provide 84% power to detect a 25% difference in atrophy rate (therapeutic benefit) change over 12 months at an alpha level of 0.05. We will use intention-to-treat analysis, estimating between-group differences in outcomes derived from appropriate (linear or logistic) multivariable regression models adjusting for minimization variables. RESULTS: The primary outcome will be rate of whole brain atrophy as a surrogate measure of disease progression. Secondary outcomes will include changes to 1) white matter hyperintensity volume and cerebral blood flow; 2) performance on a standard series of assessments of memory, cognitive function, activities of daily living, and quality of life. Major assessments (for all outcomes) and relevant safety monitoring of blood pressure and bloods will be at baseline and 12 months. Additional cognitive assessment will also be conducted at 6 months along with safety blood pressure and blood monitoring. Monitoring of blood pressure, bloods, and self-reported side effects will occur during the open-label phase and during the majority of the post-randomization dispensing visits. CONCLUSION: This study will identify whether losartan is efficacious in the treatment of AD and whether definitive Phase III trials are warranted.
Keywords: Activities of Daily Living; Alzheimer Disease; Antihypertensive Agents; Atrophy; Blood Pressure Monitors; Brain; Clinical Trials, Phase II as Topic; Disease Progression; Double-Blind Method; Female; Humans; Losartan; Magnetic Resonance Imaging; Male; Multivariate Analysis; Quality of Life; Randomized Controlled Trials as Topic; Regression Analysis; Renin-Angiotensin System

Real World Recruiting of Older Subjects with Mild Cognitive Impairment for Exercise Trials: Community Readiness is Pivotal. - Sanders, Marit L; Stuckenschneider, Tim; Devenney, Kate E; Lawlor, Brian; Schneider, Stefan; Olde Rikkert, Marcel G M (J Alzheimers Dis, 2018)
Prevention trials in subjects with mild cognitive impairment (MCI), especially lifestyle interventions, can be difficult to carry out, particularly the recruitment and retention of subjects. We experienced these challenges in our multi-site one-year exercise trial in MCI, NeuroExercise. Trial recruitment rates differed significantly across sites; the non-medical sport university site, providing free access to a range of group exercise in a sports environment, proved far more successful than memory clinics linked to hospitals. This suggests that non-medical settings and a non-medical research community facilitating physical activities may be important factors in recruitment of subjects with MCI for large prevention trials.
Keywords: Aged; Cognitive Dysfunction; Europe; Exercise; Female; Humans; Life Style; Male; Middle Aged; Patient Selection

Reduced Gray Matter Volume of the Thalamus and Hippocampal Region in Elderly Healthy Adults with no Impact of APOE ɛ4: A Longitudinal Voxel-Based Morphometry Study. - Squarzoni, Paula; Duran, Fabio Luis Souza; Busatto, Geraldo F; Alves, Tania Correa Toledo de Ferraz (J Alzheimers Dis, 2018)
BACKGROUND: Many cross-sectional voxel-based morphometry (VBM) investigations have shown significant inverse correlations between chronological age and gray matter (GM) volume in several brain regions in healthy humans. However, few VBM studies have documented GM decrements in the healthy elderly with repeated MRI measurements obtained in the same subjects. Also, the extent to which the APOE ɛ4 allele influences longitudinal findings of GM reduction in the healthy elderly is unclear. OBJECTIVE: Verify whether regional GM changes are associated with significant decrements in cognitive performance taking in account the presence of the APOE ɛ4 allele. METHODS: Using structural MRI datasets acquired in 55 cognitively intact elderly subjects at two time-points separated by approximately three years, we searched for voxels showing significant GM reductions taking into account differences in APOE genotype. RESULTS: We found global GM reductions as well as regional GM decrements in the right thalamus and left parahippocampal gyrus (p < 0.05, family-wise error corrected for multiple comparisons over the whole brain). These findings were not affected by APOE ɛ4. CONCLUSIONS: Irrespective of APOE ɛ4, longitudinal VBM analyses show that the hippocampal region and thalamus are critical sites where GM shrinkage is greater than the degree of global volume reduction in healthy elderly subjects.
Keywords: Aged; Aging; Apolipoprotein E4; Atrophy; Cross-Sectional Studies; Female; Gray Matter; Healthy Volunteers; Hippocampus; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Organ Size; Thalamus

Relationships Between Lower Olfaction and Brain White Matter Lesions in Elderly Subjects with Mild Cognitive Impairment. - Heinrich, Juliette; Vidal, Jean-Sébastien; Simon, Axelle; Rigaud, Anne-Sophie; Hanon, Olivier; Epelbaum, Jacques; Viollet, Cécile; Duron, Emmanuelle (J Alzheimers Dis, 2018)
BACKGROUND: Olfactory impairment is reported in mild cognitive impairment (MCI) and Alzheimer's disease (AD) and is associated with hippocampal atrophy. In elderly people, dementia with AD neuropathology and white matter lesions (WML) is common. In this context, olfactory impairment could also depend on the presence of WML. OBJECTIVE: To assess the cross-sectional relationship between olfaction and WML in elderly subjects with MCI. METHODS: Consecutive subjects, >65 years old, diagnosed as MCI after a comprehensive neuropsychological assessment in an expert memory center, with a brain MRI performed within a year and without major depressive state, were included. Olfaction was assessed by the Brief Smell Identification Test (BSIT). Two trained neuroradiologists, blind to cognitive and olfaction status, visually assessed hippocampal atrophy according to Scheltens' scale and WML according to Fazekas criteria. RESULTS: Seventy-five MCI subjects (mean age (SD) = 77.1 (6.2) years, 74.7% of women) were included. After adjustment for age and sex, factors associated with low BSIT scores were older age (p = 0.007), lower BMI (p = 0.08), lower MMSE score (p = 0.05), lower FCRST (p = 0.008), hippocampal atrophy (p = 0.04), periventricular WML (p = 0.007), and deep WML burden (p = 0.005). In multivariate analysis, severe deep WML (OR (95% CI) = 6.29 (1.4-35.13), p = 0.02) remained associated with low BSIT score independently from hippocampal atrophy. CONCLUSION: In elderly MCI subjects, low olfactory performances are associated with WML, whose progression may be slowed by vascular treatments. A longitudinal study to evaluate whether the progression of WML, hippocampal atrophy and low olfactory function, can predict accurately conversion from MCI to dementia is ongoing.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Atrophy; Cognitive Dysfunction; Cross-Sectional Studies; Disease Progression; Female; Humans; Logistic Models; Longitudinal Studies; Magnetic Resonance Imaging; Male; Multivariate Analysis; Neuropsychological Tests; Olfaction Disorders; Severity of Illness Index; White Matter

Retinoic Acid Enhances Apolipoprotein E Synthesis in Human Macrophages. - Clemens, Vera; Regen, Francesca; Le Bret, Nathalie; Heuser, Isabella; Hellmann-Regen, Julian (J Alzheimers Dis, 2018)
Apolipoprotein E (ApoE) represents a pivotal target in Alzheimer's disease (AD) and is modulated through retinoic acid (RA), an endogenous neuroprotective and anti-inflammatory compound. A major source of ApoE are microglia, which are pathologically activated in AD. Activated microglia are known to block RA signaling. This suggests a vicious cycle between inflammation, RA signaling, and ApoE homeostasis in AD pathogenesis. To test this hypothesis, we investigated effects of RA and proinflammatory activation on ApoE synthesis in primary human macrophage-derived microglial-like cells. Our results indicate that proinflammatory activation attenuates ApoE synthesis, an effect blocked by RA.
Keywords: Alzheimer Disease; Apolipoproteins E; Cells, Cultured; Humans; Macrophages; Signal Transduction; Tretinoin

The Role of Verb Fluency in the Detection of Early Cognitive Impairment in Alzheimer's Disease. - Alegret, Montserrat; Peretó, Mar; Pérez, Alba; Valero, Sergi; Espinosa, Ana; Ortega, Gemma; Hernandez, Isabel; Mauleón, Ana; Rosende-Roca, Maitee; Vargas, Liliana; Rodríguez-Gómez, Octavio; Abdelnour, Carla; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Verb fluency (VF) is the less commonly used fluency test, despite several studies suggesting its potential as a neuropsychological assessment tool. OBJECTIVE: To investigate the presence of VF deficits in mild cognitive impairment (MCI) and mild Alzheimer's disease (AD) dementia; to assess the usefulness of VF in the detection of cognitively healthy (CH) people who will convert to MCI, and from MCI to dementia; and to establish the VF cut-offs useful in the cognitive assessment of Spanish population. METHODS: 568 CH, 885 MCI, and 367 mild AD dementia individuals were administered the VF test and a complete neuropsychological battery. Longitudinal analyses were performed in 231 CH and 667 MCI subjects to search for VF predictors of diagnosis conversion. RESULTS: A worsening on VF performance from CH, MCI to AD dementia groups was found. Lower performances on VF were significantly related to conversion from CH to MCI/MCI to dementia. When the effect of time to conversion was analyzed, a significant effect of VF was found on the faster conversion from CH to MCI, but not from MCI to dementia. Moreover, VF cut-off scores and sensitivity/specificity values were calculated for 6 conditions (3 age ranges by 2 educational levels). CONCLUSION: The VF test may be a useful tool for the differential diagnosis of cognitive failure in the elderly. Since VF deficits seem to take place in early stages of the disease, it is a suitable neuropsychological tool for the detection not only of CH people who will convert to MCI, but also from MCI to dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cognitive Dysfunction; Cross-Sectional Studies; Early Diagnosis; Executive Function; Female; Humans; Language Tests; Logistic Models; Longitudinal Studies; Male; Middle Aged; Proportional Hazards Models; Sensitivity and Specificity; Spain

Sally-Anne Test in Patients with Alzheimer's Disease Dementia. - Takenoshita, Shintaro; Terada, Seishi; Yokota, Osamu; Kutoku, Yumiko; Wakutani, Yosuke; Nakashima, Makoto; Maki, Yohko; Hattori, Hideyuki; Yamada, Norihito (J Alzheimers Dis, 2018)
Social cognition has recently been recognized as one of the essential cognitive domains. Some reports suggested that patients with Alzheimer's disease dementia (ADD) presented significant theory of mind deficits even in the mild condition. However, most previous studies included only small numbers of patients with ADD. The present study administered the first-order false belief (Sally-Anne) test to 116 consecutive patients with ADD from the outpatient units of the Memory Clinic and compared the characteristics of the two groups with correct and incorrect answers on the test. Then various clinical characteristics were evaluated. Only 37.1% of patients with ADD correctly answered the Sally-Anne test with the right explanation. Comparison between the two groups of correct and incorrect answers revealed a significant association between the frontal assessment battery score and the result of the Sally-Anne test in the multiple logistic regression analyses. Thus, patients with ADD presented a significant deficit in social cognition even in the mild condition. Frontal dysfunction was thought to be related to the deficits in mild ADD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognition Disorders; Disease Progression; Female; Humans; Logistic Models; Male; Neuropsychological Tests; Social Behavior Disorders; Theory of Mind

Serum C-Peptide, Visfatin, Resistin, and Ghrelin are Altered in Sporadic and GRN-Associated Frontotemporal Lobar Degeneration. - Zanardini, Roberta; Benussi, Luisa; Fostinelli, Silvia; Saraceno, Claudia; Ciani, Miriam; Borroni, Barbara; Padovani, Alessandro; Binetti, Giuliano; Ghidoni, Roberta (J Alzheimers Dis, 2018)
Frontotemporal lobar degeneration (FTLD) is a group of complex neurodegenerative disease characterized by progressive deterioration of the frontal and anterior temporal lobes of the brain resulting in different heterogeneous conditions, mainly characterized by personality changes, behavioral disturbances, such as binge eating, and deficits in language and executive functions. Null mutations in progranulin gene (GRN) are one of the most frequent genetic determinants in familial frontotemporal dementia. Recently, progranulin was recognized as an adipokine involved in diet-induced obesity and insulin resistance revealing its metabolic function. Increasing evidence suggests that neurodegenerative dementias are associated with a higher prevalence of metabolic changes than in the general population. According to these findings, the aim of this study is to investigate putative alterations in markers linked to metabolic functions (i.e., C-peptide, ghrelin, glucose-dependent insulinotropic polypeptide, glucagon-like peptide-1, glucagon, insulin, resistin, and three adipokines as visfatin, leptin, and plasminogen activator inhibitor-1 total) in sporadic and GRN-related FTLD. We found that 1) C-peptide is increased in sporadic and GRN-mutated FTLD patients; in addition, we demonstrated an anticipation of the disease in patients with the highest C-peptide concentrations; 2) visfatin is slightly reduced in the whole FTLD group; 3) resistin, an adipokine involved in inflammatory-related diseases, is specifically increased in FTLD due to GRN null mutations; 4) ghrelin concentration is specifically increased in pre-symptomatic subjects and FTLD patients with GRN mutations. These findings support the hypothesis that alterations in metabolic pattern are involved in FTLD progression highlighting novel putative targets for the development of preventive and personalized therapies.
Keywords: Aged; Biomarkers; C-Peptide; Female; Frontotemporal Lobar Degeneration; Ghrelin; Humans; Kaplan-Meier Estimate; Male; Middle Aged; Mutation; Nicotinamide Phosphoribosyltransferase; Progranulins; Resistin

Serum Non-Ceruloplasmin Non-Albumin Copper Elevation in Mild Cognitive Impairment and Dementia due to Alzheimer's Disease: A Case Control Study. - Rozzini, Luca; Lanfranchi, Francesco; Pilotto, Andrea; Catalani, Simona; Gilberti, Maria Enrica; Paganelli, Matteo; Apostoli, Pietro; Padovani, Alessandro (J Alzheimers Dis, 2018)
Several studies showed high serum copper levels in Alzheimer's disease (AD). The present study applied a newly developed method to detect serum copper free from proteins (free-Cu). Forty-four patients affected by dementia due to AD, thirty-six patients affected by mild cognitive impairment (MCI) due to AD, and twenty-eight healthy controls underwent clinical, cognitive, and MRI assessment. The new method showed higher free-Cu concentrations in MCI and dementia due to AD compared to controls (p < 0.0001). No correlation between copper levels, cognitive or MRI measures were found.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cognitive Dysfunction; Copper; Female; Humans; Magnetic Resonance Imaging; Male; Psychiatric Status Rating Scales

Sex Influences the Accuracy of Subjective Memory Complaint Reporting in Older Adults. - Sundermann, Erin E; Edmonds, Emily C; Delano-Wood, Lisa; Galasko, Douglas R; Salmon, David P; Rubin, Leah H; Bondi, Mark W (J Alzheimers Dis, 2018)
Subjective memory complaints (SMC) are required when diagnosing amnestic mild cognitive impairment (aMCI), although their relationship with objective memory performance and Alzheimer's disease (AD) pathology remains unclear. We investigated whether the sex of the patient/participant moderates these associations. Participants were 940 normal control (NC) and aMCI participants from the Alzheimer's Disease Neuroimaging Initiative. SMC were assessed via the memory scale of the Everyday Cognition questionnaire. Discrepancy scores were calculated between self- and informant-reports and categorized into "overestimates," "comparable estimates", and "underestimates" of SMC. We conducted linear and logistic regressions to examine the interaction of sex with self- and informant-reported SMC and discrepancy group on the Rey Auditory Verbal Learning Test (RAVLT) Immediate and Delayed Recall and on PET measures of amyloid-β (Aβ) positivity. Diagnosis-stratified analyses were also conducted. Overall, there were sex by self- and informant-reported SMC interactions for Immediate and Delayed Recall. Despite a higher proportion of "overestimates" in women, greater self- and informant-reported SMC showed a stronger relationship to poorer RAVLT scores in women versus men. Diagnosis-stratified analyses revealed that results were driven by aMCI participants. Conversely, overall, greater self- and informant-reported SMC related to greater odds of Aβ positivity regardless of sex. In diagnosis-stratified analyses, only informant-reported SMC related to Aβ positivity in aMCI. Relative to "comparable estimates," "underestimates" of SMC were associated with poorer RAVLT scores across sexes in the overall sample and in aMCI. The predictive utility of self-report SMC may be limited to women in aMCI. Sex differences should be considered when evaluating SMC.
Keywords: Aged; Cognitive Dysfunction; Female; Humans; Logistic Models; Male; Memory Disorders; Mental Recall; Neuropsychological Tests; Self Report; Sex Factors

Simultaneous Aerobic Exercise and Memory Training Program in Older Adults with Subjective Memory Impairments. - McEwen, Sarah C; Siddarth, Prabha; Abedelsater, Berna; Kim, Yena; Mui, Wenli; Wu, Pauline; Emerson, Natacha D; Lee, Jacob; Greenberg, Shayna; Shelton, Tiffany; Kaiser, Scott; Small, Gary W; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Several modifiable lifestyle factors have been shown to have potential beneficial effects in slowing cognitive decline. Two such factors that may affect cognitive performance and slow the progression of memory loss into dementia in older adults are cognitive training and physical activity. There are currently no effective treatments for dementia; therefore, preventative strategies to delay or prevent the onset of dementia are of critical importance. OBJECTIVE: The aim of this study was to determine the relative effectiveness of simultaneous performance of memory training and aerobic exercise to a sequential performance intervention on memory functioning in older adults. METHODS: 55 older adults (aged 60- 75) with subjective memory impairments (non-demented and non-MCI) completed the intervention that consisted of 90-minute small group classes held twice weekly. Participants were randomized to either 4-weeks of supervised strategy-based memory training done simultaneously while stationary cycling (SIM) or sequentially after the stationary cycling (SEQ). Standardized neurocognitive measures of memory, executive functioning, speed of processing, attention, and cognitive flexibility were assessed at baseline and post-intervention. RESULTS: The SIM group, but not the SEQ group, had a significant improvement on composite memory following the intervention (t(51) = 2.7, p = 0.01, effect size (ES) = 0.42) and transfer to non-trained reasoning abilities (t(51) = 6.0, ES = 0.49) and complex attention (t(51) = 3.1, p = 0.003, ES = 0.70). Conversely, the SEQ group, but not the SIM, showed significant improvement in executive functioning (t(51) = 5.0, p = 0.0001, ES = 0.96). CONCLUSION: These findings indicate that a 4-week simultaneous memory training and aerobic exercise program is sufficient to improve memory, attention, and reasoning abilities in older adults.
Keywords: Aged; Attention; California; Cognition; Executive Function; Exercise; Female; Humans; Learning; Male; Memory; Memory Disorders; Middle Aged; Treatment Outcome

SORL1 Variants in Familial Alzheimer's Disease. - Gómez-Tortosa, Estrella; Ruggiero, María; Sainz, Ma José; Villarejo-Galende, Alberto; Prieto-Jurczynska, Cristina; Venegas Pérez, Begoña; Ordás, Carlos; Agüero, Pablo; Guerrero-López, Rosa; Pérez-Pérez, Julián (J Alzheimers Dis, 2018)
The SORL1 gene encodes a protein involved in the amyloidogenic process, and its variants have been associated with Alzheimer's disease (AD) physiopathology. We screened for SORL1 variants in 124 familial (44 early- and 80 late-onset) dementia of Alzheimer type (DAT) cases. Nine potentially pathogenic changes (three not previously reported and six rare variants) were found in nine probands (7%). After screening the control population and siblings (presence in at least 1/200 controls and/or absence of segregation pattern), a causal relationship with the disease was considered unlikely in six variants and uncertain in one. The change Trp848Ter and a splice-site variant remained likely correlated with the disease. SORL1 mutations are present in 7% of our familial DAT cohort, though in most cases cannot be considered the direct cause of the disease.
Keywords: Aged; Alzheimer Disease; Case-Control Studies; Female; Gene Frequency; Genetic Predisposition to Disease; Humans; LDL-Receptor Related Proteins; Male; Membrane Transport Proteins; Middle Aged; Mutation; Polymorphism, Single Nucleotide; Siblings; Spain

SPARCL1 Accelerates Symptom Onset in Alzheimer's Disease and Influences Brain Structure and Function During Aging. - Seddighi, Sahba; Varma, Vijay R; An, Yang; Varma, Sudhir; Beason-Held, Lori L; Tanaka, Toshiko; Kitner-Triolo, Melissa H; Kraut, Michael A; Davatzikos, Christos; Thambisetty, Madhav (J Alzheimers Dis, 2018)
We recently reported that alpha-2 macroglobulin (A2M) is a biomarker of neuronal injury in Alzheimer's disease (AD) and identified a network of nine genes co-expressed with A2M in the brain. This network includes the gene encoding SPARCL1, a protein implicated in synaptic maintenance. Here, we examine whether SPARCL1 is associated with longitudinal changes in brain structure and function in older individuals at risk for AD in the Baltimore Longitudinal Study of Aging. Using data from the Gene-Tissue Expression Project, we first identified two single nucleotide polymorphisms (SNPs), rs9998212 and rs7695558, associated with lower brain SPARCL1 gene expression. We then analyzed longitudinal trajectories of cognitive performance in 591 participants who remained cognitively normal (average follow-up interval: 11.8 years) and 129 subjects who eventually developed MCI or AD (average follow-up interval: 9.4 years). Cognitively normal minor allele carriers of rs7695558 who developed incident AD showed accelerated memory loss prior to disease onset. Next, we compared longitudinal changes in brain volumes (MRI; n = 120 participants; follow-up = 6.4 years; 826 scans) and resting-state cerebral blood flow (rCBF; 15O-water PET; n = 81 participants; follow-up = 7.7 years; 664 scans) in cognitively normal participants. Cognitively normal minor allele carriers of rs9998212 showed accelerated atrophy in several global, lobar, and regional brain volumes. Minor allele carriers of both SNPs showed longitudinal changes in rCBF in several brain regions, including those vulnerable to AD pathology. Our findings suggest that SPARCL1 accelerates AD pathogenesis and thus link neuroinflammation with widespread changes in brain structure and function during aging.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Brain; Calcium-Binding Proteins; Cerebrovascular Circulation; Cognition Disorders; Extracellular Matrix Proteins; Female; Humans; Independent Living; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Polymorphism, Single Nucleotide; Positron-Emission Tomography

Structural Connectivity Alterations Along the Alzheimer's Disease Continuum: Reproducibility Across Two Independent Samples and Correlation with Cerebrospinal Fluid Amyloid-β and Tau. - Tucholka, Alan; Grau-Rivera, Oriol; Falcon, Carles; Rami, Lorena; Sánchez-Valle, Raquel; Lladó, Albert; Gispert, Juan Domingo; Molinuevo, José Luis (J Alzheimers Dis, 2018)
BACKGROUND: Gray matter changes associated with the progression of Alzheimer's disease (AD) have been thoroughly studied. However, alterations in white matter tracts have received less attention, particularly during early or preclinical stages of the disease. OBJECTIVE: To identify the structural connectivity changes across the AD continuum. METHODS: We performed probabilistic tractography in a total of 183 subjects on two independent samples that include control (n = 68) and preclinical AD individuals (n = 28), patients diagnosed with mild cognitive impairment (MCI) due to AD (n = 44), and AD patients (n = 43). We compared the connectivity between groups, and with CSF Aβ42 and tau biomarkers. RESULTS: We observed disconnections in preclinical individuals, mainly located in the temporal lobe. This pattern of disconnection spread to the parietal and frontal lobes at the MCI stage and involved almost all the brain in AD. These findings were not driven by gray matter atrophy. DISCUSSION: Using tractography, we were able to identify white matter changes between subsequent disease stages and, notably, also in preclinical AD. Therefore, this method may be useful for detecting early and specific brain structural changes during preclinical AD stage.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Atrophy; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Cohort Studies; Disease Progression; Female; Gray Matter; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Reproducibility of Results; Spain; tau Proteins; White Matter

Supplemental Retinal Carotenoids Enhance Memory in Healthy Individuals with Low Levels of Macular Pigment in A Randomized, Double-Blind, Placebo-Controlled Clinical Trial. - Power, Rebecca; Coen, Robert F; Beatty, Stephen; Mulcahy, Riona; Moran, Rachel; Stack, Jim; Howard, Alan N; Nolan, John M (J Alzheimers Dis, 2018)
BACKGROUND: There is a biologically plausible rationale whereby the dietary carotenoids lutein (L), zeaxanthin (Z), and meso-zeaxanthin (MZ), which are collectively referred to as macular pigment (MP) in the central retina (macula), support the maintenance of cognition via their antioxidant and anti-inflammatory properties. OBJECTIVE: To investigate the impact of supplemental L, Z, and MZ on memory, executive function, and verbal fluency among healthy individuals with low MP levels. METHODS: In this double-blind, placebo-controlled, randomized clinical trial, subjects (n = 91; mean±SD age = 45.42±12.40; % male = 51.6) consumed a daily formulation of 10 mg L, 10 mg MZ, and 2 mg Z (n = 45) or placebo (n = 46) for 12 months. Cognitive domains assessed included verbal and visual learning, immediate and delayed memory, executive function, and verbal fluency. MP and serum carotenoid concentrations of L, Z, and MZ were also measured. RESULTS: Following 12-month supplementation, individuals in the active group exhibited statistically significant improvements in memory when compared to the placebo group (paired associated learning [PAL] memory score [rANOVA, p = 0.009]; PAL errors [rANOVA, p = 0.017]). Furthermore, the observed reduction in the number of errors made in the PAL task among those in the intervention group was positively and significantly related to observed increases in MP volume (p = 0.005) and observed increases in serum concentrations of L (p = 0.009). CONCLUSION: This randomized, double-blind, placebo-controlled clinical trial demonstrates a memory-enhancing effect of daily supplementation with L, Z, and MZ in healthy subjects with low MP at baseline. The implications of these findings for intellectual performance throughout life, and for risk of cognitive decline in later life, warrant further study.
Keywords: Adult; Cognition; Dietary Supplements; Double-Blind Method; Executive Function; Female; Healthy Volunteers; Humans; Lutein; Macular Pigment; Male; Memory, Episodic; Middle Aged; Retina; Vision Tests; Zeaxanthins

Tau and Amyloid Positron Emission Tomography Imaging Predict Driving Performance Among Older Adults with and without Preclinical Alzheimer's Disease. - Roe, Catherine M; Babulal, Ganesh M; Mishra, Shruti; Gordon, Brian A; Stout, Sarah H; Ott, Brian R; Carr, David B; Ances, Beau M; Morris, John C; Benzinger, Tammie L S (J Alzheimers Dis, 2018)
Abnormal levels of Alzheimer's disease (AD) biomarkers, measured by positron emission tomography imaging using amyloid-based radiotracers and cerebrospinal fluid, are associated with impaired driving performance in older adults. We examined whether preclinical AD staging, defined using amyloid imaging and tau imaging using the radiotracer T807 (AKA flortaucipir or AV-1451), was associated with receiving a marginal/fail rating on a standardized road test (n = 42). Participants at Stage 2 (positive amyloid and tau scans) of preclinical AD were more likely to receive a marginal/fail rating compared to participants at Stage 0 or 1. Stage 2 preclinical AD may manifest in worse driving performance.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid; Automobile Driving; Biomarkers; Carbolines; Female; Humans; Logistic Models; Male; Neuroimaging; Positron-Emission Tomography; tau Proteins

Testamentary Capacity Assessment Tool (TCAT): A Brief Instrument for Patients with Dementia. - Papageorgiou, Sokratis G; Voskou, Panagiota; Economou, Alexandra; Beratis, Ion; Douzenis, Athanasios (J Alzheimers Dis, 2018)
BACKGROUND: In current practice, it is common for the medical practitioner to assess a person's testamentary capacity (TC) and give evidence to the Courts about a potential will contest. TC is an advanced cognitive activity that is both situation- and task-specific. OBJECTIVE: The aim of the present study was the development of a brief, specialized instrument for TC assessment in patients with dementia. METHOD: We developed a short tool consisting of four subtests, assessing the person's core functions which are required for TC: memory (orientation, autobiographical memory and realistic perception of beneficiaries), absence of serious psychopathology, knowledge of financial parameters (value of assets, everyday life products, bills), and intention (vignettes, theory of mind). For its validation, we examined 64 outpatients from the Cognitive Disorders/Dementia Unit, 2nd Department of Behavioral Neurology, University of Athens. The decision of the expert served as the gold standard for the evaluation of TC. RESULTS: Of the 64 participants, 39 were judged by the expert as capable of TC and the remaining 25 as incapable. For the total scale (maximum score of 48), the best combination of sensitivity (82.6%) and specificity (100%) was obtained for a cut-off score of 32/33. Cronbach's alpha showed high levels of internal reliability for the scale (α= 0.86) and the point-biserial correlation coefficients showed high levels of criterion-related validity (rbp = 0.797, p < 0.001). CONCLUSION: The new instrument appears to be a reliable screening tool for the evaluation of TC in dementia, which can be used by both the expert and the non-expert. Further research is needed to confirm these promising findings.
Keywords: Adult; Aged; Cognition Disorders; Dementia; Female; Humans; Male; Memory; Mental Competency; Middle Aged; Neuropsychological Tests; Reproducibility of Results; Sensitivity and Specificity; Wills

Transcranial Sonography in Neurodegenerative Diseases with Cognitive Decline. - Favaretto, Silvia; Walter, Uwe; Baracchini, Claudio; Cagnin, Annachiara (J Alzheimers Dis, 2018)
Transcranial sonography (TCS) of the brain parenchyma detects alterations in the substantia nigra (SN), raphe nuclei and basal ganglia; this technique has been established as a tool for the early diagnosis of Parkinson's disease and differential diagnosis from atypical parkinsonian syndromes. Here, we aimed to review the main applications of TCS in neurodegenerative diseases presenting with dementia syndrome, focusing on Alzheimer's disease (AD), dementia with Lewy bodies (DLB), frontotemporal lobar degeneration, idiopathic normal pressure hydrocephalus, and atypical and secondary parkinsonisms. The finding of bilaterally marked hyperechogenicity of the SN appears as a characteristic feature of DLB, while it is found only in a minority of AD patients. SN hyperechogenicity is also detected in most patients with corticobasal degeneration and in about one third of patients with progressive supranuclear palsy, in which is constantly associated with hyperechogenic alterations of the basal ganglia. In conclusion, TCS is a valid supportive tool in the diagnostic workup of patients with dementia due to different neurodegenerative conditions. A promising new application is the differentiation of DLB from AD even at the early stages of these diseases.
Keywords: Cognition Disorders; Humans; Neurodegenerative Diseases; Ultrasonography, Doppler, Transcranial

The Uniform Data Set, Czech Version: Normative Data in Older Adults from an International Perspective. - Nikolai, Tomas; Stepankova, Hana; Kopecek, Miloslav; Sulc, Zdenek; Vyhnálek, Martin; Bezdicek, Ondrej (J Alzheimers Dis, 2018)
BACKGROUND: Outside of the United States, international perspectives on normative data for neuropsychological test performance, within diverse populations, have been scarce. The neuropsychological test battery from the Uniform Data Set (UDS) of the Alzheimer's Disease Centers (ADC) program of the United States National Institute on Aging (NIA) is one of the most sensitive batteries for the evaluation of both normal cognitive aging and pathological cognitive decline. OBJECTIVE: This study aimed to determine the feasibility of the Czech Neuropsychological Test Battery from the Uniform Data Set (UDS-Cz 2.0), while also evaluating the results obtained from an international perspective. METHODS: This paper describes data from 520 cognitively normal participants. Regression analyses were used to describe the influence of demographic variables on UDS-Cz test performance. RESULTS: Cognitive performance on all measures declined with age, with patient education level serving as a protective factor. Therefore, the present study provides normative data for the UDS-Cz, adjusted for the demographic variables of age and education. CONCLUSION: The present study determines the psychometric properties of the UDS-Cz and establishes normative values in the aging Czech population, which can be used in clinical settings.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognition; Czech Republic; Female; Humans; Internationality; Male; Middle Aged; National Institute on Aging (U.S.); Neuropsychological Tests; Psychometrics; Reference Values; Regression Analysis; United States

Update on Vascular Cognitive Impairment Associated with Subcortical Small-Vessel Disease. - Wallin, Anders; Román, Gustavo C; Esiri, Margaret; Kettunen, Petronella; Svensson, Johan; Paraskevas, George P; Kapaki, Elisabeth (J Alzheimers Dis, 2018)
Subcortical small-vessel disease (SSVD) is a disorder well characterized from the clinical, imaging, and neuropathological viewpoints. SSVD is considered the most prevalent ischemic brain disorder, increasing in frequency with age. Vascular risk factors include hypertension, diabetes, hyperlipidemia, elevated homocysteine, and obstructive sleep apnea. Ischemic white matter lesions are the hallmark of SSVD; other pathological lesions include arteriolosclerosis, dilatation of perivascular spaces, venous collagenosis, cerebral amyloid angiopathy, microbleeds, microinfarcts, lacunes, and large infarcts. The pathogenesis of SSVD is incompletely understood but includes endothelial changes and blood-brain barrier alterations involving metalloproteinases, vascular endothelial growth factors, angiotensin II, mindin/spondin, and the mammalian target of rapamycin pathway. Metabolic and genetic conditions may also play a role but hitherto there are few conclusive studies. Clinical diagnosis of SSVD includes early executive dysfunction manifested by impaired capacity to use complex information, to formulate strategies, and to exercise self-control. In comparison with Alzheimer's disease (AD), patients with SSVD show less pronounced episodic memory deficits. Brain imaging has advanced substantially the diagnostic tools for SSVD. With the exception of cortical microinfarcts, all other lesions are well visualized with MRI. Diagnostic biomarkers that separate AD from SSVD include reduction of cerebrospinal fluid amyloid-β (Aβ)42 and of the ratio Aβ42/Aβ40 often with increased total tau levels. However, better markers of small-vessel function of intracerebral blood vessels are needed. The treatment of SSVD remains unsatisfactory other than control of vascular risk factors. There is an urgent need of finding targets to slow down and potentially halt the progression of this prevalent, but often unrecognized, disorder.
Keywords: Animals; Cerebrovascular Disorders; Dementia; Humans

Validation of the Delayed Matching-to-Sample Task 48 (DMS48) in Elderly Chinese. - Feng, Xueyan; Zhou, Aihong; Liu, Zhixin; Li, Fangyu; Wei, Cuibai; Zhang, Guili; Jia, Jianping (J Alzheimers Dis, 2018)
BACKGROUND: Delayed Matching-to-Sample Task 48 (DMS48), a brief tool measuring visual recognition memory, is valid to identify the early stage of Alzheimer's disease (AD) in Caucasians. However, little data is available in Chinese. OBJECTIVE: To develop norms and optimal cutoff points for the DMS48 in Chinese elders. METHODS: A cross-sectional study was conducted in seven memory clinics from five cities across China. DMS48 was applied to 369 Chinese aged 50 or older (138 cognitively normal [CN], 112 mild cognitive impairment due to AD (MCI-A), and 119 mild AD dementia). The demographic factors which influence DMS48 scores were investigated and the norms were established considering those factors. Receiver operating characteristic (ROC) analysis was used to determine the optimal cutoff points. RESULTS: Age was shown to influence DMS48 scores (r = -0.36, p < 0.05), and we presented the age-stratified normative data for the DMS48. The optimal cutoff point is 42/43 for identifying cognitive impairment (MCI-A and AD dementia) against CN (sensitivity 97.80% and specificity 89.13%) and MCI-A against CN (sensitivity 86.60% and specificity 94.20%). A cutoff of 39/40 obtained good sensitivity (100.00%) and specificity (94.90%) in discriminating AD dementia from CN. The age-stratified optimal cutoff points for identifying MCI-A were 43/44 for individuals aged 50 to 59 years old, 42/43 for 60 to 69 years old, 41/42 for 70 to 79 years old, and 40/41 for 80 or older, respectively (sensitivity 84.80% and specificity 95.70%). CONCLUSION: This study proved that DMS48 is of good validation in screening MCI-A in elderly Chinese.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; China; Cognitive Dysfunction; Cross-Sectional Studies; Female; Humans; Linear Models; Male; Memory Disorders; Middle Aged; Neuropsychological Tests; ROC Curve; Sensitivity and Specificity; Severity of Illness Index

VEGFR1 and VEGFR2 in Alzheimer's Disease. - Harris, Rachel; Miners, James Scott; Allen, Shelley; Love, Seth (J Alzheimers Dis, 2018)
Vascular endothelial growth factor (VEGF) is a potent angiogenic factor. Despite upregulation of VEGF in the brain in Alzheimer's disease (AD), probably in response to amyloid-β, vasoconstriction, and tissue hypoxia, there is no consequent increase in microvessel density. VEGF binds to and activates VEGF receptor 2 (VEGFR2), but also binds to VEGF receptor 1 (VEGFR1), which exists in less-active membrane-bound and inactive soluble (sVEGFR1) forms and inhibits pro-angiogenic signaling. We have investigated whether altered expression of VEGF receptors might account for the lack of angiogenic response to VEGF in AD. We assessed the cellular distribution and protein level of VEGFR1 and VEGFR2 in parietal cortex from 50 AD and 36 age-matched control brains, and related the findings to measurements of VEGF and von Willebrand factor level (a marker of microvessel density) in the same tissue samples. VEGFR2 was expressed by neurons, astrocytes and endothelial cells. VEGFR1 was expressed predominantly neuronally and was significantly reduced in AD (p = 0.02). Western blot analysis on a subset of brains showed reduction in VEGFR1:sVEGFR1 in AD (p = 0.046). The lack of angiogenesis despite cerebral hypoperfusion in AD is not explained by altered expression of VEGFR2 or total VEGFR1; indeed, the downregulation of VEGFR1 may represent a pro-angiogenic response to the hypoperfusion. However, the relative increase in sVEGFR1 would be expected to have an anti-angiogenic effect which may be a factor in AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Case-Control Studies; Endothelial Cells; Female; Gene Expression Regulation; Humans; Male; Middle Aged; Neovascularization, Pathologic; RNA, Messenger; Signal Transduction; Vascular Endothelial Growth Factor A; Vascular Endothelial Growth Factor Receptor-1; Vascular Endothelial Growth Factor Receptor-2

Vestibular Loss Predicts Poorer Spatial Cognition in Patients with Alzheimer's Disease. - Wei, Eric X; Oh, Esther S; Harun, Aisha; Ehrenburg, Matthew; Agrawal, Yuri (J Alzheimers Dis, 2018)
The vestibular system is an important contributor to balance control, spatial orientation, and falls risk. Recent evidence has shown that Alzheimer's disease (AD) patients have a higher prevalence of vestibular impairment relative to healthy controls. We sought to evaluate whether vestibular loss is specifically associated with poor spatial cognitive skills among patients with mild cognitive impairment (MCI) and AD. We enrolled 50 patients (22 MCI and 28 AD) from an interdisciplinary Memory Clinic and measured vestibular physiologic function in all patients. Spatial cognitive function was assessed using the Money Road Map Test (MRMT) and the Trail Making Test Part B (TMT-B). General cognitive function was assessed with the Mini-Mental Status Examination (MMSE). In multivariable linear regression analyses adjusted for age, gender, education level, and MMSE, MCI and AD patients with vestibular loss made significantly more errors on the MRMT relative to patients with normal vestibular function (β= 7.3, 95% CI 2.4, 12.1 for unilateral vestibular loss and β= 6.4, 95% CI 1.9, 10.9 for bilateral vestibular loss). We further stratified AD patients into "spatially normal" and "spatially impaired" groups based on MRMT performance, and found that the prevalence of vestibular loss was significantly higher in the spatially impaired AD group relative to the spatially normal AD group. These findings support the hypothesis that vestibular loss contributes specifically to a decline in spatial cognitive ability in MCI and AD patients, independently of general cognitive decline, and may predict a "spatially impaired" subtype of AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Bilateral Vestibulopathy; Cognitive Dysfunction; Cross-Sectional Studies; Female; Humans; Linear Models; Male; Multivariate Analysis; Neuropsychological Tests; Prospective Studies; Spatial Navigation; Vestibular Function Tests

Visit-To-Visit Blood Pressure Variability and the Risk of Dementia in Older People. - van Middelaar, Tessa; van Dalen, Jan W; van Gool, Willem A; van den Born, Bert-Jan H; van Vught, Lonneke A; Moll van Charante, Eric P; Richard, Edo (J Alzheimers Dis, 2018)
BACKGROUND: High visit-to-visit variability (VVV) in blood pressure (BP) is associated with cerebrovascular lesions on neuroimaging. OBJECTIVE: Our primary objective was to investigate whether VVV is associated with incident all-cause dementia. As a secondary objective, we studied the association of VVV with cognitive decline and cardiovascular disease (CVD). METHODS: We included community-dwelling people (age 70-78 year) from the 'Prevention of Dementia by Intensive Vascular Care' (preDIVA) trial with three to five 2-yearly BP measurements during 6-8 years follow-up. VVV was defined using coefficient of variation (CV; SD/mean×100). Cognitive decline was assessed using the Mini-Mental State Examination (MMSE). Incident CVD was defined as myocardial infarction or stroke. We used a Cox proportional hazard regression and mixed-effects model adjusted for sociodemographic factors and cardiovascular risk factors. RESULTS: In 2,305 participants (aged 74.2±2.5), mean systolic BP over all available visits was 150.1 mmHg (SD 13.6), yielding a CV of 9.0. After 6.4 years (SD 0.8) follow-up, 110 (4.8%) participants developed dementia and 140 (6.1%) CVD. Higher VVV was not associated with increased risk of dementia (hazard ratio [HR] 1.00 per point CV increase; 95% confidence interval [CI] 0.96-1.05), although the highest quartile of VVV was associated with stronger decline in MMSE (β -0.09, 95% CI -0.17 to -0.01). Higher VVV was associated with incident CVD (HR 1.07; 95% CI 1.04-1.11). CONCLUSION: In our study among older people, high VVV is not associated with incident all-cause dementia. It is associated with decline in MMSE and incident CVD.
Keywords: Aged; Antihypertensive Agents; Blood Pressure; Cardiovascular Diseases; Dementia; Female; Humans; Hypertension; Incidence; Male; Netherlands; Proportional Hazards Models; Risk Factors

When Art Meets Gardens: Does It Enhance the Benefits? The Nancy Hypothesis of Care for Persons with Alzheimer's Disease. - Jonveaux, Thérèse Rivasseau; Fescharek, Reinhard (J Alzheimers Dis, 2018)
The creation of healing gardens for persons with Alzheimer's disease and related diseases (ADRD) offers vast potential. They can play a role in the scaffolding of cognitive disorders, emotional stress, sensory processing, sense of harmony, and appeasement. These effects are achieved through a distributed interplay of psychological functions with the immediate environment and local culture on the one hand, and dialogue on the other. The garden, a natural canvas created by man, shares with art the ability to foster an esthetic sense for which the perception can be measured by functional neurological imaging exploration. Art represents a mediator for the collaborative realization of distributed psychological functions between different individuals. Based on the hypothesis of an optimization of the therapeutic potential of a garden by a design adapted to the neuro-psycho-social and cultural specificities of its users combined with the thoughtful introduction of an artistic dimension, the "art, memory and life" healing garden was created at the University Hospital of Nancy as a prototype for persons with ADRD. The design concept was based on two hypotheses that we formulate herein, discuss their theoretical foundation, and suggest enhanced design for therapeutic gardens based upon our experience.
Keywords: Alzheimer Disease; Art Therapy; Cognition; Cognitive Behavioral Therapy; France; Gardening; Humans

White Matter Hyperintensity Predicts the Risk of Incident Cognitive Decline in Community Dwelling Elderly. - Ding, Ding; Xiong, Yunyun; Zhao, Qianhua; Guo, Qihao; Chu, Shuguang; Chu, Winnie W C; Luo, Jianfeng; Liang, Xiaoniu; Zheng, Li; Hong, Zhen; Wong, Lawrence K S; Mok, Vincent C T (J Alzheimers Dis, 2018)
BACKGROUND: Unlike western countries, data on white matter hyperintensity (WMH) in community dwelling elderly in Asian population is very limited. OBJECTIVE: To examine the relation between baseline WMH burden and the risk of incident cognitive decline in a community-based cohort with Chinese-dwelling elderly. METHODS: We prospectively evaluated the incident cognitive decline for 226 participants in the Shanghai Aging Study. Baseline WMH severity was visually rated by the age-related white matter changes (ARWMC) scale based on MRI. Cox proportional hazards regression model was used to estimate the relative risk (RR) of total ARWMC scale, global ARWMC score, presence of lacune and microbleed, for incident cognitive decline by adjusting potential confounders. RESULTS: Forty subjects were identified with incident cognitive decline (new onset 34 mild cognitive impairment and 6 dementia) during a median duration of 6 years follow-up. The incidence of cognitive decline was 3.0 (95% confidence interval [CI] 2.2-4.1) per 100 person-years. Increasing total ARWMC scale [RR1.21 (95% CI 1.06-1.39), p = 0.004)], confluent WMH [RR3.16 (95% CI 1.50-6.64), p = 0.002), and presence of lacunes [RR 2.73 (95% CI 1.21-6.15)] at baseline were independent predictors of incident cognitive decline. CONCLUSION: Our study demonstrated that confluent WMH may increase the risk of incident cognitive decline by 3 folds in community dwelling subjects. Small vessel disease may cause heavy burden of cognitive impairment in the elderly in China.
Keywords: Aged; China; Cognitive Dysfunction; Female; Humans; Independent Living; Kaplan-Meier Estimate; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Proportional Hazards Models; Prospective Studies; Risk Factors; White Matter

Word and Picture Version of the Free and Cued Selective Reminding Test (FCSRT): Is There Any Difference? - Arighi, Andrea; Carandini, Tiziana; Mercurio, Matteo; Carpani, Giovanni; Pietroboni, Anna Margherita; Fumagalli, Giorgio; Ghezzi, Laura; Basilico, Paola; Calvi, Alberto; Scarioni, Marta; De Riz, Milena; Fenoglio, Chiara; et al. (J Alzheimers Dis, 2018)
The Free and Cued Selective Reminding Test (FCSRT) is the most commonly used neuropsychological test to evaluate episodic memory. Two variants of FCSRT exist, using the recall of words (FCSRT-w) or pictures (FCSRT-p). Fourteen patients with mild cognitive impairment underwent neuropsychological evaluation and brain magnetic resonance. We found differences in FCSRT-w and FCSRT-p variants scores. FCSRT-p was correlated with atrophy in areas involved in visual stimuli processing while FCSRT-w was correlated to hippocampal atrophy. Our study suggests that FCSRT-w and FCSRT-p scores are not equivalent, but a larger cohort of patients is needed to validate these results.
Keywords: Aged; Aged, 80 and over; Association Learning; Cognitive Dysfunction; Cues; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Recall; Middle Aged; Neuropsychological Tests; Photic Stimulation; Vocabulary

18F-AV-1451 PET Imaging in Three Patients with Probable Cerebral Amyloid Angiopathy. - Kim, Hee Jin; Cho, Hanna; Werring, David J; Jang, Young Kyoung; Kim, Yeo Jin; Lee, Jin San; Lee, Juyoun; Jun, Soomin; Park, Seongbeom; Ryu, Young Hoon; Choi, Jae Yong; Cho, Young Seok; et al. (J Alzheimers Dis, 2017)
Cerebrovascular deposition of amyloid-β, known as cerebral amyloid angiopathy (CAA), is associated with MRI findings of lobar hemorrhage, cerebral microbleeds, and cortical superficial siderosis. Although pathological studies suggest that tau may co-localize with vascular amyloid, this has not yet been investigated in CAA in vivo. Three patients with probable CAA underwent 11C-Pittsburgh Compound B (PiB) PET or 18F-florbetaben PET to evaluate amyloid burden, and 18F-AV-1451 PET to evaluate paired helical filament tau burden. Regions that had cerebral microbleeds or cortical superficial siderosis largely overlapped with those showing increased 18F-AV-1451. Our preliminary study raised the possibility that lobar cerebral microbleeds, and cortical superficial siderosis, which are characteristic markers of vascular amyloid, may be associated with local production of paired helical filament tau.
Keywords: Aged; Aged, 80 and over; Aniline Compounds; Brain; Carbolines; Cerebral Amyloid Angiopathy; Female; Humans; Image Processing, Computer-Assisted; Male; Positron-Emission Tomography; Thiazoles

Abnormalities of Cerebral Deep Medullary Veins on 7 Tesla MRI in Amnestic Mild Cognitive Impairment and Early Alzheimer's Disease: A Pilot Study. - Bouvy, Willem H; Kuijf, Hugo J; Zwanenburg, Jaco J M; Koek, Huiberdina L; Kappelle, L Jaap; Luijten, Peter R; Ikram, M Kamran; Biessels, Geert Jan (J Alzheimers Dis, 2017)
Cerebral small vessel disease (SVD) contributes to cognitive impairment and dementia. SVD may affect veins, but veins are difficult to detect with 1.5 and 3T MRI. We compared deep medullary veins (DMVs) visualized on 7T-MRI between patients with early Alzheimer's disease (eAD; n = 17) or amnestic MCI (aMCI; n = 12) and controls (n = 40). The number and density of DMVs was similar in patients and controls, but tortuosity was higher in eAD (Cohen's d = 0.7, 95% CI: 0.1-1.2, p = 0.02) and aMCI (Cohen's d = 0.8, 95% CI: 0.2-1.5, p = 0.01), independent of brain atrophy. Venous changes provide a new perspective on vascular involvement in dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Brain; Cerebral Small Vessel Diseases; Cognitive Dysfunction; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male

Amyloid-β Deposition and Long-Term Progression in Mild Cognitive Impairment due to Alzheimer's Disease Defined with Amyloid PET Imaging. - Hatashita, Shizuo; Wakebe, Daichi (J Alzheimers Dis, 2017)
The aim was to evaluate brain amyloid-β (Aβ) deposition in patients with mild cognitive impairment (MCI) due to Alzheimer's disease (AD) using amyloid PET imaging and clarify the relationship between the annual change in Aβ deposition and disease progression. Forty-eight MCI patients underwent neuropsychological assessment and amyloid PET imaging using [11C]-PIB over a follow-up of 5.7±1.5 years. Thirty-nine MCI patients who had an amyloid-positive scan were defined as MCI due to AD, and 9 MCI patients who had an amyloid-negative scan were included. Regions of interest were defined on co-registered MRI, and the PIB standardized uptake value ratio (SUVR) on the same regions was used over follow-up. Annual change in PIB SUVR was calculated. Patients with MCI due to AD had higher baseline PIB SUVR (1.81±0.32, n = 39, p < 0.01) and a greater annual rate of change in PIB SUVR (0.044±0.027, n = 39, p < 0.01) compared to amyloid-negative MCI patients. Twenty-eight (71.8%) progressed to AD. In patients who progressed during a short duration of 1.7±0.8 years, the annual rate of increase in PIB SUVR was 0.101±0.094 (n = 16, p < 0.05), which was greater compared to patients with long conversion or stable patients. There was a negative correlation between the annual rate of increase in PIB SUVR and duration of progression to AD among individual MCI converters (r = -0.47, n = 28, p < 0.05). The patients defined as MCI due to AD could progress to AD with a shorter period if they have a greater increased annual rate in brain Aβ deposition.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid; Aniline Compounds; Cognitive Dysfunction; Disease Progression; Female; Follow-Up Studies; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Positron-Emission Tomography; Thiazoles

Cholinesterase Inhibitor Therapy in Alzheimer's Disease: The Limits and Tolerability of Irreversible CNS-Selective Acetylcholinesterase Inhibition in Primates. - Moss, Donald E; Perez, Ruth G; Kobayashi, Haruo (J Alzheimers Dis, 2017)
Irreversible acetylcholinesterase (AChE) inhibition accumulates to high levels in the central nervous system (CNS) because AChE turnover in the brain is much slower than in peripheral tissues. As expected from this CNS selectivity, the irreversible AChE inhibitor methanesulfonyl fluoride (MSF) produces significant cognitive improvement in Alzheimer's disease patients without the gastrointestinal toxicity that plagues other AChE inhibitors. However, without dose-limiting gastrointestinal toxicity, one shortcoming of the prior human studies of MSF is that the upper limits of CNS AChE inhibition that might be tolerated could not be tested. Therefore, in this study, monkeys were treated with escalating intramuscular (IM) doses of MSF that culminated with several weeks of 1.5 mg/kg dosing, more than eight times the prior human clinical dose, still without signs of toxicity. Brain biopsies showed that ∼80% AChE inhibition had been produced and that the new synthesis of cortical AChE had a half-time (t1/2) of ∼12 days. A single IM dose of 1.5 mg/kg MSF produced ∼59% inhibition in cerebrospinal fluid (CSF) AChE as measured one day later. This corresponds to a peak of ∼80% inhibition in CSF AChE at the time of the injection, recovering with a t1/2 of 2.4 days. Computational analyses suggest that MSF at clinically relevant doses could theoretically produce a steady-state AChE inhibition between 65% and 85% in the CNS. These data suggest that the full therapeutic advantage of AChE inhibition therapy can be realized without interference from dose-limiting gastrointestinal toxicity if an irreversible inhibitor is employed.
Keywords: Acetylcholinesterase; Alzheimer Disease; Animals; Brain; Cholinesterase Inhibitors; Dose-Response Relationship, Drug; Drug Evaluation, Preclinical; Erythrocytes; Injections, Intramuscular; Macaca fascicularis; Male; Nootropic Agents; Time Factors

Combined Dual-Task Gait Training and Aerobic Exercise to Improve Cognition, Mobility, and Vascular Health in Community-Dwelling Older Adults at Risk for Future Cognitive Decline1. - Gregory, Michael A; Boa Sorte Silva, Narlon C; Gill, Dawn P; McGowan, Cheri L; Liu-Ambrose, Teresa; Shoemaker, J Kevin; Hachinski, Vladimir; Holmes, Jeff; Petrella, Robert J (J Alzheimers Dis, 2017)
This 6-month experimental case series study investigated the effects of a dual-task gait training and aerobic exercise intervention on cognition, mobility, and cardiovascular health in community-dwelling older adults without dementia. Participants exercised 40 min/day, 3 days/week for 26 weeks on a Biodex GaitTrainer2 treadmill. Participants were assessed at baseline (V0), interim (V1: 12-weeks), intervention endpoint (V2: 26-weeks), and study endpoint (V3: 52-weeks). The study outcomes included: cognition [executive function (EF), processing speed, verbal fluency, and memory]; mobility: usual & dual-task gait (speed, step length, and stride time variability); and vascular health: ambulatory blood pressure, carotid arterial compliance, and intima-media thickness (cIMT). Fifty-six participants [age: 70(6) years; 61% female] were included in this study. Significant improvements following the exercise program (V2) were observed in cognition: EF (p = 0.002), processing speed (p < 0.001), verbal fluency [digit symbol coding (p < 0.001), phonemic verbal fluency (p < 0.001)], and memory [immediate recall (p < 0.001) and delayed recall (p < 0.001)]; mobility: usual & dual-task gait speed (p = 0.002 and p < 0.001, respectively) and step length (p = 0.001 and p = 0.003, respectively); and vascular health: cIMT (p = 0.002). No changes were seen in the remaining outcomes. In conclusion, 26 weeks of dual-task gait training and aerobic exercise improved performance on a number of cognitive outcomes, while increasing usual & dual-task gait speed and step length in a sample of older adults without dementia.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Blood Pressure; Blood Pressure Monitoring, Ambulatory; Carotid Intima-Media Thickness; Cognition Disorders; Exercise; Exercise Therapy; Female; Follow-Up Studies; Gait; Humans; Independent Living; Male; Middle Aged; Neuropsychological Tests

The Efficacy of Emotion Recognition Rehabilitation for People with Alzheimer's Disease. - García-Casal, J Antonio; Goñi-Imizcoz, Miguel; Perea-Bartolomé, M Victoria; Soto-Pérez, Felipe; Smith, Sarah Jane; Calvo-Simal, Sara; Franco-Martín, Manuel (J Alzheimers Dis, 2017)
BACKGROUND: The ability to recognize emotional expression is essential for social interactions, adapting to the environment, and quality of life. Emotion recognition is impaired in people with Alzheimer's disease (AD), thus rehabilitation of these skills has the potential to elicit significant benefits. OBJECTIVE: This study sought to establish whether emotion recognition capacity could be rehabilitated in people with AD. METHODS: Thirty-six participants with AD were assigned to one of three conditions: an experimental group (EG) that received 20 sessions of rehabilitation of emotion recognition and 20 sessions of cognitive stimulation therapy (CST), a control group (CG) that received 40 sessions of CST, and a treatment as usual group (TAU). RESULTS: A positive treatment effect favoring the EG was found; participants were better able to correctly identify emotions (p = 0.021), made fewer errors of commission (p = 0.002), had greater precision of processing (p = 0.021), and faster processing speed (p = 0.001). Specifically, the EG were better able to identify sadness (p = 0.016), disgust (p = 0.005), and the neutral expression (p = 0.014), with quicker processing speed for disgust (p = 0.002). These gains were maintained at one month follow-up with the exception of processing speed for surprise, which improved. CONCLUSION: Capacity to recognize facial expressions of emotions can be improved through specific rehabilitation in people with AD, and gains are still present at a one month follow up. These findings have implications for the design of rehabilitation techniques for people with AD that may lead to improved quality of life and social interactions for this population.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Therapy; Depression; Emotions; Female; Follow-Up Studies; Humans; Male; Mental Status Schedule; Neuropsychological Tests; Outcome Assessment (Health Care); Recognition (Psychology); Single-Blind Method; Statistics, Nonparametric

Exercise Training and Functional Connectivity Changes in Mild Cognitive Impairment and Healthy Elders. - Chirles, Theresa J; Reiter, Katherine; Weiss, Lauren R; Alfini, Alfonso J; Nielson, Kristy A; Smith, J Carson (J Alzheimers Dis, 2017)
BACKGROUND: Effective interventions are needed to improve brain function in mild cognitive impairment (MCI), an early stage of Alzheimer's disease (AD). The posterior cingulate cortex (PCC)/precuneus is a hub of the default mode network (DMN) and is preferentially vulnerable to disruption of functional connectivity in MCI and AD. OBJECTIVE: We investigated whether 12 weeks of aerobic exercise could enhance functional connectivity of the PCC/precuneus in MCI and healthy elders. METHODS: Sixteen MCI and 16 healthy elders (age range = 60-88) engaged in a supervised 12-week walking exercise intervention. Functional MRI was acquired at rest; the PCC/precuneus was used as a seed for correlated brain activity maps. RESULTS: A linear mixed effects model revealed a significant interaction in the right parietal lobe: the MCI group showed increased connectivity while the healthy elders showed decreased connectivity. In addition, both groups showed increased connectivity with the left postcentral gyrus. Comparing pre to post intervention changes within each group, the MCI group showed increased connectivity in 10 regions spanning frontal, parietal, temporal and insular lobes, and the cerebellum. Healthy elders did not demonstrate any significant connectivity changes. CONCLUSION: The observed results show increased functional connectivity of the PCC/precuneus in individuals with MCI after 12 weeks of moderate intensity walking exercise training. The protective effects of exercise training on cognition may be realized through the enhancement of neural recruitment mechanisms, which may possibly increase cognitive reserve. Whether these effects of exercise training may delay further cognitive decline in patients diagnosed with MCI remains to be demonstrated.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Exercise; Exercise Test; Female; Gyrus Cinguli; Humans; Image Processing, Computer-Assisted; Linear Models; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Oxygen; Psychiatric Status Rating Scales

Family History of Alzheimer's Disease is Associated with Impaired Perceptual Discrimination of Novel Objects. - Mason, Emily J; Hussey, Erin P; Molitor, Robert J; Ko, Philip C; Donahue, Manus J; Ally, Brandon A (J Alzheimers Dis, 2017)
Early detection may be the key to developing therapies that will combat Alzheimer's disease (AD). It has been consistently demonstrated that one of the main pathologies of AD, tau, is present in the brain decades before a clinical diagnosis. Tau pathology follows a stereotypical route through the medial temporal lobe beginning in the entorhinal and perirhinal cortices. If early pathology leads to very subtle changes in behavior, it may be possible to detect these changes in subjects years before a clinical diagnosis can currently be made. We aimed to discover if cognitively normal middle-aged adults (40-60 years old) at increased risk for AD due to family history would have impaired performance on a cognitive task known to challenge the perirhinal cortex. Using an oddity detection task, we found that subjects with a family history of AD had lowered accuracy without demonstrating differences in rate of acquisition. There were no differences between subjects' medial temporal lobe volume or cortical thickness, indicating that the changes in behavior were not due to significant atrophy. These results demonstrate that subtle changes in perceptual processing are detectable years before a typical diagnosis even when there are no differences detectable in structural imaging data. Anatomically-targeted cognitive testing may be useful in identifying subjects in the earliest stages of AD.
Keywords: Adult; Alzheimer Disease; Cerebral Cortex; Discrimination (Psychology); Family Health; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Perceptual Disorders; Photic Stimulation; Recognition (Psychology); Signal Detection, Psychological

Humanin Specifically Interacts with Amyloid-β Oligomers and Counteracts Their in vivo Toxicity. - Romeo, Margherita; Stravalaci, Matteo; Beeg, Marten; Rossi, Alessandro; Fiordaliso, Fabio; Corbelli, Alessandro; Salmona, Mario; Gobbi, Marco; Cagnotto, Alfredo; Diomede, Luisa (J Alzheimers Dis, 2017)
The 24-residue peptide humanin (HN) has been proposed as a peptide-based inhibitor able to interact directly with amyloid-β (Aβ) oligomers and interfere with the formation and/or biological properties of toxic Aβ species. When administered exogenously, HN, or its synthetic S14G-derivative (HNG), exerted multiple cytoprotective effects, counteracting the Aβ-induced toxicity. Whether these peptides interact directly with Aβ, particularly with the soluble oligomeric assemblies, remains largely unknown. We here investigated the ability of HN and HNG to interact directly with highly aggregating Aβ42, and interfere with the formation and toxicity of its oligomers. Experiments were run in cell-free conditions and in vivo in a transgenic C. elegans strain in which the Aβ toxicity was specifically due to oligomeric species. Thioflavin-T assay indicated that both HN and HNG delay the formation and reduce the final amount of Aβ42 fibrils. In vitro surface plasmon resonance studies indicated that they interact with Aβ42 oligomers favoring the formation of amorphous larger assemblies, observed with turbidity and electron microscopy. In vivo studies indicated that both HN and HNG decrease the relative abundance of A11-positive prefibrillar oligomers as well as OC-positive fibrillar oligomers and had similar protective effects. However, while HN possibly decreased the oligomers by promoting their assembly into larger aggregates, the reduction of oligomers caused by HNG can be ascribed to a marked decrease of the total Aβ levels, likely the consequence of the HNG-induced overexpression of the Aβ-degrading enzyme neprilysin. These findings provide information on the mechanisms underlying the anti-oligomeric effects of HN and HNG and illustrate the role of S14G substitution in regulating the in vivo mechanism of action.
Keywords: Amyloid beta-Peptides; Animals; Animals, Genetically Modified; Caenorhabditis elegans; Caenorhabditis elegans Proteins; Circular Dichroism; Disease Models, Animal; Dose-Response Relationship, Drug; Gene Expression Regulation; Humans; Intracellular Signaling Peptides and Proteins; Microscopy, Atomic Force; Microscopy, Electron, Transmission; Neprilysin; Paralysis; Peptide Fragments; Surface Plasmon Resonance

Long-Term Cognitive Decline in Dementia with Lewy Bodies in a Large Multicenter, International Cohort. - Kramberger, Milica G; Auestad, Bjørn; Garcia-Ptacek, Sara; Abdelnour, Carla; Olmo, Josep Garre; Walker, Zuzana; Lemstra, Afina W; Londos, Elisabet; Blanc, Frédéric; Bonanni, Laura; McKeith, Ian; Winblad, Bengt; et al. (J Alzheimers Dis, 2017)
BACKGROUND/OBJECTIVE: The aim of this study was to describe the rate and clinical predictors of cognitive decline in dementia with Lewy bodies (DLB), and compare the findings with Alzheimer's disease (AD) and Parkinson's disease dementia (PDD) patients. METHODS: Longitudinal scores for the Mini-Mental State Examination (MMSE) in 1,290 patients (835 DLB, 198 PDD, and 257 AD) were available from 18 centers with up to three years longitudinal data. Linear mixed effects analyses with appropriate covariates were used to model MMSE decline over time. Several subgroup analyses were performed, defined by anti-dementia medication use, baseline MMSE score, and DLB core features. RESULTS: The mean annual decline in MMSE score was 2.1 points in DLB, compared to 1.6 in AD (p = 0.07 compared to DLB) and 1.8 in PDD (p = 0.19). Rates of decline were significantly higher in DLB compared to AD and PDD when baseline MMSE score was included as a covariate, and when only those DLB patients with an abnormal dopamine transporter SPECT scan were included. Decline was not predicted by sex, baseline MMSE score, or presence of specific DLB core features. CONCLUSIONS: The average annual decline in MMSE score in DLB is approximately two points. Although in the overall analyses there were no differences in the rate of decline between the three neurodegenerative disorders, there were indications of a more rapid decline in DLB than in AD and PDD. Further studies are needed to understand the predictors and mechanisms of cognitive decline in DLB.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Cognition Disorders; Cohort Studies; Female; Humans; International Cooperation; Lewy Body Disease; Male; Mental Status Schedule; Middle Aged

Modeling the Relationships Among Late-Life Body Mass Index, Cerebrovascular Disease, and Alzheimer's Disease Neuropathology in an Autopsy Sample of 1,421 Subjects from the National Alzheimer's Coordinating Center Data Set. - Alosco, Michael L; Duskin, Jonathan; Besser, Lilah M; Martin, Brett; Chaisson, Christine E; Gunstad, John; Kowall, Neil W; McKee, Ann C; Stern, Robert A; Tripodis, Yorghos (J Alzheimers Dis, 2017)
The relationship between late-life body mass index (BMI) and Alzheimer's disease (AD) is poorly understood due to the lack of research in samples with autopsy-confirmed AD neuropathology (ADNP). The role of cerebrovascular disease (CVD) in the interplay between late-life BMI and ADNP is unclear. We conducted a retrospective longitudinal investigation and used joint modeling of linear mixed effects to investigate causal relationships among repeated antemortem BMI measurements, CVD (quantified neuropathologically), and ADNP in an autopsy sample of subjects across the AD clinical continuum. The sample included 1,421 subjects from the National Alzheimer's Coordinating Center's Uniform Data Set and Neuropathology Data Set with diagnoses of normal cognition (NC; n = 234), mild cognitive impairment (MCI; n = 201), or AD dementia (n = 986). ADNP was defined as moderate to frequent neuritic plaques and Braak stageIII-VI. Ischemic Injury Scale (IIS) operationalized CVD. Joint modeling examined relationships among BMI, IIS, and ADNP in the overall sample and stratified by initial visit Clinical Dementia Rating score. Subject-specific random intercept for BMI was the predictor for ADNP due to minimal BMI change (p = 0.3028). Analyses controlling for demographic variables and APOE ɛ4 showed lower late-life BMI predicted increased odds of ADNP in the overall sample (p < 0.001), and in subjects with CDR of 0 (p = 0.0021) and 0.5 (p = 0.0012), but not ≥1.0 (p = 0.2012). Although higher IIS predicted greater odds of ADNP (p < 0.0001), BMI did not predict IIS (p = 0.2814). The current findings confirm lower late-life BMI confers increased odds for ADNP. Lower late-life BMI may be a preclinical indicator of underlying ADNP.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Autopsy; Body Mass Index; Cerebrovascular Disorders; Datasets as Topic; Female; Humans; Male; National Institute on Aging (U.S.); Neuropathology; Neuropsychological Tests; Retrospective Studies; United States

Modulating the Balance of Synaptic and Extrasynaptic NMDA Receptors Shows Positive Effects against Amyloid-β-Induced Neurotoxicity. - Huang, Yan; Shen, Wei; Su, Jie; Cheng, Bin; Li, Dong; Liu, Gang; Zhou, Wen-Xia; Zhang, Yong-Xiang (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) patients suffer a disturbance in the balance between synaptic (GluN2A, mediating the protective pathway) and extrasynaptic NMDA receptors (NMDARs) (GluN2B, mediating the excitotoxic pathway), and, therefore, restoring the balance of GluN2A and GluN2B should be beneficial for AD. In this study, the GluN2B-selective antagonist, ifenprodil, and the non-selective NMDAR agonist, NMDA, had little effect on amyloid-β (Aβ)-induced long-term potentiation deficits. Enhancing the activity of GluN2A had a protective effect against Aβ, and specific activation of GluN2A and inhibition of GluN2B showed a better protective effect. In Aβ ICV-injected animals, the combination of ifenprodil and D-cycloserine (a co-activator of NMDRs similar to D-serine) led to greater improvement in behavior tests (nest building, novel object recognition, and Morris water maze) than ifenprodil (Morris water maze) or D-cycloserine (nest building) alone. Signal pathway analysis showed that Aβ disturbed the GluN2A/GluN2B-related pathway. The ratio of GluN2A to GluN2B decreased in Aβ-treated animals, and TORC dephosphorylation and ERK1/2 activation, which could be initiated by GluN2A, also decreased in the hippocampal tissues of Aβ-treated animals. As a result, the activation of CREB and the content of brain-derived BDNF decreased. The combination of ifenprodil and D-cycloserine reversed the signal pathway more significantly than ifenprodil or D-cycloserine alone, indicating that Aβ-induced toxicology was mediated both by functionally inhibiting GluN2A and enhancing GluN2B. These results indicate that enhancing synaptic NMDARs and inhibiting extrasynaptic NMDARs concurrently showed protective effects against Aβ-induced neurotoxicity, suggesting that modulation of the balance between GluN2A and GluN2B could be a potential strategy for AD drug development and therapy.
Keywords: Amyloid beta-Peptides; Animals; Antimetabolites; Cycloserine; Disease Models, Animal; Excitatory Amino Acid Antagonists; Excitatory Postsynaptic Potentials; Hippocampus; Locomotion; Male; Maze Learning; N-Methylaspartate; Nesting Behavior; Neurotoxicity Syndromes; Peptide Fragments; Piperidines; Rats; Rats, Wistar; Receptors, N-Methyl-D-Aspartate; Recognition (Psychology); Signal Transduction; Synapses

Palmitate Increases β-site AβPP-Cleavage Enzyme 1 Activity and Amyloid-β Genesis by Evoking Endoplasmic Reticulum Stress and Subsequent C/EBP Homologous Protein Activation. - Marwarha, Gurdeep; Rostad, Stephen; Lilek, Jaclyn; Kleinjan, Mason; Schommer, Jared; Ghribi, Othman (J Alzheimers Dis, 2017)
Epidemiological studies implicate diets rich in saturated free fatty acids (sFFA) as a potential risk factor for developing Alzheimer's disease (AD). In particular, high plasma levels of the sFFA palmitic acid (palmitate) were shown to inversely correlate with cognitive function. However, the cellular mechanisms by which sFFA may increase the risk for AD are not well known. Endoplasmic reticulum (ER) stress has emerged as one of the signaling pathways initiating and fostering the neurodegenerative changes in AD by increasing the aspartyl protease β-site AβPP cleaving enzyme 1 (BACE1) and amyloid-β (Aβ) genesis. In this study, we determined the extent to which palmitate increases BACE1 and Aβ levels in vitro and in vivo as well as the potential role of ER stress as cellular mechanism underlying palmitate effects. We demonstrate, in palmitate-treated SH-SY5Y neuroblastoma cells and in the hippocampi of palmitate-enriched diet-fed mice, that palmitate evokes the activation of the C/EBP Homologous Protein (CHOP), a transcription factor that is specifically responsive to ER stress. Induction of CHOP expression is associated with increased BACE1 mRNA, protein and activity levels, and subsequent enhanced amyloidogenic processing of amyloid-β protein precursor (AβPP) that culminates in a substantial increase in Aβ genesis. We further show that CHOP is an indispensable molecular mediator of palmitate-induced upregulation in BACE1 activity and Aβ genesis. Indeed, we show that Chop-/- mice and CHOP knocked-down SH-SY5Y neuroblastoma cells do not exhibit the same commensurate degree of palmitate-induced increase in BACE1 expression levels and Aβ genesis.
Keywords: Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Aspartic Acid Endopeptidases; Cell Line, Tumor; Dose-Response Relationship, Drug; Endoplasmic Reticulum Stress; Gene Expression Regulation; Hippocampus; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mutation; Neuroblastoma; Palmitates; RNA, Messenger; Signal Transduction; Transcription Factor CHOP; Transcription Factors; Transfection

PCSK9 Promotes oxLDL-Induced PC12 Cell Apoptosis Through the Bcl-2/Bax-Caspase 9/3 Signaling Pathway. - Liu, Lu-Shan; Bai, Xue-Qin; Gao, Ya; Wu, Qi; Ren, Zhong; Li, Qing; Pan, Li-Hong; He, Ni-Ya; Peng, Juan; Tang, Zhi-Han (J Alzheimers Dis, 2017)
BACKGROUND: Hyperlipidemia is a risk factor for neurodegenerative diseases. Proprotein convertase subtilisin / Kexin type 9 (PCSK9) degrades hepatic low-density lipoprotein receptor (LDLR) to regulate lipid metabolism. It is unclear if PCSK9 plays a role in neurodegenerative diseases. OBJECTIVE: This study was designed to determine whether PCSK9 is crucial between hyperlipidemia and Alzheimer's disease. The interrelationship between PCSK9 and neuronal apoptosis was explored in PC12 cells in response to treatment with oxidized low-density lipoprotein (oxLDL). METHODS: Cultured PC12 cells were serum-starved and incubated with different concentrations of oxLDL for 24 h. Intracytoplasmic lipid droplets were observed by oil red O staining. Morphological assessment of apoptotic cells was performed using Hoechst 33258 staining and flow cytometry analysis. The expression of mRNA and protein was detected by reverse-transcription polymerase chain reaction (RT-PCR) and western blot analyses, respectively. Transfection of small interfering RNA (siRNA) into PC12 cells was conducted using HiperFect Transfection Reagent. Concentrations of Aβ40 and Aβ42 were detected by enzyme-linked immunosorbent assay (ELISA) kit. RESULTS: Intracellular lipid content, the number of apoptotic cells, and PCSK9 expression were increased in PC12 cells after oxLDL treatment. Transfection with PCSK9 siRNA reduced the oxLDL-induced apoptosis of PC12 cells. We further confirmed the involvement of Bcl-2/Bax-Caspase (9, 3) signaling pathway in the regulation of PC12 cells apoptosis.β-Secretase 1, another target gene of PCSK9, was downregulated in PC12 cells in response to oxLDL treatment. Aβ40 and Aβ42 contents were also decreased. CONCLUSION: PCSK9 promotes oxLDL-induced PC12 cell apoptosis through the Bcl-2/Bax-Caspase 9/3 signaling pathway.
Keywords: Amyloid beta-Peptides; Analysis of Variance; Animals; Apoptosis; bcl-2-Associated X Protein; Caspases; Culture Media, Serum-Free; Dose-Response Relationship, Drug; Flow Cytometry; Lipid Metabolism; Lipoproteins, LDL; PC12 Cells; Peptide Fragments; Proprotein Convertase 9; Proto-Oncogene Proteins c-bcl-2; Rats; RNA, Messenger; RNA, Small Interfering; Signal Transduction; Transfection

The Progression of Alzheimer's Disease: Are Fast Decliners Really Fast? A Four-Year Follow-Up. - Barocco, Federica; Spallazzi, Marco; Concari, Letizia; Gardini, Simona; Pelosi, Annalisa; Caffarra, Paolo (J Alzheimers Dis, 2017)
BACKGROUND: The rate of cognitive and functional decline in Alzheimer's disease (AD) changes across individuals. OBJECTIVES: Our purpose was to assess whether the concept of "fast decline" really fits its definition and whether cognitive and functional variables at onset can predict the progression of AD. METHODS: 324 AD patients were included. We retrospectively examined their Mini-Mental State Examination (MMSE) total score and sub-items, Activities of Daily Living (ADL), and Instrumental Activities of Daily Living (IADL) at baseline and every six months for a 4-year follow-up. Patients were divided into "fast decliners" (n = 62), defined by a loss ≥5 points on the MMSE score within the first year from the baseline; "intermediate decliners" (n = 37), by a loss ≥5 points after the first year and before the 18th month; or "slow decliners" (n = 225), composed of the remaining patients. RESULTS: At baseline, the groups did not differ on demographic, clinical, and cognitive variables. The decline at the end of the 4-year follow-up period seems to be similar among the different decline clusters. Predictors of disease progression have not been identified; only the MMSE total score at 12 months <14/30 was indicative of a poor prognosis. CONCLUSIONS: Even with the limitation due to the small sample size, the lack of differences in the disease progression in time in the different clusters suggest the inconsistency of the so-called "fast decliners". This study was unable to show any significant difference among clusters of AD progression within a 4-year time interval. Further studies should better clarify whether a more consistent distinction exists between slow and fast decliners.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Cognition Disorders; Disease Progression; Female; Humans; Longitudinal Studies; Male; Psychiatric Status Rating Scales; ROC Curve; Time Factors

Role of Suppressor of Cytokine Signaling 3 (SOCS3) in Altering Activated Microglia Phenotype in APPswe/PS1dE9 Mice. - Iwahara, Naotoshi; Hisahara, Shin; Kawamata, Jun; Matsumura, Akihiro; Yokokawa, Kazuki; Saito, Taro; Fujikura, Mai; Manabe, Tatsuo; Suzuki, Hiromi; Matsushita, Takashi; Suzuki, Syuuichirou; Shimohama, Shun (J Alzheimers Dis, 2017)
In response to changes of the central nervous system environment, microglia are capable of acquiring diverse phenotypes for cytotoxic or immune regulation and resolution of injury. Alzheimer's disease (AD) pathology also induces several microglial activations, resulting in production of pro-inflammatory cytokines and reactive oxygen species or clearance of amyloid-β (Aβ) through phagocytosis. We previously demonstrated that microglial activation and increase in oxidative stress started from the middle age in APPswe/PS1dE9 mice, and hypothesized that M1 activation occurs in middle-aged AD mice by Aβ stimulation. In the present study, we analyzed in vivo expressions of pro-inflammatory cytokines (M1 microglial markers), M2 microglial markers, and suppressor of cytokine signaling (SOCS) family, and examined the microglial phenotypic profile in APPswe/PS1dE9 mice. Then we compared the in vitro gene expression patterns of Aβ- and lipopolysaccharide (LPS)-stimulated primary-cultured microglia. Microglia in APPswe/PS1dE9 mice exhibited an M1-like phenotype, expressing tumor necrosis factor α (TNFα) but not interleukin 6 (IL6). Aβ-stimulated primary-cultured microglia also expressed TNFα but not IL6, whereas LPS-stimulated primary-cultured microglia expressed both pro-inflammatory cytokines. Furthermore, both microglia in APPswe/PS1dE9 mice and Aβ-stimulated primary-cultured microglia expressed SOCS3. Reduction of SOCS3 expression in Aβ-challenged primary-cultured microglia resulted in upregulation of IL6 expression. Our findings indicate that SOCS3 suppresses complete polarization to M1 phenotype through blocking IL6 production, and Aβ-challenged primary-cultured microglia replicate the in vivo gene expression pattern of microglia in APPswe/PS1dE9 mice. Aβ may induce the M1-like phenotype through blocking of IL6 by SOCS3.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Brain; Cells, Cultured; Disease Models, Animal; Female; Humans; Interleukin-6; Lipopolysaccharides; Male; Mice, Inbred C57BL; Mice, Transgenic; Microglia; Neurons; Presenilin-1; Suppressor of Cytokine Signaling 3 Protein; Tumor Necrosis Factor-alpha

What Drives Country Differences in Cost of Alzheimer's Disease? An Explanation from Resource Use in the GERAS Study. - Reed, Catherine; Happich, Michael; Argimon, Josep Maria; Haro, Josep Maria; Wimo, Anders; Bruno, Giuseppe; Dodel, Richard; Jones, Roy W; Vellas, Bruno; Belger, Mark (J Alzheimers Dis, 2017)
BACKGROUND: Country differences in resource use and costs of Alzheimer's disease (AD) may be driven by differences in health care systems and resource availability. OBJECTIVE: To compare country resource utilization drivers of societal costs for AD dementia over 18 months. METHODS: GERAS is an observational study in France (n = 419), Germany (n = 550), and the UK (n = 526). Resource use of AD patients and caregivers contributing to >1% of total societal costs (year 2010) was assessed for country differences, adjusting for participant characteristics. RESULTS: Mean 18-month societal costs per patient were France €33,339, Germany €38,197, and UK €37,899 (£32,501). Caregiver time spent on basic and instrumental activities of daily living (ADL) contributed the most to societal costs (54% France, 64% Germany, 65% UK). Caregivers in France spent less time on ADL than UK caregivers and missed fewer work days than in other countries. Compared with other countries, patients in France used more community care services overall and were more likely to use home aid. Patients in Germany were least likely to use temporary accommodation or to be institutionalized at 18 months. UK caregivers spent the most time on instrumental ADL, UK patients used fewest outpatient resources, and UK patients/caregivers were most likely to receive financial support. CONCLUSION: Caregiver time on ADL contributed the most to societal costs and differed across countries, possibly due to use of community care services and institutionalization. Other resources had different patterns of use across countries, reflecting country-specific health and social care systems.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Caregivers; Cohort Studies; Cost of Illness; Europe; Female; Health Resources; Humans; International Cooperation; Male; Surveys and Questionnaires

Aberrant Spontaneous Brain Activity in Patients with Mild Cognitive Impairment and concomitant Lacunar Infarction: A Resting-State Functional MRI Study. - Ni, Ling; Liu, Renyuan; Yin, Zhenyu; Zhao, Hui; Nedelska, Zuzana; Hort, Jakub; Zhou, Fei; Wu, Wenbo; Zhang, Xin; Li, Ming; Yu, Haiping; Zhu, Bin; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Lacunar infarctions (LI) have been associated with a cognitive decline and an increased risk of dementia. Whether and how the pattern of spontaneous brain activity in patients with mild cognitive impairment (MCI) differs in subjects with and without concomitant LI remains unclear. OBJECTIVE: To compare the pattern of spontaneous brain activity in MCI patients with versus those without LI using resting-state functional magnetic resonance imaging (rs-fMRI). METHODS: Forty-eight MCI patients, including 22 with LI [MCI-LI] and 26 without LI [MCI-no LI], and 28 cognitive normal subjects underwent rs-fMRI post-processed using regional homogeneity (ReHo) and the amplitude of low-frequency fluctuation (ALFF) methods. RESULTS: Compared with cognitively normal subjects, the MCI-LI patients had decreased ReHo in the precuneus/cuneus (Pcu/CU) and insula; decreased ALFF in the Pcu/CU and frontal lobe; and increased ALFF and ReHo in the temporal lobe. While the MCI-no LI group had increased ReHo and ALFF in the bilateral hippocampus and parahippocampal gyrus, frontal lobe, and decreased ALFF and ReHo in the temporal lobe. Compared with the MCI-no LI patients, those with MCI-LI had decreased ALFF in the frontal lobe; decreased ReHo in the Pcu/CU and insula; and increased ALFF and ReHo in the temporal lobe (p <  0.05, AlphaSim corrected). In MCI-LI patients, the MOCA scores showed a relatively weak correlation with ALFF values in the medial frontal gyrus (r = 0.432, p = 0.045) (of borderline significance after Bonferroni correction). CONCLUSIONS: The spontaneous brain activities in MCI-LI were distinct from MCI-no LI. The probable compensatory mechanism observed in MCI-no LI might be disrupted in MCI with LI due to vascular damage.
Keywords: Aged; Aged, 80 and over; Brain; Brain Mapping; Cognitive Dysfunction; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Rest; Stroke, Lacunar

Accurate Prediction of Conversion to Alzheimer's Disease using Imaging, Genetic, and Neuropsychological Biomarkers. - Dukart, Juergen; Sambataro, Fabio; Bertolino, Alessandro (J Alzheimers Dis, 2016)
A variety of imaging, neuropsychological, and genetic biomarkers have been suggested as potential biomarkers for the identification of mild cognitive impairment (MCI) in patients who later develop Alzheimer's disease (AD). Here, we systematically evaluated the most promising combinations of these biomarkers regarding discrimination between stable and converter MCI and reflection of disease staging. Alzheimer's Disease Neuroimaging Initiative data of AD (n = 144), controls (n = 112), stable (n = 265) and converter (n = 177) MCI, for which apolipoprotein E status, neuropsychological evaluation, and structural, glucose, and amyloid imaging were available, were included in this study. Naïve Bayes classifiers were built on AD and controls data for all possible combinations of these biomarkers, with and without stratification by amyloid status. All classifiers were then applied to the MCI cohorts. We obtained an accuracy of 76% for discrimination between converter and stable MCI with glucose positron emission tomography as a single biomarker. This accuracy increased to about 87% when including further imaging modalities and genetic information. We also identified several biomarker combinations as strong predictors of time to conversion. Use of amyloid validated training data resulted in increased sensitivities and decreased specificities for differentiation between stable and converter MCI when amyloid was included as a biomarker but not for other classifier combinations. Our results indicate that fully independent classifiers built only on AD and controls data and combining imaging, genetic, and/or neuropsychological biomarkers can more reliably discriminate between stable and converter MCI than single modality classifiers. Several biomarker combinations are identified as strongly predictive for the time to conversion to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoproteins E; Area Under Curve; Brain; Cognitive Dysfunction; Disease Progression; Female; Fluorodeoxyglucose F18; Follow-Up Studies; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography; Prognosis; Radiopharmaceuticals; ROC Curve; Sensitivity and Specificity

Activities of Daily Living and Depressive Symptoms in Patients with Subjective Cognitive Decline, Mild Cognitive Impairment, and Alzheimer's Disease. - Stogmann, Elisabeth; Moser, Doris; Klug, Stefanie; Gleiss, Andreas; Auff, Eduard; Dal-Bianco, Peter; Pusswald, Gisela; Lehrner, Johann (J Alzheimers Dis, 2016)
BACKGROUND: Subjective cognitive decline (SCD) may be an early indicator for an increased risk of dementia. The exact definition of SCD remains unclear and has recently become a major research interest. OBJECTIVES: To determine impairments in activities of daily living (ADL) and depressive symptoms in elderly individuals with SCD, mild cognitive impairment (MCI), and Alzheimer's disease (AD). METHODS: We included 752 consecutive patients suffering from SCD, non-amnestic (naMCI) or amnestic MCI (aMCI), AD, and 343 healthy controls into this prospective cohort study. A neuropsychological test battery, B-ADL and BDI-II was performed. RESULTS: SCD patients showed a decreased performance in ADL compared to controls. Performance in ADL declined concurrently with cognitive abilities along the controls-SCD-naMCI-aMCI-AD continuum. Individuals with cognitive complains, no matter if SCD, MCI, or AD patients, reported more often depressive symptoms compared to healthy controls without complaints. Within all five cognitive subgroups, patients with depressive symptoms reported more difficulties in ADL in comparison to patients without depressive symptoms. Adjusting for depressive symptoms, there was no significant group difference between the control versus the SCD group (OR 1.1, CI 0.6-1.7). CONCLUSIONS: SCD is a heterogeneous clinical condition. Specific features such as slightly impaired ADL and depressive symptoms are associated with SCD. Clinical markers may serve as an indicator for preclinical AD and in combination with biomarkers guide to an early diagnosis of a progressive neurodegenerative disease.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Cognitive Dysfunction; Depression; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Odds Ratio; Perception; Prospective Studies

Age and its association with low insulin and high amyloid-β peptides in blood. - Li, Huajie; Zhu, Haihao; Wallack, Max; Mwamburi, Mkaya; Abdul-Hay, Samer O; Leissring, Malcolm A; Qiu, Wei Qiao (J Alzheimers Dis, 2016)
Age is the major risk factor for developing Alzheimer's disease (AD), and modifying age-related factors may help to delay the onset of the disease. The goal of this study was to investigate the relationship between age and the metabolic factors related to the risk of developing AD. The concentrations of insulin, amylin, and amyloid-β peptide (Aβ) in plasma were measured. We further measured the activity of serum Aβ degradation by using fluorescein- and biotin-labeled Aβ40. Apolipoprotein E4 allele (ApoE4) and cognitive impairment were characterized. Subjects were divided into three age groups: 60-70, 70-80, and ≥80 years old. We found that the older the subjects, the lower the concentration of insulin (p = 0.001) and the higher the concentration of Aβ1-40 (p = 0.004) in plasma. However, age was not associated with the concentration of another pancreatic peptide, amylin, and only marginally with Aβ1-42. These relationships remained in the absence of diabetes, cardiovascular disease, and stroke, and regardless of the presence of ApoE4 and cognitive impairment. Both age and ApoE4 were inversely associated with, while insulin was positively associated with, the activities of Aβ degradation in serum. Our study suggested that low concentration of insulin and high concentration of Aβ40 are aging factors related to the risk of AD.
Keywords: Age Distribution; Aged; Aged, 80 and over; Aging; Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Biomarkers; Cognition Disorders; Cross-Sectional Studies; Female; Humans; Insulin; Islet Amyloid Polypeptide; Linear Models; Male; Middle Aged; Multivariate Analysis; Peptide Fragments

Age-Dependent Regulation of the Blood-Brain Barrier Influx/Efflux Equilibrium of Amyloid-β Peptide in a Mouse Model of Alzheimer's Disease (3xTg-AD). - Do, Tuan Minh; Dodacki, Agnès; Alata, Wael; Calon, Frederic; Nicolic, Sophie; Scherrmann, Jean-Michel; Farinotti, Robert; Bourasset, Fanchon (J Alzheimers Dis, 2016)
The involvement of transporters located at the blood-brain barrier (BBB) has been suggested in the control of cerebral Aβ levels, and thereby in Alzheimer's disease (AD). However, little is known about the regulation of these transporters at the BBB in animal models of AD. In this study, we investigated the BBB expression of Aβ influx (Rage) and efflux (Abcb1-Abcg2-Abcg4-Lrp-1) transporters and cholesterol transporter (Abca1) in 3-18-month-old 3xTg-AD and control mice. The age-dependent effect of BBB transporters regulation on the brain uptake clearance (Clup) of [3H]cholesterol and [3H]Aβ1 - 40 was then evaluated in these mice, using the in situ brain perfusion technique. Our data suggest that transgenes expression led to the BBB increase in Aβ influx receptor (Rage) and decrease in efflux receptor (Lrp-1). Our data also indicate that mice have mechanisms counteracting this increased net influx. Indeed, Abcg4 and Abca1 are up regulated in 3- and 3/6-month-old 3xTg-AD mice, respectively. Our data show that the balance between the BBB influx and efflux of Aβ is maintained in 3 and 6-month-old 3xTg-AD mice, suggesting that Abcg4 and Abca1 control the efflux of Aβ through the BBB by a direct (Abcg4) or indirect (Abca1) mechanism. At 18 months, the BBB Aβ efflux is significantly increased in 3xTg-AD mice compared to controls. This could result from the significant up-regulation of both Abcg2 and Abcb1 in 3xTg-AD mice compared to control mice. Thus, age-dependent regulation of several Aβ and cholesterol transporters at the BBB could ultimately limit the brain accumulation of Aβ.
Keywords: Aging; Alzheimer Disease; Amyloid beta-Peptides; Animals; ATP Binding Cassette Transporter, Sub-Family G, Member 1; ATP Binding Cassette Transporter, Sub-Family G, Member 2; ATP-Binding Cassette Transporters; Biological Transport; Blood-Brain Barrier; Brain; Carbon Isotopes; Cholesterol; Disease Models, Animal; Humans; Lipoproteins; Mice; Mice, Transgenic; P-Glycoproteins; Peptide Fragments; Receptors, LDL; Sucrose; Tritium; Tumor Suppressor Proteins

Aging as a Precipitating Factor in Chronic Restraint Stress-Induced Tau Aggregation Pathology, and the Protective Effects of Rosmarinic Acid. - Shan, Ye; Wang, Dan-Dan; Xu, Yu-Xia; Wang, Chu; Cao, Lan; Liu, Yun-Sheng; Zhu, Cui-Qing (J Alzheimers Dis, 2016)
Stress is an important risk factor of Alzheimer's disease (AD). It has been evidenced that stress could induce tau phosphorylation and increase tau insolubility in brain; however, little is known about the interactional effect of stress with aging on tauopathy. Therefore, we explored the effects of aging on stress-induced tauopathy and the potential mechanism in mouse model of chronic restraint stress (CRS). Here we found that in general, the level of phosphorylated tau (P-tau) was higher in brain of middle-aged mice than that in adult mice under physiological conditions. CRS-induced tau phosphorylation and its insolubility were more prominent in middle-aged mice. The increase of AT8-labeled insoluble P-tau was dramatic in middle-aged mice, which was highly ubiquitinated but did not form PHF structures. The levels of chaperones were relatively lower in middle-aged mice brain; CRS further reduced the expression, especially for HDJ2/HSP40. CRS also suppressed the expression of Pin1, the peptidylprolyl cis/trans isomerase, in middle-aged mice but not in adult mice. Downregulation of HSP40 or Pin1 caused an increase of transfected extraneous tau in 293 cells. Rosmarinic acid (RA) could effectively suppress the elevation of P-tau and insoluble P-tau formation induced by CRS, and reversed the abnormal changes of chaperones and Pin1 particularly in middle-aged mice. Taken together, our findings provided evidence that aging could be a promoting factor in stress-induced tauopathy, which was relevant with malregulation of chaperones and Pin1, and RA might be a promising beneficial agent for stress-induced tauopathy.
Keywords: Aging; Animals; Antioxidants; Brain; Cinnamates; Corticotropin-Releasing Hormone; Depsides; Disease Models, Animal; HEK293 Cells; HSP90 Heat-Shock Proteins; Humans; Male; Mice; Mice, Inbred C57BL; Microscopy, Immunoelectron; NIMA-Interacting Peptidylprolyl Isomerase; Peptidylprolyl Isomerase; Phosphorylation; Precipitating Factors; Receptors, Corticotropin; Restraint, Physical; Stress, Psychological; tau Proteins; Transfection

Altered Affective Evaluations of Smells in Alzheimer's Disease. - Joussain, Pauline; Bessy, Marion; Fournel, Arnaud; Ferdenzi, Camille; Rouby, Catherine; Delphin-Combe, Floriane; Krolak-Salmon, Pierre; Bensafi, Moustafa (J Alzheimers Dis, 2016)
BACKGROUND: Studies of olfaction in Alzheimer's disease (AD) mainly focused on deficits in odor detection and identification, with very few investigations of olfactory emotional changes and their consequences for hedonics. OBJECTIVE: The aim of the present study was to characterize affective evaluations of odors in AD patients. METHODS: To this end, 20 AD patients and 20 matched controls were tested. Participants were screened for odor detection and identification ability and then asked to rate the intensity, pleasantness, and edibility of 20 odorants. RESULTS: Results showed that, overall, AD patients had lower detection ability and perceived all odors as weaker than controls. As expected, they had lower identification ability on both cued and non-cued tasks. In addition, when smelling pleasant odors, patients had significantly lower hedonic ratings than controls (p <  0.02), whereas no group difference was found for neutral or unpleasant odors (p >  0.05 in both cases). Moreover, an analysis combining both intensity and pleasantness ratings showed that whereas intensity increased as a function of pleasantness and unpleasantness in controls, this quadratic relationship was not observed in AD patients. CONCLUSIONS: The study suggests that the simplest categorization criteria of odors (intensity and hedonic valence) are impaired in AD patients (especially for pleasant odors).
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Case-Control Studies; Emotions; Female; Humans; Male; Mood Disorders; Odorants; Olfaction Disorders; Psychiatric Status Rating Scales; Smell; Surveys and Questionnaires

Altered sense of humor in dementia. - Clark, Camilla N; Nicholas, Jennifer M; Gordon, Elizabeth; Golden, Hannah L; Cohen, Miriam H; Woodward, Felix J; Macpherson, Kirsty; Slattery, Catherine F; Mummery, Catherine J; Schott, Jonathan M; Rohrer, Jonathan D; Warren, Jason D (J Alzheimers Dis, 2016)
Sense of humor is potentially relevant to social functioning in dementias, but has been little studied in these diseases. We designed a semi-structured informant questionnaire to assess humor behavior and preferences in patients with behavioral variant frontotemporal dementia (bvFTD; n = 15), semantic dementia (SD; n = 7), progressive nonfluent aphasia (PNFA; n = 10), and Alzheimer's disease (AD; n = 16) versus healthy age-matched individuals (n = 21). Altered (including frankly inappropriate) humor responses were significantly more frequent in bvFTD and SD (all patients) than PNFA or AD (around 40% of patients). All patient groups liked satirical and absurdist comedy significantly less than did healthy controls. This pattern was reported premorbidly for satirical comedy in bvFTD, PNFA, and AD. Liking for slapstick comedy did not differ between groups. Altered sense of humor is particularly salient in bvFTD and SD, but also frequent in AD and PNFA. Humor may be a sensitive probe of social cognitive impairment in dementia, with diagnostic, biomarker and social implications.
Keywords: Aged; Alzheimer Disease; Case-Control Studies; Cognition Disorders; Emotions; Female; Frontotemporal Dementia; Humans; Male; Middle Aged; Neuropsychological Tests; Primary Progressive Nonfluent Aphasia; Psychiatric Status Rating Scales; Surveys and Questionnaires

Anemia and Mild Cognitive Impairment in the German General Population. - Dlugaj, Martha; Winkler, Angela; Weimar, Christian; Dürig, Jan; Broecker-Preuss, Martina; Dragano, Nico; Moebus, Susanne; Jöckel, Karl-Heinz; Erbel, Raimund; Eisele, Lewin (J Alzheimers Dis, 2016)
There is increasing evidence that anemia is associated with cognitive impairment. Therefore, the aim of the study was to examine the cross-sectional association of anemia as well as the persistence of anemia over the last five years with mild cognitive impairment (MCI) and MCI subtypes (amnestic/non-amnestic MCI (aMCI/naMCI)). Out of 4,157 participants (50% men, 50-80 years) of the second examination (t1) of a cohort study (baseline (t0) 2000-2003), we included 4,033 participants with available hemoglobin information and complete cognitive assessment. Anemia was defined as hemoglobin <13 g/dl in men (n = 84) and <12 g/dl in women (n = 79). Group comparisons were used to compare the cognitive subtests. To determine the association of MCI with anemia at t1, with anemia five years prior to the cognitive assessment (t0) and anemia at both time points, we used logistic regression models and included 579 participants with MCI and 1,438 cognitively normal participants out of the total cohort. Anemic participants showed lower performances in verbal memory and executive functions. The fully adjusted odds ratios (OR) for MCI, aMCI, and naMCI in anemic versus non-anemic participants were 1.92 (95% -CI, 1.09-3.39), 1.96 (1.00-3.87), and 1.88 (0.91-3.87). Anemia at both times points showed a non-significant association with naMCI (OR 3.74, 0.94-14.81, fully adjusted). Our results suggest that anemia is associated with an increased risk of MCI independent of traditional cardiovascular risk factors. The association of anemia and MCI has important clinical relevance, because many causes of anemia can be treated effectively.
Keywords: Aged; Aged, 80 and over; Anemia; Cognitive Dysfunction; Cohort Studies; Executive Function; Female; Follow-Up Studies; Germany; Humans; Male; Memory; Middle Aged; Neuropsychological Tests; Prevalence; Speech Perception

Anthocyanins Protect SK-N-SH Cells Against Acrolein-Induced Toxicity by Preserving the Cellular Redox State. - Belkacemi, Abdenour; Ramassamy, Charles (J Alzheimers Dis, 2016)
In Alzheimer's disease (AD) and in mild cognitive impairment (MCI) patients, by-products of lipid peroxidation such as acrolein accumulated in vulnerable regions of the brain. We have previously shown that acrolein is a highly reactive and neurotoxic aldehyde and its toxicity involves the alteration of several redox-sensitive pathways. Recently, protein-conjugated acrolein in cerebrospinal fluid has been proposed as a biomarker to distinguish between MCI and AD. With growing evidence of the early involvement of oxidative stress in AD etiology, one would expect that a successful therapy should prevent brain oxidative damage. In this regard, several studies have demonstrated that polyphenol-rich extracts exert beneficial effect on cognitive impairment and oxidative stress. We have recently demonstrated the efficacy of an anthocyanin formulation (MAF14001) against amyloid-β-induced oxidative stress. The aim of this study is to investigate the neuroprotective effect of MAF14001 as a mixture of anthocyanins, a particular class of polyphenols, against acrolein-induced oxidative damage in SK-N-SH neuronal cells. Our results demonstrated that MAF14001, from 5μM, was able to efficiently protect SK-N-SH cells against acrolein-induced cell death. MAF14001 was able to lower reactive oxygen species and protein carbonyl levels induced by acrolein. Moreover, MAF1401 prevented glutathione depletion and positively modulated, in the presence of acrolein, some oxidative stress-sensitive pathways including the transcription factors NF-κB and Nrf2, the proteins γ-GCS and GSK3β, and the protein adaptator p66Shc. Along with its proven protective effect against amyloid-β toxicity, these results demonstrate that MAF14001 could target multiple mechanisms and could be a promising agent for AD prevention.
Keywords: Acrolein; Anthocyanins; Antioxidants; Cell Death; Cell Line, Tumor; Dose-Response Relationship, Drug; Glutathione; Humans; Neuroprotective Agents; NF-kappa B; Oxidation-Reduction; Oxidative Stress; Reactive Oxygen Species; Src Homology 2 Domain-Containing, Transforming Protein 1

Apathy and Attentional Biases in Alzheimer's Disease. - Chau, Sarah A; Chung, Jonathan; Herrmann, Nathan; Eizenman, Moshe; Lanctôt, Krista L (J Alzheimers Dis, 2016)
BACKGROUND: Apathy, one of the most prevalent neuropsychiatric symptoms in Alzheimer's disease (AD), can be difficult to assess as cognition deteriorates. There is a need for more objective assessments that do not rely on patient insight, communicative capacities, or caregiver observation. OBJECTIVE: We measured visual scanning behavior, using an eye-tracker, to explore attentional bias in the presence of competing stimuli to assess apathy in AD patients. METHODS: Mild-to-moderate AD patients (Standardized Mini-Mental Status Examination, sMMSE >10) were assessed for apathy (Neuropsychiatric Inventory [NPI] apathy, Apathy Evaluation Scale [AES]). Participants were presented with 16 slides, each containing 4 images of different emotional themes (2 neutral, 1 social, 1 dysphoric). The duration of time spent, and fixation frequency on images were measured. RESULTS: Of the 36 AD patients (14 females, age = 78.2±7.8, sMMSE = 22.4±3.5) included, 17 had significant apathy (based on NPI apathy ≥4) and 19 did not. These groups had comparable age and sMMSE. Repeated-measures analysis of covariance models, controlling for total NPI, showed group (apathetic versus non-apathetic) by image (social versus dysphoric) interactions for duration (F(1,32) = 4.31, p = 0.046) and fixation frequency (F(1,32) = 11.34, p = 0.002). Apathetic patients demonstrated reduced duration and fixation frequency on social images compared with non-apathetic patients. Additionally, linear regression models suggest that more severe apathy predicted decreasing fixation frequency on social images (R2 = 0.26, Adjusted R2 = 0.19, F(3,32) = 3.65, p = 0.023). CONCLUSION: These results suggest that diminished attentional bias toward social-themed stimuli is a marker of apathy in AD. Measurements of visual scanning behavior may have the potential to predict and monitor treatment response in apathy.
Keywords: Aged; Alzheimer Disease; Apathy; Attentional Bias; Cognition; Cross-Sectional Studies; Emotions; Eye Movement Measurements; Eye Movements; Female; Humans; Linear Models; Male; Neuropsychological Tests; Photic Stimulation; Severity of Illness Index; Social Perception

Apolipoprotein E Related Co-Morbidities and Alzheimer's Disease. - Singhrao, Sim K; Harding, Alice; Chukkapalli, Sasanka; Olsen, Ingar; Kesavalu, Lakshmyya; Crean, StJohn (J Alzheimers Dis, 2016)
The primary goal of advancement in clinical services is to provide a health care system that enhances an individual's quality of life. Incidence of diabetes mellitus, cardiovascular disease, and associated dementia coupled with the advancing age of the population, have led to an increase in the worldwide challenge to the healthcare system. In order to overcome these challenges, prior knowledge of common, reliable risk factors and their effectors is essential. Oral health constitutes one such relatively unexplored but indispensable risk factor for aforementioned co-morbidities, in the form of poor oral hygiene and tooth loss during aging. Behavioral traits such as low education, smoking, poor diet, neglect of oral health, lack of exercise, and hypertension are few of the risk factors that are shared commonly among these conditions. In addition, common genetic susceptibility traits such as the apolipoprotein E gene, together with an individual's lifestyle can also influence the development of co-morbidities such as periodontitis, atherosclerosis/stroke, diabetes, and Alzheimer's disease. This review specifically addresses the susceptibility of apolipoprotein E gene allele 4 as the plausible commonality for the etiology of co-morbidities that eventually result from periodontal diseases and ultimately progress to dementia.
Keywords: Aging; Alzheimer Disease; Animals; Apolipoprotein E4; Cardiovascular Diseases; Comorbidity; Diabetes Mellitus, Type 2; Humans; Mice; Periodontal Diseases

Apolipoprotein ɛ4 is Associated with Dementia and Cognitive Impairment Predominantly Due to Alzheimer's Disease and Not with Vascular Cognitive Impairment: A Singapore-Based Cohort. - Chai, Yuek Ling; Yeo, Hazel Kai-Hui; Wang, Jiehao; Hilal, Saima; Ikram, Mohammad Kamran; Venketasubramanian, Narayanaswamy; Wong, Boon-Seng; Chen, Christopher Li-Hsian (J Alzheimers Dis, 2016)
BACKGROUND AND OBJECTIVE: While the association for apolipoprotein ɛ4 allele (APOE4) with Alzheimer's disease (AD) has been consistently confirmed, the association with vascular cognitive impairment (VCI) is unclear. We therefore explored the relationship of APOE with both AD and cerebrovascular disease (CeVD) by examining the prevalence of APOE4 in AD, AD with CeVD and vascular dementia (VaD), as well as in cognitive impairment no dementia (CIND) with and without CeVD. METHODS: We performed a case-control study with subjects recruited from memory clinics and the community. All subjects underwent standardized brain neuroimaging, clinical and neuropsychological assessments, following which they were classified using research criteria. RESULTS: A total of 411 subjects; 92 controls with no cognitive impairment (NCI), 77 CIND without CeVD, 87 CIND with CeVD, 55 AD without CeVD, 68 AD with CeVD, and 32 VaD patients were recruited. Compared to NCI (16.3%), the prevalence of APOE4 carriers was significantly higher only in CIND (37.7%) and AD in the absence of CeVD (45.5%), but not in the three subgroups of VCI, namely CIND with CeVD (20.7%), AD with CeVD (27.9%) and VaD (25.0%). Logistic regression analyses also showed that APOE4 carriers were more likely to have CIND without CeVD (Odds Ratio [OR]: 3.34; 95% Confidence Interval [CI]: 1.59-7.03) and AD without CeVD (OR: 7.21; 95% CI: 2.74-18.98), but no such association was observed in the VCI subgroups. CONCLUSION: APOE4 is significantly associated with dementia and CIND due to AD pathology, but not with VCI.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Apolipoprotein E4; Cognition Disorders; Cohort Studies; Dementia; Female; Genetic Association Studies; Genotype; Humans; Male; Middle Aged; Neuroimaging; Neuropsychological Tests; Psychiatric Status Rating Scales; Singapore; Vascular Diseases

Application of the IWG-2 Diagnostic Criteria for Alzheimer's Disease to the ADNI. - Wang, Hui-Fu; Tan, Lan; Cao, Lei; Zhu, Xi-Chen; Jiang, Teng; Tan, Meng-Shan; Liu, Ying; Wang, Chong; Tsai, Richard M; Jia, Jian-Ping; Yu, Jin-Tai (J Alzheimers Dis, 2016)
BACKGROUND: The International Working Group (IWG) recently proposed the revised diagnostic criteria for Alzheimer's disease (AD) to define and refine several types of AD, and to reclassify AD-related biomarkers into diagnostic and progression markers, but its performance is not known. OBJECTIVE: This study was designed to describe the application of the revised IWG criteria in the Alzheimer's Disease Neuroimaging Initiative (ADNI) dataset, and to ascertain whether diagnostic and progression markers show significant differences in their relationships to AD severity and progression. METHODS: Based on the requirements of the refined criteria, 857 ADNI subjects with memory evaluation and at least one pathophysiological marker (CSF or amyloid imaging biomarkers) were eligible and reclassified in this study, and we calculated the associations of diagnostic (CSF and amyloid PET) and progression markers (MRI and fluorodeoxyglucose-PET) with AD severity and progression respectively. RESULTS: The majority (84.2% ) of ADNI AD group (n = 117) and 173 MCI (37.4% ) subjects in ADNI met the definition of typical AD; and 105 cognitively normal (41.0% ) individuals were diagnosed as asymptomatic AD. Furthermore, diagnostic and progression markers showed significant differences when correlated to AD severity and progression. CONCLUSION: A large proportion of AD dementia subjects were categorized as typical AD, and the revised criteria could identify typical AD from MCI status as well as asymptomatic AD at the asymptomatic stage. Moreover, the significant differences between diagnostic and progression markers further supported the new biomarkers categorization in the refined criteria.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid Precursor Protein Secretases; Aspartic Acid Endopeptidases; Cognitive Dysfunction; Databases, Factual; Disease Progression; Female; Humans; Longitudinal Studies; Male; Multicenter Studies as Topic; Neuroimaging; Psychiatric Status Rating Scales; tau Proteins

Association between Coffee Consumption and Incident Risk of Disabling Dementia in Elderly Japanese: The Ohsaki Cohort 2006 Study. - Sugiyama, Kemmyo; Tomata, Yasutake; Kaiho, Yu; Honkura, Kenji; Sugawara, Yumi; Tsuji, Ichiro (J Alzheimers Dis, 2016)
Epidemiological studies of the association between coffee consumption and dementia have yielded inconsistent results. Therefore, we investigated the association between coffee consumption and incident risk of dementia in an elderly Japanese population. 23,091 subjects aged ≥65 y living in Ohsaki City, northeastern Japan, responded to the baseline survey in 2006. Of these, we analyzed 13,137 subjects who gave informed consent and were not disabled at baseline. The outcome was the incidence of disabling dementia defined by usage of the Long-term Care Insurance database. We used the Cox proportional hazards regression model for multivariate analysis. During 5.7 y of follow-up period, we identified 1,107 cases of incident dementia. Overall, coffee consumption was significantly associated with a lower risk of incident dementia. The multivariate-adjusted HRs for the incidence of dementia according to coffee consumption categories (never, occasionally, 1-2 cups/d, and ≥3 cups/d) were 1.00, 0.73 (95% CI, 0.62-0.86), 0.72 (95% CI, 0.61-0.84), and 0.82 (95% CI, 0.65-1.02; p for trend = 0.009), respectively. In addition, this significant inverse association was more remarkable among women, non-smokers, and non-drinkers. Coffee consumption is significantly associated with a lower risk of incident dementia.
Keywords: Aged; Aged, 80 and over; Coffee; Dementia; Female; Health Surveys; Humans; Incidence; Japan; Male; Prospective Studies; Risk Factors

Association Between Serum Ceruloplasmin Specific Activity and Risk of Alzheimer's Disease. - Siotto, Mariacristina; Simonelli, Ilaria; Pasqualetti, Patrizio; Mariani, Stefania; Caprara, Deborah; Bucossi, Serena; Ventriglia, Mariacarla; Molinario, Rossana; Antenucci, Mirca; Rongioletti, Mauro; Rossini, Paolo Maria; Squitti, Rosanna (J Alzheimers Dis, 2016)
Meta-analyses demonstrate copper involvement in Alzheimer's disease (AD), and the systemic ceruloplasmin status in relation to copper is an emerging issue. To deepen this matter, we evaluated levels of ceruloplasmin concentration, ceruloplasmin activity, ceruloplasmin specific activity (eCp/iCp), copper, non-ceruloplasmin copper iron, transferrin, the ceruloplasmin/transferrin ratio, and the APOE genotype in a sample of 84 AD patients and 58 healthy volunteers. From the univariate logistic analyses we found that ceruloplasmin concentration, eCp/iCp, copper, transferrin, the ceruloplasmin/transferrin ratio, and the APOE genotype were significantly associated with the probability of AD. In the multivariable logistic regression analysis, we selected the best subset of biological predictors by the forward stepwise procedure. The analysis showed a decrease of the risk of having AD for eCp/iCp (p = 0.001) and an increase of this risk for non-ceruloplasmin copper (p = 0.008), age (p = 0.001), and APOE-ɛ4 allele (p <  0.001). The estimated model showed a good power in discriminating AD patients from healthy controls (area under curve: 88% ; sensitivity: 66% ; specificity 93%). These data strength the breakdown of copper homeostasis and propose eCp/iCp as a reliable marker of ceruloplasmin status.
Keywords: Aged; Alzheimer Disease; Apolipoprotein E4; Area Under Curve; Biomarkers; Blood Chemical Analysis; Ceruloplasmin; Copper; Female; Genotype; Genotyping Techniques; Humans; Logistic Models; Male; Multivariate Analysis; Prognosis; Risk; ROC Curve; Sensitivity and Specificity; Transferrin

Association of Butyrylcholinesterase-K Allele and Apolipoprotein E ɛ4 Allele with Cognitive Decline in Dementia with Lewy Bodies and Alzheimer's Disease. - Vijayaraghavan, Swetha; Darreh-Shori, Taher; Rongve, Arvid; Berge, Guro; Sando, Sigrid B; White, Linda R; Auestad, Bjørn H; Witoelar, Aree; Andreassen, Ole A; Ulstein, Ingun D; Aarsland, Dag (J Alzheimers Dis, 2016)
BACKGROUND: A common polymorphism of the butyrylcholinesterase gene, the K-variant (BCHE-K) is associated with reduced butyrylcholinesterase (BuChE) activity. Insufficient studies exist regarding the frequency and role of BCHE-K in dementias. OBJECTIVE: To determine the association of BCHE-K and APOEɛ4 with diagnosis and rate of cognitive decline in dementia with Lewy bodies (DLB) and Alzheimer's disease (AD) patients. METHODS: Genomic DNA from 368 subjects (108 AD, 174 DLB, and 86 controls) from two routine clinical cohort studies in Norway; DemVest and TrønderBrain, were genotyped for BCHE-K and APOEɛ4. The mild dementia DemVest subjects received annual Mini-Mental State Examination assessments for five years. RESULTS: BCHE-K frequency was lower in DLB (33.9% ; p <  0.01) than in control subjects (51.2%), and was numerically lower in AD as well (38.9% ; p = 0.11). More rapid cognitive decline was associated with the APOEɛ4 genotype, but not with the BCHE-K genotype. In an exploratory analysis of patients who completed all five follow-up visits, there was greater cognitive decline in BCHE-K carriers in the presence of the APOEɛ4 allele than in the absence of these polymorphisms. CONCLUSION: BCHE-K is associated with a reduced risk for AD and DLB whereas APOEɛ4 is associated with more rapid cognitive decline. The greater cognitive decline in individuals with both APOEɛ4 and BCHE-K alleles require prospective confirmation in well-controlled trials.
Keywords: Aged; Aged, 80 and over; Alleles; Alzheimer Disease; Apolipoprotein E4; Butyrylcholinesterase; Cognition; Disease Progression; Female; Gene Frequency; Genotype; Humans; Lewy Body Disease; Male; Neuropsychological Tests

Association of Frontotemporal Dementia GWAS Loci with Late-Onset Alzheimer's Disease in a Northern Han Chinese Population. - Tan, Chen-Chen; Wan, Yu; Tan, Meng-Shan; Zhang, Wei; Wang, Zi-Xuan; Sun, Fu-Rong; Miao, Dan; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2016)
BACKGROUND: Both Alzheimer's disease (AD) and frontotemporal dementia (FTD) are a class of neurodegenerative diseases. Strong similarities in cerebrospinal fluid biomarker, imaging markers, and disease progression profiles suggest that some or most of the pathophysiology is shared between AD and FTD. A recent large genome-wide association study reported several single nucleotide polymorphisms (SNPs) at the RAB38, RAB38/CTSC, HLA-DRA/HLA-DRB5, and BTNL2 in association with FTD. OBJECTIVE: To explore whether these SNPs are associated with AD risk. METHODS: We conducted a case-control study to investigate the association of FTD-associated loci in 2338 Han Chinese subjects. RESULTS: We observed significant differences in genotype distributions of rs302668 (pc = 0.025), rs9268877 (pc = 0.025), rs9268856 (p <  0.001), and rs1980493 (pc = 0.045) between cases and controls. The SNPs rs16913634 for RAB38/CTSC was unrelated to LOAD risk (p = 0.088). CONCLUSION: The SNPs rs302668 in RAB38, rs9268877 and rs9268856 polymorphism in HLA-DRA/HLA-DRB5, and rs1980493 polymorphism in BTNL2 might play a role in the susceptibility to late-onset AD in the Han Chinese population.
Keywords: Age of Onset; Aged; Alzheimer Disease; Apolipoprotein E4; Asian Continental Ancestry Group; Case-Control Studies; China; Female; Frontotemporal Dementia; Gene Frequency; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Genotyping Techniques; Humans; Linkage Disequilibrium; Male; Mental Status Schedule; Polymorphism, Single Nucleotide

Association of Serum Vitamin D with the Risk of Incident Dementia and Subclinical Indices of Brain Aging: The Framingham Heart Study. - Karakis, Ioannis; Pase, Matthew P; Beiser, Alexa; Booth, Sarah L; Jacques, Paul F; Rogers, Gail; DeCarli, Charles; Vasan, Ramachandran S; Wang, Thomas J; Himali, Jayandra J; Annweiler, Cedric; Seshadri, Sudha (J Alzheimers Dis, 2016)
BACKGROUND: Identifying nutrition- and lifestyle-based risk factors for cognitive impairment and dementia may aid future primary prevention efforts. OBJECTIVE: We aimed to examine the association of serum vitamin D levels with incident all-cause dementia, clinically characterized Alzheimer's disease (AD), MRI markers of brain aging, and neuropsychological function. METHODS: Framingham Heart Study participants had baseline serum 25-hydroxyvitamin D (25(OH)D) concentrations measured between 1986 and 2001. Vitamin D status was considered both as a continuous variable and dichotomized as deficient (<10 ng/mL), or at the cohort-specific 20th and 80th percentiles. Vitamin D was related to the 9-year risk of incident dementia (n = 1663), multiple neuropsychological tests (n = 1291) and MRI markers of brain volume, white matter hyperintensities and silent cerebral infarcts (n = 1139). RESULTS: In adjusted models, participants with vitamin D deficiency (n = 104, 8% of the cognitive sample) displayed poorer performance on Trail Making B-A (β= -0.03 to -0.05±0.02) and the Hooper Visual Organization Test (β= -0.09 to -0.12±0.05), indicating poorer executive function, processing speed, and visuo-perceptual skills. These associations remained when vitamin D was examined as a continuous variable or dichotomized at the cohort specific 20th percentile. Vitamin D deficiency was also associated with lower hippocampal volumes (β= -0.01±0.01) but not total brain volume, white matter hyperintensities, or silent brain infarcts. No association was found between vitamin D deficiency and incident all-cause dementia or clinically characterized AD. CONCLUSIONS: In this large community-based sample, low 25(OH)D concentrations were associated with smaller hippocampal volume and poorer neuropsychological function.
Keywords: Adult; Aging; Brain; Cohort Studies; Dementia; Female; Humans; Incidence; Magnetic Resonance Imaging; Male; Middle Aged; Multivariate Analysis; Neuropsychological Tests; Regression Analysis; Risk; Sensitivity and Specificity; Vitamin D

Associations between Neuropsychiatric Symptoms and Cerebral Amyloid Deposition in Cognitively Impaired Elderly People. - Bensamoun, David; Guignard, Renaud; Furst, Ansgar J; Derreumaux, Alexandre; Manera, Valeria; Darcourt, Jacques; Benoit, Michel; Robert, Philippe H; David, Renaud (J Alzheimers Dis, 2016)
BACKGROUND: Neuropsychiatric symptoms, also known as behavioral and psychological symptoms of dementia (BPSD), affect the majority of patients with dementia, and result in a greater cognitive and functional impairment. OBJECTIVE: To investigate associations between BPSD and amyloid cerebral deposition as measured by 18F-Florbetapir-PET quantitative uptake in elderly subjects with and without cognitive impairment. METHODS: Participants with cognitive impairment [mild cognitive impairment (MCI) or Alzheimer's disease (AD)] and healthy controls (HC) from the ADNI cohort (Alzheimer Disease Neuroimaging Initiative) who underwent an 18F-florbetapir PET scan between May 2010 and March 2014 were included. Clinical assessments included the Clinical Dementia Rating, the Mini-Mental State Examination (MMSE), and the Neuropsychiatric Inventory. Freesurfer software was used to extract PET counts based on T1-based structural ROI (frontal, cingulate, parietal, and temporal). Spearman's partial correlation scores between BPSD severity and regional amyloid uptake were calculated. RESULTS: Data for 657 participants [age = 72.6 (7.19); MMSE = 27.4 (2.67)] were analyzed, including 230 HC [age = 73.1 (6.02); MMSE = 29 (1.21)], 308 MCI [age = 71.5 (7.44); MMSE = 28.0 (1.75)], and 119 AD subjects [age = 74.7 (8.05); MMSE = 23.1 (2.08)]. Considering all diagnostic groups together, positive significant correlations were found between anxiety and 18F-florbetapir uptake in the frontal (r = 0.102; p = 0.009), cingulate (r = 0.083; p = 0.034), and global cerebral uptake (r = 0.099; p = 0.011); between irritability and frontal (r = 0.089; p = 0.023), cingulate (r = 0.085; p = 0.030), parietal (r = 0.087; p = 0.025), and global cerebral uptake (r = 0.093; p = 0.017); in the MCI subgroup, between anxiety and frontal (r = 0.126; p = 0.03) and global uptake (r = 0.14; p = 0.013); in the AD subgroup, between irritability and parietal uptake (r = 0.201; p = 0.03). CONCLUSION: Anxiety and irritability are associated with greater amyloid deposition in the neurodegenerative process leading to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloidogenic Proteins; Cerebral Cortex; Cognition Disorders; Cohort Studies; Female; Fluorodeoxyglucose F18; Humans; Male; Mental Status Schedule; Mood Disorders; Neuropsychological Tests; Positron-Emission Tomography

Associations between Serum Omega-3 Fatty Acid Levels and Cognitive Functions among Community-Dwelling Octogenarians in Okinawa, Japan: The KOCOA Study. - Nishihira, Junko; Tokashiki, Takashi; Higashiuesato, Yasushi; Willcox, Donald Craig; Mattek, Nora; Shinto, Lynne; Ohya, Yusuke; Dodge, Hiroko H (J Alzheimers Dis, 2016)
BACKGROUND: Epidemiological studies have found frequent consumption of fatty fish is protective against cognitive decline. However, the association between circulating omega-3 polyunsaturated fatty acid (PUFA) levels and cognitive functions among the oldest old is not well known. OBJECTIVE: To examine the association between serum PUFA levels and cognitive function among community-dwelling, non-demented elderly aged over 80 years old. METHODS: The data came from the Keys to Optimal Cognitive Aging (KOCOA) study; an ongoing cohort of relatively healthy volunteers aged over 80 years old, living in Okinawa, Japan. One hundred eighty five participants (mean age 84.1±3.4 years) assessed in 2011 who were free from frank dementia (defined as Clinical Dementia Rating <1.0) were used for the current cross-sectional study. We examined whether serum omega-3 PUFAs (docosahexaenoic acid [DHA] and eicosapentaenoic acid [EPA]), arachidonic acid (AA), EPA/AA ratio, DHA/AA ratio, and DHA+EPA are associated with (1) age and (2) global cognitive function (Japanese MMSE) and executive function (Verbal Fluency Letter). Data was analyzed univariately by t-test and multivariately by cumulative logistic regression models controlling for age, gender, years of education, obesity, hypertension, diabetes, and dyslipidemia. RESULTS: Serum DHA levels decreased with increasing age (p = 0.04). Higher global cognitive function was associated with higher levels of serum EPA (p = 0.03) and DHA + EPA (p = 0.03) after controlling for confounders. CONCLUSIONS: Higher serum EPA and DHA + EPA levels were independently associated with better scores on global cognitive function among the oldest old, free from dementia. Longitudinal follow-up studies are warranted.
Keywords: Age Factors; Aged, 80 and over; Arachidonic Acid; Blood Chemical Analysis; Cognition; Cross-Sectional Studies; Educational Status; Fatty Acids, Omega-3; Female; Humans; Japan; Logistic Models; Male; Mental Status Schedule; Obesity; Prospective Studies; Sex Factors

Astrocytes release HspB1 in response to amyloid-β exposure in vitro. - Nafar, Firoozeh; Williams, J Bradley; Mearow, Karen M (J Alzheimers Dis, 2016)
Although heat shock proteins are thought to function primarily as intracellular chaperones, the release and potential extracellular functions of heat shock proteins have been the focus of an increasing number of studies. Our particular interest is HspB1 (Hsp25/27) and as astrocytes are an in vivo source of HspB1 it is a reasonable possibility they could release HspB1 in response to local stresses. Using primary cultures of rat cortical astrocytes, we investigated the extracellular release of HspB1 with exposure to amyloid-β (Aβ). In order to assess potential mechanisms of release, we cotreated the cells with compounds that can modulate protein secretion including Brefeldin A, Methyl β-cyclodextrin, and MAP kinase inhibitors. Exposure to Aβ (0.1, 1.0, 2.0 μM) for 24-48 h resulted in a selective release of HspB1 that was insensitive to BFA treatment; none of the other inhibitors had any detectable influence. Protease protection assays indicated that some of the released HspB1 was associated with a membrane bound fraction, and analysis of exosomal preparations indicated the presence of HspB1 in exosomes. Finally, immunoprecipitation experiments demonstrated that the extracellular HspB1 was able to interact with extracellular Aβ. In summary, Aβ can stimulate release of HspB1 from astrocytes, this release is insensitive to Golgi or lipid raft disruption, and HspB1 can be found either free in the medium or associated with exosomes. This release suggests that there is a potential for extracellular HspB1 to be able to bind and sequester extracellular Aβ.
Keywords: Amyloid beta-Peptides; Animals; Astrocytes; Cells, Cultured; HSP27 Heat-Shock Proteins; Protein Transport; Rats

Beneficial Effects of an Integrated Psychostimulation Program in Patients with Alzheimer's Disease. - Ibarria, Marta; Alegret, Montserrat; Valero, Sergi; Morera, Amèrica; Guitart, Marina; Cañabate, Pilar; Moreno, Mariola; Lara, Susana; Diego, Susana; Hernández, Joan; Tantinyá, Natàlia; Vera, Maribel; et al. (J Alzheimers Dis, 2016)
BACKGROUND: The existing pharmacological treatments for Alzheimer's disease (AD) can only slow the progression of symptoms or delay admission to long-term care facilities. The beneficial effects of non-drug treatments are poorly studied. OBJECTIVE: To describe the effects of an Integrated Psychostimulation Program (IPP) in patients with mild-moderate AD treated with acetylcholinesterase inhibitors; and to identify factors related to greater benefit of the IPP. METHODS: 206 patients (mean age = 75.9 years; MMSE = 19.6) were evaluated before starting the IPP and 3, 6, 9, and 12 months later. Measures included: Mini-Mental State Examination (MMSE), Cognitive Subscale of Alzheimer's Disease Assessment Scale (ADAS-Cog), Rapid Disability Rating Scale (RDRS-2), and Neuropsychiatric Inventory Questionnaire (NPI-Q). RESULTS: Patients remained cognitively stable (MMSE/ADAS-Cog) for more than 6 months and significantly worsened at 9-month and 12-month follow-ups, without clinically significant functional changes (RDRS-2) or psychiatric symptoms(NPI-Q). The mean annual change on MMSE and ADAS-Cog were 2.06 and 3.56 points, respectively, lower than the annual decline demonstrated previously in similar patients (2.4 and 4.5, respectively). 42.7% of patients maintained or improved global cognitive scores between baseline and 12-month follow-up. The patients who maintained cognitive functions were older than those who did not (77.5 versus 74.7 years). CONCLUSIONS: The IPP may be an effective treatment to maintain cognition, functionality, and psychiatric symptoms in AD patients pharmacologically treated, and older age seems to increase beneficial effects of IPP.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cholinesterase Inhibitors; Cognition; Combined Modality Therapy; Disease Progression; Female; Humans; Male; Neuropsychological Tests; Psychotherapy; Severity of Illness Index; Treatment Outcome

Blood-Borne Activity-Dependent Neuroprotective Protein (ADNP) is Correlated with Premorbid Intelligence, Clinical Stage, and Alzheimer's Disease Biomarkers. - Malishkevich, Anna; Marshall, Gad A; Schultz, Aaron P; Sperling, Reisa A; Aharon-Peretz, Judith; Gozes, Illana (J Alzheimers Dis, 2016)
Biomarkers for Alzheimer's disease (AD) are vital for disease detection in the clinical setting. Discovered in our laboratory, activity-dependent neuroprotective protein (ADNP) is essential for brain formation and linked to cognitive functions. Here, we revealed that blood borne expression of ADNP and its paralog ADNP2 is correlated with premorbid intelligence, AD pathology, and clinical stage. Age adjustment showed significant associations between: 1) higher premorbid intelligence and greater serum ADNP, and 2) greater cortical amyloid and lower ADNP and ADNP2 mRNAs. Significant increases in ADNP mRNA levels were observed in patients ranging from mild cognitive impairment (MCI) to AD dementia. ADNP2 transcripts showed high correlation with ADNP transcripts, especially in AD dementia lymphocytes. ADNP plasma/serum and lymphocyte mRNA levels discriminated well between cognitively normal elderly, MCI, and AD dementia participants. Measuring ADNP blood-borne levels could bring us a step closer to effectively screening and tracking AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Chi-Square Distribution; Cognitive Dysfunction; Cohort Studies; Female; Homeodomain Proteins; Humans; Independent Living; Intelligence; Male; Mental Status Schedule; Middle Aged; Nerve Tissue Proteins; Peptide Fragments; RNA, Messenger; tau Proteins

Brain Metabolism Correlates of the Free and Cued Selective Reminding Test in Mild Cognitive Impairment. - Caffarra, Paolo; Ghetti, Caterina; Ruffini, Livia; Spallazzi, Marco; Spotti, Annamaria; Barocco, Federica; Guzzo, Caterina; Marchi, Massimo; Gardini, Simona (J Alzheimers Dis, 2016)
Free and Cued Selective Reminding Test (FCSRT) measures immediate and delayed episodic memory and cueing sensitivity and is suitable to detect prodromal Alzheimer's disease (AD). The present study aimed at investigating the segregation effect of FCSRT scores on brain metabolism of memory-related structures, usually affected by AD pathology, in the Mild Cognitive Impairment (MCI) stage. A cohort of forty-eight MCI patients underwent FCSRT and 18F-FDG-PET. Multiple regression analysis showed that Immediate Free Recall correlated with brain metabolism in the bilateral anterior cingulate and delayed free recall with the left anterior cingulate and medial frontal gyrus, whereas semantic cueing sensitivity with the left posterior cingulate. FCSRT in MCI is associated with neuro-functional activity of specific regions of memory-related structures connected to hippocampal formation, such as the cingulate cortex, usually damaged in AD.
Keywords: Aged; Brain; Cognitive Dysfunction; Cues; Female; Fluorodeoxyglucose F18; Humans; Male; Memory Disorders; Memory, Episodic; Mental Recall; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography

Cannabinoid Receptor 2 Participates in Amyloid-β Processing in a Mouse Model of Alzheimer's Disease but Plays a Minor Role in the Therapeutic Properties of a Cannabis-Based Medicine. - Aso, Ester; Andrés-Benito, Pol; Carmona, Margarita; Maldonado, Rafael; Ferrer, Isidre (J Alzheimers Dis, 2016)
The endogenous cannabinoid system represents a promising therapeutic target to modify neurodegenerative pathways linked to Alzheimer's disease (AD). The aim of the present study was to evaluate the specific contribution of CB2 receptor to the progression of AD-like pathology and its role in the positive effect of a cannabis-based medicine (1:1 combination of Δ9-tetrahidrocannabinol and cannabidiol) previously demonstrated to be beneficial in the AβPP/PS1 transgenic model of the disease. A new mouse strain was generated by crossing AβPP/PS1 transgenic mice with CB2 knockout mice. Results show that lack of CB2 exacerbates cortical Aβ deposition and increases the levels of soluble Aβ40. However, CB2 receptor deficiency does not affect the viability of AβPP/PS1 mice, does not accelerate their memory impairment, does not modify tau hyperphosphorylation in dystrophic neurites associated to Aβ plaques, and does not attenuate the positive cognitive effect induced by the cannabis-based medicine in these animals. These findings suggest a minor role for the CB2 receptor in the therapeutic effect of the cannabis-based medicine in AβPP/PS1 mice, but also constitute evidence of a link between CB2 receptor and Aβ processing.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Cannabidiol; Cognition; Disease Models, Animal; Dronabinol; Humans; Male; Medical Marijuana; Memory; Mice, Inbred C57BL; Mice, Transgenic; Nootropic Agents; Presenilin-1; Random Allocation; Receptor, Cannabinoid, CB2; tau Proteins; Treatment Outcome

Capillary amyloid-β protein deposition in a population-based study (Vantaa 85+). - Mäkelä, Mira; Paetau, Anders; Polvikoski, Tuomo; Myllykangas, Liisa; Tanskanen, Maarit (J Alzheimers Dis, 2016)
BACKGROUND: Capillary amyloid-β (capAβ) deposition in the cerebral cortex is the neuropathological feature providing the basis for categorizing cerebral amyloid angiopathy (CAA) into two distinct types, CAA-Type1 with capAβ and CAA-Type2 without capAβ. OBJECTIVE: We investigated the neuropathological and clinical characteristics of capAβ deposition in a prospective population-based study. METHODS: Vantaa 85+ includes 601 individuals aged ≥85 years, of which 300 were studied clinically and neuropathologically. 278 subjects were analyzed for the apolipoprotein E (APOE) genotype. The diagnosis of capAβ was determined using immunohistochemistry against Aβ, and of CAA using Congo red confirmed by Aβ immunohistochemistry, both analyzed in six brain areas. The severity of capAβ was graded semi-quantitatively, and the severity of CAA was based on the percentage of affected vessels. Alzheimer's disease (AD)-type neuropathology (CERAD score and Braak stage) was analyzed using standard methods. RESULTS: CAA-Type1 was present in 86/300, CAA-Type2 in 135/300, and 79/300 had no CAA. CapAβ was most frequent in the occipital lobe (79/86). CAA-Type1 was associated with the severity of CAA (p <  0.001), dementia (p <  0.001), severe AD-type neuropathology (p-value 0.09 for CERAD C and 0.017 for Braak stages V-VI), and APOE ɛ4 allele carrier status (p <  0.001). CONCLUSIONS: This population-based study confirmed the presence of distinct CAA-Type1 and its association with the severity of CAA, severe AD-type neuropathology, and the APOE ɛ4 carrier status. Both the severity and localization of the deposition seemed to determine the clinical significance of capAβ.
Keywords: Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Autopsy; Capillaries; Cerebral Amyloid Angiopathy; Female; Finland; Genotype; Humans; Immunohistochemistry; Logistic Models; Male; Multivariate Analysis; Occipital Lobe; Prospective Studies; Severity of Illness Index

Cerebral Amyloid Angiopathy (CAA)-Related Inflammation: Comparison of Inflammatory CAA and Amyloid-β-Related Angiitis. - Chu, Shuguang; Xu, Feijia; Su, Ya; Chen, Hong; Cheng, Xin (J Alzheimers Dis, 2016)
Cerebral amyloid angiopathy-related inflammation (CAA-ri) is a relatively rare syndrome of reversible encephalopathy and could be divided into two subtypes of inflammatory CAA (ICAA) and amyloid-β-related angiitis (ABRA) according to histopathology. We present a case of pathologically proved ABRA with partial seizures and headache, and a focal lesion in the right temporal lobes on magnetic resonance imaging. Summarized from previous 139 ABRA and ICAA cases, ABRA is preferred when the lesion is enhanced on MRI and requires combination drug therapy, while ICAA is highly suspected with ApoE genotype of ɛ4/ɛ4. More clinical markers for diagnosis of CAA-ri warrant further researches.
Keywords: Apolipoproteins E; Cerebral Amyloid Angiopathy; Headache; Humans; Inflammation; Magnetic Resonance Imaging; Male; Middle Aged; Seizures; Vasculitis, Central Nervous System

Cerebral Small Vessel Disease and Motoric Cognitive Risk Syndrome: Results from the Kerala-Einstein Study. - Wang, Nan; Allali, Gilles; Kesavadas, Chandrasekharan; Noone, Mohan L; Pradeep, Vayyattu G; Blumen, Helena M; Verghese, Joe (J Alzheimers Dis, 2016)
BACKGROUND: The contribution of cerebral small vessel disease to cognitive decline, especially in non-Caucasian populations, is not well established. OBJECTIVE: We examined the relationship between cerebral small vessel disease and motoric cognitive risk syndrome (MCR), a recently described pre-dementia syndrome, in Indian seniors. METHODS: 139 participants (mean age 66.6 ± 5.4 y, 33.1% female) participating in the Kerala-Einstein study in Southern India were examined in a cross-sectional study. The presence of cerebral small vessel disease (lacunar infarcts and cerebral microbleeds (CMB)) and white matter hyperintensities on MRI was ascertained by raters blinded to clinical information. MCR was defined by the presence of cognitive complaints and slow gait in older adults without dementia or mobility disability. RESULTS: Thirty-eight (27.3%) participants met MCR criteria. The overall prevalence of lacunar infarcts and CMB was 49.6% and 9.4% , respectively. Lacunar infarcts in the frontal lobe, but no other brain regions, were associated with MCR even after adjusting for vascular risk factors and presence of white matter hyperintensities (adjusted Odds Ratio (aOR): 4.67, 95% CI: 1.69-12.94). Frontal lacunar infarcts were associated with slow gait (aOR: 3.98, 95% CI: 1.46-10.79) and poor performance on memory test (β: -1.24, 95% CI: -2.42 to -0.05), but not with cognitive complaints or non-memory tests. No association of CMB was found with MCR, individual MCR criterion or cognitive tests. CONCLUSIONS: Frontal lacunar infarcts are associated with MCR in Indian seniors, perhaps, by contributing to slow gait and poor memory function.
Keywords: Aged; Brain; Cerebral Small Vessel Diseases; Cognition Disorders; Female; Humans; Image Processing, Computer-Assisted; India; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales; Risk Factors; Stroke, Lacunar; White Matter

Cerebrospinal Fluid Alzheimer's Disease Biomarkers in Cerebral Amyloid Angiopathy-Related Inflammation. - Renard, Dimitri; Wacongne, Anne; Ayrignac, Xavier; Charif, Mahmoud; Fourcade, Genevieve; Azakri, Souhayla; Le Floch, Anne; Bouly, Stephane; Marelli, Cecilia; Arquizan, Caroline; Hirtz, Christophe; Gabelle, Audrey; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Decreased cerebrospinal fluid (CSF) amyloid-β 1-40 (Aβ40) and amyloid-β 1-42 (Aβ42) and increased total and phosphorylated tau (t-tau, p-tau) concentrations have been described in cerebral amyloid angiopathy (CAA). OBJECTIVE: Our aim was to analyze these biomarkers in patients with CAA-related inflammation (CAA-I). METHODS: We prospectively recruited nine patients with acute phase CAA-I fulfilling Chung criteria. CSF was analyzed for t-tau, p-tau, Aβ42, and Aβ40. Data were compared to controls (n = 14), patients with Alzheimer's disease (AD, n = 42), CAA (n = 10), and primary angiitis of the central nervous system (PACNS, n = 3). RESULTS: For the CAA-I group, statistically significant differences were: lower Aβ42 (p = 0.00053) compared to the control group; lower t-tau (p = 0.018), p-tau (p <  0.001), and Aβ40 (p <  0.001) compared to AD; lower Aβ42 (p = 0.027) compared to CAA; lower Aβ42 (p = 0.012) compared to PACNS. Nearly significantly lower Aβ40 (p = 0.051) and higher t-tau (p = 0.051) were seen in CAA-I compared to controls. CONCLUSION: CSF biomarkers profile similar to that of CAA was observed in CAA-I (with even lower levels of Aβ42 compared to CAA). Based on our findings, high p-tau seems more specific for AD, whereas low Aβ42 differentiates CAA-I from CAA, PACNS, and controls, and low Aβ40 differentiates CAA-I from AD.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cerebral Amyloid Angiopathy; Female; Humans; Inflammation; Male; Middle Aged; Retrospective Studies; tau Proteins

Cerebrospinal Fluid Anti-Amyloid-β Autoantibodies and Amyloid PET in Cerebral Amyloid Angiopathy-Related Inflammation. - Carmona-Iragui, María; Fernández-Arcos, Ana; Alcolea, Daniel; Piazza, Fabrizio; Morenas-Rodriguez, Estrella; Antón-Aguirre, Sofía; Sala, Isabel; Clarimón, Jordi; Dols-Icardo, Oriol; Camacho, Valle; Sampedro, Frederic; Munuera, Josep; et al. (J Alzheimers Dis, 2016)
We report a biomarker and genetic evaluation of four patients with cerebral amyloid angiopathy-related inflammation (CAA-ri) treated with corticosteroids. Patients presented with focal symptomatology and cognitive impairment. MRI revealed cortical microbleeds and asymmetrical hyperintense white matter lesions (WML). Cerebrospinal fluid (CSF) biomarker analyses showed increased anti-Aβ autoantibodies, t-Tau, and p-Tau and decreased Aβ40 and Aβ42. After treatment, focal symptomatology disappeared, and WML and anti-Aβ autoantibodies decreased. The APOEɛ4 allele was overrepresented. Florbetapir-PET showed cortical deposition with lower retention in swollen areas. In the case of suspected CAA-ri, both CSF anti-Aβ autoantibodies levels and Florbetapir-PET could provide highly useful data to guide the correct diagnosis.
Keywords: Aged; Amyloid beta-Peptides; Aniline Compounds; Apolipoproteins E; Autoantibodies; Cerebral Amyloid Angiopathy; Ethylene Glycols; Female; Humans; Magnetic Resonance Imaging; Male; Meningoencephalitis; Peptide Fragments; Positron-Emission Tomography; Statistics, Nonparametric; tau Proteins

Cerebrospinal Fluid Fatty Acid-Binding Protein 3 is Related to Dementia Development in a Population-Based Sample of Older Adult Women Followed for 8 Years. - Bjerke, Maria; Kern, Silke; Blennow, Kaj; Zetterberg, Henrik; Waern, Margda; Börjesson-Hanson, Anne; Östling, Svante; Kern, Jürgen; Skoog, Ingmar (J Alzheimers Dis, 2016)
BACKGROUND: Increased fatty acid-binding protein 3 (FABP-3) levels have been reported in neurodegenerative diseases, including Alzheimer's disease (AD). Cerebrospinal fluid (CSF) FABP-3 has therefore been proposed as a putative marker for dementia. Population-based studies examining whether CSF FABP-3 predicts later development of dementia are lacking. OBJECTIVE: The aim of this study was to examine CSF levels of FABP-3 in relation to later development of dementia in elderly women and in relation to Aβ42, T-tau, P-tau181, and CSF: serum albumin ratio. METHODS: 86 non-demented women aged 70-84 years who participated in the Prospective Population Study of Women in Gothenburg, Sweden took part in a lumbar puncture in 1992-93. CSF-FABP-3, Aβ42, T-tau, P-tau181, and the CSF: serum albumin ratio were measured at baseline. Participants were examined with a neuropsychiatric exam at baseline and at follow-up in 2000. Dementia was diagnosed in accordance with DSM-III-R criteria. RESULTS: Between 1992 and 2000, 8 women developed dementia (4 AD, 3 vascular dementia, 1 mixed vascular dementia and AD). Higher levels of CSF-FABP-3 at baseline were related to development of dementia (OR 1.36 CI [1.05-1.76] p = 0.022) and the subtype AD (OR 1.38 CI [1.06-1.82), p = 0.019) during follow-up. FABP-3 correlated with CSF T-tau (r = 0.88, p <  0.001), P-tau181 (r = 0.619, p <  0.001), and CSF:serum albumin ratio (r = 0.233, p = 0.031), but not with Aβ42 (r = -0.08, p = 0.444)CONCLUSION:CSF FABP-3 may be an early marker for later development of dementia, probably related to neuronal degeneration, but independent of Aβ metabolism.
Keywords: Aged; Aged, 80 and over; Albumins; Amyloid beta-Peptides; Community Health Planning; Dementia; Fatty Acid-Binding Proteins; Female; Humans; Longitudinal Studies; Peptide Fragments; Sweden; tau Proteins

Cerebrospinal Fluid Markers of Alzheimer's Disease Pathology and Microglial Activation are Associated with Altered White Matter Microstructure in Asymptomatic Adults at Risk for Alzheimer's Disease. - Melah, Kelsey E; Lu, Sharon Yuan-Fu; Hoscheidt, Siobhan M; Alexander, Andrew L; Adluru, Nagesh; Destiche, Daniel J; Carlsson, Cynthia M; Zetterberg, Henrik; Blennow, Kaj; Okonkwo, Ozioma C; Gleason, Carey E; Dowling, N Maritza; et al. (J Alzheimers Dis, 2016)
BACKGROUND: The immune response in Alzheimer's disease (AD) involves activation of microglia which may remove amyloid-β (Aβ). However, overproduction of inflammatory compounds may exacerbate neural damage in AD. AD pathology accumulates years before diagnosis, yet the extent to which neuroinflammation is involved in the earliest disease stages is unknown. OBJECTIVE: To determine whether neuroinflammation exacerbates neural damage in preclinical AD. METHODS: We utilized cerebrospinal fluid (CSF) and magnetic resonance imaging collected in 192 asymptomatic late-middle-aged adults (mean age = 60.98 years). Neuroinflammatory markers chitinase-3-like protein 1 (YKL-40) and monocyte chemoattractant protein-1 (MCP-1) in CSF were utilized as markers of neuroinflammation. Neural cell damage was assessed using CSF neurofilament light chain protein (NFL), CSF total tau (T-Tau), and neural microstructure assessed with diffusion tensor imaging (DTI). With regard to AD pathology, CSF Aβ42 and tau phosphorylated at threonine 181 (P-Tau181) were used as markers of amyloid and tau pathology, respectively. We hypothesized that higher YKL-40 and MCP-1 in the presence of AD pathology would be associated with higher NFL, T-Tau, and altered microstructure on DTI. RESULTS: Neuroinflammation was associated with markers of neural damage. Higher CSF YKL-40 was associated with both higher CSF NFL and T-Tau. Inflammation interacted with AD pathology, such that greater MCP-1 and lower Aβ42 was associated with altered microstructure in bilateral frontal and right temporal lobe and that greater MCP-1 and greater P-Tau181 was associated with altered microstructure in precuneus. CONCLUSION: Inflammation may play a role in neural damage in preclinical AD.
Keywords: Adipokines; Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Chemokine CCL2; Chitinase-3-Like Protein 1; Diffusion Tensor Imaging; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Lectins; Male; Microglia; Middle Aged; Peptide Fragments; tau Proteins; White Matter

Characteristics of Alzheimer's Disease Patients with Severe Executive Disorders. - Godefroy, Olivier; Bakchine, Serge; Verny, Marc; Delabrousse-Mayoux, Jean-Philippe; Roussel, Martine; Pere, Jean-Jacques (J Alzheimers Dis, 2016)
BACKGROUND: Executive dysfunctions in Alzheimer's disease (AD) have been assessed using variable batteries and/or in selected populations. OBJECTIVE: The primary objective of this observational study was to determine the prevalence and severity of executive dysfunction in AD patients using a previously validated battery. The secondary objective was to determine the characteristics including treatment outcomes of AD patients with severe executive dysfunction. METHODS: The study included AD patients with mild-to-moderate dementia aged 60 or over, consulting in various clinical settings including memory clinics and requiring the introduction of an antidementia drug. Executive dysfunction was examined using a validated, shortened executive battery. RESULTS: 381 patients were included. Executive dysfunctions were observed in 88.2% of the patients (95% CI: 84.9-91.4) and were severe (defined as ≥2/3 impaired scores) in 80.4% (95% CI: 76.9-84.8). Global hypoactivity with apathy was more frequent (p = 0.0001) than impairment in executive function tests. The 308 patients with severe executive dysfunction were older (p = 0.003) and had more severe dementia (p = 0.0001). Similarly, in the subset of 257 patients with mild dementia, individuals with severe executive dysfunction were older (p = 0.003) and had more severe dementia. Global hypoactivity was independently associated with difficulties in IADL and a higher caregiver burden (p = 0.0001 for both). The severity of executive dysfunction did not significantly influence the patients' outcomes at 6 months. CONCLUSIONS: Executive dysfunction is a very common disorder in a representative population of patients with mild-to-moderate AD. It was independently correlated with impaired autonomy and increased caregiver burden but did not significantly influence treatment outcomes.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Caregivers; Cost of Illness; Executive Function; Female; Humans; Male; Mental Status Schedule; Neuropsychological Tests; Prevalence; Severity of Illness Index; Treatment Outcome

Characterization of Amyloid-β Deposits in Bovine Brains. - Vallino Costassa, Elena; Fiorini, Michele; Zanusso, Gianluigi; Peletto, Simone; Acutis, Pierluigi; Baioni, Elisa; Maurella, Cristiana; Tagliavini, Fabrizio; Catania, Marcella; Gallo, Marina; Faro, Monica Lo; Chieppa, Maria Novella; et al. (J Alzheimers Dis, 2016)
Amyloid-β (Aβ) deposits are seen in aged individuals of many mammalian species that possess the same aminoacid sequence as humans. This study describes Aβ deposition in 102 clinically characterized cattle brains from animals aged 0 to 20 years. Extracellular and intracellular Aβ deposition was detected with 4G8 antibody in the cortex, hippocampus, and cerebellum. X-34 staining failed to stain Aβ deposits, indicating the non β-pleated nature of these deposits. Western blot analysis and surface-enhanced laser desorption/ionization time-of-flight (SELDI-TOF) mass spectrometry revealed in Tris, Triton, and formic acid fractions the presence of different Aβ peptides, characterized mainly by C-terminally truncated forms. Exploration of the genetic variability of APOE, PSEN1, and PSEN2 genes involved in Alzheimer's disease pathogenesis revealed several previously unreported polymorphisms. This study demonstrates certain similarities between Aβ deposition patterns exhibited in cattle brains and those in the human brain in early stages of aging. Furthermore, the identification of the same Aβ peptides reported in humans, but unable to form aggregates, supports the hypothesis that cattle may be protected against amyloid plaque formation.
Keywords: Aging; Amyloid beta-Peptides; Animals; Apolipoproteins E; Blotting, Western; Brain; Cattle; Extracellular Space; Gene Frequency; Genotyping Techniques; Glial Fibrillary Acidic Protein; Immunohistochemistry; Intracellular Space; Neuroglia; Neurons; Polymorphism, Genetic; Presenilin-1; Presenilin-2; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization

Characterizing Aging, Mild Cognitive Impairment, and Dementia with Blood-Based Biomarkers and Neuropsychology. - Kleinschmidt, Martin; Schoenfeld, Robby; Göttlich, Claudia; Bittner, Daniel; Metzner, Jürgen Erich; Leplow, Bernd; Demuth, Hans-Ulrich (J Alzheimers Dis, 2016)
BACKGROUND: Current treatment in Alzheimer's disease (AD) is initiated at a stage where the brain already has irreversible structural deteriorations. Therefore, the concept of treatment prior to obvious cognitive deficits has become widely accepted, and simple biochemical tests to discriminate normal aging from prodromal or demented stages are now common practice. OBJECTIVE: The objective of the study was the differentiation of controls, mild cognitive impairment (MCI) and AD patients by novel blood-based assays in combination with neuropsychological tests. METHODS: In a cross-sectional study, 143 subjects aged 18 to 85 years were recruited. All participants were classified by a comprehensive neuropsychological assessment. Blood samples were analyzed for several amyloid-β (Aβ) species, pro-inflammatory markers, anti-Aβ autoantibodies, and ApoE allele status, respectively. RESULTS: Plasma Aβ1-42 was significantly decreased in MCI and AD compared to age-matched controls, whereas Aβ1-40 did not differ, but increases with age in healthy controls. The Aβ1-42 to Aβ1-40 ratio was stepwise decreased from age-matched controls via MCI to AD, and shows a clear correlation with memory scores. Reduced Aβ1-42 and Aβ1-42 to Aβ1-40 ratio have strongly correlated with carrying ApoE ɛ4 allele. Autoantibodies against pyroglutamate-modified Aβ, but only a certain subclass, were significantly decreased in AD compared to MCI and age-matched controls, whereas autoantibodies against the unmodified N-terminus of Aβ did not differ. CONCLUSION: Comprehensive sample preparation and assay standardization enable reliable usage of plasma Aβ for diagnosis of MCI and AD. Anti-pGlu-Aβ autoantibodies correlate with cognition, but not with ApoE, supporting the associated plasma Aβ analysis with additional and independent information.
Keywords: Activities of Daily Living; Adolescent; Adult; Aged; Aged, 80 and over; Aging; Amyloid beta-Peptides; Analysis of Variance; Apolipoproteins E; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Cross-Sectional Studies; Cytokines; Dementia; Female; Humans; Male; Memory Disorders; Middle Aged; Neuropsychological Tests; Young Adult

Characterizing White Matter Tract Degeneration in Syndromic Variants of Alzheimer's Disease: A Diffusion Tensor Imaging Study. - Madhavan, Ajay; Schwarz, Christopher G; Duffy, Joseph R; Strand, Edythe A; Machulda, Mary M; Drubach, Daniel A; Kantarci, Kejal; Przybelski, Scott A; Reid, Robert I; Senjem, Matthew L; Gunter, Jeffrey L; Apostolova, Liana G; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Different clinical syndromes can arise from Alzheimer's disease (AD) neuropathology, including dementia of the Alzheimer's type (DAT), logopenic primary progressive aphasia (lvPPA), and posterior cortical atrophy (PCA). OBJECTIVE: To assess similarities and differences in patterns of white matter tract degeneration across these syndromic variants of AD. METHODS: Sixty-four subjects (22 DAT, 24 lvPPA, and 18 PCA) that had diffusion tensor imaging and showed amyloid-β deposition on PET were assessed in this case-control study. A whole-brain voxel-based analysis was performed to assess differences in fractional anisotropy, mean diffusivity, axial diffusivity, and radial diffusivity across groups. RESULTS: All three groups showed overlapping diffusion abnormalities in a network of tracts, including fornix, corpus callosum, posterior thalamic radiations, superior longitudinal fasciculus, inferior longitudinal fasciculus, inferior fronto-occipital fasciculus, and uncinate fasciculus. Subtle regional differences were also observed across groups, with DAT particularly associated with degeneration of fornix and cingulum, lvPPA with left inferior fronto-occipital fasciculus and uncinate fasciculus, and PCA with posterior thalamic radiations, superior longitudinal fasciculus, posterior cingulate, and splenium of the corpus callosum. CONCLUSION: These findings show that while each AD phenotype is associated with degeneration of a specific structural network of white matter tracts, striking spatial overlap exists among the three network patterns that may be related to AD pathology.
Keywords: Aged; Alzheimer Disease; Aniline Compounds; Anisotropy; Aphasia, Primary Progressive; Case-Control Studies; Diffusion Tensor Imaging; Female; Humans; Image Processing, Computer-Assisted; Male; Middle Aged; Nerve Fibers, Myelinated; Neurodegenerative Diseases; Neuropsychological Tests; Positron-Emission Tomography; Psychiatric Status Rating Scales; Retrospective Studies; Thiazoles; White Matter

Cholesterol, 24-Hydroxycholesterol, and 27-Hydroxycholesterol as Surrogate Biomarkers in Cerebrospinal Fluid in Mild Cognitive Impairment and Alzheimer's Disease: A Meta-Analysis. - Wang, Hua-Long; Wang, Yan-Yong; Liu, Xin-Gang; Kuo, Sheng-Han; Liu, Na; Song, Qiao-Yun; Wang, Ming-Wei (J Alzheimers Dis, 2016)
Abnormal cholesterol metabolism is an established feature of Alzheimer's disease (AD). Cerebrospinal fluid (CSF) is the fluid surrounding the central nervous system, and the protein and lipid content alterations in the CSF could be biomarkers for degenerative changes in the brain. The laboratory diagnosis of AD is limited to the analysis of three biomarkers in CSF: Aβ42, total tau, and phospho-tau. The purpose of this analysis is to systematically analyze the available data describing the biomarkers of cholesterol and its metabolites in the CSF of subjects with AD. MEDLINE, EMBASE, and the Cochrane Central database were systematically queried to collect studies that have evaluated the markers of cholesterol and its metabolites in the CSF of subjects with mild cognitive impairment (MCI) or AD and age-matched controls. Analysis of the published data shows that the levels of cholesterol are increased in MCI subjects; 24-hydroxycholesterol and 27-hydroxycholesterol are elevated in AD and MCI subjects compared to controls. There is a significant dysfunction of cholesterol metabolism in the CSF of AD subjects. This analysis indicates that in addition to the available biomarkers in the CSF, such as Aβ42, total tau, and phospho-tau, 24-hydroxycholesterol, 27-hydroxycholesterol, and cholesterol appear to be sensitive biomarkers for the evaluation of MCI and AD.
Keywords: Alzheimer Disease; Cholesterol; Cognitive Dysfunction; Databases, Bibliographic; Humans; Hydroxycholesterols

Chronic Obstructive Pulmonary Disease as a Risk Factor for Cognitive Dysfunction: A Meta-Analysis of Current Studies. - Zhang, Ximeng; Cai, Xiaoying; Shi, Xiaolei; Zheng, Zhenyang; Zhang, Aiwu; Guo, Junliang; Fang, Yannan (J Alzheimers Dis, 2016)
Cognitive dysfunction has been shown to be associated with many risk factors, such as smoking, diabetes, and body mass index. Chronic obstructive pulmonary disease (COPD), a common disease within the elderly population, has also been found to be related to cognitive decline. However, whether COPD is a risk factor of cognitive dysfunction is not well established. The purpose of this meta-analysis is to investigate the role COPD plays in cognitive dysfunction. PubMed, Cochrane library and Web of Science databases were searched. Three cohort studies and eleven cross-sectional studies were found to be eligible. According to our results, COPD patients had a higher risk of cognitive dysfunction than controls (OR [odds ratio]: 1.72; 95% CI, 1.12-2.65; p = 0.01). The exacerbation of COPD was strongly correlated with cognitive decline. COPD patients performed worse than controls on the Mini- Mental State Examination test, but the results were not statistically significant (OR: -0.79; 95% CI, [-1.78, 0.19]; p = 0.11). Thus, more attention should be given to the occurrence of cognitive decline in COPD patients. The prevention and control of COPD exacerbation are critical.
Keywords: Cognitive Dysfunction; Humans; Pulmonary Disease, Chronic Obstructive; Risk Factors

Chronic Sleep Deprivation Exacerbates Learning-Memory Disability and Alzheimer's Disease-Like Pathologies in AβPP(swe)/PS1(ΔE9) Mice. - Qiu, Hongyan; Zhong, Rujia; Liu, Hui; Zhang, Feng; Li, Song; Le, Weidong (J Alzheimers Dis, 2016)
Recently, there is an increasing concern over the association between sleep disorders and Alzheimer's disease (AD). Clinical observations have reported that chronic sleep deprivation (SD) may serve as a risk factor for AD. However, the pathological evidence for this assumption is still lacking. In the present study, we examined the potential impacts of chronic SD on learning-memory and AD-related pathologies in AβPP(swe)/PS1(ΔE9) transgenic (TG) mice and their wild-type (WT) littermates. Results indicated that mice (both TG and WT) exposed to 2-month SD showed an altered amyloid-β protein precursor processing, an elevated level of phosphorylated tau protein, and impaired cognitive performance as compared to non-sleep deprivation (NSD) controls. Moreover, the SD-treated TG mice exhibited more amyloid-β(1-42) production and developed more senile plaques in the cortex and hippocampus than NSD-treated TG mice. In addition, SD caused a striking neuronal mitochondrial damage, caspase cascade activation, and neuronal apoptosis in the hippocampus of both TG and WT mice. More importantly, all these behavioral, neuropathological, and biochemical changes induced by chronic SD were long lasting and were irreversible during a 3-month normal housing condition. Collectively, these results indicate that chronic SD impairs learning and memory, exacerbates AD pathologies, and aggravates the mitochondria-mediated neuronal apoptosis in a long-lasting manner. Our findings provide important experimental evidence to prove that chronic SD is a risk factor for AD.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Apoptosis; Brain; Cognition Disorders; Disease Models, Animal; Humans; In Situ Nick-End Labeling; Learning Disorders; Mice; Mice, Transgenic; Mitochondrial Diseases; Mutation; Phosphorylation; Plaque, Amyloid; Presenilin-1; Reversal Learning; Sleep Deprivation; tau Proteins

Circadian Disruption Reveals a Correlation of an Oxidative GSH/GSSG Redox Shift with Learning and Impaired Memory in an Alzheimer's Disease Mouse Model. - LeVault, Kelsey R; Tischkau, Shelley A; Brewer, Gregory J (J Alzheimers Dis, 2016)
It is unclear whether pre-symptomatic Alzheimer's disease (AD) causes circadian disruption or whether circadian disruption accelerates AD pathogenesis. In order to examine the sensitivity of learning and memory to circadian disruption, we altered normal lighting phases by an 8 h shortening of the dark period every 3 days (jet lag) in the APPSwDI NOS2-/- model of AD (AD-Tg) at a young age (4-5 months), when memory is not yet affected compared to non-transgenic (non-Tg) mice. Analysis of activity in 12-12 h lighting or constant darkness showed only minor differences between AD-Tg and non-Tg mice. Jet lag greatly reduced activity in both genotypes during the normal dark time. Learning on the Morris water maze was significantly impaired only in the AD-Tg mice exposed to jet lag. However, memory 3 days after training was impaired in both genotypes. Jet lag caused a decrease of glutathione (GSH) levels that tended to be more pronounced in AD-Tg than in non-Tg brains and an associated increase in NADH levels in both genotypes. Lower brain GSH levels after jet lag correlated with poor performance on the maze. These data indicate that the combination of the environmental stress of circadian disruption together with latent stress of the mutant amyloid and NOS2 knockout contributes to cognitive deficits that correlate with lower GSH levels.
Keywords: Age Factors; Alzheimer Disease; Amyloid beta-Protein Precursor; Analysis of Variance; Animals; Brain; Chromatography, High Pressure Liquid; Chronobiology Disorders; Disease Models, Animal; Gene Expression Regulation; Glutathione; Glutathione Disulfide; Humans; Memory Disorders; Mice; Mice, Transgenic; Mutation; NADP; Nitric Oxide Synthase Type II; Oxidation-Reduction

Classification of Neuropsychiatric Symptoms Requiring Antipsychotic Treatment in Patients with Alzheimer's Disease: Analysis of the CATIE-AD Study. - Nagata, Tomoyuki; Shinagawa, Shunichiro; Nakajima, Shinichiro; Plitman, Eric; Mihashi, Yukiko; Hayashi, Shogo; Mimura, Masaru; Nakayama, Kazuhiko (J Alzheimers Dis, 2016)
BACKGROUND: The Neuropsychiatric Inventory (NPI) comprises 12 items, which were conventionally determined by psychopathological symptoms of patients with dementia. The clinical rating scales with structured questionnaires have been useful to evaluate neuropsychiatric symptoms (NPSs) of patients with dementia over the past twenty year. OBJECTIVE: The aim of this study was to classify the conventional NPSs in patients with Alzheimer's disease (AD) requiring antipsychotic treatment for their NPSs into distinct clusters to simplify assessment of these numerous symptoms. METHODS: Twelve items scores (product of severity and frequency of each symptom) in the NPI taken from the baseline visit were classified into subgroups by principle component analysis using data from 421 outpatients with AD enrolled in the Clinical Antipsychotic Trials of Intervention Effectiveness-Alzheimer's Disease (CATIE-AD) Phase 1. Chi square tests were conducted to examine the co-occurrence of the subgroups. RESULTS: We found four distinct clusters: aggressiveness (agitation and irritabilities), apathy and eating problems (apathy and appetite/eating disturbance), psychosis (delusions and hallucinations), and emotion and disinhibition (depression, euphoria, and disinhibition). Anxiety, aberrant motor behavior, and sleep disturbance were not included by these clusters. Apathy and eating problems, and emotion and disinhibition co-occurred (p = 0.002), whereas aggressiveness and psychosis occurred independent of the other clusters. CONCLUSIONS: Four distinct category clusters were identified from NPSs in patients with AD requiring antipsychotic treatment. Future studies should investigate psychosocial backgrounds or risk factors of each distinct cluster, in addition to their longitudinal course over treatment intervention.
Keywords: Aged; Aged, 80 and over; Aggression; Alzheimer Disease; Antipsychotic Agents; Apathy; Cluster Analysis; Female; Humans; Male; Psychiatric Status Rating Scales; Psychomotor Agitation; Psychotic Disorders; Retrospective Studies; Severity of Illness Index

Clearing Amyloid-β through PPARγ/ApoE Activation by Genistein is a Treatment of Experimental Alzheimer's Disease. - Bonet-Costa, Vicent; Herranz-Pérez, Vicente; Blanco-Gandía, MariCarmen; Mas-Bargues, Cristina; Inglés, Marta; Garcia-Tarraga, Patricia; Rodriguez-Arias, Marta; Miñarro, Jose; Borras, Consuelo; Garcia-Verdugo, Jose Manuel; Viña, Jose (J Alzheimers Dis, 2016)
Amyloid-β (Aβ) clearance from brain, which is decreased in Alzheimer's disease, is facilitated by apolipoprotein E (ApoE). ApoE is upregulated by activation of the retinoid X receptor moiety of the RXR/PPARγ dimeric receptor. Genistein, a non-toxic, well-tested, and inexpensive drug activates the other moiety of the receptor PPARγ. Treatment of an Alzheimer's disease mouse model with genistein results in a remarkable and rapid improvement in various parameters of cognition, such as hippocampal learning, recognition memory, implicit memory, and odor discrimination. This is associated with a lowering of Aβ levels in brain, in the number and the area of amyloid plaques (confirmed in vivo by positron emission tomography) as well as in microglial reactivity. Finally, incubation of primary astrocytes with genistein results in a PPARγ-mediated increased release of ApoE. Our results strongly suggest that controlled clinical trials should be performed to test the effect of genistein as treatment of human Alzheimer's disease.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Apolipoproteins E; Astrocytes; Avoidance Learning; Brain; Cells, Cultured; Disease Models, Animal; Female; Genistein; Habituation, Psychophysiologic; Maze Learning; Mice, Inbred C57BL; Mice, Transgenic; Neuroprotective Agents; Nootropic Agents; Olfactory Perception; Plaque, Amyloid; PPAR gamma; Recognition (Psychology); Tetrahydronaphthalenes

Clinical and Demographic Factors Associated with the Cognitive and Emotional Efficacy of Regular Musical Activities in Dementia. - Särkämö, Teppo; Laitinen, Sari; Numminen, Ava; Kurki, Merja; Johnson, Julene K; Rantanen, Pekka (J Alzheimers Dis, 2016)
Recent evidence suggests that music-based interventions can be beneficial in maintaining cognitive, emotional, and social functioning in persons with dementia (PWDs). Our aim was to determine how clinical, demographic, and musical background factors influence the cognitive and emotional efficacy of caregiver-implemented musical activities in PWDs. In a randomized controlled trial, 89 PWD-caregiver dyads received a 10-week music coaching intervention involving either singing or music listening or standard care. Extensive neuropsychological testing and mood and quality of life (QoL) measures were performed before and after the intervention (n = 84) and six months later (n = 74). The potential effects of six key background variables (dementia etiology and severity, age, care situation, singing/instrument playing background) on the outcome of the intervention were assessed. Singing was beneficial especially in improving working memory in PWDs with mild dementia and in maintaining executive function and orientation in younger PWDs. Music listening was beneficial in supporting general cognition, working memory, and QoL especially in PWDs with moderate dementia not caused by Alzheimer's disease (AD) who were in institutional care. Both music interventions alleviated depression especially in PWDs with mild dementia and AD. The musical background of the PWD did not influence the efficacy of the music interventions. Our findings suggest that clinical and demographic factors can influence the cognitive and emotional efficacy of caregiver-implemented musical activities and are, therefore, recommended to take into account when applying and developing the intervention to achieve the greatest benefit.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Caregivers; Case-Control Studies; Cognition Disorders; Dementia; Executive Function; Female; Follow-Up Studies; Humans; Male; Memory, Short-Term; Middle Aged; Mood Disorders; Music Therapy; Neuropsychological Tests; Orientation; Outcome Assessment (Health Care); Psychiatric Status Rating Scales; Quality of Life

Clinical Dementia Rating Scale Detects White Matter Changes in Older Adults at Risk for Alzheimer's Disease. - Chang, Yu-Ling; Yen, Yu-Shiuan; Chen, Ta-Fu; Yan, Sui-Hing; Tseng, Wen-Yih Isaac (J Alzheimers Dis, 2016)
This study investigated the putative changes in regional gray matter and cingulum bundle segments in mild cognitive impairment (MCI) by using two diagnostic criteria. Participants comprised 50 older adults with MCI and 22 healthy older controls (HC). The older adults with MCI were further divided into two groups defined by a global Clinical Dementia Rating (CDR) score of 0.5 and with (the CDR/NPT MCI group) or without (the CDR MCI group) objective cognitive impairments determined using neuropsychological tests (NPTs). Comparable regional gray matter integrity was observed among the three groups. However, the integrity of the right inferior segment of the cingulum bundle in the two MCI groups was more reduced than that in the HC group, and the CDR/NPT MCI group exhibited additional disruption in the left inferior cingulum bundle. The results also demonstrated that neuropsychological measures have greater predictive value for changes in white matter beyond the contribution of an informant-based instrument alone. Overall, the findings confirm the utility of informant-based assessment in detecting microstructural brain changes in high-risk older adults, even before objective cognitive impairment is evident. The findings also suggest that combining the neuropsychological measures with the informant-based assessment provided the greatest predictive value in assessing white matter disruption. The essential role of the white matter measurement as a biomarker for detecting individuals at a high risk of developing dementia was highlighted.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Cognition Disorders; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Memory; Middle Aged; Neuropsychological Tests; Risk Factors; White Matter

The Cognitive Change Index as a Measure of Self and Informant Perception of Cognitive Decline: Relation to Neuropsychological Tests. - Rattanabannakit, Chatchawan; Risacher, Shannon L; Gao, Sujuan; Lane, Kathleen A; Brown, Steven A; McDonald, Brenna C; Unverzagt, Frederick W; Apostolova, Liana G; Saykin, Andrew J; Farlow, Martin R (J Alzheimers Dis, 2016)
BACKGROUND: The perception of cognitive decline by individuals and those who know them well ("informants") has been inconsistently associated with objective cognitive performance, but strongly associated with depressive symptoms. OBJECTIVE: We investigated associations of self-report, informant-report, and discrepancy between self- and informant-report of cognitive decline obtained from the Cognitive Change Index (CCI) with cognitive test performance and self-reported depressive symptoms. METHODS: 267 participants with normal cognition, mild cognitive impairment (MCI), or mild dementia were included from a cohort study and memory clinic. Association of test performance and self-rated depression (Geriatric Depression Scale, GDS) with CCI scores obtained from subjects (CCI-S), their informants (CCI-I), and discrepancy scores between subjects and informants (CCI-D; CCI-S minus CCI-I) were analyzed using correlation and analysis of covariance (ANCOVA) models. RESULTS: CCI-S and CCI-I scores showed high internal consistency (Cronbach alpha 0.96 and 0.98, respectively). Higher scores on CCI-S and CCI-I, and lower scores on the CCI-D, were associated with lower performance on various cognitive tests in both univariate and in ANCOVA models adjusted for age, gender, and education. Adjustment for GDS slightly weakened the relationships between CCI and test performance but most remained significant. CONCLUSION: Self- and informant-report of cognitive decline, as measured by the CCI, show moderately strong relationships with objective test performance independent of age, gender, education, and depressive symptoms. The CCI appears to be a valid cross-sectional measure of self and informant perception of cognitive decline across the continuum of functioning. Studies are needed to address the relationship of CCI scores to longitudinal outcome.
Keywords: Adult; Aged; Aged, 80 and over; Analysis of Variance; Cognitive Dysfunction; Cross-Sectional Studies; Dementia; Female; Humans; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Perception; Self Report

Cognitive Impairment after Mild Stroke: Development and Validation of the SIGNAL2 Risk Score. - Kandiah, Nagaendran; Chander, Russell Jude; Lin, Xuling; Ng, Aloysius; Poh, Yen Yeong; Cheong, Chin Yee; Cenina, Alvin Rae; Assam, Pryseley Nkouibert (J Alzheimers Dis, 2016)
BACKGROUND: Post stroke cognitive impairment (PSCI), an important complication of strokes, has numerous risk factors. A scale adequately classifying risk of cognitive impairment 3-6 months after mild stroke will be useful for clinicians. OBJECTIVE: To develop a risk score based on clinical and neuroimaging variables that will be useful in identifying mild ischemic stroke patients at high risk for PSCI. METHODS: The risk score development cohort comprised of a retrospective dataset of 209 mild stroke patients with MRI confirmed infarcts, without pre-stroke cognitive impairment, and evaluated within 6 months post-stroke for PSCI. Logistic regression identified factors predictive of PSCI and a risk score was developed based on regression coefficients. The risk score was checked for stability using 10-fold cross-validation and validated in an independent prospective cohort of 185 ischemic mild stroke patients. RESULTS: Within 6 months post-stroke, 37.32% developed PSCI in the retrospective dataset. A 15-point risk score based on age, education, acute cortical infarcts, white matter hyperintensity, chronic lacunes, global cortical atrophy, and intracranial large vessel stenosis was highly predictive of PSCI with an AUC of 0.829. 10.11% with low scores, 52.69% with moderate scores, and 74.07% with high scores developed PSCI. In the prospective validation cohort, the model had an AUC of 0.776, and exhibited similar accuracy and stability statistics at both 6 and 12 months. CONCLUSION: The seven item risk score adequately identified mild stroke patients who are at an increased risk of developing PSCI.
Keywords: Aged; Aging; Area Under Curve; Brain; Brain Ischemia; Cognition Disorders; Constriction, Pathologic; Educational Status; Female; Follow-Up Studies; Humans; Logistic Models; Male; Middle Aged; Prospective Studies; Retrospective Studies; Risk; Severity of Illness Index; Stroke; White Matter

Cognitive Profile and its Association with Neuroimaging Markers of Non-Demented Cerebral Amyloid Angiopathy Patients in a Stroke Unit. - Xiong, Li; Davidsdottir, Sigurros; Reijmer, Yael D; Shoamanesh, Ashkan; Roongpiboonsopit, Duangnapa; Thanprasertsuk, Sekh; Martinez-Ramirez, Sergi; Charidimou, Andreas; Ayres, Alison M; Fotiadis, Panagiotis; Gurol, Edip; Blacker, Deborah L; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Cerebral amyloid angiopathy (CAA) is increasingly recognized as a cause of cognitive impairment in the elderly, but the cognitive profile in patients with the disease has not been well characterized. OBJECTIVE: To characterize the neuropsychological profile of CAA patients without dementia and to determine the association between cognitive performance in different domains and neuroimaging lesions characteristic of CAA. METHODS: Fifty-eight non-demented CAA patients were compared to 138 cognitively normal subjects using a standard neuropsychological test battery. Total brain volume (TBV), white matter hyperintensities, number of lobar cerebral microbleeds, hippocampal volume, and cortical superficial siderosis in all CAA patients were assessed. The association between these neuroimaging markers and neuropsychological performance in different cognitive domains in the CAA group were analyzed. RESULTS: Patients with CAA had significantly worse performance on all individual neuropsychological domains tested, when compared to the cognitive normal group. The cognitive decline of CAA patients was most noticeable in tests for processing speed with a Z score of -1.92±1.56 (mean±SD), then followed by executive function (-0.93±1.01), episodic memory (-0.87±1.29), semantic fluency (-0.73±1.06), and attention (-0.42±0.98). TBV of the CAA patients was correlated with processing speed (β= 0.335, p = 0.03) and executive function (β= 0.394, p = 0.01). CONCLUSIONS: Non-demented patients with CAA had cognitive deficits in multiple areas. Lower TBV was related to slower processing speed and worse executive function.
Keywords: Aged; Atrophy; Brain; Cerebral Amyloid Angiopathy; Cognition; Cognition Disorders; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Stroke

Cognitive Stimulation Modulates Platelet Total Phospholipases A2 Activity in Subjects with Mild Cognitive Impairment. - Balietti, Marta; Giuli, Cinzia; Fattoretti, Patrizia; Fabbietti, Paolo; Postacchini, Demetrio; Conti, Fiorenzo (J Alzheimers Dis, 2016)
We evaluated the effect of cognitive stimulation (CS) on platelet total phospholipases A2 activity (tPLA2A) in patients with mild cognitive impairment (MCI_P). At baseline, tPLA2A negatively correlated with Mini-Mental State Examination score (MMSE_s): patients with MMSE_s <26 (Subgroup 1) had significantly higher activity than those with MMSE_s ≥26 (Subgroup 2), who had values similar to the healthy elderly. Regarding CS effect, Subgroup 1 had a significant tPLA2A reduction, whereas Subgroup 2 did not significantly changes after training. Our results showed for the first time that tPLA2A correlates with the cognitive conditions of MCI_P, and that CS acts selectively on subjects with a dysregulated tPLA2A.
Keywords: Blood Platelets; Cognition; Cognitive Dysfunction; Cognitive Therapy; Cohort Studies; Humans; Mental Status Schedule; Neuropsychological Tests; Phospholipases A2; Treatment Outcome

Cohort Effects in the Prevalence and Survival of People with Dementia in a Rural Area in Northern Sweden. - Wimo, Anders; Sjölund, Britt-Marie; Sköldunger, Anders; Qiu, Chengxuan; Klarin, Inga; Nordberg, Gunilla; von Strauss, Eva (J Alzheimers Dis, 2016)
BACKGROUND: Recent studies suggest that trends in cardiovascular risk may result in a decrease in age-specific prevalence of dementia. Studies in rural areas are rare. OBJECTIVES: To study cohort effects in dementia prevalence and survival of people with dementia in a Swedish rural area. METHODS: Participants were from the 1995-1998 Nordanstig Project (NP) (n = 303) and the 2001-2003 Swedish National study on Aging and Care in Nordanstig (SNAC-N) (n = 384). Overall 6-year dementia prevalence and mortality in NP and SNAC-N were compared for people 78 years and older. Logistic regression analyses were used to calculate odds ratios (ORs) and 95% confidence intervals (CIs) for dementia occurrence using the NP study population as the reference group. Cox regression models were used to analyze time to death. RESULTS: The crude prevalence of dementia was 21.8% in NP and 17.4% in SNAC-N. When the NP cohort was used as the reference group, the age- and gender-adjusted OR of dementia was 0.71 (95% CI 0.48-1.04) in SNAC-N; the OR was 0.47 (0.24-0.90) for men and 0.88 (0.54-1.44) for women. In the extended model, the OR of dementia was significantly lower in SNAC-N than in the NP cohort as a whole (0.63; 0.39-0.99) and in men (0.34; 0.15-0.79), but not in women (0.81; 0.46-1.44). The Cox regression models indicated that the hazard ratio of dying was lower in the SNAC-N than NP population. CONCLUSIONS: Trends toward a lower prevalence of dementia in high-income countries seem to be evident in this Swedish rural area, at least in men.
Keywords: Aged; Aged, 80 and over; Aging; Cohort Effect; Dementia; Female; Humans; Male; Prevalence; Risk Factors; Rural Population; Sex Factors; Survival Rate; Sweden

Comparing the Effects of Multisensory Stimulation and Individualized Music Sessions on Elderly People with Severe Dementia: A Randomized Controlled Trial. - Sánchez, Alba; Maseda, Ana; Marante-Moar, M Pilar; de Labra, Carmen; Lorenzo-López, Laura; Millán-Calenti, José Carlos (J Alzheimers Dis, 2016)
The objective of this study was to compare the effects of a multisensory stimulation environment (MSSE) and individualized music sessions on agitation, emotional and cognitive status, and dementia severity in a sample of institutionalized patients with severe dementia. Twenty-two participants with a diagnosis of severe or very severe dementia were randomly assigned to two groups: MSSE and individualized music sessions. Both groups participated in two 30-min weekly sessions over 16 weeks. Outcomes were agitation (Cohen-Mansfield Agitation Inventory, CMAI), mood (Cornell Scale for Depression in Dementia, CSDD), anxiety (Rating Anxiety in Dementia, RAID), cognitive function (Severe Mini-Mental State Examination, SMMSE), and the overall severity of dementia (Bedford Alzheimer Nursing Severity Scale, BANS-S). They were assessed at baseline (pre-trial), in the middle (mid-trial), at the end of the intervention (post-trial), and 8 weeks after the intervention (follow-up). Patients in the MSSE group showed significant improvement in their RAID and BANS-S scores compared with the individualized music group post- versus pre-trial. With regard to agitation, there was improvement during the intervention in both the MSSE and individualized music groups in the CMAI total score after 16 weeks of intervention, with no significant differences between the groups. The results suggest that MSSE could have better effects on anxiety symptoms and dementia severity in comparison with individualized music sessions in elderly patients with severe dementia.
Keywords: Affect; Aged; Aged, 80 and over; Anxiety; Cognition; Dementia; Environment; Female; Follow-Up Studies; Humans; Male; Mental Status Schedule; Music Therapy; Precision Medicine; Sensory Art Therapies; Severity of Illness Index; Treatment Outcome

Comparison of Different Matrices as Potential Quality Control Samples for Neurochemical Dementia Diagnostics. - Lelental, Natalia; Brandner, Sebastian; Kofanova, Olga; Blennow, Kaj; Zetterberg, Henrik; Andreasson, Ulf; Engelborghs, Sebastiaan; Mroczko, Barbara; Gabryelewicz, Tomasz; Teunissen, Charlotte; Mollenhauer, Brit; Parnetti, Lucilla; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Assay-vendor independent quality control (QC) samples for neurochemical dementia diagnostics (NDD) biomarkers are so far commercially unavailable. This requires that NDD laboratories prepare their own QC samples, for example by pooling leftover cerebrospinal fluid (CSF) samples. OBJECTIVE: To prepare and test alternative matrices for QC samples that could facilitate intra- and inter-laboratory QC of the NDD biomarkers. METHODS: Three matrices were validated in this study: (A) human pooled CSF, (B) Aβ peptides spiked into human prediluted plasma, and (C) Aβ peptides spiked into solution of bovine serum albumin in phosphate-buffered saline. All matrices were tested also after supplementation with an antibacterial agent (sodium azide). We analyzed short- and long-term stability of the biomarkers with ELISA and chemiluminescence (Fujirebio Europe, MSD, IBL International), and performed an inter-laboratory variability study. RESULTS: NDD biomarkers turned out to be stable in almost all samples stored at the tested conditions for up to 14 days as well as in samples stored deep-frozen (at - 80°C) for up to one year. Sodium azide did not influence biomarker stability. Inter-center variability of the samples sent at room temperature (pooled CSF, freeze-dried CSF, and four artificial matrices) was comparable to the results obtained on deep-frozen samples in other large-scale projects. CONCLUSION: Our results suggest that it is possible to replace self-made, CSF-based QC samples with large-scale volumes of QC materials prepared with artificial peptides and matrices. This would greatly facilitate intra- and inter-laboratory QC schedules for NDD measurements.
Keywords: Amyloid beta-Peptides; Animals; Anti-Bacterial Agents; Biomarkers; Cattle; Clinical Chemistry Tests; Dementia; Humans; Peptide Fragments; Quality Control; Reference Standards; Serum Albumin, Bovine; Sodium Azide; tau Proteins; Time Factors; Tissue Preservation

Complementary and Alternative Medicine in the Context of Earlier Diagnoses of Alzheimer's Disease: Opening the Conversation to Prepare Ethical Responses. - Racine, Eric; Forlini, Cynthia; Aspler, John; Chandler, Jennifer (J Alzheimers Dis, 2016)
Preclinical Alzheimer's disease (AD), a newly proposed, actively researched, and hotly debated research-only diagnostic category, raises the prospect of an ethical dilemma: whether, and possibly how, to treat a disorder with no target symptoms. This proposed category rests on the detection of a number of biomarkers thought to provide evidence of AD pathophysiology years before any behavioral symptoms manifest. Faced with limited treatment options, patients and their relatives may come to consider complementary and alternative medicine (CAM) a viable option, albeit one with minimal supporting evidence. Accordingly, the hopes and needs of some preclinical patients and their relatives could further fuel market-oriented entrepreneurship for CAM. In this ethics review, we provide background and reflect on some ethical questions related to the roles of key stakeholders arising from the potential for CAM use in the context of a possible preclinical AD diagnosis.
Keywords: Alzheimer Disease; Complementary Therapies; Early Diagnosis; Ethical Analysis; Humans

Concanavalin agglutinin levels are decreased in peripheral blood of Alzheimer's disease patients. - Sun, Xuying; Ma, Ronghong; Yao, Xiuqing; Shang, Xiaoling; Wang, Qun; Wang, Jian-Zhi; Liu, Gongping (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) seriously threatens patients' lives and causes severe burden to the families. Early prevention and treatment can alleviate the development of the disease; therefore it is important to find new effective and non-traumatic biomarkers for early diagnosis. In this study, peripheral blood samples were collected from 24 AD patients and the same number of age- and gender-matched control subjects. Lectin reactive glycosylation levels including beta-D-galactosyl ricinus communis agglutinin 120 (RCA), peanut agglutinin (PNA), concanavalin agglutinin (Con A), alpha-L-fucosyl ulex europeus agglutinin (UEA), dolichos biflorus agglutinin (DBA), and galanthus nivalis (GNL), in the red blood cells of peripheral blood were examined by western blotting. We found that lectin levels were altered with aging and gender; some lectin levels were different between AD patients and the control subjects. Only Con A levels were significantly decreased in AD patients compared to age-matched control subjects. These results suggest that Con A levels in peripheral blood may be a potent diagnostic marker for AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Case-Control Studies; Concanavalin A; Female; Humans; Lectins; Male; Plant Lectins

Cost Related to Dementia in the Young and the Impact of Etiological Subtype on Cost. - Kandiah, Nagaendran; Wang, Vivian; Lin, Xuling; Nyu, Mei Mei; Lim, Linda; Ng, Adeline; Hameed, Shahul; Wee, Hwee Lin (J Alzheimers Dis, 2016)
BACKGROUND: Young onset dementia (YOD) presents in individuals who are economically productive and socially active. While the cost related to dementia in the elderly has been widely studied, the cost related to YOD is largely unknown. OBJECTIVE: To study the economic burden of community dwelling YOD in relation to late onset dementia (LOD) and cost of YOD based on etiology. METHODS: In this prospective cross-sectional study of 255 patients attending a tertiary neurology center, data on economic burden, clinical features, and caregiver burden were collected using structured financial questionnaire, standard cognitive and neuropsychiatric measures, and Zarit caregiver burden scale. Cost components were grouped into those relating to direct medical costs, direct non-medical costs, and those related to indirect costs. Cost was also categorized based on etiology of YOD. RESULTS: The mean age at symptom onset in the YOD and LOD cohort was 57.0 (SD 5.1) and 75.0 (SD 5.9) years, respectively. The median annual cost for patients with YOD was almost twice that of LOD (USD 15,815 versus USD 8,396). Indirect cost contributed heavily to cost related to YOD. Even when grouped by dementia etiology, YOD patients with Alzheimer's disease, frontotemporal dementia (FTD), and vascular dementia had higher cost compared to their elderly counterparts. Young onset FTD had the highest cost. 43.2% of YOD reported loss of employment due to dementia, which was significantly higher than that in LOD (2.4%). CONCLUSION: Patients with YOD have a high economic burden. Young patients with FTD have the highest cost followed by vascular dementia and Alzheimer's disease.
Keywords: Age of Onset; Aged; Cohort Studies; Costs and Cost Analysis; Cross-Sectional Studies; Dementia; Female; Humans; Independent Living; Male; Mental Disorders; Middle Aged; Perceptual Disorders; Prospective Studies; Psychiatric Status Rating Scales; Severity of Illness Index; Surveys and Questionnaires; Young Adult

Cycloheximide Treatment Causes a ZVAD-Sensitive Protease-Dependent Cleavage of Human Tau in Drosophila Cells. - Geng, Junhua; Xia, Lu; Li, Wanjie; Zhao, Changqi; Dou, Fei (J Alzheimers Dis, 2016)
Neurofibrillary tangles are the main pathological feature of Alzheimer's disease. Insoluble tau protein is the major component of neurofibrillary tangles. Defects in the tau protein degradation pathway in neurons can lead to the accumulation of tau and its subsequent aggregation. Currently, contradictory results on the tau degradation pathway have been reported by different groups. This discrepancy is most likely due to different cell lines and methods used in those studies. In this study, we found that cycloheximide treatment induced mild activation of a ZVAD-sensitive protease in Drosophila Kc cells, resulting in cleavage of tau at its C-terminus; this cleavage could generate misleading tau protein degradation pattern results depending on the antibodies used in the assay. Because cycloheximide is a broadly used chemical reagent for the study of protein degradation, the unexpected artificial effect we observed here indicates that cycloheximide is not suitable for the study of tau degradation. Other methods, such as inducible expression systems and pulse-chase assays, may be more appropriate for studying tau degradation under physiological conditions.
Keywords: Animals; Apoptosis; Caspase 3; Cell Line; Cycloheximide; Drosophila; Drosophila Proteins; Drug Evaluation, Preclinical; Humans; Oligopeptides; Peptide Hydrolases; Protease Inhibitors; Protein Synthesis Inhibitors; tau Proteins; Time

The Cytome Assay as a Tool to Investigate the Possible Association Between Exposure to Extremely Low Frequency Magnetic Fields and an Increased Risk for Alzheimer's Disease. - Maes, Annemarie; Anthonissen, Roel; Wambacq, Sheleen; Simons, Koen; Verschaeve, Luc (J Alzheimers Dis, 2016)
Exposure to extremely low frequency magnetic fields (ELF-MF) has been identified as one of the potential environmental risk factors for Alzheimer's disease (AD). However, this is far from being established. So far there is no experimental evidence supporting this alleged association. We have performed an in vitro cytogenetic laboratory investigation to explore the plausibility of such association. Our investigation was based on possible similarities found in cells from AD patients and in cells exposed to ELF-MF. We especially found that 50  Hz ELF-MF increase the frequency of cells with (large) micronuclei and nuclear buds indicating that fields above 50 μT may induce chromosome instabilities as those found in AD patients. It should be stressed yet that results from the few published experimental studies on ELF-MF and AD are rather reassuring. Thus, our findings certainly do not prove anything. They only suggest that further investigations might be necessary.
Keywords: Apoptosis; Carcinoma; Cell Line, Tumor; Chromosome Aberrations; Cytokinesis; Dose-Response Relationship, Radiation; Humans; Magnetic Fields; Risk Factors

Decreased Levels of VAMP2 and Monomeric Alpha-Synuclein Correlate with Duration of Dementia. - Vallortigara, Julie; Whitfield, David; Quelch, William; Alghamdi, Amani; Howlett, David; Hortobágyi, Tibor; Johnson, Mary; Attems, Johannes; O'Brien, John T; Thomas, Alan; Ballard, Clive G; Aarsland, Dag; et al. (J Alzheimers Dis, 2016)
Alpha-synuclein (α-syn) aggregations are the key pathological hallmark of dementia with Lewy bodies (DLB) and Parkinson's disease dementia (PDD), but are also frequently present in Alzheimer's disease (AD). Much remains unknown about the role of α-syn in the synapse and the wider role of synaptic dysfunction in these dementias. Changes in concentrations of key 'SNAP (Soluble N-ethylmaleimide Sensitive Factor Attachment Protein) Receptor' (SNARE) proteins as a consequence of alterations in the aggregation state of α-syn may contribute to synaptic dysfunction in patients with DLB, PDD, and AD and result in impaired cognition. We have studied a large cohort (n = 130) of autopsy confirmed DLB, PDD, AD, and control brains. Using semi-quantitative western blotting, we have demonstrated significant changes across the diagnostic groups of DLB, PDD, and AD in the SNARE and vesicle proteins syntaxin, Munc18, VAMP2, and monomeric α-syn in the prefrontal cortex, with a significant reduction of Munc18 in AD patients (p <  0.001). This correlated to the final MMSE score before death (p = 0.016). We also identified a significant negative correlation between the duration of dementia and the levels of the binding partners VAMP2 (p = 0.0004) and monomeric α-syn (p = 0.0002). Our findings may indicate that an upregulation of SNARE complex related proteins occurs in the early stages of disease as an attempt at compensating for failing synapses, prior to widespread deposition of pathological α-syn.
Keywords: Aged; Aged, 80 and over; alpha-Synuclein; Amyloid beta-Peptides; Analysis of Variance; Cognition Disorders; Dementia; Female; Humans; Male; Mental Status Schedule; Neuropsychological Tests; Regression Analysis; Synaptophysin; tau Proteins; Vesicle-Associated Membrane Protein 2

Depressive Symptoms and Small Hippocampal Volume Accelerate the Progression to Dementia from Mild Cognitive Impairment. - Chung, Jun Ku; Plitman, Eric; Nakajima, Shinichiro; Chakravarty, M Mallar; Caravaggio, Fernando; Takeuchi, Hiroyoshi; Gerretsen, Philip; Iwata, Yusuke; Patel, Raihaan; Mulsant, Benoit H; Graff-Guerrero, Ariel (J Alzheimers Dis, 2016)
Previous studies have highlighted that decreased hippocampal volume, an early neural correlate of dementia, is commonly observed in patients with mild cognitive impairment (MCI). However, it is unclear whether neurodegenerative and resultant clinical trajectories are accelerated in MCI patients with concomitant depressive symptoms, leading to a faster conversion to dementia stages than those who are not depressed. No longitudinal study has investigated whether depressed amnestic MCI (DEP+aMCI) patients show an earlier onset of progression to dementia than non-depressed amnestic MCI (DEP-aMCI) patients and whether progressive hippocampal volume reductions are related in the conversion process. Using data from Alzheimer's Disease Neuroimaging Initiative, we examined 2-year follow-up data from 38 DEP+aMCI patients and 38 matched DEP-aMCI patients and compared their ages of conversion from aMCI to AD and trajectories of progressive hippocampal volume changes. DEP+ and DEP- patients were defined as having baseline Geriatric Depression Scale scores of 5 or above and 0, respectively. DEP+ converters showed earlier ages of conversion to dementia (p = 0.009) and greater left hippocampal volume loss than both DEP- converters and DEP+ non-converters over the 2-year period (p = 0.003, p = 0.001, respectively). These findings could not be explained by changes in total brain volume, differences in their clinical symptoms of dementia, daily functioning, or apolipoprotein E4 genotypes. No difference in conversion rate to dementia or progressive hippocampal volume change was found between DEP+ patients and DEP-patients, which suggested depressive symptoms themselves may not lead to progression of dementia from MCI. In conclusion, there is a synergistic effect of depressive symptoms and smaller left hippocampal volume in MCI patients that accelerates conversion to dementia.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Dementia; Depression; Disease Progression; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Psychiatric Status Rating Scales

Development and Validation of the RxDx-Dementia Risk Index to Predict Dementia in Patients with Type 2 Diabetes and Hypertension. - Mehta, Hemalkumar B; Mehta, Vinay; Tsai, Chu-Lin; Chen, Hua; Aparasu, Rajender R; Johnson, Michael L (J Alzheimers Dis, 2016)
BACKGROUND: Elderly patients with type 2 diabetes mellitus and hypertension are at high risk for developing dementia. In addition to comorbid disease conditions (Dx), prescription drugs (Rx) are important risk factors for dementia. OBJECTIVE: Develop and validate the RxDx-Dementia risk index by combining diagnosis and prescription information in a single risk index to predict incident dementia, and compare its performance with diagnosis-based Charlson comorbidity score (CCS) and prescription-based chronic disease score (CDS). METHODS: Elderly patients diagnosed with type 2 diabetes mellitus and hypertension, and without prior dementia were identified from the Clinical Practice Research Datalink (2003-2012). A Cox proportional hazard model was constructed to model the time to dementia by incorporating age, gender, and 31 RxDx disease conditions as independent variables. Points were assigned to risk factors to obtain summary risk score. Discrimination and calibration of the risk index were evaluated. Different risk indices were compared against RxDx-Dementia risk index using c-statistic, net reclassification improvement (NRI) and integrated discrimination improvement (IDI). RESULTS: Of 133,176 patients with type 2 diabetes mellitus and hypertension, 3.42% patients developed dementia.The c-statistics value for RxDx-Dementia risk index was 0.806 (95% CI, 0.799-0.812). Based on the c-statistics, NRI and IDI values, the RxDx-Dementia risk index performed better compared to CCS, CDS, and their combinations. CONCLUSION: The RxDx-Dementia risk index can be a useful tool to identify hypertensive and diabetic patients who are at high risk of developing dementia. This has implications for clinical management of patients with multiple comorbid conditions as well as risk adjustment for database studies.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Dementia; Diabetes Mellitus, Type 2; Female; Humans; Hypertension; Male; Middle Aged; Predictive Value of Tests; Prescription Drugs; Proportional Hazards Models; Reproducibility of Results; Risk Assessment; Risk Factors

Development of a Standardized Approach to Disclosing Amyloid Imaging Research Results in Mild Cognitive Impairment. - Lingler, Jennifer H; Butters, Meryl A; Gentry, Amanda L; Hu, Lu; Hunsaker, Amanda E; Klunk, William E; Mattos, Meghan K; Parker, Lisa A; Roberts, J Scott; Schulz, Richard (J Alzheimers Dis, 2016)
The increased use of PET amyloid imaging in clinical research has sparked numerous concerns about whether and how to return such research test results to study participants. Chief among these is the question of how best to disclose amyloid imaging research results to individuals who have cognitive symptoms that could impede comprehension of the information conveyed. We systematically developed and evaluated informational materials for use in pre-test counseling and post-test disclosures of amyloid imaging research results in mild cognitive impairment (MCI). Using simulated sessions, persons with MCI and their family care partners (N = 10 dyads) received fictitious but realistic information regarding brain amyloid status, followed by an explanation of how results impact Alzheimer's disease risk. Satisfaction surveys, comprehension assessments, and focus group data were analyzed to evaluate the materials developed. The majority of persons with MCI and their care partners comprehended and were highly satisfied with the information presented. Focus group data reinforced findings of high satisfaction and included 6 recommendations for practice: 1) offer pre-test counseling, 2) use clear graphics, 3) review participants' own brain images during disclosures, 4) offer take-home materials, 5) call participants post-disclosure to address emerging questions, and 6) communicate seamlessly with primary care providers. Further analysis of focus group data revealed that participants understood the limitations of amyloid imaging, but nevertheless viewed the prospect of learning one's amyloid status as valuable and empowering.
Keywords: Adult; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid; Brain; Brain Chemistry; Cognitive Dysfunction; Disclosure; Family; Female; Focus Groups; Health Communication; Humans; Male; Middle Aged; Patient Satisfaction; Pilot Projects; Positron-Emission Tomography

Diagnostic Impact of Cerebrospinal Fluid Biomarker (Pre-)Analytical Variability in Alzheimer's Disease. - Niemantsverdriet, Ellis; Goossens, Joery; Struyfs, Hanne; Martin, Jean-Jacques; Goeman, Johan; De Deyn, Peter Paul; Vanderstichele, Hugo; Engelborghs, Sebastiaan (J Alzheimers Dis, 2016)
Intra- and inter-laboratory variability of cerebrospinal fluid (CSF) biomarker analyses remains an important issue. We investigated the clinical-diagnostic impact of CSF biomarker concentration shifts in mild cognitive impairment (MCI) and autopsy-confirmed Alzheimer's disease (AD) dementia patients. MCI patients (n = 85), autopsy-confirmed AD dementia patients (n = 72), and cognitively healthy controls (n = 100) were included in this prospective, longitudinal study. AD dementia patients were followed up until death, and controls were included from 1992 until 2003. In-house validated cutoff values of biomarkers were applied: Aβ1-42 <638.5 pg/mL, T-tau>296.5 pg/mL, P-tau(181P) >56.5 pg/mL. Both increments and decrements (from ± 5% to ± 40% ) were added to the true (=observed) CSF biomarker values, imitating the anticipated differences in biomarker concentrations. Within certain limits, the clinical diagnostic performance of AD CSF biomarkers remains largely unchanged and clinical diagnostic accuracy deviated less than 8.2% from the reference when concentration shifts ranging between -20% and +20% were added to one of the three CSF biomarkers in MCI and autopsy-confirmed AD patients. Notwithstanding the fact that (pre- and post-)analytical parameters can affect the clinical classification, the present exploratory study provides evidence that for a specific context of use, the impact on clinical accuracy of biomarker concentration shifts might be lower than originally expected. In conclusion, induced shifts of ±20% in only one of the three biomarkers has limited impact on the clinical accuracy of AD CSF biomarkers in MCI and autopsy-confirmed AD patients when using the IWG-2 criteria.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Autopsy; Cognitive Dysfunction; Enzyme-Linked Immunosorbent Assay; Exercise; Female; Follow-Up Studies; Humans; Male; Middle Aged; Peptide Fragments; Psychiatric Status Rating Scales; Retrospective Studies; Statistics, Nonparametric; tau Proteins

Diet and Inflammation in Alzheimer's Disease and Related Chronic Diseases: A Review. - Gardener, Samantha L; Rainey-Smith, Stephanie R; Martins, Ralph N (J Alzheimers Dis, 2016)
Inflammation is one of the pathological features of the neurodegenerative disease, Alzheimer's disease (AD). A number of additional disorders are likewise associated with a state of chronic inflammation, including obesity, cardiovascular disease, and type-2 diabetes, which are themselves risk factors for AD. Dietary components have been shown to modify the inflammatory process at several steps of the inflammatory pathway. This review aims to evaluate the published literature on the effect of consumption of pro- or anti-inflammatory dietary constituents on the severity of both AD pathology and related chronic diseases, concentrating on the dietary constituents of flavonoids, spices, and fats. Diet-based anti-inflammatory components could lead to the development of potent novel anti-inflammatory compounds for a range of diseases. However, further work is required to fully characterize the therapeutic potential of such compounds, including gaining an understanding of dose-dependent relationships and limiting factors to effectiveness. Nutritional interventions utilizing anti-inflammatory foods may prove to be a valuable asset in not only delaying or preventing the development of age-related neurodegenerative diseases such as AD, but also treating pre-existing conditions including type-2 diabetes, cardiovascular disease, and obesity.
Keywords: Alzheimer Disease; Cardiovascular Diseases; Chronic Disease; Diet; Humans; Inflammation; Neurodegenerative Diseases

Dietary high cholesterol and trace metals in the drinking water increase levels of ABCA1 in the rabbit hippocampus and temporal cortex. - Schreurs, Bernard G; Sparks, D Larry (J Alzheimers Dis, 2016)
BACKGROUND: Cholesterol-fed rabbits have been documented to show increased amyloid-β (Aβ) deposits in the brain that can be exacerbated by the quality of drinking water especially if rabbits drink tap water or distilled water containing copper. One mechanism of cholesterol and Aβ clearance may be through the ATP-binding cassette transporter A1 (ABCA1). OBJECTIVE AND METHODS: Using an ABCA1 antibody, we determined the number of ABCA1-immunopositive neurons in three areas of rabbit brain as a function of feeding 2% cholesterol and providing tap water, distilled water, or distilled water to which aluminum, copper, or zinc was added. RESULTS: The number of neurons with ABCA1 immunoreactivity was increased significantly as a result of dietary cholesterol in the rabbit hippocampus and inferior and superior temporal cortex. The number of neurons with ABCA1 immunoreactivity was further increased in all three areas as a result of cholesterol-fed rabbits drinking tap water or distilled water with copper. Finally, cholesterol-fed rabbits that drank distilled water with aluminum also showed an increased number of ABCA1-immunopositive neurons in inferior and superior temporal cortex. CONCLUSIONS: These data suggest that ABCA1 levels increase in parallel with previously documented increases in Aβ levels as a result of high dietary cholesterol and copper in the drinking water. Addition of aluminum to distilled water may have a similar effect in the temporal cortex. ABCA1 has been proposed as a means of clearing Aβ from the brain and manipulations that increase Aβ also result in an increase of clearance machinery.
Keywords: Aluminum; Alzheimer Disease; Animals; ATP-Binding Cassette Transporters; Brain Chemistry; Cholesterol, Dietary; Copper; Drinking Water; Hippocampus; Male; Neurons; Rabbits; Temporal Lobe; Zinc

Different Expression Patterns of Amyloid-β Protein Precursor Secretases in Human and Mouse Hippocampal Neurons: A Potential Contribution to Species Differences in Neuronal Susceptibility to Amyloid-β Pathogenesis. - Xu, Zhi-Qiang; Huang, Huang; Chen, Ya-Li; Gao, Yun-Ying; Xu, Jun; Marshall, Charles; Cai, Zhi-You; Xiao, Ming (J Alzheimers Dis, 2016)
Extensive loss of hippocampal neurons serves a pathological basis for irreversible cognitive impairment in patients with Alzheimer's disease (AD). However, this characteristic cannot be replicated by transgenic mouse models, and its underlying mechanisms are unclear. Here, we present evidence that different expression patterns of amyloid-β protein precursor (AβPP) secretases in human and mouse hippocampal neurons are a decisive cause of species difference in the susceptibility to Aβ pathogenesis. Cell bodies of both pyramidal and granular neurons did not appear to undergo Aβ deposits in the 10-month-old transgenic mutant human AβPP/presenilin-1 (PS1) mice. They expressed high levels of non-amyloidogenic α-secretase, and its neuroprotective products soluble AβPPα, but low levels of amyloidogenic β-secretase and γ-secretase, and a neurotoxic product, Aβ42 peptide. Unlike those found in the mouse, human hippocampal neuronal cell bodies expressed β-secretase and γ-secretase, but not α-secretase, which could increase Aβ generation, thus undergoing death in response to various pathological conditions. Increased hippocampal neuronal apoptosis at 48 h following local microinjection of α-secretase antibody ADAM10 into the hippocampus of AβPP/PS1 mice further suggests that high α-secretase expression in mouse neuronal cell bodies is a factor in the paucity of neuronal loss in AD-like pathology. Therefore, selective down-regulation of brain α-secretase in transgenic AD models will better replicate the disease spectrum, including decreased brain soluble AβPPα levels and massive neuronal loss in AD patients, and be beneficial for preclinical therapeutic evaluation of AD.
Keywords: ADAM10 Protein; Amyloid beta-Peptides; Amyloid Precursor Protein Secretases; Animals; Antibodies; Aspartic Acid Endopeptidases; Cell Count; Dose-Response Relationship, Drug; Female; Gene Expression Regulation; Hippocampus; Humans; Low Density Lipoprotein Receptor-Related Protein-1; Male; Mice; Mice, Transgenic; Middle Aged; Mutation; Neurons; Peptide Fragments; Presenilin-1; Species Specificity; Time Factors

Differential Diagnosis of Dementia with High Levels of Cerebrospinal Fluid Tau Protein. - Grangeon, Lou; Paquet, Claire; Bombois, Stephanie; Quillard-Muraine, Muriel; Martinaud, Olivier; Bourre, Bertrand; Lefaucheur, Romain; Nicolas, Gaël; Dumurgier, Julien; Gerardin, Emmanuel; Jan, Mary; Laplanche, Jean-Louis; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Total Tau concentration in cerebrospinal fluid (CSF) is widely used as a biomarker in the diagnosis of neurodegenerative process primarily in Alzheimer's disease (AD). A particularly high Tau level may indicate AD but may also be associated with Creutzfeldt-Jakob disease (CJD). In such situations little is known about the distribution of differential diagnoses. OBJECTIVE: Our study aimed to describe the different diagnoses encountered in clinical practice for patients with dementia and CSF Tau levels over 1000 pg/ml. We studied the p-Tau/Tau ratio to specify its ability to distinguish AD from CJD. METHODS: Patients (n = 202) with CSF Tau levels over 1000 pg/ml were recruited in three memory clinics in France. All diagnoses were made using the same diagnostic procedure and criteria. RESULTS: Patients were diagnosed with AD (n = 148, 73.2%), mixed dementia (n = 38, 18.8%), CJD, vascular dementia (n = 4, 2.0% for each), Lewy body dementia, and frontotemporal dementia (n = 3, 1.5% for each). Dispersion of CSF Tau levels clearly showed an overlap between all diagnoses. Using the p-Tau/Tau ratio suggestive of CJD (<0.075), all CJD patients were correctly categorized and only two AD patients were miscategorized. This ratio was highly associated with CJD compared to AD (p < 0.0001). CONCLUSION: Our study showed that in clinical practice, extremely high CSF Tau levels are mainly related to diagnosis of AD. CJD patients represent a minority. Our results support a sequential interpretation algorithm for CSF biomarkers in dementia. High CSF Tau levels should alert clinicians to check the p-Tau/Tau ratio to consider a probable diagnosis of CJD.
Keywords: Adult; Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Creutzfeldt-Jakob Syndrome; Dementia, Vascular; Diagnosis, Differential; Female; France; Frontotemporal Dementia; Humans; Lewy Body Disease; Male; Mental Status Schedule; Middle Aged; Phosphorylation; Retrospective Studies; Sex Factors; tau Proteins

Differential Impairment of Cognitive and Affective Mentalizing Abilities in Neurodegenerative Dementias: Evidence from Behavioral Variant of Frontotemporal Dementia, Alzheimer's Disease, and Mild Cognitive Impairment. - Dodich, Alessandra; Cerami, Chiara; Crespi, Chiara; Canessa, Nicola; Lettieri, Giada; Iannaccone, Sandro; Marcone, Alessandra; Cappa, Stefano F; Cacioppo, John T (J Alzheimers Dis, 2016)
Cognitive and affective theory of mind (ToM) can be impaired in the course of neurodegenerative dementias. Experimental tests based on different task conditions and/or complexity may fail to capture disease-specific patterns of impairments. In this study, we assessed with a single task both the affective and the cognitive facets of ToM ability in a sample of 47 patients (i.e., 12 AD, 20 bvFTD, and 15 aMCI fulfilling IWG criteria for AD in predementia phase) and 65 healthy controls. Subjects were administered the Story-based Empathy task (SET), a non-verbal task measuring the ability to infer others' intentions (IA) and emotions (EA) compared to a control condition (causal inferences, CI). Global and single sub-condition scores were evaluated with a vectorial method, analyzing the relationship between social abilities and basic cognitive functioning by means of two indices representing the basic ability to perform the task and the balance between basic functions and ToM skills.Dementia (AD and bvFTD) patients showed impaired performances on all SET sub-conditions, whereas aMCI subjects' performance was not different from healthy controls. Vectorial analysis revealed a specific change in the balance between EA and CI conditions only in the bvFTD group, supporting a disproportionate deficit in mental states attribution based on affective cues. The overall deficit in the task in AD appears to be more general and related to the severity of dementia. This latter finding is further supported by the normal performance of the prodromal AD group.
Keywords: Aged; Alzheimer Disease; Cognition; Cognitive Dysfunction; Emotions; Female; Frontotemporal Dementia; Humans; Male; Theory of Mind

Differential Mass Spectrometry Profiles of Tau Protein in the Cerebrospinal Fluid of Patients with Alzheimer's Disease, Progressive Supranuclear Palsy, and Dementia with Lewy Bodies. - Barthélemy, Nicolas R; Gabelle, Audrey; Hirtz, Christophe; Fenaille, François; Sergeant, Nicolas; Schraen-Maschke, Susanna; Vialaret, Jérôme; Buée, Luc; Junot, Christophe; Becher, François; Lehmann, Sylvain (J Alzheimers Dis, 2016)
Microtubule-associated Tau proteins are major actors in neurological disorders, the so-called tauopathies. In some of them, and specifically in Alzheimer's disease (AD), hyperphosphorylated forms of Tau aggregate into neurofibrillary tangles. Following and understanding the complexity of Tau's molecular profile with its multiple isoforms and post-translational modifications represent an important issue, and a major analytical challenge. Immunodetection methods are, in fact, limited by the number, specificity, sensitivity, and capturing property of the available antibodies. Mass spectrometry (MS) has recently allowed protein quantification in complex biological fluids using isotope-labeled recombinant standard for absolute quantification (PSAQ). To study Tau proteins, which are found at very low concentrations within the cerebrospinal fluid (CSF), we relied on an innovative two-step pre-fractionation strategy, which was not dependent on immuno-enrichment. We then developed a sensitive multiplex peptide detection capability using targeted high-resolution MS to quantify Tau-specific peptides covering its entire sequence. This approach was used on a clinical cohort of patients with AD, progressive supranuclear palsy (PSP), and dementia with Lewy body (DLB) and with control non-neurodegenerative disorders. We uncovered a common CSF Tau molecular profile characterized by a predominance of central core expression and 1N/3R isoform detection. While PSP and DLB tau profiles showed minimal changes, AD was characterized by a unique pattern with specific modifications of peptide distribution. Taken together these results provide important information on Tau biology for future therapeutic interventions, and improved molecular diagnosis of tauopathies.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Analysis of Variance; Chromatography, Liquid; Enzyme-Linked Immunosorbent Assay; Female; Humans; Lewy Body Disease; Male; Mental Status Schedule; Middle Aged; Neuroimaging; Neuropsychological Tests; Peptide Fragments; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Statistics as Topic; Supranuclear Palsy, Progressive; tau Proteins

Differential Membrane Toxicity of Amyloid-β Fragments by Pore Forming Mechanisms. - Peters, Christian; Bascuñán, Denisse; Opazo, Carlos; Aguayo, Luis G (J Alzheimers Dis, 2016)
A major characteristic of Alzheimer's disease (AD) is the presence of amyloid-β peptide (Aβ) oligomers and aggregates in the brain. It is known that Aβ oligomers interact with the neuronal membrane and induce perforations that cause an influx of calcium ions and enhance the release of synaptic vesicles leading to a delayed synaptic failure by vesicle depletion. To better understand the mechanism by which Aβ exerts its effect on the plasma membrane, we evaluated three Aβ fragments derived from different regions of Aβ(1-42); Aβ(1-28) from the N-terminal region, Aβ(25-35) from the central region, and Aβ(17-42) from the C-terminal region. The neuronal activities of these fragments were examined with patch clamp, immunofluorescence, transmission electron microscopy, aggregation assays, calcium imaging, and MTT reduction assays. The present results indicate that the fragment Aβ(1-28) contributes to aggregation, an increase in intracellular calcium and synaptotoxicity, but is not involved in membrane perforation; Aβ(25-35) is important for membrane perforation, calcium increase, and synaptotoxicity; and Aβ(17-42) induced mitochondrial toxicity similar to the full length Aβ(1-42), but was unable to induce membrane perforation and calcium increase, supporting the idea that it is less toxic in the non-amyloidogenic pathway.
Keywords: Amyloid beta-Peptides; Animals; Calcium; Cell Membrane; Cells, Cultured; Fluorescent Antibody Technique; HEK293 Cells; Hippocampus; Humans; Microscopy, Electron, Transmission; Neurons; Patch-Clamp Techniques; Peptide Fragments; Porosity; Rats, Sprague-Dawley; Voltage-Sensitive Dye Imaging

Differential Regulation of N-Methyl-D-Aspartate Receptor Subunits is an Early Event in the Actions of Soluble Amyloid-β(1-40) Oligomers on Hippocampal Neurons. - Chang, Lirong; Zhang, Yali; Liu, Jinping; Song, Yizhi; Lv, Angchu; Li, Yan; Zhou, Wei; Yan, Zhen; Almeida, Osborne F X; Wu, Yan (J Alzheimers Dis, 2016)
Synaptic dysfunction during early stages of Alzheimer's disease (AD) is triggered by soluble amyloid-β (Aβ) oligomers that interact with NMDA receptors (NMDARs). We previously showed that Aβ induces synaptic protein loss through NMDARs, albeit through undefined mechanisms. Accordingly, we here examined the contribution of individual NMDAR subunits to synaptotoxicity and demonstrate that Aβ exerts differential effects on the levels and distribution of GluN2A and GluN2B subunits of NMDAR in dendrites. Treatment of cultured hippocampal neurons with Aβ1-40 (10 μM, 1 h) induced a significant increase of dendritic and synaptic GluN2B puncta densities with parallel decreases in the puncta densities of denritic and synaptic pTyr1472-GluN2B. Conversely, Aβ significantly decreased dendritic and synaptic GluN2A and dendritic pTyr1325-GluN2A puncta densities and increased synaptic pTyr1325-GluN2A puncta densities. Unexpectedly, Aβ treatment resulted in a significant reduction of GluN2B and pTyr1472-GluN2B protein levels but did not influence GluN2A and pTyr1325-GluN2A levels. These results show that Aβ exerts complex and distinct regulatory effects on the trafficking and phosphorylation of GluN2A and GluN2B, as well as on their localization within synaptic and non-synaptic sites. Increased understanding of these early events in Aβ-induced synaptic dysfunction is likely to be important for the development of timely preventive and therapeutic interventions.
Keywords: Amyloid beta-Peptides; Animals; Animals, Newborn; Cells, Cultured; Dendrites; Gene Expression Regulation; Hippocampus; Male; Neurons; Peptide Fragments; Phosphorylation; Rats; Rats, Wistar; Receptors, N-Methyl-D-Aspartate

Diminished CRE-Induced Plasticity is Linked to Memory Deficits in Familial Alzheimer's Disease Mice. - Bartolotti, Nancy; Segura, Laura; Lazarov, Orly (J Alzheimers Dis, 2016)
The mechanism underlying impaired learning and memory in Alzheimer's disease is not fully elucidated. The phosphorylation of cyclic-AMP response element binding protein (pCREB) in the hippocampus is thought to be a critical initiating step in the formation of long-term memories. Here, we tested CRE-driven gene expression following learning in mice harboring the familial Alzheimer's disease-linked APPswe/PS1ΔE9 mutations using CRE-β galactosidase reporter. We show that young adult APPswe/PS1ΔE9 mice exhibit impaired recognition memory and reduced levels of pCREB, and its cofactors CREB binding protein (CBP) and p-300 following a learning task, compared to their wild type littermate counterparts. Impairments in learning-induced activation of CREB in these mice are manifested by reduced CRE-driven gene transcription. Importantly, expression of the CRE-driven immediate early gene, Egr-1 (Zif268) is decreased in the CA1 region of the hippocampus. These studies implicate defective CREB-dependent plasticity in the mechanism underlying learning and memory deficits in Alzheimer's disease.
Keywords: Alzheimer Disease; Animals; Cyclic AMP Response Element-Binding Protein; Disease Models, Animal; Hippocampus; Maze Learning; Memory Disorders; Mice; Neuronal Plasticity; Neurons; Phosphorylation

Direct Evidence of Internalization of Tau by Microglia In Vitro and In Vivo. - Bolós, Marta; Llorens-Martín, María; Jurado-Arjona, Jerónimo; Hernández, Félix; Rábano, Alberto; Avila, Jesús (J Alzheimers Dis, 2016)
The microtubule-associated protein (MAP) tau plays a critical role in the pathogenesis of tauopathies. Excess tau can be released into the extracellular medium in a physiological or pathological manner to be internalized by surrounding neurons-a process that contributes to the spread of this protein throughout the brain. Such spreading may correlate with the progression of the abovementioned diseases. In addition to neurons, tau can be internalized into other cells. Here we demonstrate that microglia take up tau in vitro and in vivo. In this regard, microglia from primary cultures internalized soluble (human recombinant tau42) and insoluble (homogenates derived from human AD brain) tau in vitro. Furthermore, using stereotaxic injection of tau in mice in vivo, we show that murine microglia internalize human tau. In addition, we demonstrate, for the first time, that microglia colocalize with various forms of tau in postmortem brain tissue of patients with Alzheimer's disease and non-demented control subjects. Our data reveal a potential role of microglia in the internalization of tau that might be relevant for the design of strategies to enhance the clearance of extracellular tau in neurodegenerative diseases characterized by the accumulation of this protein.
Keywords: Alzheimer Disease; Analysis of Variance; Animals; Animals, Newborn; Calcium-Binding Proteins; Cells, Cultured; Cerebral Cortex; Glial Fibrillary Acidic Protein; Hippocampus; Humans; Mice; Mice, Inbred C57BL; Microfilament Proteins; Microglia; Phosphorylation; Protein Transport; Rats; tau Proteins; Time Factors

The Disconnection Hypothesis in Alzheimer's Disease Studied Through Multimodal Magnetic Resonance Imaging: Structural, Perfusion, and Diffusion Tensor Imaging. - Lacalle-Aurioles, María; Navas-Sánchez, Francisco Javier; Alemán-Gómez, Yasser; Olazarán, Javier; Guzmán-De-Villoria, Juan Adán; Cruz-Orduña, Isabel; Mateos-Pérez, José María; Desco, Manuel (J Alzheimers Dis, 2016)
According to the so-called disconnection hypothesis, the loss of synaptic inputs from the medial temporal lobes (MTL) in Alzheimer's disease (AD) may lead to reduced activity of target neurons in cortical areas and, consequently, to decreased cerebral blood flow (CBF) in those areas. The aim of this study was to assess whether hypoperfusion in parietotemporal and frontal cortices of patients with mild cognitive impairment who converted to AD (MCI-c) and patients with mild AD is associated with atrophy in the MTL and/or microstructural changes in the white matter (WM) tracts connecting these areas. We assessed these relationships by investigating correlations between CBF in hypoperfused areas, mean cortical thickness in atrophied regions of the MTL, and fractional anisotropy (FA) in WM tracts. In the MCI-c group, a strong correlation was observed between CBF of the superior parietal gyri and FA in the parahippocampal tracts (left: r = 0.90, p <  0.0001; right: r = 0.597, p = 0.024), and between FA in the right parahippocampal tract and the right precuneus (r = 0.551, p = 0.041). No significant correlations between CBF in hypoperfused regions and FA in the WM tract were observed in the AD group. These results suggest an association between perfusion deficits and altered WM tracts in prodromal AD, while microvasculature impairments may have a greater influence in more advanced stages. We did not find correlations between cortical thinning in the medial temporal lobes and decreased FA in the WM tracts of the limbic system in either group.
Keywords: Aged; Alzheimer Disease; Brain; Brain Mapping; Cerebral Angiography; Cerebrovascular Circulation; Cognitive Dysfunction; Diffusion Tensor Imaging; Female; Functional Laterality; Humans; Magnetic Resonance Imaging; Male; Mental Status Schedule; Models, Neurological; Multimodal Imaging; Organ Size; Prospective Studies

Discovering New Genes in the Pathways of Common Sporadic Neurodegenerative Diseases: A Bioinformatics Approach. - Kim, Yong Hwan; Beak, Seung Han; Charidimou, Andreas; Song, Min (J Alzheimers Dis, 2016)
Late onset Alzheimer's disease (AD) and Parkinson's disease (PD) are mostly "sporadic" age-related neurodegenerative disorders, but with a clear genetic component. However, their genetic architecture is complex and heterogeneous, largely remaining a conundrum, with only a handful of well-established genetic risk factors consistently associated with these diseases. It is possible that numerous, yet undiscovered, AD and PD related genes might exist. We focused on the 'gene' as a mediator to find new potential genes that might have a relationship with both disorders using bio-literature mining techniques. Based on Entrez Gene, we extracted the genes and directional gene-gene relation in the entire MEDLINE records and then constructed a directional gene-gene network. We identified common genes associated with two different but related diseases by performing shortest path analysis on the network. With our approach, we were able to identify and map already known genes that have a direct relationship with PD and AD. In addition, we identified 7 genes previously unknown to be a bridge between these two disorders. We confirmed 4 genes, ROS1, FMN1, ATP8A2, and SNORD12C, by biomedical literature and further checked 3 genes, ERVK-10, PRS, and C7orf49, that might have a high possibility to be related with both diseases. Additional experiments were performed to demonstrate the effectiveness of our proposed method. Comparing to the co-occurrence approach, our approach detected 25% more candidate genes and verified 10% more genes that have the relationship between both diseases than the co-occurrence approach did.
Keywords: Computational Biology; Female; Gene Regulatory Networks; Genetic Predisposition to Disease; Humans; Male; MEDLINE; Neurodegenerative Diseases

Discovery and Subsequent Confirmation of Novel Serum Biomarkers Diagnosing Alzheimer's Disease. - Shah, Dipti Jigar; Rohlfing, Frederick; Anand, Swati; Johnson, W Evan; Alvarez, MeiHwa Tanielle Bench; Cobell, Jesse; King, Jackson; Young, Sydney A; Kauwe, John S K; Graves, Steven W (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease (AD) remains challenging to diagnose, especially early disease. Having serum AD biomarkers would be of significant interest both in the clinical setting and in drug development efforts. OBJECTIVE: We applied a novel serum proteomic approach to interrogate the low-molecular weight proteome for serum AD biomarkers. METHODS: A discovery study used sera from 58 any-stage AD cases and 55 matched controls analyzed by capillary liquid chromatography-electrospray ionization-tandem mass spectrometry. Candidate biomarkers were statistically modeled and promising biomarkers were retested in a second, blinded confirmatory study (AD cases = 68, controls = 57). Biomarkers that replicated in the second study were modeled for the diagnosis of any-stage and very early stage AD. Further, they were chemically identified by tandem MS. RESULTS: The initial discovery study found 59 novel potential AD biomarkers. Thirteen recurred in more than one multi-marker panel. In a second, blinded, confirmatory study, these same biomarkers were retested in separate specimens. In that study, four markers validated comparing controls to patients with any-stage AD and also with very early AD. The four biomarkers with replicable ability to diagnose AD were then chemically identified. CONCLUSION: These results suggest novel serum AD diagnostic biomarkers can be found using this approach.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Case-Control Studies; Chromatography, Liquid; Female; Humans; Male; Psychiatric Status Rating Scales; Reproducibility of Results; ROC Curve; Tandem Mass Spectrometry

Distinct Patterns of Cognitive Aging Modified by Education Level and Gender among Adults with Limited or No Formal Education: A Normative Study of the Mini-Mental State Examination. - Xie, Haiqun; Zhang, Chengguo; Wang, Yukai; Huang, Shuyun; Cui, Wei; Yang, Wenbin; Koski, Lisa; Xu, Xiping; Li, Youbao; Zheng, Meili; He, Mingli; Fu, Jia; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Dementia is increasingly prevalent due to rapid aging of the population, but under-recognized among people with low education levels. This is partly due to a lack of appropriate and precise normative data, which underestimates cognitive aging in the use of screening tools for dementia. OBJECTIVE: We aimed to improve the precision of screening for cognitive impairment, by characterizing the patterns of cognitive aging and derived normative data of the Mini-Mental State Examination (MMSE) for illiterate and low-educated populations. METHODS: This community-based study included data from 2,280 individuals aged 40 years or older from two rural areas. Multiple linear modeling examined the effect of aging on cognition reflected by the MMSE, stratified by education level and gender. Threshold effect of age on cognition was performed using a smoothing function. RESULTS: The majority of participants (60.4%) were illiterate or had attended only primary school (24.6%). The effect of aging on cognition varied by gender and education. Primary-school educated females and males remained cognitively stable up to 62 and 71 years of age, respectively, with MMSE score declining 0.4 and 0.8 points/year in females and males thereafter. Illiterates females scored 2.3 points lower than illiterate males, and scores for both declined 0.2 points/year. According to these results, normative data stratified by age, education and gender was generated. CONCLUSION: This study suggests gender and educational differences exist in cognitive aging among adults with limited or no formal education. To improve screening precision for cognitive impairment with the use of MMSE in low-educated population, age, gender, and education level should be considered.
Keywords: Adult; Aged; Aged, 80 and over; China; Cognition Disorders; Cognitive Aging; Educational Status; Female; Humans; Male; Mental Status Schedule; Middle Aged; Reference Values; Rural Population; Sex Characteristics

Distinctive Resting State Network Disruptions Among Alzheimer's Disease, Subcortical Vascular Dementia, and Mixed Dementia Patients. - Kim, Hee Jin; Cha, Jungho; Lee, Jong-Min; Shin, Ji Soo; Jung, Na-Yeon; Kim, Yeo Jin; Choe, Yearn Seong; Lee, Kyung Han; Kim, Sung Tae; Kim, Jae Seung; Lee, Jae Hong; Na, Duk L; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Recent advances in resting-state functional MRI have revealed altered functional networks in Alzheimer's disease (AD), especially those of the default mode network (DMN) and central executive network (CEN). However, few studies have evaluated whether small vessel disease (SVD) or combined amyloid and SVD burdens affect the DMN or CEN. OBJECTIVE: The aim of this study was to evaluate whether SVD or combined amyloid and SVD burdens affect the DMN or CEN. METHODS: In this cross-sectional study, we investigated the resting-state functional connectivity within DMN and CEN in 37 Pittsburgh compound-B (PiB)(+) AD, 37 PiB(-) subcortical vascular dementia (SVaD), 13 mixed dementia patients, and 65 normal controls. RESULTS: When the resting-state DMN of PiB(+) AD and PiB(-) SVaD patients were compared, the PiB(+) AD patients displayed lower functional connectivity in the inferior parietal lobule while the PiB(-) SVaD patients displayed lower functional connectivity in the medial frontal and superior frontal gyri. Compared to the PiB(-) SVaD or PiB(+) AD, the mixed dementia patients displayed lower functional connectivity within the DMN in the posterior cingulate gyrus. When the resting-state CEN connectivity of PiB(+) AD and PiB(-) SVaD patients were compared, the PiB(-) SVaD patients displayed lower functional connectivity in the anterior insular region. Compared to the PiB(-) SVaD or PiB(+) AD, the mixed dementia patients displayed lower functional connectivity within the CEN in the inferior frontal gyrus. CONCLUSIONS: Our findings suggest that in PiB(+) AD and PiB(-) SVaD, there is divergent disruptions in resting-state DMN and CEN. Furthermore, patients with combined amyloid and SVD burdens exhibited more disrupted resting-state DMN and CEN than patients with only amyloid or SVD burden.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Aniline Compounds; Cerebral Cortex; Cross-Sectional Studies; Dementia; Dementia, Vascular; Female; Humans; Image Processing, Computer-Assisted; Male; Middle Aged; Models, Neurological; Neural Pathways; Neuropsychological Tests; Oxygen; Psychiatric Status Rating Scales; Radionuclide Imaging; Rest; Thiazoles

Divergent Longitudinal Propagation of White Matter Degradation in Logopenic and Semantic Variants of Primary Progressive Aphasia. - Tu, Sicong; Leyton, Cristian E; Hodges, John R; Piguet, Olivier; Hornberger, Michael (J Alzheimers Dis, 2016)
BACKGROUND: Clinico-pathological distinction of primary progressive aphasia (PPA) can be challenging at clinic presentation. In particular, cross-sectional neuroimaging signatures across the logopenic (lvPPA) and semantic (svPPA) variants are difficult to establish, with longitudinal profiles showing greater divergence. OBJECTIVE: Assess longitudinal propagation of white matter degradation in lvPPA and svPPA to determine disease progression over time, and whether this reflects distinct underlying pathology. METHOD: A cohort of 27 patients with dementia (12 lvPPA; 15 svPPA) and 12 healthy controls were assessed at baseline and 1-year follow-up on the Addenbrooke's Cognitive Examination-Revised and Sydney Language Battery. Diffusion weighted images were collected at both time-points and analyzed for longitudinal white matter change using DTI-TK and TBSS. RESULTS: LvPPA patients showed a significant decline in naming and repetition, over 1 year, while svPPA patients declined in naming and comprehension. Longitudinal imaging revealed widespread bilateral degradation of white matter tracts in lvPPA over a 1-year period with early involvement of the left posterior inferior longitudinal fasciculus (ILF). SvPPA demonstrated focal left lateralized white matter degradation involving the uncinate fasciculus (UF) and anterior ILF, propagating to the right UF with disease progression. CONCLUSIONS: LvPPA and svPPA cohorts showed distinct longitudinal cognitive and white matter profiles. We propose differences in multi-centric and focal white matter dysfunction in lvPPA and svPPA, respectively, reflect underlying pathological differences. The clinical relevance of white matter degradation and mechanisms underlying disease propagation are discussed.
Keywords: Aged; Analysis of Variance; Aphasia, Primary Progressive; Brain; Cohort Studies; Cross-Sectional Studies; Disease Progression; Female; Humans; Image Processing, Computer-Assisted; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Middle Aged; Names; Neuropsychological Tests; Semantics

Diversity of Cognitive Phenotypes Associated with C9ORF72 Hexanucleotide Expansion. - Gómez-Tortosa, Estrella; Prieto-Jurczynska, Cristina; Serrano, Soledad; Franco-Macías, Emilio; Olivié, Laura; Gallego, Jesús; Guerrero-López, Rosa; Trujillo-Tiebas, María José; Ayuso, Carmen; García Ruiz, Pedro; Pérez-Pérez, Julián; Sainz, María José (J Alzheimers Dis, 2016)
For diagnostic purposes, we screened for the C9ORF72 mutation in a) 162 FTLD cases, and b) 145 cases with other diagnoses but with some frontotemporal features or manifestations previously reported in C9 carriers. Ten cases (onset 50 to 75 years) harbored the expansion: seven had FTLD syndromes (4.3% of total, 11% of familial cases), and three (2%) had a different diagnosis. All positive cases had family history of dementia, psychiatric disease, or ALS, but only 20% of families with mixed FTLD/ALS phenotypes carried the expansion. Language impairment was the most common symptom, followed by behavioral changes, memory deficits, and parkinsonism. C9ORF72 mutation has a low frequency in our dementia series and very diverse clinical manifestations.
Keywords: Adult; Age of Onset; Apolipoprotein E4; Cognition; DNA Repeat Expansion; Family; Female; Follow-Up Studies; Frontotemporal Lobar Degeneration; Genetic Association Studies; Genetic Predisposition to Disease; Genotyping Techniques; Humans; Male; Middle Aged; Prevalence; Proteins; Spain

Does Microglial Activation Influence Hippocampal Volume and Neuronal Function in Alzheimer's Disease and Parkinson's Disease Dementia? - Femminella, Grazia D; Ninan, Siddharth; Atkinson, Rebecca; Fan, Zhen; Brooks, David J; Edison, Paul (J Alzheimers Dis, 2016)
BACKGROUND: The influence of neuroinflammation on neuronal function and hippocampal atrophy in Alzheimer's disease (AD) and Parkinson's disease dementia (PDD) is still unclear. OBJECTIVES: Here we investigated whether microglial activation measured by [11C]PK11195 PET is associated with neuronal function measured by cerebral glucose metabolic rate (rCMRGlc) using FDG-PET and hippocampal volume measurements. METHODS: We enrolled 25 subjects (9 PDD, 8 AD, and 8 controls) who underwent PET scans with [11C](R)PK11195, [18F]FDG, and volumetric MRI scanning. RESULTS: SPM correlation analysis in AD and PDD showed a negative correlation between hippocampal volume and microglial activation within hippocampus or parahippocampus and with cortical and subcortical areas of projections from hippocampus, while there was a positive correlation between rCMRGlc in cortical and subcortical areas of projections from hippocampus and hippocampal volume. Hippocampal volume was significantly reduced in AD compared to controls but not in PDD. CONCLUSIONS: These findings indicate that microglial activation inversely correlated with hippocampal volume and hippocampal rCMRGlc in neurodegenerative diseases with dementia, providing further evidence for the central role of microglial activation in neurodegenerative diseases.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Antineoplastic Agents; Brain Mapping; Cognition; Female; Fluorodeoxyglucose F18; Hippocampus; Humans; Isoquinolines; Magnetic Resonance Imaging; Male; Microglia; Middle Aged; Neurons; Neuropsychological Tests; Parkinson Disease; Positron-Emission Tomography; Psychiatric Status Rating Scales; Supranuclear Palsy, Progressive

Dogs with Cognitive Dysfunction as a Spontaneous Model for Early Alzheimer's Disease: A Translational Study of Neuropathological and Inflammatory Markers. - Schütt, Trine; Helboe, Lone; Pedersen, Lars Østergaard; Waldemar, Gunhild; Berendt, Mette; Pedersen, Jan Torleif (J Alzheimers Dis, 2016)
Aged companion dogs with canine cognitive dysfunction (CCD) spontaneously develop varying degrees of progressive cognitive decline and particular neuropathological features correspondent to the changes associated with Alzheimer's disease (AD) in humans. The aim of the present study was to characterize certain aspects of neuropathology and inflammatory markers related to aging and CCD in dogs in comparison with human AD. Fifteen brains from aged dogs with normal cognitive function, mild cognitive impairment, or CCD were investigated and compared with two control brains from young dogs and brain sections from human AD subjects. The neuropathological investigations included evaluation of amyloid-β (Aβ) plaque deposition (N-terminally truncated and pyroglutamyl-modified Aβ included), tau pathology, and inflammatory markers in prefrontal cortex. Cortical Aβ deposition was found to be only of the diffuse subtype as no dense-core or neuritic plaques were found. The Aβ deposition followed a progressive pattern in four maturation stages. Accumulation of the Aβ peptide was also observed in the vessel walls. Both immunohistochemically and biochemically measured levels of Aβ pathology in prefrontal cortex showed a consistent positive correlation to age but not to cognitive deficit severity. No evidence of neurofibrillary tau pathology was found. The level of pro-inflammatory cytokines was generally low and showed no significant association to cognitive status. The findings of the present study support the senescent dog with spontaneous cognitive dysfunction as a valuable non-transgenic model for further investigations of the molecular events involved in the neurodegenerative processes associated with aging and early stage AD, especially the Aβ-related pathology.
Keywords: Aging; Alzheimer Disease; Animals; Brain; Cognitive Dysfunction; Cytokines; Denmark; Disease Models, Animal; Disease Progression; Dog Diseases; Dogs; Female; Humans; Immunohistochemistry; Longitudinal Studies; Male; Plaque, Amyloid; Severity of Illness Index; Species Specificity; tau Proteins; Translational Medical Research

Drivers: A Biologically Contextualized, Cross-Inferential View of the Epidemiology of Neurodegenerative Disorders. - de Pedro-Cuesta, Jesús; Martínez-Martín, Pablo; Rábano, Alberto; Alcalde-Cabero, Enrique; José García López, Fernando; Almazán-Isla, Javier; Ruiz-Tovar, María; Medrano, Maria-José; Avellanal, Fuencisla; Calero, Olga; Calero, Miguel (J Alzheimers Dis, 2016)
BACKGROUND: Sutherland et al. (2011) suggested that, instead of risk factors for single neurodegenerative disorders (NDDs), there was a need to identify specific "drivers", i.e., risk factors with impact on specific deposits, such as amyloid-β, tau, or α-synuclein, acting across entities. OBJECTIVES AND METHODS: Redefining drivers as "neither protein/gene- nor entity-specific features identifiable in the clinical and general epidemiology of conformational NDDs (CNDDs) as potential footprints of templating/spread/transfer mechanisms", we conducted an analysis of the epidemiology of ten CNDDs, searching for patterns. RESULTS: We identified seven potential drivers, each of which was shared by at least two CNDDs: 1) an age-at-exposure-related susceptibility to Creutzfeldt-Jakob disease (CJD) and several late-life CNDDs; 2) a relationship between age at onset, survival, and incidence; 3) shared genetic risk factors for CJD and late-life CNNDs; 4) partly shared personal (diagnostic, educational, behavioral, and social risk factors) predating clinical onset of late-life CNDDs; 5) two environmental risk factors, namely, surgery for sporadic CJD and amyotrophic lateral sclerosis, and Bordetella pertussis infection for Parkinson's disease; 6) reticulo-endothelial system stressors or general drivers (andropause or premenopausal estrogen deficiency, APOEɛ4, and vascular risk factors) for late-life CNDDs such as dementia/Alzheimer's disease, type-2 diabetes mellitus, and some sporadic cardiac and vascular degenerative diseases; and 7) a high, invariant incidence ratio of sporadic to genetic forms of mid- and late-life CNDDs, and type-2 diabetes mellitus. CONCLUSION: There might be a systematic epidemiologic pattern induced by specific proteins (PrP, TDP-43, SOD1, α-synuclein, amyloid-β, tau, Langerhans islet peptide, and transthyretin) or established combinations of these.
Keywords: Age Factors; Aging; Amyloid Precursor Protein Secretases; Apolipoproteins E; Aspartic Acid Endopeptidases; Creutzfeldt-Jakob Syndrome; Environment; Female; Humans; Incidence; Male; Neurodegenerative Diseases; Personality; Risk Factors; Vascular Diseases

Early in vivo Effects of the Human Mutant Amyloid-β Protein Precursor (hAβPPSwInd) on the Mouse Olfactory Bulb. - Rusznák, Zoltán; Kim, Woojin Scott; Hsiao, Jen-Hsiang T; Halliday, Glenda M; Paxinos, George; Fu, YuHong (J Alzheimers Dis, 2016)
The amyloid-β protein precursor (AβPP) has long been linked to Alzheimer's disease (AD). Using J20 mice, which express human AβPP with Swedish and Indiana mutations, we studied early pathological changes in the olfactory bulb. The presence of AβPP/amyloid-β (Aβ) was examined in mice aged 3 months (before the onset of hippocampal Aβ deposition) and over 5 months (when hippocampal Aβ deposits are present). The number of neurons, non-neurons, and proliferating cells was assessed using the isotropic fractionator method. Our results demonstrate that although AβPP is overexpressed in some of the mitral cells, widespread Aβ deposition and microglia aggregates are not prevalent in the olfactory bulb. The olfactory bulbs of the younger J20 group harbored significantly fewer neurons than those of the age-matched wild-type mice (5.57±0.13 million versus 6.59±0.36 million neurons; p = 0.011). In contrast, the number of proliferating cells was higher in the young J20 than in the wild-type group (i.e., 6617±425 versus 4455±623 cells; p = 0.011). A significant increase in neurogenic activity was also observed in the younger J20 olfactory bulb. In conclusion, our results indicate that (1) neurons participating in the mouse olfactory function overexpress AβPP; (2) the cellular composition of the young J20 olfactory bulb is different from that of wild-type littermates; (3) these differences may reflect altered neurogenic activity and/or delayed development of the J20 olfactory system; and (4) AβPP/Aβ-associated pathological changes that take place in the J20 hippocampus and olfactory bulb are not identical.
Keywords: Age Factors; Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Cell Proliferation; Disease Models, Animal; Gene Expression Regulation; Humans; Ki-67 Antigen; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mutation; Nerve Tissue Proteins; Neurogenesis; Neurons; Olfactory Bulb; Piriform Cortex

Economic Analysis of Formal Care, Informal Care, and Productivity Losses in Primary Care Patients who Screened Positive for Dementia in Germany. - Michalowsky, Bernhard; Thyrian, Jochen René; Eichler, Tilly; Hertel, Johannes; Wucherer, Diana; Flessa, Steffen; Hoffmann, Wolfgang (J Alzheimers Dis, 2016)
BACKGROUND: The majority of people with dementia (PwD) live at home and require professional formal care and informal care that is generally provided by close relatives. OBJECTIVE: To determine the utilization and costs of formal and informal care for PwD, indirect costs because of productivity losses of caregivers, and the associations between cost, socio-demographic and clinical variables. METHODS: The analysis includes the data of 262 community-dwelling PwD and their caregivers. Socio-demographics, clinical variables, and the utilization of formal care were assessed within the baseline assessment. To evaluate informal care costs, the Resource Utilization in Dementia (RUD) questionnaire was used. Costs were calculated from a social perspective. Associations were evaluated using multiple linear and logistic regression models. RESULTS: Formal care services were utilized less (26.3%) than informal care (85.1%), resulting in a cost ratio of one to ten(1,646 €; 16,473 €, respectively). In total, 29% of caregivers were employed, and every seventh (14.3%) experienced productivity losses, which corresponded to 1,258 € annually. Whereas increasing deficits in daily living activities were associated with higher formal and higher informal costs, living alone was significantly associated with higher formal care costs and the employment of a caregiver was associated with lower informal care costs. CONCLUSION: Informal care contributes the most to total care costs. Living alone is a major cost driver for formal costs because of the lower availability of potential informal care. The availability of informal care is limited and productivity losses are increased when a caregiver is employed.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Caregivers; Cost of Illness; Cross-Sectional Studies; Dementia; Female; Germany; Health Care Costs; Home Care Services; Humans; Male; Patient Care; Sensitivity and Specificity; Surveys and Questionnaires

Effect of Anserine/Carnosine Supplementation on Verbal Episodic Memory in Elderly People. - Hisatsune, Tatsuhiro; Kaneko, Jun; Kurashige, Hiroki; Cao, Yuan; Satsu, Hideo; Totsuka, Mamoru; Katakura, Yoshinori; Imabayashi, Etsuko; Matsuda, Hiroshi (J Alzheimers Dis, 2016)
Our goal in this study was to determine whether or not anserine/carnosine supplementation (ACS) is capable of preserving cognitive function of elderly people. In a double-blind randomized controlled trial, volunteers were randomly assigned to an ACS or placebo group at a 1:1 ratio. The ACS group took 1.0 g of an anserine/carnosine (3:1) formula daily for 3 months. Participants were evaluated by psychological tests before and after the 3-month supplementation period. Thirty-nine healthy elderly volunteers (60-78 years old) completed the follow-up tests. Among the tests, delayed recall verbal memory assessed by the Wechsler Memory Scale-Logical Memory showed significant preservation in the ACS group, compared to the placebo group (p = 0.0128). Blood analysis revealed a decreased secretion of inflammatory cytokines, including CCL-2 and IL-8, in the ACS group. MRI analysis using arterial spin labeling showed a suppression in the age-related decline in brain blood flow in the posterior cingulate cortex area in the ACS group, compared to the placebo group (p = 0.0248). In another randomized controlled trial, delayed recall verbal memory showed significant preservation in the ACS group, compared to the placebo group (p = 0.0202). These results collectively suggest that ACS may preserve verbal episodic memory and brain perfusion in elderly people, although further study is needed.
Keywords: Adult; Aged; Aging; Anserine; Brain; Carnosine; Cytokines; Dietary Supplements; Double-Blind Method; Female; Gene Expression Regulation; Humans; Image Processing, Computer-Assisted; Male; Memory, Episodic; Middle Aged; Neuropsychological Tests; Oligonucleotide Array Sequence Analysis; Verbal Learning

Effect of Early Referral to Specialist in Dementia on Institutionalization and Functional Decline: Findings from a Population-Based Study. - Pimouguet, Clément; Le-Goff, Mélanie; Rizzuto, Debora; Berr, Claudine; Leffondré, Karen; Pérès, Karine; Dartigues, Jean François; Helmer, Catherine (J Alzheimers Dis, 2016)
BACKGROUND: Although early diagnosis has been hypothesized to benefit both patients and caregivers, until now studies evaluating the effect of early dementia diagnosis are lacking. OBJECTIVE: To investigate the influence of early specialist referral for dementia on the risk of institutionalization and functional decline in Activity of Daily Living (ADL). METHODS: Incident dementia cases were screened in a prospective population-based cohort, the Three-City Study, and initial specialist consultation for cognitive complaint was assessed at dementia diagnosis. Proportional hazard regression and illness-death models were used to test the association between specialist referral and, respectively, institutionalization and functional decline. RESULTS: Only one third of the incident individuals with dementia had consulted a specialist for cognitive problems early (36%). After adjustment on potential confounders (including cognitive and functional decline) and competing risk of death, participants who had consulted a specialist early in the disease course presented a higher rate of being institutionalized than those who did not (Hazard Ratio = 2.00, 95% Confidence Interval (CI): 1.09- 3.64). But early specialist referral was not associated with further functional decline (HR = 1.09, 95% CI: 0.71- 1.67). CONCLUSIONS: Early specialist referral in dementia is associated with increased risk of institutionalization but not with functional decline in ADL. These findings suggest that early care referral in dementia may be a marker of concern for patients and/or caregivers; subsequent medical and social care could be suboptimal or inappropriate to allow patients to stay longer at home.
Keywords: Activities of Daily Living; Cognition Disorders; Community Health Planning; Dementia; Disability Evaluation; Female; Finland; Follow-Up Studies; Humans; Institutionalization; Male; Psychiatric Status Rating Scales; Referral and Consultation; Specialization

Effect of Tween-20 on Core Biomarkers Measured in Cerebrospinal Fluid from Patients with Alzheimer's Disease, Mild Cognitive Impairment, or Healthy Control Individuals. - Berge, Guro; Lauridsen, Camilla; Sando, Sigrid Botne; Holder, Daniel Joseph; Møller, Ina; Aasly, Jan Olav; Bråthen, Geir; Savage, Mary Josephine; White, Linda Rosemary (J Alzheimers Dis, 2016)
BACKGROUND: There is substantial variation caused by preanalytical procedures in the measurement of cerebrospinal fluid (CSF) biomarkers for Alzheimer's disease (AD) reported in the literature. OBJECTIVE: Determine whether the detergent Tween-20 improves diagnostic accuracy. METHODS: CSF proteins (Aβ42, Aβ40, total tau, and phosphorylated tau) were measured by standard ELISA, in uncentrifuged CSF with or without 0.05% Tween-20 from patients with AD or amnestic mild cognitive impairment, and healthy elderly controls. In the main study, collection tubes containing Tween-20 (Sarstedt 15 mL) were filled with 5 mL CSF to ensure consistent detergent concentration across subsequent aliquots into Corning 2 mL tubes. These latter were also the primary collection vessel for samples without Tween-20. The effect of centrifugation, and extra tube transfer of samples with Tween-20 were also examined. RESULTS: 0.05% Tween-20 significantly increased mean measured CSF concentration of Aβ42 (30% ), Aβ40 (23% ), and total tau (4% ), but not phosphorylated tau. Generally, these increases were similar in all groups, although for Aβ42, the mean percentage increase with Tween-20 was slightly larger for AD. Areas under receiver-operator characteristic curves were similar whether Tween-20 was present or not. Centrifuged CSF without Tween-20 significantly reduced the measured concentration of Aβ42 versus non-centrifuged samples, a difference not seen when detergent was added. Similar CSF Aβ42 levels were found whether Tween-20 was added at collection in an extra tube or directly to the main collection tube. CONCLUSION: Addition of Tween-20 to CSF did not improve differentiation of patients from controls.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Enzyme-Linked Immunosorbent Assay; Female; Humans; Longitudinal Studies; Male; Middle Aged; Peptide Fragments; Phosphorylation; Polysorbates; ROC Curve; Surface-Active Agents; tau Proteins

The Effects of Amnestic Mild Cognitive Impairment on Go/NoGo Semantic Categorization Task Performance and Event-Related Potentials. - Mudar, Raksha A; Chiang, Hsueh-Sheng; Eroh, Justin; Nguyen, Lydia T; Maguire, Mandy J; Spence, Jeffrey S; Kung, Fanting; Kraut, Michael A; Hart, John (J Alzheimers Dis, 2016)
We examined the effects of amnestic mild cognitive impairment (aMCI) on behavioral (response times and error rates) and scalp-recorded event-related potential (ERP) measures of response execution and inhibition, using Go/NoGo tasks involving basic and superordinate semantic categorization. Twenty-five aMCI (16 F; 68.5±8 years) and 25 age- and gender-matched normal control subjects (16 F; 65.4±7.1 years) completed two visual Go/NoGo tasks. In the single car task, responses were made based on single exemplars of a car (Go) and a dog (NoGo) (basic). In the object animal task, responses were based on multiple exemplars of objects (Go) and animals (NoGo) (superordinate). The aMCI subjects had higher commission errors on the NoGo trials compared to the control subjects, whereas both groups had comparable omission errors and reaction times during the Go trials. The aMCI subjects had significantly prolonged N2 ERP latency during Go and NoGo trials across tasks compared to the controls. Both groups showed similar categorization effects and response type effects in N2/P3 ERP latencies and P3 amplitude. Our findings indicate that altered early neural processing indexed by N2 latency distinguishes subjects with aMCI from controls during the Go/NoGo task. Prolonged Go-N2 latency in aMCI appears to precede behavioral changes in response execution, whereas prolonged NoGo-N2 latency underlies behavioral deterioration in response inhibition.
Keywords: Aged; Aged, 80 and over; Amnesia; Brain; Brain Mapping; Cognitive Dysfunction; Electroencephalography; Evoked Potentials; Female; Humans; Inhibition (Psychology); Male; Middle Aged; Neuropsychological Tests; Reaction Time

The Effects of Latrepirdine on Amyloid-β Aggregation and Toxicity. - Porter, Tenielle; Bharadwaj, Prashant; Groth, David; Paxman, Adrian; Laws, Simon M; Martins, Ralph N; Verdile, Giuseppe (J Alzheimers Dis, 2016)
Latrepirdine (Dimebon) has been demonstrated to be a neuroprotective and cognition improving agent in neurodegenerative diseases that feature protein aggregation and deposition, such as Alzheimer's disease (AD). The accumulation of amyloid-β (Aβ) protein aggregates is a key event in the neurodegenerative process in AD. This study explores if latrepirdine modulation of protein aggregation contributes to its neuroprotective mechanism of action. Assessment of neuronal cell death showed that there was a significant reduction in lactate dehydrogenase release at an equimolar ratio of Aβ:latrepirdine and with lower concentrations of latrepirdine. The ability of latrepirdine to alter the formation of Aβ42 aggregates was assessed by thioflavin-T fluorescence, western immunoblotting and atomic force microscopy (AFM). Despite showing a reduction in thioflavin-T fluorescence with latrepirdine treatment, indicating a decrease in aggregation, immunoblotting and AFM showed a modest increase in both the formation and size of Aβ aggregates. The discrepancies between thioflavin-T and the other assays are consistent with previous evidence that cyclic molecules can interfere with thioflavin-T binding of amyloid protein preparations. The ability of latrepirdine to modulate Aβ aggregation appears to be independent of its neuroprotective effects, and is unlikely to be a mechanism by which latrepirdine offers protection. This study investigates the effect of latrepirdine on Aβ aggregation, and presents evidence suggesting that caution should be applied in the use of thioflavin-T fluorescence based assays as a method for screening compounds for protein aggregation altering properties.
Keywords: Amyloid beta-Peptides; Analysis of Variance; Antipsychotic Agents; Cell Line, Tumor; Dose-Response Relationship, Drug; Drug Interactions; Humans; Indoles; L-Lactate Dehydrogenase; Microscopy, Atomic Force; Neuroblastoma; Peptide Fragments; Protein Aggregates

Efficacy and Safety of ABT-126 in Subjects with Mild-to-Moderate Alzheimer's Disease on Stable Doses of Acetylcholinesterase Inhibitors: A Randomized, Double-Blind, Placebo-Controlled Study. - Florian, Hana; Meier, Andreas; Gauthier, Serge; Lipschitz, Stanley; Lin, Yunzhi; Tang, Qi; Othman, Ahmed A; Robieson, Weining Z; Gault, Laura M (J Alzheimers Dis, 2016)
BACKGROUND: ABT-126 is a potent, selective α7 nicotinic acetylcholine receptor agonist with putative procognitive effects as a monotherapy in treating Alzheimer's disease (AD). OBJECTIVE: This randomized, double-blind, placebo-controlled multicenter study (NCT01549834) investigated the efficacy and safety of ABT-126 in subjects with mild-to-moderate AD who were taking stable doses of acetylcholinesterase inhibitors (AChEIs). METHODS: Subjects received 25 mg ABT-126 (n = 143), 75 mg ABT-126 (n = 145), or placebo (n = 146) once daily for 24 weeks. Subjects who completed the 24-week double-blind study were eligible to enroll in a 28-week open-label extension study (NCT01690195) and received 75 mg ABT-126 daily. The primary efficacy endpoint was the change from baseline to week 24 in the 11-item total score of the Alzheimer's Disease Assessment Scale- Cognitive Subscale (ADAS-Cog). RESULTS: Neither dose of ABT-126 demonstrated significant improvement compared with placebo in the primary efficacy endpoint. However, 25 mg ABT-126 demonstrated significant improvement compared with placebo in ADAS-Cog scores at week 4 (least squares mean difference, -1.21; standard error, 0.51; p <  0.010, one-sided); 75 mg ABT-126 did not demonstrate significant improvements in ADAS-Cog scores compared with placebo at any time point. A treatment effect was not observed for any secondary efficacy measures of cognition, function, or global improvement. ABT-126 was generally well tolerated; the most common adverse events were agitation, constipation, diarrhea, fall, and headache. CONCLUSIONS: Overall, the efficacy profile of ABT-126 did not warrant further development as add-on therapy to AChEIs to treat mild-to-moderate AD.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cholinesterase Inhibitors; Disease Progression; Dose-Response Relationship, Drug; Double-Blind Method; Female; Humans; Indans; International Cooperation; Male; Medication Adherence; Middle Aged; Piperidines; Psychiatric Status Rating Scales; Treatment Outcome

Efficacy and Safety of MMFS-01, a Synapse Density Enhancer, for Treating Cognitive Impairment in Older Adults: A Randomized, Double-Blind, Placebo-Controlled Trial. - Liu, Guosong; Weinger, Jason G; Lu, Zhong-Lin; Xue, Feng; Sadeghpour, Safa (J Alzheimers Dis, 2016)
BACKGROUND: Cognitive impairment is a major problem in elderly, affecting quality of life. Pre-clinical studies show that MMFS-01, a synapse density enhancer, is effective at reversing cognitive decline in aging rodents. OBJECTIVE: Since brain atrophy during aging is strongly associated with both cognitive decline and sleep disorder, we evaluated the efficacy of MMFS-01 in its ability to reverse cognitive impairment and improve sleep. METHODS: We conducted a randomized, double-blind, placebo-controlled, parallel-designed trial in older adult subjects (age 50-70) with cognitive impairment. Subjects were treated with MMFS-01 (n = 23) or placebo (n = 21) for 12 weeks and cognitive ability, sleep quality, and emotion were evaluated. Overall cognitive ability was determined by a composite score of tests in four major cognitive domains. RESULTS: With MMFS-01 treatment, overall cognitive ability improved significantly relative to placebo (p = 0.003; Cohen's d = 0.91). Cognitive fluctuation was also reduced. The study population had more severe executive function deficits than age-matched controls from normative data and MMFS-01 treatment nearly restored their impaired executive function, demonstrating that MMFS-01 may be clinically significant. Due to the strong placebo effects on sleep and anxiety, the effects of MMFS-01 on sleep and anxiety could not be determined. CONCLUSIONS: The current study demonstrates the potential of MMFS-01 for treating cognitive impairment in older adults.
Keywords: Aged; Anxiety; Butyrates; Cognition; Cognition Disorders; Double-Blind Method; Emotions; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Nootropic Agents; Sleep; Synapses; Treatment Outcome

Efficacy and Safety of Sustained Release Donepezil High Dose versus Immediate Release Donepezil Standard Dose in Japanese Patients with Severe Alzheimer's Disease: A Randomized, Double-Blind Trial. - Homma, Akira; Atarashi, Hirotsugu; Kubota, Naoki; Nakai, Kenya; Takase, Takao (J Alzheimers Dis, 2016)
BACKGROUND: Donepezil is an established treatment for mild, moderate, and severe Alzheimer's disease (AD). An international study demonstrated superior efficacy of sustained release (SR) 23 mg/day donepezil over immediate release (IR) 10 mg/day donepezil for cognitive function, but not global function in moderate-to-severe AD. OBJECTIVE: To demonstrate the superiority of SR 23 mg/day donepezil over IR 10 mg/day donepezil in Japanese patients with severe AD (SAD). METHODS: In this multicenter, randomized, double-blind, parallel-group study, Japanese outpatients with SAD were randomly assigned to continue IR 10 mg/day or switch to SR 23 mg/day for 24 weeks. Endpoints included the Severe Impairment Battery (SIB), Clinician's Interview-Based Impression of Change Plus Caregiver Input (CIBIC-plus), and safety. RESULTS: Overall, 166 and 185 patients were randomized to receive IR 10 mg/day and SR 23 mg/day, respectively. SR 23 mg/day was not statistically superior to IR 10 mg/day by SIB (least squares mean difference [LSMD]: 0.0; 95% confidence interval [CI]: -1.7, 1.8; p = 0.981) or CIBIC-plus (LSMD: 0.2; 95% CI: 0.0, 0.4; p = 0.080). Common adverse events in the SR 23 mg group were decreased appetite, vomiting, diarrhea, and contusion. Safety findings were consistent with known safety profiles of donepezil. CONCLUSION: SR 23 mg/day donepezil was not superior to IR 10 mg/day donepezil regarding the efficacy endpoints for Japanese SAD. Considering that a 10 mg/day dose is approved for SAD in Japan, the present findings suggest that IR 10 mg/day donepezil is the optimal dosage for Japanese patients with SAD.
Keywords: Aged; Alzheimer Disease; Cholinesterase Inhibitors; Delayed-Action Preparations; Double-Blind Method; Female; Humans; Indans; Japan; Male; Mental Status Schedule; Nootropic Agents; Outpatients; Piperidines; Psychiatric Status Rating Scales; Severity of Illness Index; Treatment Outcome

Empirically Defining Trajectories of Late-Life Cognitive and Functional Decline. - Hochstetler, Helen; Trzepacz, Paula T; Wang, Shufang; Yu, Peng; Case, Michael; Henley, David B; Degenhardt, Elisabeth; Leoutsakos, Jeannie-Marie; Lyketsos, Constantine G (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease (AD) is associated with variable cognitive and functional decline, and it is difficult to predict who will develop the disease and how they will progress. OBJECTIVE: This exploratory study aimed to define latent classes from participants in the Alzheimer's Disease Neuroimaging Initiative (ADNI) database who had similar growth patterns of both cognitive and functional change using Growth Mixture Modeling (GMM), identify characteristics associated with those trajectories, and develop a decision tree using clinical predictors to determine which trajectory, as determined by GMM, individuals will most likely follow. METHODS: We used ADNI early mild cognitive impairment (EMCI), late MCI (LMCI), AD dementia, and healthy control (HC) participants with known amyloid-β status and follow-up assessments on the Alzheimer's Disease Assessment Scale - Cognitive Subscale or the Functional Activities Questionnaire (FAQ) up to 24 months postbaseline. GMM defined trajectories. Classification and Regression Tree (CART) used certain baseline variables to predict likely trajectory path. RESULTS: GMM identified three trajectory classes (C): C1 (n = 162, 13.6%) highest baseline impairment and steepest pattern of cognitive/functional decline; C3 (n = 819, 68.7%) lowest baseline impairment and minimal change on both; C2 (n = 211, 17.7%) intermediate pattern, worsening on both, but less steep than C1. C3 had fewer amyloid- or apolipoprotein-E ɛ4 (APOE4) positive and more healthy controls (HC) or EMCI cases. CART analysis identified two decision nodes using the FAQ to predict likely class with 82.3% estimated accuracy. CONCLUSIONS: Cognitive/functional change followed three trajectories with greater baseline impairment and amyloid and APOE4 positivity associated with greater progression. FAQ may predict trajectory class.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Apolipoprotein E4; Cognition Disorders; Databases, Factual; Dementia; Disease Progression; Female; Follow-Up Studies; Humans; Male; Middle Aged; Neuroimaging; Neuropsychological Tests; Surveys and Questionnaires

Enalapril Alone or Co-Administered with Losartan Rescues Cerebrovascular Dysfunction, but not Mnemonic Deficits or Amyloidosis in a Mouse Model of Alzheimer's Disease. - Ongali, Brice; Nicolakakis, Nektaria; Tong, Xing-Kang; Aboulkassim, Tahar; Imboden, Hans; Hamel, Edith (J Alzheimers Dis, 2016)
The co-administration of angiotensin converting enzyme inhibitors (ACEi) and angiotensin II (AngII) receptor blockers (ARB) that bind angiotensin type 1 receptors (AT1R) may protect from Alzheimer's disease (AD) better than each treatment taken alone. We tested the curative potential of the non brain-penetrant ACEi enalapril (3 mg/kg/day) administered for 3 months either alone or in combination with the brain penetrant ARB losartan (10 mg/kg/day) in aged (∼15 months) transgenic mice overexpressing a mutated form of the human amyloid-β protein precursor (AβPP, thereafter APP mice). We studied cerebrovascular function, protein levels of oxidative stress markers (superoxide dismutases SOD1, SOD2 and the NADPH oxidase subunit p67phox), amyloid-β (Aβ) pathology, astrogliosis, cholinergic innervation, AT1R and angiotensin IV receptor (AT4R) levels, together with cognitive performance. Both treatments normalized cerebrovascular reactivity and p67phox protein levels, but they did not reduce the cerebrovascular levels of SOD1. Combined treatment normalized cerebrovascular SOD2 levels, significantly attenuated astrogliosis, but did not reduce the increased levels of cerebrovascular AT1R. Yet, combined therapy enhanced thioflavin-S labeled Aβ plaque burden, a tendency not significant when Aβ1 - 42 plaque load was considered. None of the treatments rescued cognitive deficits, cortical AT4R or cholinergic innervation. We conclude that both treatments normalized cerebrovascular function by inhibiting the AngII-induced oxidative stress cascade, and that the positive effects of the combined therapy on astrogliosis were likely due to the ability of losartan to enter brain parenchyma. However, enalapril did not potentiate, and may even dampen, the reported cognitive benefits of losartan, raising caution when selecting the most appropriate antihypertensive therapy in AD patients.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloidosis; Analysis of Variance; Animals; Antihypertensive Agents; Cerebrovascular Disorders; Cholinesterases; Disease Models, Animal; Drug Combinations; Enalapril; Female; Glial Fibrillary Acidic Protein; Humans; Losartan; Male; Maze Learning; Memory Disorders; Mice; Mice, Transgenic; Mutation

The Evolution of Caregiver Burden in Frontotemporal Dementia with and without Amyotrophic Lateral Sclerosis. - Hsieh, Sharpley; Leyton, Cristian E; Caga, Jashelle; Flanagan, Emma; Kaizik, Cassandra; O'Connor, Claire M; Kiernan, Matthew C; Hodges, John R; Piguet, Olivier; Mioshi, Eneida (J Alzheimers Dis, 2016)
BACKGROUND AND AIMS: Frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS) represent a disease spectrum. Caregiver burden in subtypes of FTD has not yet been directly compared with those patients who have co-existent FTD and ALS (ALSFTD). METHOD: Perceived caregiver burden was evaluated using the short Zarit Burden Interview (ZBI) in patients with behavioral-variant FTD (bvFTD, n = 21), semantic dementia (SD, n = 18), and ALSFTD (n = 15) at the initial clinical presentation and follow-up assessments. The Mini-Addenbrooke's Cognitive Examination (M-ACE) and the Motor Neuron Disease Behaviour Scale (MiND-B) were also used. Linear mixed effects models examined longitudinal changes on the ZBI, M-ACE, and MiND-B across groups. RESULTS: Burden at baseline was highest for the bvFTD group. Longitudinally, perceived burden increased for the SD and ALSFTD groups whereas in bvFTD, the level of burden which was high at baseline and remained high with disease progression. The severity of abnormal behaviors at baseline, as assessed by the MiND-B, correlated with baseline levels of caregiver burden and further accounted for 23% of the variance in caregiver burden at clinical follow-up. CONCLUSIONS: The trajectory of perceived burden differs across the FTD-ALS spectrum, with SD and ALSFTD caregivers demonstrating an increased burden that develops over time, compared to a persistently high level for bvFTD caregivers, evident throughout the disease course. The evolution of burden in these three syndromes likely reflects the initial presentation and clinical characterization that develops with time. Psycho-education programs for caregivers, which provide better coping strategies for challenging behaviors, may reduce levels of burden experienced with disease progression.
Keywords: Adaptation, Psychological; Aged; Amyotrophic Lateral Sclerosis; Analysis of Variance; Caregivers; Case-Control Studies; Cost of Illness; Disease Progression; Female; Frontotemporal Dementia; Humans; Interviews as Topic; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Surveys and Questionnaires

Examining the Relationship Between Autobiographical Memory Impairment and Carer Burden in Dementia Syndromes. - Kumfor, Fiona; Teo, Drusilla; Miller, Laurie; Lah, Suncica; Mioshi, Eneida; Hodges, John R; Piguet, Olivier; Irish, Muireann (J Alzheimers Dis, 2016)
BACKGROUND: Autobiographical memory (ABM) refers to the capacity to remember one's own past, and is known to be central for supporting one's identity and sense of self. This capacity is commonly affected in Alzheimer's disease (AD), as well as semantic dementia (SD) and behavioral-variant frontotemporal dementia (bvFTD). Importantly, ABM plays a critical social function, facilitating relationship intimacy and empathy, and thus loss of ABM may also negatively affect families and carers. OBJECTIVE: To explore the relationship between ABM disruption and carer burden in AD, SD, and bvFTD, and establish whether characteristic ABM profiles differentially relate to carer burden across dementia syndromes. METHODS: We recruited 12 AD, 10 SD, and 13 bvFTD patients and their primary carer. All participants completed the Autobiographical Interview to assess memory for recent and remote events. Carers completed: the Zarit Burden Interview; Depression, Anxiety and Stress Scale (DASS-21); and the Intimate Bond Measure (IBM). RESULTS: In AD, loss of recent ABM was associated with worse psychological wellbeing of carers on the DASS-21. In contrast in SD, remote ABM dysfunction was associated with SD patients showing greater controlling behavior within their intimate relationships. In bvFTD, surprisingly, despite pervasive ABM impairment, no relationship between extent of ABM loss and carer burden was observed. CONCLUSION: These preliminary results reveal that ABM impairment impacts on patients' families and carers and suggest that these influences vary according to the pattern of ABM dysfunction. Disease-specific interventions focusing on preserved aspects of ABM may improve quality of life for both patients and carers.
Keywords: Adaptation, Psychological; Aged; Alzheimer Disease; Analysis of Variance; Behavioral Symptoms; Caregivers; Female; Frontotemporal Dementia; Humans; Male; Memory Disorders; Memory, Episodic; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales; Statistics as Topic

Exercise Plus Cognitive Performance Over and Above Exercise Alone in Subjects with Mild Cognitive Impairment. - Sacco, Guillaume; Caillaud, Corinne; Ben Sadoun, Gregory; Robert, Philippe; David, Renaud; Brisswalter, Jeanick (J Alzheimers Dis, 2016)
BACKGROUND: Epidemiological studies highlight the relevance of regular exercise interventions to enhance or maintain neurocognitive function in subjects with cognitive impairments. OBJECTIVES: The aim of this study was to ascertain the effect of aerobic exercise associated with cognitive enrichment on cognitive performance in subjects with mild cognitive impairment (MCI). METHOD: Eight participants with MCI (72 ± 2 years) were enrolled in a 9-month study that consisted of two 3-months experimental interventions separated by a training cessation period of 3 months. The interventions included either aerobic exercise alone or aerobic exercise combined with cognitive enrichment. The exercise program involved two 20-min cycling exercise bouts per week at an intensity corresponding to 60% of the heart rate reserve. Cognitive performance was assessed using a task of single reaction time (SRT) and an inhibition task (Go-no-Go) before, immediately after, and 1 month after each intervention. RESULTS: The exercise intervention improved the speed of responses during the Go-no-Go task without any increase in errors. This improvement was enhanced by cognitive enrichment (6 ± 1% ; p >  0.05), when compared with exercise alone (4 ± 0.5% ,). Following exercise cessation, this positive effect disappeared. No effect was observed on SRT performance. CONCLUSION: Regular aerobic exercise improved cognitive performance in MCI subjects and the addition of cognitive tasks during exercise potentiated this effect. However, the influence of aerobic exercise on cognitive performance did not persist after cessation of training. Studies involving a larger number of subjects are necessary to confirm these results.
Keywords: Aged; Analysis of Variance; Cognitive Dysfunction; Cognitive Therapy; Exercise; Exercise Therapy; Female; Humans; Inhibition (Psychology); Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Reaction Time; Retrospective Studies; Treatment Outcome

Formal Psychiatric Disorders are not Overrepresented in Behavioral Variant Frontotemporal Dementia. - Gossink, Flora T; Dols, Annemieke; Krudop, Welmoed A; Sikkes, Sietske A; Kerssens, Cora J; Prins, Niels D; Scheltens, Philip; Stek, Max L; Pijnenburg, Yolande A L (J Alzheimers Dis, 2016)
While psychiatric misdiagnosis is well-known in behavioral variant frontotemporal dementia (bvFTD), a systematic evaluation of standardized criteria for psychiatric disorders in bvFTD is still missing. Our aim was to define frequency and character of DSM-IV psychiatric disorders among patients with probable and definite bvFTD compared to possible bvFTD, other neurodegenerative diseases, and psychiatric diagnoses, using MINI-International Neuropsychiatric Interview. We additionally compared psychiatric prodromes between these groups. Subjects were participants of the late-onset frontal lobe (LOF) study, a longitudinal multicenter study. In each patient, after baseline diagnostic procedure, a neurologist and geriatric psychiatrist made a joint clinical diagnosis. Independently, a structured diagnostic interview according to DSM-IV and ICD-10 criteria (MINI-Plus) was performed by a trained professional blinded to clinical diagnosis. Out of 91 patients, 23 with probable and definite bvFTD, 3 with possible bvFTD, 25 with a non bvFTD neurodegenerative disease, and 40 with a clinical psychiatric diagnosis were included. Overall frequency of formal current and past psychiatric disorders in probable and definite bvFTD (21.7% current, 8.7% past) did not differ from other neurodegenerative diseases (12.0% current, 16.0% past) or possible bvFTD (66.7% current, 66.7% past), but was less than in patients with a clinical psychiatric diagnosis (57.5% current, 62.5% past; p <  0.01). In probable and definite bvFTD unipolar mood disorders were most common. Formally diagnosed psychiatric disorders are not overrepresented in probable bvFTD, suggesting that psychiatric misdiagnosis in bvFTD can be reduced by strictly applying diagnostic criteria. In suspected bvFTD close collaboration between neurologists and psychiatrists will advance diagnostics and subsequent treatment.
Keywords: Aged; Cohort Studies; Diagnostic and Statistical Manual of Mental Disorders; Female; Frontotemporal Dementia; Humans; Male; Mental Disorders; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales

Functional Connectivity of Ventral and Dorsal Visual Streams in Posterior Cortical Atrophy. - Migliaccio, Raffaella; Gallea, Cécile; Kas, Aurélie; Perlbarg, Vincent; Samri, Dalila; Trotta, Laura; Michon, Agnès; Lacomblez, Lucette; Dubois, Bruno; Lehéricy, Stéphane; Bartolomeo, Paolo (J Alzheimers Dis, 2016)
BACKGROUND: Posterior cortical atrophy (PCA) induces progressive dysfunction of ventral and dorsal visual networks. Little is known, however, about corresponding changes in functional connectivity (FC). OBJECTIVES: To investigate FC changes in the visual networks, their relationship with cortical atrophy, and the association with Alzheimer's disease (AD) pathology. METHODS: Ten PCA patients and 28 age-matched controls participated in the study. Using resting state fMRI, we measured FC in ventral and dorsal cortical visual networks, defined on the basis of a priori knowledge of long-range white matter connections. To assess the relationships with AD, we determined AD biomarkers in cerebrospinal fluid and FC in the default mode network (DMN), which is vulnerable to AD pathology. Voxel-based morphometry analysis assessed the pattern of grey matter (GM) atrophy. RESULTS: PCA patients showed GM atrophy in bilateral occipital and inferior parietal regions. PCA patients had lower FC levels in a ventral network than controls, but higher FC in inferior components of the dorsal network. In particular, the increased connectivity correlated with greater GM atrophy in occipital regions. All PCA patients had positive cerebrospinal fluid biomarkers for AD; however, FC in global DMN did not differ from controls. CONCLUSIONS: FC in PCA reflects brain structure in a non-univocal way. Hyperconnectivity of dorsal networks may indicate aberrant communication in response to posterior brain atrophy or processes of neural resilience during the initial stage of brain dysfunction. The lack of difference from controls in global DMN FC highlights the atypical nature of PCA with respect to typical AD.
Keywords: Aged; Alzheimer Disease; Atrophy; Case-Control Studies; Cerebral Cortex; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Oxygen; Visual Pathways

Future Dementia Severity is Almost Entirely Explained by the Latent Variable δ's Intercept and Slope. - Palmer, Raymond F; Royall, Donald R (J Alzheimers Dis, 2016)
BACKGROUND: Structural equation models (SEM) can explicitly distinguish dementia-relevant variance in cognitive task performance. The resulting latent construct "δ" (for dementia) provides a relatively "error free" continuously varying dementia-specific phenotype. OBJECTIVE: To estimate δ's change over time (Δδ) and determine Δδ's predictive validity using future dementia status as an outcome. METHODS: Data from n = 2,191 participants of the Texas Alzheimer's Research and Care Consortium (TARCC) were used to construct a latent growth curve model of longitudinal change over four years using five cognitive measures and one measure of Instrumental Activities of Daily Living. Four final latent factors, including baseline δ and Δδ, were simultaneously entered as predictors of wave 4 dementia severity, as estimated by the Clinical Dementia Rating Scale "sum of boxes" (CDR). RESULTS: All observed measures exhibited significant change [χ2 = 1,152 (df = 229); CFI = 0.968; RMSEA = 0.043]. The final model demonstrated excellent fit to the data [χ2 = 543 (df = 245); CFI = 0.991; RMSEA = 0.023]. All latent indicator loadings were significant, yielding four distinct factors. After adjustment for demographic covariates and baseline CDR scores, d and Δd were significantly independently associated with CDR4, explaining 25% and 49% of its variance, respectively. The latent variable g' significantly explained 3% of CDR4 variance independently of d and Δd. Δg' was not significantly associated with CDR4. Baseline CDR explained 16% of CDR4 variance. CONCLUSIONS: Future dementia severity is almost entirely explained by the latent construct δ's intercept and slope.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognition; Cognitive Dysfunction; Factor Analysis, Statistical; Female; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Psychiatric Status Rating Scales

Genetic Counseling and Testing for Alzheimer's Disease and Frontotemporal Lobar Degeneration: An Italian Consensus Protocol. - Bocchetta, Martina; Mega, Anna; Bernardi, Livia; Di Maria, Emilio; Benussi, Luisa; Binetti, Giuliano; Borroni, Barbara; Colao, Rosanna; Di Fede, Giuseppe; Fostinelli, Silvia; Galimberti, Daniela; Gennarelli, Massimo; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Genetic testing of familial Alzheimer's disease (AD) and frontotemporal lobar degeneration (FTLD) is attracting interest thanks to innovative primary prevention clinical trials and increased request for information by at-risk individuals. However, ethical, social, and psychological implications are paramount and genetic testing must be supported by structured genetic counseling. In Italy, practice parameters and guidelines for genetic counseling in dementia are not available. OBJECTIVE: To develop a nationally harmonized protocol for genetic counseling and testing of familial AD and FTLD. METHODS: Activities were carried out in the context of the Italian Dominantly Inherited Alzheimer's and Frontotemporal Network (IT-DIAfN) project, a national network of centers of excellence with expertise in managing patients with familial AD and FTLD. A survey of the literature on genetic counseling protocols and guidelines was conducted. Local protocols for genetic counseling were surveyed. Differences and commonalities among protocols were identified and discussed among project partners. Consensus was reached following implicit aggregation methods. RESULTS: Consensus was reached on a protocol for patients with clinically diagnosed familial AD or FTLD and a distinct protocol for their at-risk relatives. Genetic counseling should be provided by a multidisciplinary team including a geneticist, a neurologist/geriatrician, and a psychologist/psychiatrist, according to the following schedule: (i) initial consultation with tailored information on the genetics of the dementias; (ii) clinical, psychological, and cognitive assessment; if deemed appropriate (iii) genetic testing following a structured decision tree for gene mutation search; (iv) genetic testing result disclosure; (v) psychological support follow-up. CONCLUSION: This genetic counseling protocol provides Italian centers with a line of shared practice for dealing with the requests for genetic testing for familial AD and FTLD from patients and at-risk relatives, who may also be eligible participants for novel prevention clinical trials.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Consensus; Female; Follow-Up Studies; Frontotemporal Lobar Degeneration; Genetic Counseling; Genetic Testing; Humans; Italy; Male; Peptide Fragments; Psychiatric Status Rating Scales

Genetic Influences on Plasma Homocysteine Levels in African Americans and Yoruba Nigerians. - Kim, Sungeun; Nho, Kwangsik; Ramanan, Vijay K; Lai, Dongbing; Foroud, Tatiana M; Lane, Katie; Murrell, Jill R; Gao, Sujuan; Hall, Kathleen S; Unverzagt, Frederick W; Baiyewu, Olusegun; Ogunniyi, Adesola; et al. (J Alzheimers Dis, 2016)
Plasma homocysteine, a metabolite involved in key cellular methylation processes seems to be implicated in cognitive functions and cardiovascular health with its high levels representing a potential modifiable risk factor for Alzheimer's disease (AD) and other dementias. A better understanding of the genetic factors regulating homocysteine levels, particularly in non-white populations, may help in risk stratification analyses of existing clinical trials and may point to novel targets for homocysteine-lowering therapy. To identify genetic influences on plasma homocysteine levels in individuals with African ancestry, we performed a targeted gene and pathway-based analysis using a priori biological information and then to identify new association performed a genome-wide association study. All analyses used combined data from the African American and Yoruba cohorts from the Indianapolis-Ibadan Dementia Project. Targeted analyses demonstrated significant associations of homocysteine and variants within the CBS (Cystathionine beta-Synthase) gene. We identified a novel genome-wide significant association of the AD risk gene CD2AP (CD2-associated protein) with plasma homocysteine levels in both cohorts. Minor allele (T) carriers of identified CD2AP variant (rs6940729) exhibited decreased homocysteine level. Pathway enrichment analysis identified several interesting pathways including the GABA receptor activation pathway. This is noteworthy given the known antagonistic effect of homocysteine on GABA receptors. These findings identify several new targets warranting further investigation in relation to the role of homocysteine in neurodegeneration.
Keywords: Adaptor Proteins, Signal Transducing; African Americans; African Continental Ancestry Group; Aged; Aged, 80 and over; Cohort Studies; Cystathionine beta-Synthase; Cytoskeletal Proteins; Female; Genetic Variation; Genome-Wide Association Study; Heterozygote; Homocysteine; Humans; Indiana; Longitudinal Studies; Male; Nigeria; Prospective Studies

Greater specificity for cerebrospinal fluid P-tau231 over P-tau181 in the differentiation of healthy controls from Alzheimer's disease. - Spiegel, Jonathan; Pirraglia, Elizabeth; Osorio, Ricardo S; Glodzik, Lidia; Li, Yi; Tsui, Wai; Saint Louis, Leslie A; Randall, Catherine; Butler, Tracy; Xu, Jinfeng; Zinkowski, Raymond P; Zetterberg, Henrik; et al. (J Alzheimers Dis, 2016)
Cerebrospinal fluid (CSF) measures of phosphorylated-tau (P-tau) 231 and P-tau181 are two biomarkers for the identification of tau pathology as related to Alzheimer's disease (AD). While both are pathologically validated, their relative diagnostic performances are not well known. This cross-sectional diagnostic study of 87 normal (NL) subjects and 28 AD subjects compared CSF P-tau231 with CSF P-tau181. Logistic regression modeling demonstrated that the P-tau231 was superior to the P-tau181 in the diagnostic classifications. At a fixed 85% sensitivity cutoff, the ROC analysis shows that P-tau231 has greater overall specificity than P-tau181. While both P-tau analytes demonstrated equivalent negative predictive accuracies, P-tau231 yielded significantly fewer false positives. Moreover, P-tau231, but not P-tau181, demonstrated sensitivity to the E4 genotype. A postmortem validation with 9 AD subjects confirmed the superiority of the CSF P-tau231 specificity. This study suggests that P-tau231 has the potential to improve the CSF tau biomarker diagnosis of AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Case-Control Studies; Cross-Sectional Studies; Female; Humans; Logistic Models; Male; Middle Aged; Phosphorylation; ROC Curve; Sensitivity and Specificity; tau Proteins

Greater than the Sum of Its Parts: δ can be Constructed from Item Level Data. - Royall, Donald R; Palmer, Raymond F; Matsuoka, Teruyuki; Kato, Yuka; Taniguchi, Shogo; Ogawa, Mayu; Fujimoto, Hiroshi; Okamura, Aiko; Shibata, Keisuke; Nakamura, Kaeko; Nakaaki, Shutaro; Koumi, Hiroyuki; et al. (J Alzheimers Dis, 2016)
"δ", a latent variable constructed from cognitive performance and functional status measures, can accurately diagnose dementia. The minimal assessment needed is unknown. We have constructed a δ homolog, "dTEXAS", from Telephone Executive Assessment Scale (TEXAS) items, and validated it in a convenience sample of Japanese persons (n = 176). dTEXAS scores correlated strongly with both Instrumental Activities of Daily Living (IADL) (r = -0.86, p <  0.001) and Clinical Dementia Rating Scale (CDR) (r = 0.71, p <  0.001). Constructed independently of their diagnoses, dTEXAS scores accurately distinguished dementia versus controls (area under the receiver operating curve [(AUC; ROC) = 0.92], dementia versus mild cognitive impairment (MCI) (AUC = 0.80) and controls versus MCI (AUC = 0.74). These AUCs are higher than those of multiple observed executive measures, as reported recently by Matsuoka et al., 2014. A dTEXAS score of -0.58 best discriminated between dementia versus controls with 90.1% sensitivity and 80.0% specificity.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Executive Function; Female; Humans; Japan; Male; Neuropsychological Tests; Psychiatric Status Rating Scales; ROC Curve; United States

GSK-3β is Dephosphorylated by PP2A in a Leu309 Methylation-Independent Manner. - Chu, Dandan; Tan, Jianxin; Xie, Shutao; Jin, Nana; Yin, Xiaomin; Gong, Cheng-Xin; Iqbal, Khalid; Liu, Fei (J Alzheimers Dis, 2016)
Hyperphosphorylation of tau is pivotally involved in the pathogenesis of Alzheimer's disease (AD) and related tauopathies. Glycogen synthase kinase-3β (GSK-3β) and protein phosphate 2A (PP2A) are crucial enzymes to regulate tau phosphorylation. GSK-3β activity is regulated by its inhibitory phosphorylation at Ser9. We previously reported the cross-talk between GSK-3β and PP2A signaling and showed that PP2A could dephosphorylate GSK-3β at Ser9. Here, we investigated the dephosphorylation of GSK-3β in brain extracts in the presence of phosphatase inhibitors and found that a PP2A-like phosphatase activity was required for dephosphorylation of GSK-3β at Ser9. PP2A interacted with GSK-3β and suppressed its Ser9 phosphorylation in vitro and in HEK-293FT cells. Activity of PP2A negatively correlated to the level of phosphorylated GSK-3β in kainic acid-induced excitotoxic mouse brain. Alteration of methylation of the catalytic subunit of PP2A (PP2Ac) at Leu309 did not affect GSK-3β phosphorylation. These findings suggest that Leu309 methylation is not required for PP2A to dephosphorylate GSK-3β at Ser9.
Keywords: Animals; Brain; Carboxylic Ester Hydrolases; Cell Line, Transformed; Dose-Response Relationship, Drug; Enzyme Inhibitors; Excitatory Amino Acid Agonists; Glycogen Synthase Kinase 3; Glycogen Synthase Kinase 3 beta; Humans; Kainic Acid; Leucine; Luminescent Proteins; Male; Methylation; Mice; Phosphorylation; Protein O-Methyltransferase; Protein Phosphatase 2; RNA, Small Interfering; Serine; tau Proteins

Gx-50 Inhibits Neuroinflammation via α7 nAChR Activation of the JAK2/STAT3 and PI3K/AKT Pathways. - Shi, Shi; Liang, Dongli; Bao, Min; Xie, Yilin; Xu, Wangjie; Wang, Lianyun; Wang, Zhaoxia; Qiao, Zhongdong (J Alzheimers Dis, 2016)
Recent studies have revealed that the α7 nicotinic acetylcholine receptor (α7 nAChR) is a critical link between inflammation and neurodegeneration, which is closely associated with Alzheimer's disease (AD). The JAK2/STAT3 and PI3K/AKT signaling pathways contribute to the neuroprotective and anti-inflammatory effects of α7nAChR. Our previous studies have shown that treatment with gx-50 improves cognitive function and is neuroprotective. Here, we investigated the effect of gx-50 on α7 nAChR and Aβ-induced inflammation in microglia. First, the binding affinity of gx-50 to α7 nAChR was examined using the fluorescence-based Octet RED system, and the expression of α7 nAChR was detected using real-time PCR and western blotting. We also investigated downstream events of α7 nAChR activity, including the translocation of p-STAT3 and the phosphorylation of JAK2, STAT3, PI3K, and AKT. Finally, the effect of gx-50 on Aβ-induced inflammation via α7 nAChR-mediated signaling pathways was investigated using cytokine assays. The results showed that gx-50 is able to act as a specific ligand to activate α7 nAChR, which then upregulates the JAK2/STAT3 and PI3K/AKT signaling pathways to inhibit the secretions of pro-inflammatory cytokines, such as IL-1β. In conclusion, the results suggest that gx-50 could inhibit the Aβ-induced inflammatory response in microglia via α7 nAChR activity, which might be a successful therapeutic target against AD.
Keywords: Acrylamides; alpha7 Nicotinic Acetylcholine Receptor; Amyloid beta-Peptides; Analysis of Variance; Animals; Anti-Inflammatory Agents; Cell Line, Transformed; Cytokines; Enzyme Inhibitors; Enzyme-Linked Immunosorbent Assay; Gene Expression Regulation; Janus Kinase 2; Mice; Microglia; Phosphatidylinositol 3-Kinases; Protein Binding; RNA, Messenger; Signal Transduction

Health-Related Quality of Life in Patients with Alzheimer's Disease in Different German Health Care Settings. - Heßmann, Philipp; Seeberg, Greta; Reese, Jens Peter; Dams, Judith; Baum, Erika; Müller, Matthias J; Dodel, Richard; Balzer-Geldsetzer, Monika (J Alzheimers Dis, 2016)
The purpose of this study is to evaluate the health-related quality of life (HrQoL) of patients with Alzheimer's disease (AD) in different care settings (institutionalized versus community-dwelling) across all severity stages of dementia. Patients were consecutively recruited with their primary caregivers (123 inpatients and 272 outpatients), and the impact of patient-related parameters such as behavioral and psychological symptoms of dementia (BPSD) (Geriatric Depression Scale [GDS] and Neuropsychiatric Inventory [NPI]) and functional capacity (Alzheimer's Disease Cooperative Study-Activities of Daily Living [ADCS-ADL]) on HrQoL was analyzed. Patients' HrQoL was assessed using self-reported and caregiver-rated generic (EuroQoL Instrument) and dementia-specific (Quality of Life-Alzheimer's Disease [Qol-AD]) scales. Patients reported a considerably higher HrQoL than their caregivers on the QoL-AD, EQ-5D, and EQ VAS (p <  0.001). Different dementia severity groups showed significantly worse results in HrQoL for patients with lower MMSE scores. The mean self-reported QoL-AD decreased from 32.3±5.7 in the group with the highest MMSE scores to 27.1±5.5 in patients with the lowest MMSE scores (p <  0.001). A considerably lower HrQoL was shown for institutionalized patients versus participants in outpatient settings (proxy-rated QoL-AD 19.7±4.6 versus 26.0±7.1, p <  0.001). Depressive symptoms (GDS), BPSD (NPI), and reduced functional capacity (ADCS-ADL) were evaluated for their impact on patients' HrQoL. Multivariate models explained between 22% and 54% of the variance in patients' HrQoL. To analyze the causative direction of the reported associations, further longitudinal studies should be conducted.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Caregivers; Depression; Female; Germany; Humans; Inpatients; Male; Multivariate Analysis; Neuropsychological Tests; Outpatients; Psychiatric Status Rating Scales; Quality of Life; Residential Facilities; Self Report; Severity of Illness Index

Heterogeneity of Cognitive Anosognosia and its Variation with the Severity of Dementia in Patients with Alzheimer's Disease. - Avondino, Emilie; Antoine, Pascal (J Alzheimers Dis, 2016)
Currently, the lack of awareness of deficits, i.e., anosognosia, is a major obstacle in the healthcare circuit that delays the diagnosis of Alzheimer's disease (AD). However, a clear framework is lacking in the literature related to this phenomenon in terms of its definition, mechanisms, and objects. The aim of this study is to assess the different levels of cognitive anosognosia using a prediction-performance procedure and to identify the potential correlates of these levels. A sample of patients with probable AD was divided into three groups according to the severity of dementia (mild (MiD), moderate (MoD), and moderately severe (MSD) dementia), ranked according to the results of the Mini-Mental State Examination. We observed the following three scores: the real score, the prediction score, and the anosognosia score. These scores were calculated based on the prediction-performance task MISAwareness from the Dementia Rating Scale for cognitive processes (i.e., Attention, Initiation, Conceptualization, Construction, and Memory). We obtained a strong plateau effect between the MiD and MoD groups for anosognosia scores for actual performance or prediction for both the level of overall functioning and for specific processes. The sole exception was the result for memory processes. Moreover, the profiles of the patients' responses on the Memory subscale were substantially different and, indeed, opposite from those for the other processes. The main results confirm the multidimensionality of anosognosia and its variability with the stage of dementia and specifically implicate memory processes that indicate a cleavage between memory and other cognitive functions.
Keywords: Agnosia; Alzheimer Disease; Attention; Chi-Square Distribution; Cognition Disorders; Dementia; Female; Humans; Male; Memory; Neuropsychological Tests; Predictive Value of Tests; Prospective Studies; Psychiatric Status Rating Scales; Severity of Illness Index

Hierarchical Distribution of the Tau Cytoskeletal Pathology in the Thalamus of Alzheimer's Disease Patients. - Rüb, Udo; Stratmann, Katharina; Heinsen, Helmut; Del Turco, Domenico; Ghebremedhin, Estifanos; Seidel, Kay; den Dunnen, Wilfred; Korf, Horst-Werner (J Alzheimers Dis, 2016)
In spite of considerable progress in neuropathological research on Alzheimer's disease (AD), knowledge regarding the exact pathoanatomical distribution of the tau cytoskeletal pathology in the thalamus of AD patients in the advanced Braak and Braak AD stages V or VI of the cortical cytoskeletal pathology is still fragmentary. Investigation of serial 100 μm-thick brain tissue sections through the thalamus of clinically diagnosed AD patients with Braak and Braak AD stage V or VI cytoskeletal pathologies immunostained with the anti-tau AT8 antibody, along with the affection of the extraterritorial reticular nucleus of the thalamus, reveals a consistent and severe tau immunoreactive cytoskeletal pathology in the limbic nuclei of the thalamus (e.g., paraventricular, anterodorsal and laterodorsal nuclei, limitans-suprageniculate complex). The thalamic nuclei integrated into the associative networks of the human brain (e.g., ventral anterior and mediodorsal nuclei) are only mildly affected, while its motor precerebellar (ventral lateral nucleus) and sensory nuclei (e.g., lateral and medial geniculate bodies, ventral posterior medial and lateral nuclei, parvocellular part of the ventral posterior medial nucleus) are more or less spared. The highly stereotypical and characteristic thalamic distribution pattern of the AD-related tau cytoskeletal pathology represents an anatomical mirror of the hierarchical topographic distribution of the cytoskeletal pathology in the interconnected regions of the cerebral cortex of AD patients. These pathoanatomical parallels support the pathophysiological concept of a transneuronal spread of the disease process of AD along anatomical pathways. The AD-related tau cytoskeletal pathology in the thalamus most likely contributes substantially to the neuropsychiatric disease symptoms (e.g., dementia), attention deficits, oculomotor dysfunctions, altered non-discriminative aspects of pain experience of AD patients, and the disruption of their waking and sleeping patterns.
Keywords: Alzheimer Disease; Cytoskeleton; Humans; tau Proteins; Thalamus

Higher Fasting Plasma Glucose Levels, within the Normal Range, are Associated with Decreased Processing Speed in High Functioning Young Elderly. - Raizes, Meytal; Elkana, Odelia; Franko, Motty; Ravona Springer, Ramit; Segev, Shlomo; Beeri, Michal Schnaider (J Alzheimers Dis, 2016)
We explored the association of plasma glucose levels within the normal range with processing speed in high functioning young elderly, free of type 2 diabetes mellitus (T2DM). A sample of 41 participants (mean age = 64.7, SD = 10; glucose 94.5 mg/dL, SD = 9.3), were examined with a computerized cognitive battery. Hierarchical linear regression analysis showed that higher plasma glucose levels, albeit within the normal range (<110 mg/dL), were associated with longer reaction times (p <  0.01). These findings suggest that even in the subclinical range and in the absence of T2DM, monitoring plasma glucose levels may have an impact on cognitive function.
Keywords: Aged; Blood Glucose; Cognition; Diabetes Mellitus, Type 2; Fasting; Female; Humans; Linear Models; Male; Middle Aged; Neuropsychological Tests; Psychomotor Performance; Reaction Time; Reference Values

Homotaurine Effects on Hippocampal Volume Loss and Episodic Memory in Amnestic Mild Cognitive Impairment. - Spalletta, Gianfranco; Cravello, Luca; Gianni, Walter; Piras, Federica; Iorio, Mariangela; Cacciari, Claudia; Casini, Anna Rosa; Chiapponi, Chiara; Sancesario, Giuseppe; Fratangeli, Claudia; Orfei, Maria Donata; Caltagirone, Carlo; et al. (J Alzheimers Dis, 2016)
Homotaurine supplementation may have a positive effect on early Alzheimer's disease. Here, we investigated its potential neuroprotective effect on the hippocampus structure and episodic memory performances in amnestic mild cognitive impairment (aMCI). Neuropsychological, clinical, and neuroimaging assessment in 11 treated and 22 untreated patients were performed at baseline and after 1 year. Magnetic resonance data were analyzed using voxel-based morphometry to explore significant differences (Family Wise Error corrected) between the two groups over time. Patients treated with homotaurine showed decreased volume loss in the left and right hippocampal tail, left and right fusiform gyrus, and right inferior temporal cortex which was associated with improved short-term episodic memory performance as measured by the recency effect of the Rey 15-word list learning test immediate recall. Thus, homotaurine supplementation in individuals with aMCI has a positive effect on hippocampus atrophy and episodic memory loss. Future studies should further clarify the mechanisms of its effects on brain morphometry.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Chi-Square Distribution; Cognitive Dysfunction; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Longitudinal Studies; Magnetic Resonance Imaging; Male; Memory, Episodic; Mental Status Schedule; Middle Aged; Neuroprotective Agents; Neuropsychological Tests; Taurine

Hyperactivity with Agitative-Like Behavior in a Mouse Tauopathy Model. - Jul, Pia; Volbracht, Christiane; de Jong, Inge E M; Helboe, Lone; Elvang, Anders Brandt; Pedersen, Jan Torleif (J Alzheimers Dis, 2016)
Tauopathies, such as Alzheimer's disease (AD) and frontotemporal dementia (FTD), are characterized by formation of neurofibrillary tangles consisting of hyperphosphorylated tau. In addition to memory loss, patients experience behavioral symptoms such as agitation, aggression, depression, and insomnia. We explored the behavioral phenotype of a mouse model (rTg4510) carrying the human tau P301L mutation found in a familial form of FTD. We tested these mice in locomotor activity assays as well as in the Morris water maze to access spatial memory. In addition to cognitive impairments, rTg4510 mice exhibited a hyperactivity phenotype which correlated with progression of tau pathology and was dependent on P301L tau transgene expression. The hyperactive phenotype was characterized by significantly increased locomotor activity in a novel and in a simulated home cage environment together with a disturbed day/night cycle. The P301L-tau-dependent hyperactivity and agitative-like phenotype suggests that these mice may form a correlate to some of the behavioral disturbances observed in advanced AD and FTD.
Keywords: Age Factors; Analysis of Variance; Animals; Brain; Cognition Disorders; Disease Models, Animal; Doxycycline; Exploratory Behavior; Humans; Hyperkinesis; Male; Maze Learning; Mice; Mice, Transgenic; Motor Activity; Mutation; Psychomotor Agitation; tau Proteins; Tauopathies; Time Factors

"I Don't Think Of It As An Illness": Illness Representations in Mild to Moderate Dementia. - Clare, Linda; Quinn, Catherine; Jones, Ian Rees; Woods, Robert T (J Alzheimers Dis, 2016)
The self-regulatory model proposes that illness representations influence adjustment and coping in chronic conditions. Better understanding of the illness representations held by people with dementia could help with targeting information and support so as to optimize adjustment and coping. In this mixed-methods study of illness representations among people with mild to moderate Alzheimer's, vascular, or mixed dementia we aimed to clarify the nature of the representations held, to determine whether specific profiles can be identified based on perceptions of the identity and cause of the condition, and to examine associations between these profiles and other participant characteristics. Data were collected in the second wave of the Memory Impairment and Dementia Awareness Study (MIDAS). Sixty-four people with dementia, who had been told their diagnosis at a memory clinic, completed interviews and responded to questionnaires. In each case a carer was also interviewed. Cluster analysis based on responses about identity and cause identified three profiles. 'Illness' cluster participants saw themselves as living with an illness and used diagnostic labels, 'ageing' cluster participants did not use diagnostic labels and viewed their difficulties as related to ageing, and 'no problem' cluster participants considered that they did not have any difficulties. 'Illness' cluster participants had better cognition and better awareness, but lower mood, and perceived more practical consequences, than 'ageing' cluster participants. Holding an 'illness' model may not be advantageous. Rather than encouraging adoption of such a model, it may be preferable to target information and select interventions in line with the person's representation profile.
Keywords: Adaptation, Psychological; Aged; Aged, 80 and over; Aging; Awareness; Caregivers; Dementia; Female; Follow-Up Studies; Humans; Male; Middle Aged; Psychiatric Status Rating Scales; Residence Characteristics; Self Concept; Statistics, Nonparametric; Surveys and Questionnaires

Impact of Depressive Symptoms on Conversion from Mild Cognitive Impairment Subtypes to Alzheimer's Disease: A Community-Based Longitudinal Study. - Kida, Jiro; Nemoto, Kiyotaka; Ikejima, Chiaki; Bun, Shogyoku; Kakuma, Tatsuyuki; Mizukami, Katsuyoshi; Asada, Takashi (J Alzheimers Dis, 2016)
BACKGROUND: While longitudinal studies have investigated the relationships between mild cognitive impairment (MCI) subtypes and dementia subtypes, the results have been contradictory. In addition, some research shows that depression accompanied by MCI might increase the risk of Alzheimer's disease (AD). OBJECTIVE: The aim of this study is to longitudinally investigate the relationships between MCI subtypes and dementia subtypes, with special attention to the effect of comorbid depressive symptoms in a Japanese rural community. METHODS: Non-demented participants (n = 802) completed a baseline and follow-up study. Outcomes were conversion to dementia especially AD, MCI, or no conversion. A complementary log-log analysis was conducted to investigate the risk of dementia and AD in amnestic MCI (aMCI) compared to nonamnestic MCI (naMCI) groups. The impact of depressive symptoms on the transition from MCI to AD and from cognitively normal to MCI or AD was also analyzed. RESULTS: The risk of developing dementia, in particular AD, for the aMCI group was significantly higher than that for the naMCI group. In the aMCI group, the presence of depressive symptoms increased the risk of developing AD, but depressive symptoms in the naMCI group did not. In the cognitively normal group, the presence of depressive symptoms increased the risk of aMCI but not naMCI or AD. CONCLUSION: MCI subtyping could be useful in finding a prodrome for dementia and in particular for AD. The differing impacts of depressive symptoms on the development of AD suggest that the relationship between depressive symptoms and cognitive impairment could differ in aMCI and naMCI patients.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Cognitive Dysfunction; Depression; Disease Progression; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Prodromal Symptoms; Prognosis; Risk

Impact of Omega-3 Fatty Acid Supplementation on Memory Functions in Healthy Older Adults. - Külzow, Nadine; Witte, A Veronica; Kerti, Lucia; Grittner, Ulrike; Schuchardt, Jan Philipp; Hahn, Andreas; Flöel, Agnes (J Alzheimers Dis, 2016)
As the process of Alzheimer's disease (AD) begins years before disease onset, searching for prevention strategies is of major medical and economic importance. Nutritional supplementation with long-chain polyunsaturated omega-3 fatty acids (LC-n3-FA) may exert beneficial effects on brain structure and function. However, experimental evidence in older adults without clinical dementia is inconsistent, possibly due to low sensitivity of previously employed test batteries for detecting subtle improvements in cognition in healthy individuals. Here we used LOCATO, recently described as a robust and sensitive tool for assessing object-location memory (OLM) in older adults, to evaluate the impact of LC-n3-FA supplementation on learning and memory formation. In a double-blind placebo-controlled proof-of-concept study, 44 (20 female) cognitively healthy individuals aged 50-75 years received either LC-n3-FA (2,200 mg/day, n = 22) or placebo (n = 22) for 26 weeks. Before and after intervention, memory performance in the OLM-task (primary) was tested. As secondary outcome parameters, performance in Rey Auditory Verbal Learning Test (AVLT), dietary habits, omega-3-index, and other blood-derived parameters were assessed. Omega-3 index increased significantly in the LC-n3-FA group compared with the placebo group. Moreover, recall of object locations was significantly better after LC-n3-FA supplementation compared with placebo. Performance in the AVLT was not significantly affected by LC-n3-FA. This double-blind placebo-controlled proof-of-concept study provides further experimental evidence that LC-n3-FA exert positive effects on memory functions in healthy older adults. Our findings suggest novel strategies to maintain cognitive functions into old age.
Keywords: Aged; Apolipoproteins E; Auditory Perception; Blood Chemical Analysis; Cognitive Aging; Dietary Supplements; Double-Blind Method; Fatty Acids, Omega-3; Feeding Behavior; Female; Humans; Learning; Male; Memory; Middle Aged; Neuropsychological Tests; Nootropic Agents; Treatment Outcome

Impacts of High Serum Total Cholesterol Level on Brain Functional Connectivity in Non-Demented Elderly. - Zhang, Ting; Li, He; Zhang, Junying; Li, Xin; Qi, Di; Wang, Nuo; Zhang, Zhanjun (J Alzheimers Dis, 2016)
Epidemiological and clinical studies suggest that high serum cholesterol is a risk factor of dementia. However, the effects of cholesterol on cognition and brain remain largely unclear. This study aims to investigate the associations between serum total cholesterol (TC) and neuropsychological performance, and intrinsic functional networks in non-demented elderly. Among a cohort of 120 community-dwelling Beijing residents, 29 subjects in the high-TC group (1st quartile) and 31 in the low-TC group (4th quartile) were included in this study, and underwent a battery of neuropsychological tests and magnetic resonance imaging (MRI) scans, including T2- and T1-weighted imaging, and resting-state functional MRI. No significant group difference was found in any of the neuropsychological tests used. Stronger connectivity in the default mode network was observed in the high-TC group compared to that in the low-TC group (p <  0.001, uncorrected). While in the salience network (SN), the high-TC group showed lower connectivity in the anterior cingulate cortex and frontal regions, compared to the low-TC group (p <  0.05, FWE corrected). Our findings suggest that in non-demented elderly persons, high serum cholesterol is associated with disruption of functional connectivity in the SN. The results not only deepen our understanding of how cholesterol affects the brain, but are also significant for selecting sensitive indicators for monitoring the impairments of cholesterol on the neural system.
Keywords: Aged; Brain; Brain Mapping; Cholesterol; Cognition; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Nerve Net; Neuropsychological Tests

Impaired Autophagy in APOE4 Astrocytes. - Simonovitch, Shira; Schmukler, Eran; Bespalko, Alina; Iram, Tal; Frenkel, Dan; Holtzman, David M; Masliah, Eliezer; Michaelson, Danny M; Pinkas-Kramarski, Ronit (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is the most prevalent form of dementia in elderly. Genetic studies revealed allelic segregation of the apolipoprotein E (ApoE) gene in sporadic AD and in families with higher risk of AD. The mechanisms underlying the pathological effects of ApoE4 are not yet entirely clear. Several studies indicate that autophagy, which plays an important role in degradation pathways of proteins, organelles and protein aggregates, may be impaired in AD. In the present study, we investigated the effects of ApoE4 versus the ApoE3 isoform on the process of autophagy in mouse-derived astrocytes. The results obtained reveal that under several autophagy-inducing conditions, astrocytes expressing ApoE4 exhibit lower autophagic flux compared to astrocytes expressing ApoE3. Using an in situ model, we examined the role of autophagy and the effects thereon of ApoE4 in the elimination of Aβ plaques from isolated brain sections of transgenic 5xFAD mice. This revealed that ApoE4 astrocytes eliminate Aβ plaques less effectively than the corresponding ApoE3 astrocytes. Additional experiments showed that the autophagy inducer, rapamycin, enhances Aβ plaque degradation by ApoE4 astrocytes whereas the autophagy inhibitor, chloroquine, blocks Aβ plaque degradation by ApoE3 astrocytes. Taken together, these findings show that ApoE4 impairs autophagy in astrocyte cultures and that this effect is associated with reduced capacity to clear Aβ plaques. This suggests that impaired autophagy may play a role in mediating the pathological effects of ApoE4 in AD.
Keywords: Amyloid beta-Peptides; Animals; Apolipoprotein E3; Apolipoprotein E4; Astrocytes; Autophagy; Brain; Cells, Cultured; Central Nervous System Agents; Chloroquine; Disease Models, Animal; Humans; Mice, Transgenic; Plaque, Amyloid; Sirolimus; Time Factors

Impaired Parahippocampus Connectivity in Mild Cognitive Impairment and Alzheimer's Disease. - Liu, Jieqiong; Zhang, Xinqing; Yu, Chunshui; Duan, Yunyun; Zhuo, Junjie; Cui, Yue; Liu, Bing; Li, Kuncheng; Jiang, Tianzi; Liu, Yong (J Alzheimers Dis, 2016)
BACKGROUND: The parahippocampal gyrus (PHG) is an important region of the limbic system that plays an important role in episodic memory. Elucidation of the PHG connectivity pattern will aid in the understanding of memory deficits in neurodegenerative diseases. OBJECTIVE: To investigate if disease severity associated altered PHG connectivity in Alzheimer's disease (AD) exists. METHODS: We evaluated resting-state functional magnetic resonance imaging data from 18 patients with amnestic mild cognitive impairment (MCI), 35 patients with AD, and 21 controls. The PHG connectivity pattern was examined by calculating Pearson's correlation coefficients between the bilateral PHG and whole brain. Group comparisons were performed after controlling for the effects of age and gender. The functional connectivity strength in each identified region was correlated with the MMSE score to evaluate the relationship between connectivity and cognitive ability. RESULTS: Several brain regions of the default mode network showed reduced PHG connectivity in the AD patients, and PHG connectivity was associated with disease severity in the MCI and AD subjects. More importantly, correlation analyses showed that there were positive correlations between the connectivity strengths of the left PHG-PCC/Pcu and left PHG-left MTG and the Mini-Mental State Examination, indicating that with disease progression from MCI to severe AD, damage to the functional connectivity of the PHG becomes increasingly severe. CONCLUSIONS: These results indicate that disease severity is associated with altered PHG connectivity, contributing to knowledge about the reduction in cognitive ability and impaired brain activity that occur in AD/MCI. These early changes in the functional connectivity of the PHG might provide some potential clues for identification of imaging markers for the early detection of MCI and AD.
Keywords: Aged; Alzheimer Disease; Apolipoproteins E; Brain Mapping; Cognitive Dysfunction; Female; Hippocampus; Humans; Limbic System; Magnetic Resonance Imaging; Male; Mental Status Schedule; Neural Pathways; Rest; Severity of Illness Index

The Incidence of Benzodiazepine and Related Drug Use in Persons with and without Alzheimer's Disease. - Saarelainen, Laura; Taipale, Heidi; Koponen, Marjaana; Tanskanen, Antti; Tolppanen, Anna-Maija; Tiihonen, Jari; Hartikainen, Sirpa (J Alzheimers Dis, 2016)
BACKGROUND: Benzodiazepines and related drugs (BZDR) are occasionally used to treat certain symptoms of Alzheimer's disease (AD). However, the risks related to BZDR use are high in older persons. Although frequent BZDR use has been reported in persons with AD, no previous study has focused specifically on the incidence of BZDR use in this population. OBJECTIVE: We investigated the incidence of BZDR use in persons with and without AD during a five-year follow-up. METHODS: The Finnish nationwide, register-based MEDALZ cohort includes all AD cases who received a clinically verified AD diagnosis in 2005-2011 (n = 70,718) and their matched comparison persons. Incidence of BZDR, including benzodiazepines (lorazepam, oxazepam, temazepam, alprazolam, chlordiazepoxide, diazepam, and nitrazepam) and Z-drugs (zolpidem and zopiclone), use was investigated in the cohort from two years before to three years after the diagnosis of AD. Further, initial BZDRs were investigated. RESULTS: The incidence of BZDR use was higher in persons with AD starting from 12 months before the diagnosis and peaked at six months after the diagnosis of AD (incidence rate ratio [IRR] = 2.6, 95% confidence interval [CI] = 2.5-2.8). Benzodiazepines were more frequently initiated by persons with AD, with the incidence peaking at six months after the diagnosis (IRR = 4.5, 95% CI = 4.1-4.9) and remaining over three times higher than in comparison persons until three years after the diagnosis. CONCLUSION: Early symptomatic treatment with BZDRs is contrary to AD treatment guidelines. As BZDRs impair cognition, the observed early treatment with BZDRs may complicate the monitoring of AD treatment effectiveness.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Alzheimer Disease; Antipsychotic Agents; Benzodiazepines; Cohort Studies; Female; Finland; Humans; Incidence; Male; Middle Aged; Substance-Related Disorders

Increase of α-Secretase ADAM10 in Platelets Along Cognitively Healthy Aging. - Schuck, Florian; Wolf, Dominik; Fellgiebel, Andreas; Endres, Kristina (J Alzheimers Dis, 2016)
ADAM10 is one of the key players in ectodomain-shedding of the amyloid-β protein precursor (AβPP). Previous research with postmortem tissue has shown reduced expression and activity of ADAM10 within the central nervous system (CNS) of Alzheimer's disease (AD) patients. Determination of cerebral ADAM10 in living humans is hampered by its transmembrane property; only the physiological AβPP cleavage product generated by ADAM10, sAβPPα, can be assessed in cerebrospinal fluid. Establishment of surrogate markers in easily accessible material therefore is crucial. It has been demonstrated that ADAM10 is expressed in platelets and that platelet amount is decreased in AD patients. Just recently it has been shown that platelet ADAM10 and cognitive performance of AD patients positively correlate. In contrast to AD patients, to our knowledge almost no information has been published regarding ADAM10 expression during normal aging. We investigated ADAM10 amount and activity in platelets of cognitively healthy individuals from three different age groups ranging from 22-85 years. Interestingly, we observed an age-dependent increase in ADAM10 levels and activity in platelets.
Keywords: ADAM Proteins; ADAM10 Protein; Adult; Age Factors; Aged; Aged, 80 and over; Aging; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Analysis of Variance; Apolipoprotein E4; Cognition; Female; Healthy Volunteers; Humans; Integrin beta3; Male; Membrane Proteins; Middle Aged; Neuropsychological Tests; Young Adult

Increased Electron Paramagnetic Resonance Signal Correlates with Mitochondrial Dysfunction and Oxidative Stress in an Alzheimer's disease Mouse Brain. - Fang, Du; Zhang, Zhihua; Li, Hang; Yu, Qing; Douglas, Justin T; Bratasz, Anna; Kuppusamy, Periannan; Yan, Shirley ShiDu (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a progressive neurodegenerative disease characterized clinically by cognitive decline and memory loss. The pathological features are amyloid-β peptide (Aβ) plaques and intracellular neurofibrillary tangles. Many studies have suggested that oxidative damage induced by reactive oxygen species (ROS) is an important mechanism for AD progression. Our recent study demonstrated that oxidative stress could further impair mitochondrial function. In the present study, we adopted a transgenic mouse model of AD (mAPP, overexpressing AβPP/Aβ in neurons) and performed redox measurements using in vivo electron paramagnetic resonance (EPR) imaging with methoxycarbamyl-proxyl (MCP) as a redox-sensitive probe for studying oxidative stress in an early stage of pathology in a transgenic AD mouse model. Through assessing oxidative stress, mitochondrial function and cognitive behaviors of mAPP mice at the age of 8-9 months, we found that oxidative stress and mitochondrial dysfunction appeared in the early onset of AD. Increased ROS levels were associated with defects of mitochondrial and cognitive dysfunction. Notably, the in vivo EPR method offers a unique way of assessing tissue oxidative stress in living animals under noninvasive conditions, and thus holds a potential for early diagnosis and monitoring the progression of AD.
Keywords: Adenosine Triphosphate; Age of Onset; Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Brain; Cognition; Disease Models, Animal; Electron Spin Resonance Spectroscopy; Electron Transport Complex IV; Female; Humans; Male; Maze Learning; Mice, Transgenic; Mitochondria; Oxidative Stress; Reactive Oxygen Species; Spatial Memory

Increased Intrinsic Activity of Medial-Temporal Lobe Subregions is Associated with Decreased Cortical Thickness of Medial-Parietal Areas in Patients with Alzheimer's Disease Dementia. - Pasquini, Lorenzo; Scherr, Martin; Tahmasian, Masoud; Myers, Nicholas E; Ortner, Marion; Kurz, Alexander; Förstl, Hans; Zimmer, Claus; Grimmer, Timo; Akhrif, Atae; Wohlschläger, Afra M; Riedl, Valentin; et al. (J Alzheimers Dis, 2016)
In Alzheimer's disease (AD), disrupted connectivity between medial-parietal cortices and medial-temporal lobes (MTL) is linked with increased MTL local functional connectivity, and parietal atrophy is associated with increased MTL memory activation. We hypothesized that intrinsic activity in MTL subregions is increased and associated with medial-parietal degeneration and impaired memory in AD. To test this hypothesis, resting-state-functional and structural-MRI was assessed in 22 healthy controls, 22 mild cognitive impairment patients, and 21 AD-dementia patients. Intrinsic activity was measured by power-spectrum density of blood-oxygenation-level-dependent signal, medial-parietal degeneration by cortical thinning. In AD-dementia patients, intrinsic activity was increased for several right MTL subregions. Raised intrinsic activity in dentate gyrus and cornu ammonis 1 was associated with cortical thinning in posterior cingulate cortices, and at-trend with impaired delayed recall. Critically, increased intrinsic activity in the right entorhinal cortex was associated with ipsilateral posterior cingulate degeneration. Our results provide evidence that in AD, intrinsic activity in MTL subregions is increased and associated with medial-parietal atrophy. Results fit a model in which medial-parietal degeneration contributes to MTL dysconnectivity from medial-parietal cortices, potentially underpinning disinhibition-like changes in MTL activity.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Memory Disorders; Middle Aged; Nerve Net; Parietal Lobe; Temporal Lobe

Increased Total Homocysteine Levels Predict the Risk of Incident Dementia Independent of Cerebral Small-Vessel Diseases and Vascular Risk Factors. - Miwa, Kaori; Tanaka, Makiko; Okazaki, Shuhei; Yagita, Yoshiki; Sakaguchi, Manabu; Mochizuki, Hideki; Kitagawa, Kazuo (J Alzheimers Dis, 2016)
BACKGROUND: Homocysteine has been identified as a potential risk factor for stroke, cerebral small-vessel diseases (SVD), and dementia. OBJECTIVE: The present study aimed to investigate the predictive value of homocysteine levels on incident dementia while simultaneously controlling for MRI findings and vascular risk factors. METHODS: Within a Japanese cohort of participants with vascular risk factors in an observational study, we evaluated the association between baseline total homocysteine (tHcy) levels (per 1 μmol/L and the tertile of tHcy), the prevalence of MRI-findings at baseline, and incident all-cause dementia. Baseline brain MRI was used to determine SVD (lacunas, white matter hyperintensities, and cerebral microbleeds [CMBs]) and atrophy (medial-temporal lobe atrophy and bicaudate ratio). Logistic regression analyses were used to estimate the cross-sectional association between tHcy and each of MRI findings. Cox proportional hazards analyses were performed to estimate the longitudinal association between tHcy and dementia. RESULTS: In the 643 subjects (age: 67.2 ± 8.4 years, male: 59% ; education: 12.9 ± 2.6 years), multivariable analyses adjusted for several potential confounders, including estimated glomerular filtration rate (eGFR) and intima-media thickness, showed that highest tHcy tertile was associated with lacunas, CMBs, and strictly deep CMBs. During the mean 7.3-year follow-up (range: 2-13), 47 patients were diagnosed with dementia (Alzheimer's disease: 24; vascular dementia: 18; mixed-type: 3; other: 2). After adjusting for age, gender, APOE ɛ4, education, BMI, MMSE, hypertension, cerebrovascular events, eGFR, and MRI-findings, tHcy level (hazard ratios [HR]: 1.08, p = 0.043) and the highest tertile of tHcy (HR: 2.50, p = 0.047) for all-cause dementia remained significant. CONCLUSIONS: Our results provide additional evidence of tHcy that contributes to increased susceptibility to dementia risk.
Keywords: Aged; Carotid Intima-Media Thickness; Cerebral Small Vessel Diseases; Dementia; Female; Homocysteine; Humans; Incidence; Longitudinal Studies; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Predictive Value of Tests; Proportional Hazards Models; Risk Factors; Statistics, Nonparametric

Influence of Incipient Dementia on Hospitalization for Primary Care Sensitive Conditions: A Population-Based Cohort Study. - Pimouguet, Clément; Rizzuto, Debora; Fastbom, Johan; Lagergren, Mårten; Fratiglioni, Laura; Xu, Weili (J Alzheimers Dis, 2016)
BACKGROUND: Studies have reported that moderate/severe stages of dementia are linked to increased hospitalization rates, but little is known about the influence of incipient dementia on hospitalizations for primary care sensitive conditions (PCSCs). OBJECTIVE: To examine the associations between incipient dementia and hospitalization outcomes, including all-cause and PCSC hospitalization. METHODS: A total of 2,268 dementia-free participants in the Swedish National study on Aging and Care-Kungsholmen were interviewed and clinically examined at baseline. Participants aged ≥78 years were followed for 3 years, and those aged 60-72 years, for 6 years. Number of hospitalizations was retrieved from the National Patient Register. Dementia was diagnosed in accordance with Diagnostic and Statistical Manual of Mental Disorders-IV criteria. Hospitalization outcomes were compared in participants who did and did not develop dementia. Zero-inflated Poisson regressions and logistic regressions were used in data analysis. RESULTS: During the follow-up, 175 participants developed dementia. The unadjusted PCSC admission rate was 88.2 per 1000 person-years in those who developed dementia and 25.6 per 1000 person-years in those who did not. In the fully adjusted logistic regression model, incipient dementia was associated with an increased risk of hospitalization for PCSCs (OR = 2.3, 95% CI 1.3-3.9) but not with the number of hospitalizations or with all-cause hospitalization. Risks for hospitalization for diabetes, congestive heart failure, and pyelonephritis were higher in those who developed dementia than in those who did not. About 10% participants had a PCSC hospitalization attributable to incipient dementia. CONCLUSION: People with incipient dementia are more prone to hospitalization for PCSCs but not to all-cause hospitalization.
Keywords: Acute Disease; Age Factors; Aged; Aged, 80 and over; Chronic Disease; Dementia; Female; Follow-Up Studies; Hospitalization; Humans; Logistic Models; Longitudinal Studies; Male; Primary Health Care; Registries; Risk; Sensitivity and Specificity; Socioeconomic Factors; Sweden

Inhibition of Cholesterol Biosynthesis Reduces γ-Secretase Activity and Amyloid-β Generation. - Kim, Yoonhee; Kim, Chaeyoung; Jang, Hye Young; Mook-Jung, Inhee (J Alzheimers Dis, 2016)
Amyloid-β (Aβ) is one of major molecules contributing to the pathogenesis of Alzheimer's disease (AD). Aβ is derived from amyloid-β protein precursor (AβPP) through sequential cleavages by β- and γ-secretases. Regulation of these components is thought to be an important factor in Aβ generation during the pathogenesis of AD. AβPP, β-secretase, and γ-secretase reside in lipid rafts, where cholesterol regulates the integrity and flexibility of membrane proteins and Aβ is generated. However, the relationship between cholesterol and Aβ generation is controversial. In this study, we aimed to elucidate the direct effects of cholesterol depletion on AβPP processing using AY9944, which blocks the last step of cholesterol biosynthesis and thus minimizes the unknown side effects of upstream inhibitors, such as HMG-CoA reductase inhibitors. Treatment with AY9944 decreased γ-secretase activity and Aβ generation. These results suggested that changes in membrane composition by lowering cholesterol with AY9944 affected γ-secretase activity and Aβ generation, which is associated with AD pathogenesis.
Keywords: Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Analysis of Variance; Animals; Anticholesteremic Agents; Cell Line; Cholesterol; Cricetinae; Down-Regulation; Humans; In Situ Nick-End Labeling; Luminescent Proteins; Membrane Glycoproteins; Membrane Microdomains; Mutation; Presenilin-1; Protein Transport; trans-1,4-Bis(2-chlorobenzaminomethyl)cyclohexane Dihydrochloride; Transfection

Integrating Biomarkers for Underlying Alzheimer's Disease in Mild Cognitive Impairment in Daily Practice: Comparison of a Clinical Decision Support System with Individual Biomarkers. - Rhodius-Meester, Hanneke F M; Koikkalainen, Juha; Mattila, Jussi; Teunissen, Charlotte E; Barkhof, Frederik; Lemstra, Afina W; Scheltens, Philip; Lötjönen, Jyrki; van der Flier, Wiesje M (J Alzheimers Dis, 2016)
BACKGROUND: Recent criteria allow biomarkers to provide evidence of Alzheimer's disease (AD) pathophysiology. How they should be implemented in daily practice remains unclear, especially in mild cognitive impairment (MCI) patients. OBJECTIVE: We evaluated how a clinical decision support system such as the PredictAD tool can aid clinicians to integrate biomarker evidence to support AD diagnosis. METHODS: With available data on demographics, cerebrospinal fluid (CSF), and MRI, we trained the PredictAD tool on a reference population of 246 controls and 491 AD patients. We then applied the identified algorithm to 211 MCI patients. For comparison, we also classified patients based on individual biomarkers (MRI; CSF) and the NIA-AA criteria. Progression to dementia was used as outcome measure. RESULTS: After a median follow up of 3 years, 72 (34%) MCI patients remained stable and 139 (66%) progressed to AD. The PredictAD tool assigned a likelihood of underlying AD to each patient (AUC 0.82). Excluding patients with missing data resulted in an AUC of 0.87. According to the NIA-AA criteria, half of the MCI patients had uninformative biomarkers, precluding an assignment of AD likelihood. A minority (41%) was assigned to high or low AD likelihood with good predictive value. The individual biomarkers showed best value for CSF total tau (AUC 0.86). CONCLUSION: The ability of the PredictAD tool to identify AD pathophysiology was comparable to individual biomarkers. The PredictAD tool has the advantage that it assigns likelihood to all patients, regardless of missing or conflicting data, allowing clinicians to integrate biomarker data in daily practice.
Keywords: Aged; Aged, 80 and over; Algorithms; Alzheimer Disease; Area Under Curve; Biomarkers; Cognitive Dysfunction; Cohort Studies; Decision Support Systems, Clinical; Disease Progression; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Outcome Assessment (Health Care); Predictive Value of Tests

Intranasal TAT-haFGF Improves Cognition and Amyloid-β Pathology in an AβPP/PS1 Mouse Model of Alzheimer's Disease. - Lou, Guofeng; Zhang, Qihao; Xiao, Fei; Xiang, Qi; Su, Zhijian; Huang, Yadong (J Alzheimers Dis, 2016)
Neurotoxic amyloid-β (Aβ) peptide causing cognitive function disabilities is one of the most characteristic pathological features in Alzheimer's disease (AD). A novel fusion protein, TAT-haFGF, was administrated to AβPP/PS1 transgenic mice by intravenous (IV) injection and intranasal (IN) delivery, respectively, for 5 weeks to compare the pharmacodynamics between the two routes of administration. Our results showed that IN administration of TAT-haFGF improved cognition and reduced Aβ plaques more significantly in AβPP/PS1 mice, when compared with IV injection. Our new findings suggest that TAT-haFGF might be a promising new therapy to attenuate AD pathological process.
Keywords: Administration, Intranasal; Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Brain; Cognition Disorders; Disease Models, Animal; Fibroblast Growth Factors; Gene Products, tat; Humans; Injections, Intraventricular; Maze Learning; Mice; Mice, Inbred C57BL; Mice, Transgenic; Movement; Mutation; Peptide Fragments; Plaque, Amyloid; Presenilin-1

Iron Regulates Apolipoprotein E Expression and Secretion in Neurons and Astrocytes. - Xu, He; Perreau, Victoria M; Dent, Krista A; Bush, Ashley I; Finkelstein, David I; Adlard, Paul A (J Alzheimers Dis, 2016)
BACKGROUND: There is strong evidence that iron homeostasis is impaired in the aging and Alzheimer's disease (AD) brain and that this contributes to neurodegeneration. Apolipoprotein E (APOE) has been identified as the strongest genetic risk factor for AD. However, the interaction between the two has yet to be fully explored. OBJECTIVE: This study aimed to investigate the relationship between exogenous iron levels and ApoE in neurons and astrocytes. METHODS: Our study used primary cultured cortical neurons and astrocytes to investigate the changes in ApoE caused by iron. Western blot and RT-PCR were used to measure ApoE. RESULTS: We observed that iron upregulated intracellular ApoE levels in both neurons and astrocytes at the post-transcriptional and transcriptional level, respectively. However, there was less full-length ApoE secreted by neurons and astrocytes after iron treatment. We speculate that this might impair brain lipid metabolism and amyloid-β clearance. In terms of ApoE receptors, we observed that neuronal LRP-1 levels were increased by the addition of exogenous iron, which could contribute to AβPP endocytosis in neurons. However, there were no significant changes in neuronal LDLR, astrocyte LDLR, or astrocyte LRP-1. CONCLUSION: Our study reveals that iron may contribute to the pathogenesis of AD by affecting ApoE and its receptors and supports the notion that iron chelation should be investigated as a therapeutic strategy for AD.
Keywords: Amyloid beta-Peptides; Animals; Apolipoproteins E; Astrocytes; Blotting, Western; Cell Survival; Cells, Cultured; Cerebral Cortex; Copper; Ferritins; Immunohistochemistry; Iron; Mice, Inbred C57BL; Neurons; Polymerase Chain Reaction; Reactive Oxygen Species; Receptors, LDL; RNA, Messenger; Tumor Suppressor Proteins; Zinc

Japanese Care Location and Medical Procedures for People with Dementia in the Last Month of Life. - Nakanishi, Miharu; Nakashima, Taeko; Shindo, Yumi; Niimura, Junko; Nishida, Atsushi (J Alzheimers Dis, 2016)
BACKGROUND: Dementia-related societies worldwide have called for palliative end-of-life care for those suffering dementia; meanwhile, the Japanese dementia plan was revised on January 2015 to introduce into its objectives the support for end-of-life care via increased social and health care collaboration. OBJECTIVE: The study focus was the use of medical procedures in the last month of life among dementia patients in different care locations in Japan. METHODS: This study was conducted using a retrospective study design. Data from the Survey of Institutions and Establishments for Long-Term Care, which is a nationally representative cross-sectional survey of the public long-term care insurance services, were used. The 6,148 patients who received end-of-life care in their own home, nursing homes, or hospitals in September 2007, 2010, and 2013 were included for analysis. The primary disease of each patient was based on the ICD-10 code; a diagnosis of dementia included F00 (Alzheimer's), F01 (vascular), F02 (other), and F03 (unspecified). RESULTS: Of 6,148 patients, 886 (14.4%) had dementia as a primary disease; most received care in the last month of life in nursing homes (48.0%) or hospitals (44.8%) rather than in their own home (7.2%). Patients were less likely to undergo pain management when their primary disease was dementia (adjusted odds ratio, 0.44; 95% confidence interval, 0.21-0.91). CONCLUSION: Education and policy efforts are required to provide palliative end-of-life care to people with dementia at home. The national dementia plan should also explore possible approaches regarding pain management for dying people who have dementia.
Keywords: Aged, 80 and over; Cross-Sectional Studies; Dementia; Female; Hospitals; Housing; Humans; Japan; Male; Nursing Homes; Pain Management; Retrospective Studies; Terminal Care; Time Factors

JNK: A Putative Link Between Insulin Signaling and VGLUT1 in Alzheimer's Disease. - Rodriguez-Perdigon, Manuel; Solas, Maite; Ramirez, Maria Javier (J Alzheimers Dis, 2016)
In the present work, the involvement of JNK in insulin signaling alterations and its role in glutamatergic deficits in Alzheimer's disease (AD) has been studied. In postmortem cortical tissues, pJNK levels were increased, while insulin signaling and the expression of VGLUT1 were decreased. A significant correlation was found between reduced expression of insulin receptor and VGLUT1. The administration of a JNK inhibitor reversed the decrease in VGLUT1 expression found in a mice model of insulin resistance. It is suggested that activation of JNK in AD inhibits insulin signaling which could lead to a decreased expression of VGLUT1, therefore contributing to the glutamatergic deficit in AD.
Keywords: Aged; Alzheimer Disease; Animals; Brain; Corticosterone; Disease Models, Animal; Female; Humans; Insulin; Insulin Resistance; Male; MAP Kinase Kinase 4; Mice, Inbred C57BL; Mitogen-Activated Protein Kinase 1; Neuroprotective Agents; RNA, Messenger; Vesicular Glutamate Transport Protein 1

Lack of evidence for a role of HHV-6 in the pathogenesis of Alzheimer's disease. - Agostini, Simone; Mancuso, Roberta; Baglio, Francesca; Cabinio, Monia; Hernis, Ambra; Guerini, Franca Rosa; Calabrese, Elena; Nemni, Raffaello; Clerici, Mario (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease (AD), the most common form of dementia worldwide, is associated with impairment in the mechanisms of the clearing of amyloid-β within a scenario of neuroinflammation. The etiopathogenesis of the AD is unclear, but a role for viral infection is suspected to play a role in initiating the disease. We recently described a positive correlation between high titers of HSV-1-specific antibodies (Ab) and the volumes of brain regions typically affected in disease. OBJECTIVE: The exploration of a possible role for Herpesviridae in AD was extended by analyzing HHV-6-specific humoral immunity in individuals with AD or a diagnosis of amnestic mild cognitive impairment (aMCI), a condition that is often prodromic of the development of AD. METHODS: 59 AD, 60 aMCI, and 61 age-matched healthy controls were enrolled in the study. Serum HHV-6 IgG antibody titers and avidity index were tested by ELISA. Two randomly selected subgroups of AD and aMCI in whom HHV-6 serum antibodies were detected underwent brain magnetic resonance imaging (MRI) by 1.5 T scanner. RESULTS: HHV-6 seroprevalence, antibody titers, and avidity were similar in the three groups. No correlation was found between Ab titers or avidity and brain volumes, either overall or in the regions typically affected by disease. CONCLUSIONS: The lack of any relation between humoral immune response against HHV-6 and AD and aMCI seems to rule out a role for this virus in the pathogenesis of AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Antibodies; Case-Control Studies; Cognitive Dysfunction; Female; Herpesvirus 1, Human; Herpesvirus 6, Human; Humans; Immunity, Humoral; Magnetic Resonance Imaging; Male; Seroepidemiologic Studies; Temporal Lobe

The Language Profile of Behavioral Variant Frontotemporal Dementia. - Hardy, Chris J D; Buckley, Aisling H; Downey, Laura E; Lehmann, Manja; Zimmerer, Vitor C; Varley, Rosemary A; Crutch, Sebastian J; Rohrer, Jonathan D; Warrington, Elizabeth K; Warren, Jason D (J Alzheimers Dis, 2016)
BACKGROUND: The language profile of behavioral variant frontotemporal dementia (bvFTD) remains to be fully defined. OBJECTIVE: We aimed to quantify the extent of language deficits in this patient group. METHODS: We assessed a cohort of patients with bvFTD (n = 24) in relation to patients with semantic variant primary progressive aphasia (svPPA; n = 14), nonfluent variant primary progressive aphasia (nfvPPA; n = 18), and healthy age-matched individuals (n = 24) cross-sectionally and longitudinally using a comprehensive battery of language and general neuropsychological tests. Neuroanatomical associations of language performance were assessed using voxel-based morphometry of patients' brain magnetic resonance images. RESULTS: Relative to healthy controls, and after accounting for nonverbal executive performance, patients with bvFTD showed deficits of noun and verb naming and single word comprehension, diminished spontaneous propositional speech, and deterioration in naming performance over time. Within the bvFTD group, patients with MAPT mutations had more severe impairments of noun naming and single word comprehension than patients with C9orf72 mutations. Overall the bvFTD group had less severe language deficits than patients with PPA, but showed a language profile that was qualitatively similar to svPPA. Neuroanatomical correlates of naming and word comprehension performance in bvFTD were identified predominantly in inferior frontal and antero-inferior temporal cortices within the dominant hemispheric language network. CONCLUSIONS: bvFTD is associated with a language profile including verbal semantic impairment that warrants further evaluation as a novel biomarker.
Keywords: Aged; Aphasia, Primary Progressive; Atrophy; Brain; Cognition; Comprehension; Female; Frontotemporal Dementia; Humans; Language; Magnetic Resonance Imaging; Male; Middle Aged; Neuroimaging; Neuropsychological Tests; Primary Progressive Nonfluent Aphasia

A Late Life Risk Index for Severe Cognitive Impairment in Mexico. - Downer, Brian; Veeranki, Sreenivas P; Wong, Rebeca (J Alzheimers Dis, 2016)
BACKGROUND: Several dementia risk indices have been developed for older adults in high-income countries. However, no index has been developed for populations in low- or middle-income countries. OBJECTIVE: To create a risk index for predicting severe cognitive impairment among adults aged ≥60 in Mexico and to compare the accuracy of this index to the Dementia Screening Indicator (DSI). METHODS: This study included 3,002 participants from the Mexican Health and Aging Study (MHAS) interviewed in 2001 and 2012. The MHAS risk index included sociodemographic, health, and functional characteristics collected in 2001. A point value based on the beta coefficients from a multivariable logistic regression model was assigned to each risk factor and the total score was calculated. RESULTS: The MHAS risk index (AUC = 0.74 95% CI = 0.70-0.77) and DSI (AUC = 0.72 95% CI = 0.69-0.77) had similar accuracy for discriminating between participants who developed severe cognitive impairment from those who did not. A score of ≥16 on the MHAS risk index had a sensitivity of 0.69 (95% CI = 0.64-0.70) and specificity of 0.67 (95% CI = 0.66-0.69). A score of ≥23 on the DSI had a sensitivity of 0.56 (95% CI = 0.50-0.63) and specificity of 0.78 (95% CI = 0.76-0.79). DISCUSSION: The MHAS risk index and DSI have moderate accuracy for predicting severe cognitive impairment among older adults in Mexico. This provides evidence that existing dementia risk indices may be applicable in low- and middle-income countries such as Mexico. Future research should seek to identify additional risk factors that can improve the accuracy of the MHAS risk index.
Keywords: Age Factors; Aged; Cognitive Dysfunction; Female; Humans; Life Style; Logistic Models; Longitudinal Studies; Male; Mexico; Middle Aged; Multivariate Analysis; Risk Factors; Social Behavior; Socioeconomic Factors

The Latent Dementia Phenotype δ is Associated with Cerebrospinal Fluid Biomarkers of Alzheimer's Disease and Predicts Conversion to Dementia in Subjects with Mild Cognitive Impairment. - Koppara, Alexander; Wolfsgruber, Steffen; Kleineidam, Luca; Schmidtke, Klaus; Frölich, Lutz; Kurz, Alexander; Schulz, Stefanie; Hampel, Harald; Heuser, Isabella; Peters, Oliver; Reischies, Friedel M; Jahn, Holger; et al. (J Alzheimers Dis, 2016)
BACKGROUND: The recently proposed latent variable δ is a new tool for dementia case finding. It is built in a structural equation modeling framework of cognitive and functional data and constitutes a novel endophenotype for Alzheimer's disease (AD) research and clinical trials. OBJECTIVE: To investigate the association of δ with AD biomarkers and to compare the prediction of δ with established scales for conversion to dementia in patients with mild cognitive impairment (MCI). METHODS: Using data from a multicenter memory clinic study, we examined the external associations of the latent variable δ and compared δ with well-established cognitive and functional scales and cognitive-functional composite scores. For that purpose, logistic regressions with cerebrospinal fluid (CSF) biomarkers and conversion to dementia as dependent variables were performed with the investigated scores. The models were tested for significant differences. RESULTS: In patients with MCI, δ based on a broad range of cognitive scales (including the ADAS-cog, the MMSE, and the CERAD neuropsychological battery) predicted an abnormal CSF Aβ42/tau ratio indicative of AD (n = 340, AUC = 0.78, p <  0.001), and predicted incident dementia within 1-3 years of follow-up (n = 525, AUC = 0.84, p <  0.001). These associations were generally stronger than for any other scale or cognitive-functional composite examined. Homologs of δ based on reduced test batteries yielded somewhat lower effects. CONCLUSION: These findings support the interpretation of δ as a construct capturing the disease-related "essence" of cognitive and functional impairments in patients with MCI and dementia, and suggest that δ might become an analytical tool for dementia research.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Dementia; Disease Progression; Female; Humans; Logistic Models; Longitudinal Studies; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptide Fragments; Phenotype; Predictive Value of Tests; Retrospective Studies; tau Proteins

Late-Onset Metachromatic Leukodystrophy with Early Onset Dementia Associated with a Novel Missense Mutation in the Arylsulfatase A Gene. - Stoeck, Katharina; Psychogios, Marios Nikos; Ohlenbusch, Andreas; Steinfeld, Robert; Schmidt, Jens (J Alzheimers Dis, 2016)
A 48-year-old male patient presented with personality changes and progressive memory loss over 2 years with initially suspected Hashimoto's encephalopathy. Strategy of diagnostic workup of early onset dementia included dementia from neurodegenerative, neuroinflammatory, metabolic/toxic, and psychiatric origin. The patient's neurological exam was normal. MRI revealed a leukencephalopathy, predominantly in the frontal periventricular white matter, without notable changes over 2 years. On neurophysiological examination, prolonged central conduction times and a sensorimotor polyneuropathy were noted. Neuropsychological impairment included disorientation in place and a reduced short time memory. Behavioral alterations were predominated by sudden mood changes and disinhibition. Cerebrospinal fluid was normal. Despite presence of thyroid autoantibodies, glucocorticosteroid treatment did not improve the dementia. A metachromatic leukodystrophy was diagnosed by decreased arylsulfatase-A activity in leucocytes/fibroblasts and identification of a compound heterozygous mutation in the ARSA gene: c.542T>G (exon 3) and the novel mutation c.1013T>C (exon 6). Pathogenic function was suggested by bioinformatic mutation search. In a patient with early onset dementia, strategic diagnostic workup including genetic assessment revealed an adult-onset metachromatic leukodystrophy with a novel mutation in the arylsulfatase A gene.
Keywords: Age of Onset; Brain; Cerebroside-Sulfatase; Dementia; Diagnosis, Differential; DNA Mutational Analysis; Exons; Humans; Leukodystrophy, Metachromatic; Male; Middle Aged; Mutation, Missense; Neuropsychological Tests

Lewy Bodies, Vascular Risk Factors, and Subcortical Arteriosclerotic Leukoencephalopathy, but not Alzheimer Pathology, are Associated with Development of Psychosis in Alzheimer's Disease. - Fischer, Corinne E; Qian, Winnie; Schweizer, Tom A; Millikin, Colleen P; Ismail, Zahinoor; Smith, Eric E; Lix, Lisa M; Shelton, Paul; Munoz, David G (J Alzheimers Dis, 2016)
BACKGROUND: The neuropathological correlates of psychosis in Alzheimer's disease (AD) is unclear, with some studies reporting a correlation between psychosis and increased AD pathology while others have found no association. OBJECTIVE: To determine the demographic, clinical, and neuropathological features associated with psychotic symptoms in clinically attributed and neuropathologically proven AD. METHOD: We separately reviewed two overlapping groups of clinically diagnosed (cAD) AD patients with neuropathology data and neuropathologically definite (npAD) cases (regardless of clinical diagnosis) from the NACC database, and explored the relationships between psychosis and clinical variables, neuropathologic correlates, and vascular risk factors. Delusions and hallucinations, defined according to the NPI-Q, were analyzed separately. RESULTS: 1,073 subjects in the database fulfilled our criteria (890 cAD and 728 npAD patients). 34% of cAD and 37% of npAD had psychotic symptoms during their illness. Hallucinations were associated with greater cognitive and functional impairments on the MMSE and CDR, while delusional patients showed less impairment on CDR, consistent across cAD and npAD groups. Burden of AD pathology appears to relate to presence of psychotic symptoms in the clinical AD group, but this result is not confirmed in the neuropathologically confirmed group suggesting the findings in the clinical group were due to misdiagnosis of AD. Lewy body pathology, subcortical arteriosclerotic leukoencephalopathy, and vascular risk factors, including a history of hypertension and diabetes, were associated with the development of psychosis. METHOD: Vascular and Lewy body pathologies and vascular risk factors are important modifiers of the risk of psychosis in AD.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cognition Disorders; Databases, Factual; Dementia, Vascular; Female; Hemorrhage; Humans; Lewy Bodies; Male; Middle Aged; Psychiatric Status Rating Scales; Psychotic Disorders; Retrospective Studies; Risk Factors; Severity of Illness Index; Surveys and Questionnaires

Lifelong Reading Disorder and Mild Cognitive Impairment: Implications for Diagnosis. - Lebowitz, Brian K; Weinstein, Cheryl; Beiser, Alexa; Seshadri, Sudha; Wolf, Philip A; Auerbach, Sandford; Au, Rhoda (J Alzheimers Dis, 2016)
Although neuropsychological tests are commonly used in the evaluation of possible mild cognitive impairment (MCI), poor test scores may be indicative of factors other than neurological compromise. The current study assessed the role of lifelong reading disorder on MCI classification. Community dwelling older adults with a suspected developmental reading disorder were identified by inference based on reading test performance. Individuals with a suspected reading disorder were significantly more likely to perform at a level consistent with MCI on several commonly used neuropsychological tests. The findings suggest a relationship between a history of reading disorder and MCI classification.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Dyslexia; Female; Humans; Independent Living; Longitudinal Studies; Male; Neuropsychological Tests; Psychometrics; Retrospective Studies

Longitudinal Changes in Functional Brain Connectivity Predicts Conversion to Alzheimer's Disease. - Serra, Laura; Cercignani, Mara; Mastropasqua, Chiara; Torso, Mario; Spanò, Barbara; Makovac, Elena; Viola, Vanda; Giulietti, Giovanni; Marra, Camillo; Caltagirone, Carlo; Bozzali, Marco (J Alzheimers Dis, 2016)
This longitudinal study investigates the modifications in structure and function occurring to typical Alzheimer's disease (AD) brains over a 2-year follow-up, from pre-dementia stages of disease, with the aim of identifying biomarkers of prognostic value. Thirty-one patients with amnestic mild cognitive impairment were recruited and followed-up with clinical, neuropsychological, and MRI assessments. Patients were retrospectively classified as AD Converters or Non-Converters, and the data compared between groups. Cross-sectional MRI data at baseline, assessing volume and functional connectivity abnormalities, confirmed previous findings, showing a more severe pattern of regional grey matter atrophy and default-mode network disconnection in Converters than in Non-Converters. Longitudinally, Converters showed more grey matter atrophy in the frontotemporal areas, accompanied by increased connectivity in the precuneus. Discriminant analysis revealed that functional connectivity of the precuneus within the default mode network at baseline is the parameter able to correctly classify patients in Converters and Non-Converters with high sensitivity, specificity, and accuracy.
Keywords: Aged; Alzheimer Disease; Atrophy; Brain; Brain Mapping; Cognitive Dysfunction; Cross-Sectional Studies; Discriminant Analysis; Disease Progression; Female; Follow-Up Studies; Gray Matter; Humans; Image Processing, Computer-Assisted; Longitudinal Studies; Magnetic Resonance Imaging; Male; Neural Pathways; Neuropsychological Tests; Prognosis; Rest

Longitudinal Protein Changes in Blood Plasma Associated with the Rate of Cognitive Decline in Alzheimer's Disease. - Sattlecker, Martina; Khondoker, Mizanur; Proitsi, Petroula; Williams, Stephen; Soininen, Hilkka; Kłoszewska, Iwona; Mecocci, Patrizia; Tsolaki, Magda; Vellas, Bruno; Lovestone, Simon; Dobson, Richard Jb (J Alzheimers Dis, 2016)
Biomarkers of Alzheimer's disease (AD) progression are needed to support the development of urgently needed disease modifying drugs. We employed a SOMAscan assay for quantifying 1,001 proteins in blood samples from 90 AD subjects, 37 stable mild cognitive impaired (MCI) subjects, 39 MCI subjects converting to AD within a year and 69 controls at baseline and one year follow up. We used linear mixed effects models to identify proteins changing significantly over one year with the rate of cognitive decline, which was quantified as the reduction in Mini Mental State Examination (MMSE) scores. Additionally, we investigated proteins changing differently across disease groups and during the conversion from MCI to AD. We found that levels of proteins belonging to the complement cascade increase significantly in fast declining AD patients. Longitudinal changes in the complement cascade might be a surrogate biomarker for disease progression. We also found that members of the cytokine-cytokine receptor interaction pathway change during AD when compared to healthy aging subjects.
Keywords: Aged; Alzheimer Disease; Biomarkers; Cognition; Cognitive Dysfunction; Disease Progression; Female; Follow-Up Studies; Humans; Linear Models; Longitudinal Studies; Male; Mental Status Schedule; Neuropsychological Tests

Looking for Neuroimaging Markers in Frontotemporal Lobar Degeneration Clinical Trials: A Multi-Voxel Pattern Analysis Study in Granulin Disease. - Premi, Enrico; Cauda, Franco; Costa, Tommaso; Diano, Matteo; Gazzina, Stefano; Gualeni, Vera; Alberici, Antonella; Archetti, Silvana; Magoni, Mauro; Gasparotti, Roberto; Padovani, Alessandro; Borroni, Barbara (J Alzheimers Dis, 2016)
In light of future pharmacological interventions, neuroimaging markers able to assess the response to treatment would be crucial. In Granulin (GRN) disease, preclinical data will prompt pharmacological trials in the future. Two main points need to be assessed: (1) to identify target regions in different disease stages and (2) to determine the most accurate functional and structural neuroimaging index to be used. To this aim, we have taken advantage of the multivariate approach of multi-voxel pattern analysis (MVPA) to explore the information of brain activity patterns in a cohort of GRN Thr272fs carriers at different disease stages (14 frontotemporal dementia (FTD) patients and 17 asymptomatic carriers) and a group of 33 healthy controls. We studied structural changes by voxel-based morphometry (VBM), functional connectivity by assessing salience, default mode, fronto-parietal, dorsal attentional, executive networks, and local connectivity by regional homogeneity, amplitude of low frequency fluctuations (ALFF), fractional ALFF (fALFF), degree centrality, and voxel-mirrored homotopic connectivity. In FTD patients with GRN mutation, the most predictive measure was VBM structural analysis, while in asymptomatic carriers the best predictor marker was the local connectivity measure (fALFF). Altogether, all indexes demonstrated fronto-temporo-parietal damage in GRN pathology, with widespread structural damage of fronto-parietal and temporal regions when disease is overt. MVPA could be of aid in identifying the most accurate neuroimaging marker for clinical trials. This approach was able to identify both the target region and the best neuroimaging approach, which would be specific in the different disease stages. Further studies are needed to simultaneously integrate multimodal indexes in a classifier able to trace the disease progression moving from preclinical to clinical stage of the disease.
Keywords: Adult; Aged; Brain; Brain Mapping; Cohort Studies; Female; Frontotemporal Lobar Degeneration; Humans; Image Processing, Computer-Assisted; Intercellular Signaling Peptides and Proteins; Magnetic Resonance Imaging; Male; Middle Aged; Mutation; Neural Pathways; Oxygen; Phenylalanine; Threonine

Low Prevalence of Mixed Dementia in a Cohort of 2,000 Elderly Patients in a Memory Clinic Setting. - Claus, Jules J; Staekenborg, Salka S; Roorda, Jelmen J; Stevens, Martijn; Herderschee, Dirk; van Maarschalkerweerd, Willy; Schuurmans, Lilly; Tielkes, Caroline E M; Koster, Pieter; Bavinck, Chris; Scheltens, Philip (J Alzheimers Dis, 2016)
BACKGROUND: It is generally assumed that with increasing age, pathology in clinically diagnosed Alzheimer's disease (AD) becomes more mixed, i.e., co-existence of amyloid plaques and cerebrovascular pathology. OBJECTIVE: To test the hypothesis of increasing prevalence of mixed dementia in late-onset clinically diagnosed Alzheimer's disease (AD) in a single-center memory clinic population. METHODS: Patients included had diagnoses of AD (n = 832), subjective cognitive impairment (SCI, n = 333), mild cognitive impairment (MCI, n = 492), vascular dementia (VaD, n = 57), other dementia (n = 53), or other diagnosis (n = 233). Prevalence of severe white matter lesions (WML) was defined as a score of 2 or higher on the Fazekas-scale on brain computed tomography to classify AD patients as having mixed dementia. We examined the effect of age on WML using multiple linear regression analysis, and AD patients were compared to SCI to determine the effect of disease on WML. RESULTS: Prevalence of severe WML was 33.6% in AD patients (mixed dementia), 11.4% in SCI, 22.7% in MCI, 75.4% in VaD, 3.8% in other dementia, and 15.5% in other diagnosis. With increasing age there was a significant and similar increase of WML scores in SCI, MCI, AD, other dementia, and other diagnosis, indicating no effect modification by AD. The difference between AD patients and SCI averaged 0.16 on the WML score and difference in percentage severe WML between AD and SCI patients was 15% across all ages. CONCLUSION: We found a low prevalence of mixed dementia. Furthermore, severe WML in AD was largely explained by age rather than effect of disease.
Keywords: Age Factors; Aged; Aged, 80 and over; Analysis of Variance; Cognitive Dysfunction; Cohort Studies; Dementia; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Prevalence; Regression Analysis; Risk Factors; Tomography Scanners, X-Ray Computed

Lower Prevalence of Alzheimer's Disease among Tibetans: Association with Religious and Genetic Factors. - Huang, Fukai; Shang, Ying; Luo, Yuandai; Wu, Peng; Huang, Xue; Tan, Xiaohui; Lu, Xingyi; Zhen, Lifang; Hu, Xianda (J Alzheimers Dis, 2016)
BACKGROUND: The prevalence of dementia differs among racial groups, the highest prevalence being in Latin America (8.5%) compared to sub-Saharan African regions (2-4%). The most common type of dementia is Alzheimer's disease (AD). OBJECTIVE: To estimate the prevalence of AD in the Qinghai-Tibet plateau and to investigate the related factors. METHODS: This was a cross-sectional, multistage cluster sampling design survey. Data was collected from May 2014 to September 2014 from 4,060 Tibetan aged >60 years. Participants underwent clinical examinations and neuropsychological evaluations. MALDI-TOF was used to test the genotypes of CLU, TFAM, TP53INP1, IGHV1-67, CR1, ApoE, and BIN1. Logistic regression models were used to ascertain the associations with AD. RESULTS: The prevalence of AD among Tibetan individuals aged >60 years was 1.33% (95% CI: 0.98-1.69). The CLU haplotypes AA+GA (odds ratio (OR) = 4.483; 95% CI: 1.069-18.792) of rs2279590 was correlated with AD. The CLU haplotypes GG+GC (OR = 0.184; 95% CI: 0.038-0.888) of rs9331888 and kowtow (OR = 0.203; 95% CI 0.046-0.896) were negatively correlated with AD. CONCLUSION: A low prevalence of AD was found in Tibetans from the Qinghai-Tibet plateau. Multivariate analysis might suggest that regular "mind-body" religious meditative activities may be negatively associated with AD in this population, as well as the CLU genotype at rs9331888.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Clusterin; Cognition Disorders; Cross-Sectional Studies; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Polymorphism, Single Nucleotide; Psychiatric Status Rating Scales; Religion; Risk Factors; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Tibet

LRP/LR Antibody Mediated Rescuing of Amyloid-β-Induced Cytotoxicity is Dependent on PrPc in Alzheimer's Disease. - Pinnock, Emma C; Jovanovic, Katarina; Pinto, Maxine G; Ferreira, Eloise; Dias, Bianca Da Costa; Penny, Clement; Knackmuss, Stefan; Reusch, Uwe; Little, Melvyn; Schatzl, Hermann M; Weiss, Stefan F T (J Alzheimers Dis, 2016)
The neuronal perturbations in Alzheimer's disease are attributed to the formation of extracellular amyloid-β (Aβ) neuritic plaques, composed predominantly of the neurotoxic Aβ42 isoform. Although the plaques have demonstrated a role in synaptic dysfunction, neuronal cytotoxicity has been attributed to soluble Aβ42 oligomers. The 37kDa/67kDa laminin receptor has been implicated in Aβ42 shedding and Aβ42-induced neuronal cytotoxicity, as well as internalization of this neurotoxic peptide. As the cellular prion protein binds to both LRP/LR and Aβ42, the mechanism underlying this cytotoxicity may be indirectly due to the PrPc-Aβ42 interaction with LRP/LR. The effects of this interaction were investigated by 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide assays. PrPc overexpression significantly enhanced Aβ42 cytotoxicity in vitro, while PrP-/-  cells were more resistant to the cytotoxic effects of Aβ42 and exhibited significantly less cell death than PrPc expressing N2a cells. Although anti-LRP/LR specific antibody IgG1-iS18 significantly enhanced cell viability in both pSFV1-huPrP1-253 transfected and non-transfected cells treated with exogenous Aβ42, it failed to have any cell rescuing effect in PrP-/-  HpL3-4 cells. These results suggest that LRP/LR plays a significant role in Aβ42-PrPc mediated cytotoxicity and that anti-LRP/LR specific antibodies may serve as potential therapeutic tools for Alzheimer's disease.
Keywords: Amyloid beta-Peptides; Animals; Antibodies; Cell Line, Transformed; Cell Survival; Flow Cytometry; Gene Expression Regulation; Humans; Mice; Peptide Fragments; Prions; Receptors, Laminin; Transfection

Maintenance of Cognitive Performance and Mood for Individuals with Alzheimer's Disease Following Consumption of a Nutraceutical Formulation: A One-Year, Open-Label Study. - Remington, Ruth; Bechtel, Cynthia; Larsen, David; Samar, Annemarie; Page, Robert; Morrell, Christopher; Shea, Thomas B (J Alzheimers Dis, 2016)
Nutritional interventions have shown varied efficacy on cognitive performance during Alzheimer's disease (AD). Twenty-four individuals diagnosed with AD received a nutraceutical formulation (NF: folate, alpha-tocopherol, B12, S-adenosyl methioinine, N-acetyl cysteine, acetyl-L-carnitine) under open-label conditions (ClinicalTrials.gov NCT01320527). Primary outcome was cognitive performance. Secondary outcomes were behavioral and psychological symptoms of dementia (BPSD) and activities of daily living. Participants maintained their baseline cognitive performance and BPSD over 12 months. These findings are consistent with improvement in cognitive performance and BPSD in prior placebo-controlled studies with NF, and contrast with the routine decline for participants receiving placebo.
Keywords: Aged; Aged, 80 and over; alpha-Tocopherol; Alzheimer Disease; Cognition Disorders; Dietary Supplements; Disease Progression; Female; Folic Acid; Follow-Up Studies; Humans; Male; Mood Disorders; Neuropsychological Tests; Psychiatric Status Rating Scales; Time Factors; Vitamin B 12

Measuring Information Processing Speed in Mild Cognitive Impairment: Clinical Versus Research Dichotomy. - Haworth, Judy; Phillips, Michelle; Newson, Margaret; Rogers, Peter J; Torrens-Burton, Anna; Tales, Andrea (J Alzheimers Dis, 2016)
A substantial body of research evidence is indicative of disproportionately slowed information processing speed in a wide range of multi-trial, computer-based, neuroimaging- and electroencephalography-based reaction time (RT) tests in Alzheimer's disease and mild cognitive impairment (MCI). However, in what is arguably a dichotomy between research evidence and clinical practice, RT associated with different brain functions is rarely assessed as part of their diagnosis. Indeed, often only the time taken to perform a single, specific task, commonly the Trail making test (TMT), is measured. In clinical practice therefore, there can be a failure to assess adequately the integrity of the rapid, serial information processing and response, necessary for efficient, appropriate, and safe interaction with the environment. We examined whether a typical research-based RT task could at least match the TMT in differentiating amnestic MCI (aMCI) from cognitively healthy aging at group level. As aMCI is a heterogeneous group, typically containing only a proportion of individuals for whom aMCI represents the early stages of dementia, we examined the ability of each test to provide intra-group performance variation. The results indicate that as well as significant slowing in performance of the operations involved in TMT part B (but not part A), individuals with aMCI also experience significant slowing in RT compared to controls. The results also suggest that research-typical RT tests may be superior to the TMT in differentiating between cognitively healthy aging and aMCI at group level and in revealing the performance variability one would expect from an etiologically heterogeneous disorder such as aMCI.
Keywords: Aged; Aged, 80 and over; Attention; Cognitive Dysfunction; Electroencephalography; Female; Humans; Male; Mental Processes; Mental Status Schedule; Middle Aged; Neuroimaging; Neuropsychological Tests; Photic Stimulation; Reaction Time; Residence Characteristics

Memory for Public Events in Mild Cognitive Impairment and Alzheimer's Disease: The Importance of Rehearsal. - Langlois, Roxane; Joubert, Sven; Benoit, Sophie; Dostie, Valérie; Rouleau, Isabelle (J Alzheimers Dis, 2016)
Ribot's law refers to the better preservation of remote memories compared with recent ones that presumably characterizes retrograde amnesia. Even if Ribot-type temporal gradient has been extensively studied in retrograde amnesia, particularly in Alzheimer's disease (AD), this pattern has not been consistently found. One explanation for these results may be that rehearsal frequency rather than remoteness accounts for the better preservation of these memories. Thus, the aim of present study was to address this question by studying retrograde semantic memory in subjects with amnestic mild cognitive impairment (aMCI) (n = 20), mild AD (n = 20) and in healthy older controls (HC; n = 19). In order to evaluate the impact of repetition as well as the impact of remoteness, we used a test assessing memory for enduring and transient public events that occurred in the recent and remote past. Results show no clear temporal gradient across time periods (1960-1975; 1976-1990; 1991-2005; 2006-2011), but a better performance was observed in all three groups for enduring compared with transient events. Moreover, although deficits were globally found in both patients groups compared with HC, more specific analyses revealed that aMCI patients were only impaired on transient events while AD patients were impaired on both transient and enduring events. Exploratory analyses also revealed a tendency suggesting preservation of remote transient events in aMCI. These findings are discussed with regards to memory consolidation models.
Keywords: Aged; Alzheimer Disease; Cognitive Dysfunction; Female; Humans; Learning; Male; Memory; Psychological Tests; Semantics

A Mercaptoacetamide-Based Class II Histone Deacetylase Inhibitor Increases Dendritic Spine Density via RasGRF1/ERK Pathway. - Song, Jung Min; Sung, You Me; Nam, Jin Han; Yoon, Hyejin; Chung, Andrew; Moffat, Emily; Jung, Mira; Pak, Daniel T S; Kim, Jungsu; Hoe, Hyang-Sook (J Alzheimers Dis, 2016)
BACKGROUND: The accumulation of amyloid-β (Aβ) leads to the loss of dendritic spines and synapses, which is hypothesized to cause cognitive impairments in Alzheimer's disease (AD) patients. In our previous study, we demonstrated that a novel mercaptoacetamide-based class II histone deacetylase inhibitor (HDACI), known as W2, decreased Aβ levels and improved learning and memory in mice. However, the underlying mechanism of this effect is unknown. OBJECTIVE: Because dendritic spine formation is associated with cognitive performance, here we investigated whether HDACI W2 regulates dendritic spine density and its molecular mechanism of action. METHODS: To examine the effect of HDACI W2 on dendritic spine density, we conducted morphological analysis of dendritic spines using GFP transfection and Golgi staining. In addition, to determine the molecular mechanism of W2 effects on spines, we measured the levels of mRNAs and proteins involved in the Ras signaling pathway using quantitative real-time PCR, immunocytochemistry, and western analysis. RESULTS: We found that HDACI W2 altered dendritic spine density and morphology in vitro and in vivo. Additionally, W2 increased the mRNA or protein levels of Ras GRF1 and phospho-ERK. Moreover, knockdown of RasGRF1 and inhibition of ERK activity prevented the W2-mediated spinogenesis in primary hippocampal neurons. CONCLUSION: Our Class II-selective HDACI W2 promotes the formation and growth of dendritic spines in a RasGRF1 and ERK dependent manner in primary hippocampal neurons.
Keywords: Acetamides; Animals; Blotting, Western; Cells, Cultured; Cerebral Cortex; Dendritic Spines; Gene Knockdown Techniques; Green Fluorescent Proteins; Hippocampus; Histone Deacetylase Inhibitors; Immunohistochemistry; MAP Kinase Signaling System; Mice, Inbred C57BL; ras-GRF1; Rats, Sprague-Dawley; Real-Time Polymerase Chain Reaction; Receptors, AMPA; Receptors, N-Methyl-D-Aspartate; RNA, Messenger; Thioglycolates; Transfection

A Meta-Analysis of Alzheimer's Disease Incidence and Prevalence Comparing African-Americans and Caucasians. - Steenland, Kyle; Goldstein, Felicia C; Levey, Allan; Wharton, Whitney (J Alzheimers Dis, 2016)
BACKGROUND: Several studies have shown higher Alzheimer's disease (AD) incidence rates are in African-Americans (AAs) than Caucasians (CCs). If this finding is consistent across studies, it raises important etiologic questions regarding factors responsible for this discrepancy. It also affects the likely public health burden of AD in the US in the future, as the non-Caucasian population becomes the majority. OBJECTIVE: Estimate the AA/CC rate ratio for AD incidence across all available studies. METHODS: We conducted a meta-analysis of population-based studies for the rate ratio (RR) of AD incidence for AAs versus CCs, after identifying six relevant studies from the literature. We calculated an AA/CC rate ratio across all studies using inverse-variance weighting, and assessed inter-study heterogeneity. Using these incidence data, as well as data on survival after diagnosis, and on all-cause mortality, we also estimated the US prevalence of AD among AAs and CCs. RESULTS: There were six population-based studies with data comparing AD incidence between AAs and CCs, with an estimated 370 AA and 640 CC incident cases. The meta-analysis RR showed that the AD rate for AAs was 64% higher than for CCs (RR = 1.64 (95% CI 1.35-2.00)) 1.35-2.00)), with no evidence of heterogeneity. We estimated the current US AD prevalence for ages 65-90 to be 5.5% for CCs, and 8.6% for AAs (prevalence ratio 1.56). CONCLUSION: AAs have an increased risk of incident and prevalent AD compared to CCs for reasons which are unknown, but are hypothesized to reflect biological, psychological, and socioeconomic factors.
Keywords: African Americans; Alzheimer Disease; Community Health Planning; European Continental Ancestry Group; Female; Follow-Up Studies; Humans; Incidence; Male; Prevalence

Meta-Analysis of Transcriptome Data Related to Hippocampus Biopsies and iPSC-Derived Neuronal Cells from Alzheimer's Disease Patients Reveals an Association with FOXA1 and FOXA2 Gene Regulatory Networks. - Wruck, Wasco; Schröter, Friederike; Adjaye, James (J Alzheimers Dis, 2016)
Although the incidence of Alzheimer's disease (AD) is continuously increasing in the aging population worldwide, effective therapies are not available. The interplay between causative genetic and environmental factors is partially understood. Meta-analyses have been performed on aspects such as polymorphisms, cytokines, and cognitive training. Here, we propose a meta-analysis approach based on hierarchical clustering analysis of a reliable training set of hippocampus biopsies, which is condensed to a gene expression signature. This gene expression signature was applied to various test sets of brain biopsies and iPSC-derived neuronal cell models to demonstrate its ability to distinguish AD samples from control. Thus, our identified AD-gene signature may form the basis for determination of biomarkers that are urgently needed to overcome current diagnostic shortfalls. Intriguingly, the well-described AD-related genes APP and APOE are not within the signature because their gene expression profiles show a lower correlation to the disease phenotype than genes from the signature. This is in line with the differing characteristics of the disease as early-/late-onset or with/without genetic predisposition. To investigate the gene signature's systemic role(s), signaling pathways, gene ontologies, and transcription factors were analyzed which revealed over-representation of response to stress, regulation of cellular metabolic processes, and reactive oxygen species. Additionally, our results clearly point to an important role of FOXA1 and FOXA2 gene regulatory networks in the etiology of AD. This finding is in corroboration with the recently reported major role of the dopaminergic system in the development of AD and its regulation by FOXA1 and FOXA2.
Keywords: Alzheimer Disease; Biopsy; Cells, Cultured; Gene Regulatory Networks; Hepatocyte Nuclear Factor 3-alpha; Hepatocyte Nuclear Factor 3-beta; Hippocampus; Humans; Induced Pluripotent Stem Cells; Transcriptome

Metabolic Syndrome and Mild Cognitive Impairment: A Case-Control Study among Elderly in a Shanghai Suburb. - Yao, Qian; Jiang, Guo-Xin; Zhou, Zhi-Ming; Chen, Jin-Mei; Cheng, Qi (J Alzheimers Dis, 2016)
BACKGROUND: Metabolic syndrome (MetS) maybe associated with mild cognitive impairment (MCI). OBJECTIVE: To investigate the relationship between MetS, with its individual or combined components, and MCI among elderly. METHODS: A case-control study was conducted among the elderly aged 65 years and over in a community located in the southwestern suburb of Shanghai, China. The Chinese version of the Mini-Mental Status Examination (C-MMSE) was used to screen subjects with MCI. Associations of MetS with its individual or combined components and MCI were analyzed using conditional regression analyses with or without adjustment for gender, education, current smoking, current drinking, and physical activities. RESULTS: There were 379 subjects with MCI and 379 gender- and age-matched healthy controls in the study. Compared with healthy controls in univariate analyses, subjects with MCI were more likely to have less time spent on physical activity, lower C-MMSE score, heavier weight, larger waistline and hipline, higher diastolic blood pressure, higher body mass index, higher abdominal obesity index, higher serum glycated hemoglobin, higher serum triglycerides, higher serum cholesterol, higher serum uric acid, and higher serum alanine aminotransferase. After multivariable adjustment, MetS was significantly associated with an increased risk of MCI (OR = 2.277; 95% CI: 1.086-4.773). Among MetS components, abdominal obesity (OR = 2.101; 95% CI: 1.224-3.608) and hypertension (OR = 2.075; 95% CI: 1.170-3.678) showed a significant association with MCI, respectively; while these two components were combined, the association was stronger (OR = 2.459; 95% CI: 1.360-4.447). CONCLUSION: MetS and its components, particularly abdominal obesity and hypertension, were found to be significantly associated with the risk of MCI.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Case-Control Studies; Chi-Square Distribution; China; Cities; Cognition Disorders; Community Health Planning; Female; Humans; Male; Mental Status Schedule; Metabolic Diseases; Risk Factors

Metformin Facilitates Amyloid-β Generation by β- and γ-Secretases via Autophagy Activation. - Son, Sung Min; Shin, Hong-Joon; Byun, Jayoung; Kook, Sun Young; Moon, Minho; Chang, Yu Jin; Mook-Jung, Inhee (J Alzheimers Dis, 2016)
The evidence of strong pathological associations between type 2 diabetes and Alzheimer's disease (AD) has increased in recent years. Contrary to suggestions that anti-diabetes drugs may have potential for treating AD, we demonstrate here that the insulin sensitizing anti-diabetes drug metformin (Glucophage®) increased the generation of amyloid-β (Aβ), one of the major pathological hallmarks of AD, by promoting β- and γ-secretase-mediated cleavage of amyloid-β protein precursor (AβPP) in SH-SY5Y cells. In addition, we show that metformin caused autophagosome accumulation in Tg6799 AD model mice. Extremely high γ-secretase activity was also detected in autophagic vacuoles, apparently a novel site of Aβ peptide generation. Together, these data suggest that metformin-induced accumulation of autophagosomes resulted in increased γ-secretase activity and Aβ generation. Additional experiments indicated that metformin increased phosphorylation of AMP-activated protein kinase, which activates autophagy by suppressing mammalian target of rapamycin (mTOR). The suppression of mTOR then induces the abnormal accumulation of autophagosomes. We conclude that metformin, an anti-diabetes drug, may exacerbate AD pathogenesis by promoting amyloidogenic AβPP processing in autophagosomes.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Autophagy; Cell Line, Tumor; Disease Models, Animal; Female; Humans; Hypoglycemic Agents; Lysosomes; Metformin; Mice; Mice, Inbred C57BL; Mice, Transgenic; Microscopy, Electron; Mutation; Neuroblastoma; Signal Transduction

Metformin in Amnestic Mild Cognitive Impairment: Results of a Pilot Randomized Placebo Controlled Clinical Trial. - Luchsinger, Jose A; Perez, Thania; Chang, Helena; Mehta, Pankaj; Steffener, Jason; Pradabhan, Gnanavalli; Ichise, Masanori; Manly, Jennifer; Devanand, Davangere P; Bagiella, Emilia (J Alzheimers Dis, 2016)
Diabetes and hyperinsulinemia may be risk factors for Alzheimer's disease (AD). We conducted a pilot study of metformin, a medication efficacious in treating and preventing diabetes while reducing hyperinsulinemia, among persons with amnestic mild cognitive impairment (aMCI) with the goal of collecting preliminary data on feasibility, safety, and efficacy. Participants were 80 men and women aged 55 to 90 years with aMCI, overweight or obese, without treated diabetes. We randomized participants to metformin 1000 mg twice a day or matching placebo for 12 months. The co-primary clinical outcomes were changes from baseline to 12 months in total recall of the Selective Reminding Test (SRT) and the score of the Alzheimer's Disease Assessment Scale-cognitive subscale (ADAS-cog). The secondary outcome was change in relative glucose uptake in the posterior cingulate-precuneus in brain fluorodeoxyglucose positron emission tomography. Change in plasma Aβ42 was an exploratory outcome. The mean age of participants was 65 years. Fifty percent of participants were women. The only baseline variable that was different between the arms was the ADAS-Cog. Metformin could not be tolerated by 7.5% of participants; 15% tolerated 500 mg/day, 35% tolerated 1000 mg/day, 32.5% tolerated 1500 mg/day, and only 10% tolerated the maximum dose. There were no serious adverse events related to metformin. The 7.5% of persons who did not tolerate metformin reported gastrointestinal symptoms. After adjusting for baseline ADAS-cog, changes in total recall of the SRT favored the metformin group (9.7±8.5 versus 5.3±8.5; p = 0.02). Differences for other outcomes were not significant. A larger trial seems warranted to evaluate the efficacy and cognitive safety of metformin in prodromal AD.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Brain; Cognitive Dysfunction; Double-Blind Method; Female; Follow-Up Studies; Glucose; Humans; Male; Metformin; Middle Aged; Nootropic Agents; Overweight; Peptide Fragments; Pilot Projects; Positron-Emission Tomography; Psychological Tests; Severity of Illness Index; Treatment Outcome

Mild Cognitive Impairment and Susceptibility to Scams in Old Age. - Han, S Duke; Boyle, Patricia A; James, Bryan D; Yu, Lei; Bennett, David A (J Alzheimers Dis, 2016)
BACKGROUND: Falling victim to financial scams can have a significant impact upon social and financial wellbeing and independence. A large proportion of scam victims are older adults, but whether older victims with mild cognitive impairment (MCI) are at higher risk remains unknown. OBJECTIVE: We tested the hypothesis that older persons with MCI exhibit greater susceptibility to scams compared to those without cognitive impairment. METHODS: Seven hundred and thirty older adults without dementia were recruited from the Rush Memory and Aging Project, a community-based epidemiologic study of aging. Participants completed a five-item self-report measure of susceptibility to scams, a battery of cognitive measures, and clinical diagnostic evaluations. RESULTS: In models adjusted for age, education, and gender, the presence of MCI was associated with greater susceptibility to scams (B = 0.125, SE = 0.063, p-value = 0.047). Further, in analyses of the role of specific cognitive systems in susceptibility to scams among persons with MCI (n = 144), the level of performance in two systems, episodic memory and perceptual speed abilities, were associated with susceptibility. CONCLUSIONS: Adults with MCI may be more susceptible to scams in old age than older persons with normal cognition. Lower abilities in specific cognitive systems, particularly perceptual speed and episodic memory, may contribute to greater susceptibility to scams in those with MCI.
Keywords: Aged; Aged, 80 and over; Aging; Cognitive Dysfunction; Crime Victims; Disease Susceptibility; Female; Humans; Male; Memory, Episodic; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales; Residence Characteristics; Self Report

Mindfulness in the Maintenance of Cognitive Capacities in Alzheimer's Disease: A Randomized Clinical Trial. - Quintana-Hernández, Domingo J; Miró-Barrachina, María T; Ibáñez-Fernández, Ignacio J; Pino, Angelo Santana-Del; Quintana-Montesdeoca, María P; Rodríguez-de Vera, Bienvenida; Morales-Casanova, David; Pérez-Vieitez, María Del Carmen; Rodríguez-García, Javier; Bravo-Caraduje, Noelia (J Alzheimers Dis, 2016)
BACKGROUND: The Canary Islands longitudinal study on non-pharmacological treatments showed the overall effectiveness of mindfulness in Alzheimer's disease (AD). However, no specific data on the maintenance of cognitive capacities were presented. OBJECTIVE: To determine whether the practice of mindfulness modifies the course of cognitive impairment in AD. METHODS: DESIGN: Longitudinal, non-inferiority and equivalence, randomized clinical trial, repeated-measures design, with three experimental groups and one control group. PARTICIPANTS: Patients with AD who voluntarily attended the Lidia García Foundation (n = 502). Only those who were treated with donepezil and MMSE ≥18 were included (n = 120). INTERVENTION: Over a two-year period, each group carried out three weekly sessions of stimulation based on mindfulness, cognitive stimulation therapy, and progressive muscle relaxation. MEASURES: Cognitive assessment CAMDEX-R (MMSE and CAMCOG). STATISTICAL ANALYSIS: Repeated-measures ANOVA (p <  0.05) and the effect size Cohen's d were performed. RESULTS: The mindfulness group showed significant scores compared with the control and muscle relaxation groups (p <  0.05), while mindfulness and cognitive stimulation therapy were equivalent (p≥0.05). Group cognitive stimulation evolved better than the control (p <  0.05) group but not better than the muscle relaxation group (p≥0.05). The effect size compared over two years was large for the mindfulness group (p≥0.80), moderate for the relaxation group (p≥0.50), and low for the cognitive stimulation group (p≥0.20). CONCLUSION: The practice of mindfulness maintained cognitive function over a period of two years. This longitudinal study suggests that mindfulness can be used as a non-pharmacological treatment to slow cognitive impairment in AD.
Keywords: Age Factors; Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Cognition Disorders; Double-Blind Method; Female; Humans; Longitudinal Studies; Male; Mental Status Schedule; Mindfulness; Neuropsychological Tests; Treatment Outcome

miR-302 Attenuates Amyloid-β-Induced Neurotoxicity through Activation of Akt Signaling. - Li, Hsin-Hua; Lin, Shi-Lung; Huang, Chien-Ning; Lu, Fung-Jou; Chiu, Pai-Yi; Huang, Wen-Nung; Lai, Te-Jen; Lin, Chih-Li (J Alzheimers Dis, 2016)
Deficiency of insulin signaling has been linked to diabetes and ageing-related neurodegenerative diseases such as Alzheimer's disease (AD). In this regard, brains exhibit defective insulin receptor substrate-1 (IRS-1) and hence result in alteration of insulin signaling in progression of AD, the most common cause of dementia. Consequently, dysregulation of insulin signaling plays an important role in amyloid-β (Aβ)-induced neurotoxicity. As the derivation of induced pluripotent stem cells (iPSC) involves cell reprogramming, it may provide a means for regaining the control of ageing-associated dysfunction and neurodegeneration via affecting insulin-related signaling. To this, we found that an embryonic stem cell (ESC)-specific microRNA, miR-302, silences phosphatase and tensin homolog (PTEN) to activate Akt signaling, which subsequently stimulates nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) elevation and hence inhibits Aβ-induced neurotoxicity. miR-302 is predominantly expressed in iPSCs and is known to regulate several important biological processes of anti-oxidative stress, anti-apoptosis, and anti-aging through activating Akt signaling. In addition, we also found that miR-302-mediated Akt signaling further stimulates Nanog expression to suppress Aβ-induced p-Ser307 IRS-1 expression and thus enhances tyrosine phosphorylation and p-Ser 473-Akt/p-Ser 9-GSK3β formation. Furthermore, our in vivo studies revealed that the mRNA expression levels of both Nanog and miR-302-encoding LARP7 genes were significantly reduced in AD patients' blood cells, providing a novel diagnosis marker for AD. Taken together, our findings demonstrated that miR-302 is able to inhibit Aβ-induced cytotoxicity via activating Akt signaling to upregulate Nrf2 and Nanog expressions, leading to a marked restoration of insulin signaling in AD neurons.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Cell Line, Tumor; Cell Survival; Female; Glycogen Synthase Kinase 3 beta; Heme Oxygenase-1; Humans; Insulin; Male; Membrane Potential, Mitochondrial; MicroRNAs; Neurons; NF-E2-Related Factor 2; Oxidative Stress; Proto-Oncogene Proteins c-akt; PTEN Phosphohydrolase; Reactive Oxygen Species; Ribonucleoproteins

A Mitochondrial Role of SV2a Protein in Aging and Alzheimer's Disease: Studies with Levetiracetam. - Stockburger, Carola; Miano, Davide; Baeumlisberger, Marion; Pallas, Thea; Arrey, Tabiwang N; Karas, Michael; Friedland, Kristina; Müller, Walter E (J Alzheimers Dis, 2016)
Aberrant neuronal network activity associated with neuronal hyperexcitability seems to be an important cause of cognitive decline in aging and Alzheimer's disease (AD). Out of many antiepileptics, only levetiracetam improved cognitive dysfunction in AD patients and AD animal models by reducing hyperexcitability. As impaired inhibitory interneuronal function, rather than overactive neurons, seems to be the underlying cause, improving impaired neuronal function rather than quieting overactive neurons might be relevant in explaining the lack of activity of the other antiepileptics. Interestingly, improvement of cognitive deficits by levetiracetam caused by small levels of soluble Aβ was accompanied by improvement of synaptic function and plasticity. As the negative effects of Aβ on synaptic plasticity strongly correlate with mitochondrial dysfunction, wehypothesized that the effect of levetiracetam on synaptic activity might be raised by an improved mitochondrial function. Accordingly, we investigated possible effects of levetiracetam on neuronal deficits associated with mitochondrial dysfunction linked to aging and AD. Levetiracetam improved several aspects of mitochondrial dysfunction including alterations of fission and fusion balance in a cell model for aging and early late-onset AD. We demonstrate for the first time, using immunohistochemistry and proteomics, that the synaptic vesicle protein 2A (SV2a), the molecular target of levetiracetam, is expressed in mitochondria. In addition, levetiracetam shows significant effect on the opening of the mitochondrial permeability transition pore. Importantly, the effects of levetiracetam were significantly abolished when SV2a was knockdown using siRNA. In conclusion, interfering with the SV2a protein at the mitochondrial level and thereby improving mitochondrial function might represent an additional therapeutic effect of levetiracetam to improve symptoms of late-onset AD.
Keywords: Adenosine Triphosphate; Aging; Alzheimer Disease; Animals; Brain; Cell Line; Cognition Disorders; Female; GAP-43 Protein; Gene Expression Regulation; Humans; Male; Membrane Glycoproteins; Mitochondria; Mitochondrial Membrane Transport Proteins; Nerve Tissue Proteins; Nitroprusside; Nootropic Agents; Piracetam; Proteomics; Rats; RNA, Small Interfering

Moderate-to-High Intensity Physical Exercise in Patients with Alzheimer's Disease: A Randomized Controlled Trial. - Hoffmann, Kristine; Sobol, Nanna A; Frederiksen, Kristian S; Beyer, Nina; Vogel, Asmus; Vestergaard, Karsten; Brændgaard, Hans; Gottrup, Hanne; Lolk, Annette; Wermuth, Lene; Jacobsen, Søren; Laugesen, Lars P; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Studies of physical exercise in patients with Alzheimer's disease (AD) are few and results have been inconsistent. OBJECTIVE: To assess the effects of a moderate-to-high intensity aerobic exercise program in patients with mild AD. METHODS: In a randomized controlled trial, we recruited 200 patients with mild AD to a supervised exercise group (60-min sessions three times a week for 16 weeks) or to a control group. Primary outcome was changed from baseline in cognitive performance estimated by Symbol Digit Modalities Test (SDMT) in the intention-to-treat (ITT) group. Secondary outcomes included changes in quality of life, ability to perform activities of daily living, and in neuropsychiatric and depressive symptoms. RESULTS: The ITT analysis showed no significant differences between intervention and control groups in change from baseline of SDMT, other cognitive tests, quality of life, or activities of daily living. The change from baseline in Neuropsychiatric Inventory differed significantly in favor of the intervention group (mean: -3.5, 95% confidence interval (CI) -5.8 to -1.3, p = 0.002). In subjects who adhered to the protocol, we found a significant effect on change from baseline in SDMT as compared with the control group (mean: 4.2, 95% CI 0.5 to 7.9, p = 0.028), suggesting a dose-response relationship between exercise and cognition. CONCLUSIONS: This is the first randomized controlled trial with supervised moderate-to-high intensity exercise in patients with mild AD. Exercise reduced neuropsychiatric symptoms in patients with mild AD, with possible additional benefits of preserved cognition in a subgroup of patients exercising with high attendance and intensity.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cognition; Depression; Exercise; Exercise Therapy; Female; Humans; Male; Middle Aged; Quality of Life; Treatment Outcome

Modulation of miR-19 in Aluminum-Induced Neural Cell Apoptosis. - Zhu, Mingming; Huang, Cong; Ma, Xiao; Wu, Rui; Zhu, Weiwei; Li, Xiaoting; Liang, Zhaofeng; Deng, Feifei; Zhu, Jianyun; Xie, Wei; Yang, Xue; Jiang, Ye; et al. (J Alzheimers Dis, 2016)
Neuronal cell death is an important feature of neurodegeneration. Aluminum is associated with neurodegenerative disorders, particularly Alzheimer's disease. However, the underlying mechanisms by which aluminum induces neuronal apoptosis remain to be elucidated. miR-19 is a key miRNA implicated in regulating cell survival process, while the role of miR-19 in Alzheimer's disease has not been investigated. In the present study, we showed that Aluminum maltolate (Al-malt), a lipophilic Al complex which is a common component of human diet with the ability to facilitate the entry of Al into the brain, induced apoptosis in human neuroblastoma SH-SY5Y cells, along with downregulation of miR-19a/miR-19b, upregulation of miR-19-targeted PTEN, and alterations of its downstream apoptosis related proteins including AKT, p53, Bax, and Bcl-2. miR-19 overexpression attenuated Al-malt-induced apoptosis as well as changes in the expression of apoptosis related proteins in SH-SY5Y cells. We further revealed that exposure of rats to Al-malt for 12 weeks at doses relevant to human exposure significantly elevated Al concentrations in serum and brain tissues. Al-malt dose-dependently induced apoptosis in rat brain, as evidenced by increased caspase activation and increased TUNEL staining. Consistent with in vitro results, Al-malt reduced miR-19 expression and altered the expression of apoptotic related proteins in rat brain. Taken together, our data suggest for the first time that miR-19 modulation is critically involved in Al-induced neural cell apoptosis. Findings from this study could provide new insight into the molecular mechanisms of Al-associated neurodegenerative pathogenesis.
Keywords: Aluminum; Animals; Apoptosis; Brain; Cell Line, Tumor; Dose-Response Relationship, Drug; Humans; Male; MicroRNAs; Neurons; Proto-Oncogene Proteins c-akt; PTEN Phosphohydrolase; Rats, Sprague-Dawley; Tumor Suppressor Protein p53

Molecular markers of amnestic mild cognitive impairment among Mexican Americans. - Edwards, Melissa; Hall, James; Williams, Benjamin; Johnson, Leigh; O'Bryant, Sid (J Alzheimers Dis, 2016)
BACKGROUND: Mexican Americans face a significant health disparity when it comes to Alzheimer's disease (AD) as they present with higher rates of the disease and develop AD at an earlier age compared to other ethnic groups. Recent work identified a proteomic profile of AD among this population; however, no work to date has sought to examine the biological profile of pre-AD among Mexican Americans. OBJECTIVE: This study aims to identify an amnestic mild cognitive impairment (aMCI) proteomic profile among Mexican Americans. METHODS: Data were analyzed from 284 Mexican American participants (aMCI, n = 73; normal controls, n = 211) from the Health & Aging Brain among Latino Elders study. Fasting serum samples were analyzed using a multi-plex biomarker assay platform. A biomarker profile was generated using random forest analyses. RESULTS: Among aMCI cases, the biomarker profile was found to be largely inflammatory with the top three markers shown to include TNFα, IL10, and TARC. The overall diagnostic accuracy of the biomarkers in detecting aMCI was 96% (sensitivity = 0.82; specificity = 0.97). Inclusion of clinical variables with the selected biomarkers did not impact the overall detection accuracy (area under the curve = 0.96) but led to a slight improvement in specificity (specificity = 0.99) and decrease in sensitivity (sensitivity = 0.74). CONCLUSION: The biomarker profile of aMCI was shown to be different from our previously generated AD profile among Mexican Americans, which was largely metabolic in nature. The findings implicate a possible interplay between inflammatory and metabolic processes and additional work is needed to further examine this.
Keywords: Aged; Alzheimer Disease; Area Under Curve; Biomarkers; Cognitive Dysfunction; Female; Humans; Male; Mexican Americans; Middle Aged; Neuropsychological Tests; Proteome; Sensitivity and Specificity; United States

Morroniside-Induced PP2A Activation Antagonizes Tau Hyperphosphorylation in a Cellular Model of Neurodegeneration. - Yang, Cui-cui; Kuai, Xue-xian; Gao, Wen-bin; Yu, Jian-chun; Wang, Qi; Li, Lin; Zhang, Lan (J Alzheimers Dis, 2016)
BACKGROUND: An accumulation of hyperphosphorylated tau in the brain is a hallmark of Alzheimer's disease (AD). Deficits in protein phosphatase 2A (PP2A) are associated with tau hyperphosphorylation in AD. OBJECTIVE: To investigate the effects of morroniside (MOR), isolated from Cornus officinalis, on tau hyperphosphorylation and its underlying mechanisms related to PP2A. METHODS: SK-N-SH cells were pretreated with 50-200 μM MOR for 24 h followed by 20 nM okadaic acid (OA) for 6 h. PP2Ac siRNA was transfected into HEK293 cells to determine the direct interaction of MOR with PP2A. Western blotting was used to measure the expression of proteins and enzymes. PP2A activity was measured by molybdenum blue spectrophotometry. RESULTS: Pretreatment with MOR improved the cellular morphological damage and inhibited tau hyperphosphorylation in SK-N-SH cells induced by OA, a PP2A inhibitor. Moreover, MOR increased PP2A activity, concurrent with a decrease in the expression of demethylated PP2A at Leu309 and phosphorylated PP2A at Tyr307. MOR decreased protein phosphatase methylesterase 1 (PME-1) expression and the ratio of PME-1/leucine carboxyl methyltransferase 1 (LCMT-1). Furthermore, MOR treatment decreased the phosphorylation of Src at Tyr416, which regulates the phosphorylation of PP2A. MOR had no effect on PP2Ac expression and tau hyperphosphorylation in PP2Ac siRNA-transfected cells. CONCLUSION: MOR attenuated OA-induced tau hyperphosphorylation via PP2A activation, and its mechanism might be related to the regulation of PP2Ac post-translational modification and upstream enzymes such as Src and PME-1.
Keywords: Analysis of Variance; Cell Line; Enzyme Inhibitors; Gene Expression Regulation; Glycogen Synthase Kinase 3 beta; Glycosides; HEK293 Cells; Humans; Neuroblastoma; Okadaic Acid; Phosphorylation; Protein Phosphatase 2; RNA, Small Interfering; tau Proteins; Transfection; Tyrosine

Multifunctional Effect of Human Serum Albumin Reduces Alzheimer's Disease Related Pathologies in the 3xTg Mouse Model. - Ezra, Assaf; Rabinovich-Nikitin, Inna; Rabinovich-Toidman, Polina; Solomon, Beka (J Alzheimers Dis, 2016)
Alzheimer's disease (AD), the prevalent dementia in the elderly, involves many related and interdependent pathologies that manifests simultaneously, eventually leading to cognitive impairment and death. No treatment is currently available; however, an agent addressing several key pathologies simultaneously has a better therapeutic potential. Human serum albumin (HSA) is a highly versatile protein, harboring multifunctional properties that are relevant to key pathologies underlying AD. This study provides insight into the mechanism for HSA's therapeutic effect. In vivo, a myriad of beneficial effects were observed by pumps infusing HSA intracerebroventricularly, for the first time in an AD 3xTg mice model. A significant effect on amyloid-β (Aβ) pathology was observed. Aβ1-42, soluble oligomers, and total plaque area were reduced. Neuroblastoma SHSY5Y cell line confirmed that the reduction in Aβ1-42 toxicity was due to direct binding rather than other properties of HSA. Total and hyperphosphorylated tau were reduced along with an increase in tubulin, suggesting increased microtubule stability. HSA treatment also reduced brain inflammation, affecting both astrocytes and microglia markers. Finally, evidence for blood-brain barrier and myelin integrity repair was observed. These multidimensional beneficial effects of intracranial administrated HSA, together or individually, contributed to an improvement in cognitive tests, suggesting a non-immune or Aβ efflux dependent means for treating AD.
Keywords: Albumins; Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Blood-Brain Barrier; Brain; Calcium; Cell Line, Tumor; Cognition Disorders; Disease Models, Animal; Drug Delivery Systems; Encephalitis; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mutation; Neuroblastoma; Neuropsychological Tests; Peptide Fragments; Presenilin-1; tau Proteins

Multimodal Magnetic Resonance Imaging in Alzheimer's Disease Patients at Prodromal Stage. - Eustache, Pierre; Nemmi, Federico; Saint-Aubert, Laure; Pariente, Jérémie; Péran, Patrice (J Alzheimers Dis, 2016)
One objective of modern neuroimaging is to identify markers that can aid in diagnosis, monitor disease progression, and impact long-term drug analysis. In this study, physiopathological modifications in seven subcortical structures of patients with mild cognitive impairment (MCI) due to Alzheimer's disease (AD) were characterized by simultaneously measuring quantitative magnetic resonance parameters that are sensitive to complementary tissue characteristics (e.g., volume atrophy, shape changes, microstructural damage, and iron deposition). Fourteen MCI patients and fourteen matched, healthy subjects underwent 3T-magnetic resonance imaging with whole-brain, T1-weighted, T2*-weighted, and diffusion-tensor imaging scans. Volume, shape, mean R2*, mean diffusivity (MD), and mean fractional anisotropy (FA) in the thalamus, hippocampus, putamen, amygdala, caudate nucleus, pallidum, and accumbens were compared between MCI patients and healthy subjects. Comparisons were then performed using voxel-based analyses of R2*, MD, FA maps, and voxel-based morphometry to determine which subregions showed the greatest difference for each parameter. With respect to the micro- and macro-structural patterns of damage, our results suggest that different and distinct physiopathological processes are present in the prodromal phase of AD. MCI patients had significant atrophy and microstructural changes within their hippocampi and amygdalae, which are known to be affected in the prodromal stage of AD. This suggests that the amygdala is affected in the same, direct physiopathological process as the hippocampus. Conversely, atrophy alone was observed within the thalamus and putamen, which are not directly involved in AD pathogenesis. This latter result may reflect another mechanism, whereby atrophy is linked to indirect physiopathological processes.
Keywords: Aged; Alzheimer Disease; Biomarkers; Brain; Cognitive Dysfunction; Diffusion Tensor Imaging; Female; Fluorodeoxyglucose F18; Humans; Magnetic Resonance Imaging; Male; Mental Status Schedule; Multimodal Imaging; Neuropsychological Tests; Organ Size; Positron-Emission Tomography; Prodromal Symptoms; Radiopharmaceuticals

Naphthoquinone-Tryptophan Hybrid Inhibits Aggregation of the Tau-Derived Peptide PHF6 and Reduces Neurotoxicity. - Frenkel-Pinter, Moran; Tal, Sharon; Scherzer-Attali, Roni; Abu-Hussien, Malak; Alyagor, Idan; Eisenbaum, Tal; Gazit, Ehud; Segal, Daniel (J Alzheimers Dis, 2016)
Tauopathies, such as Alzheimer's disease (AD), are a group of disorders characterized neuropathologically by intracellular toxic accumulations of abnormal protein aggregates formed by misfolding of the microtubule-associated protein tau. Since protein self-assembly appears to be an initial key step in the pathology of this group of diseases, intervening in this process can be both a prophylactic measure and a means for modifying the course of the disease for therapeutic purposes. We and others have shown that aromatic small molecules can be effective inhibitors of aggregation of various protein assemblies, by binding to the aromatic core in aggregation-prone motifs and preventing their self-assembly. Specifically, we have designed a series of small aromatic naphthoquinone-tryptophan hybrid molecules as candidate aggregation inhibitors of β -sheet based assembly and demonstrated their efficacy toward inhibiting aggregation of the amyloid-β peptide, another culprit of AD, as well as of various other aggregative proteins involved in other protein misfolding diseases. Here we tested whether a leading naphthoquinone-tryptophan hybrid molecule, namely NQTrp, can be repurposed as an inhibitor of the aggregation of the tau protein in vitro and in vivo. We show that the molecule inhibits the in vitro assembly of PHF6, the aggregation-prone fragment of tau protein, reduces hyperphosphorylated tau deposits and ameliorates tauopathy-related behavioral defect in an established transgenic Drosophila model expressing human tau. We suggest that NQTrp, or optimized versions of it, could act as novel disease modifying drugs for AD and other tauopathies.
Keywords: Animals; Carrier Proteins; Disease Models, Animal; Drosophila; Drosophila Proteins; Eye; Female; Humans; Immunoprecipitation; In Vitro Techniques; Larva; Locomotion; Mice, Transgenic; Microscopy, Electron, Scanning; Naphthoquinones; Neurotoxicity Syndromes; Protein Aggregates; Retinal Pigments; tau Proteins; Tryptophan

Neurophysiological assessment of Alzheimer's disease individuals by a single electroencephalographic marker. - Lizio, Roberta; Del Percio, Claudio; Marzano, Nicola; Soricelli, Andrea; Yener, Görsev G; Başar, Erol; Mundi, Ciro; De Rosa, Salvatore; Triggiani, Antonio Ivano; Ferri, Raffaele; Arnaldi, Dario; Nobili, Flavio Mariano; et al. (J Alzheimers Dis, 2016)
Here we presented a single electroencephalographic (EEG) marker for a neurophysiological assessment of Alzheimer's disease (AD) patients already diagnosed by current guidelines. The ability of the EEG marker to classify 127 AD individuals and 121 matched cognitively intact normal elderly (Nold) individuals was tested. Furthermore, its relationship to AD patients' cognitive status and structural brain integrity was examined. Low-resolution brain electromagnetic tomography (LORETA) freeware estimated cortical sources of resting state eyes-closed EEG rhythms. The EEG marker was defined as the ratio between the activity of parieto-occipital cortical sources of delta (2-4 Hz) and low-frequency alpha (8-10.5 Hz) rhythms. Results showed 77.2% of sensitivity in the recognition of the AD individuals; 65% of specificity in the recognition of the Nold individuals; and 0.75 of area under the receiver-operating characteristic curve. Compared to the AD subgroup with the EEG maker within one standard deviation of the Nold mean (EEG-), the AD subgroup with EEG+ showed lower global cognitive status, as revealed by Mini-Mental State Evaluation score, and more abnormal values of white-matter and cerebrospinal fluid normalized volumes, as revealed by structural magnetic resonance imaging. We posit that cognitive and functional status being equal, AD patients with EEG+ should receive special clinical attention due to a neurophysiological "frailty". EEG+ label can be also used in clinical trials (i) to form homogeneous groups of AD patients diagnosed by current guidelines and (ii) as end-point to evaluate intervention effects.
Keywords: Aged; Alzheimer Disease; Biomarkers; Brain Mapping; Case-Control Studies; Cognition Disorders; Electroencephalography; Female; Humans; Italy; Magnetic Resonance Imaging; Male; Middle Aged; Occipital Lobe; Rest; ROC Curve; Turkey

Normal Amplitude of Electroretinography and Visual Evoked Potential Responses in AβPP/PS1 Mice. - Leinonen, Henri; Lipponen, Arto; Gurevicius, Kestutis; Tanila, Heikki (J Alzheimers Dis, 2016)
Alzheimer's disease has been shown to affect vision in human patients and animal models. This may pose the risk of bias in behavior studies and therefore requires comprehensive investigation. We recorded electroretinography (ERG) under isoflurane anesthesia and visual evoked potentials (VEP) in awake amyloid expressing AβPPswe/PS1dE9 (AβPP/PS1) and wild-type littermate mice at a symptomatic age. The VEPs in response to patterned stimuli were normal in AβPP/PS1 mice. They also showed normal ERG amplitude but slightly shortened ERG latency in dark-adapted conditions. Our results indicate subtle changes in visual processing in aged male AβPP/PS1 mice specifically at a retinal level.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Contrast Sensitivity; Disease Models, Animal; Electroencephalography; Electroretinography; Evoked Potentials, Visual; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mutation; Photic Stimulation; Presenilin-1; Reaction Time

Novel Selective Calpain 1 Inhibitors as Potential Therapeutics in Alzheimer's Disease. - Fà, Mauro; Zhang, Hong; Staniszewski, Agnieszka; Saeed, Faisal; Shen, Li W; Schiefer, Isaac T; Siklos, Marton I; Tapadar, Subhasish; Litosh, Vladislav A; Libien, Jenny; Petukhov, Pavel A; Teich, Andrew F; et al. (J Alzheimers Dis, 2016)
Alzheimer's disease, one of the most important brain pathologies associated with neurodegenerative processes, is related to overactivation of calpain-mediated proteolysis. Previous data showed a compelling efficacy of calpain inhibition against abnormal synaptic plasticity and memory produced by the excess of amyloid-β, a distinctive marker of the disease. Moreover, a beneficial effect of calpain inhibitors in Alzheimer's disease is predictable by the occurrence of calpain hyperactivation leading to impairment of memory-related pathways following abnormal calcium influxes that might ensue independently of amyloid-β elevation. However, molecules currently available as effective calpain inhibitors lack adequate selectivity. This work is aimed at characterizing the efficacy of a novel class of epoxide-based inhibitors, synthesized to display improved selectivity and potency towards calpain 1 compared to the prototype epoxide-based generic calpain inhibitor E64. Both functional and preliminary toxicological investigations proved the efficacy, potency, and safety of the novel and selective calpain inhibitors NYC438 and NYC488 as possible therapeutics against the disease.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Cysteine Proteinase Inhibitors; Disease Models, Animal; Dose-Response Relationship, Drug; Fear; Glycoproteins; Hippocampus; Humans; In Vitro Techniques; Long-Term Potentiation; Maze Learning; Memory; Mice; Mice, Inbred ICR; Mice, Transgenic; Mutation; Patch-Clamp Techniques; Peptide Fragments; Presenilin-1; Spectrin

N-truncated Aβ2-X starting with position two in sporadic Alzheimer's disease cases and two Alzheimer mouse models. - Savastano, Adriana; Klafki, Hans; Haußmann, Ute; Oberstein, Timo Jan; Muller, Petr; Wirths, Oliver; Wiltfang, Jens; Bayer, Thomas A (J Alzheimers Dis, 2016)
According to the modified amyloid hypothesis, the key event in the pathogenesis of Alzheimer's disease (AD) is the deposition of neurotoxic amyloid β-peptides (Aβs) in plaques and cerebral blood vessels. Additionally to full-length peptides, a great diversity of N-truncated Aβ variants is derived from the larger amyloid-β protein precursor (AβPP). Vast evidence suggests that Aβx-42 isoforms play an important role in triggering neurodegeneration due to their high abundance, amyloidogenic propensity and toxicity. Although N-truncated Aβ peptides and Aβx-42 species appear to be the crucial players in AD etiology, the Aβ2-X isoforms did not receive much attention yet. The present study is the first to show immunohistochemical evidence of Aβ2-X in cases of AD and its distribution in AβPP/PS1KI and 5XFAD transgenic mouse models using a novel antibody pAB77 that has been developed using Aβ2-14 as antigen. Positive plaques and congophilic amyloid angiopathy (CAA) were observed in AD cases and in both mouse models. While in AD cases, abundant CAA and less pronounced plaque pathology was evident, the two mouse models showed predominantly extracellular Aβ deposits and minor CAA staining. Western blotting and a capillary isoelectric focusing immunoassay demonstrated the high specificity of the antibody pAb77 against Aβ-variants starting with the N-terminal Alanine-2.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Animals; Blotting, Western; Brain; Cerebral Amyloid Angiopathy; Disease Models, Animal; Female; Humans; Male; Mice; Mice, Transgenic; Plaque, Amyloid

Oculodentodigital dysplasia with massive brain calcification and a new mutation of GJA1 gene. - Tumminelli, Gemma; Di Donato, Ilaria; Guida, Valentina; Rufa, Alessandra; De Luca, Alessandro; Federico, Antonio (J Alzheimers Dis, 2016)
Oculodentodigital dysplasia (ODDD) [MIM 164200] is a rare disorder caused by mutations in the gap junction alpha 1 (GJA1) gene encoding for connexin 43 (Cx43). Typical signs include type III syndactyly, microphtalmia, microdontia, and neurological disturbances. We report a 59-year-old man having clinical symptoms and signs suggestive of ODDD, with some rarely reported features, that is the presence of gross calcifications of basal ganglia and cerebellar nuclei. Mutation analysis of GJA1 gene identified an unreported heterozygous missense mutation [NM_000165.3:c.124 G>C;p.(Glu42Gln)], which may be thought to alter the brain microvessels leading to massive calcifications, as in primary familial brain calcification.
Keywords: Basal Ganglia; Calcinosis; Connexin 43; Craniofacial Abnormalities; DNA Mutational Analysis; Eye Abnormalities; Fingers; Foot Deformities, Congenital; Humans; Male; Middle Aged; Mutation, Missense; Syndactyly; Tomography, X-Ray Computed; Tooth Abnormalities

Older Adults Taking AT1-Receptor Blockers Exhibit Reduced Cerebral Amyloid Retention. - Nation, Daniel A; Ho, Jean; Yew, Belinda (J Alzheimers Dis, 2016)
BACKGROUND: Evidence suggests that angiotensin II AT1-receptor blockers (ARBs) may be protective against dementia, and studies in transgenic animals indicate that this may be due to improved amyloid-β (Aβ) clearance. OBJECTIVE: We investigated whether taking ARBs was associated with an attenuation of age-related increases in cerebral Aβ retention, and reduced progression to dementia. METHODS: Eight hundred seventy-one stroke-free and dementia-free older adults from the Alzheimer's Disease Neuroimaging Initiative (ADNI) study underwent baseline lumbar puncture, and a subgroup (n = 124) underwent 12 and 24 month follow-up lumbar puncture. Participants were followed at variable intervals for clinical progression to dementia. Linear mixed models and ANCOVA compared ARBs users with those taking other antihypertensives (O-antiHTN) or no antihypertensives (No-antiHTN) on cerebrospinal fluid (CSF) Aβ and phosphorylated tau (P-tau) levels. Cox regression and chi-square analyses compared groups on progression to dementia. RESULTS: ARBs users exhibited greater vascular risk and lower educational attainment than the No-antiHTN group. Longitudinal analyses indicated higher CSF Aβ and lower P-tau in ARBs users versus other groups. Cross-sectional analyses revealed age-related decreases in CSF Aβ in other groups but not ARBs users. ARBs users were less likely to progress to dementia and showed reduced rate of progression relative to the No-antiHTN group. DISCUSSION: Patients taking ARBs showed an attenuation of age-related decreases in CSF Aβ, a finding that is consistent with studies done in transgenic animals. These findings may partly explain why ARBs users show reduced progression to dementia despite their lower educational attainment and greater vascular risk burden.
Keywords: Aged; Aged, 80 and over; Aging; Amyloid beta-Peptides; Angiotensin Receptor Antagonists; Antihypertensive Agents; Chi-Square Distribution; Cross-Sectional Studies; Dementia; Female; Humans; Longitudinal Studies; Male; Middle Aged; Peptide Fragments; Psychiatric Status Rating Scales; Regression Analysis; tau Proteins; Time Factors

Omega-3 Fatty Acid Status Enhances the Prevention of Cognitive Decline by B Vitamins in Mild Cognitive Impairment. - Oulhaj, Abderrahim; Jernerén, Fredrik; Refsum, Helga; Smith, A David; de Jager, Celeste A (J Alzheimers Dis, 2016)
A randomized trial (VITACOG) in people with mild cognitive impairment (MCI) found that B vitamin treatment to lower homocysteine slowed the rate of cognitive and clinical decline. We have used data from this trial to see whether baseline omega-3 fatty acid status interacts with the effects of B vitamin treatment. 266 participants with MCI aged ≥70 years were randomized to B vitamins (folic acid, vitamins B6 and B12) or placebo for 2 years. Baseline cognitive test performance, clinical dementia rating (CDR) scale, and plasma concentrations of total homocysteine, total docosahexaenoic and eicosapentaenoic acids (omega-3 fatty acids) were measured. Final scores for verbal delayed recall, global cognition, and CDR sum-of-boxes were better in the B vitamin-treated group according to increasing baseline concentrations of omega-3 fatty acids, whereas scores in the placebo group were similar across these concentrations. Among those with good omega-3 status, 33% of those on B vitamin treatment had global CDR scores >0 compared with 59% among those on placebo. For all three outcome measures, higher concentrations of docosahexaenoic acid alone significantly enhanced the cognitive effects of B vitamins, while eicosapentaenoic acid appeared less effective. When omega-3 fatty acid concentrations are low, B vitamin treatment has no effect on cognitive decline in MCI, but when omega-3 levels are in the upper normal range, B vitamins interact to slow cognitive decline. A clinical trial of B vitamins combined with omega-3 fatty acids is needed to see whether it is possible to slow the conversion from MCI to AD.
Keywords: Aged; Aged, 80 and over; Cognition; Cognitive Dysfunction; Disease Progression; Fatty Acids, Omega-3; Female; Humans; Male; Neuropsychological Tests; Treatment Outcome; Vitamin B Complex

The Online Environment: A Key Variable in the Ethical Response to Complementary and Alternative Medicine for Alzheimer's Disease. - Robillard, Julie M (J Alzheimers Dis, 2016)
Racine et al.'s Ethics Review highlights the challenges associated with the use of complementary and alternative medicine (CAM) in the context of early diagnosis of Alzheimer's disease (AD). As CAM are increasingly promoted and sold on the Internet, the unregulated online environment has the potential to significantly impact the health and well-being of the aging demographic, and in particular of individuals concerned about AD. In this response, the ethical challenges specific to the online environment are discussed and solutions are put forward to empower the aging population to maximize the benefits of the online environment while minimizing the potential harms of misinformation, conflict of interest, and other ethical concerns.
Keywords: Alzheimer Disease; Complementary Therapies; Humans

Optimization of Statistical Single Subject Analysis of Brain FDG PET for the Prognosis of Mild Cognitive Impairment-to-Alzheimer's Disease Conversion. - Lange, Catharina; Suppa, Per; Frings, Lars; Brenner, Winfried; Spies, Lothar; Buchert, Ralph (J Alzheimers Dis, 2016)
BACKGROUND: Positron emission tomography (PET) with the glucose analog F-18-fluorodeoxyglucose (FDG) is widely used in the diagnosis of neurodegenerative diseases. Guidelines recommend voxel-based statistical testing to support visual evaluation of the PET images. However, the performance of voxel-based testing strongly depends on each single preprocessing step involved. OBJECTIVE: To optimize the processing pipeline of voxel-based testing for the prognosis of dementia in subjects with amnestic mild cognitive impairment (MCI). METHODS: The study included 108 ADNI MCI subjects grouped as 'stable MCI' (n = 77) or 'MCI-to-AD converter' according to their diagnostic trajectory over 3 years. Thirty-two ADNI normals served as controls. Voxel-based testing was performed with the statistical parametric mapping software (SPM8) starting with default settings. The following modifications were added step-by-step: (i) motion correction, (ii) custom-made FDG template, (iii) different reference regions for intensity scaling, and (iv) smoothing was varied between 8 and 18 mm. The t-sum score for hypometabolism within a predefined AD mask was compared between the different settings using receiver operating characteristic (ROC) analysis with respect to differentiation between 'stable MCI' and 'MCI-to-AD converter'. The area (AUC) under the ROC curve was used as performance measure. RESULTS: The default setting provided an AUC of 0.728. The modifications of the processing pipeline improved the AUC up to 0.832 (p = 0.046). Improvement of the AUC was confirmed in an independent validation sample of 241 ADNI MCI subjects (p = 0.048). CONCLUSION: The prognostic value of voxel-based single subject analysis of brain FDG PET in MCI subjects can be improved considerably by optimizing the processing pipeline.
Keywords: Aged; Alzheimer Disease; Area Under Curve; Brain; Cognitive Dysfunction; Disease Progression; Female; Fluorodeoxyglucose F18; Follow-Up Studies; Glucose; Humans; Image Interpretation, Computer-Assisted; Male; Positron-Emission Tomography; Prognosis; Radiopharmaceuticals; ROC Curve

An Optimized Combination of Ginger and Peony Root Effectively Inhibits Amyloid-β Accumulation and Amyloid-β-Mediated Pathology in AβPP/PS1 Double-Transgenic Mice. - Lim, Soonmin; Choi, Jin Gyu; Moon, Minho; Kim, Hyo Geun; Lee, Wonil; Bak, Hyoung-Rok; Sung, Hachang; Park, Chi Hye; Kim, Sun Yeou; Oh, Myung Sook (J Alzheimers Dis, 2016)
The progressive aggregation of amyloid-β protein (Aβ) into senile plaques is a major pathological factor of Alzheimer's disease (AD) and is believed to result in memory impairment. We aimed to investigate the effect of an optimized combination of ginger and peony root (OCGP), a standardized herbal mixture of ginger and peony root, on Aβ accumulation and memory impairment in amyloid-β protein precursor (AβPP)/presenilin 1 (PS1) double-transgenic mice. In an in vitro thioflavin T fluorescence assay, 100 μg/ml OCGP inhibited Aβ accumulation to the same extent as did 10 μM curcumin. Furthermore, AβPP/PS1 double-transgenic mice treated with OCGP (50 or 100 mg/kg/day given orally for 14 weeks) exhibited reduced Aβ plaque accumulation in the hippocampus and lower levels of glial fibrillary acid protein and cyclooxygease-2 expression compared with vehicle-treated controls. These results suggest that OCGP may prevent memory impairment in AD by inhibiting Aβ accumulation and inflammation in the brain.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Analysis of Variance; Animals; Cyclooxygenase 2; Disease Models, Animal; Dose-Response Relationship, Drug; Ginger; Glial Fibrillary Acidic Protein; Humans; Male; Mice; Mice, Transgenic; Mutation; Paeonia; Phytotherapy; Plant Preparations; Plaque, Amyloid; Presenilin-1

Palmomental Reflex a Relevant Sign in Early Alzheimer's Disease Diagnosis? - Gabelle, Audrey; Gutierrez, Laure-Anne; Dartigues, Jean-François; Ritchie, Karen; Touchon, Jacques; Berr, Claudine (J Alzheimers Dis, 2016)
BACKGROUND: Sophisticated and expensive biomarkers are proposed for the diagnostic of Alzheimer's disease (AD). The amyloid process seems to be early in AD, and brain amyloid load affects the frontal lobe. OBJECTIVE: To determine if certain simple clinical signs, especially frontal-related signs, could help reach an earlier and better diagnosis. METHODS: In the frame of the 3-City cohort, we conducted a nested case-control study comparing incident cases of AD to controls matched for age, gender, and education. The standardized neurological exam included extrapyramidal signs (akinesia, rigidity, rest tremor), pyramidal symptoms (spastic rigidity, Babinski reflex), primitive reflexes (snout, palmomental reflex grasping), and tremor (essential, intentional, head) at the time of diagnosis and two years before. RESULTS: We compared 106 incident AD subjects (mean age at diagnosis 82.2 (SD = 5.9); median MMSE at diagnosis = 23) to 208 matched controls. In patients younger than 80, palmomental reflexes were more frequent in AD than controls, two years before diagnosis (25.0 versus 7.0% , p = 0.03) and at time of diagnosis (30.3 versus 12.3% , p = 0.02). No difference was observed for other signs two years before diagnosis or for patients older than 80. CONCLUSION: Before diagnosis, the clinical examination of AD patients is not strictly normal; the primitive reflexes appear to be pathological. It might be in connection with the frontal amyloid load at an early stage of the disease. Clinical examination can reveal simple and interesting signs that deserve consideration as well as the other more invasive and expensive biomarkers.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cohort Studies; Early Diagnosis; Female; Follow-Up Studies; France; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Reflex

A Pathway Based Classification Method for Analyzing Gene Expression for Alzheimer's Disease Diagnosis. - Voyle, Nicola; Keohane, Aoife; Newhouse, Stephen; Lunnon, Katie; Johnston, Caroline; Soininen, Hilkka; Kloszewska, Iwona; Mecocci, Patrizia; Tsolaki, Magda; Vellas, Bruno; Lovestone, Simon; Hodges, Angela; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Recent studies indicate that gene expression levels in blood may be able to differentiate subjects with Alzheimer's disease (AD) from normal elderly controls and mild cognitively impaired (MCI) subjects. However, there is limited replicability at the single marker level. A pathway-based interpretation of gene expression may prove more robust. OBJECTIVES: This study aimed to investigate whether a case/control classification model built on pathway level data was more robust than a gene level model and may consequently perform better in test data. The study used two batches of gene expression data from the AddNeuroMed (ANM) and Dementia Case Registry (DCR) cohorts. METHODS: Our study used Illumina Human HT-12 Expression BeadChips to collect gene expression from blood samples. Random forest modeling with recursive feature elimination was used to predict case/control status. Age and APOE ɛ4 status were used as covariates for all analysis. RESULTS: Gene and pathway level models performed similarly to each other and to a model based on demographic information only. CONCLUSIONS: Any potential increase in concordance from the novel pathway level approach used here has not lead to a greater predictive ability in these datasets. However, we have only tested one method for creating pathway level scores. Further, we have been able to benchmark pathways against genes in datasets that had been extensively harmonized. Further work should focus on the use of alternative methods for creating pathway level scores, in particular those that incorporate pathway topology, and the use of an endophenotype based approach.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoproteins E; Cohort Studies; Datasets as Topic; Female; Gene Expression; Gene Expression Profiling; Humans; Male; Models, Genetic; Oligonucleotide Array Sequence Analysis; Signal Transduction

Patients that have Undergone Hemodialysis Exhibit Lower Amyloid Deposition in the Brain: Evidence Supporting a Therapeutic Strategy for Alzheimer's Disease by Removal of Blood Amyloid. - Sakai, Kazuyoshi; Senda, Takao; Hata, Ryuji; Kuroda, Makoto; Hasegawa, Midori; Kato, Masao; Abe, Masato; Kawaguchi, Kazunori; Nakai, Shigeru; Hiki, Yoshiyuki; Yuzawa, Yukio; Kitaguchi, Nobuya (J Alzheimers Dis, 2016)
As a proof of concept that removal of blood amyloid-β (Aβ) can reduce Aβ deposition in the brains of patients with Alzheimer's disease, cortices of patients who had undergone hemodialysis (HD), which removes Aβ from the blood, were histochemically analyzed; postmortem brain sections were stained with anti-Aβ antibodies. Brains from patients who had undergone HD had significantly fewer senile plaques than those of patient who had not undergone HD. This significant difference was also confirmed by silver staining. Our findings suggest that removal of blood Aβ by hemodialysis results in lower accumulation of Aβ in the brain.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Autopsy; Brain; Case-Control Studies; Humans; Kidney Diseases; Plaque, Amyloid; Renal Dialysis; Silver Staining; Statistics, Nonparametric

Patterns of Brain Iron Accumulation in Vascular Dementia and Alzheimer's Dementia Using Quantitative Susceptibility Mapping Imaging. - Moon, Yeonsil; Han, Seol-Heui; Moon, Won-Jin (J Alzheimers Dis, 2016)
BACKGROUND: Emerging evidence suggests that the excessive accumulation of iron in subcortical and deep gray matter has been related to dementia. However, the presence and pattern of iron accumulation in vascular dementia (VaD) and Alzheimer's disease (AD) are rarely investigated. OBJECTIVE: To examine and compare the pattern and presence of brain iron accumulation of VaD and AD using quantitative susceptibility mapping (QSM). MATERIALS AND METHODS: Twelve patients with VaD, 27 patients with AD, and 18 control subjects were recruited in this institutional review-board approved study. Susceptibility maps were reconstructed from a three-dimensional multiecho spoiled gradient-echo sequence. Four regions of interest were drawn manually on QSM images, namely the globus pallidus, putamen, caudate nucleus, and pulvinar nucleus of the thalamus. Comparisons of patient demographics, and iron concentrations among the VaD, AD, and control subjects were assessed using analysis of variance and post-hoc analyses. The relationships of age and cognitive state with susceptibility values were assessed using partial correlation analysis. RESULTS: In VaD and AD, overall susceptibility values were higher than those of control subjects. A significant difference in susceptibility values was found in the putamen and caudate nucleus (p <  0.001 and p = 0.002, respectively). However, susceptibility values did not differ between VaD and AD. Age and cognitive deficit severity were not related to susceptibility values in the VaD and AD groups. CONCLUSION: Increased iron deposition in the putamen and caudate nucleus in VaD and AD patients was not associated with age or the severity of cognitive deficits. Further evaluations are needed to determine the temporal changes in iron load and their diagnostic role in dementia pathology.
Keywords: Aged; Aging; Alzheimer Disease; Brain; Brain Mapping; Cognition; Dementia, Vascular; Female; Humans; Imaging, Three-Dimensional; Iron; Magnetic Resonance Imaging; Male; Mental Status Schedule; Retrospective Studies; Severity of Illness Index

PDE5 Exists in Human Neurons and is a Viable Therapeutic Target for Neurologic Disease. - Teich, Andrew F; Sakurai, Mikako; Patel, Mitesh; Holman, Cameron; Saeed, Faisal; Fiorito, Jole; Arancio, Ottavio (J Alzheimers Dis, 2016)
Phosphodiesterase 5 (PDE5) is a critical component of the cGMP-PKG axis of cellular signaling in neurons, and inhibition of PDE5 has been shown to be therapeutic in a wide range of neurologic conditions in animal models. However, enthusiasm for PDE5 inhibitors in humans is limited by data suggesting that PDE5 may not exist in human neurons. Here, we first show that past attempts to quantify PDE5 mRNA were flawed due to the use of incorrect primers, and that when correct primers are used, PDE5 mRNA is detectable in human brain tissue. We then show that PDE5 protein exists in human brain by western blot and ELISA. Most importantly, we performed immunohistochemistry and demonstrate that PDE5 is present in human neurons. We hope that this work will trigger a renewed interest in the development of PDE5 inhibitors for neurologic disease.
Keywords: Blotting, Western; Brain; Cyclic Nucleotide Phosphodiesterases, Type 5; DNA Primers; Enzyme-Linked Immunosorbent Assay; Humans; Immunohistochemistry; Nervous System Diseases; Neurons; Phosphodiesterase 5 Inhibitors; Polymerase Chain Reaction; RNA, Messenger

Performance of Hippocampus Volumetry with FSL-FIRST for Prediction of Alzheimer's Disease Dementia in at Risk Subjects with Amnestic Mild Cognitive Impairment. - Suppa, Per; Hampel, Harald; Kepp, Timo; Lange, Catharina; Spies, Lothar; Fiebach, Jochen B; Dubois, Bruno; Buchert, Ralph (J Alzheimers Dis, 2016)
MRI-based hippocampus volume, a core feasible biomarker of Alzheimer's disease (AD), is not yet widely used in clinical patient care, partly due to lack of validation of software tools for hippocampal volumetry that are compatible with routine workflow. Here, we evaluate fully-automated and computationally efficient hippocampal volumetry with FSL-FIRST for prediction of AD dementia (ADD) in subjects with amnestic mild cognitive impairment (aMCI) from phase 1 of the Alzheimer's Disease Neuroimaging Initiative. Receiver operating characteristic analysis of FSL-FIRST hippocampal volume (corrected for head size and age) revealed an area under the curve of 0.79, 0.70, and 0.70 for prediction of aMCI-to-ADD conversion within 12, 24, or 36 months, respectively. Thus, FSL-FIRST provides about the same power for prediction of progression to ADD in aMCI as other volumetry methods.
Keywords: Aged; Aging; Alzheimer Disease; Area Under Curve; Cognitive Dysfunction; Databases, Factual; Disease Progression; Hippocampus; Humans; Image Interpretation, Computer-Assisted; Magnetic Resonance Imaging; Neuropsychological Tests; Organ Size; Pattern Recognition, Automated; Prognosis; Reproducibility of Results; Risk; ROC Curve; Sensitivity and Specificity; Time Factors

Performance on Specific Cognitive Domains and Cause of Death: A Prospective Population-Based Study in Non-Demented Older Adults (NEDICES). - Benito-León, Julián; Contador, Israel; Mitchell, Alex J; Domingo-Santos, Ángela; Bermejo-Pareja, Félix (J Alzheimers Dis, 2016)
Evidence regarding the relationship between performance on specific cognitive domains and cause of death is scarce. We assessed whether specific cognitive domains predicted mortality and the presence of any association with specific causes of death in a population-dwelling sample of non-demented older adults. In this population-based, prospective study (NEDICES), 2,390 non-demented subjects ≥65 years completed a brief neuropsychological battery. Cox's proportional hazards models, adjusted by sociodemographic and comorbidity factors, global cognitive performance, educational level, and premorbid intelligence were used to assess the risk of death. Participants were followed for a median of 9.2 years (range 0.01-10.7), after which the death certificates of those who died were examined. 880 (36.8%) of 2,390 participants died over a median follow-up of 5.5 years (range 0.01-10.5). Using adjusted Cox regression models, we found that hazard ratios for mortality in participants within the lowest tertiles (worse performance) were 1.31 (speed of cognitive processing, p = 0.03); 1.22 (semantic fluency, p = 0.04), 1.32 (delayed free recall, p = 0.003), and 1.23 (delayed logical memory, p = 0.03). Poor performance on delayed recall and speed of cognitive processing tests were associated with dementia and cerebrovascular disease mortality, respectively. Further, poor performance on semantic fluency was associated with decreased cancer mortality. In this study of community dwelling non-demented older adults, worse neuropsychological performance was associated with increased risk of mortality. Performance on specific cognitive domains were related to different causes of death. Of particular note there appears to be an inverse association between poor semantic fluency and cancer mortality.
Keywords: Aged; Cause of Death; Cerebrovascular Disorders; Cognitive Aging; Dementia; Educational Status; Female; Follow-Up Studies; Humans; Intelligence; Longitudinal Studies; Male; Neuropsychological Tests; Prospective Studies; Risk; Spain

Platelet Membrane β-Secretase Activity in Mild Cognitive Impairment and Conversion to Dementia: a Longitudinal Study. - McGuinness, Bernadette; Fuchs, Marc; Barrett, Suzanne L; Passmore, A Peter; Johnston, Janet A (J Alzheimers Dis, 2016)
A blood-based biomarker to complement the clinical and neuropsychological assessments used to evaluate the risk of individuals with mild cognitive impairment (MCI) developing Alzheimer's disease (AD) would be invaluable. Previous pilot studies by our group identified elevated platelet membrane β-secretase activity in patients with AD and MCI, as compared to controls, and this activity was influenced by membrane cholesterol levels. The present study investigated baseline platelet membrane β-secretase activity and cholesterol levels in 97 MCI participants and 85 controls and explored whether these parameters differed in individuals with stable MCI, as compared to those who subsequently developed AD. To evaluate signal specificity, β-secretase activity assays were conducted in the presence and absence of beta-site amyloid-β protein precursor-cleaving enzyme (BACE) inhibitors. Baseline platelet membrane β-secretase activity did not differ significantly in MCI participants, as compared to controls, and platelet membrane cholesterol levels were significantly lower in the MCI group. The longitudinal study indicated that the activities inhibited by two different BACE inhibitors did not predict conversion to AD; however, the activity that was not affected by BACE inhibitors was significantly (40%) higher in individuals with stable MCI, as compared with those who subsequently developed AD. These findings indicated that further research into the source of this activity could contribute to a measure facilitating prediction of the risk of conversion from MCI to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid Precursor Protein Secretases; Biomarkers; Blood Platelets; Cholesterol; Cognitive Dysfunction; Cross-Sectional Studies; Disease Progression; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Middle Aged; Neuropsychological Tests; Sensitivity and Specificity

Post Hoc Analyses of ApoE Genotype-Defined Subgroups in Clinical Trials. - Kennedy, Richard E; Cutter, Gary R; Wang, Guoqiao; Schneider, Lon S (J Alzheimers Dis, 2016)
BACKGROUND: Many post hoc analyses of clinical trials in Alzheimer's disease (AD) and mild cognitive impairment (MCI) are in small Phase 2 trials. Subject heterogeneity may lead to statistically significant post hoc results that cannot be replicated in larger follow-up studies. OBJECTIVE: We investigated the extent of this problem using simulation studies mimicking current trial methods with post hoc analyses based on ApoE4 carrier status. METHODS: We used a meta-database of 24 studies, including 3,574 subjects with mild AD and 1,171 subjects with MCI/prodromal AD, to simulate clinical trial scenarios. Post hoc analyses examined if rates of progression on the Alzheimer's Disease Assessment Scale-cognitive (ADAS-cog) differed between ApoE4 carriers and non-carriers. RESULTS: Across studies, ApoE4 carriers were younger and had lower baseline scores, greater rates of progression, and greater variability on the ADAS-cog. Up to 18% of post hoc analyses for 18-month trials in AD showed greater rates of progression for ApoE4 non-carriers that were statistically significant but unlikely to be confirmed in follow-up studies. The frequency of erroneous conclusions dropped below 3% with trials of 100 subjects per arm. In MCI, rates of statistically significant differences with greater progression in ApoE4 non-carriers remained below 3% unless sample sizes were below 25 subjects per arm. CONCLUSIONS: Statistically significant differences for ApoE4 in post hoc analyses often reflect heterogeneity among small samples rather than true differential effect among ApoE4 subtypes. Such analyses must be viewed cautiously. ApoE genotype should be incorporated into the design stage to minimize erroneous conclusions.
Keywords: Alzheimer Disease; Apolipoprotein E4; Clinical Trials as Topic; Cognitive Dysfunction; Data Interpretation, Statistical; Humans; Research Design

Prediction of Progressive Mild Cognitive Impairment by Multi-Modal Neuroimaging Biomarkers. - Xu, Lele; Wu, Xia; Li, Rui; Chen, Kewei; Long, Zhiying; Zhang, Jiacai; Guo, Xiaojuan; Yao, Li (J Alzheimers Dis, 2016)
For patients with mild cognitive impairment (MCI), the likelihood of progression to probable Alzheimer's disease (AD) is important not only for individual patient care, but also for the identification of participants in clinical trial, so as to provide early interventions. Biomarkers based on various neuroimaging modalities could offer complementary information regarding different aspects of disease progression. The current study adopted a weighted multi-modality sparse representation-based classification method to combine data from the Alzheimer's Disease Neuroimaging Initiative (ADNI) database, from three imaging modalities: Volumetric magnetic resonance imaging (MRI), fluorodeoxyglucose (FDG) positron emission tomography (PET), and florbetapir PET. We included 117 normal controls (NC) and 110 MCI patients, 27 of whom progressed to AD within 36 months (pMCI), while the remaining 83 remained stable (sMCI) over the same time period. Modality-specific biomarkers were identified to distinguish MCI from NC and to predict pMCI among MCI. These included the hippocampus, amygdala, middle temporal and inferior temporal regions for MRI, the posterior cingulum, precentral, and postcentral regions for FDG-PET, and the hippocampus, amygdala, and putamen for florbetapir PET. Results indicated that FDG-PET may be a more effective modality in discriminating MCI from NC and in predicting pMCI than florbetapir PET and MRI. Combining modality-specific sensitive biomarkers from the three modalities boosted the discrimination accuracy of MCI from NC (76.7%) and the prediction accuracy of pMCI (82.5%) when compared with the best single-modality results (73.6% for MCI and 75.6% for pMCI with FDG-PET).
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Aniline Compounds; Biomarkers; Brain; Cognitive Dysfunction; Disease Progression; Ethylene Glycols; Female; Fluorodeoxyglucose F18; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Positron-Emission Tomography; Predictive Value of Tests; Psychiatric Status Rating Scales; Sensitivity and Specificity

Predictive Value of Cerebrospinal Fluid Visinin-Like Protein-1 Levels for Alzheimer's Disease Early Detection and Differential Diagnosis in Patients with Mild Cognitive Impairment. - Babić Leko, Mirjana; Borovečki, Fran; Dejanović, Nenad; Hof, Patrick R; Šimić, Goran (J Alzheimers Dis, 2016)
Visinin-like protein 1 (VILIP-1) recently emerged as a potential biomarker of Alzheimer's disease (AD). This neuronal calcium sensor protein previously used as a marker of acute ischemic stroke is elevated in the cerebrospinal fluid (CSF) of AD patients. The goal of this study was to assess CSF VILIP-1 potential in early AD diagnosis and in differentiating mild cognitive impairment (MCI) patients with and without risk of AD. Additionally, we tested VILIP-1 ability to differentiate AD from other primary causes of dementia, and predict the progression of AD-related cognitive decline. VILIP-1 levels were compared with five CSF AD biomarkers (t-tau, Aβ1-42, p-tau181, p-tau199, and p-tau231). VILIP-1 successfully differentiated two MCI patient groups characterized by absence or presence of pathological levels of these CSF biomarkers, except for t-tau. VILIP-1/Aβ(1-42) and VILIP-1/p-tau181 ratios also differentiated MCI patients with pathological CSF biomarker levels. However, there was no difference in VILIP-1 levels between AD and MCI patients. VILIP-1/Aβ(1-42) and VILIP-1/p-tau231 ratios reached high sensitivities (above 70%) and very high specificities (above 85%) in differentiating AD patients from HC. Additionally, VILIP-1 differentiated AD from patients with Lewy body disease with 77.1% sensitivity and 100% specificity. VILIP-1 potential as a prognostic biomarker of cognitive decline in AD was also proved since VILIP-1/t-tau, VILIP-1/p-tau181, and VILIP-1/p-tau231 ratios correlated with MMSE scores. These data indicate that VILIP-1 alone or in combination with other AD CSF biomarkers represent a valuable marker for the early diagnosis of AD, recognition of MCI patients at higher risk to develop dementia, and in differentiating AD from LBD.
Keywords: Adult; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Diagnosis, Differential; Disease Progression; Female; Humans; Male; Mental Status Schedule; Middle Aged; Neurocalcin; Peptide Fragments; Predictive Value of Tests; ROC Curve; Statistics as Topic; tau Proteins

Predictors of Response to Cholinesterase Inhibitors Treatment of Alzheimer's Disease: Date Mining from the TREDEM Registry. - Gallucci, Maurizio; Spagnolo, Pierpaolo; Aricò, Maria; Grossi, Enzo (J Alzheimers Dis, 2016)
BACKGROUND: The pharmacological treatment of Alzheimer's disease (AD) is based largely on cholinesterase inhibitors (ChEI). OBJECTIVE: To investigate whether or not some non-pharmacological and contextual factors measured prior to starting treatment such as past occupation, lifestyles, marital status, degree of autonomy and cognitive impairment, living alone or with others, and the degree of brain atrophy are associated with a better response to ChEI treatment. METHODS: Eighty-four AD and six AD with cerebrovascular disease (AD + CVD) outpatients of Treviso Dementia (TREDEM) Registry, with an average cholinesterase inhibitors treatment length of four years, were considered. The outpatients had undergone a complete evaluation and some non-pharmacological and contextual factors were collected. We defined responder a patient with a delta score T0 - T1 equal or inferior to 2.0 points per year of MMSE and a non-responder a patient with a delta score T0 - T1 superior to 2.0 points per year. In order to identify hidden relationships between variables related to response and non-response, we use a special kind of artificial neural network called Auto-CM, able to create a semantic connectivity map of the variables considered in the study. RESULTS: A higher cognitive profile, a previous intellectual occupation, healthier lifestyles, being married and not living alone, a higher degree of autonomy, and lower degree of brain atrophy at baseline resulted in affecting the response to long-term ChEI therapy. CONCLUSION: Non-pharmacological and contextual factors appear to influence the effectiveness of treatment with ChEI in the long term.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cerebrovascular Disorders; Cholinesterase Inhibitors; Female; Humans; Life Style; Male; Marital Status; Mental Status Schedule; Neural Networks (Computer); Neuropsychological Tests; Occupations; Outpatients; Prognosis; Registries; Treatment Outcome

Preliminary Study of Plasma Exosomal Tau as a Potential Biomarker for Chronic Traumatic Encephalopathy. - Stern, Robert A; Tripodis, Yorghos; Baugh, Christine M; Fritts, Nathan G; Martin, Brett M; Chaisson, Christine; Cantu, Robert C; Joyce, James A; Shah, Sahil; Ikezu, Tsuneya; Zhang, Jing; Gercel-Taylor, Cicek; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Chronic traumatic encephalopathy (CTE) is a tauopathy associated with prior exposure to repetitive head impacts, such as those incurred through American football and other collision sports. Diagnosis is made through neuropathological examination. Many of the clinical features of CTE are common in the general population, with and without a history of head impact exposure, making clinical diagnosis difficult. As is now common in the diagnosis of other neurodegenerative disorders, such as Alzheimer's disease, there is a need for methods to diagnose CTE during life through objective biomarkers. OBJECTIVE: The aim of this study was to examine tau-positive exosomes in plasma as a potential CTE biomarker. METHODS: Subjects were 78 former National Football League (NFL) players and 16 controls. Extracellular vesicles were isolated from plasma. Fluorescent nanoparticle tracking analysis was used to determine the number of vesicles staining positive for tau. RESULTS: The NFL group had higher exosomal tau than the control group (p <  0.0001). Exosomal tau discriminated between the groups, with 82% sensitivity, 100% specificity, 100% positive predictive value, and 53% negative predictive value. Within the NFL group, higher exosomal tau was associated with worse performance on tests of memory (p = 0.0126) and psychomotor speed (p = 0.0093). CONCLUSION: These preliminary findings suggest that exosomal tau in plasma may be an accurate, noninvasive CTE biomarker.
Keywords: Adult; Aged; Analysis of Variance; Case-Control Studies; Chronic Traumatic Encephalopathy; Extracellular Vesicles; Humans; Male; Middle Aged; Plasma; tau Proteins

The Presence of Select Tau Species in Human Peripheral Tissues and Their Relation to Alzheimer's Disease. - Dugger, Brittany N; Whiteside, Charisse M; Maarouf, Chera L; Walker, Douglas G; Beach, Thomas G; Sue, Lucia I; Garcia, Angelica; Dunckley, Travis; Meechoovet, Bessie; Reiman, Eric M; Roher, Alex E (J Alzheimers Dis, 2016)
Tau becomes excessively phosphorylated in Alzheimer's disease (AD) and is widely studied within the brain. Further examination of the extent and types of tau present in peripheral tissues and their relation to AD is warranted given recent publications on pathologic spreading. Cases were selected based on the presence of pathological tau spinal cord deposits (n = 18). Tissue samples from sigmoid colon, scalp, abdominal skin, liver, and submandibular gland were analyzed by western blot and enzyme-linked immunosorbent assays (ELISAs) for certain tau species; frontal cortex gray matter was used for comparison. ELISAs revealed brain to have the highest total tau levels, followed by submandibular gland, sigmoid colon, liver, scalp, and abdominal skin. Western blots with antibodies recognizing tau phosphorylated at threonine 231(pT231), serine 396 and 404 (PHF-1), and an unmodified total human tau between residues 159 and 163 (HT7) revealed multiple banding patterns, some of which predominated in peripheral tissues. As submandibular gland had the highest levels of peripheral tau, a second set of submandibular gland samples were analyzed (n = 36; 19 AD, 17 non-demented controls). ELISAs revealed significantly lower levels of pS396 (p = 0.009) and pT231 (p = 0.005) in AD cases but not total tau (p = 0.18). Furthermore, pT231 levels in submandibular gland inversely correlated with Braak neurofibrillary tangle stage (p = 0.04), after adjusting for age at death, gender, and postmortem interval. These results provide evidence that certain tau species are present in peripheral tissues. Of potential importance, submandibular gland pT231 is progressively less abundant with increasing Braak neurofibrillary tangle stage.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Blotting, Western; Colon; Enzyme-Linked Immunosorbent Assay; Female; Frontal Lobe; Gray Matter; Humans; Immunohistochemistry; Liver; Male; Neurofibrillary Tangles; Phosphorylation; Severity of Illness Index; Sex Characteristics; Skin; Submandibular Gland; tau Proteins

Prevalence and Risk Factor of Cognitive Impairment were Different between Urban and Rural Population: A Community-Based Study. - Tang, Hui-Dong; Zhou, Yi; Gao, Xiang; Liang, Liang; Hou, Miao-Miao; Qiao, Yuan; Ma, Jian-Fang; Chen, Sheng-Di (J Alzheimers Dis, 2016)
BACKGROUND: China is facing a continuously rising numbers of people with cognitive impairment (CI). OBJECTIVES: To investigate the prevalence and risk factors of CI among elderly people living in rural and urban communities. METHODS: We conducted a face-to-face survey of CI on 7,900 individuals aged 50 years or older meeting inclusion criteria in the Malu (rural community, n = 4,429) and Wuliqiao (urban community, n = 3,471) communities of Shanghai. The Mini-Mental State Examination (MMSE) was used to evaluate the cognitive function. Information on demographic features and potential risk factors for CI was collected during the interview. Multivariate logistic regression was performed to identify risk factors associated with CI. RESULTS: Based on the education modified MMSE score, we identified 329 CI cases in rural community and 227 in urban community. The prevalence of CI was 7.43% in rural population and 6.54% in urban population (p = 0.13). In the urban population, risk of having CI was associated with age (OR = 1.04; 95% CI: 1.01-1.08), lack of physical activities (OR = 2.25; 95% CI: 1.11-4.57), presence of diabetes mellitus (OR = 1.79; 95% CI: 1.04-3.07), and having three or more children (OR = 2.39; 95% CI: 1.27-4.50). In contrast, factors associated with rural populations included female gender (OR = 2.03; 95% CI: 1.08-3.82), age (OR = 1.06; 95% CI: 1.03-1.08), exposure to pesticides (OR = 4.68; 95% CI: 1.27-17.21), history of encephalitis or meningitis (OR = 6.02; 95% CI: 1.92-18.85) and head trauma (OR = 1.89; 95% CI: 1.10-3.24). CONCLUSIONS: Urban rural and populations showed different risk factors for CI, suggesting that different preventive strategies in these areas should be performed.
Keywords: Aged; Aged, 80 and over; China; Cognition Disorders; Female; Humans; Logistic Models; Male; Mental Status Schedule; Middle Aged; Multivariate Analysis; Prevalence; Risk Factors; Rural Population; Urban Population

Prevention Trials in Alzheimer's Disease: Current Status and Future Perspectives. - Wang, Jun; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is the most common form of dementia in the elderly. Over the past 20 years, both pharmacological and lifestyle interventions have been studied for AD prevention, but the overall results have been disappointing. The majority of disappointing results have raised questions and great challenges for the future of AD prevention trials. Ongoing advances in the knowledge of pathogenesis, in the identification of novel targets, in improved outcome measures, and in identification and validation of biomarkers may lead to effective strategies for AD prevention. In this paper, we review the selection of participants and interventions, trial design, outcome assessments, and promising biomarkers in prevention trials, and summarize the lessons learned from completed trials and perspectives from ongoing trials in AD prevention. Selection of optimal participants and interventions, coupled with more refined outcomes and more efficient trial design, may have the capacity to deliver a new era of preventive discovery in this challenging area.
Keywords: Alzheimer Disease; Biomarkers; Clinical Trials as Topic; Humans

Prion Protein-Hemin Interaction Upregulates Hemoglobin Synthesis: Implications for Cerebral Hemorrhage and Sporadic Creutzfeldt-Jakob Disease. - Tripathi, Ajai K; Singh, Neena (J Alzheimers Dis, 2016)
Hemin is known to induce endocytosis of prion-protein (PrP(C)) from the neuronal plasma membrane, potentially limiting propagation of the disease causing PrP-scrapie (PrP(Sc)) isoform. Hemin is therefore an attractive disease-modifying option for sporadic Creutzfeldt-Jakob disease (sCJD), a human prion disorder with no effective treatment. The hemin-PrP(C) interaction is also of interest in cerebral-hemorrhage (CH), a condition where potentially toxic hemin molecules come in contact with neuronal PrP(C). Interestingly, PrP(C) is upregulated in penumbric neurons surrounding CH and is known to confer neuroprotection in a dose-dependent manner. The underlying mechanism, however, is not clear. Here, we report that hemin binds PrP(C) on diverse cell lines, resulting in its aggregation or degradation in a cell-type specific manner. Surprisingly, the hemin-PrP(C) interaction upregulates Hb synthesis in hematopoietic cells, a response reversed by deleting the hemin-binding octa-peptide repeat region of PrP(C). A similar response is noted in brain organotypic cultures where exposure to hemin induces significantly more α-globin in wild-type (PrP(+/+)) relative to PrP-knock-out (PrP(-/-)) samples. Furthermore, red blood cells and brain tissue from PrP(-/-) mice show significantly less α-globin relative to PrP(+/+) controls, indicating a positive effect of PrP(C) on Hb synthesis under physiological conditions as well. Surprisingly, levels of α-globin are significantly higher in sCJD brain tissue relative to controls, suggesting compensatory upregulation of Hb synthesis by surviving neurons or misregulation in diseased brains. These observations reveal a unique function of PrP(C) that is likely to impact the therapeutic management of CH and sCJD.
Keywords: Animals; Brain; Cell Line, Tumor; Creutzfeldt-Jakob Syndrome; Endocytosis; Ferritins; Green Fluorescent Proteins; Hemin; Hemoglobins; Humans; In Vitro Techniques; Leukemia, Erythroblastic, Acute; Mice; Mice, Transgenic; Neuroblastoma; Neuroglia; Neurons; Organ Culture Techniques; Prion Proteins; Transfection; Up-Regulation

Prognostic Significance of Mild Cognitive Impairment Subtypes for Dementia and Mortality: Data from the NEDICES Cohort. - Bermejo-Pareja, Félix; Contador, Israel; Trincado, Rocío; Lora, David; Sánchez-Ferro, Álvaro; Mitchell, Alex J; Boycheva, Elina; Herrero, Alejandro; Hernández-Gallego, Jesús; Llamas, Sara; Villarejo Galende, Alberto; Benito-León, Julián (J Alzheimers Dis, 2016)
BACKGROUND: The predictive value of diverse subtypes of mild cognitive impairment (MCI) for dementia and death is highly variable. OBJECTIVE: To compare the predictive value of several MCI subtypes in progression to dementia and/or mortality in the NEDICES (Neurological Disorders in Central Spain) elderly cohort. METHODS: Retrospect algorithmic MCI subgroups were established in a non-dementia baseline NEDICES cohort using Spanish adaptations of the original Mini-Mental State Examination (MMSE-37) and Pfeffer's Functional Activities Questionnaire (Pfeffer-11). The presence of MCI was defined according two cognitive criteria: using two cut-offs points on the total MMSE-37 score. Five cognitive domains were used to establish the MCI subtypes. Functional capacity (Pfeffer-11) was preserved or minimally impaired in all MCI participants. The incident dementia diagnoses were established by specialists and the mortality data obtained from Spanish official registries. RESULTS: 3,411 participants without dementia were assessed in 1994-5. The baseline prevalence of MCI varied according to the MCI definition (4.3%-31.8%). The follow-up was a mean of 3.2 years (1997-8). The dementia incidence varied between 14.9 and 71.8 per 1,000/person-years. The dementia conversion rate was increased in almost all MCI subgroups (p >  0.01), and mortality rate was raised only in four MCI subtypes. The amnestic-multi-domain MCI (aMd-MCI) had the best dementia predictive accuracy (highest positive likelihood ratio and highest clinical utility when negative). CONCLUSIONS: Those with aMd-MCI were at greatest risk of progression to dementia, as in other surveys and might be explored with increased attention in MCI research and in dementia preventive trials.
Keywords: Aged; Aged, 80 and over; Algorithms; Cognitive Dysfunction; Cohort Studies; Dementia; Female; Humans; Male; Mental Status Schedule; Neuropsychological Tests; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Spain

Progression of Extrapyramidal Signs in Alzheimer's Disease: Clinical and Neuropathological Correlates. - Tosto, Giuseppe; Monsell, Sarah E; Hawes, Stephen E; Bruno, Giuseppe; Mayeux, Richard (J Alzheimers Dis, 2016)
BACKGROUND: Extrapyramidal signs (EPS) are frequent in Alzheimer's disease (AD) and core manifestation of related diseases, i.e., dementia with Lewy bodies and Parkinson's disease; furthermore, Lewy bodies and AD-type pathology occur in all three conditions. OBJECTIVE: To identify clusters of EPS progression over time and their clinical and neuropathological correlates. METHODS: 3,502 AD patients with longitudinal assessment from the National Alzheimer's Coordinating Center database were included; 394 provided neuropathological data. k-means algorithm was employed to identify clusters of EPS progression and those were compared in terms of cognitive profile, neuropsychiatric features and neuropathological findings. RESULTS: Three clusters of EPS progression were identified: no/low (n = 1,583), medium (n = 1,259), and high (n = 660) EPS burden. Compared to those with no/low and medium EPS, those with high EPS had greater cognitive and neuropsychiatric impairment, specifically hallucinations. Despite similar AD-pathology across the three clusters, the high EPS cluster had a significantly number of subjects diagnosed with dementia with Lewy bodies. CONCLUSIONS: Cluster analysis of EPS progression over time identified different subgroups of AD patients with distinct clinical and neuropathological features.
Keywords: Aged; Algorithms; Alzheimer Disease; Cluster Analysis; Databases, Factual; Disease Progression; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Severity of Illness Index

Protective Effect of Amyloid-β Peptides Against Herpes Simplex Virus-1 Infection in a Neuronal Cell Culture Model. - Bourgade, Karine; Le Page, Aurélie; Bocti, Christian; Witkowski, Jacek M; Dupuis, Gilles; Frost, Eric H; Fülöp, Tamás (J Alzheimers Dis, 2016)
Senile amyloid plaques are one of the main hallmarks of Alzheimer's disease (AD). They correspond to insoluble deposits of amyloid-β peptides (Aβ) and are responsible for the inflammatory response and neurodegeneration that lead to loss of memory. Recent data suggest that Aβ possess antimicrobial and anti-viral activity in vitro. Here, we have used cocultures of neuroglioma (H4) and glioblastoma (U118-MG) cells as a minimal in vitro model to investigate whether Aβ is produced by neuroglioma cells and whether this could result in protective anti-viral activity against HSV-1 infection. Results showed that H4 cells secreted Aβ42 in response to HSV-1 challenge and that U118-MG cells could rapidly internalize Aβ42. Production of pro-inflammatory cytokines TNFα and IL-1β by H4 and U118-MG cells occurred under basal conditions but infection of the cells with HSV-1 did not significantly upregulate production. Both cell lines produced low levels of IFNα. However, extraneous Aβ42 induced strong production of these cytokines. A combination of Aβ42 and HSV-1 induced production of pro-inflammatory cytokines TNFα and IL-1β, and IFNα in the cell lines. The reported anti-viral protection of Aβ42 was revealed in transfer experiments involving conditioned medium (CM) of HSV-1-infected H4 cells. CM conferred Aβ-dependent protection against HSV-1 replication in de novo cultures of H4 cells challenged with HSV-1. Type 1 interferons did not play a role in these assays. Our data established that H4 neuroglioma cells produced Aβ42 in response to HSV-1 infection thus inhibiting secondary replication. This mechanism may play a role in the etiology of AD.
Keywords: Amyloid beta-Peptides; Amyloid Precursor Protein Secretases; Cell Line, Tumor; Coculture Techniques; Culture Media, Conditioned; Herpes Simplex; Herpesvirus 1, Human; Humans; Interferon-alpha; Interleukin-1beta; Neuroglia; Neurons; Peptide Fragments; Tumor Necrosis Factor-alpha; Virus Replication

Protein Kinase Activity Decreases with Higher Braak Stages of Alzheimer's Disease Pathology. - Rosenberger, Andrea F N; Hilhorst, Riet; Coart, Elisabeth; García Barrado, Leandro; Naji, Faris; Rozemuller, Annemieke J M; van der Flier, Wiesje M; Scheltens, Philip; Hoozemans, Jeroen J M; van der Vies, Saskia M (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is characterized by a long pre-clinical phase (20-30 years), during which significant brain pathology manifests itself. Disease mechanisms associated with pathological hallmarks remain elusive. Most processes associated with AD pathogenesis, such as inflammation, synaptic dysfunction, and hyper-phosphorylation of tau are dependent on protein kinase activity. The objective of this study was to determine the involvement of protein kinases in AD pathogenesis. Protein kinase activity was determined in postmortem hippocampal brain tissue of 60 patients at various stages of AD and 40 non-demented controls (Braak stages 0-VI) using a peptide-based microarray platform. We observed an overall decrease of protein kinase activity that correlated with disease progression. The phosphorylation of 96.7% of the serine/threonine peptides and 37.5% of the tyrosine peptides on the microarray decreased significantly with increased Braak stage (p-value <0.01). Decreased activity was evident at pre-clinical stages of AD pathology (Braak I-II). Increased phosphorylation was not observed for any peptide. STRING analysis in combination with pathway analysis and identification of kinases responsible for peptide phosphorylation showed the interactions between well-known proteins in AD pathology, including the Ephrin-receptor A1 (EphA1), a risk gene for AD, and sarcoma tyrosine kinase (Src), which is involved in memory formation. Additionally, kinases that have not previously been associated with AD were identified, e.g., protein tyrosine kinase 6 (PTK6/BRK), feline sarcoma oncogene kinase (FES), and fyn-associated tyrosine kinase (FRK). The identified protein kinases are new biomarkers and potential drug targets for early (pre-clinical) intervention.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cohort Studies; Female; Hippocampus; Humans; Male; Middle Aged; Phosphorylation; Protein Kinases; Protein-Serine-Threonine Kinases; Severity of Illness Index

Psychotropic Drug Prescription in Patients with Dementia: Nursing Home Residents Versus Patients Living at Home. - Jacquin-Piques, Agnès; Sacco, Guillaume; Tavassoli, Neda; Rouaud, Olivier; Bejot, Yannick; Giroud, Maurice; Robert, Philippe; Vellas, Bruno; Bonin-Guillaume, Sylvie (J Alzheimers Dis, 2016)
BACKGROUND: Psychotropic drugs are frequently prescribed in nursing homes (NH). Nonetheless, we hoped that institutionalization decreases the number of psychotropic drug classes prescribed, because NH residents may have more psychosocial interventions than patients living at home. OBJECTIVE: The aim was to compare the type and number of psychotropic drugs prescribed in elderly NH residents with dementia with those in community-living patients. METHODS: This cross-sectional study included elderly patients (at least 75 years old) with dementia recorded in the National Alzheimer's data Bank ("Banque Nationale Alzheimer") during the year 2012 and who were taking at least one psychotropic drug. Psychotropic drugs were classified as follows: antidepressant, anxiolytic, hypnotic, and antipsychotic drugs. Patients were classified into three categories of dementia severity according to the MMSE score. RESULTS: Among the 50,932 patients with dementia recorded in the BNA, 40.1% had at least one psychotropic drug prescribed. Most of the patients who were treated by at least one psychotropic drug class had antidepressant therapy (69.0%), whatever their residence type, and 16.1% were treated with antipsychotics. Among the study population, 51.9% of the NH residents and 67.4% of the patients living at home had only one psychotropic drug class prescribed. Living in a NH was significantly associated with the more frequent prescription of anxiolytic, hypnotic, and antipsychotic drugs, and with a greater number of psychotropic drug classes prescribed, whatever the severity of the dementia. CONCLUSION: We underlined the more frequent prescription of psychotropic drugs in NH residents regardless of MMSE scores.
Keywords: Aged; Aged, 80 and over; Chi-Square Distribution; Cross-Sectional Studies; Databases, Factual; Dementia; Drug Prescriptions; Female; Humans; Male; Nursing Homes; Psychotropic Drugs; Residence Characteristics

Puerarin Ameliorates D-Galactose Induced Enhanced Hippocampal Neurogenesis and Tau Hyperphosphorylation in Rat Brain. - Hong, Xiao-Ping; Chen, Tao; Yin, Ni-Na; Han, Yong-Ming; Yuan, Fang; Duan, Yan-Jun; Shen, Feng; Zhang, Yan-Hong; Chen, Ze-Bin (J Alzheimers Dis, 2016)
Enhanced neurogenesis has been reported in the hippocampus of patients with Alzheimer's disease (AD), the most common neurodegenerative disorder characterized with amyloid-β (Aβ) aggregation, tau hyperphosphorylation, and progressive neuronal loss. Previously we reported that tau phosphorylation played an essential role in adult hippocampal neurogenesis, and activation of glycogen synthase kinase (GSK-3), a crucial tau kinase, could induce increased hippocampal neurogenesis. In the present study, we found that treatment of D-galactose rats with Puerarin could significantly improve behavioral performance and ameliorate the enhanced neurogenesis and microtubule-associated protein tau hyperphosphorylation in the hippocampus of D-galactose rat brains. FGF-2/GSK-3 signaling pathway might be involved in the effects of Puerarin on hippocampal neurogenesis and tau hyperphosphorylation. Our finding provides primary in vivo evidence that Puerarin can attenuate AD-like enhanced hippocampal neurogenesis and tau hyperphosphorylation. Our finding also suggests Puerarin can be served as a treatment for age-related neurodegenerative disorders, such as AD.
Keywords: Animals; Cognition Disorders; Disease Models, Animal; Fibroblast Growth Factor 2; Galactose; Glycogen Synthase Kinase 3; Hippocampus; Isoflavones; Male; Maze Learning; Neurogenesis; Neurons; Neuroprotective Agents; Phosphorylation; Random Allocation; Rats, Sprague-Dawley; Signal Transduction; Spatial Memory; tau Proteins

Quantitative Neuroimaging Software for Clinical Assessment of Hippocampal Volumes on MR Imaging. - Ahdidan, Jamila; Raji, Cyrus A; DeYoe, Edgar A; Mathis, Jedidiah; Noe, Karsten Ø; Rimestad, Jens; Kjeldsen, Thomas K; Mosegaard, Jesper; Becker, James T; Lopez, Oscar (J Alzheimers Dis, 2016)
BACKGROUND: Multiple neurological disorders including Alzheimer's disease (AD), mesial temporal sclerosis, and mild traumatic brain injury manifest with volume loss on brain MRI. Subtle volume loss is particularly seen early in AD. While prior research has demonstrated the value of this additional information from quantitative neuroimaging, very few applications have been approved for clinical use. Here we describe a US FDA cleared software program, NeuroreaderTM, for assessment of clinical hippocampal volume on brain MRI. OBJECTIVE: To present the validation of hippocampal volumetrics on a clinical software program. METHOD: Subjects were drawn (n = 99) from the Alzheimer Disease Neuroimaging Initiative study. Volumetric brain MR imaging was acquired in both 1.5 T (n = 59) and 3.0 T (n = 40) scanners in participants with manual hippocampal segmentation. Fully automated hippocampal segmentation and measurement was done using a multiple atlas approach. The Dice Similarity Coefficient (DSC) measured the level of spatial overlap between NeuroreaderTM and gold standard manual segmentation from 0 to 1 with 0 denoting no overlap and 1 representing complete agreement. DSC comparisons between 1.5 T and 3.0 T scanners were done using standard independent samples T-tests. RESULTS: In the bilateral hippocampus, mean DSC was 0.87 with a range of 0.78-0.91 (right hippocampus) and 0.76-0.91 (left hippocampus). Automated segmentation agreement with manual segmentation was essentially equivalent at 1.5 T (DSC = 0.879) versus 3.0 T (DSC = 0.872). CONCLUSION: This work provides a description and validation of a software program that can be applied in measuring hippocampal volume, a biomarker that is frequently abnormal in AD and other neurological disorders.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Female; Hippocampus; Humans; Image Interpretation, Computer-Assisted; Magnetic Resonance Imaging; Male; Middle Aged; Software

Quantitative phosphoproteomic analyses of the inferior parietal lobule from three different pathological stages of Alzheimer's disease. - Triplett, Judy C; Swomley, Aaron M; Cai, Jian; Klein, Jon B; Butterfield, D Allan (J Alzheimers Dis, 2016)
Alzheimer's disease (AD), the most common age-related neurodegenerative disorder, is clinically characterized by progressive neuronal loss resulting in loss of memory and dementia. AD is histopathologically characterized by the extensive distribution of senile plaques and neurofibrillary tangles, and synapse loss. Amnestic mild cognitive impairment (MCI) is generally accepted to be an early stage of AD. MCI subjects have pathology and symptoms that fall on the scale intermediately between 'normal' cognition with little or no pathology and AD. A rare number of individuals, who exhibit normal cognition on psychometric tests but whose brains show widespread postmortem AD pathology, are classified as 'asymptomatic' or 'preclinical' AD (PCAD). In this study, we evaluated changes in protein phosphorylation states in the inferior parietal lobule of subjects with AD, MCI, PCAD, and control brain using a 2-D PAGE proteomics approach in conjunction with Pro-Q Diamond phosphoprotein staining. Statistically significant changes in phosphorylation levels were found in 19 proteins involved in energy metabolism, neuronal plasticity, signal transduction, and oxidative stress response. Changes in the disease state phosphoproteome may provide insights into underlying mechanisms for the preservation of memory with expansive AD pathology in PCAD and the progressive memory loss in amnestic MCI that escalates to the dementia and the characteristic pathology of AD brain.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Disease Progression; Female; Humans; Male; Memory; Neurofibrillary Tangles; Oxidative Stress; Parietal Lobe; Phosphorylation; Plaque, Amyloid; Proteome

Reduction of Amyloid-β Plasma Levels by Hemodialysis: An Anti-Amyloid Treatment Strategy? - Tholen, Susanne; Schmaderer, Christoph; Chmielewski, Stefan; Förstl, Hans; Heemann, Uwe; Baumann, Marcus; Steubl, Dominik; Grimmer, Timo (J Alzheimers Dis, 2016)
BACKGROUND: Cognitive impairment in hemodialysis patients is common, but the underlying pathogenesis remains unclear. Alzheimer's disease is the most common cause of dementia in the general elderly population. Histopathological hallmarks are, among others, senile plaques, which consist of amyloid-β (Aβ). OBJECTIVE: To measure plasma levels of Aβ42 and Aβ40 during hemodialysis and to examine potential associations with cognitive performance in cognitively impaired hemodialysis patients. METHODS: Plasma samples of 26 hemodialysis patients were collected shortly before, after 50% of dialysis time, and at the end of a dialysis session. Aβ42 and Aβ40 levels were measured by a high-sensitivity ELISA for human amyloid-β. Cognition was tested under standardized conditions using the Montreal Cognitive Assessment (MoCA) as proposed previously. RESULTS: Clearance rates of both peptides during one dialysis session were 22% and 35% for Aβ42 and Aβ40, respectively. Aβ42 but not Aβ40 baseline levels were significantly associated with MoCA test results (r = 0.654, p = 0.001). CONCLUSION: In cognitively impaired hemodialysis patients plasma Aβ42 levels were associated with cognitive performance and both Aβ42 and Aβ40 plasma levels could be effectively reduced by dialysis. By inducing peripheral Aβ sink, hemodialysis may be considered as an anti-amyloid treatment strategy.
Keywords: Adult; Aged; Aged, 80 and over; Amyloid beta-Peptides; Cognition Disorders; Enzyme-Linked Immunosorbent Assay; Female; Humans; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptide Fragments; Renal Dialysis

Region-Specific Vulnerability to Oxidative Stress, Neuroinflammation, and Tau Hyperphosphorylation in Experimental Diabetes Mellitus Mice. - Elahi, Montasir; Hasan, Zafrul; Motoi, Yumiko; Matsumoto, Shin-Ei; Ishiguro, Koichi; Hattori, Nobutaka (J Alzheimers Dis, 2016)
Recent epidemiological evidence suggests that diabetes mellitus (DM) is a risk factor for Alzheimer's disease (AD). One of the pathological hallmarks of AD is hyperphosphorylated tau protein, which forms neurofibrillary tangles. Oxidative stress and the activation of inflammatory pathways are features that are associated with both DM and AD. However, the brain region specificity of AD-related neurodegeneration, which mainly occurs in the hippocampus while the cerebellum is relatively unaffected, has not yet been clarified. Therefore, we used experimental DM mice (caused by an intraperitoneal injection of streptozotocin [STZ]) to determine whether these neurodegeneration-associated mechanisms were associated with region-specific selective vulnerability or tau phosphorylation. The hippocampus, midbrain, and cerebellum of aged (14 to 18 months old) non-transgenic (NTg) and transgenic mice overexpressing wild-type human tau (Tg601 mice) were evaluated after a treatment with STZ. The STZ injection increased reactive oxygen species, lipid peroxidation markers such as 4-hydroxynonenal and malondialdehyde in the hippocampus, but not in the midbrain or cerebellum. The STZ treatment also increased the number of Iba-1-positive and CD68-positive microglial cells, astrocytes, and IL-1β, IL-6, IL-10, and IL-18 levels in the hippocampus, but not in the midbrain or cerebellum. Tau hyperphosphorylation was also enhanced in the hippocampus, but not in the midbrain or cerebellum. When the effects of STZ were compared between Tg601 and NTg mice, microglial proliferation and elevations in IL-6 and phosphorylated tau were higher in Tg601 mice. These results suggest that neuroinflammation and oxidative stress in STZ-treated mice are associated with tau hyperphosphorylation, which may contribute to selective neurodegeneration in human AD.
Keywords: Adaptor Proteins, Signal Transducing; Animals; Antibiotics, Antineoplastic; Brain; Calcium-Binding Proteins; Calcium-Calmodulin-Dependent Protein Kinase Type 2; Cell Proliferation; Diabetes Mellitus, Experimental; Disease Models, Animal; Encephalitis; Female; Humans; Lipid Peroxidation; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Microfilament Proteins; Neuroglia; Oxidative Stress; Reactive Oxygen Species; Streptozocin; tau Proteins

Reproductive history and risk of cognitive impairment in elderly women: a cross-sectional study in eastern China. - Li, Fu-Dong; He, Fan; Chen, Ting-Rui; Xiao, Yuan-Yuan; Lin, Shang-Tong; Shen, Wei; Wang, Xin-Yi; Zhai, Yu-Jia; Shang, Xiao-Peng; Lin, Jun-Fen (J Alzheimers Dis, 2016)
BACKGROUND: Epidemiological studies suggest that proxies of higher lifetime estrogen exposure are associated with better cognitive function in postmenopausal women, but this has not been found consistently. OBJECTIVE: To determine whether reproductive history, an important modifier of estrogen exposure across the lifetime, is associated with risk of cognitive impairment in postmenopausal women. METHODS: We analyzed the baseline data from Zhejiang Major Public Health Surveillance Program (ZPHS) including 4,796 postmenopausal women. Cognitive impairment was assessed through the application of Mini-Mental State Examination questionnaire. Logistic regression models, controlled for an extensive range of potential confounders, were generated to examine the associations between women's reproductive history and risk of cognitive impairment in their later life. RESULTS: The length of reproductive period was inversely associated with risk of cognitive impairment (p = 0.001). Odds ratio (OR) of cognitive impairment were 1.316 (95% CI 1.095∼1.582) for women with 5 or more times of full-term pregnancies, compared with those with 1∼4 times of full-term pregnancies. Women without incomplete pregnancy had a significant higher risk of cognitive impairment (OR = 1.194, 95% CI 1.000∼1.429), compared with the reference (1∼2 times of incomplete pregnancies). Oral contraceptive use (OR = 0.489, 95% CI 0.263∼0.910) and intrauterine device (IUD) use (OR = 0.684, 95% CI 0.575∼0.815) were associated with significantly reduced risk of cognitive impairment. CONCLUSION: Our results indicated that shorter reproductive period, higher number of full-term pregnancies and no incomplete pregnancy history were associated with an increased risk of cognitive impairment. In contrast, oral contraceptive and IUD use corresponded to reduced risk of cognitive impairment.
Keywords: Aged; Aged, 80 and over; China; Cognition; Cognition Disorders; Contraceptives, Oral; Cross-Sectional Studies; Estrogens; Female; Humans; Intrauterine Devices; Logistic Models; Middle Aged; Neuropsychological Tests; Odds Ratio; Postmenopause; Psychiatric Status Rating Scales; Reproductive History

Retinal oximetry imaging in Alzheimer's disease. - Einarsdottir, Anna Bryndis; Hardarson, Sveinn Hakon; Kristjansdottir, Jona Valgerdur; Bragason, David Thor; Snaedal, Jon; Stefánsson, Einar (J Alzheimers Dis, 2016)
BACKGROUND: Structural and physiological abnormalities have been reported in the retina in Alzheimer's disease (AD). Retinal oximetry detects changes in retinal oxygen metabolism in many eye diseases, where structural changes are seen. OBJECTIVE: To compare oxygen saturation in retinal blood vessels in patients with AD and a healthy cohort. METHODS: Oxygen saturation of hemoglobin was measured in retinal blood vessels, using imaging with spectrophotometric noninvasive retinal oximeter. 18 individuals with mild to moderate dementia of the Alzheimer-type (stage 3-5 according to the Global Deterioration Scale) and 18 healthy subjects underwent retinal oximetry in a case control study. RESULTS: Retinal oxygen saturation in arterioles and venules in patients with moderate AD was significantly elevated compared to healthy individuals. Retinal arterioles have 94.2 ± 5.4% oxygen saturation in moderate AD compared with 90.5 ± 3.1% in healthy subjects (mean ± SD, n = 10, p = 0.028). Retinal venules were 51.9 ± 6.0% saturated in moderate AD compared with 49.7 ± 7.0% in healthy subjects (mean ± SD, n = 10, p = 0.02). CONCLUSION: This is the first study of retinal oxygen metabolism in any central nervous system disease. It discovers abnormalities in retinal oxygen metabolism in AD. The findings are similar to those seen in age-related macular degeneration and diabetic retinopathy. Noninvasive retinal oximetry may offer new insights into pathophysiology of AD. Further studies are needed to confirm and expand these findings.
Keywords: Aged; Alzheimer Disease; Case-Control Studies; Female; Hemoglobins; Humans; Male; Middle Aged; Oximetry; Oxygen; Oxygen Consumption; Regional Blood Flow; Retina; Retinal Vessels

Reversal of LTP-Like Cortical Plasticity in Alzheimer's Disease Patients with Tau-Related Faster Clinical Progression. - Koch, Giacomo; Di Lorenzo, Francesco; Del Olmo, Miguel Fernandez; Bonní, Sonia; Ponzo, Viviana; Caltagirone, Carlo; Bozzali, Marco; Martorana, Alessandro (J Alzheimers Dis, 2016)
Cerebrospinal fluid (CSF) concentrations of amyloid-β (Aβ), total tau (t-tau), and phosphorylated tau proteins are associated with different clinical progression in Alzheimer's disease (AD). We enrolled forty newly diagnosed AD patients, who underwent lumbar puncture, and carried out a K-means cluster analysis based on CSF biomarkers levels, resulting in two AD patient groups: Cluster 1 showed relatively high levels of Aβ and low levels of tau; Cluster 2 showed relatively low levels of Aβ and high levels of tau. Cortical plasticity was tested using the intermittent and continuous theta burst stimulation (iTBS and cTBS) protocols evoking respectively long-term potentiation (LTP) and depression (LTD). Cholinergic transmission was tested by the short-latency afferent inhibition protocol. Neurophysiological evaluation showed that the two AD groups differed in terms of cortical plasticity: after iTBS, Cluster 2 patients showed a remarkable reversal of LTP toward LTD that was not observed in Cluster 1. LTD and central cholinergic transmission did not differ between groups. Patients were assessed longitudinally with Mini-Mental State Examination at 6, 12, and 18 month follow-ups. Cluster 2 AD had a faster cognitive decline already evident at the 12 month follow-up. High tau CSF levels were associated with LTD-like cortical plasticity and faster clinical progression. These results suggest that more aggressive tau pathology is associated with prominent LTD-like mechanisms of cortical plasticity and faster cognitive decline.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Cognition; Disease Progression; Evoked Potentials, Motor; Female; Humans; Male; Motor Cortex; Neuronal Plasticity; Neuropsychological Tests; Phosphorylation; tau Proteins; Transcranial Magnetic Stimulation

Reversible Mild Cognitive Impairment: The Role of Comorbidities at Baseline Evaluation. - Grande, Giulia; Cucumo, Valentina; Cova, Ilaria; Ghiretti, Roberta; Maggiore, Laura; Lacorte, Eleonora; Galimberti, Daniela; Scarpini, Elio; Clerici, Francesca; Pomati, Simone; Vanacore, Nicola; Mariani, Claudio (J Alzheimers Dis, 2016)
The prognostic value of mild cognitive impairment (MCI) is being questioned, with some MCI subjects reverting to normal cognition (NC). The reversion rate varies mostly depending on the study design, the setting, and both MCI and NC definitions. Previous studies have focused on the profile of subjects who revert to NC, but the role of comorbidities has not been entirely investigated. We aimed to evaluate the proportion of MCI subjects who revert to NC in a memory clinic context, focusing on the role of comorbidities. Between 2004 and 2013, 374 MCI subjects were recruited. During a mean time of 32 ± 25.5 months, 21 subjects (5.6%) reverted to NC. Subjects who reverted to NC were younger (p = 0.0001), more educated (p = 0.0001), had a better global cognition (p = 0.0001), as assessed by the Mini-Mental State Examination (MMSE) and suffered from more comorbidities (p = 0.002), as assessed by Cumulative Illness Rating Scale (CIRS) than those who developed dementia. The Cox Regression Model, constructed to adjust for the confounders, showed that the higher were the MMSE (HR = 1.83, CI 95%: 1.07-3.11) and the CIRS score (HR = 1.3, CI 95% 0.88-1.92) at baseline, the higher was the probability of returning to NC than developing dementia, though the last association was not significant. Subjects who reverted to NC were more frequently affected by respiratory (p = 0.002), urologic (p = 0.012), and psychiatric (p = 0.012) diseases. The cognitive performance of subjects with medical comorbidities could benefit from preventive strategies aimed at treating the underlying diseases.
Keywords: Analysis of Variance; Cognitive Dysfunction; Cohort Studies; Comorbidity; Female; Humans; Male; Memory; Mental Status Schedule; Neuropsychological Tests; Reference Values; Verbal Learning

Revisiting the Heidenhain Variant of Creutzfeldt-Jakob Disease: Evidence for Prion Type Variability Influencing Clinical Course and Laboratory Findings. - Baiardi, Simone; Capellari, Sabina; Ladogana, Anna; Strumia, Silvia; Santangelo, Mario; Pocchiari, Maurizio; Parchi, Piero (J Alzheimers Dis, 2016)
The Heidenhain variant defines a peculiar clinical presentation of sporadic Creutzfeldt-Jakob disease (sCJD) characterized by isolated visual disturbances at disease onset and reflecting the early targeting of prions to the occipital cortex. Molecular and histopathological typing, thus far performed in 23 cases, has linked the Heidenhain variant to the MM1 sCJD type. To contribute a comprehensive characterization of cases with the Heidenhain variant, we reviewed a series of 370 definite sCJD cases. Eighteen patients (4.9%) fulfilled the selection criteria. Fourteen of them belonging to sCJD types MM1 or MM1+2C had a short duration of isolated visual symptoms and overall clinical disease, a high prevalence of periodic sharp-wave complexes in EEG, and a marked increase of cerebrospinal fluid proteins t-tau and 14-3-3 levels. In contrast, three cases of the MM 2C or MM 2+1C types showed a longer duration of isolated visual symptoms and overall clinical disease, non-specific EEG findings, and cerebrospinal fluid concentration below threshold for the diagnosis of "probable" CJD of both 14-3-3 and t-tau. However, a brain DWI-MRI disclosed an occipital cortical hyperintensity in the majority of examined cases of both groups. While confirming the strong linkage with the methionine genotype at the polymorphic codon 129 of the prion protein gene, our results definitely establish that the Heidenhain variant can also be associated with the MM 2C sCJD type in addition to the more common MM1 type. Likewise, our results highlight the significant differences in clinical evolution and laboratory findings between cases according to the dominant PrPSc type (type 1 versus type 2).
Keywords: Aged; Aged, 80 and over; Brain; Creutzfeldt-Jakob Syndrome; Female; Genotype; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Phenotype; Prions

Risk of dementia in patients with celiac disease: a population-based cohort study. - Lebwohl, Benjamin; Luchsinger, Jose A; Freedberg, Daniel E; Green, Peter H R; Ludvigsson, Jonas F (J Alzheimers Dis, 2016)
BACKGROUND: Patients with celiac disease (CD) frequently report cognitive symptoms when they are exposed to gluten, and cognitive deficits have been quantified in patients with newly diagnosed CD. OBJECTIVE: To determine whether patients with CD have an increased risk of dementia. METHODS: Using a population-based database of older adults (age ≥50 years) with histologically proven CD (duodenal/jejunal villous atrophy) from all 28 pathology departments in Sweden, we compared the incidence of a subsequent dementia diagnosis to those of age- and gender-matched controls. RESULTS: Among patients with CD (n = 8,846) and controls (n = 43,474), the median age was 63 years and 56% were female. During a median follow-up time of 8.4 years, dementia was diagnosed in 4.3% of CD patients and 4.4% of controls (HR 1.07; 95% CI 0.95-1.20). Although there was an increased risk of dementia in the first year following a diagnosis of CD (HR 1.73; 95% CI 1.15-2.61), this risk was not present in the whole observation period. Among those subjects with a dementia subtype specified, the increased risk was restricted to vascular dementia (HR 1.28; 95% CI 1.00-1.64) and was not present for Alzheimer's dementia (HR 1.12; 95% CI 0.91-1.37). CONCLUSIONS: Patients with CD are not at increased risk for dementia overall, though subgroup analysis suggests that they may be at increased risk for vascular dementia.
Keywords: Aged; Celiac Disease; Cohort Studies; Databases, Factual; Dementia; Female; Humans; Incidence; Logistic Models; Male; Middle Aged; Proportional Hazards Models; Risk Factors; Sweden

The Role of Alzheimer's and Cerebrovascular Pathology in Mediating the Effects of Age, Race, and Apolipoprotein E Genotype on Dementia Severity in Pathologically-Confirmed Alzheimer's Disease. - Gavett, Brandon E; John, Samantha E; Gurnani, Ashita S; Bussell, Cara A; Saurman, Jessica L (J Alzheimers Dis, 2016)
BACKGROUND: Dementia severity can be modeled as the construct δ, representing the "cognitive correlates of functional status." OBJECTIVE: We recently validated a model for estimating δ in the National Alzheimer's Coordinating Center's Uniform Data Set; however, the association of δ with neuropathology remains untested. METHODS: We used data from 727 decedents evaluated at Alzheimer's Disease (AD) Centers nationwide. Participants spoke English, had no genetic abnormalities, and were pathologically diagnosed with AD as a primary or contributing etiology. Clinical data from participants' last visit prior to death were used to estimate dementia severity (δ). RESULTS: A structural equation model using age, education, race, and apolipoprotein E (APOE) genotype (number of ɛ2 and ɛ4 alleles) as predictors and latent AD pathology and cerebrovascular disease (CVD) pathology as mediators fit the data well (RMSEA = 0.031; CFI = 0.957). AD pathology mediated the effects of age and APOE genotype on dementia severity. An older age at death and more ɛ2 alleles were associated with less AD pathology and, in turn, with less severe dementia. In contrast, more ɛ4 alleles were associated with more pathology and more severe dementia. Although age and race contributed to differences in CVD pathology, CVD pathology was not related to dementia severity in this sample of decedents with pathologically-confirmed AD. CONCLUSIONS: Using δ as an estimate of dementia severity fits well within a structural model in which AD pathology directly affects dementia severity and mediates the relationship between age and APOE genotype on dementia severity.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Apolipoproteins E; Cerebrovascular Disorders; Continental Population Groups; Dementia; Educational Status; Female; Genotype; Humans; Male; Mental Status Schedule; Middle Aged; Models, Theoretical

The Role of Ethnicity in Alzheimer's Disease: Findings From The C-PATH Online Data Repository. - Chen, Huei-Yang; Panegyres, Peter K (J Alzheimers Dis, 2016)
BACKGROUND: Ethnic minorities seem to be at an increased risk of Alzheimer's disease (AD). However, little is known about ethnic differences and the risks of early onset AD (EOAD). OBJECTIVE: Cognitive function changes over time and odds of EOAD by ethnicity were analyzed by the mixed model and the logistic regression. METHODS: Information on demographics, self-reported co-morbidities, cognitive functions (MMSE and ADAS-COG), and ApoE genotypes were collected for 6,500 subjects with AD obtained from the placebo arm of clinical trials; this data was examined by ethnicities: Caucasian, Asian, African American, Hispanic, and other minorities--including Native Alaskans, Americans, and Hawaiians. RESULTS: Of the total subjects, Caucasians accounted for 89.0% , followed by 4.7% Asians, 2.7% African Americans, 2.4% Hispanics, and 1.2% Native Americans, Alaskans, and Hawaiians. Age, gender, EOAD status, co-morbidities, family history of AD, and ApoE genotypes were significantly different by ethnicity. ApoE ɛ2 allele is possibly overrepresented in the Native Americans, Africans, Hawaiians, and African Americans. A significant interaction with time, ethnicity, and cognitive performance was found, indicating more cognitive deterioration in other minorities than Caucasians for mini-mental state (p <  0.01). After adjusting for co-morbidities and gender, the odds of EOAD among African Americans (OR: 1.6, 95% CI: 1.1-2.4) and Native Alaskans, Americans, and Hispanics (OR: 2.1, 95% CI: 1.2-3.5) were significantly higher, compared with Caucasians. CONCLUSIONS: Ethnicity may impact AD through age of onset, co-morbidities, family history, ApoE gene status, and cognitive change over time. The greater odds of EOAD among African Americans, Alaskans, and Hawaiians suggest that some ethnicities may be at risk of AD at a younger age.
Keywords: African Americans; Age Factors; Aged; Alaska Natives; Alzheimer Disease; Apolipoproteins E; Asian Continental Ancestry Group; Clinical Trials as Topic; Comorbidity; Databases, Factual; European Continental Ancestry Group; Female; Hispanic Americans; Humans; Indians, North American; Internet; Logistic Models; Male; Oceanic Ancestry Group; Risk; Sex Factors

Safety and Efficacy of Medical Cannabis Oil for Behavioral and Psychological Symptoms of Dementia: An-Open Label, Add-On, Pilot Study. - Shelef, Assaf; Barak, Yoram; Berger, Uri; Paleacu, Diana; Tadger, Shelly; Plopsky, Igor; Baruch, Yehuda (J Alzheimers Dis, 2016)
BACKGROUND: Tetrahydrocannabinol (THC) is a potential treatment for Alzheimer's disease (AD). OBJECTIVE: To measure efficacy and safety of medical cannabis oil (MCO) containing THC as an add-on to pharmacotherapy, in relieving behavioral and psychological symptoms of dementia (BPSD). METHODS: Eleven AD patients were recruited to an open label, 4 weeks, prospective trial. RESULTS: Ten patients completed the trial. Significant reduction in CGI severity score (6.5 to 5.7; p <  0.01) and NPI score were recorded (44.4 to 12.8; p <  0.01). NPI domains of significant decrease were: Delusions, agitation/aggression, irritability, apathy, sleep and caregiver distress. CONCLUSION: Adding MCO to AD patients' pharmacotherapy is safe and a promising treatment option.
Keywords: Aged; Aged, 80 and over; Antipsychotic Agents; Behavioral Symptoms; Cognition Disorders; Dementia; Female; Humans; Male; Medical Marijuana; Neuropsychological Tests; Outcome Assessment (Health Care); Physical Examination; Pilot Projects; Prospective Studies; Psychiatric Status Rating Scales

Salidroside, a Bioactive Compound of Rhodiola Rosea, Ameliorates Memory and Emotional Behavior in Adult Mice. - Palmeri, Agostino; Mammana, Leonardo; Tropea, Maria Rosaria; Gulisano, Walter; Puzzo, Daniela (J Alzheimers Dis, 2016)
Rhodiola Rosea (R. Rosea) is a plant used in traditional popular medicine to enhance cognition and physical performance. R. Rosea medicinal properties have been related to its capability to act as an adaptogen, i.e., a substance able to increase the organism's resistance to a variety of chemical, biological, and physical stressors in a non-specific way. These adaptogen properties have been mainly attributed to the glycoside salidroside, one of the bioactive compounds present in the standardized extracts of R. Rosea. Here, we aimed to investigate whether a single dose of salidroside is able to affect memory and emotional behavior in wild type adult mice. We performed fear conditioning to assess cued and contextual memory, elevated plus maze and open field to evaluate anxiety, and tail suspension test to evaluate depression. Our results showed that a single i.p. administration of salidroside was able to enhance fear memory and exerted an anxiolytic and antidepressant effect. These data confirmed the adaptogenic effect of R. Rosea bioactive compounds in animal models and suggest that salidroside might represent an interesting pharmacological tool to ameliorate cognition and counteract mood disorders.
Keywords: Animals; Anti-Anxiety Agents; Antidepressive Agents; Anxiety Disorders; Conditioning (Psychology); Depressive Disorder; Disease Models, Animal; Drug Evaluation, Preclinical; Exploratory Behavior; Fear; Female; Freezing Reaction, Cataleptic; Glucosides; Male; Maze Learning; Memory; Mice, Inbred C57BL; Motor Activity; Nootropic Agents; Phenols; Phytotherapy; Plant Extracts; Rhodiola

Screening for Mild Cognitive Impairment: Comparison of "MCI Specific" Screening Instruments. - O'Caoimh, Rónán; Timmons, Suzanne; Molloy, D William (J Alzheimers Dis, 2016)
BACKGROUND: Sensitive and specific instruments are required to screen for cognitive impairment (CI) in busy clinical practice. The Montreal Cognitive Assessment (MoCA) is widely validated but few studies compare it to tests designed specifically to detect mild cognitive impairment (MCI). OBJECTIVE: Comparison of two "MCI specific" screens: the Quick Mild Cognitive Impairment screen (Qmci) and MoCA. METHODS: Patients with subjective memory complaints (SMC; n = 73), MCI (n = 103), or dementia (n = 274), were referred to a university hospital memory clinic and underwent comprehensive assessment. Caregivers, without cognitive symptoms, were recruited as normal controls (n = 101). RESULTS: The Qmci was more accurate than the MoCA in differentiating MCI from controls, area under the curve (AUC) of 0.90 versus 0.80, p = 0.009. The Qmci had greater (AUC 0.81), albeit non-significant, accuracy than the MoCA (AUC 0.73) in separating MCI from SMC, p = 0.09. At its recommended cut-off (<62/100), the Qmci had a sensitivity of 90% and specificity of 87% for CI (MCI/dementia). Raising the cut-off to <65 optimized sensitivity (94%), reducing specificity (80%). At <26/30 the MoCA had better sensitivity (96%) but poor specificity (58%). A MoCA cut-off of <24 provided the optimal balance. Median Qmci administration time was 4.5 (±1.3) minutes compared with 9.5 (±2.8) for the MoCA. CONCLUSIONS: Although both tests distinguish MCI from dementia, the Qmci is particularly accurate in separating MCI from normal cognition and has shorter administration times, suggesting it is more useful in busy hospital clinics. This study reaffirms the high sensitivity of the MoCA but suggests a lower cut-off (<24) in this setting.
Keywords: Aged; Aged, 80 and over; Area Under Curve; Cognitive Dysfunction; Dementia; Diagnosis, Differential; Female; Humans; Male; Neuropsychological Tests; Perception; ROC Curve; Sensitivity and Specificity; Time Factors

Self-Reported Traumatic Brain Injury and Mild Cognitive Impairment: Increased Risk and Earlier Age of Diagnosis. - LoBue, Christian; Denney, David; Hynan, Linda S; Rossetti, Heidi C; Lacritz, Laura H; Hart, John; Womack, Kyle B; Woon, Fu L; Cullum, C Munro (J Alzheimers Dis, 2016)
This study examined whether history of traumatic brain injury (TBI) is associated with increased risk and earlier onset of mild cognitive impairment (MCI). Subjects with MCI (n = 3,187) and normal cognition (n = 3,244) were obtained from the National Alzheimer's Coordinating Center database. TBI was categorized based on lifetime reported TBI with loss of consciousness (LOC) without chronic deficit. Logistic regression was used to examine TBI history as a predictor of MCI, adjusted for demographics, apolipoprotein E-ɛ4 (ApoE4), a composite vascular risk score, and history of psychiatric factors. ANCOVA was used to examine whether age at MCI diagnosis and estimated age of onset differed between those with (TBI+) and without (TBI-) a history of TBI. TBI history was a significant predictor (p <  0.01) and associated with increased odds of MCI diagnosis in unadjusted (OR = 1.25; 95% CI = 1.05-1.49) and adjusted models, accounting for age, education, ApoE4, and a composite vascular score (OR = 1.32; 95% CI = 1.10-1.58). This association, however, was largely attenuated (OR = 1.14; 95% CI = 0.94-1.37; p = 0.18) after adjustment for reported history of depression. MCI was diagnosed a mean of 2.3 years earlier (p <  0.001) in the TBI+ group, and although TBI+ subjects had an estimated mean of decline 1.7 years earlier, clinician-estimated age of onset failed to differ (p = 0.13) when gender and psychiatric factors were controlled. This is the first report of a possible role for TBI as a risk factor in MCI, but its association may be related to other factors such as gender and depression and requires further investigation.
Keywords: Age of Onset; Aged; Apolipoproteins E; Brain Injuries, Traumatic; Cognitive Dysfunction; Cohort Studies; Databases, Factual; Depression; Educational Status; Female; Humans; Logistic Models; Male; Risk Factors; Self Report; United States

Sensitivity of Neuropsychological Tests to Identify Cognitive Decline in Highly Educated Elderly Individuals: 12 Months Follow up. - Elkana, Odelia; Eisikovits, Osnat Reichman; Oren, Noga; Betzale, Vered; Giladi, Nir; Ash, Elissa L (J Alzheimers Dis, 2016)
Highly educated individuals have a lower risk of developing dementia and Alzheimer's disease (AD). A common assumption is that their "cognitive reserve" protects them from cognitive decline and postpones the clinical manifestation of dementia. These highly educated individuals usually obtain normal scores on cognitive screening tests, although at the same time they can experience subjective cognitive decline and difficulty in multiple cognitive domains. Although comprehensive neuropsychological evaluations usually identify subtle changes in cognition, they demand extensive resources and thus are expensive and difficult to obtain. Therefore, lack of sensitivity of screening tests on the one hand, along with difficulty to acquire a comprehensive neuropsychological evaluation on the other hand, impede identification of cognitive decline at its earliest stages in this special population. Accordingly, this study aims to identify which neuropsychological tests have the highest sensitivity to detect the earliest stages of cognitive decline among highly educated elderly [n = 27, ages 66-80 (mean = 72.6 SD = 4.54), mean education level = 17.14 (SD = 3.21 range: 12-24 years)]. Baseline scores and scores at one-year follow up were obtained. We also conducted MRI scans to characterize the relation between brain volume and cognitive performance. Results show significant reductions in RVALT, Semantic verbal Fluency, ROCF copy, and MoCA scores whereas PF, TMT, ROCF delay, digit span, and knowledge tests were not significant. The study stresses the importance of using sensitive neuropsychological tests to examine this special population and the need to create norms that combine an individual's education with age.
Keywords: Aged; Aged, 80 and over; Aging; Brain; Cognition Disorders; Educational Status; Female; Follow-Up Studies; Humans; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Sensitivity and Specificity; Statistics as Topic

Shared Genetic Etiology between Type 2 Diabetes and Alzheimer's Disease Identified by Bioinformatics Analysis. - Gao, Lei; Cui, Zhen; Shen, Liang; Ji, Hong-Fang (J Alzheimers Dis, 2016)
Type 2 diabetes (T2D) and Alzheimer's disease (AD) are two major health issues, and increasing evidence in recent years supports the close connection between these two diseases. The present study aimed to explore the shared genetic etiology underlying T2D and AD based on the available genome wide association studies (GWAS) data collected through August 2014. We performed bioinformatics analyses based on GWAS data of T2D and AD on single nucleotide polymorphisms (SNPs), gene, and pathway levels, respectively. Six SNPs (rs111789331, rs12721046, rs12721051, rs4420638, rs56131196, and rs66626994) were identified for the first time to be shared genetic factors between T2D and AD. Further functional enrichment analysis found lipid metabolism related pathways to be common between these two disorders. The findings may have important implications for future mechanistic and interventional studies for T2D and AD.
Keywords: Alzheimer Disease; Apolipoprotein C-I; Computational Biology; Databases, Factual; Diabetes Mellitus, Type 2; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Lipid Metabolism; Male; Polymorphism, Single Nucleotide

Social Cognition Deficits: The Key to Discriminate Behavioral Variant Frontotemporal Dementia from Alzheimer's Disease Regardless of Amnesia? - Bertoux, Maxime; de Souza, Leonardo Cruz; O'Callaghan, Claire; Greve, Andrea; Sarazin, Marie; Dubois, Bruno; Hornberger, Michael (J Alzheimers Dis, 2016)
Relative sparing of episodic memory is a diagnostic criterion of behavioral variant frontotemporal dementia (bvFTD). However, increasing evidence suggests that bvFTD patients can show episodic memory deficits at a similar level as Alzheimer's disease (AD). Social cognition tasks have been proposed to distinguish bvFTD, but no study to date has explored the utility of such tasks for the diagnosis of amnestic bvFTD. Here, we contrasted social cognition performance of amnestic and non-amnestic bvFTD from AD, with a subgroup having confirmed in vivo pathology markers. Ninety-six participants (38 bvFTD and 28 AD patients as well as 30 controls) performed the short Social-cognition and Emotional Assessment (mini-SEA). BvFTD patients were divided into amnestic versus non-amnestic presentation using the validated Free and Cued Selective Reminding Test (FCSRT) assessing episodic memory. As expected, the accuracy of the FCSRT to distinguish the overall bvFTD group from AD was low (69.7% ) with ∼50% of bvFTD patients being amnestic. By contrast, the diagnostic accuracy of the mini-SEA was high (87.9% ). When bvFTD patients were split on the level of amnesia, mini-SEA diagnostic accuracy remained high (85.1% ) for amnestic bvFTD versus AD and increased to very high (93.9% ) for non-amnestic bvFTD versus AD. Social cognition deficits can distinguish bvFTD and AD regardless of amnesia to a high degree and provide a simple way to distinguish both diseases at presentation. These findings have clear implications for the diagnostic criteria of bvFTD. They suggest that the emphasis should be on social cognition deficits with episodic memory deficits not being a helpful diagnostic criterion in bvFTD.
Keywords: Aged; Alzheimer Disease; Amnesia; Cognition; Diagnosis, Differential; Emotions; Female; Frontotemporal Dementia; Humans; Male; Memory, Episodic; Neuropsychological Tests; Social Perception

The Societal Cost of Dementia in Singapore: Results from the WiSE Study. - Abdin, Edimansyah; Subramaniam, Mythily; Achilla, Evanthia; Chong, Siow Ann; Vaingankar, Janhavi Ajit; Picco, Louisa; Sambasivam, Rajeswari; Pang, Shirlene; Chua, Boon Yiang; Ng, Li Ling; Chua, Hong Choon; Heng, Derrick; et al. (J Alzheimers Dis, 2016)
BACKGROUND: There is currently limited evidence on the economic burden that dementia exerts on multi-ethnic Asian populations. OBJECTIVE: The present study aimed to estimate the economic cost of dementia in Singapore. METHODS: We used data from the Well-being of the Singapore Elderly study, a nationally representative survey of the older Singapore Resident population aged 60 years and above. Generalized linear modeling was used to estimate factors associated with costs. RESULTS: The total cost of dementia in 2013 was estimated at S$532 million (95% CI, S$361 million to S$701 million) while the annual cost per person was estimated at S$10,245 per year (95% CI, S$6,954 to S$12,495). Apart from dementia, higher total societal cost were also significantly associated with older age, Indian ethnicity, and those who were diagnosed with heart problems, stroke, diabetes or depression, whereas being divorced/separated, lower education, and those who were diagnosed with hypertension were significantly associated with lower total societal cost. CONCLUSION: The study provides a rich body of information on healthcare utilization and cost of dementia, which is essential for future planning of services for the elderly population.
Keywords: Adult; Aged, 80 and over; Cost of Illness; Dementia; Female; Humans; Linear Models; Male; Middle Aged; Singapore

Spatial Memory Impairment is Associated with Intraneural Amyloid-β Immunoreactivity and Dysfunctional Arc Expression in the Hippocampal-CA3 Region of a Transgenic Mouse Model of Alzheimer's Disease. - Morin, Jean-Pascal; Cerón-Solano, Giovanni; Velázquez-Campos, Giovanna; Pacheco-López, Gustavo; Bermúdez-Rattoni, Federico; Díaz-Cintra, Sofía (J Alzheimers Dis, 2016)
Dysfunction of synaptic communication in cortical and hippocampal networks has been suggested as one of the neuropathological hallmarks of the early stages of Alzheimer's disease (AD). Also, several lines of evidence have linked disrupted levels of activity-regulated cytoskeletal associated protein (Arc), an immediate early gene product that plays a central role in synaptic plasticity, with AD "synaptopathy". The mapping of Arc expression patterns in brain networks has been extensively used as a marker of memory-relevant neuronal activity history. Here we evaluated basal and behavior-induced Arc expression in hippocampal networks of the 3xTg-AD mouse model of AD. The basal percentage of Arc-expressing cells in 10-month-old 3xTg-AD mice was higher than wild type in CA3 (4.88% versus 1.77% , respectively) but similar in CA1 (1.75% versus 2.75% ). Noteworthy, this difference was not observed at 3 months of age. Furthermore, although a Morris water maze test probe induced a steep (∼4-fold) increment in the percentage of Arc+ cells in the CA3 region of the 10-month-old wild-type group, no such increment was observed in age-matched 3xTg-AD, whereas the amount of Arc+ cells in CA1 increased in both groups. Further, we detected that CA3 neurons with amyloid-β were much more likely to express Arc protein under basal conditions. We propose that in 3xTg-AD mice, intraneuronal amyloid-β expression in CA3 could increase unspecific neuronal activation and subsequent Arc protein expression, which might impair further memory-stabilizing processes.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Benzeneacetamides; CA3 Region, Hippocampal; Cytoskeletal Proteins; Disease Models, Animal; Gene Expression Regulation; Humans; Maze Learning; Memory Disorders; Mice; Mice, Transgenic; Mutation; Nerve Tissue Proteins; Neurons; Presenilin-1; Pyridines; tau Proteins

Specific Features of Subjective Cognitive Decline Predict Faster Conversion to Mild Cognitive Impairment. - Fernández-Blázquez, Miguel A; Ávila-Villanueva, Marina; Maestú, Fernando; Medina, Miguel (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease (AD) is a silent disorder that needs the earliest possible intervention in order to reduce its high economic and social impact. It has been recently suggested that subjective cognitive decline (SCD) appears at preclinical stages many years before the onset of AD. Therefore, SCD could become an ideal target for early therapeutic intervention. OBJECTIVE: The goal of this study was to evaluate the clinical significance of SCD on the conversion from a cognitively healthy stage to a mild cognitive impairment (MCI) in one-year follow-up. METHODS: A total of 608 cognitively intact individuals from the Vallecas Project's cohort, a community-based prospective study to identify early markers of AD, were enrolled in this study. Participants were classified in three groups: i) No Complaints (NCg), ii) Subjects with complaints in one or more cognitive domains (SCDg), and iii) Subjects who, besides complaints, fulfilled the features of SCD Plus proposed by the International Working Group of SCD (SCD-Pg). RESULTS: Individuals were followed up for a mean of 13.1 months (range 10.7-22.4). During this time, 41 volunteers developed MCI (6.7% of total sample). The conversion rate for SCD-Pg (18.9%) was significantly higher than SCDg (5.6%) and NCg (4.9%). CONCLUSION: Specific features associated with SCD may help to identify individuals at high risk of fast conversion to MCI. These results highlight the importance of a close follow-up of subjects with SCD-P and include them in early intervention programs because of their increased risk for the development of MCI.
Keywords: Aged; Alzheimer Disease; Apolipoprotein E4; Cognitive Dysfunction; Disease Progression; Female; Follow-Up Studies; Genotyping Techniques; Humans; Kaplan-Meier Estimate; Male; Neuropsychological Tests; Perception; Prodromal Symptoms; Prognosis; Prospective Studies; Time Factors

Strategies for improving memory: a randomized trial of memory groups for older people, including those with mild cognitive impairment. - Kinsella, Glynda J; Ames, David; Storey, Elsdon; Ong, Ben; Pike, Kerryn E; Saling, Michael M; Clare, Linda; Mullaly, Elizabeth; Rand, Elizabeth (J Alzheimers Dis, 2016)
BACKGROUND: Governments are promoting the importance of maintaining cognitive health into older age to minimize risk of cognitive decline and dementia. Older people with amnestic mild cognitive impairment (aMCI) are particularly vulnerable to memory challenges in daily activities and are seeking ways to maintain independent living. OBJECTIVE: To evaluate the effectiveness of memory groups for improving memory strategies and memory ability of older people, especially those with aMCI. METHODS: 113 healthy older adults (HOA) and 106 adults with aMCI were randomized to a six-week memory group or a waitlist control condition. Outcome was evaluated through knowledge and use of memory strategies, memory ability (self-report and neuropsychological tests), and wellbeing. Assessments included a six-month follow-up. RESULTS: Using intention to treat analyses, there were intervention effects for HOA and aMCI groups in strategy knowledge (HOA: η2= 0.20; aMCI: η2= 0.06), strategy use (HOA: η2= 0.18; aMCI: η2= 0.08), and wellbeing (HOA: η2= 0.11; aMCI: η2= 0.05). There were also intervention effects in the HOA group, but not the aMCI group, in self-reported memory ability (η2= 0.06) and prospective memory tests (η2= 0.02). By six-month follow-up, gains were found on most HOA outcomes. In the aMCI group gains were found in strategy use, and by this stage, gains in prospective memory were also found. CONCLUSION: Memory groups can engage older people in techniques for maintaining cognitive health and improve memory performance, but more modest benefits are seen for older adults with aMCI.
Keywords: Aged; Aged, 80 and over; Aging; Cognitive Dysfunction; Cross-Over Studies; Female; Humans; Male; Memory, Episodic; Neuropsychological Tests; Self Report

STX, a Novel Membrane Estrogen Receptor Ligand, Protects Against Amyloid-β Toxicity. - Gray, Nora E; Zweig, Jonathan A; Kawamoto, Colleen; Quinn, Joseph F; Copenhaver, Philip F (J Alzheimers Dis, 2016)
Because STX is a selective ligand for membrane estrogen receptors, it may be able to confer the beneficial effects of estrogen without eliciting the deleterious side effects associated with activation of the nuclear estrogen receptors. This study evaluates the neuroprotective properties of STX in the context of amyloid-β (Aβ) exposure. MC65 and SH-SY5Y neuroblastoma cell lines, as well as primary hippocampal neurons from wild type (WT) and Tg2576 mice, were used to investigate the ability of STX to attenuate cell death, mitochondrial dysfunction, dendritic simplification, and synaptic loss induced by Aβ. STX prevented Aβ-induced cell death in both neuroblastoma cell lines; it also normalized the decrease in ATP and mitochondrial gene expression caused by Aβ in these cells. Notably, STX also increased ATP content and mitochondrial gene expression in control neuroblastoma cells (in the absence of Aβ). Likewise in primary neurons, STX increased ATP levels and mitochondrial gene expression in both genotypes. In addition, STX treatment enhanced dendritic arborization and spine densities in WT neurons and prevented the diminished outgrowth of dendrites caused by Aβ exposure in Tg2576 neurons. These data suggest that STX can act as an effective neuroprotective agent in the context of Aβ toxicity, improving mitochondrial function as well as dendritic growth and synaptic differentiation. In addition, since STX also improved these endpoints in the absence of Aβ, this compound may have broader therapeutic value beyond Alzheimer's disease.
Keywords: Acrylamides; Adenosine Triphosphate; Amyloid beta-Peptides; Animals; Cell Death; Cell Line, Tumor; Drug Evaluation, Preclinical; Estrogen Receptor Modulators; Genes, Mitochondrial; Hippocampus; Humans; Mice, Transgenic; Mitochondria; Neurons; Neuroprotective Agents

Subjective Memory Complaints in APOEɛ4 Carriers are Associated with High Amyloid-β Burden. - Zwan, Marissa D; Villemagne, Victor L; Doré, Vincent; Buckley, Rachel; Bourgeat, Pierrick; Veljanoski, Robyn; Salvado, Olivier; Williams, Rob; Margison, Laura; Rembach, Alan; Macaulay, S Lance; Martins, Ralph; et al. (J Alzheimers Dis, 2016)
BACKGROUND: APOEɛ4 genotype and aging have been identified as risk factors for Alzheimer's disease (AD). In addition, subjective memory complaints (SMC) might be a first clinical expression of the effect of AD pathology on cognitive functioning. OBJECTIVE: To assess whether APOEɛ4 genotype, age, SMC, and episodic memory are risk factors for high amyloid-β (Aβ) burden in cognitively normal elderly. METHODS: 307 cognitively normal participants (72.7 ± 6.8 years, 53% female, 55% SMC) from the Australian Imaging, Biomarkers and Lifestyle (AIBL) study underwent amyloid PET and APOE genotyping. Logistic regression analyses were performed to determine the association of APOEɛ4 genotype, age, SMC, and episodic memory with Aβ pathology. RESULTS: Odds of high Aβ burden were greater at an older age (OR = 3.21; 95% CI = 1.68-6.14), when SMC were present (OR = 1.90; 95% CI = 1.03-3.48), and for APOEɛ4 carriers (OR = 7.49; 95% CI = 3.96-14.15), while episodic memory was not associated with odds of high Aβ burden. Stratified analyses showed that odds of SMC for high Aβ burden were increased in specifically APOEɛ4 carriers (OR = 4.58, 95% CI = 1.83-11.49) and younger participants (OR = 3.73, 95% CI = 1.39-10.01). CONCLUSION: Aging, APOEɛ4 genotype, and SMC were associated with high Aβ burden. SMC were especially indicative of high Aβ burden in younger participants and in APOEɛ4 carriers. These findings suggest that selection based on the presence of SMC, APOEɛ4 genotype and age may help identify healthy elderly participants with high Aβ burden eligible for secondary prevention trials.
Keywords: Aged; Aging; Amyloid beta-Peptides; Aniline Compounds; Apolipoprotein E4; Benzothiazoles; Brain; Cognition Disorders; Female; Genotyping Techniques; Heterozygote; Humans; Logistic Models; Male; Neuropsychological Tests; Positron-Emission Tomography; Radiopharmaceuticals; Thiazoles

T3D-959: A Multi-Faceted Disease Remedial Drug Candidate for the Treatment of Alzheimer's Disease. - Tong, Ming; Deochand, Chetram; Didsbury, John; de la Monte, Suzanne M (J Alzheimers Dis, 2016)
BACKGROUND: T3D-959, a dual PPAR-δ/PPAR γ nuclear receptor agonist and former diabetes drug candidate, has been repositioned as an Alzheimer's disease (AD)-modifying therapy. OBJECTIVE: This study examines the effectiveness and mechanisms of T3D-959's therapeutic effects using in vivo and ex vivo rat models of sporadic AD. METHODS: A sporadic AD model was generated by intracerebral (i.c.) administration of streptozotocin (STZ). Control and i.c. STZ treated rats were gavaged with saline or T3D-959 (0.3 to 3.0 mg/kg/day) for 28 days. Spatial learning and memory were evaluated using the Morris water maze test. Frontal lobe slice cultures generated 24 hours after i.c. STZ or vehicle were used to study early effects of T3D-959 (0.5-1.0 μM) on viability and molecular markers of AD. RESULTS: T3D-959 significantly improved spatial learning and memory in i.c STZ-treated rats. Mechanistically, T3D-959 significantly improved culture viability and brain morphology, reduced levels of oxidative stress and Aβ, and normalized expression of phospho-tau, choline acetyltransferase, and myelin-associated glycoprotein. Protective effects occurred even at the lowest tested dose of T3D-959. CONCLUSIONS: Pre-clinical proof of concept has been demonstrated that T3D-959 can improve multiple pathologies of AD resulting in significant improvements in cognitive function and molecular and biochemical indices of neurodegeneration. These results support the theses that (1) effective disease modification in AD can be achieved by targeting relevant nuclear receptors, and (2) treating AD as a metabolic disease has the potential to be disease remedial. A Phase 2a trial of T3D-959 in mild-to-moderate AD patients has been initiated (ClinicalTrials.gov identifier NCT02560753).
Keywords: Alzheimer Disease; Analysis of Variance; Animals; Animals, Newborn; Antibiotics, Antineoplastic; Antipsychotic Agents; Blood Glucose; Body Weight; Brain; Choline O-Acetyltransferase; Disease Models, Animal; Dose-Response Relationship, Drug; Glial Fibrillary Acidic Protein; Glucosephosphate Dehydrogenase; In Vitro Techniques; Maze Learning; Myelin Basic Protein; Neurotoxicity Syndromes; Organ Culture Techniques; PPAR delta; PPAR gamma; Rats; Rats, Long-Evans; Spatial Learning; Streptozocin

Targretin Improves Cognitive and Biological Markers in a Patient with Alzheimer's Disease. - Pierrot, Nathalie; Lhommel, Renaud; Quenon, Lisa; Hanseeuw, Bernard; Dricot, Laurence; Sindic, Christian; Maloteaux, Jean-Marie; Octavea, Jean-Noël; Ivanoiu, Adrian (J Alzheimers Dis, 2016)
We present the effects of Targretin® (bexarotene) on cognition and biomarkers in a patient with mild Alzheimer's disease (AD). Targretin® is a Retinoic X Receptor (RXR) agonist shown to improve synaptic and cognitive functions in animal models of AD by increasing neuronal cholesterol efflux. After 6 months of treatment with Targretin® 300 mg/day, memory improved by about 40% and the tau protein in the cerebrospinal fluid decreased by about 20% . No significant side effects were noticed. This observation in a single patient indicates that Targretin® may improve memory performance and biological markers at an early stage of AD.
Keywords: Aged; Alzheimer Disease; Amyloidogenic Proteins; Biomarkers; Cognition Disorders; Humans; Male; Mental Recall; Neuropsychological Tests; Receptors, Retinoic Acid; tau Proteins; Tetrahydronaphthalenes

Tau Accumulation in Primary Motor Cortex of Variant Alzheimer's Disease with Spastic Paraparesis. - Lyoo, Chul Hyoung; Cho, Hanna; Choi, Jae Yong; Hwang, Mi Song; Hong, Sang Kyoon; Kim, Yun Joong; Ryu, Young Hoon; Lee, Myung Sik (J Alzheimers Dis, 2016)
We studied topographic distribution of tau and amyloid-β in a patient with variant Alzheimer's disease with spastic paraparesis (VarAD) by comparing AD patients. The proband developed progressive memory impairment, dysarthria, and spastic paraparesis at age 23. Heterozygous missense mutation (L166P) was found in exon 6 of presenilin-1 gene. The proband showed prominently increased amyloid binding in striatum and cerebellum and asymmetrical tau binding in the primary sensorimotor cortex contralateral to the side more affected by spasticity. We suspect that upper motor neuron dysfunctions may be attributed to excessive abnormal tau accumulation rather than amyloid-β in the primary motor cortex.
Keywords: Adult; Aged; Alzheimer Disease; Aniline Compounds; Brain Mapping; Carbolines; Female; Humans; Male; Motor Cortex; Mutation, Missense; Paraparesis, Spastic; Positron-Emission Tomography; Presenilin-1; Radiopharmaceuticals; Stilbenes; tau Proteins

A TgCRND8 Mouse Model of Alzheimer's Disease Exhibits Sexual Dimorphisms in Behavioral Indices of Cognitive Reserve. - Granger, Matthew W; Franko, Bettina; Taylor, Matthew W; Messier, Claude; George-Hyslop, Peter St; Bennett, Steffany A L (J Alzheimers Dis, 2016)
Cognitive decline is sexually dimorphic in Alzheimer's disease (AD). Men show higher incidences of amnestic mild cognitive impairment yet women disproportionally phenoconvert to AD. It is hypothesized that men maintain greater cognitive reserve than women under comparable amyloid-β (Aβ) challenge. One behavioral aspect of cognitive reserve in mice is the capacity to cope with Aβ-associated stereotypies by switching to increasingly effective navigational search strategies in the Morris water maze. To explore inherent sex differences in this paradigm, however, we require an AβPP mouse model wherein behavioral flexibility is impaired earlier in females than males despite equivalent Aβ load. Here, we show that when F1 C57Bl/6×C3H/HeJ TgCRND8 mice are placed on C57Bl/6 background, N5 Tg males and females exhibit equivalent Aβ pathologies at 2, 4, 6, and 8 months of age yet females display learning and memory deficits earlier than males. We further show that this N5 line does not carry the autosomal recessive pde6brd1 mutation that impairs visual acuity and that the estrous cycle is not disrupted on this genetic background. At 5.5 months of age, Tg males, but not females, compensate for Aβ-associated stereotypic behaviors (i.e., hyperactive tight circling) by alternating navigational search strategies and adopting increasingly productive spatial search strategies. Females fail to overcome Aβ-associated stereotypies and do not efficiently switch from systematic to spatial learning strategies. Together, these data identify a novel AβPP mouse model that can be used for preclinical testing of interventions targeting sexual dimorphisms in behavioral indices of cognitive reserve.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Brain; Cognitive Reserve; Cyclic Nucleotide Phosphodiesterases, Type 6; Disease Models, Animal; Female; Humans; Male; Maze Learning; Mice, Inbred C3H; Mice, Inbred C57BL; Mice, Transgenic; Plaque, Amyloid; Psychomotor Performance; Sex Characteristics; Spatial Memory; Spatial Navigation; Survival Analysis

Thyroid-Stimulating Hormone and Mild Cognitive Impairment: Results of the Heinz Nixdorf Recall Study. - Winkler, Angela; Weimar, Christian; Jöckel, Karl-Heinz; Erbel, Raimund; Dragano, Nico; Broecker-Preuss, Martina; Moebus, Susanne; Führer-Sakel, Dagmar; Dlugaj, Martha (J Alzheimers Dis, 2016)
BACKGROUND: Although some studies reported on the association of serum thyroid-stimulating hormone (TSH) concentration and cognition, only one population-based study investigated the association of TSH concentration and mild cognitive impairment (MCI). OBJECTIVE: To investigate the gender-specific association of low- and high-normal TSH concentrations with MCI in euthyroid participants. METHODS: Analysis sample 1 included 2,563 euthyroid participants (aged 50-80 years) from the second examination of the population-based Heinz Nixdorf Recall study. Gender-specific TSH quintiles (Q1 low, Q2-Q4 middle, Q5 high TSH concentration) were determined and group comparisons of age- and education-adjusted mean scores were performed for all cognitive subtests. Analysis sample 2 included 378 participants with MCI and 931 cognitively normal participants. MCI was diagnosed according to previously published MCI criteria. Multivariate logistic regression models were performed using TSH quintiles (Q2-Q4 as reference) to assess the association of low- and high-normal TSH concentration with MCI. Models were performed unadjusted and adjusted for sociodemographic and cardiovascular risk factors. RESULTS: Group comparisons showed significant differences only in the immediate recall of the verbal memory task in women. Only women showed a strong association of high-normal TSH concentration with MCI (unadjusted: odds ratio 2.09, 95% confidence interval 1.29-3.37, full adjusted: 1.86, 1.06-3.27). There was no association with low-normal TSH concentration in women and no association of either low- or high-normal TSH concentration with MCI in men. CONCLUSIONS: These results suggest that women with high-normal TSH concentration might be at higher risk of cognitive decline. This needs to be confirmed in the longitudinal analysis.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Case-Control Studies; Cognitive Dysfunction; Female; Follow-Up Studies; Humans; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Risk Factors; Sex Characteristics; Statistics, Nonparametric; Thyrotropin

Tract-Specific Correlates of Neuropsychological Deficits in Patients with Subcortical Vascular Cognitive Impairment. - Jung, Na-Yeon; Han, Cheol E; Kim, Hee Jin; Yoo, Sang Wook; Kim, Hee-Jong; Kim, Eun-Joo; Na, Duk L; Lockhart, Samuel N; Jagust, William J; Seong, Joon-Kyung; Seo, Sang Won (J Alzheimers Dis, 2016)
The white matter tract-specific correlates of neuropsychological deficits are not fully established in patients with subcortical vascular cognitive impairment (SVCI), where white matter tract damage may be a critical factor in cognitive impairment. The purpose of this study is to investigate the tract-specific correlates of neuropsychological deficits in SVCI patients using tract-specific statistical analysis (TSSA). We prospectively recruited 114 SVCI patients, and 55 age-, gender-, and education-matched individuals with normal cognition (NC). All participants underwent diffusion weighted imaging and neuropsychological testing. We classified tractography results into fourteen major fiber tracts and analyzed group comparison and correlation with cognitive impairments. Relative to NC subjects, SVCI patients showed decreased fractional anisotropy values in bilateral anterior-thalamic radiation, cingulum, superior-longitudinal fasciculus, uncinate fasciculus, corticospinal tract, and left inferior-longitudinal fasciculus. Focal disruptions in specific tracts were associated with specific cognitive impairments. Our findings suggest that disconnection of specific white matter tracts, especially those neighboring and providing connections between gray matter regions important to certain cognitive functions, may contribute to specific cognitive impairments in SVCI.
Keywords: Aged; Brain; Cerebrovascular Disorders; Cognitive Dysfunction; Diffusion Magnetic Resonance Imaging; Diffusion Tensor Imaging; Female; Gray Matter; Humans; Male; Neural Pathways; Neuropsychological Tests; White Matter

Transferring cut-off values between assays for cerebrospinal fluid Alzheimer's disease biomarkers. - García Barrado, Leandro; Coart, Els; Vanderstichele, Hugo M J; Burzykowski, Tomasz (J Alzheimers Dis, 2016)
Current technologies quantifying cerebrospinal fluid biomarkers to identify subjects with Alzheimer's disease pathology report different concentrations in function of technology and suffer from between-laboratory variability. Hence, lab- and technology-specific cut-off values are required. It is common practice to establish cut-off values on small datasets and, in the absence of well-characterized samples, to transfer the cut-offs to another assay format using 'side-by-side' testing of samples with both assays. We evaluated the uncertainty in cut-off estimation and the performance of two methods of cut-off transfer by using two clinical datasets and simulated data. The cut-off for the new assay was transferred by applying the commonly-used linear regression approach and a new Bayesian method, which consists of using prior information about the current assay for estimation of the biomarker's distributions for the new assay. Simulations show that cut-offs established with current sample sizes are insufficiently precise and also show the effect of increasing sample sizes on the cut-offs' precision. The Bayesian method results in unbiased and less variable cut-offs with substantially narrower 95% confidence intervals compared to the linear-regression transfer. For the BIODEM datasets, the transferred cut-offs for INNO-BIA Aβ1-42 are 167.5 pg/mL (95% credible interval [156.1, 178.0] and 172.8 pg/mL (95% CI [147.6, 179.6]) with Bayesian and linear regression methods, respectively. For the EUROIMMUN assay, the estimated cut-offs are 402.8 pg/mL (95% credible interval [348.0, 473.9]) and 364.4 pg/mL (95% CI [269.7, 426.8]). Sample sizes and statistical methods used to establish and transfer cut-off values have to be carefully considered to guarantee optimal diagnostic performance of biomarkers.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Bayes Theorem; Biomarkers; Cognitive Dysfunction; Datasets as Topic; Humans; Linear Models; Multivariate Analysis; Peptide Fragments; tau Proteins

UCH-L1 Inhibition Decreases the Microtubule-Binding Function of Tau Protein. - Xie, Min; Han, Yun; Yu, Quntao; Wang, Xia; Wang, Shaohui; Liao, Xiaomei (J Alzheimers Dis, 2016)
Ubiquitin C-terminal hydrolase L1 (UCH-L1) is critical for protein degradation and free ubiquitin recycling. In Alzheimer's disease brains, UCH-L1 is negatively related to neurofibrillary tangles whose major component is hyperphosphorylated tau protein, but the direct action of UCH-L1 on tau has not been reported. In the current study, mouse neuroblastoma Neuro2a (N2a) cells were treated by the different concentrations of UCH-L1 inhibitor LDN (2.5, 5 and 10 μM) to inhibit the hydrolase activity of UCH-L1. In addition, we also used UCH-L1 siRNA to treat the HEK293/tau441 cells to decrease the expression of UCH-L1. After LDN and UCH-L1 siRNA treatment, we used immunofluorescence, immunoprecipitation, and tau-microtubule binding assay to measure the microtubule-binding ability and post-translational modifications of tau protein. All the results presented that both inhibition of the activity and expression of UCH-L1 induced the decreased microtubule-binding ability and increased phosphorylation of tau protein. Abnormal aggregation and ubiquitination of tau protein was also observed after UCH-L1 inhibition. The above results suggested that aggregation of tau protein might be devoted to the abnormal post-translational modifications of tau protein. Our study first indicates that dysfunction of UCH-L1 most likely affected normal biological function of tau protein through decreasing degradation of ubiquitinated and hyperphosphorylated tau.
Keywords: Animals; Cell Line, Tumor; Dose-Response Relationship, Drug; HEK293 Cells; Humans; Immunoprecipitation; Indoles; Mice; Microtubules; Neuroblastoma; Oximes; Protein Binding; Proteolysis; RNA, Small Interfering; tau Proteins; Ubiquitin Thiolesterase; Ubiquitination

Unmet Needs of Community-Dwelling Primary Care Patients with Dementia in Germany: Prevalence and Correlates. - Eichler, Tilly; Thyrian, Jochen René; Hertel, Johannes; Richter, Steffen; Wucherer, Diana; Michalowsky, Bernhard; Teipel, Stefan; Kilimann, Ingo; Dreier, Adina; Hoffmann, Wolfgang (J Alzheimers Dis, 2016)
BACKGROUND: To provide an optimal care for persons with dementia (PWD), their individual unmet needs have to be identified and comprehensively addressed. OBJECTIVES: Present analyses aim to describe the number and types of unmet needs of German primary care patients screened positive for dementia and factors associated with the number of unmet needs. METHODS: DelpHi-MV (Dementia: life- and person-centered help in Mecklenburg-Western Pomerania) is a general practitioner-based, cluster-randomized controlled intervention trial. Analyses are based on the baseline data of 227 PWD (≥70 years, living at home) of the intervention group who had screened positive for dementia (DemTect<9) and received a standardized computer-assisted needs assessment. RESULTS: PWD had on average 8.77±5.04 unmet needs (Range = 0-31). More than 90% of the PWD had three or more unmet needs. Unmet needs were identified across all predefined 26 subcategories. The majority of unmet needs occurred in the domains "nursing treatment and care" (38%), "social counseling and legal support" (20%), and "pharmacological treatment and care" (15%). More impairment in the activities of daily living was the only factor that was significantly associated with a higher number of unmet needs, independent of age, gender, living situation, presence of an informal caregiver, cognitive impairment, and depression. CONCLUSIONS: Present results demonstrate that community-dwelling PWD had a broad range of varying unmet needs. These findings emphasize the importance of a comprehensive needs assessment that allows the identification of individual needs as the basis for a tailored intervention- such as Dementia Care Management- that can address these needs.
Keywords: Aged, 80 and over; Caregivers; Cross-Sectional Studies; Dementia; Depression; Female; Germany; Health Services Needs and Demand; Humans; Male; Needs Assessment; Prevalence

Unstable Body Mass Index and Progression to Probable Alzheimer's Disease Dementia in Patients with Amnestic Mild Cognitive Impairment. - Ye, Byoung Seok; Jang, Eun Young; Kim, Seong Yoon; Kim, Eun-Joo; Park, Sun Ah; Lee, Yunhwan; Hong, Chang Hyung; Choi, Seong Hye; Yoon, Bora; Yoon, Soo Jin; Na, Hae Ri; Lee, Jae-Hong; et al. (J Alzheimers Dis, 2016)
BACKGROUND AND OBJECTIVE: We investigated the influence of body mass index (BMI) status at baseline and changes in BMI over a follow-up period on the development of dementia in amnestic mild cognitive impairment (aMCI) patients. METHODS: The longitudinal data of 747 aMCI patients were used to investigate the relationships among baseline BMI status, subsequent changes in BMI (median follow-up duration: 1.6 years, interquartile range: 1.0-2.3 years), and risk of progression to probable Alzheimer's disease dementia (pADD). The aMCI patients were classified into underweight, normal weight, overweight, and obese subgroups, and further categorized into increased BMI, stable BMI, and decreased BMI subgroups during follow-up using a 4% mean annual change in BMI cut-off value. RESULTS: Compared to the normal weight group, the underweight group had a higher risk of pADD (hazard ratio [HR]: 1.89, 95% confidence interval [CI]: 1.07-3.37) while the obese group had a lower risk (HR: 0.70, 95% CI: 0.49-0.999). After controllingfor baseline BMI status, the decreased BMI (HR: 2.29, 95% CI: 1.41-3.72) and increased BMI (HR: 3.96, 95% CI: 2.62-6.00) groups were at increased risk of progression to pADD. CONCLUSIONS: Our findings suggested that underweight at baseline was associated with a higher risk of progression to pADD, while obesity at baseline predicted a lower risk. Furthermore, significant changes in BMI during the follow-up period reflected an increased risk of progression to pADD, regardless of BMI status at baseline.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Body Mass Index; Body Weight; Cognitive Dysfunction; Dementia; Disease Progression; Female; Humans; Kaplan-Meier Estimate; Longitudinal Studies; Male; Neuropsychological Tests; Registries

Upregulation of Connexin 43 Expression Via C-Jun N-Terminal Kinase Signaling in Prion Disease. - Lee, Geon-Hwi; Jang, Byungki; Choi, Hong-Seok; Kim, Hee-Jun; Park, Jeong-Ho; Jeon, Yong-Chul; Carp, Richard I; Kim, Yong-Sun; Choi, Eun-Kyoung (J Alzheimers Dis, 2016)
Prion infection leads to neuronal cell death, glial cell activation, and the accumulation of misfolded prion proteins. However, the altered cellular environments in animals with prion diseases are poorly understood. In the central nervous system, cells connect the cytoplasm of adjacent cells via connexin (Cx)-assembled gap junction channels to allow the direct exchange of small molecules, including ions, neurotransmitters, and signaling molecules, which regulate the activities of the connected cells. Here, we investigate the role of Cx43 in the pathogenesis of prion diseases. Upregulated Cx43 expression, which was dependent on c-Jun N-Terminal Kinase (JNK)/c-Jun signaling cascades, was found in prion-affected brain tissues and hippocampal neuronal cells. Scrapie infection-induced Cx43 formed aggregated plaques within the cytoplasmic compartments at the cell-cell interfaces. The ethidium bromide (EtBr) uptake assay and scrape-loading dye transfer assay demonstrated that increased Cx43 has functional consequences for the activity of Cx43 hemichannels. Interestingly, blockade of PrPSc accumulation reduced Cx43 expression through the inhibition of JNK signaling, indicating that PrPSc accumulation may be directly involved in JNK activation-mediated Cx43 upregulation. Overall, our findings describe a scrapie infection-mediated novel regulatory signaling pathway of Cx43 expression and may suggest a role for Cx43 in the pathogenesis of prion diseases.
Keywords: Animals; Brain; Cell Membrane; Cells, Cultured; Connexin 43; Disease Models, Animal; JNK Mitogen-Activated Protein Kinases; MAP Kinase Signaling System; Mesocricetus; Mice, Inbred C57BL; Mice, Knockout; PrPSc Proteins; RNA, Messenger; Scrapie; Up-Regulation

Usefulness of an Integrated Analysis of Different Memory Tasks to Predict the Progression from Mild Cognitive Impairment to Alzheimer's Disease: The Episodic Memory Score (EMS). - Marra, Camillo; Gainotti, Guido; Fadda, Lucia; Perri, Roberta; Lacidogna, Giordano; Scaricamazza, Eugenia; Piccininni, Chiara; Quaranta, Davide (J Alzheimers Dis, 2016)
Taking into the account both the severity and the consistency of performances obtained on memory tests by patients with amnestic mild cognitive impairment (aMCI) could improve the power to predict their progression to Alzheimer's disease. For this purpose, we constructed the Episodic Memory Score (EMS), which is obtained by subdividing in tertiles performances obtained at baseline in verbal (RAVLT) and visual episodic memory (Rey-Osterrieth Figure-delayed recall) and giving a score ranging from 1 (worst result) to 3 (best result) to results falling within each tertile. The EMS was computed for each patient by summing the tertile score obtained on each memory task, so that the total score ranged from 4 (worst performance) to 12 (best performance). The aMCI sample consisted of 198 subjects who completed the two-year follow-up, at the end of which 55 subjects had converted to dementia. The mean EMS score obtained by aMCI converters was significantly lower than that of aMCI-stable patients. In detecting conversion to dementia, the comparison between EMS and individual memory scores obtained at baseline was made by computing ROC curves, and estimating the respective area under the curve (AUC). The EMS had a larger AUC than the individual memory scores. At baseline aMCI converters performed worse than non-converters not only on memory tasks, but also on executive functions tasks. However, in a multiple variables logistic regression analysis in which all scores showing statistically significant differences between aMCI-converters and aMCI-stable were entered, the EMS was the only reliable predictor of progression from aMCI to dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Disease Progression; Female; Humans; Logistic Models; Longitudinal Studies; Male; Memory, Episodic; Mental Recall; Neuropsychological Tests; ROC Curve

The Utilization of Retinal Nerve Fiber Layer Thickness to Predict Cognitive Deterioration. - Shi, Zhongyong; Zhu, Yingbo; Wang, Meijuan; Wu, Yujie; Cao, Jing; Li, Chunbo; Xie, Zhongcong; Shen, Yuan (J Alzheimers Dis, 2016)
Our previous studies have shown that longitudinal reduction in retinal nerve fiber layer (RNFL) thickness is associated with cognitive deterioration. However, whether the combination of longitudinal reduction in RNFL thickness with baseline episodic memory performance can better predict cognitive deterioration remains unknown. Therefore, we set out to re-analyze the data obtained from our previous studies with 78 elderly adults (mean age 74.4 ± 3.83 years, 48.7% male) in the community over a 25-month period. The participants were categorized as either stable participants whose cognitive status did not change (n = 60) or converted participants whose cognitive status deteriorated (n = 18). A logistic regression analysis was applied to determine a conversion score for predicting the cognitive deterioration in the participants. We found that the area under the receiver operating characteristic curve (AUC) for the multivariable model was 0.854 (95% CI 0.762-0.947) using baseline story recall as a predictor, but the AUC increased to 0.915 (95% CI 0.849-0.981) with the addition of the longitudinal reduction of RNFL thickness in the inferior quadrant. The conversion score was significantly higher for the converted participants than the stable participants (0.59 ± 0.30 versus 0.12 ± 0.19, p <  0.001). Finally, the optimal cutoff value of the conversion score (0.134) was determined by the analysis of receiver operating characteristic curve, and this conversion score generated a sensitivity of 0.944 and a specificity of 0.767 in predicting the cognitive deterioration. These findings have established a system to perform a larger scale study to further test whether the longitudinal reduction in RNFL thickness could serve as a biomarker of Alzheimer's disease.
Keywords: Aged; Cognition Disorders; Female; Humans; Logistic Models; Longitudinal Studies; Male; Nerve Fibers; Neuropsychological Tests; Predictive Value of Tests; Retina; ROC Curve; Statistics, Nonparametric; Tomography, Optical Coherence

Validation of the Spanish version of the Baylor Profound Mental Status Examination. - Salmerón, Sergio; Huedo, Isabel; López-Utiel, Melisa; Soler-Moratalla, Isabel; Flores-Ruano, Teresa; Fernández-Sánchez, Miguel; Noguerón, Alicia; Doody, Rachelle S; Abizanda, Pedro (J Alzheimers Dis, 2016)
BACKGROUND: There are no short valid instruments to evaluate cognitive status in severe Alzheimer's disease (AD) patients in the Spanish language. OBJECTIVE: To validate the Spanish version of the Baylor Profound Mental Status Examination (BPMSE-Sp). METHODS: The Baylor Profound Mental Status Examination (BPMSE) was translated to Spanish and back translated. Validation was conducted in 100 patients with severe probable AD with a Mini-Mental State Examination (MMSE) <12. We assessed internal consistency (Cronbach's alpha), concurrent validity (Pearson's correlations) with the MMSE, Severe Impairment Battery (SIB), Neuropsychiatric Inventory Short Form (NPI-Q) and the Functional Assessment Staging and reliability. RESULTS: The mean age of patients was 84.9; 74% were female; 64% were institutionalized. The mean MMSE was 5.6; the mean BPMSE-Sp was 13.6; the mean BPMSE-Sp behavior was 1.2; the mean SIB was 42.2; and the mean NPI-Q was 4.7. BPMSE-Sp presented good internal consistency (Cronbach α= 0.84). There were significant correlations between the BPMSE-Sp and MMSE (r = 0.86, p <  0.001), and between the BPMSE-Sp and SIB (r = 0.92, p <  0.001). Inter-rater and test-retest reliability were in both cases excellent, ranging between 0.96 and 0.99 (p <  0.001). BPMSE-Sp had fewer floor and ceiling effects than the MMSE. CONCLUSIONS: The BPMSE-Sp is a valid tool for use in daily practice and research in the evaluation of cognitive function of patients with severe AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognition; Cognition Disorders; Female; Humans; Language; Male; Mental Status Schedule; Neuropsychological Tests; Reproducibility of Results; Severity of Illness Index; Spain

The Vanderbilt Memory & Aging Project: Study Design and Baseline Cohort Overview. - Jefferson, Angela L; Gifford, Katherine A; Acosta, Lealani Mae Y; Bell, Susan P; Donahue, Manus J; Davis, L Taylor; Gottlieb, JoAnn; Gupta, Deepak K; Hohman, Timothy J; Lane, Elizabeth M; Libon, David J; Mendes, Lisa A; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Vascular health factors frequently co-occur with Alzheimer's disease (AD). A better understanding of how systemic vascular and cerebrovascular health intersects with clinical and pathological AD may inform prevention and treatment opportunities. OBJECTIVE: To establish the Vanderbilt Memory & Aging Project, a case-control longitudinal study investigating vascular health and brain aging, and describe baseline methodology and participant characteristics. METHODS: From September 2012 to November 2014, 335 participants age 60- 92 were enrolled, including 168 individuals with mild cognitive impairment (MCI, 73±8 years, 41% female) and 167 age-, sex-, and race-matched cognitively normal controls (NC, 72±7 years, 41% female). At baseline, participants completed a physical and frailty examination, fasting blood draw, neuropsychological assessment, echocardiogram, cardiac MRI, and brain MRI. A subset underwent 24-hour ambulatory blood pressure monitoring and lumbar puncture for cerebrospinal fluid (CSF) collection. RESULTS: As designed, participant groups were comparable for age (p = 0.31), sex (p = 0.95), and race (p = 0.65). MCI participants had greater Framingham Stroke Risk Profile scores (p = 0.008), systolic blood pressure values (p = 0.008), and history of left ventricular hypertrophy (p = 0.04) than NC participants. As expected, MCI participants performed worse on all neuropsychological measures (p-values < 0.001), were more likely to be APOEɛ4 carriers (p = 0.02), and had enhanced CSF biomarkers, including lower Aβ42 (p = 0.02), higher total tau (p = 0.004), and higher p-tau (p = 0.02) compared to NC participants. CONCLUSION: Diverse sources of baseline and longitudinal data will provide rich opportunities to investigate pathways linking vascular and cerebrovascular health, clinical and pathological AD, and neurodegeneration contributing to novel strategies to delay or prevent cognitive decline.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Blood Pressure Monitoring, Ambulatory; Brain; Case-Control Studies; Cerebral Angiography; Cognitive Dysfunction; Echocardiography; Epidemiologic Research Design; Female; Follow-Up Studies; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Research Design

Vascular Health Indices and Cognitive Domain Function: Singapore Longitudinal Ageing Studies. - Lim, Shir Lynn; Gao, Qi; Nyunt, Ma Shwe Zin; Gong, Lingli; Lunaria, Josephine B; Lim, May Li; Ling, Audrey; Lam, Carolyn Su-Ping; Richards, Arthur Mark; Ling, Lieng Hsi; Ng, Tze Pin (J Alzheimers Dis, 2016)
BACKGROUND: Few studies have comprehensively evaluated the relationship between vascular disease and cognition of older adults without cardiac disease. OBJECTIVE: We explored the associations of structural atherosclerosis, vascular stiffness, and reactivity with global, memory, attention, language, visuospatial ability, and executive function in community-dwelling, non-demented older Asians without cardiac diseases. METHODS: Cognition was assessed by Mini-Mental State Examination (MMSE) (n = 308) and detailed neuropsychological tests (n = 155). Vascular measures included carotid intima-media thickness; aortic stiffness [carotid-femoral pulse wave velocity (CFPWV), aortic augmentation index (AI), and aortic pulse pressure (PP)]; carotid stiffness [elasticity modulus (Ep), beta index (β), arterial compliance (AC), carotid AI]; and endothelial function [reactive hyperemia index (RHI)]. Multivariable analyses controlled for potential confounding by demographics, apolipoprotein E genotype and cardiovascular risk factors. RESULTS: The participants' mean age was 63.0 ± 6.1 years. Inverse associations with MMSE were found for AC (β= 0.128, p = 0.019), Ep (β= -0.151, p = 0.008), β index (β= -0.122, p = 0.029), carotid stiffness z-score (β= -0.154, p = 0.007); with executive function for CFPWV (β= -0.209, p = 0.026), AC (β= 0.214, p = 0.005), Ep (β= -0.160, p = 0.050), β index (β= -0.165, p = 0.041), and both aortic (β= -0.229, p = 0.010) and carotid (β= -0.208, p = 0.010) stiffness z-scores; with verbal memory for AI (β= -0.229, p = 0.004) and aortic (β= -0.263, p = 0.004) stiffness z-score; with language for AI (β= -0.155, p = 0.025), aortic stiffness z-score (β= -0.196, p = 0.011). RHI positively correlated with visuospatial ability (β= 0.195, p = 0.013) and executive function (β= 0.151, p = 0.045). CONCLUSION: The results support a link between systemic vascular health and neurocognitive function in older Asian adults. Subclinical noninvasive measures of arterial stiffness and reactivity may identify individuals vulnerable to cognitive impairment.
Keywords: Aged; Blood Flow Velocity; Blood Pressure; Cardiovascular Diseases; Carotid Intima-Media Thickness; Cognitive Aging; Female; Humans; Longitudinal Studies; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Singapore; Vascular Stiffness

Volumetric and shape analysis of the thalamus and striatum in amnestic mild cognitive impairment. - Leh, Sandra E; Kälin, Andrea M; Schroeder, Clemens; Park, Min Tae M; Chakravarty, M Mallar; Freund, Patrick; Gietl, Anton F; Riese, Florian; Kollias, Spyros; Hock, Christoph; Michels, Lars (J Alzheimers Dis, 2016)
Alterations in brain structures, including progressive neurodegeneration, are a hallmark in patients with Alzheimer's disease (AD). However, pathological mechanisms, such as the accumulation of amyloid and the proliferation of tau, are thought to begin years, even decades, before the initial clinical manifestations of AD. In this study, we compare the brain anatomy of amnestic mild cognitive impairment patients (aMCI, n = 16) to healthy subjects (CS, n = 22) using cortical thickness, subcortical volume, and shape analysis, which we believe to be complimentary to volumetric measures. We were able to replicate "classical" cortical thickness alterations in aMCI in the hippocampus, amygdala, putamen, insula, and inferior temporal regions. Additionally, aMCI showed significant thalamic and striatal shape differences. We observed higher global amyloid deposition in aMCI, a significant correlation between striatal displacement and global amyloid, and an inverse correlation between executive function and right-hemispheric thalamic displacement. In contrast, no volumetric differences were detected in thalamic, striatal, and hippocampal regions. Our results provide new evidence for early subcortical neuroanatomical changes in patients with aMCI, which are linked to cognitive abilities and amyloid deposition. Hence, shape analysis may aid in the identification of structural biomarkers for identifying individuals at highest risk of conversion to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Corpus Striatum; Female; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography; Thalamus

What are the Most Frequently Impaired Markers of Neurodegeneration in ADNI Subjects? - Andriuta, Daniela; Moullart, Véronique; Schraen, Susanna; Devendeville, Agnes; Meyer, Marc-Etienne; Godefroy, Olivier (J Alzheimers Dis, 2016)
The aim of this study was to examine the relationship between cerebrospinal fluid (CSF) levels of biomarkers for Alzheimer's disease (AD) (Aβ1-42, t-tau, and p-tau) and 18Fluorodeoxyglucose positron emission tomography (FDG-PET) hypometabolism in subjects from the Alzheimer's Disease Neuroimaging Initiative, and specifically to determine which index of neurodegeneration was most frequently affected. The secondary objective was to determine the most frequently hypometabolic region in patients with a CSF AD signature (abnormal Aβ1-42 and abnormal p-tau). We included the 372 subjects (85 normal subjects, 212 patients with mild cognitive impairment, and 75 patients with AD) with a CSF biomarker dosage (Aβ1-42, t-tau, and p-tau) and brain FDG-PET. The relationship between FDG-PET metabolism (in five regions of interest (ROI) known to be damaged in AD) and CSF t-tau and p-tau levels was studied as a function of CSF Aβ1-42 status. FDG-PET hypometabolism and CSF t-tau and p-tau levels were correlated only in patients with an abnormal CSF Aβ1-42 level (t-tau: R2 = 0.044, p = 0.001; p-tau: R2 = 0.02, p = 0.03). In the latter patients, CSF p-tau was the most frequently (p = 0.0001) abnormal neurodegeneration marker (p-tau: 92.8%; FDG-PET: 56.5%; CSF t-tau: 59.1%). Within the five ROI of FDG PET, the angular gyrus metabolism (R2 = 0.149; p = 0.0001) was selected as the most tightly associated with CSF AD signature. The relation between CSF markers of neurodegeneration (p-tau and t-tau) and brain hypometabolism (in FDG-PET) is conditioned by presence of amyloid abnormality. This finding supports the current physiopathological model of AD. P-tau is the most frequently impaired biomarker. Using FDG PET angular gyrus hypometabolism is the most sensitive to CSF-biomarker-defined AD.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Brain; Cognitive Dysfunction; Databases, Factual; Female; Fluorodeoxyglucose F18; Humans; Male; Peptide Fragments; Phosphorylation; Positron-Emission Tomography; Radiopharmaceuticals; tau Proteins

White Matter Abnormalities Track Disease Progression in PSEN1 Autosomal Dominant Alzheimer's Disease. - Sánchez-Valle, Raquel; Monté, Gemma C; Sala-Llonch, Roser; Bosch, Beatriz; Fortea, Juan; Lladó, Albert; Antonell, Anna; Balasa, Mircea; Bargalló, Nuria; Molinuevo, José Luis (J Alzheimers Dis, 2016)
PSEN1 mutations are the most frequent cause of autosomal dominant Alzheimer's disease (ADAD), and show nearly full penetrance. There is presently increasing interest in the study of biomarkers that track disease progression in order to test therapeutic interventions in ADAD. We used white mater (WM) volumetric characteristics and diffusion tensor imaging (DTI) metrics to investigate correlations with the normalized time to expected symptoms onset (relative age ratio) and group differences in a cohort of 36 subjects from PSEN1 ADAD families: 22 mutation carriers, 10 symptomatic (SMC) and 12 asymptomatic (AMC), and 14 non-carriers (NC). Subjects underwent a 3T MRI. WM morphometric data and DTI metrics were analyzed. We found that PSEN1 MC showed significant negative correlation between fractional anisotropy (FA) and the relative age ratio in the genus and body of corpus callosum and corona radiate (p <  0.05 Family-wise error correction (FWE) at cluster level) and positive correlation with mean diffusivity (MD), axial diffusivity (AxD), and radial diffusivity (RD) in the splenium of corpus callosum. SMC presented WM volume loss, reduced FA and increased MD, AxD, and RD in the anterior and posterior corona radiate, corpus callosum (p <  0.05 FWE) compared with NC. No significant differences were observed between AMC and NC in WM volume or DTI measures. These findings suggest that the integrity of the WM deteriorates linearly in PSEN1 ADAD from the early phases of the disease; thus DTI metrics might be useful to monitor the disease progression. However, the lack of significant alterations at the preclinical stages suggests that these indexes might not be good candidates for early markers of the disease.
Keywords: Adult; Aging; Alzheimer Disease; Brain; Cohort Studies; Diffusion Tensor Imaging; Disease Progression; Family; Female; Heterozygote; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Mutation; Neuropsychological Tests; Organ Size; Presenilin-1; White Matter

White Matter and Hippocampal Volume Predict the Risk of Dementia in Patients with Cerebral Small Vessel Disease: The RUN DMC Study. - van Uden, Ingeborg W M; van der Holst, Helena M; Tuladhar, Anil M; van Norden, Anouk G W; de Laat, Karlijn F; Rutten-Jacobs, Loes C A; Norris, David G; Claassen, Jurgen A H R; van Dijk, Ewoud J; Kessels, Roy P C; de Leeuw, Frank-Erik (J Alzheimers Dis, 2016)
BACKGROUND: The relationship between cerebral small vessel disease (SVD) and dementia has been studied without considering white matter (WM) volume, the microstructural integrity of the WM surrounding the SVD, and grey matter (GM). OBJECTIVE: We prospectively investigated the relationship between these structures and the risk of dementia, and formed a prediction model to investigate which characteristics (macro- or microstructural) explained most of the variance. METHODS: The RUN DMC study is a prospective cohort study among 503 non-demented participants with an age between 50 and 85 years at baseline, with baseline assessment in 2006 and follow-up assessment in 2012. Two were lost to follow-up (yielding a 99.6% response-rate). Cox regression analysis was used, to calculate hazard ratios for dementia, of baseline MRI characteristics. Tract-Based Spatial Statistics (TBSS) analysis was used to assess the added value of microstructural integrity of the WM. RESULTS: Mean age at baseline was 65.6 years (SD 8.8) and 56.8% was male. 43 participants developed dementia (8.6%), resulting in a 5.5-year cumulative risk of 11.1% (95% CI 7.7-14.6). Low WM and hippocampal volume are significant predictors for dementia. WM, WM hyperintensities, and hippocampal volume explained most of the variance. TBSS analyses showed no additional value of diffusion parameters. CONCLUSIONS: WM and hippocampal volume were the main predictors for the development of incident dementia at 5-year follow-up in elderly with SVD. There was no additional diagnostic value of the diffusion tensor imaging parameters on top of the macrostructural characteristics.
Keywords: Aged; Cerebral Small Vessel Diseases; Cohort Studies; Dementia; Diffusion Tensor Imaging; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Statistics, Nonparametric; White Matter

White Matter Changes are Associated with Ventricular Expansion in Aging, Mild Cognitive Impairment, and Alzheimer's Disease. - Coutu, Jean-Philippe; Goldblatt, Alison; Rosas, H Diana; Salat, David H (J Alzheimers Dis, 2016)
White matter lesions are highly prevalent in individuals with Alzheimer's disease (AD). Although these lesions are presumed to be of vascular origin and linked to small vessel disease in older adults, little information exists about their relationship to markers of classical AD neurodegeneration. Thus, we examined the link between these white matter changes (WMC) segmented on T1-weighted MRI and imaging markers presumed to be altered due to primary AD neurodegenerative processes. Tissue microstructure of WMC was quantified using diffusion tensor imaging and the relationship of WMC properties and volume to neuroimaging markers was examined in 219 cognitively healthy older adults and individuals with mild cognitive impairment and AD using data from the Alzheimer's Disease Neuroimaging Initiative. No significant group differences in WMC properties were found. However, there were strong associations between diffusivity of WMC and ventricular volume, volume of WMC and total WM volume. In comparison, group differences in parahippocampal white matter microstructure were found for all diffusion metrics and were largely explained by hippocampal volume. Factor analysis on neuroimaging markers suggested two independent sets of covarying degenerative changes, with potentially age- and vascular-mediated tissue damage contributing to one factor and classical neurodegenerative changes associated with AD contributing to a second factor. These data demonstrate two potentially distinct classes of degenerative change in AD, with one factor strongly linked to aging, ventricular expansion, and both volume and tissue properties of white matter lesions, while the other factor related to classical patterns of cortical and hippocampal neurodegeneration in AD.
Keywords: Aged; Aging; Alzheimer Disease; Cognitive Dysfunction; Diffusion Tensor Imaging; Factor Analysis, Statistical; Female; Hippocampus; Humans; Imaging, Three-Dimensional; Male; Mental Status Schedule; Neuropsychological Tests; White Matter

δ Scores are Exportable Across Cultural and Linguistic Boundaries. - Royall, Donald R; Palmer, Raymond F; Matsuoka, Teruyuki; Kato, Yuka; Taniguchi, Shogo; Ogawa, Mayu; Fujimoto, Hiroshi; Okamura, Aiko; Shibata, Keisuke; Nakamura, Kaeko; Nakaaki, Shutaro; Koumi, Hiroyuki; et al. (J Alzheimers Dis, 2016)
The latent variable "δ", can accurately diagnose dementia. Its generalizability across populations is unknown. We constructed a δ homolog ("dT2J") in data collected by the Texas Alzheimer's Research and Care Consortium (TARCC). From this, we calculated a composite d-score "d". We then tested d's generalizability across random subsets of TARCC participants and to a convenience sample of elderly Japanese persons with normal cognition (NC), mild cognitive impairment (MCI), and dementia (AD) (n = 176). dT2J was indicated by Instrumental Activities of Daily Living and psychometric measures. Embedded in this battery were the Mini-Mental Status Examination (MMSE) and an executive clock-drawing task (CLOX). Only MMSE and CLOX were available in both TARCC and the Japanese cohort. Therefore, a second composite variable, "T2J", was constructed solely from the factor loadings of CLOX and MMSE on d. The diagnostic accuracy of T2J was estimated in the validation sample, the remainder of the TARCC cohort, and in the Japanese sample. The areas under the receiver operating curve (AUC; ROC) for T2J were compared in each sample, and against d in TARCC. The AUCs for T2J were statistically indiscriminable within TARCC, and in Japanese persons. In Japanese persons, AUCs for T2J were 0.97 for the discrimination between AD versus NC, 0.86 for AD versus MCI, and 0.79 for NC versus MCI. The AUCs for T2J in Japanese persons were higher than any individual psychometric measure in that sample. Valid d-score composites can be abstracted from a subset of δ's indicators. Moreover, those composites are exportable across cultural and linguistic boundaries.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Cognitive Dysfunction; Cohort Studies; Culture; Executive Function; Female; Humans; Linguistics; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Psychometrics; Reproducibility of Results; ROC Curve; Texas

C9orf72 nucleotide repeat structures initiate molecular cascades of disease. - Haeusler, Aaron R; Donnelly, Christopher J; Periz, Goran; Simko, Eric A J; Shaw, Patrick G; Kim, Min-Sik; Maragakis, Nicholas J; Troncoso, Juan C; Pandey, Akhilesh; Sattler, Rita; Rothstein, Jeffrey D; Wang, Jiou (Nature, 2014)
A hexanucleotide repeat expansion (HRE), (GGGGCC)n, in C9orf72 is the most common genetic cause of the neurodegenerative diseases amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Here we identify a molecular mechanism by which structural polymorphism of the HRE leads to ALS/FTD pathology and defects. The HRE forms DNA and RNA G-quadruplexes with distinct structures and promotes RNA•DNA hybrids (R-loops). The structural polymorphism causes a repeat-length-dependent accumulation of transcripts aborted in the HRE region. These transcribed repeats bind to ribonucleoproteins in a conformation-dependent manner. Specifically, nucleolin, an essential nucleolar protein, preferentially binds the HRE G-quadruplex, and patient cells show evidence of nucleolar stress. Our results demonstrate that distinct C9orf72 HRE structural polymorphism at both DNA and RNA levels initiates molecular cascades leading to ALS/FTD pathologies, and provide the basis for a mechanistic model for repeat-associated neurodegenerative diseases.
Keywords: Amyotrophic Lateral Sclerosis; B-Lymphocytes; Base Sequence; Cell Nucleolus; DNA; DNA Repeat Expansion; Frontotemporal Dementia; G-Quadruplexes; HEK293 Cells; Humans; Models, Molecular; Neurons; Open Reading Frames; Phosphoproteins; Ribonucleoproteins; RNA; RNA-Binding Proteins; Stress, Physiological; Transcription, Genetic

Phase 3 trials of solanezumab for mild-to-moderate Alzheimer's disease. - Doody, Rachelle S; Thomas, Ronald G; Farlow, Martin; Iwatsubo, Takeshi; Vellas, Bruno; Joffe, Steven; Kieburtz, Karl; Raman, Rema; Sun, Xiaoying; Aisen, Paul S; Siemers, Eric; Liu-Seifert, Hong; et al. (N Engl J Med, 2014)
BACKGROUND: Alzheimer's disease is characterized by amyloid-beta plaques, neurofibrillary tangles, gliosis, and neuronal loss. Solanezumab, a humanized monoclonal antibody, preferentially binds soluble forms of amyloid and in preclinical studies promoted its clearance from the brain. METHODS: In two phase 3, double-blind trials (EXPEDITION 1 and EXPEDITION 2), we randomly assigned 1012 and 1040 patients, respectively, with mild-to-moderate Alzheimer's disease to receive placebo or solanezumab (administered intravenously at a dose of 400 mg) every 4 weeks for 18 months. The primary outcomes were the changes from baseline to week 80 in scores on the 11-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog11; range, 0 to 70, with higher scores indicating greater cognitive impairment) and the Alzheimer's Disease Cooperative Study-Activities of Daily Living scale (ADCS-ADL; range, 0 to 78, with lower scores indicating worse functioning). After analysis of data from EXPEDITION 1, the primary outcome for EXPEDITION 2 was revised to the change in scores on the 14-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog14; range, 0 to 90, with higher scores indicating greater impairment), in patients with mild Alzheimer's disease. RESULTS: Neither study showed significant improvement in the primary outcomes. The modeled difference between groups (solanezumab group minus placebo group) in the change from baseline was -0.8 points for the ADAS-cog11 score (95% confidence interval [CI], -2.1 to 0.5; P=0.24) and -0.4 points for the ADCS-ADL score (95% CI, -2.3 to 1.4; P=0.64) in EXPEDITION 1 and -1.3 points (95% CI, -2.5 to 0.3; P=0.06) and 1.6 points (95% CI, -0.2 to 3.3; P=0.08), respectively, in EXPEDITION 2. Between-group differences in the changes in the ADAS-cog14 score were -1.7 points in patients with mild Alzheimer's disease (95% CI, -3.5 to 0.1; P=0.06) and -1.5 in patients with moderate Alzheimer's disease (95% CI, -4.1 to 1.1; P=0.26). In the combined safety data set, the incidence of amyloid-related imaging abnormalities with edema or hemorrhage was 0.9% with solanezumab and 0.4% with placebo for edema (P=0.27) and 4.9% and 5.6%, respectively, for hemorrhage (P=0.49). CONCLUSIONS: Solanezumab, a humanized monoclonal antibody that binds amyloid, failed to improve cognition or functional ability. (Funded by Eli Lilly; EXPEDITION 1 and 2 ClinicalTrials.gov numbers, NCT00905372 and NCT00904683.).
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Antibodies, Monoclonal, Humanized; Apolipoproteins E; Biomarkers; Cognition; Double-Blind Method; Female; Humans; Intention to Treat Analysis; Male; Neuropsychological Tests; Severity of Illness Index; tau Proteins; Treatment Failure

Plasma phospholipids identify antecedent memory impairment in older adults. - Mapstone, Mark; Cheema, Amrita K; Fiandaca, Massimo S; Zhong, Xiaogang; Mhyre, Timothy R; MacArthur, Linda H; Hall, William J; Fisher, Susan G; Peterson, Derick R; Haley, James M; Nazar, Michael D; Rich, Steven A; et al. (Nat Med, 2014)
Alzheimer's disease causes a progressive dementia that currently affects over 35 million individuals worldwide and is expected to affect 115 million by 2050 (ref. 1). There are no cures or disease-modifying therapies, and this may be due to our inability to detect the disease before it has progressed to produce evident memory loss and functional decline. Biomarkers of preclinical disease will be critical to the development of disease-modifying or even preventative therapies. Unfortunately, current biomarkers for early disease, including cerebrospinal fluid tau and amyloid-β levels, structural and functional magnetic resonance imaging and the recent use of brain amyloid imaging or inflammaging, are limited because they are either invasive, time-consuming or expensive. Blood-based biomarkers may be a more attractive option, but none can currently detect preclinical Alzheimer's disease with the required sensitivity and specificity. Herein, we describe our lipidomic approach to detecting preclinical Alzheimer's disease in a group of cognitively normal older adults. We discovered and validated a set of ten lipids from peripheral blood that predicted phenoconversion to either amnestic mild cognitive impairment or Alzheimer's disease within a 2-3 year timeframe with over 90% accuracy. This biomarker panel, reflecting cell membrane integrity, may be sensitive to early neurodegeneration of preclinical Alzheimer's disease.
Keywords: Aged; Alzheimer Disease; Asparagine; Biomarkers; Carnitine; Cohort Studies; Dipeptides; Female; Humans; Longitudinal Studies; Lysophosphatidylcholines; Malates; Male; Memory Disorders; Metabolome; Mild Cognitive Impairment; Neuropsychological Tests; Phosphatidylcholines; Phosphatidylinositols; Phospholipids; Proline; Prospective Studies; Sensitivity and Specificity; Sphingomyelins; Ursodeoxycholic Acid

REST and stress resistance in ageing and Alzheimer's disease. - Lu, Tao; Aron, Liviu; Zullo, Joseph; Pan, Ying; Kim, Haeyoung; Chen, Yiwen; Yang, Tun-Hsiang; Kim, Hyun-Min; Drake, Derek; Liu, X Shirley; Bennett, David A; Colaiácovo, Monica P; et al. (Nature, 2014)
Human neurons are functional over an entire lifetime, yet the mechanisms that preserve function and protect against neurodegeneration during ageing are unknown. Here we show that induction of the repressor element 1-silencing transcription factor (REST; also known as neuron-restrictive silencer factor, NRSF) is a universal feature of normal ageing in human cortical and hippocampal neurons. REST is lost, however, in mild cognitive impairment and Alzheimer's disease. Chromatin immunoprecipitation with deep sequencing and expression analysis show that REST represses genes that promote cell death and Alzheimer's disease pathology, and induces the expression of stress response genes. Moreover, REST potently protects neurons from oxidative stress and amyloid β-protein toxicity, and conditional deletion of REST in the mouse brain leads to age-related neurodegeneration. A functional orthologue of REST, Caenorhabditis elegans SPR-4, also protects against oxidative stress and amyloid β-protein toxicity. During normal ageing, REST is induced in part by cell non-autonomous Wnt signalling. However, in Alzheimer's disease, frontotemporal dementia and dementia with Lewy bodies, REST is lost from the nucleus and appears in autophagosomes together with pathological misfolded proteins. Finally, REST levels during ageing are closely correlated with cognitive preservation and longevity. Thus, the activation state of REST may distinguish neuroprotection from neurodegeneration in the ageing brain.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Amyloid beta-Peptides; Animals; Autophagy; Brain; Caenorhabditis elegans Proteins; Cell Death; Cell Nucleus; Chromatin Immunoprecipitation; Cognition; DNA-Binding Proteins; Down-Regulation; Frontotemporal Dementia; Gene Expression Regulation; Humans; Lewy Body Disease; Longevity; Mice; Mild Cognitive Impairment; Neurons; Neuroprotective Agents; Oxidative Stress; Phagosomes; Repressor Proteins; Transcription Factors; Up-Regulation; Wnt Signaling Pathway; Young Adult

Ten-year effects of the advanced cognitive training for independent and vital elderly cognitive training trial on cognition and everyday functioning in older adults. - Rebok, George W; Ball, Karlene; Guey, Lin T; Jones, Richard N; Kim, Hae-Young; King, Jonathan W; Marsiske, Michael; Morris, John N; Tennstedt, Sharon L; Unverzagt, Frederick W; Willis, Sherry L (J Am Geriatr Soc, 2014)
OBJECTIVES: To determine the effects of cognitive training on cognitive abilities and everyday function over 10 years. DESIGN: Ten-year follow-up of a randomized, controlled single-blind trial (Advanced Cognitive Training for Independent and Vital Elderly (ACTIVE)) with three intervention groups and a no-contact control group. SETTING: Six U.S. cities. PARTICIPANTS: A volunteer sample of 2,832 persons (mean baseline age 73.6; 26% African American) living independently. INTERVENTION: Ten training sessions for memory, reasoning, or speed of processing; four sessions of booster training 11 and 35 months after initial training. MEASUREMENTS: Objectively measured cognitive abilities and self-reported and performance-based measures of everyday function. RESULTS: Participants in each intervention group reported less difficulty with instrumental activities of daily living (IADLs) (memory: effect size = 0.48, 99% confidence interval (CI) = 0.12-0.84; reasoning: effect size = 0.38, 99% CI = 0.02-0.74; speed of processing: effect size = 0.36, 99% CI = 0.01-0.72). At a mean age of 82, approximately 60% of trained participants, versus 50% of controls (P < .05), were at or above their baseline level of self-reported IADL function at 10 years. The reasoning and speed-of-processing interventions maintained their effects on their targeted cognitive abilities at 10 years (reasoning: effect size = 0.23, 99% CI = 0.09-0.38; speed of processing: effect size = 0.66, 99% CI = 0.43-0.88). Memory training effects were no longer maintained for memory performance. Booster training produced additional and durable improvement for the reasoning intervention for reasoning performance (effect size = 0.21, 99% CI = 0.01-0.41) and the speed-of-processing intervention for speed-of-processing performance (effect size = 0.62, 99% CI = 0.31-0.93). CONCLUSION: Each Advanced Cognitive Training for Independent and Vital Elderly cognitive intervention resulted in less decline in self-reported IADL compared with the control group. Reasoning and speed, but not memory, training resulted in improved targeted cognitive abilities for 10 years.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Cognition Disorders; Cognitive Therapy; Female; Follow-Up Studies; Humans; Independent Living; Male; Memory Disorders; Mental Processes; Single-Blind Method; United States

A three-dimensional human neural cell culture model of Alzheimer's disease. - Choi, Se Hoon; Kim, Young Hye; Hebisch, Matthias; Sliwinski, Christopher; Lee, Seungkyu; D'Avanzo, Carla; Chen, Hechao; Hooli, Basavaraj; Asselin, Caroline; Muffat, Julien; Klee, Justin B; Zhang, Can; et al. (Nature, 2014)
Alzheimer's disease is the most common form of dementia, characterized by two pathological hallmarks: amyloid-β plaques and neurofibrillary tangles. The amyloid hypothesis of Alzheimer's disease posits that the excessive accumulation of amyloid-β peptide leads to neurofibrillary tangles composed of aggregated hyperphosphorylated tau. However, to date, no single disease model has serially linked these two pathological events using human neuronal cells. Mouse models with familial Alzheimer's disease (FAD) mutations exhibit amyloid-β-induced synaptic and memory deficits but they do not fully recapitulate other key pathological events of Alzheimer's disease, including distinct neurofibrillary tangle pathology. Human neurons derived from Alzheimer's disease patients have shown elevated levels of toxic amyloid-β species and phosphorylated tau but did not demonstrate amyloid-β plaques or neurofibrillary tangles. Here we report that FAD mutations in β-amyloid precursor protein and presenilin 1 are able to induce robust extracellular deposition of amyloid-β, including amyloid-β plaques, in a human neural stem-cell-derived three-dimensional (3D) culture system. More importantly, the 3D-differentiated neuronal cells expressing FAD mutations exhibited high levels of detergent-resistant, silver-positive aggregates of phosphorylated tau in the soma and neurites, as well as filamentous tau, as detected by immunoelectron microscopy. Inhibition of amyloid-β generation with β- or γ-secretase inhibitors not only decreased amyloid-β pathology, but also attenuated tauopathy. We also found that glycogen synthase kinase 3 (GSK3) regulated amyloid-β-mediated tau phosphorylation. We have successfully recapitulated amyloid-β and tau pathology in a single 3D human neural cell culture system. Our unique strategy for recapitulating Alzheimer's disease pathology in a 3D neural cell culture model should also serve to facilitate the development of more precise human neural cell models of other neurodegenerative disorders.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Cell Culture Techniques; Cell Differentiation; Drug Evaluation, Preclinical; Extracellular Space; Glycogen Synthase Kinase 3; Humans; Microtubule-Associated Proteins; Models, Biological; Neural Stem Cells; Neurites; Phosphorylation; Presenilin-1; Protein Aggregation, Pathological; Reproducibility of Results; tau Proteins

Two phase 3 trials of bapineuzumab in mild-to-moderate Alzheimer's disease. - Salloway, Stephen; Sperling, Reisa; Fox, Nick C; Blennow, Kaj; Klunk, William; Raskind, Murray; Sabbagh, Marwan; Honig, Lawrence S; Porsteinsson, Anton P; Ferris, Steven; Reichert, Marcel; Ketter, Nzeera; et al. (N Engl J Med, 2014)
BACKGROUND: Bapineuzumab, a humanized anti-amyloid-beta monoclonal antibody, is in clinical development for the treatment of Alzheimer's disease. METHODS: We conducted two double-blind, randomized, placebo-controlled, phase 3 trials involving patients with mild-to-moderate Alzheimer's disease--one involving 1121 carriers of the apolipoprotein E (APOE) ε4 allele and the other involving 1331 noncarriers. Bapineuzumab or placebo, with doses varying by study, was administered by intravenous infusion every 13 weeks for 78 weeks. The primary outcome measures were scores on the 11-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog11, with scores ranging from 0 to 70 and higher scores indicating greater impairment) and the Disability Assessment for Dementia (DAD, with scores ranging from 0 to 100 and higher scores indicating less impairment). A total of 1090 carriers and 1114 noncarriers were included in the efficacy analysis. Secondary outcome measures included findings on positron-emission tomographic amyloid imaging with the use of Pittsburgh compound B (PIB-PET) and cerebrospinal fluid phosphorylated tau (phospho-tau) concentrations. RESULTS: There were no significant between-group differences in the primary outcomes. At week 78, the between-group differences in the change from baseline in the ADAS-cog11 and DAD scores (bapineuzumab group minus placebo group) were -0.2 (P=0.80) and -1.2 (P=0.34), respectively, in the carrier study; the corresponding differences in the noncarrier study were -0.3 (P=0.64) and 2.8 (P=0.07) with the 0.5-mg-per-kilogram dose of bapineuzumab and 0.4 (P=0.62) and 0.9 (P=0.55) with the 1.0-mg-per-kilogram dose. The major safety finding was amyloid-related imaging abnormalities with edema among patients receiving bapineuzumab, which increased with bapineuzumab dose and APOE ε4 allele number and which led to discontinuation of the 2.0-mg-per-kilogram dose. Between-group differences were observed with respect to PIB-PET and cerebrospinal fluid phospho-tau concentrations in APOE ε4 allele carriers but not in noncarriers. CONCLUSIONS: Bapineuzumab did not improve clinical outcomes in patients with Alzheimer's disease, despite treatment differences in biomarkers observed in APOE ε4 carriers. (Funded by Janssen Alzheimer Immunotherapy and Pfizer; Bapineuzumab 301 and 302 ClinicalTrials.gov numbers, NCT00575055 and NCT00574132, and EudraCT number, 2009-012748-17.).
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Antibodies, Monoclonal, Humanized; Apolipoproteins E; Biomarkers; Brain; Cognition; Double-Blind Method; Edema; Female; Humans; Intention to Treat Analysis; Male; Middle Aged; Neuropsychological Tests; Phosphorylation; Positron-Emission Tomography; Severity of Illness Index; tau Proteins; Treatment Failure

Young blood reverses age-related impairments in cognitive function and synaptic plasticity in mice. - Villeda, Saul A; Plambeck, Kristopher E; Middeldorp, Jinte; Castellano, Joseph M; Mosher, Kira I; Luo, Jian; Smith, Lucas K; Bieri, Gregor; Lin, Karin; Berdnik, Daniela; Wabl, Rafael; Udeochu, Joe; et al. (Nat Med, 2014)
As human lifespan increases, a greater fraction of the population is suffering from age-related cognitive impairments, making it important to elucidate a means to combat the effects of aging. Here we report that exposure of an aged animal to young blood can counteract and reverse pre-existing effects of brain aging at the molecular, structural, functional and cognitive level. Genome-wide microarray analysis of heterochronic parabionts--in which circulatory systems of young and aged animals are connected--identified synaptic plasticity-related transcriptional changes in the hippocampus of aged mice. Dendritic spine density of mature neurons increased and synaptic plasticity improved in the hippocampus of aged heterochronic parabionts. At the cognitive level, systemic administration of young blood plasma into aged mice improved age-related cognitive impairments in both contextual fear conditioning and spatial learning and memory. Structural and cognitive enhancements elicited by exposure to young blood are mediated, in part, by activation of the cyclic AMP response element binding protein (Creb) in the aged hippocampus. Our data indicate that exposure of aged mice to young blood late in life is capable of rejuvenating synaptic plasticity and improving cognitive function.
Keywords: Age Factors; Aging; Animals; Blood Transfusion; Blotting, Western; Cell Line; Cognition Disorders; Cyclic AMP Response Element-Binding Protein; DNA Primers; Hippocampus; Immunohistochemistry; Mice; Mice, Inbred C57BL; Microarray Analysis; Neuronal Plasticity; Parabiosis; Polymerase Chain Reaction

Alzheimer's disease risk gene CD33 inhibits microglial uptake of amyloid beta. - Griciuc, Ana; Serrano-Pozo, Alberto; Parrado, Antonio R; Lesinski, Andrea N; Asselin, Caroline N; Mullin, Kristina; Hooli, Basavaraj; Choi, Se Hoon; Hyman, Bradley T; Tanzi, Rudolph E (Neuron, 2013)
The transmembrane protein CD33 is a sialic acid-binding immunoglobulin-like lectin that regulates innate immunity but has no known functions in the brain. We have previously shown that the CD33 gene is a risk factor for Alzheimer's disease (AD). Here, we observed increased expression of CD33 in microglial cells in AD brain. The minor allele of the CD33 SNP rs3865444, which confers protection against AD, was associated with reductions in both CD33 expression and insoluble amyloid beta 42 (Aβ42) levels in AD brain. Furthermore, the numbers of CD33-immunoreactive microglia were positively correlated with insoluble Aβ42 levels and plaque burden in AD brain. CD33 inhibited uptake and clearance of Aβ42 in microglial cell cultures. Finally, brain levels of insoluble Aβ42 as well as amyloid plaque burden were markedly reduced in APP(Swe)/PS1(ΔE9)/CD33(-/-) mice. Therefore, CD33 inactivation mitigates Aβ pathology and CD33 inhibition could represent a novel therapy for AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Case-Control Studies; Disease Models, Animal; Genetic Predisposition to Disease; Humans; Matched-Pair Analysis; Mice; Mice, Inbred C57BL; Mice, Knockout; Mice, Transgenic; Microglia; Polymorphism, Single Nucleotide; Reference Values; RNA, Messenger; Sialic Acid Binding Ig-like Lectin 3

Anti-amyloid β autoantibodies in cerebral amyloid angiopathy-related inflammation: implications for amyloid-modifying therapies. - Piazza, Fabrizio; Greenberg, Steven M; Savoiardo, Mario; Gardinetti, Margherita; Chiapparini, Luisa; Raicher, Irina; Nitrini, Ricardo; Sakaguchi, Hideya; Brioschi, Monica; Billo, Giuseppe; Colombo, Antonio; Lanzani, Francesca; et al. (Ann Neurol, 2013)
OBJECTIVE: Cerebral amyloid angiopathy-related inflammation (CAA-ri) is characterized by vasogenic edema and multiple cortical/subcortical microbleeds, sharing several aspects with the recently defined amyloid-related imaging abnormalities (ARIA) reported in Alzheimer's disease (AD) passive immunization therapies. Herein, we investigated the role of anti-amyloid β (Aβ) autoantibodies in the acute and remission phases of CAA-ri. METHODS: We used a novel ultrasensitive technique on patients from a retrospective multicenter case-control study, and evaluated the anti-Aβ autoantibody concentration in the cerebrospinal fluid (CSF) of 10 CAA-ri, 8 CAA, 14 multiple sclerosis, and 25 control subjects. Levels of soluble Aβ40, Aβ42, tau, P-181 tau, and APOE genotype were also investigated. RESULTS: During the acute phase of CAA-ri, anti-Aβ autoantibodies were specifically increased and directly correlated with Aβ mobilization, together with augmented tau and P-181 tau. Following clinical and radiological remission, autoantibodies progressively returned to control levels, and both soluble Aβ and axonal degeneration markers decreased in parallel. INTERPRETATION: Our data support the hypothesis that the pathogenesis of CAA-ri may be mediated by a selective autoimmune reaction against cerebrovascular Aβ, directly related to autoantibody concentration and soluble Aβ. The CSF dosage of anti-Aβ autoantibodies with the technique here described can thus be proposed as a valid alternative tool for the diagnosis of CAA-ri. Moreover, given the similarities between ARIA developing spontaneously and those observed during immunization trials, anti-Aβ autoantibodies can be considered as novel potential biomarkers in future amyloid-modifying therapies for the treatment of AD and CAA.
Keywords: Adult; Aged; Amyloid beta-Peptides; Apolipoproteins E; Autoantibodies; Brain; Case-Control Studies; Cerebral Amyloid Angiopathy; Female; Humans; Inflammation; Male; Middle Aged; Peptide Fragments; Phosphorylation; Retrospective Studies; Steroids; tau Proteins

Meta-analysis of 74,046 individuals identifies 11 new susceptibility loci for Alzheimer's disease. - Lambert, J C; Ibrahim-Verbaas, C A; Harold, D; Naj, A C; Sims, R; Bellenguez, C; DeStafano, A L; Bis, J C; Beecham, G W; Grenier-Boley, B; Russo, G; Thorton-Wells, T A; et al. (Nat Genet, 2013)
Eleven susceptibility loci for late-onset Alzheimer's disease (LOAD) were identified by previous studies; however, a large portion of the genetic risk for this disease remains unexplained. We conducted a large, two-stage meta-analysis of genome-wide association studies (GWAS) in individuals of European ancestry. In stage 1, we used genotyped and imputed data (7,055,881 SNPs) to perform meta-analysis on 4 previously published GWAS data sets consisting of 17,008 Alzheimer's disease cases and 37,154 controls. In stage 2, 11,632 SNPs were genotyped and tested for association in an independent set of 8,572 Alzheimer's disease cases and 11,312 controls. In addition to the APOE locus (encoding apolipoprotein E), 19 loci reached genome-wide significance (P < 5 × 10(-8)) in the combined stage 1 and stage 2 analysis, of which 11 are newly associated with Alzheimer's disease.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cohort Studies; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Modeling Alzheimer's disease with iPSCs reveals stress phenotypes associated with intracellular Aβ and differential drug responsiveness. - Kondo, Takayuki; Asai, Masashi; Tsukita, Kayoko; Kutoku, Yumiko; Ohsawa, Yutaka; Sunada, Yoshihide; Imamura, Keiko; Egawa, Naohiro; Yahata, Naoki; Okita, Keisuke; Takahashi, Kazutoshi; Asaka, Isao; et al. (Cell Stem Cell, 2013)
Oligomeric forms of amyloid-β peptide (Aβ) are thought to play a pivotal role in the pathogenesis of Alzheimer's disease (AD), but the mechanism involved is still unclear. Here, we generated induced pluripotent stem cells (iPSCs) from familial and sporadic AD patients and differentiated them into neural cells. Aβ oligomers accumulated in iPSC-derived neurons and astrocytes in cells from patients with a familial amyloid precursor protein (APP)-E693Δ mutation and sporadic AD, leading to endoplasmic reticulum (ER) and oxidative stress. The accumulated Aβ oligomers were not proteolytically resistant, and docosahexaenoic acid (DHA) treatment alleviated the stress responses in the AD neural cells. Differential manifestation of ER stress and DHA responsiveness may help explain variable clinical results obtained with the use of DHA treatment and suggests that DHA may in fact be effective for a subset of patients. It also illustrates how patient-specific iPSCs can be useful for analyzing AD pathogenesis and evaluating drugs.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Cell Differentiation; Cerebral Cortex; Docosahexaenoic Acids; Humans; Induced Pluripotent Stem Cells; Intracellular Space; Models, Biological; Mutant Proteins; Neurons; Oxidative Stress; Phenotype; Protein Structure, Quaternary

Tracking pathophysiological processes in Alzheimer's disease: an updated hypothetical model of dynamic biomarkers. - Jack, Clifford R; Knopman, David S; Jagust, William J; Petersen, Ronald C; Weiner, Michael W; Aisen, Paul S; Shaw, Leslie M; Vemuri, Prashanthi; Wiste, Heather J; Weigand, Stephen D; Lesnick, Timothy G; Pankratz, Vernon S; et al. (Lancet Neurol, 2013)
In 2010, we put forward a hypothetical model of the major biomarkers of Alzheimer's disease (AD). The model was received with interest because we described the temporal evolution of AD biomarkers in relation to each other and to the onset and progression of clinical symptoms. Since then, evidence has accumulated that supports the major assumptions of this model. Evidence has also appeared that challenges some of our assumptions, which has allowed us to modify our original model. Refinements to our model include indexing of individuals by time rather than clinical symptom severity; incorporation of interindividual variability in cognitive impairment associated with progression of AD pathophysiology; modifications of the specific temporal ordering of some biomarkers; and recognition that the two major proteinopathies underlying AD biomarker changes, amyloid β (Aβ) and tau, might be initiated independently in sporadic AD, in which we hypothesise that an incident Aβ pathophysiology can accelerate antecedent limbic and brainstem tauopathy.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognition Disorders; Humans; Models, Biological; Nonlinear Dynamics; tau Proteins

Cognitive reserve in ageing and Alzheimer's disease. - Stern, Yaakov (Lancet Neurol, 2012)
The concept of cognitive reserve provides an explanation for differences between individuals in susceptibility to age-related brain changes or pathology related to Alzheimer's disease, whereby some people can tolerate more of these changes than others and maintain function. Epidemiological studies suggest that lifelong experiences, including educational and occupational attainment, and leisure activities in later life, can increase this reserve. For example, the risk of developing Alzheimer's disease is reduced in individuals with higher educational or occupational attainment. Reserve can conveniently be divided into two types: brain reserve, which refers to differences in the brain structure that may increase tolerance to pathology, and cognitive reserve, which refers to differences between individuals in how tasks are performed that might enable some people to be more resilient to brain changes than others. Greater understanding of the concept of cognitive reserve could lead to interventions to slow cognitive ageing or reduce the risk of dementia.
Keywords: Aging; Alzheimer Disease; Animals; Cognitive Reserve; Humans

Demonstrated brain insulin resistance in Alzheimer's disease patients is associated with IGF-1 resistance, IRS-1 dysregulation, and cognitive decline. - Talbot, Konrad; Wang, Hoau-Yan; Kazi, Hala; Han, Li-Ying; Bakshi, Kalindi P; Stucky, Andres; Fuino, Robert L; Kawaguchi, Krista R; Samoyedny, Andrew J; Wilson, Robert S; Arvanitakis, Zoe; Schneider, Julie A; et al. (J Clin Invest, 2012)
While a potential causal factor in Alzheimer's disease (AD), brain insulin resistance has not been demonstrated directly in that disorder. We provide such a demonstration here by showing that the hippocampal formation (HF) and, to a lesser degree, the cerebellar cortex in AD cases without diabetes exhibit markedly reduced responses to insulin signaling in the IR→IRS-1→PI3K signaling pathway with greatly reduced responses to IGF-1 in the IGF-1R→IRS-2→PI3K signaling pathway. Reduced insulin responses were maximal at the level of IRS-1 and were consistently associated with basal elevations in IRS-1 phosphorylated at serine 616 (IRS-1 pS⁶¹⁶) and IRS-1 pS⁶³⁶/⁶³⁹. In the HF, these candidate biomarkers of brain insulin resistance increased commonly and progressively from normal cases to mild cognitively impaired cases to AD cases regardless of diabetes or APOE ε4 status. Levels of IRS-1 pS⁶¹⁶ and IRS-1 pS⁶³⁶/⁶³⁹ and their activated kinases correlated positively with those of oligomeric Aβ plaques and were negatively associated with episodic and working memory, even after adjusting for Aβ plaques, neurofibrillary tangles, and APOE ε4. Brain insulin resistance thus appears to be an early and common feature of AD, a phenomenon accompanied by IGF-1 resistance and closely associated with IRS-1 dysfunction potentially triggered by Aβ oligomers and yet promoting cognitive decline independent of classic AD pathology.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Brain; Cerebellar Cortex; Cognition Disorders; Diabetes Complications; Drug Resistance; Female; Glucose; Hippocampus; Humans; Insulin; Insulin Receptor Substrate Proteins; Insulin Resistance; Insulin-Like Growth Factor I; Male; Middle Aged; Phosphorylation; Phosphoserine; Protein Processing, Post-Translational; Recombinant Proteins; Signal Transduction

Exercise Engagement as a Moderator of the Effects of APOE Genotype on Amyloid Deposition. - Head, Denise; Bugg, Julie M; Goate, Alison M; Fagan, Anne M; Mintun, Mark A; Benzinger, Tammie; Holtzman, David M; Morris, John C (Arch Neurol, 2012)
OBJECTIVE: APOE ε4 status has been associated with greater cortical amyloid deposition, whereas exercise has been associated with less in cognitively normal adults. The primary objective here was to examine whether physical exercise moderates the association between APOE genotype and amyloid deposition in cognitively normal adults. DESIGN: APOE genotyping data and answers to a questionnaire on physical exercise engagement over the last decade were obtained in conjunction with cerebrospinal fluid (CSF) samples and amyloid imaging with carbon 11-labeled Pittsburgh Compound B ([(11)C]PiB) positron emission tomography. Participants were classified as either low or high exercisers based on exercise guidelines of the American Heart Association. SETTING: Knight Alzheimer's Disease Research Center at Washington University, St Louis, Missouri. PARTICIPANTS: A total of 201 cognitively normal adults (135 of whom were women) aged 45 to 88 years were recruited from the Knight Alzheimer's Disease Research Center. Samples of CSF were collected from 165 participants. Amyloid imaging was performed for 163 participants. RESULTS: APOE ε4 carriers evidenced higher [(11)C]PiB binding (P<.001) and lower CSF Aβ42 levels (P<.001) than did noncarriers. Our previous findings of higher [(11)C]PiB binding (P=.005) and lower CSF Aβ42 levels (P=.009) in more sedentary individuals were replicated. Most importantly, we observed a novel interaction between APOE status and exercise engagement for [(11)C]PiB binding (P=.008) such that a more sedentary lifestyle was significantly associated with higher [(11)C]PiB binding for ε4 carriers (P=.013) but not for noncarriers (P=.20). All findings remained significant after controlling for age; sex; educational level; body mass index; the presence or history of hypertension, diabetes mellitus, heart problems, or depression; and the interval between assessments. CONCLUSION: Collectively, these results suggest that cognitively normal sedentary APOE ε4-positive individuals may be at augmented risk for cerebral amyloid deposition.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Aniline Compounds; Apolipoprotein E4; Brain; Cognition; Cohort Studies; Exercise; Female; Genetic Association Studies; Genotype; Humans; Male; Middle Aged; Neuropsychological Tests; Peptide Fragments; Positron-Emission Tomography; Regression Analysis; Surveys and Questionnaires; Thiazoles

A mutation in APP protects against Alzheimer's disease and age-related cognitive decline. - Jonsson, Thorlakur; Atwal, Jasvinder K; Steinberg, Stacy; Snaedal, Jon; Jonsson, Palmi V; Bjornsson, Sigurbjorn; Stefansson, Hreinn; Sulem, Patrick; Gudbjartsson, Daniel; Maloney, Janice; Hoyte, Kwame; Gustafson, Amy; et al. (Nature, 2012)
The prevalence of dementia in the Western world in people over the age of 60 has been estimated to be greater than 5%, about two-thirds of which are due to Alzheimer's disease. The age-specific prevalence of Alzheimer's disease nearly doubles every 5 years after age 65, leading to a prevalence of greater than 25% in those over the age of 90 (ref. 3). Here, to search for low-frequency variants in the amyloid-β precursor protein (APP) gene with a significant effect on the risk of Alzheimer's disease, we studied coding variants in APP in a set of whole-genome sequence data from 1,795 Icelanders. We found a coding mutation (A673T) in the APP gene that protects against Alzheimer's disease and cognitive decline in the elderly without Alzheimer's disease. This substitution is adjacent to the aspartyl protease β-site in APP, and results in an approximately 40% reduction in the formation of amyloidogenic peptides in vitro. The strong protective effect of the A673T substitution against Alzheimer's disease provides proof of principle for the hypothesis that reducing the β-cleavage of APP may protect against the disease. Furthermore, as the A673T allele also protects against cognitive decline in the elderly without Alzheimer's disease, the two may be mediated through the same or similar mechanisms.
Keywords: Aging; Alleles; Alzheimer Disease; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Aspartic Acid Endopeptidases; Cognition; Cognition Disorders; Genetic Predisposition to Disease; HEK293 Cells; Humans; Mutation; Plaque, Amyloid

National Institute on Aging-Alzheimer's Association guidelines for the neuropathologic assessment of Alzheimer's disease. - Hyman, Bradley T; Phelps, Creighton H; Beach, Thomas G; Bigio, Eileen H; Cairns, Nigel J; Carrillo, Maria C; Dickson, Dennis W; Duyckaerts, Charles; Frosch, Matthew P; Masliah, Eliezer; Mirra, Suzanne S; Nelson, Peter T; et al. (Alzheimers Dement, 2012)
A consensus panel from the United States and Europe was convened recently to update and revise the 1997 consensus guidelines for the neuropathologic evaluation of Alzheimer's disease (AD) and other diseases of brain that are common in the elderly. The new guidelines recognize the pre-clinical stage of AD, enhance the assessment of AD to include amyloid accumulation as well as neurofibrillary change and neuritic plaques, establish protocols for the neuropathologic assessment of Lewy body disease, vascular brain injury, hippocampal sclerosis, and TDP-43 inclusions, and recommend standard approaches for the workup of cases and their clinico-pathologic correlation.
Keywords: Alzheimer Disease; Brain; Consensus Development Conferences, NIH as Topic; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; Societies, Medical; United States

Neuroinflammation, hyperphosphorylated tau, diffuse amyloid plaques, and down-regulation of the cellular prion protein in air pollution exposed children and young adults. - Calderón-Garcidueñas, Lilian; Kavanaugh, Michael; Block, Michelle; D'Angiulli, Amedeo; Delgado-Chávez, Ricardo; Torres-Jardón, Ricardo; González-Maciel, Angelica; Reynoso-Robles, Rafael; Osnaya, Norma; Villarreal-Calderon, Rodolfo; Guo, Ruixin; Hua, Zhaowei; et al. (J Alzheimers Dis, 2012)
Air pollution exposures have been linked to neuroinflammation and neuropathology. Autopsy samples of the frontal cortex from control (n = 8) and pollution-exposed (n = 35) children and young adults were analyzed by RT-PCR (n = 43) and microarray analysis (n = 12) for gene expression changes in oxidative stress, DNA damage signaling, NFκB signaling, inflammation, and neurodegeneration pathways. The effect of apolipoprotein E (APOE) genotype on the presence of protein aggregates associated with Alzheimer's disease (AD) pathology was also explored. Exposed urbanites displayed differential (>2-fold) regulation of 134 genes. Forty percent exhibited tau hyperphosphorylation with pre-tangle material and 51% had amyloid-β (Aβ) diffuse plaques compared with 0% in controls. APOE4 carriers had greater hyperphosphorylated tau and diffuse Aβ plaques versus E3 carriers (Q = 7.82, p = 0.005). Upregulated gene network clusters included IL1, NFκB, TNF, IFN, and TLRs. A 15-fold frontal down-regulation of the prion-related protein (PrP(C)) was seen in highly exposed subjects. The down-regulation of the PrP(C) is critical given its important roles for neuroprotection, neurodegeneration, and mood disorder states. Elevation of indices of neuroinflammation and oxidative stress, down-regulation of the PrP(C) and AD-associated pathology are present in young megacity residents. The inducible regulation of gene expression suggests they are evolving different mechanisms in an attempt to cope with the constant state of inflammation and oxidative stress related to their environmental exposures. Together, these data support a role for air pollution in CNS damage and its impact upon the developing brain and the potential etiology of AD and mood disorders.
Keywords: Adolescent; Adult; Age Factors; Air Pollution; Child; Child, Preschool; Cohort Studies; Down-Regulation; Encephalitis; Female; Frontal Lobe; Gene Regulatory Networks; Humans; Infant; Male; Mexico; Phosphorylation; Plaque, Amyloid; Prions; tau Proteins; Young Adult

An operational approach to National Institute on Aging-Alzheimer's Association criteria for preclinical Alzheimer disease. - Jack, Clifford R; Knopman, David S; Weigand, Stephen D; Wiste, Heather J; Vemuri, Prashanthi; Lowe, Val; Kantarci, Kejal; Gunter, Jeffrey L; Senjem, Matthew L; Ivnik, Robert J; Roberts, Rosebud O; Rocca, Walter A; et al. (Ann Neurol, 2012)
OBJECTIVE: A workgroup commissioned by the Alzheimer's Association (AA) and the National Institute on Aging (NIA) recently published research criteria for preclinical Alzheimer disease (AD). We performed a preliminary assessment of these guidelines. METHODS: We employed Pittsburgh compound B positron emission tomography (PET) imaging as our biomarker of cerebral amyloidosis, and (18) fluorodeoxyglucose PET imaging and hippocampal volume as biomarkers of neurodegeneration. A group of 42 clinically diagnosed AD subjects was used to create imaging biomarker cutpoints. A group of 450 cognitively normal (CN) subjects from a population-based sample was used to develop cognitive cutpoints and to assess population frequencies of the different preclinical AD stages using different cutpoint criteria. RESULTS: The new criteria subdivide the preclinical phase of AD into stages 1 to 3. To classify our CN subjects, 2 additional categories were needed. Stage 0 denotes subjects with normal AD biomarkers and no evidence of subtle cognitive impairment. Suspected non-AD pathophysiology (SNAP) denotes subjects with normal amyloid PET imaging, but abnormal neurodegeneration biomarker studies. At fixed cutpoints corresponding to 90% sensitivity for diagnosing AD and the 10th percentile of CN cognitive scores, 43% of our sample was classified as stage 0, 16% stage 1, 12 % stage 2, 3% stage 3, and 23% SNAP. INTERPRETATION: This cross-sectional evaluation of the NIA-AA criteria for preclinical AD indicates that the 1-3 staging criteria coupled with stage 0 and SNAP categories classify 97% of CN subjects from a population-based sample, leaving only 3% unclassified. Future longitudinal validation of the criteria will be important.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Aniline Compounds; Biomarkers; Brain; Cognition Disorders; Disease Progression; Female; Fluorodeoxyglucose F18; Humans; Longitudinal Studies; Male; Mental Status Schedule; National Institute on Aging (U.S.); Neuropsychological Tests; Positron-Emission Tomography; Thiazoles; United States

A paravascular pathway facilitates CSF flow through the brain parenchyma and the clearance of interstitial solutes, including amyloid β. - Iliff, Jeffrey J; Wang, Minghuan; Liao, Yonghong; Plogg, Benjamin A; Peng, Weiguo; Gundersen, Georg A; Benveniste, Helene; Vates, G Edward; Deane, Rashid; Goldman, Steven A; Nagelhus, Erlend A; Nedergaard, Maiken (Sci Transl Med, 2012)
Because it lacks a lymphatic circulation, the brain must clear extracellular proteins by an alternative mechanism. The cerebrospinal fluid (CSF) functions as a sink for brain extracellular solutes, but it is not clear how solutes from the brain interstitium move from the parenchyma to the CSF. We demonstrate that a substantial portion of subarachnoid CSF cycles through the brain interstitial space. On the basis of in vivo two-photon imaging of small fluorescent tracers, we showed that CSF enters the parenchyma along paravascular spaces that surround penetrating arteries and that brain interstitial fluid is cleared along paravenous drainage pathways. Animals lacking the water channel aquaporin-4 (AQP4) in astrocytes exhibit slowed CSF influx through this system and a ~70% reduction in interstitial solute clearance, suggesting that the bulk fluid flow between these anatomical influx and efflux routes is supported by astrocytic water transport. Fluorescent-tagged amyloid β, a peptide thought to be pathogenic in Alzheimer's disease, was transported along this route, and deletion of the Aqp4 gene suppressed the clearance of soluble amyloid β, suggesting that this pathway may remove amyloid β from the central nervous system. Clearance through paravenous flow may also regulate extracellular levels of proteins involved with neurodegenerative conditions, its impairment perhaps contributing to the mis-accumulation of soluble proteins.
Keywords: Amyloid beta-Peptides; Animals; Aquaporin 4; Astrocytes; Biological Transport; Brain; Cerebral Ventricles; Cerebrospinal Fluid; Extracellular Fluid; Imaging, Three-Dimensional; Male; Mice; Mice, Inbred C57BL; Microscopy, Fluorescence, Multiphoton; Water

Reduction of hippocampal hyperactivity improves cognition in amnestic mild cognitive impairment. - Bakker, Arnold; Krauss, Gregory L; Albert, Marilyn S; Speck, Caroline L; Jones, Lauren R; Stark, Craig E; Yassa, Michael A; Bassett, Susan S; Shelton, Amy L; Gallagher, Michela (Neuron, 2012)
Elevated hippocampal activation is observed in conditions that confer risk for Alzheimer's disease, including amnestic mild cognitive impairment (aMCI). Studies in relevant animal models have indicated that overactivity in selective hippocampal circuits contributes to cognitive impairment. Here, we tested the effect of reducing hippocampal activation in aMCI. Under placebo treatment, hippocampal activation in the dentate gyrus/CA3 was elevated in aMCI patients compared to a healthy control group. By using a low dose of the antiepileptic levetiracetam hippocampal activation in aMCI was reduced to a level that did not differ from the control group. Compared to aMCI memory performance under placebo, performance in the scanning task was significantly improved under drug treatment. Contrary to the view that greater hippocampal activation might serve a beneficial function, these results support the view that increased hippocampal activation in aMCI is a dysfunctional condition and that targeting excess hippocampal activity has therapeutic potential.
Keywords: Aged; Aged, 80 and over; Amnesia; Brain Mapping; Case-Control Studies; Choice Behavior; Double-Blind Method; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Middle Aged; Mild Cognitive Impairment; Neuropsychological Tests; Nootropic Agents; Oxygen; Photic Stimulation; Piracetam; Statistics as Topic

Anti-aβ therapeutics in Alzheimer's disease: the need for a paradigm shift. - Golde, Todd E; Schneider, Lon S; Koo, Edward H (Neuron, 2011)
Most current Alzheimer's disease (AD) therapies in advanced phases of development target amyloid β-peptide (Aβ) production, aggregation, or accumulation. Translational models suggest that anti-Aβ therapies may be highly effective if tested as agents to prevent or delay development of the disease or as therapies for asymptomatic patients with very early signs of AD pathology. However, anti-Aβ therapeutics are currently being tested in symptomatic patients where they are likely to be much less effective or ineffective. The lack of alignment between human clinical studies and preclinical studies, together with predictions about optimal trial design based on our understanding of the initiating role of Aβ aggregates in AD, has created a treatment versus prevention dilemma. In this perspective, we discuss why it is imperative to resolve this dilemma and suggest ways for moving forward in the hopes of enhancing the development of truly effective AD therapeutics.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Biomarkers; Clinical Trials as Topic; Disease Progression; Health Services Needs and Demand; Humans; Translational Medical Research

Caspase signalling controls microglia activation and neurotoxicity. - Burguillos, Miguel A; Deierborg, Tomas; Kavanagh, Edel; Persson, Annette; Hajji, Nabil; Garcia-Quintanilla, Albert; Cano, Josefina; Brundin, Patrik; Englund, Elisabet; Venero, Jose L; Joseph, Bertrand (Nature, 2011)
Activation of microglia and inflammation-mediated neurotoxicity are suggested to play a decisive role in the pathogenesis of several neurodegenerative disorders. Activated microglia release pro-inflammatory factors that may be neurotoxic. Here we show that the orderly activation of caspase-8 and caspase-3/7, known executioners of apoptotic cell death, regulate microglia activation through a protein kinase C (PKC)-δ-dependent pathway. We find that stimulation of microglia with various inflammogens activates caspase-8 and caspase-3/7 in microglia without triggering cell death in vitro and in vivo. Knockdown or chemical inhibition of each of these caspases hindered microglia activation and consequently reduced neurotoxicity. We observe that these caspases are activated in microglia in the ventral mesencephalon of Parkinson's disease (PD) and the frontal cortex of individuals with Alzheimer's disease (AD). Taken together, we show that caspase-8 and caspase-3/7 are involved in regulating microglia activation. We conclude that inhibition of these caspases could be neuroprotective by targeting the microglia rather than the neurons themselves.
Keywords: Alzheimer Disease; Animals; Caspase 3; Caspase 7; Caspase 8; Caspase Inhibitors; Caspases; Cell Death; Cells, Cultured; Dopamine; Enzyme Activation; Frontal Lobe; Gene Knockdown Techniques; Humans; Lipopolysaccharides; Mice; Microglia; Neostriatum; Neurotoxicity Syndromes; Parkinson Disease; Protein Kinase C-delta; Rats; Signal Transduction; Substantia Nigra; Toll-Like Receptor 4

The diagnosis of mild cognitive impairment due to Alzheimer's disease: recommendations from the National Institute on Aging-Alzheimer's Association workgroups on diagnostic guidelines for Alzheimer's disease. - Albert, Marilyn S; DeKosky, Steven T; Dickson, Dennis; Dubois, Bruno; Feldman, Howard H; Fox, Nick C; Gamst, Anthony; Holtzman, David M; Jagust, William J; Petersen, Ronald C; Snyder, Peter J; Carrillo, Maria C; et al. (Alzheimers Dement, 2011)
The National Institute on Aging and the Alzheimer's Association charged a workgroup with the task of developing criteria for the symptomatic predementia phase of Alzheimer's disease (AD), referred to in this article as mild cognitive impairment due to AD. The workgroup developed the following two sets of criteria: (1) core clinical criteria that could be used by healthcare providers without access to advanced imaging techniques or cerebrospinal fluid analysis, and (2) research criteria that could be used in clinical research settings, including clinical trials. The second set of criteria incorporate the use of biomarkers based on imaging and cerebrospinal fluid measures. The final set of criteria for mild cognitive impairment due to AD has four levels of certainty, depending on the presence and nature of the biomarker findings. Considerable work is needed to validate the criteria that use biomarkers and to standardize biomarker analysis for use in community settings.
Keywords: Alzheimer Disease; Biomarkers; Cognition Disorders; Diagnosis, Differential; Diagnostic Imaging; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; Societies, Medical; United States

Directed conversion of Alzheimer's disease patient skin fibroblasts into functional neurons. - Qiang, Liang; Fujita, Ryousuke; Yamashita, Toru; Angulo, Sergio; Rhinn, Herve; Rhee, David; Doege, Claudia; Chau, Lily; Aubry, Laetitia; Vanti, William B; Moreno, Herman; Abeliovich, Asa (Cell, 2011)
Directed conversion of mature human cells, as from fibroblasts to neurons, is of potential clinical utility for neurological disease modeling as well as cell therapeutics. Here, we describe the efficient generation of human-induced neuronal (hiN) cells from adult skin fibroblasts of unaffected individuals and Alzheimer's patients, using virally transduced transcription regulators and extrinsic support factors. hiN cells from unaffected individuals display morphological, electrophysiological, and gene expression profiles that typify glutamatergic forebrain neurons and are competent to integrate functionally into the rodent CNS. hiN cells from familial Alzheimer disease (FAD) patients with presenilin-1 or -2 mutations exhibit altered processing and localization of amyloid precursor protein (APP) and increased production of Aβ, relative to the source patient fibroblasts or hiN cells from unaffected individuals. Together, our findings demonstrate directed conversion of human fibroblasts to a neuronal phenotype and reveal cell type-selective pathology in hiN cells derived from FAD patients.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Cell Transdifferentiation; Cells, Cultured; Fibroblasts; Humans; Neurons; Presenilin-1; Presenilin-2; Regenerative Medicine; Skin

Disrupted energy metabolism and neuronal circuit dysfunction in cognitive impairment and Alzheimer's disease. - Kapogiannis, Dimitrios; Mattson, Mark P (Lancet Neurol, 2011)
Epidemiological, neuropathological, and functional neuroimaging evidence implicates global and regional disruptions in brain metabolism and energetics in the pathogenesis of cognitive impairment. Nerve cell microcircuits are modified by excitatory and inhibitory synaptic activity and neurotrophic factors. Ageing and Alzheimer's disease cause perturbations in cellular energy metabolism, level of excitation or inhibition, and neurotrophic factor release, which overwhelm compensatory mechanisms and result in dysfunction of neuronal microcircuits and brain networks. A prolonged positive energy balance impairs the ability of neurons to adapt to oxidative and metabolic stress. Results from experimental studies in animals show how disruptions caused by chronic positive energy balance, such as diabetes, lead to accelerated cognitive ageing and Alzheimer's disease. Therapeutic interventions to allay cognitive dysfunction that target energy metabolism and adaptive stress responses (such as neurotrophin signalling) have been effective in animal models and in preliminary studies in humans.
Keywords: Alzheimer Disease; Animals; Brain; Cognition Disorders; Energy Metabolism; Humans; Nerve Net

Neuronal activity regulates the regional vulnerability to amyloid-β deposition. - Bero, Adam W; Yan, Ping; Roh, Jee Hoon; Cirrito, John R; Stewart, Floy R; Raichle, Marcus E; Lee, Jin-Moo; Holtzman, David M (Nat Neurosci, 2011)
Amyloid-β (Aβ) plaque deposition in specific brain regions is a pathological hallmark of Alzheimer's disease. However, the mechanism underlying the regional vulnerability to Aβ deposition in Alzheimer's disease is unknown. Herein, we provide evidence that endogenous neuronal activity regulates the regional concentration of interstitial fluid (ISF) Aβ, which drives local Aβ aggregation. Using in vivo microdialysis, we show that ISF Aβ concentrations in several brain regions of APP transgenic mice before plaque deposition were commensurate with the degree of subsequent plaque deposition and with the concentration of lactate, a marker of neuronal activity. Furthermore, unilateral vibrissal stimulation increased ISF Aβ, and unilateral vibrissal deprivation decreased ISF Aβ and lactate, in contralateral barrel cortex. Long-term unilateral vibrissal deprivation decreased amyloid plaque formation and growth. Our results suggest a mechanism to account for the vulnerability of specific brain regions to Aβ deposition in Alzheimer's disease.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Cerebral Cortex; Disease Models, Animal; Extracellular Fluid; Female; Lactic Acid; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Microdialysis; Neurons; Plaque, Amyloid; Sensory Deprivation; Somatosensory Cortex

Neuronal basis of age-related working memory decline. - Wang, Min; Gamo, Nao J; Yang, Yang; Jin, Lu E; Wang, Xiao-Jing; Laubach, Mark; Mazer, James A; Lee, Daeyeol; Arnsten, Amy F T (Nature, 2011)
Many of the cognitive deficits of normal ageing (forgetfulness, distractibility, inflexibility and impaired executive functions) involve prefrontal cortex (PFC) dysfunction. The PFC guides behaviour and thought using working memory, which are essential functions in the information age. Many PFC neurons hold information in working memory through excitatory networks that can maintain persistent neuronal firing in the absence of external stimulation. This fragile process is highly dependent on the neurochemical environment. For example, elevated cyclic-AMP signalling reduces persistent firing by opening HCN and KCNQ potassium channels. It is not known if molecular changes associated with normal ageing alter the physiological properties of PFC neurons during working memory, as there have been no in vivo recordings, to our knowledge, from PFC neurons of aged monkeys. Here we characterize the first recordings of this kind, revealing a marked loss of PFC persistent firing with advancing age that can be rescued by restoring an optimal neurochemical environment. Recordings showed an age-related decline in the firing rate of DELAY neurons, whereas the firing of CUE neurons remained unchanged with age. The memory-related firing of aged DELAY neurons was partially restored to more youthful levels by inhibiting cAMP signalling, or by blocking HCN or KCNQ channels. These findings reveal the cellular basis of age-related cognitive decline in dorsolateral PFC, and demonstrate that physiological integrity can be rescued by addressing the molecular needs of PFC circuits.
Keywords: Action Potentials; Adrenergic alpha-2 Receptor Agonists; Aging; Animals; Biomedical Enhancement; Cues; Cyclic AMP; Cyclic Nucleotide-Gated Cation Channels; Guanfacine; Humans; Hyperpolarization-Activated Cyclic Nucleotide-Gated Channels; KCNQ Potassium Channels; Macaca mulatta; Male; Memory, Short-Term; Models, Neurological; Neural Pathways; Potassium Channel Blockers; Potassium Channels; Prefrontal Cortex; Receptors, Adrenergic, alpha-2; Signal Transduction; Time Factors

Report of the task force on designing clinical trials in early (predementia) AD. - Aisen, P S; Andrieu, S; Sampaio, C; Carrillo, M; Khachaturian, Z S; Dubois, B; Feldman, H H; Petersen, R C; Siemers, E; Doody, R S; Hendrix, S B; Grundman, M; et al. (Neurology, 2011)
BACKGROUND: A large number of promising candidate disease-modifying treatments for Alzheimer disease (AD) continue to advance into phase II and phase III testing. However, most completed trials have failed to demonstrate efficacy, and there is growing concern that methodologic difficulties may contribute to these clinical trial failures. The optimal time to intervene with such treatments is probably in the years prior to the onset of dementia, before the neuropathology has progressed to the advanced stage corresponding to clinical dementia. METHOD: An international task force of individuals from academia, industry, nonprofit foundations, and regulatory agencies was convened to discuss optimal trial design in early (predementia) AD. RESULTS: General consensus was reached on key principles involving the scope of the AD diagnosis, the selection of subjects for trials, outcome measures, and analytical methods. CONCLUSION: A consensus has been achieved in support of the testing of candidate treatments in the early (predementia) AD population.
Keywords: Advisory Committees; Alzheimer Disease; Amyloidogenic Proteins; Biomarkers; Clinical Trials as Topic; Cognition; Consensus; Disease Progression; Drug Industry; Early Diagnosis; Europe; Humans; Indans; International Cooperation; Nootropic Agents; Outcome Assessment (Health Care); Patient Selection; Piperidines; Positron-Emission Tomography; Research Design; Treatment Outcome; United States; United States Food and Drug Administration; Vitamin E

Soluble amyloid beta-protein dimers isolated from Alzheimer cortex directly induce Tau hyperphosphorylation and neuritic degeneration. - Jin, Ming; Shepardson, Nina; Yang, Ting; Chen, Gang; Walsh, Dominic; Selkoe, Dennis J (Proc Natl Acad Sci U S A, 2011)
Alzheimer disease is a major cause of cognitive failure, and a pathogenically related but more subtle process accounts for many cases of mild memory symptoms in older humans. Insoluble fibrillar plaques of amyloid β-proteins (Aβ) and neurofibrillary deposits of hyperphosphorylated tau proteins are the diagnostic lesions of AD, but their temporal mechanistic relationship has long been debated. The recent recognition that small, diffusible oligomers may be the principal bioactive form of Aβ raises the key question of whether these are sufficient to initiate cytoskeletal change and neurite degeneration. A few studies have examined the effects of oligomers of synthetic Aβ peptides of one defined length at supraphysiological concentrations, but the existence of such assemblies in the AD brain is not established. Here, we isolated Aβ dimers, the most abundant form of soluble oligomer detectable in the human brain, from the cortices of typical AD subjects and found that at subnanomolar concentrations, they first induced hyperphosphorylation of tau at AD-relevant epitopes in hippocampal neurons and then disrupted the microtubule cytoskeleton and caused neuritic degeneration, all in the absence of amyloid fibrils. Application of pure, synthetic dimers confirmed the effects of the natural AD dimers, although the former were far less potent. Knocking down endogenous tau fully prevented the neuritic changes, whereas overexpressing human tau accelerated them. Coadministering Aβ N-terminal antibodies neutralized the cytoskeletal disruption. We conclude that natural dimers isolated from the AD brain are sufficient to potently induce AD-type tau phosphorylation and then neuritic dystrophy, but passive immunotherapy mitigates this.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Blotting, Western; Chromatography, Gel; Dimerization; Genetic Vectors; Hippocampus; Humans; Immunohistochemistry; Immunoprecipitation; In Situ Nick-End Labeling; Lentivirus; Microscopy, Confocal; Microtubules; Neurites; Phosphorylation; Rats; Rats, Sprague-Dawley; tau Proteins

Stages of the pathologic process in Alzheimer disease: age categories from 1 to 100 years. - Braak, Heiko; Thal, Dietmar R; Ghebremedhin, Estifanos; Del Tredici, Kelly (J Neuropathol Exp Neurol, 2011)
Two thousand three hundred and thirty two nonselected brains from 1- to 100-year-old individuals were examined using immunocytochemistry (AT8) and Gallyas silver staining for abnormal tau; immunocytochemistry (4G8) and Campbell-Switzer staining were used for the detection ofβ-amyloid. A total of 342 cases was negative in the Gallyas stain but when restaged for AT8 only 10 were immunonegative. Fifty-eight cases had subcortical tau predominantly in the locus coeruleus, but there was no abnormal cortical tau (subcortical Stages a-c). Cortical involvement (abnormal tau in neurites) was identified first in the transentorhinal region (Stage 1a, 38 cases). Transentorhinal pyramidal cells displayed pretangle material (Stage 1b, 236 cases). Pretangles gradually became argyrophilic neurofibrillary tangles (NFTs) that progressed in parallel with NFT Stages I to VI. Pretangles restricted to subcortical sites were seen chiefly at younger ages. Of the total cases, 1,031 (44.2%) had β-amyloid plaques. The first plaques occurred in the neocortex after the onset of tauopathy in the brainstem. Plaques generally developed in the 40s in 4% of all cases, culminating in their tenth decade (75%). β-amyloid plaques and NFTs were significantly correlated (p < 0.0001). These data suggest that tauopathy associated with sporadic Alzheimer disease may begin earlier than previously thought and possibly in the lower brainstem rather than in the transentorhinal region.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Brain; Child; Child, Preschool; Cohort Studies; Disease Progression; Female; Humans; Infant; Male; Middle Aged; Neurofibrillary Tangles; Neurons; Silver Staining; Statistics, Nonparametric; tau Proteins; Young Adult

Toward defining the preclinical stages of Alzheimer's disease: recommendations from the National Institute on Aging-Alzheimer's Association workgroups on diagnostic guidelines for Alzheimer's disease. - Sperling, Reisa A; Aisen, Paul S; Beckett, Laurel A; Bennett, David A; Craft, Suzanne; Fagan, Anne M; Iwatsubo, Takeshi; Jack, Clifford R; Kaye, Jeffrey; Montine, Thomas J; Park, Denise C; Reiman, Eric M; et al. (Alzheimers Dement, 2011)
The pathophysiological process of Alzheimer's disease (AD) is thought to begin many years before the diagnosis of AD dementia. This long "preclinical" phase of AD would provide a critical opportunity for therapeutic intervention; however, we need to further elucidate the link between the pathological cascade of AD and the emergence of clinical symptoms. The National Institute on Aging and the Alzheimer's Association convened an international workgroup to review the biomarker, epidemiological, and neuropsychological evidence, and to develop recommendations to determine the factors which best predict the risk of progression from "normal" cognition to mild cognitive impairment and AD dementia. We propose a conceptual framework and operational research criteria, based on the prevailing scientific evidence to date, to test and refine these models with longitudinal clinical research studies. These recommendations are solely intended for research purposes and do not have any clinical implications at this time. It is hoped that these recommendations will provide a common rubric to advance the study of preclinical AD, and ultimately, aid the field in moving toward earlier intervention at a stage of AD when some disease-modifying therapies may be most efficacious.
Keywords: Alzheimer Disease; Biomarkers; Cognition Disorders; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; United States

Vascular risk factors promote conversion from mild cognitive impairment to Alzheimer disease. - Li, J; Wang, Y J; Zhang, M; Xu, Z Q; Gao, C Y; Fang, C Q; Yan, J C; Zhou, H D (Neurology, 2011)
OBJECTIVE: Growing evidence suggests that vascular risk factors (VRF) contribute to cognitive decline. The aim of this study was to investigate the impact of VRF on the conversion from mild cognitive impairment (MCI) to Alzheimer disease (AD) dementia. METHODS: A total of 837 subjects with MCI were enrolled at baseline and followed up annually for 5 years. The incidence of AD dementia was investigated. A mixed random effects regression model was used to analyze the association between VRF and the progression of MCI assessed with Mini-Mental State Examination and instrumental Activities of Daily Living. Cox proportional hazard models were used to identify the association between VRF and dementia conversion, and to examine whether treatment of VRF can prevent dementia conversion. RESULTS: At the end of the follow-up, 298 subjects converted to AD dementia, while 352 remained MCI. Subjects with VRF had a faster progression in cognition and function relative to subjects without. VRF including hypertension, diabetes, cerebrovascular diseases, and hypercholesterolemia increased the risk of dementia conversion. Those subjects with MCI in whom all VRF were treated had a lower risk of dementia than those who had some VRF treated. Treatment of individual VRF including hypertension, diabetes, and hypercholesterolemia was associated with the reduced risk of AD conversion. CONCLUSION: VRF increased the risk of incident AD dementia. Treatment of VRF was associated with a reduced risk of incident AD dementia. Although our findings are observational, they suggest active intervention for VRF might reduce progression in MCI to AD dementia.
Keywords: Aged; Alzheimer Disease; Cerebrovascular Disorders; Cognition Disorders; Disease Progression; Female; Humans; Incidence; Longitudinal Studies; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptides; Regression Analysis; Residence Characteristics; Retrospective Studies; Risk Factors; Statistics, Nonparametric

Alzheimer's Disease Neuroimaging Initiative (ADNI): clinical characterization. - Petersen, R C; Aisen, P S; Beckett, L A; Donohue, M C; Gamst, A C; Harvey, D J; Jack, C R; Jagust, W J; Shaw, L M; Toga, A W; Trojanowski, J Q; Weiner, M W (Neurology, 2010)
BACKGROUND: Neuroimaging measures and chemical biomarkers may be important indices of clinical progression in normal aging and mild cognitive impairment (MCI) and need to be evaluated longitudinally. OBJECTIVE: To characterize cross-sectionally and longitudinally clinical measures in normal controls, subjects with MCI, and subjects with mild Alzheimer disease (AD) to enable the assessment of the utility of neuroimaging and chemical biomarker measures. METHODS: A total of 819 subjects (229 cognitively normal, 398 with MCI, and 192 with AD) were enrolled at baseline and followed for 12 months using standard cognitive and functional measures typical of clinical trials. RESULTS: The subjects with MCI were more memory impaired than the cognitively normal subjects but not as impaired as the subjects with AD. Nonmemory cognitive measures were only minimally impaired in the subjects with MCI. The subjects with MCI progressed to dementia in 12 months at a rate of 16.5% per year. Approximately 50% of the subjects with MCI were on antidementia therapies. There was minimal movement on the Alzheimer's Disease Assessment Scale-Cognitive Subscale for the normal control subjects, slight movement for the subjects with MCI of 1.1, and a modest change for the subjects with AD of 4.3. Baseline CSF measures of Abeta-42 separated the 3 groups as expected and successfully predicted the 12-month change in cognitive measures. CONCLUSION: The Alzheimer's Disease Neuroimaging Initiative has successfully recruited cohorts of cognitively normal subjects, subjects with mild cognitive impairment (MCI), and subjects with Alzheimer disease with anticipated baseline characteristics. The 12-month progression rate of MCI was as predicted, and the CSF measures heralded progression of clinical measures over 12 months.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Cross-Sectional Studies; Diagnostic Imaging; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Middle Aged

Gamma-secretase activating protein is a therapeutic target for Alzheimer's disease. - He, Gen; Luo, Wenjie; Li, Peng; Remmers, Christine; Netzer, William J; Hendrick, Joseph; Bettayeb, Karima; Flajolet, Marc; Gorelick, Fred; Wennogle, Lawrence P; Greengard, Paul (Nature, 2010)
Accumulation of neurotoxic amyloid-beta is a major hallmark of Alzheimer's disease. Formation of amyloid-beta is catalysed by gamma-secretase, a protease with numerous substrates. Little is known about the molecular mechanisms that confer substrate specificity on this potentially promiscuous enzyme. Knowledge of the mechanisms underlying its selectivity is critical for the development of clinically effective gamma-secretase inhibitors that can reduce amyloid-beta formation without impairing cleavage of other gamma-secretase substrates, especially Notch, which is essential for normal biological functions. Here we report the discovery of a novel gamma-secretase activating protein (GSAP) that drastically and selectively increases amyloid-beta production through a mechanism involving its interactions with both gamma-secretase and its substrate, the amyloid precursor protein carboxy-terminal fragment (APP-CTF). GSAP does not interact with Notch, nor does it affect its cleavage. Recombinant GSAP stimulates amyloid-beta production in vitro. Reducing GSAP concentrations in cell lines decreases amyloid-beta concentrations. Knockdown of GSAP in a mouse model of Alzheimer's disease reduces levels of amyloid-beta and plaque development. GSAP represents a type of gamma-secretase regulator that directs enzyme specificity by interacting with a specific substrate. We demonstrate that imatinib, an anticancer drug previously found to inhibit amyloid-beta formation without affecting Notch cleavage, achieves its amyloid-beta-lowering effect by preventing GSAP interaction with the gamma-secretase substrate, APP-CTF. Thus, GSAP can serve as an amyloid-beta-lowering therapeutic target without affecting other key functions of gamma-secretase.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Benzamides; Cell Line; Disease Models, Animal; Gene Knockdown Techniques; Humans; Imatinib Mesylate; Mice; Peptide Fragments; Piperazines; Proteins; Pyrimidines; Receptor, Notch1; RNA Interference

Genetic evidence implicates the immune system and cholesterol metabolism in the aetiology of Alzheimer's disease. - Jones, Lesley; Holmans, Peter A; Hamshere, Marian L; Harold, Denise; Moskvina, Valentina; Ivanov, Dobril; Pocklington, Andrew; Abraham, Richard; Hollingworth, Paul; Sims, Rebecca; Gerrish, Amy; Pahwa, Jaspreet Singh; et al. (PLoS One, 2010)
BACKGROUND: Late Onset Alzheimer's disease (LOAD) is the leading cause of dementia. Recent large genome-wide association studies (GWAS) identified the first strongly supported LOAD susceptibility genes since the discovery of the involvement of APOE in the early 1990s. We have now exploited these GWAS datasets to uncover key LOAD pathophysiological processes. METHODOLOGY: We applied a recently developed tool for mining GWAS data for biologically meaningful information to a LOAD GWAS dataset. The principal findings were then tested in an independent GWAS dataset. PRINCIPAL FINDINGS: We found a significant overrepresentation of association signals in pathways related to cholesterol metabolism and the immune response in both of the two largest genome-wide association studies for LOAD. SIGNIFICANCE: Processes related to cholesterol metabolism and the innate immune response have previously been implicated by pathological and epidemiological studies of Alzheimer's disease, but it has been unclear whether those findings reflected primary aetiological events or consequences of the disease process. Our independent evidence from two large studies now demonstrates that these processes are aetiologically relevant, and suggests that they may be suitable targets for novel and existing therapeutic approaches.
Keywords: Alzheimer Disease; Apolipoproteins E; Cholesterol; Chromosome Mapping; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Immune System; Polymorphism, Single Nucleotide

National Institutes of Health State-of-the-Science Conference statement: preventing alzheimer disease and cognitive decline. - Daviglus, Martha L; Bell, Carl C; Berrettini, Wade; Bowen, Phyllis E; Connolly, E Sander; Cox, Nancy Jean; Dunbar-Jacob, Jacqueline M; Granieri, Evelyn C; Hunt, Gail; McGarry, Kathleen; Patel, Dinesh; Potosky, Arnold L; et al. (Ann Intern Med, 2010)
The National Institute on Aging and the Office of Medical Applications of Research of the National Institutes of Health convened a State-of-the-Science Conference on 26-28 April 2010 to assess the available scientific evidence on prevention of cognitive decline and Alzheimer disease. This article provides the panel's assessment of the available evidence.
Keywords: Aged; Alzheimer Disease; Cognition Disorders; Evidence-Based Medicine; Humans; Risk Factors; Risk Reduction Behavior

Neuroinflammation in Alzheimer's disease and mild cognitive impairment: a field in its infancy. - McGeer, Edith G; McGeer, Patrick L (J Alzheimers Dis, 2010)
Neuroinflammation is a prominent feature of Alzheimer disease (AD) and other chronic neurodegenerative disorders. It exacerbates the fundamental pathology by generating a plethora of inflammatory mediators and neurotoxic compounds. Inflammatory cytokines, complement components, and toxic free radicals are among the many species that are generated. Microglia attack the pathological entities and may inadvertently injure host neurons. Recent evidence indicates that microglia can be stimulated to assume an antiinflammatory state rather than a proinflammatory state which may have therapeutic potential. Proinflammatory cytokines include IL-1, IL-6 and TNF, while antiinflammatory cytokines include IL-4 and IL-10. Complement activation is a separate process which causes extensive neuronal damage in AD through assembly of the membrane attack complex. Aggregated amyloid-beta is a potent activator of human complement but not of mouse complement. This is an important difference between AD and transgenic mouse models of AD. Many so far unexplored molecules may contribute to neuroinflammation or act to inhibit it. Stable isotope labeling by amino acids in cell culture (SILAC) analysis identified 174 proteins that were upregulated by two-fold or more, and 189 that were downregulated by 2-fold or more following inflammatory stimulation of microglial-like THP-1 cells. Neurotoxicity may result from any combination of these and further exploration is clearly warranted. In addition, many small molecules may play a significant role. One example is hydrogen sulfide which appears to be an endogenous antiinflammatory agent.
Keywords: Alzheimer Disease; Animals; Cognition Disorders; Humans; Inflammation; Neurology